Correction to: Extratropical storms induce carbon outgassing over the Southern Ocean (npj Climate and Atmospheric Science, (2024), 7, 1, (106), 10.1038/s41612-024-00657-7) - Carranza, M.M.; Long, M.C.; Di Luca, A.; Fassbender, A.J.; Johnson, K.S.; Takeshita, Y.; Mongwe, P.; Turner, K.E. (npj Climate and Atmospheric Science, 2024)

Vulnerability of barley yields in Québec - Epule Epule, T.; Poirier, V.; Peng, C.; Etongo, D. (Environmental Monitoring and Assessment, 2024)

Contrasted changes of sea-surface salinity in the southern and northern Okinawa Trough since the mid-Holocene - Li, D.; Wu, Y.; Seidenkrantz, M.-S.; de Vernal, A.; Hu, B.; Song, B.; Jiang, H.; Sha, L. (Global and Planetary Change, 2024)

Nocturnal peak methane flux diel patterns in rice paddy fields - Li, H.; Peng, C.; Helbig, M.; Zhao, M.; Guo, H.; Zhao, B. (Agricultural and Forest Meteorology, 2024)

Reconstruct the intertropical convergence zone over the Indo-Pacific Warm Pool with extended records and empirical orthogonal function - Lu, F.; Pausata, F.S.R.; Mohtadi, M. (Proceedings of the National Academy of Sciences of the United States of America, 2024)

A Detailed Limited-Area Atmospheric Energy Cycle for Climate and Weather Studies - Ngueto, Y.F.; Laprise, R.; Nikiéma, O. (Atmosphere, 2024)

Dynamic patterns of particulate matter concentration and size distribution in urban street canyons: insights into diurnal and short-term seasonal variations - Wang, X.; Chen, X.; Zhou, Z.; Teng, M.; Xiang, Y.; Peng, C.; Huang, C.; Peng, C. (Environmental Monitoring and Assessment, 2024)

Rapid decrease of the Labrador Sea’s influence on black spruce ecosystems with distance inland - Larose, J.; Boucher, É.; de Vernal, A.; de Mendoza, I.H.; Gennaretti, F.; Lavergne, A.; Andreu-Hayles, L.; Field, R.D. (Communications Earth and Environment, 2024)

Climate variations in eastern Hudson bay over the past 3000 years - Vallerand, J.; de Vernal, A.; Roy, N. (Quaternary Science Reviews, 2024)

Observed Vertical Dispersion Patterns of Particulate Matter in Urban Street Canyons and Dominant Influencing Factors - Wang, X.; Chen, X.; Ma, B.; Zhou, Z.; Peng, C. (Forests, 2024)

Future soil organic carbon stocks in China under climate change - Wu, J.; Liu, S.; Peng, C.; Luo, Y.; Terrer, C.; Yue, C.; Peng, S.; Li, J.; Wang, B.; Shangguan, Z.; Deng, L. (Cell Reports Sustainability, 2024)

Global riverine land-to-ocean carbon export constrained by observations and multi-model assessment - Liu, M.; Raymond, P.A.; Lauerwald, R.; Zhang, Q.; Trapp-Müller, G.; Davis, K.L.; Moosdorf, N.; Xiao, C.; Middelburg, J.J.; Bouwman, A.F.; Beusen, A.H.W.; Peng, C.; et al. (Nature Geoscience, 2024)

Estimating wetland CH4 emissions on the Qinghai-Tibetan Plateau based on a processed model coupled with inundation dynamics between 1960 and 2100 - Zhang, J.; Chen, H.; Peng, C.; Huang, Y.; Wang, Y.; Liu, X.; Wang, M.; Wang, L.; Yu, D.; Zhu, Q. (Science of the Total Environment, 2024)

Critical needs to close monitoring gaps in pan-tropical wetland CH4 emissions - Zhu, Q.; Yuan, K.; Li, F.; Riley, W.J.; Hoyt, A.; Jackson, R.; McNicol, G.; Chen, M.; Knox, S.H.; Briner, O.; Beerling, D.; Gedney, N.; et al. (Environmental Research Letters, 2024)

Opposed east-west climate response of the Arctic Ocean during the present interglacial - de Vernal, A.; Hillaire-Marcel, C.; Song, T.; Radi, T.; Falardeau, J.; Liu, Y. (Science Advances, 2024)

Biochar amendment alleviates soil microbial nitrogen and phosphorus limitation and increases soil heterotrophic respiration under long-term nitrogen input in a subtropical forest - Li, Q.; Ji, H.; Zhang, C.; Cui, Y.; Peng, C.; Chang, S.X.; Cao, T.; Shi, M.; Li, Y.; Wang, X.; Zhang, J.; Song, X. (Science of the Total Environment, 2024)

Long-term nitrogen addition has a positive legacy effect on soil respiration in subtropical Moso bamboo forests - Li, Q.; Zhang, C.; Shi, M.; Lv, J.; Peng, C.; Zhang, J.; Chang, S.X.; Cao, T.; Li, T.; Song, X. (Geoderma, 2024)

Dynamics of the intertropical convergence zone during the early Heinrich Stadial 1 - Lu, F.; Mohtadi, M.; Pausata, F.S.R. (Nature Communications, 2024)

Dinoflagellate cysts as proxies of environmental, ocean and climate changes in the Atlantic realm during the quaternary - Marret, F.; de Vernal, A. (Frontiers in Ecology and Evolution, 2024)

Labrador coastal current and productivity variations offshore Nain (Nunatsiavut) during the late Holocene - Atkinson, M.; Normandeau, A.; Van Nieuwenhove, N.; de Vernal, A.; Saunders, M.; Woollett, J.; Limoges, A. (Quaternary Science Reviews, 2024)

Drought and warming interaction cause substantial economic losses in the carbon market potential of China's northern grasslands - Guo, J.; Li, T.; Wu, T.; Wang, Z.; Zou, Z.; Peng, C.; Zhou, X.; Li, P.; Liu, Z.; Tang, J.; Zhang, C. (Science of the Total Environment, 2024)

Shifts in Plant Phenology Significantly Affect the Carbon Allocation in Different Plant Organs - Ren, P.; Li, P.; Zhou, X.; Liu, Z.; Tang, J.; Zhang, C.; Zou, Z.; Li, T.; Peng, C. (Ecology Letters, 2024)

A resilient ice cover over the southernmost Mendeleev Ridge during the late Quaternary - Song, T.; Hillaire-Marcel, C.; de Vernal, A.; Liu, Y. (Boreas, 2024)

High rates of marine organic carbon burial on the southwest Greenland margin induced by Neoglacial advances - Wang, Y.; Gélinas, Y.; de Vernal, A.; Mucci, A.O.; Allan, E.; Seidenkrantz, M.-S.; Douglas, P.M.J. (Communications Earth and Environment, 2024)

Evolution of West-East Contrast in the Subarctic Pacific Gyre During the Plio-Pleistocene Based on Palynological Evidence at ODP Sites 882 and 887 - Zorzi, C.; de Vernal, A. (Paleoceanography and Paleoclimatology, 2024)

Characteristics of Meteorological Drought Evolution in the Yangtze River Basin - Bai, W.; Zhang, C.; Xiao, X.; Zou, Z.; Liu, Z.; Li, P.; Tang, J.; Li, T.; Zhou, X.; Peng, C. (Water (Switzerland), 2024)

Effect of secondary ice production processes on the simulation of ice pellets using the Predicted Particle Properties microphysics scheme - Lachapelle, M.; Cholette, M.; Thériault, J.M. (Atmospheric Chemistry and Physics, 2024)

Impacts of Urbanization on Economic Development and Ecological Protection of the Wuhan City Circle, China - Li, Y.; Huang, C.; Liu, S.; Cheng, J.; Xiang, Y.; Peng, C. (Land Degradation and Development, 2024)

Balancing Water Yield and Water Use Efficiency Between Planted and Natural Forests: A Global Analysis - Sun, S.; Xiang, W.; Ouyang, S.; Hu, Y.; Peng, C. (Global Change Biology, 2024)

The 2023 wildfire season in Quebec: An overview of extreme conditions, impacts, lessons learned and considerations for the future - Boulanger, Y.; Arseneault, D.; Bélisle, A.C.; Bergeron, Y.; Boucher, J.; Boucher, Y.; Danneyrolles, V.; Erni, S.; Gachon, P.; Girardin, M.P.; Grant, E.; Grondin, P.; et al. (Canadian Journal of Forest Research, 2024)

Implementation of a large‐scale variable velocity river flow routing algorithm in the Canadian Regional Climate Model (CRCM) - Lucas‐Picher, Philippe; Arora, Vivek K.; Caya, Daniel; Laprise, René (Atmosphere-Ocean, 2003)

On the need for bias correction of regional climate change projections of temperature and precipitation - Christensen, Jens H.; Boberg, Fredrik; Christensen, Ole B.; Lucas‐Picher, Philippe (Geophysical Research Letters, 2008)
Within the framework of the European project ENSEMBLES (ensembles‐based predictions of climate changes and their impacts) we explore the systematic bias in simulated monthly mean temperature and precipitation for an ensemble of thirteen regional climate models (RCMs). The models have been forced with the European Centre for Medium Range Weather Forecasting Reanalysis (ERA40) and are compared to a new high resolution gridded observational data set. We find that each model has a distinct systematic bias relating both temperature and precipitation bias to the observed mean. By excluding the twenty‐five percent warmest and wettest months, respectively, we find that a derived second‐order fit from the remaining months can be used to estimate the values of the excluded months. We demonstrate that the common assumption of bias cancellation (invariance) in climate change projections can have significant limitations when temperatures in the warmest months exceed 4–6 °C above present day conditions.

Investigation of regional climate models’ internal variability with a ten-member ensemble of 10-year simulations over a large domain - Lucas-Picher, Philippe; Caya, Daniel; De Elía, Ramón; Laprise, René (Climate Dynamics, 2008)

Quantification of the Lateral Boundary Forcing of a Regional Climate Model Using an Aging Tracer - Lucas-Picher, Philippe; Caya, Daniel; Biner, Sébastien; Laprise, René (Monthly Weather Review, 2008)
Abstract The present work introduces a new and useful tool to quantify the lateral boundary forcing of a regional climate model (RCM). This tool, an aging tracer, computes the time the air parcels spend inside the limited-area domain of an RCM. The aging tracers are initialized to zero when the air parcels enter the domain and grow older during their migrations through the domain with each time step in the integration of the model. This technique was employed in a 10-member ensemble of 10-yr (1980–89) simulations with the Canadian RCM on a large domain covering North America. The residency time is treated and archived as the other simulated meteorological variables, therefore allowing computation of its climate diagnostics. These diagnostics show that the domain-averaged residency time is shorter in winter than in summer as a result of the faster winter atmospheric circulation. The residency time decreases with increasing height above the surface because of the faster atmospheric circulation at high levels dominated by the jet stream. Within the domain, the residency time increases from west to east according to the transportation of the aging tracer with the westerly general atmospheric circulation. A linear relation is found between the spatial distribution of the internal variability—computed with the variance between the ensemble members—and residency time. This relation indicates that the residency time can be used as a quantitative indicator to estimate the level of control exerted by the lateral boundary conditions on the RCM simulations.

Challenging some tenets of Regional Climate Modelling - Laprise, R.; De Elía, R.; Caya, D.; Biner, S.; Lucas-Picher, P.; Diaconescu, E.; Leduc, M.; Alexandru, A.; Separovic, L.; Canadian Network for Regional Climate Modelling and Diagnostics (Meteorology and Atmospheric Physics, 2008)

Mass balance of the Greenland ice sheet (2003–2008) from ICESat data – the impact of interpolation, sampling and firn density - Sørensen, L. S.; Simonsen, S. B.; Nielsen, K.; Lucas-Picher, P.; Spada, G.; Adalgeirsdottir, G.; Forsberg, R.; Hvidberg, C. S. (The Cryosphere, 2011)
Abstract. ICESat has provided surface elevation measurements of the ice sheets since the launch in January 2003, resulting in a unique dataset for monitoring the changes of the cryosphere. Here, we present a novel method for determining the mass balance of the Greenland ice sheet, derived from ICESat altimetry data. Three different methods for deriving elevation changes from the ICESat altimetry dataset are used. This multi-method approach provides a method to assess the complexity of deriving elevation changes from this dataset. The altimetry alone can not provide an estimate of the mass balance of the Greenland ice sheet. Firn dynamics and surface densities are important factors that contribute to the mass change derived from remote-sensing altimetry. The volume change derived from ICESat data is corrected for changes in firn compaction over the observation period, vertical bedrock movement and an intercampaign elevation bias in the ICESat data. Subsequently, the corrected volume change is converted into mass change by the application of a simple surface density model, in which some of the ice dynamics are accounted for. The firn compaction and density models are driven by the HIRHAM5 regional climate model, forced by the ERA-Interim re-analysis product, at the lateral boundaries. We find annual mass loss estimates of the Greenland ice sheet in the range of 191 ± 23 Gt yr−1 to 240 ± 28 Gt yr−1 for the period October 2003 to March 2008. These results are in good agreement with several other studies of the Greenland ice sheet mass balance, based on different remote-sensing techniques.

Can Regional Climate Models Represent the Indian Monsoon? - Lucas-Picher, Philippe; Christensen, Jens H.; Saeed, Fahad; Kumar, Pankaj; Asharaf, Shakeel; Ahrens, Bodo; Wiltshire, Andrew J.; Jacob, Daniela; Hagemann, Stefan (Journal of Hydrometeorology, 2011)
Abstract The ability of four regional climate models (RCMs) to represent the Indian monsoon was verified in a consistent framework for the period 1981–2000 using the 45-yr European Centre for Medium-Range Weather Forecasts (ECMWF) Re-Analysis (ERA-40) as lateral boundary forcing data. During the monsoon period, the RCMs are able to capture the spatial distribution of precipitation with a maximum over the central and west coast of India, but with important biases at the regional scale on the east coast of India in Bangladesh and Myanmar. Most models are too warm in the north of India compared to the observations. This has an impact on the simulated mean sea level pressure from the RCMs, being in general too low compared to ERA-40. Those biases perturb the land–sea temperature and pressure contrasts that drive the monsoon dynamics and, as a consequence, lead to an overestimation of wind speed, especially over the sea. The timing of the monsoon onset of the RCMs is in good agreement with the one obtained from observationally based gridded datasets, while the monsoon withdrawal is less well simulated. A Hovmöller diagram representation of the mean annual cycle of precipitation reveals that the meridional motion of the precipitation simulated by the RCMs is comparable to the one observed, but the precipitation amounts and the regional distribution differ substantially between the four RCMs. In summary, the spread at the regional scale between the RCMs indicates that important feedbacks and processes are poorly, or not, taken into account in the state-of-the-art regional climate models.

Greenland ice sheet surface mass balance: evaluating simulations and making projections with regional climate models - Rae, J. G. L.; Aðalgeirsdóttir, G.; Edwards, T. L.; Fettweis, X.; Gregory, J. M.; Hewitt, H. T.; Lowe, J. A.; Lucas-Picher, P.; Mottram, R. H.; Payne, A. J.; Ridley, J. K.; Shannon, S. R.; et al. (The Cryosphere, 2012)
Abstract. Four high-resolution regional climate models (RCMs) have been set up for the area of Greenland, with the aim of providing future projections of Greenland ice sheet surface mass balance (SMB), and its contribution to sea level rise, with greater accuracy than is possible from coarser-resolution general circulation models (GCMs). This is the first time an intercomparison has been carried out of RCM results for Greenland climate and SMB. Output from RCM simulations for the recent past with the four RCMs is evaluated against available observations. The evaluation highlights the importance of using a detailed snow physics scheme, especially regarding the representations of albedo and meltwater refreezing. Simulations with three of the RCMs for the 21st century using SRES scenario A1B from two GCMs produce trends of between −5.5 and −1.1 Gt yr−2 in SMB (equivalent to +0.015 and +0.003 mm sea level equivalent yr−2), with trends of smaller magnitude for scenario E1, in which emissions are mitigated. Results from one of the RCMs whose present-day simulation is most realistic indicate that an annual mean near-surface air temperature increase over Greenland of ~ 2°C would be required for the mass loss to increase such that it exceeds accumulation, thereby causing the SMB to become negative, which has been suggested as a threshold beyond which the ice sheet would eventually be eliminated.

Very high resolution regional climate model simulations over Greenland: Identifying added value - Lucas‐Picher, Philippe; Wulff‐Nielsen, Maria; Christensen, Jens H.; Aðalgeirsdóttir, Guðfinna; Mottram, Ruth; Simonsen, Sebastian B. (Journal of Geophysical Research: Atmospheres, 2012)
This study presents two simulations of the climate over Greenland with the regional climate model (RCM) HIRHAM5 at 0.05° and 0.25° resolution driven at the lateral boundaries by the ERA‐Interim reanalysis for the period 1989–2009. These simulations are validated against observations from meteorological stations (Danish Meteorological Institute) at the coast and automatic weather stations on the ice sheet (Greenland Climate Network). Generally, the temperature and precipitation biases are small, indicating a realistic simulation of the climate over Greenland that is suitable to drive ice sheet models. However, the bias between the simulations and the few available observations does not reduce with higher resolution. This is partly explained by the lack of observations in regions where the higher resolution is expected to improve the simulated climate. The RCM simulations show that the temperature has increased the most in the northern part of Greenland and at lower elevations over the period 1989–2009. Higher resolution increases the relief variability in the model topography and causes the simulated precipitation to be larger on the coast and smaller over the main ice sheet compared to the lower‐resolution simulation. The higher‐resolution simulation likely represents the Greenlandic climate better, but the lack of observations makes it difficult to validate fully. The detailed temperature and precipitation fields that are generated with the higher resolution are recommended for producing adequate forcing fields for ice sheet models, particularly for their improved simulation of the processes occurring at the steep margins of the ice sheet. , Key Points Validation of regional climate model simulations over Greenland Description of the climate over Greenland Assessment of added value

Assessing a multilayered dynamic firn-compaction model for Greenland with ASIRAS radar measurements - Simonsen, Sebastian B.; Stenseng, Lars; Ađalgeirsdóttir, Guðfinna; Fausto, Robert S.; Hvidberg, Christine S.; Lucas-Picher, Philippe (Journal of Glaciology, 2013)
Abstract A method to assess firn compaction using data collected with the Airborne SAR (Synthetic Aperture Radar)/Interferometric Radar Altimeter System (ASIRAS) is developed. For this, we develop a dynamical firn-compaction model that includes meltwater retention. Based on the ASIRAS data, which show internal layers as annual horizons in the uppermost firn, the method relies on inferring the age/ depth (internal layers) information from the radar data using a Monte Carlo inversion technique to tune in parallel both the firn model and the atmospheric forcing parameters (temperature and accumulation). The model is validated against two firn cores, and it is shown that applying both firn densities and age/ depth information for the inversion gives the most accurate understanding of model biases. The method is then applied to a 67 km section of the EGIG line forced by atmospheric output from a regional climate model using only age/depth information in the inversion step. The layers traced by the ASIRAS data are modeled with a root-mean-square error of 9 cm, which is within the estimated error of the layer tracing. This gives us confidence in applying observed annual layering from firn radar data to assess firn compaction; however, the study also indicates that our firn-model-tuning parameters are site-dependent and cannot be parameterized by temperature and accumulation alone.

Dynamical Downscaling with Reinitializations: A Method to Generate Finescale Climate Datasets Suitable for Impact Studies - Lucas-Picher, Philippe; Boberg, Fredrik; Christensen, Jens H.; Berg, Peter (Journal of Hydrometeorology, 2013)
Abstract To retain the sequence of events of a regional climate model (RCM) simulation driven by a reanalysis, a method that has not been widely adopted uses an RCM with frequent reinitializations toward its driving field. In this regard, this study highlights the benefits of an RCM simulation with frequent (daily) reinitializations compared to a standard continuous RCM simulation. Both simulations are carried out with the RCM HIRHAM5, driven with the European Centre for Medium-Range Weather Forecasts (ECMWF) Interim Re-Analysis (ERA-Interim) data, over the 12-km-resolution European Coordinated Regional Climate Downscaling Experiment (CORDEX) domain covering the period 1989–2009. The analysis of daily precipitation shows improvements in the sequence of events and the maintenance of the added value from the standard continuous RCM simulation. The validation of the two RCM simulations with observations reveals that the simulation with reinitializations indeed improves the temporal correlation. Furthermore, the RCM simulation with reinitializations has lower systematic errors compared to the continuous simulation, which has a tendency to be too wet. A comparison of the distribution of wet day precipitation intensities shows similar added value in the continuous and reinitialized simulations with higher variability and extremes compared to the driving field ERA-Interim. Overall, the results suggest that the finescale climate dataset of the RCM simulation with reinitializations better suits the needs of impact studies by providing a sequence of events matching closely the observations, while limiting systematic errors and generating reliable added value. Downsides of the method with reinitializations are increased computational costs and the introduction of temporal discontinuities that are similar to those of a reanalysis.

Downscaled climate change projections with uncertainty assessment over India using a high resolution multi-model approach - Kumar, Pankaj; Wiltshire, Andrew; Mathison, Camilla; Asharaf, Shakeel; Ahrens, Bodo; Lucas-Picher, Philippe; Christensen, Jens H.; Gobiet, Andreas; Saeed, Fahad; Hagemann, Stefan; Jacob, Daniela (Science of The Total Environment, 2013)

Evaluation of the regional climate model ALADIN to simulate the climate over North America in the CORDEX framework - Lucas-Picher, Philippe; Somot, Samuel; Déqué, Michel; Decharme, Bertrand; Alias, Antoinette (Climate Dynamics, 2013)

Effects of Irrigation in India on the Atmospheric Water Budget - Tuinenburg, O. A.; Hutjes, R. W. A.; Stacke, T.; Wiltshire, A.; Lucas-Picher, P. (Journal of Hydrometeorology, 2014)
Abstract The effect of large-scale irrigation in India on the moisture budget of the atmosphere was investigated using three regional climate models and one global climate model, all of which performed an irrigated run and a natural run without irrigation. Using a common irrigation map, year-round irrigation was represented by adding water to the soil moisture to keep it at 90% of the maximum soil moisture storage capacity, regardless of water availability. For two focus regions, the seasonal cycle of irrigation matched that of the reference dataset, but irrigation application varied between the models by up to 0.8 mm day−1. Because of the irrigation, evaporation increased in all models, but precipitation decreased because of a strong decrease in atmospheric moisture convergence. A moisture tracking scheme was used to track individual evaporated moisture parcels through the atmosphere to determine where these lead to precipitation. Up to 35% of the evaporation moisture from the Ganges basin is recycling within the river basin. However, because of a decreased moisture convergence into the river basin, the total amount of precipitation in the Ganges basin decreases. Although a significant fraction of the evaporation moisture recycles within the river basin, the changes in large-scale wind patterns due to irrigation shift the precipitation from the eastern parts of India and Nepal to the northern and western parts of India and Pakistan. In these areas where precipitation increases, the relative precipitation increase is larger than the relative decrease in the areas where precipitation decreases. It is concluded 1) that the direct effects of irrigation on precipitation are small and are not uniform across the models; 2) that a fraction of up to 35% of any marginal evaporation increase (for example, due to irrigation) will recycle within the river basin; and 3) that when irrigation is applied on a large scale, the dominant effect will be a change in large-scale atmospheric flow that decreases precipitation in eastern India and increases it in western and northern India.

Role of model initialization for projections of 21st-century Greenland ice sheet mass loss - Ađalgeirsdóttir, G.; Aschwanden, A.; Khroulev, C.; Boberg, F.; Mottram, R.; Lucas-Picher, P.; Christensen, J.H. (Journal of Glaciology, 2014)
Abstract Model simulations of the Greenland ice sheet contribution to 21st-century sea-level rise are performed with a state-of-the-art ice-sheet model (Parallel Ice Sheet Model (PISM)). The climate-forcing fields are obtained from the European Union’s Seventh Framework Programme project ice2sea, in which three regional climate models are used to dynamically downscale two scenarios (A1B and E1) from two general circulation models (ECHAM5 and HadCM3). To assess the sensitivity of the projections to the model initial state, four initialization methods are applied. In these experiments, the simulated contribution to sea-level rise by 2100 ranges from an equivalent of 0.2 to 6.8 cm. The largest uncertainties arise from different formulations of the regional climate models (0.8–3.9 cm) and applied scenarios (0.65–1.9 cm), but an important source of uncertainty is the initialization method (0.1–0.8 cm). These model simulations do not account for the recently observed acceleration of ice streams and consequent thinning rates, the changing ice discharge that may result from the spatial and temporal variability of ocean forcing, or the feedback occurring between ice-sheet elevation changes and climate forcing. Thus the results should be considered the lower limit of Greenland ice sheet contributions to sea-level rise, until such processes have been integrated into large-scale ice-sheet models.

Reconstruction of the Spring 2011 Richelieu River Flood by Two Regional Climate Models and a Hydrological Model - Lucas-Picher, Philippe; Riboust, Philippe; Somot, Samuel; Laprise, René (Journal of Hydrometeorology, 2015)
Abstract Climate simulations made with two regional climate models (RCMs), the French Aire Limitée Adaptation Dynamique Développement International (ALADIN) and the Canadian Regional Climate Model, version 5 (CRCM5), operating on 10-km meshes for the period 1989–2011, and the Hydro-Québec hydrological model (HSAMI), are used to reconstruct the spring 2011 Richelieu River flood in the southern region of the province of Québec, Canada. The analysis shows that the simulated fields of 2-m air temperature, precipitation, and snow water equivalent by the RCMs closely match the observations with similar multiyear means and a high correlation of the monthly anomalies. The climatic conditions responsible for the 2011 flood are generally well simulated by the RCMs. The use of multidecadal RCM simulations facilitates the identification of anomalies that contributed to the flood. The flood was linked to a combination of factors: the 2010/11 winter was cold and snowy, the snowmelt in spring was fast, and there was a record amount of precipitation in April and May. Driven by outputs from the RCMs, HSAMI was able to reproduce the mean hydrograph of the Richelieu River, but it underestimated the peak of the 2011 flood. HSAMI adequately computes the water transport from the mountains to the river mouth and the storage effect of Lake Champlain, which dampens the flood over a long period. Overall, the results suggest that RCM simulations can be useful for reconstructing high-resolution climate information and providing new variables that can help better understand the causes of extreme climatic events.

Assessing the limits of bias‐correcting climate model outputs for climate change impact studies - Chen, Jie; Brissette, François P.; Lucas‐Picher, Philippe (Journal of Geophysical Research: Atmospheres, 2015)
Abstract Bias correction of climate model outputs has emerged as a standard procedure in most recent climate change impact studies. A crucial assumption of all bias correction approaches is that climate model biases are constant over time. The validity of this assumption has important implications for impact studies and needs to be verified to properly address uncertainty in future climate projections. Using 10 climate model simulations, this study specifically tests the bias stationarity of climate model outputs over Canada and the contiguous United States (U.S.) by comparing model outputs with corresponding observations over two 20 year historical periods (1961–1980 and 1981–2000). The results show that precipitation biases are clearly nonstationary over much of Canada and the contiguous U.S. and where they vary over much shorter time scales than those normally considered in climate change impact studies. In particular, the difference in biases over two very close periods of the recent past are, in fact, comparable to the climate change signal between future (2061–2080) and historical (1961–1980) periods for precipitation over large parts of Canada and the contiguous U.S., indicating that the uncertainty of future impacts may have been underestimated in most impact studies. In comparison, temperature bias can be considered to be approximately stationary for most of Canada and the contiguous U.S. when compared with the magnitude of the climate change signal. Given the reality that precipitation is usually considered to be more important than temperature for many impact studies, it is advisable that natural climate variability and climate model sensitivity be better emphasized in future impact studies. , Key Points Climate model biases are nonstationary over much of North America The difference in biases is comparable to the climate change signal The uncertainty of impacts may have been underestimated in most impact studies

Transferability of optimally-selected climate models in the quantification of climate change impacts on hydrology - Chen, Jie; Brissette, François P.; Lucas-Picher, Philippe (Climate Dynamics, 2016)

Using Natural Variability as a Baseline to Evaluate the Performance of Bias Correction Methods in Hydrological Climate Change Impact Studies - Chen, Jie; St-Denis, Blaise Gauvin; Brissette, François P.; Lucas-Picher, Philippe (Journal of Hydrometeorology, 2016)
Abstract Postprocessing of climate model outputs is usually performed to remove biases prior to performing climate change impact studies. The evaluation of the performance of bias correction methods is routinely done by comparing postprocessed outputs to observed data. However, such an approach does not take into account the inherent uncertainty linked to natural climate variability and may end up recommending unnecessary complex postprocessing methods. This study evaluates the performance of bias correction methods using natural variability as a baseline. This baseline implies that any bias between model simulations and observations is only significant if it is larger than the natural climate variability. Four bias correction methods are evaluated with respect to reproducing a set of climatic and hydrological statistics. When using natural variability as a baseline, complex bias correction methods still outperform the simplest ones for precipitation and temperature time series, although the differences are much smaller than in all previous studies. However, after driving a hydrological model using the bias-corrected precipitation and temperature, all bias correction methods perform similarly with respect to reproducing 46 hydrological metrics over two watersheds in different climatic zones. The sophisticated distribution mapping correction methods show little advantage over the simplest scaling method. The main conclusion is that simple bias correction methods appear to be just as good as other more complex methods for hydrological climate change impact studies. While sophisticated methods may appear more theoretically sound, this additional complexity appears to be unjustified in hydrological impact studies when taking into account the uncertainty linked to natural climate variability.

Use of Four Reanalysis Datasets to Assess the Terrestrial Branch of the Water Cycle over Quebec, Canada - Sabarly, Florent; Essou, Gilles; Lucas-Picher, Philippe; Poulin, Annie; Brissette, François (Journal of Hydrometeorology, 2016)
Abstract Reanalyses have the potential to provide meteorological information in areas where few or no traditional observation records are available. The terrestrial branch of the water cycle of CFSR, MERRA, ERA-Interim, and NARR is examined over Quebec, Canada, for the 1979–2008 time period. Precipitation, evaporation, runoff, and water balance are studied using observed precipitation and streamflows, according to three spatial scales: 1) the entire province of Quebec, 2) five regions derived from a climate classification, and 3) 11 river basins. The results reveal that MERRA provides a relatively closed water balance, while a significant residual was found for the other three reanalyses. MERRA and ERA-Interim seem to provide the most reliable precipitation over the province. On the other hand, precipitation from CFSR and NARR do not appear to be particularly reliable, especially over southern Quebec, as they almost systematically showed the highest and the lowest values, respectively. Moreover, the partitioning of precipitation into evaporation and runoff from MERRA and NARR does not agree with what was expected, particularly over southern, central, and eastern Quebec. Despite the weaknesses identified, the ability of reanalyses to reproduce the terrestrial water cycle of the recent past (i.e., 1979–2008) remains globally satisfactory. Nonetheless, their potential to provide reliable information must be validated by comparing reanalyses directly with weather stations, especially in remote areas.

How does large-scale nudging in a regional climate model contribute to improving the simulation of weather regimes and seasonal extremes over North America? - Lucas-Picher, Philippe; Cattiaux, Julien; Bougie, Alexandre; Laprise, René (Climate Dynamics, 2016)

Can Precipitation and Temperature from Meteorological Reanalyses Be Used for Hydrological Modeling? - Essou, Gilles R. C.; Sabarly, Florent; Lucas-Picher, Philippe; Brissette, François; Poulin, Annie (Journal of Hydrometeorology, 2016)
Abstract This paper investigates the potential of reanalyses as proxies of observed surface precipitation and temperature to force hydrological models. Three global atmospheric reanalyses (ERA-Interim, CFSR, and MERRA), one regional reanalysis (NARR), and one global meteorological forcing dataset obtained by bias-correcting ERA-Interim [Water and Global Change (WATCH) Forcing Data ERA-Interim (WFDEI)] were compared to one gridded observation database over the contiguous United States. Results showed that all temperature datasets were similar to the gridded observation over most of the United States. On the other hand, precipitation from all three global reanalyses was biased, especially in summer and winter in the southeastern United States. The regional reanalysis precipitation was closer to observations since it indirectly assimilates surface precipitation. The WFDEI dataset was generally less biased than the reanalysis datasets. All datasets were then used to force a global conceptual hydrological model on 370 watersheds of the Model Parameter Estimation Experiment (MOPEX) database. River flows were computed for each watershed, and results showed that the flows simulated using NARR and gridded observations forcings were very similar to the observed flows. The simulated flows forced by the global reanalysis datasets were also similar to the observations, except in the humid continental and subtropical climatic regions, where precipitation seasonality biases degraded river flow simulations. The WFDEI dataset led to better river flows than reanalysis in the humid continental and subtropical climatic regions but was no better than reanalysis—and sometimes worse—in other climatic zones. Overall, the results indicate that global reanalyses have good potential to be used as proxies to observations to force hydrological models, especially in regions with few weather stations.

Evidence of added value in North American regional climate model hindcast simulations using ever-increasing horizontal resolutions - Lucas-Picher, Philippe; Laprise, René; Winger, Katja (Climate Dynamics, 2017)

The Use of Reanalyses and Gridded Observations as Weather Input Data for a Hydrological Model: Comparison of Performances of Simulated River Flows Based on the Density of Weather Stations - Essou, Gilles R. C.; Brissette, François; Lucas-Picher, Philippe (Journal of Hydrometeorology, 2017)
Abstract Precipitation forcing is critical for hydrological modeling as it has a strong impact on the accuracy of simulated river flows. In general, precipitation data used in hydrological modeling are provided by weather stations. However, in regions with sparse weather station coverage, the spatial interpolation of the individual weather stations provides a rough approximation of the real precipitation fields. In such regions, precipitation from interpolated weather stations is generally considered unreliable for hydrological modeling. Precipitation estimates from reanalyses could represent an interesting alternative in regions where the weather station density is low. This article compares the performances of river flows simulated by a watershed model using precipitation and temperature estimates from reanalyses and gridded observations. The comparison was carried out based on the density of surface weather stations for 316 Canadian watersheds located in three climatic regions. Three state-of-the-art atmospheric reanalyses—ERA-Interim, CFSR, and MERRA—and one gridded observations database over Canada—Natural Resources Canada (NRCan)—were used. Results showed that the Nash–Sutcliffe values of simulated river flows using precipitation and temperature data from CFSR and NRCan were generally equivalent regardless of the weather station density. ERA-Interim and MERRA performed significantly better than NRCan for watersheds with weather station densities of less than 1 station per 1000 km2 in the mountainous region. Overall, these results indicate that for hydrological modeling in regions with high spatial variability of precipitation such as mountainous regions, reanalyses perform better than gridded observations when the weather station density is low.

Impacts of weighting climate models for hydro-meteorological climate change studies - Chen, Jie; Brissette, François P.; Lucas-Picher, Philippe; Caya, Daniel (Journal of Hydrology, 2017)

Impacts of combining reanalyses and weather station data on the accuracy of discharge modelling - Essou, Gilles R.C.; Brissette, François; Lucas-Picher, Philippe (Journal of Hydrology, 2017)

Convection ‐permitting modeling with regional climate models: Latest developments and next steps - Lucas‐Picher, Philippe; Argüeso, Daniel; Brisson, Erwan; Tramblay, Yves; Berg, Peter; Lemonsu, Aude; Kotlarski, Sven; Caillaud, Cécile (WIREs Climate Change, 2021)
Abstract Approximately 10 years ago, convection‐permitting regional climate models (CPRCMs) emerged as a promising computationally affordable tool to produce fine resolution (1–4 km) decadal‐long climate simulations with explicitly resolved deep convection. This explicit representation is expected to reduce climate projection uncertainty related to deep convection parameterizations found in most climate models. A recent surge in CPRCM decadal simulations over larger domains, sometimes covering continents, has led to important insights into CPRCM advantages and limitations. Furthermore, new observational gridded datasets with fine spatial and temporal (~1 km; ~1 h) resolutions have leveraged additional knowledge through evaluations of the added value of CPRCMs. With an improved coordination in the frame of ongoing international initiatives, the production of ensembles of CPRCM simulations is expected to provide more robust climate projections and a better identification of their associated uncertainties. This review paper presents an overview of the methodology to produce CPRCM simulations and the latest research on the related added value in current and future climates. Impact studies that are already taking advantage of these new CPRCM simulations are highlighted. This review paper ends by proposing next steps that could be accomplished to continue exploiting the full potential of CPRCMs. This article is categorized under: Climate Models and Modeling > Earth System Models

Contrasting lightning projection using the lightning potential index adapted in a convection-permitting regional climate model - Brisson, Erwan; Blahak, Ulrich; Lucas-Picher, Philippe; Purr, Christopher; Ahrens, Bodo (Climate Dynamics, 2021)
Abstract Lightning climate change projections show large uncertainties caused by limited empirical knowledge and strong assumptions inherent to coarse-grid climate modeling. This study addresses the latter issue by implementing and applying the lightning potential index parameterization (LPI) into a fine-grid convection-permitting regional climate model (CPM). This setup takes advantage of the explicit representation of deep convection in CPMs and allows for process-oriented LPI inputs such as vertical velocity within convective cells and coexistence of microphysical hydrometeor types, which are known to contribute to charge separation mechanisms. The LPI output is compared to output from a simpler flash rate parameterization, namely the CAPE $$×$$ × PREC parameterization, applied in a non-CPM on a coarser grid. The LPI’s implementation into the regional climate model COSMO-CLM successfully reproduces the observed lightning climatology, including its latitudinal gradient, its daily and hourly probability distributions, and its diurnal and annual cycles. Besides, the simulated temperature dependence of lightning reflects the observed dependency. The LPI outperforms the CAPE $$×$$ × PREC parameterization in all applied diagnostics. Based on this satisfactory evaluation, we used the LPI to a climate change projection under the RCP8.5 scenario. For the domain under investigation centered over Germany, the LPI projects a decrease of $$4.8%$$ 4.8 % in flash rate by the end of the century, in opposition to a projected increase of $$17.4%$$ 17.4 % as projected using the CAPE $$×$$ × PREC parameterization. The future decrease of LPI occurs mostly during the summer afternoons and is related to (i) a change in convection occurrence and (ii) changes in the microphysical mixing. The two parameterizations differ because of different convection occurrences in the CPM and non-CPM and because of changes in the microphysical mixing, which is only represented in the LPI lightning parameterization.

Notice of Retraction: Short-Term Response of Koelreuteria paniculata Seedlings to Simulated Soils Polluted by Manganese Mining Wasteland in Central South China - Zhao, Kun; Huang, Zhihong; Ma, Yu'e; Xiang, Wenhua; Peng, Changhui; Deng, Xiangwen (2011 5th International Conference on Bioinformatics and Biomedical Engineering, 2011)

The Vegetation Carbon Storage Variation in Europe Since 6000 BP: Reconstruction from Pollen - Peng, C. H.; Guiot, J.; Van Campo, E.; Cheddadi, R. (Journal of Biogeography, 1994)

Reconstruction of past terrestrial carbon storage in the Northern Hemisphere from the Osnabrück Biosphere Model and palaeodata - Peng, Ch; Guiot, J; Van Campo, E (Climate Research, 1995)

Temporal and spatial variations of terrestrial biomes and carbon storage since 13 000 yr BP in Europe: Reconstruction from pollen data and statistical models - Peng, C. H.; Guiot, J.; Van Campo, E.; Cheddadi, R. (Water, Air, and Soil Pollution, 1995)

The Variation of Terrestrial Carbon Storage at 6000 yr BP in Europe: Reconstruction from Pollen Data Using Two Empirical Biosphere Models - Peng, C. H.; Guiot, J.; Van Campo, E.; Cheddadi, R. (Journal of Biogeography, 1995)

Contribution of China to the global carbon cycle since the last glacial maximum - Peng, Changhui; Apps, Michael J. (Tellus B: Chemical and Physical Meteorology, 1997)

Simulating carbon dynamics along the Boreal Forest Transect Case Study (BFTCS) in central Canada: 1. Model testing - Peng, Changhui; Apps, Michael J.; Price, David T.; Nalder, Ian A.; Halliwell, David H. (Global Biogeochemical Cycles, 1998)
CENTURY 4.0, a simulation model of carbon and nitrogen dynamics of terrestrial ecosystems based on the relationships between climate, soil texture, plant productivity, decomposition and human management, was tested against observed data along the boreal forest transect case study (BFTCS) in central Canada. The results show that the simulated average aboveground biomass and net N mineralization were consistent with observed data. The modeled estimates for soil carbon were consistent with those from regional‐scale empirical regression models. High correlation ( R 2 = 0.92) with data was obtained for the simulation of soil carbon dynamics of the boreal forest, but the model overestimated soil carbon (O–20 cm) by 2–8% for fine‐textured soil and underestimated soil carbon by 5–18% for sandy soil. The effects of climatic variation on temporal changes in biomass and soil carbon storage over the past century were found to be very different for southern and northern sites but relatively insensitive to site‐specific soil texture. The main discrepancies between observed data and CENTURY 4.0 results are associated with the effects of soil texture and an inadequate representation of fire disturbance on C dynamics of boreal forests. Further improvements, particularly in the representation of disturbance regimes and in the simulation of slow pool C dynamics, are suggested to enhance its predictive capability.

simulating carbon dynamics along the Boreal Forest Transect Case Study (BFTCS) in central Canada: 2. Sensitivity to climate change - Peng, Changhui; Apps, Michael J. (Global Biogeochemical Cycles, 1998)
The effects of climate change and doubling atmospheric CO 2 on carbon dynamics of the boreal forest in the area of the Boreal Forest Transect Case Study in central Canada were investigated using the process‐based plant‐soil model CENTURY 4.0. The results presented here suggest that (1) across the transect climate change would result in increased total carbon in vegetation biomass but decreased overall carbon in soil; (2) increased atmospheric CO 2 concentration under current climatic patterns would result in increased total carbon in vegetation and in soil organic matter; and (3) combined climate change and elevated CO 2 would increase both net primary productivity and decomposition rates relative to the current climate condition, but their combined action would be a reduction of soil carbon losses relative to those due to climate change alone. The interactive effects of climate change and elevated CO 2 , however, are not a simple additive combination of the individual responses. The responses to climate change and elevated CO 2 vary across the climate gradient from southern to northern sites on the transect. The present simulations indicate that the northern sites are more sensitive to climate change than the southern sites are, but these simulations do not consider likely changes in the disturbance regime or changes in forest species distribution.

Estimating changes in terrestrial vegetation and carbon storage - Peng, C.H; Guiot, J; Van Campo, E (Quaternary Science Reviews, 1998)

Adapting a patch model to simulate the sensitivity of Central‐Canadian boreal ecosystems to climate variability - Price, D. T.; Halliwell, D. H.; Apps, M. J.; Peng, C. H. (Journal of Biogeography, 1999)
Summary Aim To investigate effects of within‐season and interannual climate variability on the behaviour of boreal forest ecosystems as simulated by the FORSKA2 patch model. Location Eleven climate station locations distributed along a transect across the boreal zone of central Canada. Methods FORSKA2′s water balance submodel was modified to enable it to behave more realistically under a varying climate. Long‐term actual monthly time‐series of temperature and precipitation data were detrended and used to drive the modified model. Long‐term monthly averages of the same detrended data were used to drive the unmodified model. Results Modifications created significant improvements when simulating species composition at sites in boreal Canada. Simulated forest biomass values were slightly higher than those obtained from the unmodified model using averaged climate records, but resembled the observed distribution of vegetation more closely. Main conclusions Modified FORSKA2 suggests that boreal forest composition and distribution may be more sensitive to changes in monthly rainfall data than to changes in temperature. Climate variability affects seasonal water balances and should be considered when using patch models to forecast vegetation dynamics during and following a period of climate transition. The modified model provided improved representation of the latitudinal trend in spatially averaged biomass density in this region.

Simulating effects of climate change on boreal ecosystem carbon pools in central Canada - Price, D. T.; Peng, C. H.; Apps, M. J.; Halliwell, D. H. (Journal of Biogeography, 1999)
Summary Aim Possible effects of current and future climates on boreal vegetation dynamics and carbon (C) cycling were investigated using the CENTURY 4.0 soil process model and a modified version of the FORSKA2 forest patch model. Location Eleven climate station locations distributed along a transect across the boreal zone of central Canada. Methods Both models were driven by detrended long‐term monthly climate data. Using a climate change signal derived from the GISS general circulation model (GCM) 2×CO 2 equilibrium climate scenario, the output from the two models was then used to compare simulated current and possible future total ecosystem C storage at the climate station locations. Results After allowing for their different underlying structures, comparison of output from both models showed good agreement with local field data under current climate conditions. CENTURY 4.0 was able to reproduce spatial variation in soil and litter C densities satisfactorily but tended to overestimate biomass productivity. FORSKA2 reproduced aboveground biomass productivity and spatially averaged biomass densities relatively well. Under the GISS 2×CO 2 scenario, both models generally predicted small increases in aboveground biomass C density for forest and tundra locations, but CENTURY 4.0 predicted greater decreases in soil and litter pools, for overall decreases in ecosystem C storage in the range 16–19%. Main conclusions With some caveats, results imply that effects of increased precipitation (as simulated by the GISS GCM) would more than compensate for any negative effects of increased temperature on forest growth. Increased temperature would also increase decomposition rates of soil and litter organic matter, however, for a net overall decrease in total ecosystem C storage.

Modelling the response of net primary productivity (NPP) of boreal forest ecosystems to changes in climate and fire disturbance regimes - Peng, Changhui; Apps, Michael J (Ecological Modelling, 1999)

Modelling the net primary productivity of temperate forest ecosystems in China with a GAP model - Jiang, Hong; Peng, Changhui; Apps, Michael J; Zhang, Yanli; Woodard, Paul M; Wang, Zhiming (Ecological Modelling, 1999)

Modelling the spatial pattern of net primary productivity in Chinese forests - Jiang, Hong; Apps, Michael J; Zhang, Yanli; Peng, Changhui; Woodard, Paul M (Ecological Modelling, 1999)

Understanding the role of forest simulation models in sustainable forest management - Peng, Changhui (Environmental Impact Assessment Review, 2000)

Growth and yield models for uneven-aged stands: past, present and future - Peng, Changhui (Forest Ecology and Management, 2000)

From static biogeographical model to dynamic global vegetation model: a global perspective on modelling vegetation dynamics - Peng, Changhui (Ecological Modelling, 2000)

Developing carbon-based ecological indicators to monitor sustainability of Ontario’s forests - Peng, Changhui; Liu, Jinxun; Dang, Qinglai; Zhou, Xiaolu; Apps, Mike (Ecological Indicators, 2002)

Developing and Validating Nonlinear Height–Diameter Models for Major Tree Species of Ontario's Boreal Forests - Peng, Changhui; Zhang, Lianjun; Liu, Jinxun (Northern Journal of Applied Forestry, 2001)
Abstract Six commonly used nonlinear growth functions were fitted to individual tree height-diameter data of nine major tree species in Ontario's boreal forests. A total of 22,571 trees was collected from new permanent sample plots across the northeast and northwest of Ontario.The available data for each species were split into two sets: the majority (90%) was used to estimate model parameters, and the remaining data (10%) were reserved to validate the models. The performance of the models was compared and evaluated by model, R2, mean difference, and mean absolute difference. The results showed that these six sigmoidal models were able to capture the height–diameter relationships and fit the data equally well, but produced different asymptote estimates. Sigmoidal models such as Chapman–Richards, Weibull, and Schnute functions provided the most satisfactory height predictions. The effect of model performance on tree volume estimation was also investigated. Tree volumes of different species were computed by Honer's volume equations using a range of diameters and the predicted tree total height from the six models. For trees with diameter less than 55 cm, the six height-diameter models produced very similar results for all species, while more differentiation among the models was observed for large-sized trees (e.g., diameters > 80 cm). North. J. Appl. For. 18:87–94.

Interannual Variability in Net Primary Production and Precipitation - Fang, Jingyun; Piao, Shilong; Tang, Zhiyao; Peng, Changhui; Ji, Wei (Science, 2001)

Changes in Forest Biomass Carbon Storage in China Between 1949 and 1998 - Fang, Jingyun; Chen, Anping; Peng, Changhui; Zhao, Shuqing; Ci, Longjun (Science, 2001)
The location and mechanisms responsible for the carbon sink in northern mid-latitude lands are uncertain. Here, we used an improved estimation method of forest biomass and a 50-year national forest resource inventory in China to estimate changes in the storage of living biomass between 1949 and 1998. Our results suggest that Chinese forests released about 0.68 petagram of carbon between 1949 and 1980, for an annual emission rate of 0.022 petagram of carbon. Carbon storage increased significantly after the late 1970s from 4.38 to 4.75 petagram of carbon by 1998, for a mean accumulation rate of 0.021 petagram of carbon per year, mainly due to forest expansion and regrowth. Since the mid-1970s, planted forests (afforestation and reforestation) have sequestered 0.45 petagram of carbon, and their average carbon density increased from 15.3 to 31.1 megagrams per hectare, while natural forests have lost an additional 0.14 petagram of carbon, suggesting that carbon sequestration through forest management practices addressed in the Kyoto Protocol could help offset industrial carbon dioxide emissions.

Effects of harvesting regimes on carbon and nitrogen dynamics of boreal forests in central Canada: a process model simulation - Peng, Changhui; Jiang, Hong; Apps, Michael J.; Zhang, Yanli (Ecological Modelling, 2002)

TRIPLEX: a generic hybrid model for predicting forest growth and carbon and nitrogen dynamics - Peng, Changhui; Liu, Jinxun; Dang, Qinglai; Apps, Michael J; Jiang, Hong (Ecological Modelling, 2002)

A component object model strategy for reusing ecosystem models - Liu, Jinxun; Peng, Changhui; Dang, Qinglai; Apps, Mike; Jiang, Hong (Computers and Electronics in Agriculture, 2002)

Development and evaluation of ecoregion-based jack pine height-diameter models for Ontario - Zhang, Lianjun; Peng, Changhui; Huang, Shongming; Zhou, Xiaolu (The Forestry Chronicle, 2002)
The Chapman-Richards growth function is used to model jack pine (Pinus banksiana Lamb.) tree height-diameter relationships at provincial, regional, and ecoregional levels. The results suggest that the tree height-diameter relationships of jack pine are significantly different among the geographic regions of Ontario, depending on local climatic, soil, and ecological conditions. In light of this study, the provincial and regional height-diameter models are not appropriate for predicting tree heights at the ecoregional level. Further, applying a specific ecoregional model to other ecoregions will also result in significant biases for predicting local tree heights. The ecoregion-based height-diameter models developed in this study may provide more accurate information on tree growth and development to forest resource managers and planners. Key words: Chapman-Richards growth function, permanent sample plot, non-linear extra sum of square method, forest management

Historic carbon budgets of Ontario’s forest ecosystems - Liu, Jinxun; Peng, Changhui; Apps, Mike; Dang, Qinglai; Banfield, Edwin; Kurz, Werner (Forest Ecology and Management, 2002)

Modelling the influence of harvesting on Chinese boreal forest carbon dynamics - Jiang, Hong; Apps, Michael J; Peng, Changhui; Zhang, Yanli; Liu, Jinxun (Forest Ecology and Management, 2002)

Distribution and storage of soil organic carbon in China - Wu, Haibin; Guo, Zhengtang; Peng, Changhui (Global Biogeochemical Cycles, 2003)
Surface soils hold the largest terrestrial organic carbon pool, although estimates of the world's soil organic carbon storage remain controversial, largely due to spatial data gaps or insufficient data density. In this study, spatial distribution and storage of soil organic carbon in China are estimated using the published data from 34,411 soil profiles investigated during China's second national soil survey. Results show that organic carbon density in soils varies from 0.73 to 70.79 kg C/m 2 with the majority ranging between 4.00 and 11.00 kg C/m 2 . Carbon density decreases from east to west. A general southward increase is obvious for western China, while carbon density decreases from north to south in eastern China. Highest values are observed in forest soils in northeast China and in subalpine soils in the southeastern part of the Tibetan Plateau. The average density of ∼8.01 kg C/m 2 in China is lower than the world's mean organic carbon density in soil (∼10.60 kg C/m 2 ), mainly due to the extended arid and semi‐arid regions. Total organic carbon storage in soils in China is estimated to be ∼70.31 Pg C, representing ∼4.7% of the world storage. Carbon storage in the surface organic horizons which is most sensitive to interactions with the atmosphere and environmental change is ∼32.54 Pg C.

Land use induced changes of organic carbon storage in soils of China - Wu, Haibin; Guo, Zhengtang; Peng, Changhui (Global Change Biology, 2003)
Abstract Using the data compiled from China's second national soil survey and an improved method of soil carbon bulk density, we have estimated the changes of soil organic carbon due to land use, and compared the spatial distribution and storage of soil organic carbon (SOC) in cultivated soils and noncultivated soils in China. The results reveal that ∼ 57% of the cultivated soil subgroups ( ∼ 31% of the total soil surface) have experienced a significant carbon loss, ranging from 40% to 10% relative to their noncultivated counterparts. The most significant carbon loss is observed for the non‐irrigated soils (dry farmland) within a semiarid/semihumid belt from northeastern to southwestern China, with the maximum loss occurring in northeast China. On the contrary, SOC has increased in the paddy and irrigated soils in northwest China. No significant change is observed for forest soils in southern China, grassland and desert soils in northwest China, as well as irrigated soils in eastern China. The SOC storage and density under noncultivated conditions in China are estimated to ∼ 77.4 Pg (10 15 g) and ∼ 8.8 kg C m −2 , respectively, compared to a SOC storage of ∼ 70.3 Pg and an average SOC density of ∼ 8.0 kg C m −2 under the present‐day conditions. This suggests a loss of ∼ 7.1 Pg SOC and a decrease of ∼ 0.8 kg C m −2 SOC density due to increasing human activities, in which the loss in organic horizons has contributed to ∼ 77%. This total loss of SOC in China induced by land use represents ∼ 9.5% of the world's SOC decrease. This amount is equivalent to ∼ 3.5 ppmv of the atmospheric CO 2 increase. Since ∼ 78% of the currently cultivated soils in China have been degraded to a low/medium productivities and are responsible for most of the SOC loss, an improved land management, such as the development of irrigated and paddy land uses, would have a considerable potential in restoring the SOC storage. Assuming a restoration of ∼ 50% of the lost SOC during the next 20–50 years, the soils in China would absorb ∼ 3.5 Pg of carbon from the atmosphere.

Increasing net primary production in China from 1982 to 1999 - Fang, Jingyun; Piao, Shilong; Field, Christopher B.; Pan, Yude; Guo, Qinghua; Zhou, Liming; Peng, Changhui; Tao, Shu (Frontiers in Ecology and the Environment, 2003)

Individual-tree basal area growth models for jack pine and black spruce in northern Ontario - Zhang, Lianjun; Peng, Changhui; Dang, Qinglai (The Forestry Chronicle, 2004)
Individual-tree models of five-year basal area growth were developed for jack pine (Pinus banksiana Lamb.) and black spruce (Picea mariana (Mill.) BSP) in northern Ontario. Tree growth data were collected from long-term permanent plots of pure and mixed stands of the two species. The models were fitted using mixed model methods due to correlated remeasurements of tree growth over time. Since the data covered a wide range of stand ages, stand conditions and tree sizes, serious heterogeneous variances existed in the data. Therefore, the coefficients of the final models were obtained using weighted regression techniques. The models for the two species were evaluated across 4-cm diameter classes using independent data. The results indicated (1) the models of jack pine and black spruce produced similar prediction errors and biases for intermediate-sized trees (1228 cm in tree diameter), (2) both models yielded relatively large errors and biases for larger trees (> 28 cm) than those for smaller trees, and (3) the jack pine model produced much larger errors and biases for small-sized trees (< 12 cm) than did the black spruce model. Key words: mixed models, repeated measures, model validation

Assessing the generality and accuracy of the TRIPLEX model using in situ data of boreal forests in central Canada - Zhou, X; Peng, C; Dang, Q (Environmental Modelling & Software, 2004)

Developing and Evaluating Tree Height-Diameter Models at Three Geographic Scales for Black Spruce in Ontario - Peng, Changhui; Zhang, Lianjun; Zhou, Xiaolu; Dang, Qinglai; Huang, Shongming (Northern Journal of Applied Forestry, 2004)
Abstract A total of 11,612 black spruce trees were measured from permanent sample plots across the boreal and central regions of Ontario and were used to fit the well-known Chapman-Richards growth model at provincial, regional, and ecoregional scales. The results suggest that the height-diameter relationships of black spruce vary with different geographic regions and scales. There were significant variations in height-diameter relationships for black spruce between boreal and central regions as well as among some of the seven ecoregions. The ecoregion-based height-diameter models presented here will provide more accurate predictions for tree height and, consequently, tree volume than these models developed at both provincial and regional scales. Furthermore, the heterogeneity of tree species should be considered in developing and applying ecoregion-based height-diameter models for predicting local tree height.

The 7-Decade Degradation of a Large Freshwater Lake in Central Yangtze River, China - Zhao, Shuqing; Fang, Jingyun; Miao, Shili; Gu, Ben; Tao, Shu; Peng, Changhui; Tang, Zhiyao (Environmental Science & Technology, 2005)

Predicting forest growth and yield in northeastern Ontario using the process-based model of TRIPLEX1.0 - Zhou, Xiaolu; Peng, Changhui; Dang, Qing-Lai; Chen, Jiaxin; Parton, Sue (Canadian Journal of Forest Research, 2005)
Process-based carbon dynamic models are rarely validated against traditional forest growth and yield data and are difficult to use as a practical tool for forest management. To bridge the gap between empirical and process-based models, a simulation using a hybrid model of TRIPLEX1.0 was performed for the forest growth and yield of the boreal forest ecosystem in the Lake Abitibi Model Forest in northeastern Ontario. The model was tested using field measurements, forest inventory data, and the normal yield table. The model simulations of tree height and diameter at breast height (DBH) showed a good agreement with measurements for black spruce (Picea mariana (Mill.) BSP), jack pine (Pinus banksiana Lamb.), and trembling aspen (Populus tremuloides Michx.). The coefficients of determination (R 2 ) between simulated values and permanent sample plot measurements were 0.92 for height and 0.95 for DBH. At the landscape scale, model predictions were compared with forest inventory data and the normal yield table. The R 2 ranged from 0.73 to 0.89 for tree height and from 0.72 to 0.85 for DBH. The simulated basal area is consistent with the normal yield table. The R 2 for basal area ranged from 0.82 to 0.96 for black spruce, jack pine, and trembling aspen for each site class. This study demonstrated the feasibility of testing the performance of the process-based carbon dynamic model using traditional forest growth and yield data and the ability of the TRIPLEX1.0 model for predicting growth and yield variables. The current work also introduces a means to test model accuracy and its prediction of forest stand variables to provide a complement to empirical growth and yield models for forest management practices, as well as for investigating climate change impacts on forest growth and yield in regions without sufficient established permanent sample plots and remote areas without suitable field measurements.

C-Lock (Patent Pending): A System for Estimating and Certifying Carbon Emission Reduction Credits for the Sequestration of Soil Carbon on Agricultural Land - Zimmerman, Patrick R.; Price, Maribeth; Peng, Changhui; Capehart, William J.; Updegraff, Karen; Kozak, Patrick; Vierling, Lee; Baker, Elaine; Kopp, Fred; Duke, Genet; Das, Chandan (Mitigation and Adaptation Strategies for Global Change, 2005)

The relationships between terrestrial vertebrate species richness in China’s nature reserves and environmental variables - Zhao, Shuqing; Fang, Jingyun; Peng, Changhui; Tang, Zhiyao (Canadian Journal of Zoology, 2006)
Explaining species richness patterns over broad geographic scales is a central issue of biogeography and macroecology. In this study, we took spatial autocorrelation into account and used terrestrial vertebrate species richness data from 211 nature reserves, together with climatic and topographical variables and reserve area, to explain terrestrial vertebrate species richness patterns in China and to test two climatically based hypotheses for animals. Our results demonstrated that species richness patterns of different terrestrial vertebrate taxa were predicted by the environmental variables used, in a decreasing order, as reptiles (56.5%), followed by amphibians (51.8%), mammals (42%), and birds (19%). The endothermic vertebrates (mammals and birds) were closely correlated with net primary productivity (NPP), which supports the productivity hypothesis, whereas the ectothermic vertebrates (amphibians and reptiles) were strongly associated with both water and energy variables but weakly with NPP, which supports the physiologically based ambient climate hypothesis. The differences in the dependence of endothermic and ectothermic vertebrates on productivity or ambient climate may be due in part to their different thermoregulatory mechanisms. Consistent with earlier studies, mammals were strongly and positively related to geomorphologic heterogeneity, measured by elevation range, implying that the protection of mountains may be especially important in conserving mammalian diversity.

Patterns of fish species richness in China's lakes - Zhao, Shuqing; Fang, Jingyun; Peng, Changhui; Tang, Zhiyao; Piao, Shilong (Global Ecology and Biogeography, 2006)
ABSTRACT Aim To document the patterns of fish species richness and their possible causes in China's lakes at regional and national scales. Location Lakes across China. Methods We compiled data of fish species richness, limnological characteristics and climatic variables for 109 lakes across five regions of China: East region, Northeast region, Southwest region, North‐Northwest region, and the Tibetan Plateau. Correlation analyses, regression models and a general linear model were used to explore the patterns of fish species richness. Results At the national scale, lake altitude, energy availability (potential evapotranspiration, PET) and lake area explained 79.6% of the total variation of the lake fish species richness. The determinants of the fish richness pattern varied among physiographic regions. Lake area was the strongest predictor of fish species richness in the East and Southwest lakes, accounting for 22.2% and 82.9% of the variation, respectively. Annual PET explained 68.7% of the variation of fish richness in the Northeast lakes. Maximum depth, mineralization degree, and lake area explained 45.5% of the fish variation in the lakes of the North‐Northwest region. On the Tibetan Plateau, lake altitude was the first predictor variable, interpreting 32.2% of the variation. Main conclusions Lake altitude was the most important factor explaining the variation of fish species richness across China's lakes, and accounted for 74.5% of the variation. This may stem in part from the fact that the lakes investigated in our study span the largest altitudinal range anywhere in the world. The effects of the lake altitude on fish species richness can be separated into direct and indirect aspects due to its collinearity with PET. We also found that the fish diversity and its determinants were scale‐dependent. Fish species richness was probably energy‐determined in the cold region, while it was best predicted by the lake area in the relatively geologically old region. The independent variables we used only explained a small fraction of the variations in the lake fish species richness in East China and the Tibetan Plateau, which may be due to the effects of human activity and historical events, respectively.

Land use change in Asia and the ecological consequences - Zhao, Shuqing; Peng, Changhui; Jiang, Hong; Tian, Dalun; Lei, Xiangdong; Zhou, Xiaolu (Ecological Research, 2006)
Abstract Viewed within a historical context, Asia has experienced dramatic land transformations, and currently more than 50% of Asian land area is under agriculture. The consequences of this transformation are manifold. Southeast Asia has the highest deforestation rate of any major tropical region. Many of the world's large rivers and lakes in Asia have been heavily degraded. About 11 of 19 world megacities with more than 10 million inhabitants are in Asia. These land use activities have resulted in substantial negative ecological consequences, including increased anthropogenic CO 2 emissions, deteriorated air and water quality, alteration of regional climate, an increase of disease and a loss of biodiversity. Although land use occurs at the local level, it has the potential to cause ecological impact across local, regional and global scales. Reducing the negative environmental impacts of land use change while maintaining economic viability and social acceptability is an major challenge for most developing countries in Asia.

Formulating and parameterizing the allocation of net primary productivity for modeling overmature stands in boreal forest ecosystems - Zhou, Xiaolu; Peng, Changhui; Dang, Qing-Lai (Ecological Modelling, 2006)

Relationships between species richness of vascular plants and terrestrial vertebrates in China: analyses based on data of nature reserves - Zhao, Shuqing; Fang, Jingyun; Peng, Changhui; Tang, Zhiyao (Diversity and Distributions, 2006)
ABSTRACT The relationship between plant diversity and animal diversity on a broadscale and its mechanisms are uncertain. In this study, we explored this relationship and its possible mechanisms using data from 186 nature reserves across China on species richness of vascular plants and terrestrial vertebrates, and climatic and topographical variables. We found significant positive correlations between species richness in almost all taxa of vascular plants and terrestrial vertebrates. Multiple regression analyses indicated that plant richness was a significant predictor of richness patterns for terrestrial vertebrates (except birds), suggesting that a causal association may exist between plant diversity and vertebrate diversity in China. The mechanisms for the relationships between species richness of plants and animals are probably dependent on vertebrate groups. For mammals (endothermic vertebrates), this relationship probably represents the integrated effects of plants on animals through trophic links (i.e. providing foods) and non‐trophic interactions (i.e. supplying habitats), whereas for amphibians and reptiles (ectothermic vertebrates), this may be a result of the non‐trophic links, such as the effects of plants on the resources that amphibians and reptiles require.

Building a "Green" Railway in China - Peng, Changhui; Ouyang, Hua; Gao, Qiong; Jiang, Yuan; Zhang, Feng; Li, Jun; Yu, Qiang (Science, 2007)

Growth and structure development of semi-natural larch-spruce-fir (Larix olgensis–Picea jezoensis–Abies nephrolepis) forests in northeast China: 12-year results after thinning - Lei, Xiangdong; Lu, Yuanchang; Peng, Changhui; Zhang, Xiaopeng; Chang, Jie; Hong, Lingxia (Forest Ecology and Management, 2007)

Meta-analysis and its application in global change research - Lei, XiangDong; Peng, ChangHui; Tian, DaLun; Sun, JianFeng (Chinese Science Bulletin, 2007)

Satellite-based estimation of biomass carbon stocks for northeast China's forests between 1982 and 1999 - Tan, Kun; Piao, Shilong; Peng, Changhui; Fang, Jingyun (Forest Ecology and Management, 2007)

A Simulation of Temporal and Spatial Variations in Carbon at Landscape Level: A Case Study for Lake Abitibi Model Forest in Ontario, Canada - Zhou, Xiaolu; Peng, Changhui; Dang, Qing-Lai; Chen, Jiaxin; Parton, Sue (Mitigation and Adaptation Strategies for Global Change, 2007)

Carbon storage by ecological service forests in Zhejiang Province, subtropical China - Zhang, Jun; Ge, Ying; Chang, Jie; Jiang, Bo; Jiang, Hong; Peng, Changhui; Zhu, Jinru; Yuan, Weigao; Qi, Lianzhong; Yu, Shuquan (Forest Ecology and Management, 2007)

Dominant factors controlling glacial and interglacial variations in the treeline elevation in tropical Africa - Wu, Haibin; Guiot, Joël; Brewer, Simon; Guo, Zhengtang; Peng, Changhui (Proceedings of the National Academy of Sciences, 2007)
The knowledge of tropical palaeoclimates is crucial for understanding global climate change, because it is a test bench for general circulation models that are ultimately used to predict future global warming. A longstanding issue concerning the last glacial maximum in the tropics is the discrepancy between the decrease in sea-surface temperatures reconstructed from marine proxies and the high-elevation decrease in land temperatures estimated from indicators of treeline elevation. In this study, an improved inverse vegetation modeling approach is used to quantitatively reconstruct palaeoclimate and to estimate the effects of different factors (temperature, precipitation, and atmospheric CO 2 concentration) on changes in treeline elevation based on a set of pollen data covering an altitudinal range from 100 to 3,140 m above sea level in Africa. We show that lowering of the African treeline during the last glacial maximum was primarily triggered by regional drying, especially at upper elevations, and was amplified by decreases in atmospheric CO 2 concentration and perhaps temperature. This contrasts with scenarios for the Holocene and future climates, in which the increase in treeline elevation will be dominated by temperature. Our results suggest that previous temperature changes inferred from tropical treeline shifts may have been overestimated for low-CO 2 glacial periods, because the limiting factors that control changes in treeline elevation differ between glacial and interglacial periods.

Sectoral approaches to improve regional carbon budgets - Smith, Pete; Nabuurs, Gert-Jan; Janssens, Ivan A.; Reis, Stefan; Marland, Gregg; Soussana, Jean-François; Christensen, Torben R.; Heath, Linda; Apps, Mike; Alexeyev, Vlady; Fang, Jingyun; Gattuso, Jean-Pierre; et al. (Climatic Change, 2008)

Leaf δ13 C reflects ecosystem patterns and responses of alpine plants to the environments on the Tibetan Plateau - Song, Minghua; Duan, Deyu; Chen, Hui; Hu, Qiwu; Zhang, Feng; Xu, Xingliang; Tian, Yuqiang; Ouyang, Hua; Peng, Changhui (Ecography, 2008)
Leaf δ 13 C is an indicator of water‐use efficiency and provides useful information on the carbon and water balance of plants over longer periods. Variation in leaf δ 13 C between or within species is determined by plant physiological characteristics and environmental factors. We hypothesized that variation in leaf δ 13 C values among dominant species reflected ecosystem patterns controlled by large‐scale environmental gradients, and that within‐species variation indicates plant adaptability to environmental conditions. To test these hypotheses, we collected leaves of dominant species from six ecosystems across a horizontal vegetation transect on the Tibetan Plateau, as well as leaves of Kobresia pygmaea (herbaceous) throughout its distribution and leaves of two coniferous tree species ( Picea crassifolia, Abies fabri ) along an elevation gradient throughout their distribution in the Qilian Mountains and Gongga Mountains, respectively. Leaf δ 13 C of dominant species in the six ecosystems differed significantly, with values for evergreen coniferous<evergreen broadleaved tree<alpine shrub<sedges∼graminoid<xeromorphs. Leaf δ 13 C values of the dominant species and of K. pygmaea were negatively correlated with annual precipitation along a water gradient, but leaf δ 13 C of A. fabri was not significantly correlated with precipitation in habitats without water‐stress. This confirms that variation of δ 13 C between or within species reflects plant responses to environmental conditions. Leaf δ 13 C of the dominant species also reflected water patterns on the Tibetan Plateau, providing evidence that precipitation plays a primary role in controlling ecosystem changes from southeast to northwest on the Tibetan Plateau.

Simulating carbon exchange in Canadian Boreal forests - Zhou, Xiaolu; Peng, Changhui; Dang, Qing-Lai; Sun, Jianfeng; Wu, Haibin; Hua, Dong (Ecological Modelling, 2008)

Micrometeorological measurements of nitrous oxide exchange above a cropland - Li, Jun; Tong, Xiaojuan; Yu, Qiang; Dong, Yunshe; Peng, Changhui (Atmospheric Environment, 2008)

TRIPLEX model testing and application for predicting forest growth and biomass production in the subtropical forest zone of China's Zhejiang Province - Zhang, Jun; Chu, Ziyan; Ge, Ying; Zhou, Xiaolu; Jiang, Hong; Chang, Jie; Peng, Changhui; Zheng, Jiawen; Jiang, Bo; Zhu, Jinru; Yu, Shuquan (Ecological Modelling, 2008)

Ecosystem service value assessment for constructed wetlands: A case study in Hangzhou, China - Yang, Wu; Chang, Jie; Xu, Bin; Peng, Changhui; Ge, Ying (Ecological Economics, 2008)

Variation in runoff with age of Chinese fir plantations in Central South China - Tian, Dalun; Yan, Wende; Chen, Xiaoyong; Deng, Xiangwen; Peng, Yuanying; Kang, Wenxing; Peng, Changhui (Hydrological Processes, 2008)
Abstract To determine the influence of forest structures on runoff characteristics, the hydrological effects of Chinese fir plantations were studied by analysing runoff patterns at different growth and development stages (stand age classes I to V) from 1984 to 2004 at the Huitong Ecosystem Research Station, Central South University of Forestry and Technology, Hunan Province, Central South China. Results for two small experimental Chinese fir watersheds showed different peak values for surface runoff amount and coefficients at different ages, with lowest values in age classes I and V and highest values in age classes II and III. However, both underground and total runoff coefficients decreased with increasing age class. Total runoff coefficient was about twice as high in age class I (30·8%) as that in age class V (15·8%). Higher underground and total runoff coefficients were found in young forests. This was mainly attributed to soil disturbance due to human management practices such as site ploughing. Results indicate that Chinese fir plantations play a significant role in regulating water distribution in the watershed. Useful information is provided on the effects of forest management practices on hydrological processes in forest plantations. Copyright © 2008 John Wiley & Sons, Ltd.

Simulating carbon exchange of Canadian boreal forests - Sun, Jianfeng; Peng, Changhui; McCaughey, Harry; Zhou, Xiaolu; Thomas, Valerie; Berninger, Frank; St-Onge, Benoît.; Hua, Dong (Ecological Modelling, 2008)

Marginal effects of silvicultural treatments on soil nutrients following harvest in a Chinese fir plantation - Xiang, Wenhua; Chai, Hongxia; Tian, Dalun; Peng, Changhui (Soil Science and Plant Nutrition, 2009)

Distribution of soil inorganic carbon storage and its changes due to agricultural land use activity in China - Wu, Haibin; Guo, Zhengtang; Gao, Qiong; Peng, Changhui (Agriculture, Ecosystems & Environment, 2009)

New coupled model used inversely for reconstructing past terrestrial carbon storage from pollen data: validation of model using modern data - Wu, Haibin; Guiot, Joël; Peng, Changhui; Guo, Zhengtang (Global Change Biology, 2009)
Abstract The knowledge of potential impacts of climate change on terrestrial vegetation is crucial to understand long‐term global carbon cycle development. Discrepancy in data has long existed between past carbon storage reconstructions since the Last Glacial Maximum by way of pollen, carbon isotopes, and general circulation model (GCM) analysis. This may be due to the fact that these methods do not synthetically take into account significant differences in climate distribution between modern and past conditions, as well as the effects of atmospheric CO 2 concentrations on vegetation. In this study, a new method to estimate past biospheric carbon stocks is reported, utilizing a new integrated ecosystem model (PCM) built on a physiological process vegetation model (BIOME4) coupled with a process‐based biospheric carbon model (DEMETER). The PCM was constrained to fit pollen data to obtain realistic estimates. It was estimated that the probability distribution of climatic parameters, as simulated by BIOME4 in an inverse process, was compatible with pollen data while DEMETER successfully simulated carbon storage values with corresponding outputs of BIOME4. The carbon model was validated with present‐day observations of vegetation biomes and soil carbon, and the inversion scheme was tested against 1491 surface pollen spectra sample sites procured in Africa and Eurasia. Results show that this method can successfully simulate biomes and related climates at most selected pollen sites, providing a coefficient of determination ( R ) of 0.83–0.97 between the observed and reconstructed climates, while also showing a consensus with an R ‐value of 0.90–0.96 between the simulated biome average terrestrial carbon variables and the available observations. The results demonstrate the reliability and feasibility of the climate reconstruction method and its potential efficiency in reconstructing past terrestrial carbon storage.

Constructed wetlands in China: recent developments and future challenges - Liu, Dong; Ge, Ying; Chang, Jie; Peng, Changhui; Gu, Binhe; Chan, Gilbert Ys; Wu, Xiaofu (Frontiers in Ecology and the Environment, 2009)
Constructed wetlands (CWs) are an emerging, environmentally friendly engineering system employed in China. They require lower investment and operation costs while providing higher treatment efficiency and more ecosystem services than conventional wastewater treatment methods. Introduced to China in 1987, CW systems used for wastewater treatment have rapidly increased in number, particularly since the late 1990s. This review summarizes the state‐of‐the‐art application of CW systems for water pollution treatment by reviewing the basics of the technology and its historical development and performance efficiency. Current progress, limitations, future concerns, and the challenges of CW technologies are also discussed. Also highlighted is the need for sufficient and appropriate data to assist in the further development of CW systems and the implementation of integrated “bottom‐up” and “top‐down” approaches by both the public in general and government bodies in particular.

Simulating age-related changes in carbon storage and allocation in a Chinese fir plantation growing in southern China using the 3-PG model - Zhao, Meifang; Xiang, Wenhua; Peng, Changhui; Tian, Dalun (Forest Ecology and Management, 2009)

Individual height–diameter models for young black spruce ( Picea mariana ) and jack pine ( Pinus banksiana ) plantations in New Brunswick, Canada - Lei, Xiangdong; Peng, Changhui; Wang, Haiyan; Zhou, Xiaolu (The Forestry Chronicle, 2009)
Historically, height–diameter models have mainly been developed for mature trees; consequently, few height–diameter models have been calibrated for young forest stands. In order to develop equations predicting the height of trees with small diameters, 46 individual height–diameter models were fitted and tested in young black spruce (Picea mariana) and jack pine (Pinus banksiana) plantations between the ages of 4 to 8 years, measured from 182 plots in New Brunswick, Canada. The models were divided into 2 groups: a diameter group and a second group applying both diameter and additional stand- or tree-level variables (composite models). There was little difference in predicting tree height among the former models (Group I) while the latter models (Group II) generally provided better prediction. Based on goodness of fit (R 2 and MSE), prediction ability (the bias and its associated prediction and tolerance intervals in absolute and relative terms), and ease of application, 2 Group II models were recommended for predicting individual tree heights within young black spruce and jack pine forest stands. Mean stand height was required for application of these models. The resultant tolerance intervals indicated that most errors (95%) associated with height predictions would be within the following limits (a 95% confidence level): [-0.54 m, 0.54 m] or [-14.7%, 15.9%] for black spruce and [-0.77 m, 0.77 m] or [-17.1%, 18.6%] for jack pine. The recommended models are statistically reliable for growth and yield applications, regeneration assessment and management planning. Key words: composite model, linear model, model calibration, model validation, prediction interval, tolerance interval

Relationships between stand growth and structural diversity in spruce-dominated forests in New Brunswick, Canada - Lei, Xiangdong; Wang, Weifeng; Peng, Changhui (Canadian Journal of Forest Research, 2009)
Relationships between stand growth and structural diversity were examined in spruce-dominated forests in New Brunswick, Canada. Net growth, survivor growth, mortality, and recruitment represented stand growth, and tree species, size, and height diversity indices were used to describe structural diversity. Mixed-effects second-order polynomial regressions were employed for statistical analysis. Results showed stand structural diversity had a significant positive effect on net growth and survivor growth by volume but not on mortality and recruitment. Among the tested diversity indices, the integrated diversity of tree species and height contributed most to stand net growth and survivor growth. Structural diversity showed increasing trends throughout the developmental stages from young, immature, mature, and overmature forest stands. This relationship between stand growth and structural diversity may be due to stands featuring high structural diversity that enhances niche complementarities of resource use because trees exist within different horizontal and vertical layers, and strong competition resulted from size differences among trees. It is recommended to include effects of species and structural diversity in forest growth modeling initiatives. Moreover, uneven-aged stand management in conjunction with selective or partial cutting to maintain high structural diversity is also recommended to maintain biodiversity and rapid growth in spruce-dominated forests.

Anthropogenic modification of the nitrogen cycling within the Greater Hangzhou Area system, China - Gu, Baojing; Chang, Jie; Ge, Ying; Ge, Hanliang; Yuan, Chi; Peng, Changhui; Jiang, Hong (Ecological Applications, 2009)
Based on the mass balance approach, a detailed quantification of nitrogen (N) cycling was constructed for an urban–rural complex system, named the Greater Hangzhou Area (GHA) system, for this paper. The GHA is located in the humid climatic region on the southeastern coast of China, one of the earliest regions in the Yangtze Delta to experience economic development. Total N input into the GHA was calculated at 274.66 Gg/yr (1 Gg = 10 9 g), and total output was calculated at 227.33 Gg/yr, while N accumulation was assessed at 47.33 Gg/yr (17.2% of the total N input). Human activity resulted in 73% of N input by means of synthetic fertilizers, human food, animal feed, imported N containing chemicals, fossil fuel combustion, and other items. More than 69.3% of N was released into the atmosphere, and riverine N export accounted for 22.2% of total N output. N input and output to and from the GHA in 1980 were estimated at 119.53 Gg/yr and 98.30 Gg/yr, respectively, with an increase of 130% and 131%, respectively, during a 24‐year period (from 1980 to 2004). The N input increase was influenced by synthetic fertilizers (138%), animal feed (225%), N‐containing chemicals (371%), riverine input (311%), and N deposition (441%). Compared to the N balance seen in the arid Central Arizona–Phoenix (CAP) system in the United States, the proportion of N transferred to water bodies in the humid GHA system was found to be 36 times higher than the CAP system. Anthropogenic activity, as it typically does, enhanced the flux of N biogeochemistry in the GHA; however, a lack of an N remover (N pollutant treatment facilities) causes excess reactive N (N r ; such as NH 3 , N 2 O, NO x ), polluting water bodies and the atmosphere within the GHA. Therefore many challenges remain ahead in order to achieve sustainable development in the rapidly developing GHA system.

Quantifying the response of forest carbon balance to future climate change in Northeastern China: Model validation and prediction - Peng, Changhui; Zhou, Xiaolu; Zhao, Shuqing; Wang, Xiangping; Zhu, Biao; Piao, Shilong; Fang, Jingyun (Global and Planetary Change, 2009)

Heavy metal accumulation by panicled goldenrain tree (Koelreuteria paniculata) and common elaeocarpus (Elaeocarpus decipens) in abandoned mine soils in southern China - Tian, Dalun; Zhu, Fan; Yan, Wende; Xi, Fang; Xiang, Wenhua; Deng, Xiangwen; Wang, Guangjun; Peng, Changhui (Journal of Environmental Sciences, 2009)

Application of artificial neural networks in global climate change and ecological research: An overview - Liu, ZeLin; Peng, ChangHui; Xiang, WenHua; Tian, DaLun; Deng, XiangWen; Zhao, MeiFang (Chinese Science Bulletin, 2010)

Soil respiration dynamics in Cinnamomum camphora forest and a nearby Liquidambar formosana forest in Subtropical China - Tian, DaLun; Wang, GuangJun; Yan, WenDe; Xiang, WenHua; Peng, ChangHui (Chinese Science Bulletin, 2010)

A model‐data intercomparison of CO2 exchange across North America: Results from the North American Carbon Program site synthesis - Schwalm, Christopher R.; Williams, Christopher A.; Schaefer, Kevin; Anderson, Ryan; Arain, M. Altaf; Baker, Ian; Barr, Alan; Black, T. Andrew; Chen, Guangsheng; Chen, Jing Ming; Ciais, Philippe; Davis, Kenneth J.; et al. (Journal of Geophysical Research: Biogeosciences, 2010)
Our current understanding of terrestrial carbon processes is represented in various models used to integrate and scale measurements of CO 2 exchange from remote sensing and other spatiotemporal data. Yet assessments are rarely conducted to determine how well models simulate carbon processes across vegetation types and environmental conditions. Using standardized data from the North American Carbon Program we compare observed and simulated monthly CO 2 exchange from 44 eddy covariance flux towers in North America and 22 terrestrial biosphere models. The analysis period spans ∼220 site‐years, 10 biomes, and includes two large‐scale drought events, providing a natural experiment to evaluate model skill as a function of drought and seasonality. We evaluate models' ability to simulate the seasonal cycle of CO 2 exchange using multiple model skill metrics and analyze links between model characteristics, site history, and model skill. Overall model performance was poor; the difference between observations and simulations was ∼10 times observational uncertainty, with forested ecosystems better predicted than nonforested. Model‐data agreement was highest in summer and in temperate evergreen forests. In contrast, model performance declined in spring and fall, especially in ecosystems with large deciduous components, and in dry periods during the growing season. Models used across multiple biomes and sites, the mean model ensemble, and a model using assimilated parameter values showed high consistency with observations. Models with the highest skill across all biomes all used prescribed canopy phenology, calculated NEE as the difference between GPP and ecosystem respiration, and did not use a daily time step.

Toward dynamic global vegetation models for simulating vegetation–climate interactions and feedbacks: recent developments, limitations, and future challenges - Quillet, Anne; Peng, Changhui; Garneau, Michelle (Environmental Reviews, 2010)
There is a lack in representation of biosphere–atmosphere interactions in current climate models. To fill this gap, one may introduce vegetation dynamics in surface transfer schemes or couple global climate models (GCMs) with vegetation dynamics models. As these vegetation dynamics models were not designed to be included in GCMs, how are the latest generation dynamic global vegetation models (DGVMs) suitable for use in global climate studies? This paper reviews the latest developments in DGVM modelling as well as the development of DGVM–GCM coupling in the framework of global climate studies. Limitations of DGVM and coupling are shown and the challenges of these methods are highlighted. During the last decade, DGVMs underwent major changes in the representation of physical and biogeochemical mechanisms such as photosynthesis and respiration processes as well as in the representation of regional properties of vegetation. However, several limitations such as carbon and nitrogen cycles, competition, land-use and land-use changes, and disturbances have been identified. In addition, recent advances in model coupling techniques allow the simulation of the vegetation–atmosphere interactions in GCMs with the help of DGVMs. Though DGVMs represent a good alternative to investigate vegetation–atmosphere interactions at a large scale, some weaknesses in evaluation methodology and model design need to be further investigated to improve the results.

Evaluating the spatiotemporal variations of water budget across China over 1951–2006 using IBIS model - Zhu, Qiuan; Jiang, Hong; Liu, Jinxun; Wei, Xiaohua; Peng, Changhui; Fang, Xiuqing; Liu, Shirong; Zhou, Guomo; Yu, Shuquan; Ju, Weiming (Hydrological Processes, 2010)
Abstract The Integrated Biosphere Simulator is used to evaluate the spatial and temporal patterns of the crucial hydrological variables [run‐off and actual evapotranspiration (AET)] of the water balance across China for the period 1951–2006 including a precipitation analysis. Results suggest three major findings. First, simulated run‐off captured 85% of the spatial variability and 80% of the temporal variability for 85 hydrological gauges across China. The mean relative errors were within 20% for 66% of the studied stations and within 30% for 86% of the stations. The Nash–Sutcliffe coefficients indicated that the quantity pattern of run‐off was also captured acceptably except for some watersheds in southwestern and northwestern China. The possible reasons for underestimation of run‐off in the Tibetan plateau include underestimation of precipitation and uncertainties in other meteorological data due to complex topography, and simplified representations of the soil depth attribute and snow processes in the model. Second, simulated AET matched reasonably with estimated values calculated as the residual of precipitation and run‐off for watersheds controlled by the hydrological gauges. Finally, trend analysis based on the Mann–Kendall method indicated that significant increasing and decreasing patterns in precipitation appeared in the northwest part of China and the Yellow River region, respectively. Significant increasing and decreasing trends in AET were detected in the Southwest region and the Yangtze River region, respectively. In addition, the Southwest region, northern China (including the Heilongjiang, Liaohe, and Haihe Basins), and the Yellow River Basin showed significant decreasing trends in run‐off, and the Zhemin hydrological region showed a significant increasing trend. Copyright © 2009 John Wiley & Sons, Ltd.

Altitudinal changes in carbon storage of temperate forests on Mt Changbai, Northeast China - Zhu, Biao; Wang, Xiangping; Fang, Jingyun; Piao, Shilong; Shen, Haihua; Zhao, Shuqing; Peng, Changhui (Journal of Plant Research, 2010)

Nitrous oxide fluxes from the littoral zone of a lake on the Qinghai-Tibetan Plateau - Chen, Huai; Wang, Meng; Wu, Ning; Wang, Yanfen; Zhu, Dan; Gao, Yongheng; Peng, Changhui (Environmental Monitoring and Assessment, 2011)

A long-term evaluation of biomass production in first and second rotations of Chinese fir plantations at the same site - Tian, D.; Xiang, W.; Chen, X.; Yan, W.; Fang, X.; Kang, W.; Dan, X.; Peng, C.; Peng, Y. (Forestry, 2011)

Quantification of provincial-level carbon emissions from energy consumption in China - Geng, Yuhuan; Tian, Mingzhong; Zhu, Qiuan; Zhang, Jianjun; Peng, Changhui (Renewable and Sustainable Energy Reviews, 2011)

Weak indirect effects inherent to nitrogen biogeochemical cycling within anthropogenic ecosystems: A network environ analysis - Min, Yong; Jin, Xiaogang; Chang, Jie; Peng, Changhui; Gu, Baojing; Ge, Ying; Zhong, Yang (Ecological Modelling, 2011)

Leaf respiration/photosynthesis relationship and variation: an investigation of 39 woody and herbaceous species in east subtropical China - Chu, Ziyan; Lu, Yijun; Chang, Jie; Wang, Meng; Jiang, Hong; He, Jinsheng; Peng, Changhui; Ge, Ying (Trees, 2011)

Detecting One-Hundred-Year Environmental Changes in Western China Using Seven-Year Repeat Photography - Chen, Huai; Yin, Kaipu; Wang, Haiyan; Zhong, Shenxian; Wu, Ning; Shi, Fusun; Zhu, Dan; Zhu, Qiuan; Wang, Weifeng; Ma, Zhihai; Fang, Xiuqin; Li, Weizhong; et al. (PLoS ONE, 2011)

Assessment of net ecosystem services of plastic greenhouse vegetable cultivation in China - Chang, Jie; Wu, Xu; Liu, Anqin; Wang, Yan; Xu, Bin; Yang, Wu; Meyerson, Laura A.; Gu, Baojing; Peng, Changhui; Ge, Ying (Ecological Economics, 2011)

Evaluating the effects of future climate change and elevated CO2 on the water use efficiency in terrestrial ecosystems of China - Zhu, Qiuan; Jiang, Hong; Peng, Changhui; Liu, Jinxun; Wei, Xiaohua; Fang, Xiuqin; Liu, Shirong; Zhou, Guomo; Yu, Shuquan (Ecological Modelling, 2011)

Selected papers presented in symposia organized at the 2009 conference of the International Society for Ecological Modelling (ISEM) in Quebec City, Canada, October 6–9, 2009 - Larocque, Guy R.; Yue, Tian-Xiang; Peng, Changhui; Bhatti, Jagtar; Etterson, Matthew A.; Kazanci, Caner; Goethals, Peter (Ecological Modelling, 2011)

Focus on quality, not just quantity - Peng, Changhui (Nature, 2011)

General allometric equations and biomass allocation of Pinus massoniana trees on a regional scale in southern China - Xiang, Wenhua; Liu, Shaohui; Deng, Xiangwen; Shen, Aihua; Lei, Xiangdong; Tian, Dalun; Zhao, Meifang; Peng, Changhui (Ecological Research, 2011)
Abstract Applying allometric equations in combination with forest inventory data is an effective approach to use when qualifying forest biomass and carbon storage on a regional scale. The objectives of this study were to (1) develop general allometric tree component biomass equations and (2) investigate tree biomass allocation patterns for Pinus massoniana , a principal tree species native to southern China, by applying 197 samples across 20 site locations. The additive allometric equations utilized to compute stem, branch, needle, root, aboveground, and total tree biomass were developed by nonlinear seemingly unrelated regression. Results show that the relative proportion of stem biomass to tree biomass increased while the contribution of canopy biomass to tree biomass decreased as trees continued to grow through time. Total root biomass was a large biomass pool in itself, and its relative proportion to tree biomass exhibited a slight increase with tree growth. Although equations employing stem diameter at breast height (dbh) alone as a predictor could accurately predict stem, aboveground, root, and total tree biomass, they were poorly fitted to predict the canopy biomass component. The inclusion of the tree height ( H ) variable either slightly improved or did not in any way increase model fitness. Validation results demonstrate that these equations are suitable to estimate stem, aboveground, and total tree biomass across a broad range of P . massoniana stands on a regional scale.

Integrating models with data in ecology and palaeoecology: advances towards a model-data fusion approach: Model-data fusion in ecology - Peng, Changhui; Guiot, Joel; Wu, Haibin; Jiang, Hong; Luo, Yiqi (Ecology Letters, 2011)

Quantification of net carbon flux from plastic greenhouse vegetable cultivation: A full carbon cycle analysis - Wang, Yan; Xu, Hao; Wu, Xu; Zhu, Yimei; Gu, Baojing; Niu, Xiaoyin; Liu, Anqin; Peng, Changhui; Ge, Ying; Chang, Jie (Environmental Pollution, 2011)

Quantifying carbon storage for tea plantations in China - Li, Shiyu; Wu, Xu; Xue, Hui; Gu, Baojng; Cheng, Hao; Zeng, Jianming; Peng, Changhui; Ge, Ying; Chang, Jie (Agriculture, Ecosystems & Environment, 2011)

The role of technology and policy in mitigating regional nitrogen pollution - Gu, Baojing; Zhu, Yimei; Chang, Jie; Peng, Changhui; Liu, Dong; Min, Yong; Luo, Weidong; Howarth, Robert W; Ge, Ying (Environmental Research Letters, 2011)

Methane emissions from the surface of the Three Gorges Reservoir: CH4 EMISSIONS FROM TGR - Chen, Huai; Yuan, Xingzhong; Chen, Zhongli; Wu, Yuyuan; Liu, Xianshu; Zhu, Dan; Wu, Ning; Zhu, Qiu'an; Peng, Changhui; Li, Weizhong (Journal of Geophysical Research: Atmospheres, 2011)

Delayed spring phenology on the Tibetan Plateau may also be attributable to other factors than winter and spring warming - Chen, Huai; Zhu, Qiuan; Wu, Ning; Wang, Yanfen; Peng, Chang-Hui (Proceedings of the National Academy of Sciences, 2011)

Forest Loss Triggers in Cameroon: A Quantitative Assessment Using Multiple Linear Regression Approach - Epule, Epule Terence; Peng, Changhui; Lepage, Laurent; Chen, Zhi (Journal of Geography and Geology, 2011)

Positive Relationship between Aboveground Carbon Stocks and Structural Diversity in Spruce-Dominated Forest Stands in New Brunswick, Canada - Wang, Weifeng; Lei, Xiangdong; Ma, Zhihai; Kneeshaw, Daniel D.; Peng, Changhui (Forest Science, 2011)
Abstract Maintaining both the structure and functionality of forest ecosystems is a primary goal of forest management. In this study, relationships between structural diversity and aboveground stand carbon (C) stocks were examined in spruce-dominated forests in New Brunswick, Canada. Tree species, size, and height diversity indices as well as a combination of these diversity indices were used to correlate aboveground C stocks. Multiple linear regressions were subsequently used to quantify the relationships between these indices and aboveground C stocks, and partial correlation analysis was also adopted to remove the effects of other explanatory variables. Results show that stand structural diversity has a significant positive effect on aboveground C stocks even though the relationship is weak overall. Positive relationships observed between the diversity indices and aboveground C stocks support the hypothesis that increased structural diversity enhances aboveground C storage capacity. This occurs because complex forest structures allow for greater light infiltration and promote a more efficient resource use by trees, leading to an increase in biomass and C production. Mixed tolerant species composition and uneven-aged stand management in conjunction with selection or partial cutting to maintain high structural diversity is therefore recommended to preserve biodiversity and C stocks in spruce-dominated forests.

Common challenges for ecological modelling: Synthesis of facilitated discussions held at the symposia organized for the 2009 conference of the International Society for Ecological Modelling in Quebec City, Canada, (October 6–9, 2009) - Larocque, G.R.; Mailly, D.; Yue, T.-X.; Anand, M.; Peng, C.; Kazanci, C.; Etterson, M.; Goethals, P.; Jørgensen, S.E.; Schramski, J.R.; McIntire, E.J.B.; Marceau, D.J.; et al. (Ecological Modelling, 2011)

Characterizing the performance of ecosystem models across time scales: A spectral analysis of the North American Carbon Program site-level synthesis - Dietze, Michael C.; Vargas, Rodrigo; Richardson, Andrew D.; Stoy, Paul C.; Barr, Alan G.; Anderson, Ryan S.; Arain, M. Altaf; Baker, Ian T.; Black, T. Andrew; Chen, Jing M.; Ciais, Philippe; Flanagan, Lawrence B.; et al. (Journal of Geophysical Research, 2011)

Carbon sequestration by Chinese bamboo forests and their ecological benefits: assessment of potential, problems, and future challenges - Song, Xinzhang; Zhou, Guomo; Jiang, Hong; Yu, Shuquan; Fu, Jinhe; Li, Weizhong; Wang, Weifeng; Ma, Zhihai; Peng, Changhui (Environmental Reviews, 2011)

Development of TRIPLEX-Management model for simulating the response of forest growth to pre-commercial thinning - Wang, Weifeng; Peng, Changhui; Zhang, S.Y.; Zhou, Xiaolu; Larocque, Guy R.; Kneeshaw, Daniel D.; Lei, Xiangdong (Ecological Modelling, 2011)

A drought-induced pervasive increase in tree mortality across Canada's boreal forests - Peng, Changhui; Ma, Zhihai; Lei, Xiangdong; Zhu, Qiuan; Chen, Huai; Wang, Weifeng; Liu, Shirong; Li, Weizhong; Fang, Xiuqin; Zhou, Xiaolu (Nature Climate Change, 2011)

Methane Emissions from Paddy Rice Fields: Strategies towards Achieving A Win-Win Sustainability Scenario between Rice Production and Methane Emission Reduction - Epule, Epule Terence; Peng, Changhui; Mafany, Ndiva Mongoh (Journal of Sustainable Development, 2011)

Well Water Quality and Public Health Implications: the Case of Four Neighbourhoods of the City of Douala Cameroon - Epule, Terence Epule; Peng, Changhui; Mirielle Wase, Moto; Mafany, Ndiva Mongoh (Global Journal of Health Science, 2011)

Overyielding of fine root biomass as increasing plant species richness in subtropical forests in central southern China: Overyielding of fine root biomass as increasing plant species richness in subtropical forests in central southern China - Liu, Cong; Xiang, Wen-Hua; Tian, Da-Lun; Fang, Xi; Peng, Chang-Hui (Chinese Journal of Plant Ecology, 2011)

Elevated UV-B radiation did not affect decomposition rates of needles of two coniferous species in subtropical China - Song, Xin-zhang; Jiang, Hong; Zhang, Hui-ling; Peng, Chang-hui; Yu, Shu-quan (European Journal of Soil Biology, 2011)

Methane Fluxes from Alpine Wetlands of Zoige Plateau in Relation to Water Regime and Vegetation under Two Scales - Chen, Huai; Wu, Ning; Wang, Yanfen; Gao, Yongheng; Peng, Changhui (Water, Air, & Soil Pollution, 2011)

Rainfall and Deforestation Dilemma for Cereal Production in the Sudano-Sahel of Cameroon - Epule, Terence Epule; Peng, Changhui; Lepage, Laurent; Chen, Zhi (Journal of Agricultural Science, 2012)

N-fertilization has different effects on the growth, carbon and nitrogen physiology, and wood properties of slow- and fast-growing Populus species - Li, Hong; Li, Mengchun; Luo, Jie; Cao, Xu; Qu, Long; Gai, Ying; Jiang, Xiangning; Liu, Tongxian; Bai, Hua; Janz, Dennis; Polle, Andrea; Peng, Changhui; et al. (Journal of Experimental Botany, 2012)

Drought-induced tree mortality: ecological consequences, causes, and modeling - Wang, Weifeng; Peng, Changhui; Kneeshaw, Daniel D.; Larocque, Guy R.; Luo, Zhibin (Environmental Reviews, 2012)
Drought-induced tree mortality, which rapidly alters forest ecosystem composition, structure, and function, as well as the feedbacks between the biosphere and climate, has occurred worldwide over the past few decades, and is expected to increase pervasively as climate change progresses. The objectives of this review are to (1) highlight the likely ecological consequences of drought-induced tree mortality, (2) synthesize the hypotheses related to drought-induced tree mortality, (3) discuss the implications of current knowledge for modeling tree mortality processes under climate change, and (4) highlight future research needs. First, we emphasize the likely ecological consequences of tree mortality from ecosystem to biome to continental scales. We then document and criticize multiple non-exclusive tree mortality hypotheses (e.g., carbon starvation — carbon supply is less than carbon demand; and hydraulic failure — desiccation from failed water transport) from a more comprehensive ecological perspective. Next, we extend a forest decline concept model, Manion’s framework, by considering new emerging environmental conditions, for a more thorough understanding of the effects of climate change on forest decline. We find that an increase in drought frequency and (or) climate-change-type droughts may trigger increased background tree mortality rates and severe forest dieback events, accelerating species turnover and ecological regime shifts. The contribution of CO 2 fertilization, rising temperature within the optimal growth range, and increased nitrogen deposition may defer or reduce this trend in tree mortality, but such contributions will vary between locations, species, and tree sizes. Multiple hypotheses proposed for drought-induced tree mortality are discussed, but coupling carbon and water cycles could help resolve the debate. The absence of a physiological understanding of tree mortality mechanisms limits the predictive ability of current models from stand-level process-based models to dynamic global vegetation models. We thus suggest that long-term observations, experiments, and models should be tightly interwoven during the research process to better forecast future climate changes and evaluate their impacts on forests.

Quantifying the effects of climate change and harvesting on carbon dynamics of boreal aspen and jack pine forests using the TRIPLEX-Management model - Wang, Weifeng; Peng, Changhui; Kneeshaw, Daniel D.; Larocque, Guy R.; Song, Xinzhang; Zhou, Xiaolu (Forest Ecology and Management, 2012)

Photosynthesis, water use efficiency and stable carbon isotope composition are associated with anatomical properties of leaf and xylem in six poplar species - Cao, X.; Jia, J. B.; Li, H.; Li, M. C.; Luo, J.; Liang, Z. S.; Liu, T. X.; Liu, W. G.; Peng, C. H.; Luo, Z. B. (Plant Biology, 2012)
Abstract Although fast‐growing Populus species consume a large amount of water for biomass production, there are considerable variations in water use efficiency (WUE) across different poplar species. To compare differences in growth, WUE and anatomical properties of leaf and xylem and to examine the relationship between photosynthesis/WUE and anatomical properties of leaf and xylem, cuttings of six poplar species were grown in a botanical garden. The growth performance, photosynthesis, intrinsic WUE (WUE i ), stable carbon isotope composition (δ 13 C) and anatomical properties of leaf and xylem were analysed in these poplar plants. Significant differences were found in growth, photosynthesis, WUE i and anatomical properties among the examined species. Populus cathayana was the clone with the fastest growth and the lowest WUE i /δ 13 C, whereas P. × euramericana had a considerable growth increment and the highest WUE i /δ 13 C. Among the analysed poplar species, the highest total stomatal density in P. cathayana was correlated with its highest stomatal conductance (g s ) and lowest WUE i /δ 13 C. Moreover, significant correlations were observed between WUE i and abaxial stomatal density and stem vessel lumen area. These data suggest that photosynthesis, WUE i and δ 13 C are associated with leaf and xylem anatomy and there are tradeoffs between growth and WUE i . It is anticipated that some poplar species, e.g. P. × euramericana , are better candidates for water‐limited regions and others, e.g. P. cathayana , may be better for water‐abundant areas.

Spatiotemporal Variations in Nitrous Oxide Emissions from an Open Fen on the Qinghai–Tibetan Plateau: a 3-Year Study - Chen, Huai; Wang, Yanfen; Wu, Ning; Zhu, Dan; Li, Wei; Gao, Yongheng; Zhu, Qiu’an; Yang, Gang; Peng, Changhui (Water, Air, & Soil Pollution, 2012)

Determining stem biomass of Pinus massoniana L. through variations in basic density - Zhang, L.; Deng, X.; Lei, X.; Xiang, W.; Peng, C.; Lei, P.; Yan, W. (Forestry, 2012)

An inventory of biogenic volatile organic compounds for a subtropical urban–rural complex - Chang, Jie; Ren, Yuan; Shi, Yan; Zhu, Yimei; Ge, Ying; Hong, Shengmao; Jiao, Li; Lin, Fengmei; Peng, Changhui; Mochizuki, Tomoki; Tani, Akira; Mu, Ying; et al. (Atmospheric Environment, 2012)

The long-term impact of urbanization on nitrogen patterns and dynamics in Shanghai, China - Gu, Baojing; Dong, Xiaoli; Peng, Changhui; Luo, Weidong; Chang, Jie; Ge, Ying (Environmental Pollution, 2012)

Elevated UV-B radiation increased the decomposition of Cinnamomum camphora and Cyclobalanopsis glauca leaf litter in subtropical China - Song, Xinzhang Z.; Zhang, Huiling L.; Chang, Scott X.; Jiang, Hong; Peng, Changhui H.; Yu, Shuquan Q. (Journal of Soils and Sediments, 2012)

Regional drought-induced reduction in the biomass carbon sink of Canada's boreal forests - Ma, Zhihai; Peng, Changhui; Zhu, Qiuan; Chen, Huai; Yu, Guirui; Li, Weizhong; Zhou, Xiaolu; Wang, Weifeng; Zhang, Wenhua (Proceedings of the National Academy of Sciences, 2012)
The boreal forests, identified as a critical “tipping element” of the Earth's climate system, play a critical role in the global carbon budget. Recent findings have suggested that terrestrial carbon sinks in northern high-latitude regions are weakening, but there has been little observational evidence to support the idea of a reduction of carbon sinks in northern terrestrial ecosystems. Here, we estimated changes in the biomass carbon sink of natural stands throughout Canada's boreal forests using data from long-term forest permanent sampling plots. We found that in recent decades, the rate of biomass change decreased significantly in western Canada (Alberta, Saskatchewan, and Manitoba), but there was no significant trend for eastern Canada (Ontario and Quebec). Our results revealed that recent climate change, and especially drought-induced water stress, is the dominant cause of the observed reduction in the biomass carbon sink, suggesting that western Canada's boreal forests may become net carbon sources if the climate change–induced droughts continue to intensify.

Simulations of runoff and evapotranspiration in Chinese fir plantation ecosystems using artificial neural networks - Liu, Zelin; Peng, Changhui; Xiang, Wenhua; Deng, Xiangwen; Tian, DaLun; Zhao, Meifang; Yu, Guirui (Ecological Modelling, 2012)

Simulations show potential for reduced emissions and carbon stocks increase in boreal forests under ecosystem management - Boisvenue, C; Bergeron, Y; Bernier, P; Peng, C (Carbon Management, 2012)

Constructed wetlands as biofuel production systems - Liu, Dong; Wu, Xu; Chang, Jie; Gu, Baojing; Min, Yong; Ge, Ying; Shi, Yan; Xue, Hui; Peng, Changhui; Wu, Jianguo (Nature Climate Change, 2012)

A model‐data comparison of gross primary productivity: Results from the North American Carbon Program site synthesis - Schaefer, Kevin; Schwalm, Christopher R.; Williams, Chris; Arain, M. Altaf; Barr, Alan; Chen, Jing M.; Davis, Kenneth J.; Dimitrov, Dimitre; Hilton, Timothy W.; Hollinger, David Y.; Humphreys, Elyn; Poulter, Benjamin; et al. (Journal of Geophysical Research: Biogeosciences, 2012)
Accurately simulating gross primary productivity (GPP) in terrestrial ecosystem models is critical because errors in simulated GPP propagate through the model to introduce additional errors in simulated biomass and other fluxes. We evaluated simulated, daily average GPP from 26 models against estimated GPP at 39 eddy covariance flux tower sites across the United States and Canada. None of the models in this study match estimated GPP within observed uncertainty. On average, models overestimate GPP in winter, spring, and fall, and underestimate GPP in summer. Models overpredicted GPP under dry conditions and for temperatures below 0°C. Improvements in simulated soil moisture and ecosystem response to drought or humidity stress will improve simulated GPP under dry conditions. Adding a low‐temperature response to shut down GPP for temperatures below 0°C will reduce the positive bias in winter, spring, and fall and improve simulated phenology. The negative bias in summer and poor overall performance resulted from mismatches between simulated and observed light use efficiency (LUE). Improving simulated GPP requires better leaf‐to‐canopy scaling and better values of model parameters that control the maximum potential GPP, such as ε max (LUE), V cmax (unstressed Rubisco catalytic capacity) or J max (the maximum electron transport rate). , Key Points Gross primary productivity (GPP) from 26 models tested at 39 flux tower sites Simulated light use efficiency controls model performance Models overpredict GPP under dry conditions

Effects of future climate change, CO2 enrichment, and vegetation structure variation on hydrological processes in China - Zhu, Qiuan; Jiang, Hong; Peng, Changhui; Liu, Jinxun; Fang, Xiuqin; Wei, Xiaohua; Liu, Shirong; Zhou, Guomo (Global and Planetary Change, 2012)

Assessment of private economic benefits and positive environmental externalities of tea plantation in China - Xue, Hui; Ren, Xiaoyi; Li, Shiyu; Wu, Xu; Cheng, Hao; Xu, Bin; Gu, Baojing; Yang, Guofu; Peng, Changhui; Ge, Ying; Chang, Jie (Environmental Monitoring and Assessment, 2013)

Cadmium tolerance in six poplar species - He, Jiali; Ma, Chaofeng; Ma, Yonglu; Li, Hong; Kang, Jingquan; Liu, Tongxian; Polle, Andrea; Peng, Changhui; Luo, Zhi-Bin (Environmental Science and Pollution Research, 2013)

The North American Carbon Program Multi-scale synthesis and Terrestrial Model Intercomparison Project – Part 1: Overview and experimental design - Huntzinger, D. N.; Schwalm, C.; Michalak, A. M.; Schaefer, K.; King, A. W.; Wei, Y.; Jacobson, A.; Liu, S.; Cook, R. B.; Post, W. M.; Berthier, G.; Hayes, D.; et al. (Biogeosciences, 2013)
Abstract. Terrestrial biosphere models (TBMs) have become an integral tool for extrapolating local observations and understanding of land-atmosphere carbon exchange to larger regions. The North American Carbon Program (NACP) Multi-scale synthesis and Terrestrial Model Intercomparison Project (MsTMIP) is a formal model intercomparison and evaluation effort focused on improving the diagnosis and attribution of carbon exchange at regional and global scales. MsTMIP builds upon current and past synthesis activities, and has a unique framework designed to isolate, interpret, and inform understanding of how model structural differences impact estimates of carbon uptake and release. Here we provide an overview of the MsTMIP effort and describe how the MsTMIP experimental design enables the assessment and quantification of TBM structural uncertainty. Model structure refers to the types of processes considered (e.g. nutrient cycling, disturbance, lateral transport of carbon), and how these processes are represented (e.g. photosynthetic formulation, temperature sensitivity, respiration) in the models. By prescribing a common experimental protocol with standard spin-up procedures and driver data sets, we isolate any biases and variability in TBM estimates of regional and global carbon budgets resulting from differences in the models themselves (i.e. model structure) and model-specific parameter values. An initial intercomparison of model structural differences is represented using hierarchical cluster diagrams (a.k.a. dendrograms), which highlight similarities and differences in how models account for carbon cycle, vegetation, energy, and nitrogen cycle dynamics. We show that, despite the standardized protocol used to derive initial conditions, models show a high degree of variation for GPP, total living biomass, and total soil carbon, underscoring the influence of differences in model structure and parameterization on model estimates.

Evaluating the agreement between measurements and models of net ecosystem exchange at different times and timescales using wavelet coherence: an example using data from the North American Carbon Program Site-Level Interim Synthesis - Stoy, P. C.; Dietze, M. C.; Richardson, A. D.; Vargas, R.; Barr, A. G.; Anderson, R. S.; Arain, M. A.; Baker, I. T.; Black, T. A.; Chen, J. M.; Cook, R. B.; Gough, C. M.; et al. (Biogeosciences, 2013)
Abstract. Earth system processes exhibit complex patterns across time, as do the models that seek to replicate these processes. Model output may or may not be significantly related to observations at different times and on different frequencies. Conventional model diagnostics provide an aggregate view of model–data agreement, but usually do not identify the time and frequency patterns of model–data disagreement, leaving unclear the steps required to improve model response to environmental drivers that vary on characteristic frequencies. Wavelet coherence can quantify the times and timescales at which two time series, for example time series of models and measurements, are significantly different. We applied wavelet coherence to interpret the predictions of 20 ecosystem models from the North American Carbon Program (NACP) Site-Level Interim Synthesis when confronted with eddy-covariance-measured net ecosystem exchange (NEE) from 10 ecosystems with multiple years of available data. Models were grouped into classes with similar approaches for incorporating phenology, the calculation of NEE, the inclusion of foliar nitrogen (N), and the use of model–data fusion. Models with prescribed, rather than prognostic, phenology often fit NEE observations better on annual to interannual timescales in grassland, wetland and agricultural ecosystems. Models that calculated NEE as net primary productivity (NPP) minus heterotrophic respiration (HR) rather than gross ecosystem productivity (GPP) minus ecosystem respiration (ER) fit better on annual timescales in grassland and wetland ecosystems, but models that calculated NEE as GPP minus ER were superior on monthly to seasonal timescales in two coniferous forests. Models that incorporated foliar nitrogen (N) data were successful at capturing NEE variability on interannual (multiple year) timescales at Howland Forest, Maine. The model that employed a model–data fusion approach often, but not always, resulted in improved fit to data, suggesting that improving model parameterization is important but not the only step for improving model performance. Combined with previous findings, our results suggest that the mechanisms driving daily and annual NEE variability tend to be correctly simulated, but the magnitude of these fluxes is often erroneous, suggesting that model parameterization must be improved. Few NACP models correctly predicted fluxes on seasonal and interannual timescales where spectral energy in NEE observations tends to be low, but where phenological events, multi-year oscillations in climatological drivers, and ecosystem succession are known to be important for determining ecosystem function. Mechanistic improvements to models must be made to replicate observed NEE variability on seasonal and interannual timescales.

Nitrous oxide emissions from the surface of the Three Gorges Reservoir - Zhu, Dan; Chen, Huai; Yuan, Xingzhong; Wu, Ning; Gao, Yongheng; Wu, Yan; Zhang, Yongmei; Peng, Changhui; Zhu, Qiu’an; Yang, Gang; Wu, Jianghua (Ecological Engineering, 2013)

The effects of plant diversity on nitrous oxide emissions in hydroponic microcosms - Sun, Hongying; Zhang, Chongbang; Song, Changchun; Chang, Scott X.; Gu, Baojing; Chen, Zhengxin; Peng, Changhui; Chang, Jie; Ge, Ying (Atmospheric Environment, 2013)

Changes in carbon, nutrients and stoichiometric relations under different soil depths, plant tissues and ages in black locust plantations - Li, Hong; Li, Jing; He, Yalong; Li, Shaojun; Liang, Zongsuo; Peng, Changhui; Polle, Andrea; Luo, Zhi-Bin (Acta Physiologiae Plantarum, 2013)

Assessing the spatio-temporal variation and uncertainty patterns of historical and future projected water resources in China - Zhu, Qiuan; Jiang, Hong; Peng, Changhui; Liu, Jinxun; Fang, Xiuqin; Chen, Huai; Liu, Shirong (Journal of Water and Climate Change, 2013)
The spatial and temporal variation and uncertainty of precipitation and runoff in China were compared and evaluated between historical and future periods under different climate change scenarios. The precipitation pattern is derived from observed and future projected precipitation data for historical and future periods, respectively. The runoff is derived from simulation results in historical and future periods using a dynamic global vegetation model (DGVM) forced with historical observed and global climate models (GCMs) future projected climate data, respectively. One GCM (CGCM3.1) under two emission scenarios (SRES A2 and SRES B1) was used for the future period simulations. The results indicated high uncertainties and variations in climate change effects on hydrological processes in China: precipitation and runoff showed a significant increasing trend in the future period but a decreasing trend in the historical period at the national level; the temporal variation and uncertainty of projected precipitation and runoff in the future period were predicted to be higher than those in the historical period; the levels of precipitation and runoff in the future period were higher than those in the historical period. The change in trends of precipitation and runoff are highly affected by different climate change scenarios. GCM structure and emission scenarios should be the major sources of uncertainty.

Global Priority Conservation Areas in the Face of 21st Century Climate Change - Li, Junsheng; Lin, Xin; Chen, Anping; Peterson, Townsend; Ma, Keping; Bertzky, Monika; Ciais, Philippe; Kapos, Valerie; Peng, Changhui; Poulter, Benjamin (PLoS ONE, 2013)

Net fluxes of ammonium and nitrate in association with H+ fluxes in fine roots of Populus popularis - Luo, Jie; Qin, Jingjing; He, Fangfang; Li, Hong; Liu, Tongxian; Polle, Andrea; Peng, Changhui; Luo, Zhi-Bin (Planta, 2013)

Differences in fine root traits between early and late-successional tree species in a Chinese subtropical forest - Xiang, W.; Wu, W.; Tong, J.; Deng, X.; Tian, D.; Zhang, L.; Liu, C.; Peng, C. (Forestry, 2013)

Assessing the role of parameter interactions in the sensitivity analysis of a model of peatland dynamics - Quillet, Anne; Frolking, Steve; Garneau, Michelle; Talbot, Julie; Peng, Changhui (Ecological Modelling, 2013)

Climate warming-induced upward shift of Moso bamboo population on Tianmu Mountain, China - Song, Xin-zhang; Peng, Chang-hui; Zhou, Guo-mo; Jiang, Hong; Wang, Wei-feng; Xiang, Wen-hua (Journal of Mountain Science, 2013)

A climate change‐induced threat to the ecological resilience of a subtropical monsoon evergreen broad‐leaved forest in Southern China - Zhou, Guoyi; Peng, Changhui; Li, Yuelin; Liu, Shizhong; Zhang, Qianmei; Tang, Xuli; Liu, Juxiu; Yan, Junhua; Zhang, Deqiang; Chu, Guowei (Global Change Biology, 2013)
Abstract Recent studies have suggested that tropical forests may not be resilient against climate change in the long term, primarily owing to predicted reductions in rainfall and forest productivity, increased tree mortality, and declining forest biomass carbon sinks. These changes will be caused by drought‐induced water stress and ecosystem disturbances. Several recent studies have reported that climate change has increased tree mortality in temperate and boreal forests, or both mortality and recruitment rates in tropical forests. However, no study has yet examined these changes in the subtropical forests that account for the majority of China's forested land. In this study, we describe how the monsoon evergreen broad‐leaved forest has responded to global warming and drought stress using 32 years of data from forest observation plots. Due to an imbalance in mortality and recruitment, and changes in diameter growth rates between larger and smaller trees and among different functional groups, the average DBH of trees and forest biomass have decreased. Sap flow measurements also showed that larger trees were more stressed than smaller trees by the warming and drying environment. As a result, the monsoon evergreen broad‐leaved forest community is undergoing a transition from a forest dominated by a cohort of fewer and larger individuals to a forest dominated by a cohort of more and smaller individuals, with a different species composition, suggesting that subtropical forests are threatened by their lack of resilience against long‐term climate change.

Effects of Increased Nitrogen Deposition and Rotation Length on Long-Term Productivity of Cunninghamia lanceolata Plantation in Southern China - Zhao, Meifang; Xiang, Wenhua; Tian, Dalun; Deng, Xiangwen; Huang, Zhihong; Zhou, Xiaolu; Peng, Changhui (PLoS ONE, 2013)

Does growing vegetables in plastic greenhouses enhance regional ecosystem services beyond the food supply? - Chang, Jie; Wu, Xu; Wang, Yan; Meyerson, Laura A; Gu, Baojing; Min, Yong; Xue, Hui; Peng, Changhui; Ge, Ying (Frontiers in Ecology and the Environment, 2013)
In recent years, plastic greenhouse vegetable cultivation (PGVC) has expanded worldwide, particularly in China, where it accounts for more than 90% of all global PGVC operations. As compared with conventional agricultural methods, PGVC has doubled crop yields by extending growing seasons and intensifying agriculture. PGVC also offers more ecosystem services relative to conventional approaches, including greater soil carbon sequestration, lower water consumption, and improved soil protection at regional scales. The economic benefits of this easily implemented agricultural method are attractive to small‐holder farmers. However, greater environmental impacts (eg greenhouse‐gas emissions, generation of large amounts of plastic waste) are associated with PGVC than with conventional approaches. Here, we review what is currently known about PGVC and identify future research priorities that will comprehensively assess the ecosystem services offered by this method of cultivation, as well as its environmental impacts and socioeconomic benefits.

The role of industrial nitrogen in the global nitrogen biogeochemical cycle - Gu, Baojing; Chang, Jie; Min, Yong; Ge, Ying; Zhu, Qiuan; Galloway, James N.; Peng, Changhui (Scientific Reports, 2013)

Inter-Annual Variations of Methane Emission from an Open Fen on the Qinghai-Tibetan Plateau: A Three-Year Study - Chen, Huai; Wu, Ning; Wang, Yanfen; Zhu, Dan; Zhu, Qiu’an; Yang, Gang; Gao, Yongheng; Fang, Xiuqin; Wang, Xu; Peng, Changhui (PLoS ONE, 2013)

Methane emissions from rice paddies natural wetlands, lakes in China: synthesis new estimate - Chen, Huai; Zhu, Qiu'an; Peng, Changhui; Wu, Ning; Wang, Yanfen; Fang, Xiuqin; Jiang, Hong; Xiang, Wenhua; Chang, Jie; Deng, Xiangwen; Yu, Guirui (Global Change Biology, 2013)
Abstract Sources of methane ( CH 4 ) become highly variable for countries undergoing a heightened period of development due to both human activity and climate change. An urgent need therefore exists to budget key sources of CH 4 , such as wetlands (rice paddies and natural wetlands) and lakes (including reservoirs and ponds), which are sensitive to these changes. For this study, references in relation to CH 4 emissions from rice paddies, natural wetlands, and lakes in C hina were first reviewed and then reestimated based on the review itself. Total emissions from the three CH 4 sources were 11.25 Tg CH 4 yr −1 (ranging from 7.98 to 15.16 Tg CH 4 yr −1 ). Among the emissions, 8.11 Tg CH 4 yr −1 (ranging from 5.20 to 11.36 Tg CH 4 yr −1 ) derived from rice paddies, 2.69 Tg CH 4 yr −1 (ranging from 2.46 to 3.20 Tg CH 4 yr −1 ) from natural wetlands, and 0.46 Tg CH 4 yr −1 (ranging from 0.33 to 0.59 Tg CH 4 yr −1 ) from lakes (including reservoirs and ponds). Plentiful water and warm conditions, as well as its large rice paddy area make rice paddies in southeastern C hina the greatest overall source of CH 4 , accounting for approximately 55% of total paddy emissions. Natural wetland estimates were slightly higher than the other estimates owing to the higher CH 4 emissions recorded within Q inghai‐ T ibetan P lateau peatlands. Total CH 4 emissions from lakes were estimated for the first time by this study, with three quarters from the littoral zone and one quarter from lake surfaces. Rice paddies, natural wetlands, and lakes are not constant sources of CH 4 , but decreasing ones influenced by anthropogenic activity and climate change. A new progress‐based model used in conjunction with more observations through model‐data fusion approach could help obtain better estimates and insights with regard to CH 4 emissions deriving from wetlands and lakes in C hina.

MODELING INDIVIDUAL TREE MORTALITY RATES USING MARGINAL AND RANDOM EFFECTS REGRESSION MODELS - Ma, Zhihai; Peng, Changhui; Li, Weizhong; Zhu, Qiuan; Wang, Weifeng; Song, Xinzhang; Liu, Jianwei (Natural Resource Modeling, 2013)
A bstract Developing models to predict tree mortality using data from long‐term repeated measurement data sets can be difficult and challenging due to the nature of mortality as well as the effects of dependence on observations. Marginal (population‐averaged) generalized estimating equations (GEE) and random effects (subject‐specific) models offer two possible ways to overcome these effects. For this study, standard logistic, marginal logistic based on the GEE approach, and random logistic regression models were fitted and compared. In addition, four model evaluation statistics were calculated by means of K ‐fold cross‐valuation. They include the mean prediction error, the mean absolute prediction error, the variance of prediction error, and the mean square error. Results from this study suggest that the random effects model produced the smallest evaluation statistics among the three models. Although marginal logistic regression accommodated for correlations between observations, it did not provide noticeable improvements of model performance compared to the standard logistic regression model that assumed impendence. This study indicates that the random effects model was able to increase the overall accuracy of mortality modeling. Moreover, it was able to ascertain correlation derived from the hierarchal data structure as well as serial correlation generated through repeated measurements.

Incorporating weather sensitivity in inventory-based estimates of boreal forest productivity: A meta-analysis of process model results - Wang, Z.; Grant, R.F.; Arain, M.A.; Bernier, P.Y.; Chen, B.; Chen, J.M.; Govind, A.; Guindon, L.; Kurz, W.A.; Peng, C.; Price, D.T.; Stinson, G.; et al. (Ecological Modelling, 2013)

Application of TRIPLEX model for predicting Cunninghamia lanceolata and Pinus massoniana forest stand production in Hunan Province, southern China - Zhao, Meifang; Xiang, Wenhua; Deng, Xiangwen; Tian, Dalun; Huang, Zhihong; Zhou, Xiaolu; Yu, Guirui; He, Honglin; Peng, Changhui (Ecological Modelling, 2013)

The impacts of climate change and human activities on biogeochemical cycles on the Q inghai‐ T ibetan P lateau - Chen, Huai; Zhu, Qiuan; Peng, Changhui; Wu, Ning; Wang, Yanfen; Fang, Xiuqing; Gao, Yongheng; Zhu, Dan; Yang, Gang; Tian, Jianqing; Kang, Xiaoming; Piao, Shilong; et al. (Global Change Biology, 2013)
Abstract With a pace of about twice the observed rate of global warming, the temperature on the Qinghai‐Tibetan Plateau (Earth's ‘third pole’) has increased by 0.2 °C per decade over the past 50 years, which results in significant permafrost thawing and glacier retreat. Our review suggested that warming enhanced net primary production and soil respiration, decreased methane ( CH 4 ) emissions from wetlands and increased CH 4 consumption of meadows, but might increase CH 4 emissions from lakes. Warming‐induced permafrost thawing and glaciers melting would also result in substantial emission of old carbon dioxide ( CO 2 ) and CH 4 . Nitrous oxide ( N 2 O ) emission was not stimulated by warming itself, but might be slightly enhanced by wetting. However, there are many uncertainties in such biogeochemical cycles under climate change. Human activities (e.g. grazing, land cover changes) further modified the biogeochemical cycles and amplified such uncertainties on the plateau. If the projected warming and wetting continues, the future biogeochemical cycles will be more complicated. So facing research in this field is an ongoing challenge of integrating field observations with process‐based ecosystem models to predict the impacts of future climate change and human activities at various temporal and spatial scales. To reduce the uncertainties and to improve the precision of the predictions of the impacts of climate change and human activities on biogeochemical cycles, efforts should focus on conducting more field observation studies, integrating data within improved models, and developing new knowledge about coupling among carbon, nitrogen, and phosphorus biogeochemical cycles as well as about the role of microbes in these cycles.

Direct and Indirect Effects of UV-B Exposure on Litter Decomposition: A Meta-Analysis - Song, Xinzhang; Peng, Changhui; Jiang, Hong; Zhu, Qiuan; Wang, Weifeng (PLoS ONE, 2013)

Monitoring and estimating drought-induced impacts on forest structure, growth, function, and ecosystem services using remote-sensing data: recent progress and future challenges - Zhang, Yao; Peng, Changhui; Li, Weizhong; Fang, Xiuqin; Zhang, Tinglong; Zhu, Qiuan; Chen, Huai; Zhao, Pengxiang (Environmental Reviews, 2013)
Alongside global warming, droughts are expected to increase in frequency, severity, and extent in the near future, which will likely result in significant impacts on forest growth, production, structure, composition, and ecosystem services. However, due to spatial and temporal characteristics, it is difficult to monitor and assess the potential effects of droughts. Remote sensing can provide an effective way to obtain real-time conditions of forests affected by drought and offer a range of spatial and temporal insights into drought-induced changes to forest ecosystem structure, function, and services. Remote sensing is rapidly developing as more satellites are launched. In situ and remotely sensed data fusion techniques have achieved notable success in assessing drought-induced damage to forests and carbon cycles. Even so, constraints still exist when using satellite data. The objectives of this review are to (1) briefly review existing data sources and methods of remote sensing; (2) synthesize current applications and contributions of remote sensing in monitoring and estimating impacts of droughts on forest ecosystems; and (3) highlight research gaps and future challenges.

Plant phenological modeling and its application in global climate change research: overview and future challenges - Zhao, Meifang; Peng, Changhui; Xiang, Wenhua; Deng, Xiangwen; Tian, Dalun; Zhou, Xiaolu; Yu, Guirui; He, Honglin; Zhao, Zhonghui (Environmental Reviews, 2013)
Plants interact to the seasonality of their environments, and changes in plant phenology have long been regarded as sensitive indicators of climatic change. Plant phenology modeling has been shown to be the simplest and most useful tool to assess phenol–climate shifts. Temperature, solar radiation, and water availability are assumed to be the key factors that control plant phenology. Statistical, mechanistic, and theoretical approaches have often been used for the parameterization of plant phenology models. The statistical approaches correlate the timing of phenological events to environmental factors or heat unit accumulations. The approaches have the simplified calculation procedures, correct phenological mechanism assumptions, but limited applications and predictive abilities. The mechanistic approaches describe plant phenology with the known or assumed “cause–effect relationships” between biological processes and key driving variables. The mechanistic approaches have the improved parameter processes, realistic assumptions, broad applications, and effective predictions. The theoretical approaches assume cost–benefit tradeoff strategies in trees. These methods are capable of capturing and quantifying the potential impacts and consequences of global climate change and human activity. However, certain limitations still exist related to our understanding of phenological mechanisms in relation to (1) interactions between plants and their specific climates, (2) the integration of both field observational and remote sensing data with plant phenology models across taxa and ecosystem type, (3) amplitude clarification of scale-related sensitivity to global climate change, and (4) improvements in parameterization processes and the overall reduction of modeling uncertainties to forecast impacts of future climate change on plant phenological dynamics. To improve our capacity in the prediction of the amplitude of plant phenological responses with regard to both structural and functional sensitivity to future global climate change, it is important to refine modeling methodologies by applying long-term and large-scale observational data. It is equally important to consider other less used but critical factors (such as heredity, pests, and anthropogenic drivers), apply advanced model parameterization and data assimilation techniques, incorporate process-based plant phenology models as a dynamic component into global vegetation dynamic models, and test plant phenology models against long-term ground observations and high-resolution satellite data across different spatial and temporal scales.

Nitrogen metabolism of two contrasting poplar species during acclimation to limiting nitrogen availability - Luo, Jie; Li, Hong; Liu, Tongxian; Polle, Andrea; Peng, Changhui; Luo, Zhi-Bin (Journal of Experimental Botany, 2013)

Policy options towards deforestation reduction in Cameroon: An analysis based on a systematic approach - Epule, Epule Terence; Peng, Changhui; Lepage, Laurent; Chen, Zhi (Land Use Policy, 2014)

Carbon dynamics of peatlands in China during the Holocene - Wang, Mei; Chen, Huai; Wu, Ning; Peng, Changhui; Zhu, Qiuan; Zhu, Dan; Yang, Gang; Wu, Jianghua; He, Yixin; Gao, Yongheng; Tian, Jianqing; Zhao, Xinquan (Quaternary Science Reviews, 2014)

An assessment of the predictors of the dynamics in arable production per capita index, arable production and permanent cropland and forest area based on structural equation models - Epule, Epule Terence; Bryant, Christopher Robin; Akkari, Cherine; Sarr, Mamadou Adama; Peng, Changhui (SpringerPlus, 2014)

Soil N forms and gross transformation rates in Chinese subtropical forests dominated by different tree species - Zeng, Yelin; Xiang, Wenhua; Deng, Xiangwen; Fang, Xi; Liu, Cong; Peng, Changhui (Plant and Soil, 2014)

Eradicating invasive Spartina alterniflora with alien Sonneratia apetala and its implications for invasion controls - Chen, Huai; Liao, Baowen; Liu, Bin’er; Peng, Changhui; Zhang, Yao; Guan, Wei; Zhu, Qiu’an; Yang, Gang (Ecological Engineering, 2014)

Applying an artificial neural network to simulate and predict Chinese fir (Cunninghamia lanceolata) plantation carbon flux in subtropical China - Wen, Xuding; Zhao, Zhonghui; Deng, Xiangwen; Xiang, Wenhua; Tian, Dalun; Yan, Wende; Zhou, Xiaolu; Peng, Changhui (Ecological Modelling, 2014)

High carbon dioxide uptake by subtropical forest ecosystems in the East Asian monsoon region - Yu, Guirui; Chen, Zhi; Piao, Shilong; Peng, Changhui; Ciais, Philippe; Wang, Qiufeng; Li, Xuanran; Zhu, Xianjin (Proceedings of the National Academy of Sciences, 2014)
Significance Understanding the location of carbon sources and sinks is essential for accurately predicting future changes in atmospheric carbon dioxide and climate. Mid- to high-latitude terrestrial ecosystems are well known to be the principal carbon sink regions, yet less attention has been paid to the mid- to low-latitude ecosystems. In this study, long-term eddy covariance observations demonstrate that there is a high carbon dioxide uptake (net ecosystem productivity) by the mid- to low-latitude East Asian monsoon subtropical forests that were shaped by the uplift of the Tibetan Plateau. Increasing nitrogen deposition, a young forest age structure, and sufficient water and heat availability combined to contribute to this large carbon dioxide uptake. , Temperate- and high-latitude forests have been shown to contribute a carbon sink in the Northern Hemisphere, but fewer studies have addressed the carbon balance of the subtropical forests. In the present study, we integrated eddy covariance observations established in the 1990s and 2000s to show that East Asian monsoon subtropical forests between 20°N and 40°N represent an average net ecosystem productivity (NEP) of 362 ± 39 g C m −2 yr −1 (mean ± 1 SE). This average forest NEP value is higher than that of Asian tropical and temperate forests and is also higher than that of forests at the same latitudes in Europe–Africa and North America. East Asian monsoon subtropical forests have comparable NEP to that of subtropical forests of the southeastern United States and intensively managed Western European forests. The total NEP of East Asian monsoon subtropical forests was estimated to be 0.72 ± 0.08 Pg C yr −1 , which accounts for 8% of the global forest NEP. This result indicates that the role of subtropical forests in the current global carbon cycle cannot be ignored and that the regional distributions of the Northern Hemisphere's terrestrial carbon sinks are needed to be reevaluated. The young stand ages and high nitrogen deposition, coupled with sufficient and synchronous water and heat availability, may be the primary reasons for the high NEP of this region, and further studies are needed to quantify the contribution of each underlying factor.

Chinese Grain for Green Program led to highly increased soil organic carbon levels: A meta-analysis - Song, Xinzhang; Peng, Changhui; Zhou, Guomo; Jiang, Hong; Wang, Weifeng (Scientific Reports, 2014)

Ectomycorrhizas with P axillus involutus enhance cadmium uptake and tolerance in P opulus × canescens - Ma, Yonglu; He, Jiali; Ma, Chaofeng; Luo, Jie; Li, Hong; Liu, Tongxian; Polle, Andrea; Peng, Changhui; Luo, Zhi‐Bin (Plant, Cell & Environment, 2014)
Ectomycorrhizas ( EMs ), which are symbiotic organs formed between tree roots and certain fungi, can mediate cadmium ( Cd ) tolerance of host plants, but the underlying physiological and molecular mechanisms are not fully understood. P opulus × canescens was inoculated with or without P axillus involutus (strain MAJ ) and subsequently exposed to 0 or 50 μM CdSO 4 . Higher net Cd 2+ influx in EMs well corresponded to higher transcript levels of genes involved in Cd 2+ uptake, transport and detoxification processes than those in nonmycorrhizal roots. Higher CO 2 assimilation, improved nutrient and carbohydrate status, and alleviated oxidative stress were found in mycorrhizal compared to nonmycorrhizal poplars despite higher Cd 2+ accumulation. , Abstract Ectomycorrhizas ( EMs ), which are symbiotic organs formed between tree roots and certain fungi, can mediate cadmium ( Cd ) tolerance of host plants, but the underlying physiological and molecular mechanisms are not fully understood. To investigate EMs mediated Cd tolerance in woody plants, P opulus × canescens was inoculated with P axillus involutus (strain MAJ ) to establish mycorrhizal roots. Mycorrhizal poplars and non‐mycorrhizal controls were exposed to 0 or 50 μ M CdSO 4 . EMs displayed higher net Cd 2+ influx than non‐mycorrhizal roots. Net Cd 2+ influx was coupled with net H + efflux and inactivation of plasma membrane ( PM ) H + ‐ ATPases reduced Cd 2+ uptake of EMs less than of non‐mycorrhizal roots. Consistent with higher Cd 2+ uptake in EMs , in most cases, transcript levels of genes involved in Cd 2+ uptake, transport and detoxification processes were increased in EMs compared to non‐mycorrhizal roots. Higher CO 2 assimilation, improved nutrient and carbohydrate status, and alleviated oxidative stress were found in mycorrhizal compared to non‐mycorrhizal poplars despite higher Cd 2+ accumulation. These results indicate that mycorrhizas increase Cd 2+ uptake, probably by an enlarged root volume and overexpression of genes involved in Cd 2+ uptake and transport, and concurrently enhance P o. × canescens Cd tolerance by increased detoxification, improved nutrient and carbohydrate status and defence preparedness.

Interactive effects of elevated UV-B radiation and N deposition on decomposition of Moso bamboo litter - Song, Xinzhang; Jiang, Hong; Zhang, Zhiting; Zhou, Guomo; Zhang, Shuikui; Peng, Changhui (Soil Biology and Biochemistry, 2014)

Modeling dissolved organic carbon in temperate forest soils: TRIPLEX-DOC model development and validation - Wu, H.; Peng, C.; Moore, T. R.; Hua, D.; Li, C.; Zhu, Q.; Peichl, M.; Arain, M. A.; Guo, Z. (Geoscientific Model Development, 2014)
Abstract. Even though dissolved organic carbon (DOC) is the most active carbon (C) cycling in soil organic carbon (SOC) pools, it receives little attention from the global C budget. DOC fluxes are critical to aquatic ecosystem inputs and contribute to the C balance of terrestrial ecosystems, but few ecosystem models have attempted to integrate DOC dynamics into terrestrial C cycling. This study introduces a new process-based model, TRIPLEX-DOC, that is capable of estimating DOC dynamics in forest soils by incorporating both ecological drivers and biogeochemical processes. TRIPLEX-DOC was developed from Forest-DNDC, a biogeochemical model simulating C and nitrogen (N) dynamics, coupled with a new DOC process module that predicts metabolic transformations, sorption/desorption, and DOC leaching in forest soils. The model was validated against field observations of DOC concentrations and fluxes at white pine forest stands located in southern Ontario, Canada. The model was able to simulate seasonal dynamics of DOC concentrations and the magnitudes observed within different soil layers, as well as DOC leaching in the age sequence of these forests. Additionally, TRIPLEX-DOC estimated the effect of forest harvesting on DOC leaching, with a significant increase following harvesting, illustrating that land use change is of critical importance in regulating DOC leaching in temperate forests as an important source of C input to aquatic ecosystems.

Modelling methane emissions from natural wetlands by development and application of the TRIPLEX-GHG model - Zhu, Q.; Liu, J.; Peng, C.; Chen, H.; Fang, X.; Jiang, H.; Yang, G.; Zhu, D.; Wang, W.; Zhou, X. (Geoscientific Model Development, 2014)
Abstract. A new process-based model TRIPLEX-GHG was developed based on the Integrated Biosphere Simulator (IBIS), coupled with a new methane (CH4) biogeochemistry module (incorporating CH4 production, oxidation, and transportation processes) and a water table module to investigate CH4 emission processes and dynamics that occur in natural wetlands. Sensitivity analysis indicates that the most sensitive parameters to evaluate CH4 emission processes from wetlands are r (defined as the CH4 to CO2 release ratio) and Q10 in the CH4 production process. These two parameters were subsequently calibrated to data obtained from 19 sites collected from approximately 35 studies across different wetlands globally. Being heterogeneously spatially distributed, r ranged from 0.1 to 0.7 with a mean value of 0.23, and the Q10 for CH4 production ranged from 1.6 to 4.5 with a mean value of 2.48. The model performed well when simulating magnitude and capturing temporal patterns in CH4 emissions from natural wetlands. Results suggest that the model is able to be applied to different wetlands under varying conditions and is also applicable for global-scale simulations.

Relationship between Air Pollutants and Economic Development of the Provincial Capital Cities in China during the Past Decade - Luo, Yunpeng; Chen, Huai; Zhu, Qiu'an; Peng, Changhui; Yang, Gang; Yang, Yanzheng; Zhang, Yao (PLoS ONE, 2014)

Effects of soil warming, rainfall reduction and water table level on CH 4 emissions from the Zoige peatland in China - Yang, Gang; Chen, Huai; Wu, Ning; Tian, Jianqing; Peng, Changhui; Zhu, Qiuan; Zhu, Dan; He, Yixin; Zheng, Qunying; Zhang, Changbing (Soil Biology and Biochemistry, 2014)

The carbon stock of alpine peatlands on the Qinghai–Tibetan Plateau during the Holocene and their future fate - Chen, Huai; Yang, Gang; Peng, Changhui; Zhang, Yao; Zhu, Dan; Zhu, Qiuan; Hu, Ji; Wang, Mei; Zhan, Wei; Zhu, Erxiong; Bai, Zengzhi; Li, Wei; et al. (Quaternary Science Reviews, 2014)

Soil methane uptake by grasslands and forests in China - Wang, Yanfen; Chen, Huai; Zhu, Qiuan; Peng, Changhui; Wu, Ning; Yang, Gang; Zhu, Dan; Tian, Jianqing; Tian, Liuxi; Kang, Xiaoming; He, Yixin; Gao, Yongheng; et al. (Soil Biology and Biochemistry, 2014)

The causes, effects and challenges of Sahelian droughts: a critical review - Epule, Epule Terence; Peng, Changhui; Lepage, Laurent; Chen, Zhi (Regional Environmental Change, 2014)

Climate Change Contribution to Forest Growth in Eastern China over Past Two Decades - Jin, Jiaxin; Jiang, Hong; Peng, Changhui; Zhang, Xiuying; Wang, Ying; Wang, Jinyin (Terrestrial, Atmospheric and Oceanic Sciences, 2014)

Quantification of soil respiration in forest ecosystems across China - Song, Xinzhang; Peng, Changhui; Zhao, Zhengyong; Zhang, Zhiting; Guo, Baohua; Wang, Weifeng; Jiang, Hong; Zhu, Qiuan (Atmospheric Environment, 2014)

Combination of nitrogen deposition and ultraviolet-B radiation decreased litter decomposition in subtropical China - Song, Xinzhang; Zhang, Huiling; Jiang, Hong; Peng, Changhui (Plant and Soil, 2014)

The 5000-year climate change of northeastern Qinghai-Tibetan Plateau and historical ecology of Zoige wetlands - He Yixin, 何奕忻; Wu Ning, 吴宁; Zhu Qiu'an, 朱求安; Chen Huai, 陈槐; Zhu Dan, 朱单; Peng Changhui, 彭长辉; Yang Gang, 杨刚; Gao Yongheng, 高永恒; Zhao Chuan, 赵川 (Acta Ecologica Sinica, 2014)

Anatomical, physiological and transcriptional responses of two contrasting poplar genotypes to drought and re‐watering - Cao, Xu; Jia, Jingbo; Zhang, Chao; Li, Hong; Liu, Tongxian; Jiang, Xiangning; Polle, Andrea; Peng, Changhui; Luo, Zhi‐Bin (Physiologia Plantarum, 2014)
Populus × euramericana (Pe) displays higher stable carbon isotope composition ( δ 13 C ) and intrinsic water use efficiency ( WUE i ) than Populus cathayana (Pc) under unlimited water conditions, rendering us to hypothesize that Pe is better acclimated to water deficiency than Pc. To examine this hypothesis, saplings of Pc and Pe were exposed to drought and subsequently re‐watered. Pc and Pe exhibited distinct anatomical, physiological and transcriptional responses in acclimation to drought and re‐watering, mainly due to stronger responsiveness of transcriptional regulation of genes encoding plasma membrane intrinsic proteins ( PIPs ), higher starch accumulation, δ 13 C , stable nitrogen isotope composition ( δ 15 N ) and WUE i , and lower reactive oxygen species ( ROS ) accumulation and scavenging in Pe. In acclimation to drought, both poplar genotypes demonstrated altered anatomical properties, declined height growth, differential expression of PIP s, activation of ABA signaling pathway, decreased total soluble sugars and starch, increased δ 13 C, δ 15 N and WUE i , and shifted homeostasis of ROS production and scavenging, and these changes can be recovered upon re‐watering. These data indicate that Pe is more tolerant to drought than Pc, and that anatomical, physiological and transcriptional acclimation to drought and re‐watering is essential for poplars to survive and grow under projected dry climate scenarios in the future.

Admixture of alder (Alnus formosana) litter can improve the decomposition of eucalyptus (Eucalyptus grandis) litter - Wu, Fuzhong; Peng, Changhui; Yang, Wanqin; Zhang, Jian; Han, Yu; Mao, Tao (Soil Biology and Biochemistry, 2014)

Insect‐induced tree mortality of boreal forests in eastern Canada under a changing climate - Zhang, Xiongqing; Lei, Yuancai; Ma, Zhihai; Kneeshaw, Dan; Peng, Changhui (Ecology and Evolution, 2014)
Abstract Forest insects are major disturbances that induce tree mortality in eastern coniferous (or fir‐spruce) forests in eastern North America. The spruce budworm ( SBW ) ( Choristoneura fumiferana [Clemens]) is the most devastating insect causing tree mortality. However, the relative importance of insect‐caused mortality versus tree mortality caused by other agents and how this relationship will change with climate change is not known. Based on permanent sample plots across eastern Canada, we combined a logistic model with a negative model to estimate tree mortality. The results showed that tree mortality increased mainly due to forest insects. The mean difference in annual tree mortality between plots disturbed by insects and those without insect disturbance was 0.0680 per year ( P < 0.0001, T ‐test), and the carbon sink loss was about 2.87t C ha −1 year −1 larger than in natural forests. We also found that annual tree mortality increased significantly with the annual climate moisture index ( CMI ) and decreased significantly with annual minimum temperature ( T min ), annual mean temperature ( T mean ) and the number of degree days below 0°C ( DD 0), which was inconsistent with previous studies (Adams et al. ; van Mantgem et al. ; Allen et al. ). Furthermore, the results for the trends in the magnitude of forest insect outbreaks were consistent with those of climate factors for annual tree mortality. Our results demonstrate that forest insects are the dominant cause of the tree mortality in eastern Canada but that tree mortality induced by insect outbreaks will decrease in eastern Canada under warming climate.

Enabling Conditions for Successful Greening of Public Spaces: The Case of Touroua, Cameroon Based on Perceptions - Epule, Epule Terence; Peng, Changhui; Lepage, Laurent; Chen, Zhi (Small-scale Forestry, 2014)

Integrating global socio-economic influences into a regional land use change model for China - Xu, Xia; Gao, Qiong; Peng, Changhui; Cui, Xuefeng; Liu, Yinghui; Jiang, Li (Frontiers of Earth Science, 2014)

Analysis of vegetation dynamics and climatic variability impacts on greenness across Canada using remotely sensed data from 2000 to 2009 - Fang, Xiuqin; Zhu, Qiuan; Chen, Huai; Ma, Zhihai; Wang, Weifeng; Song, Xinzhang; Zhao, Pengxiang; Peng, Changhui (Journal of Applied Remote Sensing, 2014)

Nitrous oxide fluxes from three forest types of the tropical mountain rainforests on Hainan Island, China - Bai, Zhenzhi; Yang, Gang; Chen, Huai; Zhu, Qiuan; Chen, Dexiang; Li, Yide; Wang, Xu; Wu, Zhongmin; Zhou, Guangyi; Peng, Changhui (Atmospheric Environment, 2014)

Elevation‐induced climate change as a dominant factor causing the late Miocene C4 plant expansion in the Himalayan foreland - Wu, Haibin; Guo, Zhengtang; Guiot, Joël; Hatté, Christine; Peng, Changhui; Yu, Yanyan; Ge, Junyi; Li, Qin; Sun, Aizhi; Zhao, Deai (Global Change Biology, 2014)
Abstract During the late Miocene, a dramatic global expansion of C 4 plant distribution occurred with broad spatial and temporal variations. Although the event is well documented, whether subsequent expansions were caused by a decreased atmospheric CO 2 concentration or climate change is a contentious issue. In this study, we used an improved inverse vegetation modeling approach that accounts for the physiological responses of C 3 and C 4 plants to quantitatively reconstruct the paleoclimate in the Siwalik of Nepal based on pollen and carbon isotope data. We also studied the sensitivity of the C 3 and C 4 plants to changes in the climate and the atmospheric CO 2 concentration. We suggest that the expansion of the C 4 plant distribution during the late Miocene may have been primarily triggered by regional aridification and temperature increases. The expansion was unlikely caused by reduced CO 2 levels alone. Our findings suggest that this abrupt ecological shift mainly resulted from climate changes related to the decreased elevation of the Himalayan foreland.

[Spatiotemporal variations of natural wetland CH4 emissions over China under future climate change] - Liu, Jian-gong; Zhu, Qiu-an; Shen, Yan; Yang, Yan-zheng; Luo, Yun-peng; Peng, Chang-hui (Ying Yong Sheng Tai Xue Bao = The Journal of Applied Ecology, 2015)
Based on a new process-based model, TRIPLEX-GHG, this paper analyzed the spatio-temporal variations of natural wetland CH4 emissions over China under different future climate change scenarios. When natural wetland distributions were fixed, the amount of CH4 emissions from natural wetland ecosystem over China would increase by 32.0%, 55.3% and 90.8% by the end of 21st century under three representative concentration pathways (RCPs) scenarios, RCP2. 6, RCP4.5 and RCP8.5, respectively, compared with the current level. Southern China would have higher CH4 emissions compared to that from central and northern China. Besides, there would be relatively low emission fluxes in western China while relatively high emission fluxes in eastern China. Spatially, the areas with relatively high CH4 emission fluxes would be concentrated in the middle-lower reaches of the Yangtze River, the Northeast and the coasts of the Pearl River. In the future, most natural wetlands would emit more CH4 for RCP4.5 and RCP8.5 than that of 2005. However, under RCP2.6 scenario, the increasing trend would be curbed and CH4 emissions (especially from the Qinghai-Tibet Plateau) begin to decrease in the late 21st century.
Keywords: Air Pollutants; China; Climate Change; Environmental Monitoring; Methane; Spatio-Temporal Analysis; Wetlands

Carbon accumulation and sequestration of lakes in China during the Holocene - Wang, Mei; Chen, Huai; Yu, Zicheng; Wu, Jianghua; Zhu, Qiu'an; Peng, Changhui; Wang, Yanfen; Qin, Boqiang (Global Change Biology, 2015)
Abstract Understanding the responses of lake systems to past climate change and human activity is critical for assessing and predicting the fate of lake carbon (C) in the future. In this study, we synthesized records of the sediment accumulation from 82 lakes and of C sequestration from 58 lakes with direct organic C measurements throughout China. We also identified the controlling factors of the long‐term sediment and C accumulation dynamics in these lakes during the past 12 ka (1 ka = 1000 cal yr BP ). Our results indicated an overall increasing trend of sediment and C accumulation since 12 ka, with an accumulation peak in the last couple of millennia for lakes in China, corresponding to terrestrial organic matter input due to land‐use change. The Holocene lake sediment accumulation rate ( SAR ) and C accumulation rate ( CAR ) averaged (mean ± SE ) 0.47 ± 0.05 mm yr −1 and 7.7 ± 1.4 g C m −2 yr −1 in China, respectively, comparable to the previous estimates for boreal and temperate regions. The SAR for lakes in the East Plain of subtropical China (1.05 ± 0.28 mm yr −1 ) was higher than those in other regions ( P < 0.05). However, CAR did not vary significantly among regions. Overall, the variability and history of climate and anthropogenic interference regulated the temporal and spatial dynamics of sediment and C sequestration for lakes in China. We estimated the total amount of C burial in lakes of China as 8.0 ± 1.0 Pg C. This first estimation of total C storage and dynamics in lakes of China confirms the importance of lakes in land C budget in monsoon‐influenced regions.

Disentangling climatic and anthropogenic controls on global terrestrial evapotranspiration trends - Mao, Jiafu; Fu, Wenting; Shi, Xiaoying; Ricciuto, Daniel M; Fisher, Joshua B; Dickinson, Robert E; Wei, Yaxing; Shem, Willis; Piao, Shilong; Wang, Kaicun; Schwalm, Christopher R; Tian, Hanqin; et al. (Environmental Research Letters, 2015)

Application of the ecosystem model and Markov Chain Monte Carlo for parameter estimation and productivity prediction - Li, Weizhong; Peng, Changhui; Zhou, Xiaolu; Sun, Jianfeng; Zhu, Qiuan; Wu, Haibin; St-Onge, Benoit (Ecosphere, 2015)
It is increasingly being recognized that global ecological research requires novel methods and strategies in which to combine process‐based ecological models and data in cohesive, systematic ways. In process‐based model applications, inherent spatial and temporal heterogeneities found within terrestrial ecosystems may lead to the uncertainties of model predictions. To reduce simulation uncertainties due to inaccurate model parameters, the Markov Chain Monte Carlo (MCMC) method was applied in this study to improve the estimations of four key parameters used in the process‐based ecosystem model of TRIPLEX‐FLUX. These four key parameters include a maximum photosynthetic carboxylation rate of 25°C (Vmax), an electron transport (Jmax) light‐saturated rate within the photosynthetic carbon reduction cycle of leaves, a coefficient of stomatal conductance (m), and a reference respiration rate of 10°C (R10). Seven forest flux tower sites located across North America were used to investigate and facilitate understanding of the daily variation in model parameters for three deciduous forests, three evergreen temperate forests, and one evergreen boreal forest. Eddy covariance CO 2 exchange measurements were assimilated to optimize the parameters in the year 2006. After parameter optimization and adjustment took place, net ecosystem production prediction significantly improved (by approximately 25%) compared to the CO 2 flux measurements taken at the seven forest ecosystem sites. Results suggest that greater seasonal variability occurs in broadleaf forests in respect to the selected parameters than in needleleaf forests. This study also demonstrated that the model‐data fusion approach by incorporating MCMC method is able to better estimate parameters and improve simulation accuracy for different ecosystems located across North America.

Phosphorus and nitrogen physiology of two contrasting poplar genotypes when exposed to phosphorus and/or nitrogen starvation - Gan, Honghao; Jiao, Yu; Jia, Jingbo; Wang, Xinli; Li, Hong; Shi, Wenguang; Peng, Changhui; Polle, Andrea; Luo, Zhi-Bin (Tree Physiology, 2016)

Monitoring the impact of aerosol contamination on the drought-induced decline of gross primary productivity - Zhang, Yao; Li, Weizhong; Zhu, Qiuan; Chen, Huai; Fang, Xiuqin; Zhang, Tinglong; Zhao, Pengxiang; Peng, Changhui (International Journal of Applied Earth Observation and Geoinformation, 2015)

From plant functional types to plant functional traits: A new paradigm in modelling global vegetation dynamics - Yang, Yanzheng; Zhu, Qiuan; Peng, Changhui; Wang, Han; Chen, Huai (Progress in Physical Geography: Earth and Environment, 2015)
Dynamic global vegetation models (DGVMs) typically track the material and energy cycles in ecosystems with finite plant functional types (PFTs). Increasingly, the community ecology and modelling studies recognize that current PFT scheme is not sufficient for simulating ecological processes. Recent advances in the study of plant functional traits (FTs) in community ecology provide a novel and feasible approach for the improvement of PFT-based DGVMs. This paper reviews the development of current DGVMs over recent decades. After characterizing the advantages and disadvantages of the PFT-based scheme, it summarizes trait-based theories and discusses the possibility of incorporating FTs into DGVMs. More importantly, this paper summarizes three strategies for constructing next-generation DGVMs with FTs. Finally, the method’s limitations, current challenges and future research directions for FT theory are discussed for FT theory. We strongly recommend the inclusion of several FTs, namely specific leaf area (SLA), leaf nitrogen content (LNC), carbon isotope composition of leaves (Leaf δ 13 C), the ratio between leaf-internal and ambient mole fractions of CO 2 (Leaf C i /C a ), seed mass and plant height. These are identified as the most important in constructing DGVMs based on FTs, which are also recognized as important ecological strategies for plants. The integration of FTs into dynamic vegetation models is a critical step towards improving the results of DGVM simulations; communication and cooperation among ecologists and modellers is equally important for the development of the next generation of DGVMs.

A novel pathway of direct methane production and emission by eukaryotes including plants, animals and fungi: An overview - Liu, Jiangong; Chen, Huai; Zhu, Qiuan; Shen, Yan; Wang, Xue; Wang, Meng; Peng, Changhui (Atmospheric Environment, 2015)

Estimating global natural wetland methane emissions using process modelling: spatio‐temporal patterns and contributions to atmospheric methane fluctuations - Zhu, Qiuan; Peng, Changhui; Chen, Huai; Fang, Xiuqin; Liu, Jinxun; Jiang, Hong; Yang, Yanzheng; Yang, Gang (Global Ecology and Biogeography, 2015)
Abstract Aim The fluctuations of atmospheric methane ( CH 4 ) that have occurred in recent decades are not fully understood, particularly with regard to the contribution from wetlands. The application of spatially explicit parameters has been suggested as an effective method for reducing uncertainties in bottom‐up approaches to wetland CH 4 emissions, but has not been included in recent studies. Our goal was to estimate spatio‐temporal patterns of global wetland CH 4 emissions using a process model and then to identify the contribution of wetland emissions to atmospheric CH 4 fluctuations. Location Global. Methods A process‐based model integrated with full descriptions of methanogenesis ( TRIPLEX‐GHG ) was used to simulate global wetland CH 4 emissions. Results Global annual wetland CH 4 emissions ranged from 209 to 245 T g CH 4 year −1 between 1901 and 2012, with peaks occurring in 1991 and 2012. There is a decreasing trend between 1990 and 2010 with a rate of approximately 0.48 T g CH 4 year −1 , which was largely caused by emissions from tropical wetlands showing a decreasing trend of 0.44 T g CH 4 year −1 since the 1970s. Emissions from tropical, temperate and high‐latitude wetlands comprised 59, 26 and 15% of global emissions, respectively. Main conclusion Global wetland CH 4 emissions, the interannual variability of which was primary controlled by tropical wetlands, partially drive the atmospheric CH 4 burden. The stable to decreasing trend in wetland CH 4 emissions, a result of a balance of emissions from tropical and extratropical wetlands, was a particular factor in slowing the atmospheric CH 4 growth rate during the 1990s. The rapid decrease in tropical wetland CH 4 emissions that began in 2000 was supposed to offset the increase in anthropogenic emissions and resulted in a relatively stable level of atmospheric CH 4 from 2000 to 2006. Increasing wetland CH 4 emissions, particularly after 2010, should be an important contributor to the growth in atmospheric CH 4 seen since 2007.

Development and Evaluation of Models for the Relationship between Tree Height and Diameter at Breast Height for Chinese-Fir Plantations in Subtropical China - Li, Yan-qiong; Deng, Xiang-wen; Huang, Zhi-hong; Xiang, Wen-hua; Yan, Wen-de; Lei, Pi-feng; Zhou, Xiao-lu; Peng, Chang-hui (PLOS ONE, 2015)

Agricultural carbon flux changes driven by intensive plastic greenhouse cultivation in five climatic regions of China - Wu, Xu; Ge, Ying; Wang, Yan; Liu, Dong; Gu, Baojing; Ren, Yuan; Yang, Guofu; Peng, Changhui; Cheng, Jihua; Chang, Jie (Journal of Cleaner Production, 2015)

Effects of Topographic and Soil Factors on Woody Species Assembly in a Chinese Subtropical Evergreen Broadleaved Forest - Zhao, Lijuan; Xiang, Wenhua; Li, Jiaxiang; Lei, Pifeng; Deng, Xiangwen; Fang, Xi; Peng, Changhui (Forests, 2015)
Evergreen broadleaved forests in subtropical China contain a complicated structure of diverse species. The impact of topographic and soil factors on the assembly of woody species in the forest has been poorly understood. We used Ripley’s K(t) function to analyze the spatial patterns and associations of dominant species and residual analysis (RDA) to quantify the contribution of topography and soil to species assembly. The 1 ha plot investigated had 4797 stems with a diameter at breast height (dbh) larger than 1 cm that belong to 73 species, 55 genera, and 38 families. All stems of the entire forest and four late successional species exhibited a reversed J shape for dbh distribution, while two early successional species showed a unimodal shape. Aggregation was the major spatial pattern for entire forests and dominant species across vertical layers. Spatial associations between inter- and intra-species were mostly independent. Topographic and soil factors explained 28.1% of species assembly. The forest was close to late succession and showed the characteristics of diverse woody species, high regeneration capacity, and aggregated spatial patterns. Topographic and soil factors affected species assembly, but together they could only explain a small part of total variance.

Nitrous oxide emission from infralittoral zone and pelagic zone in a shallow lake: Implications for whole lake flux estimation and lake restoration - Zhu, Dan; Wu, Yan; Wu, Ning; Chen, Huai; He, Yixin; Zhang, Yongmei; Peng, Changhui; Zhu, Qiu'an (Ecological Engineering, 2015)

Higher recent peat C accumulation than that during the Holocene on the Zoige Plateau - Wang, Mei; Yang, Gang; Gao, Yongheng; Chen, Huai; Wu, Ning; Peng, Changhui; Zhu, Qiuan; Zhu, Dan; Wu, Jianghua; He, Yixin; Tian, Jianqing; Zhao, Xinquan; et al. (Quaternary Science Reviews, 2015)

Using ecosystem service bundles to detect trade-offs and synergies across urban–rural complexes - Yang, Guofu; Ge, Ying; Xue, Hui; Yang, Wu; Shi, Yan; Peng, Changhui; Du, Yuanyuan; Fan, Xing; Ren, Yuan; Chang, Jie (Landscape and Urban Planning, 2015)

Temperature sensitivity of soil carbon dioxide and nitrous oxide emissions in mountain forest and meadow ecosystems in China - Zhang, Junjun; Peng, Changhui; Zhu, Qiuan; Xue, Wei; Shen, Yan; Yang, Yanzheng; Shi, Guohua; Shi, Shengwei; Wang, Meng (Atmospheric Environment, 2016)

A global meta-analysis of changes in soil carbon, nitrogen, phosphorus and sulfur, and stoichiometric shifts after forestation - Shi, Shengwei; Peng, Changhui; Wang, Meng; Zhu, Qiuan; Yang, Gang; Yang, Yanzheng; Xi, Tingting; Zhang, Tinglong (Plant and Soil, 2016)

Degradation of lignin and cellulose during foliar litter decomposition in an alpine forest river - Yue, Kai; Peng, Changhui; Yang, Wanqin; Peng, Yan; Zhang, Chuan; Huang, Chunping; Wu, Fuzhong (Ecosphere, 2016)
Abstract Lignin and cellulose are thought to be critical factors that affect the rate of litter decomposition; however, few data are available on their degradation dynamics during litter decomposition in lotic ecosystems, such as forest rivers, where litter can decompose much more rapidly than in terrestrial ecosystems. We studied the degradation of lignin and cellulose in the foliar litter of four dominant riparian species (willow: Salix paraplesia ; azalea: Rhododendron lapponicum ; cypress: Sabina saltuaria ; and larch: Larix mastersiana ) in an alpine forest river. Over an entire year's incubation, litter lignin and cellulose degraded by 14.7–100% and 57.7–100% of their initial masses, respectively, depending on litter species. Strong degradations of lignin and cellulose occurred in the prefreezing period (i.e., the first 41 d) during litter decomposition, and the degradation rate was the highest among all the decomposition periods regardless of litter species. Litter species, decomposition period, and environmental factors such as temperature and nutrient availability showed significant influences on lignin and cellulose degradation rates. Compared with previously reported data regarding the dynamics of lignin and cellulose during litter decomposition in terrestrial ecosystems, our results suggest that lignin and cellulose can be degraded much more rapidly in lotic ecosystems, indicating that the traditionally used two‐phased model for the dynamics of lignin in decomposing litter may not be suitable in lotic ecosystems.

The Spatial and Temporal Distribution of Dissolved Organic Carbon Exported from Three Chinese Rivers to the China Sea - Shi, Guohua; Peng, Changhui; Wang, Meng; Shi, Shengwei; Yang, Yanzheng; Chu, Junyao; Zhang, Junjun; Lin, Guanghui; Shen, Yan; Zhu, Qiuan (PLOS ONE, 2016)

Soil properties and species composition under different grazing intensity in an alpine meadow on the eastern Tibetan Plateau, China - Yang, Zhen’an; Xiong, Wan; Xu, Yingyi; Jiang, Lin; Zhu, Erxiong; Zhan, Wei; He, Yixin; Zhu, Dan; Zhu, Qiuan; Peng, Changhui; Chen, Huai (Environmental Monitoring and Assessment, 2016)

Climate-driven increase of natural wetland methane emissions offset by human-induced wetland reduction in China over the past three decades - Zhu, Qiuan; Peng, Changhui; Liu, Jinxun; Jiang, Hong; Fang, Xiuqin; Chen, Huai; Niu, Zhenguo; Gong, Peng; Lin, Guanghui; Wang, Meng; Wang, Han; Yang, Yanzheng; et al. (Scientific Reports, 2016)
Abstract Both anthropogenic activities and climate change can affect the biogeochemical processes of natural wetland methanogenesis. Quantifying possible impacts of changing climate and wetland area on wetland methane (CH 4 ) emissions in China is important for improving our knowledge on CH 4 budgets locally and globally. However, their respective and combined effects are uncertain. We incorporated changes in wetland area derived from remote sensing into a dynamic CH 4 model to quantify the human and climate change induced contributions to natural wetland CH 4 emissions in China over the past three decades. Here we found that human-induced wetland loss contributed 34.3% to the CH 4 emissions reduction (0.92 TgCH 4 ), and climate change contributed 20.4% to the CH 4 emissions increase (0.31 TgCH 4 ), suggesting that decreasing CH 4 emissions due to human-induced wetland reductions has offset the increasing climate-driven CH 4 emissions. With climate change only, temperature was a dominant controlling factor for wetland CH 4 emissions in the northeast (high latitude) and Qinghai-Tibet Plateau (high altitude) regions, whereas precipitation had a considerable influence in relative arid north China. The inevitable uncertainties caused by the asynchronous for different regions or periods due to inter-annual or seasonal variations among remote sensing images should be considered in the wetland CH 4 emissions estimation.

Simulated effects of nitrogen saturation on the global carbon budget using the IBIS model - Lu, Xuehe; Jiang, Hong; Liu, Jinxun; Zhang, Xiuying; Jin, Jiaxin; Zhu, Qiuan; Zhang, Zhen; Peng, Changhui (Scientific Reports, 2016)
Abstract Over the past 100 years, human activity has greatly changed the rate of atmospheric N (nitrogen) deposition in terrestrial ecosystems, resulting in N saturation in some regions of the world. The contribution of N saturation to the global carbon budget remains uncertain due to the complicated nature of C-N (carbon-nitrogen) interactions and diverse geography. Although N deposition is included in most terrestrial ecosystem models, the effect of N saturation is frequently overlooked. In this study, the IBIS (Integrated BIosphere Simulator) was used to simulate the global-scale effects of N saturation during the period 1961–2009. The results of this model indicate that N saturation reduced global NPP (Net Primary Productivity) and NEP (Net Ecosystem Productivity) by 0.26 and 0.03 Pg C yr −1 , respectively. The negative effects of N saturation on carbon sequestration occurred primarily in temperate forests and grasslands. In response to elevated CO 2 levels, global N turnover slowed due to increased biomass growth, resulting in a decline in soil mineral N. These changes in N cycling reduced the impact of N saturation on the global carbon budget. However, elevated N deposition in certain regions may further alter N saturation and C-N coupling.

Stimulation of terrestrial ecosystem carbon storage by nitrogen addition: a meta-analysis - Yue, Kai; Peng, Yan; Peng, Changhui; Yang, Wanqin; Peng, Xin; Wu, Fuzhong (Scientific Reports, 2016)
Abstract Elevated nitrogen (N) deposition alters the terrestrial carbon (C) cycle, which is likely to feed back to further climate change. However, how the overall terrestrial ecosystem C pools and fluxes respond to N addition remains unclear. By synthesizing data from multiple terrestrial ecosystems, we quantified the response of C pools and fluxes to experimental N addition using a comprehensive meta-analysis method. Our results showed that N addition significantly stimulated soil total C storage by 5.82% ([2.47%, 9.27%], 95% CI, the same below) and increased the C contents of the above- and below-ground parts of plants by 25.65% [11.07%, 42.12%] and 15.93% [6.80%, 25.85%], respectively. Furthermore, N addition significantly increased aboveground net primary production by 52.38% [40.58%, 65.19%] and litterfall by 14.67% [9.24%, 20.38%] at a global scale. However, the C influx from the plant litter to the soil through litter decomposition and the efflux from the soil due to microbial respiration and soil respiration showed insignificant responses to N addition. Overall, our meta-analysis suggested that N addition will increase soil C storage and plant C in both above- and below-ground parts, indicating that terrestrial ecosystems might act to strengthen as a C sink under increasing N deposition.

Archaeal communities in the sediments of different mangrove stands at Dongzhaigang, China - Li, Wei; Guan, Wei; Chen, Huai; Liao, Baowen; Hu, Ji; Peng, Changhui; Rui, Junpeng; Tian, Jianqing; Zhu, Dan; He, Yixin (Journal of Soils and Sediments, 2016)

Biomass offsets little or none of permafrost carbon release from soils, streams, and wildfire: an expert assessment - Abbott, Benjamin W; Jones, Jeremy B; Schuur, Edward A G; Chapin Iii, F Stuart; Bowden, William B; Bret-Harte, M Syndonia; Epstein, Howard E; Flannigan, Michael D; Harms, Tamara K; Hollingsworth, Teresa N; Mack, Michelle C; McGuire, A David; et al. (Environmental Research Letters, 2016)

A novel approach for modelling vegetation distributions and analysing vegetation sensitivity through trait-climate relationships in China - Yang, Yanzheng; Zhu, Qiuan; Peng, Changhui; Wang, Han; Xue, Wei; Lin, Guanghui; Wen, Zhongming; Chang, Jie; Wang, Meng; Liu, Guobin; Li, Shiqing (Scientific Reports, 2016)
Abstract Increasing evidence indicates that current dynamic global vegetation models (DGVMs) have suffered from insufficient realism and are difficult to improve, particularly because they are built on plant functional type (PFT) schemes. Therefore, new approaches, such as plant trait-based methods, are urgently needed to replace PFT schemes when predicting the distribution of vegetation and investigating vegetation sensitivity. As an important direction towards constructing next-generation DGVMs based on plant functional traits, we propose a novel approach for modelling vegetation distributions and analysing vegetation sensitivity through trait-climate relationships in China. The results demonstrated that a Gaussian mixture model (GMM) trained with a LMA-N mass -LAI data combination yielded an accuracy of 72.82% in simulating vegetation distribution, providing more detailed parameter information regarding community structures and ecosystem functions. The new approach also performed well in analyses of vegetation sensitivity to different climatic scenarios. Although the trait-climate relationship is not the only candidate useful for predicting vegetation distributions and analysing climatic sensitivity, it sheds new light on the development of next-generation trait-based DGVMs.

Evaluating the carbon budget pattern of Chinese terrestrial ecosystem from 1960 to 2006 using Integrated Biosphere Simulator - Yang Yanzheng, 杨延征; Ma Yuandan, 马元丹; Jiang Hong, 江洪; Zhu Qiu'an, 朱求安; Liu Jinxun, 刘金勋; Peng Changhui, 彭长辉 (Acta Ecologica Sinica, 2016)

Integrating a model with remote sensing observations by a data assimilation approach to improve the model simulation accuracy of carbon flux and evapotranspiration at two flux sites - Zhang, TingLong; Sun, Rui; Peng, ChangHui; Zhou, GuoYi; Wang, ChunLing; Zhu, QiuAn; Yang, YanZheng (Science China Earth Sciences, 2016)

Simulating carbon dioxide exchange in boreal ecosystems flooded by reservoirs - Kim, Youngil; Roulet, Nigel T.; Li, Changsheng; Frolking, Steve; Strachan, Ian B.; Peng, Changhui; Teodoru, Cristian R.; Prairie, Yves T.; Tremblay, Alain (Ecological Modelling, 2016)

Significant effects of biodiversity on forest biomass during the succession of subtropical forest in south China - Ouyang, Shuai; Xiang, Wenhua; Wang, Xiangping; Zeng, Yelin; Lei, Pifeng; Deng, Xiangwen; Peng, Changhui (Forest Ecology and Management, 2016)

Foliar litter decomposition in an alpine forest meta-ecosystem on the eastern Tibetan Plateau - Yue, Kai; Yang, Wanqin; Peng, Changhui; Peng, Yan; Zhang, Chuan; Huang, Chunping; Tan, Yu; Wu, Fuzhong (Science of The Total Environment, 2016)

Soil Carbon Dioxide Fluxes from Three Forest Types of the Tropical Montane Rainforest on Hainan Island, China - Jiang, Xinhua; Chen, Huai; Peng, Changhui; Li, Yide; He, Yixin; Chen, Dexiang; Lin, Mingxian; Hu, Ji; Ma, Tianli; Liu, Liangfeng; Liu, Xinwei; Xia, Miao; et al. (Water, Air, & Soil Pollution, 2016)

Uncertainty analysis of terrestrial net primary productivity and net biome productivity in China during 1901–2005 - Shao, Junjiong; Zhou, Xuhui; Luo, Yiqi; Zhang, Guodong; Yan, Wei; Li, Jiaxuan; Li, Bo; Dan, Li; Fisher, Joshua B.; Gao, Zhiqiang; He, Yong; Huntzinger, Deborah; et al. (Journal of Geophysical Research: Biogeosciences, 2016)
Abstract Despite the importance of net primary productivity (NPP) and net biome productivity (NBP), estimates of NPP and NBP for China are highly uncertain. To investigate the main sources of uncertainty, we synthesized model estimates of NPP and NBP for China from published literature and the Multi‐scale Synthesis and Terrestrial Model Intercomparison Project (MsTMIP). The literature‐based results showed that total NPP and NBP in China were 3.35 ± 1.25 and 0.14 ± 0.094 Pg C yr −1 , respectively. Classification and regression tree analysis based on literature data showed that model type was the primary source of the uncertainty, explaining 36% and 64% of the variance in NPP and NBP, respectively. Spatiotemporal scales, land cover conditions, inclusion of the N cycle, and effects of N addition also contributed to the overall uncertainty. Results based on the MsTMIP data suggested that model structures were overwhelmingly important (>90%) for the overall uncertainty compared to simulations with different combinations of time‐varying global change factors. The interannual pattern of NPP was similar among diverse studies and increased by 0.012 Pg C yr −1 during 1981–2000. In addition, high uncertainty in China's NPP occurred in areas with high productivity, whereas NBP showed the opposite pattern. Our results suggest that to significantly reduce uncertainty in estimated NPP and NBP, model structures should be substantially tested on the basis of empirical results. To this end, coordinated distributed experiments with multiple global change factors might be a practical approach that can validate specific structures of different models. , Key Points Large uncertainty exists in estimates of terrestrial NPP and NBP in China Methodological differences greatly contribute to the uncertainty in NPP and NBP Uncertainty in the interannual pattern of NBP is greater than that of NPP

Spatial and seasonal variations of leaf area index (LAI) in subtropicalsecondary forests related to floristic composition and stand characters - Zhu, Wenjuan; Xiang, Wenhua; Pan, Qiong; Zeng, Yelin; Ouyang, Shuai; Lei, Pifeng; Deng, Xiangwen; Fang, Xi; Peng, Changhui (Biogeosciences, 2016)
Abstract. Leaf area index (LAI) is an important parameter related to carbon, water, and energy exchange between canopy and atmosphere and is widely applied in process models that simulate production and hydrological cycles in forest ecosystems. However, fine-scale spatial heterogeneity of LAI and its controlling factors have yet to be fully understood in Chinese subtropical forests. We used hemispherical photography to measure LAI values in three subtropical forests (Pinus massoniana–Lithocarpus glaber coniferous and evergreen broadleaved mixed forests, Choerospondias axillaris deciduous broadleaved forests, and L. glaber–Cyclobalanopsis glauca evergreen broadleaved forests) from April 2014 to January 2015. Spatial heterogeneity of LAI and its controlling factors were analysed using geostatistical methods and the generalised additive models (GAMs) respectively. Our results showed that LAI values differed greatly in the three forests and their seasonal variations were consistent with plant phenology. LAI values exhibited strong spatial autocorrelation for the three forests measured in January and for the L. glaber–C. glauca forest in April, July, and October. Obvious patch distribution pattern of LAI values occurred in three forests during the non-growing period and this pattern gradually dwindled in the growing season. Stem number, crown coverage, proportion of evergreen conifer species on basal area basis, proportion of deciduous species on basal area basis, and forest types affected the spatial variations in LAI values in January, while stem number and proportion of deciduous species on basal area basis affected the spatial variations in LAI values in July. Floristic composition, spatial heterogeneity, and seasonal variations should be considered for sampling strategy in indirect LAI measurement and application of LAI to simulate functional processes in subtropical forests.

Dynamic allocation and transfer of non-structural carbohydrates, a possible mechanism for the explosive growth of Moso bamboo (Phyllostachys heterocycla) - Song, Xinzhang; Peng, Changhui; Zhou, Guomo; Gu, Honghao; Li, Quan; Zhang, Chao (Scientific Reports, 2016)
Abstract Moso bamboo can rapidly complete its growth in both height and diameter within only 35–40 days after shoot emergence. However, the underlying mechanism for this “explosive growth” remains poorly understood. We investigated the dynamics of non-structural carbohydrates (NSCs) in shoots and attached mature bamboos over a 20-month period. The results showed that Moso bamboos rapidly completed their height and diameter growth within 38 days. At the same time, attached mature bamboos transferred almost all the NSCs of their leaves, branches and especially trunks and rhizomes to the “explosively growing” shoots via underground rhizomes for the structural growth and metabolism of shoots. Approximately 4 months after shoot emergence, this transfer stopped when the leaves of the young bamboos could independently provide enough photoassimilates to meet the carbon demands of the young bamboos. During this period, the NSC content of the leaves, branches, trunks and rhizomes of mature bamboos declined by 1.5, 23, 28 and 5 fold, respectively. The trunk contributed the most NSCs to the shoots. Our findings provide new insight and a possible rational mechanism explaining the “explosive growth” of Moso bamboo and shed new light on understanding the role of NSCs in the rapid growth of Moso bamboo.

Interannual variation in methane emissions from tropical wetlands triggered by repeated El Niño Southern Oscillation - Zhu, Qiuan; Peng, Changhui; Ciais, Philippe; Jiang, Hong; Liu, Jinxun; Bousquet, Philippe; Li, Shiqin; Chang, Jie; Fang, Xiuqin; Zhou, Xiaolu; Chen, Huai; Liu, Shirong; et al. (Global Change Biology, 2017)
Abstract Methane (CH 4 ) emissions from tropical wetlands contribute 60%–80% of global natural wetland CH 4 emissions. Decreased wetland CH 4 emissions can act as a negative feedback mechanism for future climate warming and vice versa. The impact of the El Niño–Southern Oscillation (ENSO) on CH 4 emissions from wetlands remains poorly quantified at both regional and global scales, and El Niño events are expected to become more severe based on climate models’ projections. We use a process‐based model of global wetland CH 4 emissions to investigate the impacts of the ENSO on CH 4 emissions in tropical wetlands for the period from 1950 to 2012. The results show that CH 4 emissions from tropical wetlands respond strongly to repeated ENSO events, with negative anomalies occurring during El Niño periods and with positive anomalies occurring during La Niña periods. An approximately 8‐month time lag was detected between tropical wetland CH 4 emissions and ENSO events, which was caused by the combined time lag effects of ENSO events on precipitation and temperature over tropical wetlands. The ENSO can explain 49% of interannual variations for tropical wetland CH 4 emissions. Furthermore, relative to neutral years, changes in temperature have much stronger effects on tropical wetland CH 4 emissions than the changes in precipitation during ENSO periods. The occurrence of several El Niño events contributed to a lower decadal mean growth rate in atmospheric CH 4 concentrations throughout the 1980s and 1990s and to stable atmospheric CH 4 concentrations from 1999 to 2006, resulting in negative feedback to global warming.

Modeling Global Soil Carbon and Soil Microbial Carbon by Integrating Microbial Processes into the Ecosystem Process Model TRIPLEX‐GHG - Wang, Kefeng; Peng, Changhui; Zhu, Qiuan; Zhou, Xiaolu; Wang, Meng; Zhang, Kerou; Wang, Gangsheng (Journal of Advances in Modeling Earth Systems, 2017)
Abstract Microbial physiology plays a critical role in the biogeochemical cycles of the Earth system. However, most traditional soil carbon models are lacking in terms of the representation of key microbial processes that control the soil carbon response to global climate change. In this study, the improved process‐based model TRIPLEX‐GHG was developed by coupling it with the new MEND (Microbial‐ENzyme‐mediated Decomposition) model to estimate total global soil organic carbon (SOC) and global soil microbial carbon. The new model (TRIPLEX‐MICROBE) shows considerable improvement over the previous version (TRIPLEX‐GHG) in simulating SOC. We estimated the global soil carbon stock to be approximately 1195 Pg C, with 348 Pg C located in the high northern latitudes, which is in good agreement with the well‐regarded Harmonized World Soil Database (HWSD) and the Northern Circumpolar Soil Carbon Database (NCSCD). We also estimated the global soil microbial carbon to be 21 Pg C, similar to the 23 Pg C estimated by Xu et al. (2014). We found that the microbial carbon quantity in the latitudinal direction showed reversions at approximately 30°N, near the equator and at 25°S. A sensitivity analysis suggested that the tundra ecosystem exhibited the highest sensitivity to a 1°C increase or decrease in temperature in terms of dissolved organic carbon (DOC), microbial biomass carbon (MBC), and mineral‐associated organic carbon (MOC). However, our work represents the first step toward a new generation of ecosystem process models capable of integrating key microbial processes into soil carbon cycles. , Key Points Traditional soil carbon models are lacking in their representation of key microbial processes that control the soil carbon response to global climate change A Ecosystem model (TRIPLEX‐MICROBE) offers considerable improvement over a previous version (TRIPLEX‐GHG) in simulating soil organic carbon Our work is the first step toward a new generation of ecosystem process models that integrate key microbial processes into soil carbon cycles

Past and future carbon sequestration benefits of China’s grain for green program - Deng, Lei; Liu, Shuguang; Kim, Dong Gill; Peng, Changhui; Sweeney, Sandra; Shangguan, Zhouping (Global Environmental Change, 2017)

Spatial variations in soil organic carbon, nitrogen and phosphorus concentrations related to stand characteristics in subtropical areas - Jiang, Fang; Wu, Xiaohong; Xiang, Wenhua; Fang, Xi; Zeng, Yeling; Ouyang, Shuai; Lei, Pifeng; Deng, Xiangwen; Peng, Changhui (Plant and Soil, 2017)

Spatial patterns of leaf δ13 C and its relationship with plant functional groups and environmental factors in China: Factors Dominate Plant Traits - Li, Mingxu; Peng, Changhui; Wang, Meng; Yang, Yanzheng; Zhang, Kerou; Li, Peng; Yang, Yan; Ni, Jian; Zhu, Qiuan (Journal of Geophysical Research: Biogeosciences, 2017)

Model prediction of biome‐specific global soil respiration from 1960 to 2012 - Zhao, Zhengyong; Peng, Changhui; Yang, Qi; Meng, Fan‐Rui; Song, Xinzhang; Chen, Shutao; Epule, Terence Epule; Li, Peng; Zhu, Qiuan (Earth's Future, 2017)
Abstract Biome‐specific soil respiration (Rs) has important yet different roles in both the carbon cycle and climate change from regional to global scales. To date, no comparable studies related to global biome‐specific Rs have been conducted applying comprehensive global Rs databases. The goal of this study was to develop artificial neural network ( ANN ) models capable of spatially estimating global Rs and to evaluate the effects of interannual climate variations on 10 major biomes. We used 1976 annual Rs field records extracted from global Rs literature to train and test the ANN models. We determined that the best ANN model for predicting biome‐specific global annual Rs was the one that applied mean annual temperature ( MAT ), mean annual precipitation ( MAP ), and biome type as inputs ( r 2 = 0.60). The ANN models reported an average global Rs of 93.3 ± 6.1 Pg C yr −1 from 1960 to 2012 and an increasing trend in average global annual Rs of 0.04 Pg C yr −1 . Estimated annual Rs increased with increases in MAT and MAP in cropland, boreal forest, grassland, shrubland, and wetland biomes. Additionally, estimated annual Rs decreased with increases in MAT and increased with increases in MAP in desert and tundra biomes, and only significantly decreased with increases in MAT ( r 2 = 0.87) in the savannah biome. The developed biome‐specific global Rs database for global land and soil carbon models will aid in understanding the mechanisms underlying variations in soil carbon dynamics and in quantifying uncertainty in the global soil carbon cycle. , Key Points Predict biome‐specific global soil respiration from 1960 to 2012 using an artificial neural network model Prediction determined an average global soil respiration of 93.3 ± 6.1 Pg C yr −1 and an increasing trend of 0.04 Pg C yr −1 The 10 biome‐specific soil respiration estimates made it possible to trace different responses to global climate change in each biome

The carbon flux of global rivers: A re-evaluation of amount and spatial patterns - Li, Mingxu; Peng, Changhui; Wang, Meng; Xue, Wei; Zhang, Kerou; Wang, Kefeng; Shi, Guohua; Zhu, Qiuan (Ecological Indicators, 2017)

Observed high and persistent carbon uptake by Moso bamboo forests and its response to environmental drivers - Song, Xinzhang; Chen, Xiaofeng; Zhou, Guomo; Jiang, Hong; Peng, Changhui (Agricultural and Forest Meteorology, 2017)

Global wetland contribution to 2000–2012 atmospheric methane growth rate dynamics - Poulter, Benjamin; Bousquet, Philippe; Canadell, Josep G; Ciais, Philippe; Peregon, Anna; Saunois, Marielle; Arora, Vivek K; Beerling, David J; Brovkin, Victor; Jones, Chris D; Joos, Fortunat; Gedney, Nicola; et al. (Environmental Research Letters, 2017)
Abstract Increasing atmospheric methane (CH 4 ) concentrations have contributed to approximately 20% of anthropogenic climate change. Despite the importance of CH 4 as a greenhouse gas, its atmospheric growth rate and dynamics over the past two decades, which include a stabilization period (1999–2006), followed by renewed growth starting in 2007, remain poorly understood. We provide an updated estimate of CH 4 emissions from wetlands, the largest natural global CH 4 source, for 2000–2012 using an ensemble of biogeochemical models constrained with remote sensing surface inundation and inventory-based wetland area data. Between 2000–2012, boreal wetland CH 4 emissions increased by 1.2 Tg yr −1 (−0.2–3.5 Tg yr −1 ), tropical emissions decreased by 0.9 Tg yr −1 (−3.2−1.1 Tg yr −1 ), yet globally, emissions remained unchanged at 184 ± 22 Tg yr −1 . Changing air temperature was responsible for increasing high-latitude emissions whereas declines in low-latitude wetland area decreased tropical emissions; both dynamics are consistent with features of predicted centennial-scale climate change impacts on wetland CH 4 emissions. Despite uncertainties in wetland area mapping, our study shows that global wetland CH 4 emissions have not contributed significantly to the period of renewed atmospheric CH 4 growth, and is consistent with findings from studies that indicate some combination of increasing fossil fuel and agriculture-related CH 4 emissions, and a decrease in the atmospheric oxidative sink.

The NEBIE plot network: Highlights of long-term scientific studies - Bell, F. Wayne; Dacosta, Jennifer; Newmaster, Steven G.; Mallik, Azim; Hunt, Shelley; Anand, Madhur; Maloles, Jose; Peng, Changhui; Parton, John; McLaughlin, John; Winters, John; Wester, Monique; et al. (The Forestry Chronicle, 2017)
The NEBIE plot network is a stand-scale, multi-agency research project designed to compare the ecological effects of a range of silvicultural treatments in northern temperate and boreal forest regions of Ontario, Canada. While research on silviculture intensities has been previously conducted, the NEBIE plot network is at a larger scale, and covers a wider range of intensities in a variety of northern temperate and boreal forest types. Details about experimental design, treatment designs and research sites, are presented in a companion paper which is published in this edition of The Forestry Chronicle. The operational scale of treatment plots allow for assessment of a variety of forest values. We used a criteria and indicator approach to organize long-term research studies on the network sites, with the goal of providing scientific findings that would inform forest policy. Pre-treatment, and 2-, 5-, and 10-year post-harvesting data have been collected. These initial data add to existing information on the effects of intensification of silviculture on biological diversity, forest productivity, ecosystem health and vitality, soil and water resources, contribution of enhanced forest management global carbon cycles, and long-term multiple socio-economic benefits of northern forests.

Higher temperature variability reduces temperature sensitivity of vegetation growth in Northern Hemisphere - Wu, Xiuchen; Liu, Hongyan; Li, Xiaoyan; Piao, Shilong; Ciais, Philippe; Guo, Weichao; Yin, Yi; Poulter, Ben; Peng, Changhui; Viovy, Nicolas; Vuichard, Nicolas; Wang, Pei; et al. (Geophysical Research Letters, 2017)
Abstract Interannual air temperature variability has changed over some regions in Northern Hemisphere (NH), accompanying with climate warming. However, whether and to what extent it regulates the interannual sensitivity of vegetation growth to temperature variability (i.e., interannual temperature sensitivity)—one central issue in understanding and predicting the responses of vegetation growth to changing climate—still remains poorly quantified and understood. Here we quantify the relationships between the interannual temperature sensitivity of mean growing‐season (April–October) normalized difference vegetation index (NDVI) and ecosystem model simulations of gross primary productivity (GPP), and variability in mean growing‐season temperature for forest, shrub, and grass over NH. We find that higher interannual variability in mean growing‐season temperature leads to consistent decrease in interannual temperature sensitivity of mean growing‐season NDVI among all vegetation types but not in model simulations of GPP. Drier condition associates with ~130 ± 150% further decrease in interannual temperature sensitivity of mean growing‐season NDVI by temperature variability in forest and shrub. These results illustrate that varying temperature variability can significantly regulate the interannual temperature sensitivity of vegetation growth over NH, interacted with drought variability and nonlinear responses of photosynthesis to temperature. Our findings call for an improved characterization of the nonlinear effects of temperature variability on vegetation growth within global ecosystem models. , Key Points It shows consistent decrease in temperature sensitivity of vegetation growth by temperature variability for all vegetation types Larger decrease in temperature sensitivity of vegetation growth by temperature variability is found in forest and shrub in dry regions Drier condition adds further decrease in temperature sensitivity of vegetation growth by temperature variability for forest and shrub in dry regions

Effects of canopy gaps on N 2 O fluxes in a tropical montane rainforest in Hainan of China - Yang, Huai; Detto, Matteo; Liu, Shirong; Yuan, Wenping; Hsieh, Cheng-I; Wang, Xu; Chen, Renli; Chen, Huai; Peng, Changhui; Jiang, Xinhua; Li, Yide; Xu, Han; et al. (Ecological Engineering, 2017)

Quantification of methane emissions from municipal solid waste landfills in China during the past decade - Du, Mingxi; Peng, Changhui; Wang, Xiaoge; Chen, Huai; Wang, Meng; Zhu, Qiuan (Renewable and Sustainable Energy Reviews, 2017)

Effects of nitrogen deposition and management practices on leaf litterfall and N and P return in a Moso bamboo forest - Zhang, Junbo; Lv, Jianhua; Li, Quan; Ying, Yeqing; Peng, Changhui; Song, Xinzhang (Biogeochemistry, 2017)

Effects of three global change drivers on terrestrial C:N:P stoichiometry: a global synthesis - Yue, Kai; Fornara, Dario A.; Yang, Wanqin; Peng, Yan; Li, Zhijie; Wu, Fuzhong; Peng, Changhui (Global Change Biology, 2017)
Abstract Over the last few decades, there has been an increasing number of controlled‐manipulative experiments to investigate how plants and soils might respond to global change. These experiments typically examined the effects of each of three global change drivers [i.e., nitrogen (N) deposition, warming, and elevated CO 2 ] on primary productivity and on the biogeochemistry of carbon (C), N, and phosphorus (P) across different terrestrial ecosystems. Here, we capitalize on this large amount of information by performing a comprehensive meta‐analysis (>2000 case studies worldwide) to address how C:N:P stoichiometry of plants, soils, and soil microbial biomass might respond to individual vs. combined effects of the three global change drivers. Our results show that (i) individual effects of N addition and elevated CO 2 on C:N:P stoichiometry are stronger than warming, (ii) combined effects of pairs of global change drivers (e.g., N addition + elevated CO 2 , warming + elevated CO 2 ) on C:N:P stoichiometry were generally weaker than the individual effects of each of these drivers, (iii) additive interactions (i.e., when combined effects are equal to or not significantly different from the sum of individual effects) were more common than synergistic or antagonistic interactions, (iv) C:N:P stoichiometry of soil and soil microbial biomass shows high homeostasis under global change manipulations, and (v) C:N:P responses to global change are strongly affected by ecosystem type, local climate, and experimental conditions. Our study is one of the first to compare individual vs. combined effects of the three global change drivers on terrestrial C:N:P ratios using a large set of data. To further improve our understanding of how ecosystems might respond to future global change, long‐term ecosystem‐scale studies testing multifactor effects on plants and soils are urgently required across different world regions.

Stoichiometric and nutrient resorption characteristics of dominant tree species in subtropical Chinese forests - Zeng, Yelin; Fang, Xi; Xiang, Wenhua; Deng, Xiangwen; Peng, Changhui (Ecology and Evolution, 2017)
Abstract This study investigated seasonal patterns in stoichiometric ratios, nutrient resorption characteristics, and nutrient use strategies of dominant tree species at three successional stages in subtropical China, which have not been fully understood. Fresh leaf and leaf litterfall samples were collected in growing and nongrowing seasons for determining the concentrations of carbon (C), nitrogen (N), and phosphorus (P). Then, stoichiometric ratios (i.e., C:N, C:P, N:P, and C:N:P) and resorption parameters were calculated. Our results found that there was no consistent variation in leaf C:N and C:P ratios among different species. However, leaf N:P ratios in late‐successional species became significantly higher, indicating that P limitation increases during successional development. Due to the P limitation in this study area, P resorption efficiency and proficiency were higher than corresponding N resorption parameters. Dominant tree species at early‐successional stage adopted “conservative consumption” nutrient use strategy, whereas the species at late‐successional stage inclined to adopt “resource spending” strategy.

Towards a universal model for carbon dioxide uptake by plants - Wang, Han; Prentice, I. Colin; Keenan, Trevor F.; Davis, Tyler W.; Wright, Ian J.; Cornwell, William K.; Evans, Bradley J.; Peng, Changhui (Nature Plants, 2017)

Photosynthetic responses to altitude: an explanation based on optimality principles - Wang, Han; Prentice, I. Colin; Davis, Tyler W.; Keenan, Trevor F.; Wright, Ian J.; Peng, Changhui (New Phytologist, 2017)

Soil CH4 and CO2 dynamics and nitrogen transformations with incubation in mountain forest and meadow ecosystems - Zhang, Junjun; Peng, Changhui; Xue, Wei; Yang, Zhenan; Yang, Bin; Li, Peng; Zhu, Qiuan; Wang, Meng (CATENA, 2018)

Modeling Gross Primary Production of a Typical Coastal Wetland in China Using MODIS Time Series and CO2 Eddy Flux Tower Data - Kang, Xiaoming; Yan, Liang; Zhang, Xiaodong; Li, Yong; Tian, Dashuan; Peng, Changhui; Wu, Haidong; Wang, Jinzhi; Zhong, Lei (Remote Sensing, 2018)
How to effectively combine remote sensing data with the eddy covariance (EC) technique to accurately quantify gross primary production (GPP) in coastal wetlands has been a challenge and is also important and necessary for carbon (C) budgets assessment and climate change studies at larger scales. In this study, a satellite-based Vegetation Photosynthesis Model (VPM) combined with EC measurement and Moderate Resolution Imaging Spectroradiometer (MODIS) data was used to evaluate the phenological characteristics and the biophysical performance of MODIS-based vegetation indices (VIs) and the feasibility of the model for simulating GPP of coastal wetland ecosystems. The results showed that greenness-related and water-related VIs can better identify the green-up and the senescence phases of coastal wetland vegetation, corresponds well with the C uptake period and the phenological patterns that were delineated by GPP from EC tower (GPPEC). Temperature can explain most of the seasonal variation in VIs and GPPEC fluxes. Both enhanced vegetation index (EVI) and water-sensitive land surface water index (LSWI) have a higher predictive power for simulating GPP in this coastal wetland. The comparisons between modeled GPP (GPPVPM) and GPPEC indicated that VPM model can commendably simulate the trajectories of the seasonal dynamics of GPPEC fluxes in terms of patterns and magnitudes, explaining about 85% of GPPEC changes over the study years (p < 0.0001). The results also demonstrate the potential of satellite-driven VPM model for modeling C uptake at large spatial and temporal scales in coastal wetlands, which can provide valuable production data for the assessment of global wetland C sink/source.

Biochar mitigates dissolved organic carbon loss but does not affect dissolved organic nitrogen leaching loss caused by nitrogen deposition in Moso bamboo plantations - Lei, Zhaofeng; Li, Quan; Song, Xinzhang; Wang, Weifeng; Zhang, Zhiting; Peng, Changhui; Tian, Linlin (Global Ecology and Conservation, 2018)

Allocation Mechanisms of Non-Structural Carbohydrates of Robinia pseudoacacia L. Seedlings in Response to Drought and Waterlogging - Yang, Bin; Peng, Changhui; Harrison, Sandy P.; Wei, Hua; Wang, Han; Zhu, Qiuan; Wang, Meng (Forests, 2018)
Climate change is likely to lead to an increased frequency of droughts and floods, both of which are implicated in large-scale carbon allocation and tree mortality worldwide. Non-structural carbohydrates (NSCs) play an important role in tree survival under stress, but how NSC allocation changes in response to drought or waterlogging is still unclear. We measured soluble sugars (SS) and starch in leaves, twigs, stems and roots of Robinia pseudoacacia L. seedlings that had been subjected to a gradient in soil water availability from extreme drought to waterlogged conditions for a period of 30 days. Starch concentrations decreased and SS concentrations increased in tissues of R. pseudoacacia seedlings, such that the ratio of SS to starch showed a progressive increase under both drought and waterlogging stress. The strength of the response is asymmetric, with the largest increase occurring under extreme drought. While the increase in SS concentration in response to extreme drought is the largest in roots, the increase in the ratio of SS to starch is the largest in leaves. Individual components of SS showed different responses to drought and waterlogging across tissues: glucose concentrations increased significantly with drought in all tissues but showed little response to waterlogging in twigs and stems; sucrose and fructose concentrations showed marked increases in leaves and roots in response to drought but a greater response to drought and waterlogging in stems and twigs. These changes are broadly compatible with the roles of individual SS under conditions of water stress. While it is important to consider the role of NSC in buffering trees against mortality under stress, modelling this behaviour is unlikely to be successful unless it accounts for different responses within organs and the type of stress involved.

Hydrologic and Edaphic Controls on Soil Carbon Emission in Dongting Lake Floodplain, China - Deng, Zhengmiao; Li, Youzhi; Xie, Yonghong; Peng, Changhui; Chen, Xinsheng; Li, Feng; Ren, Yijie; Pan, Baihan; Zhang, Chengyi (Journal of Geophysical Research: Biogeosciences, 2018)
Abstract Wetlands play a critical role in mitigating carbon emission. However, little is known about soil carbon emission and their environmental controls from inland floodplain wetlands. This study aimed to determine the effects of hydrologic and edaphic controllers (water table depth [ WTD ], soil temperature [ Ts ], and soil water content [ SWC ]) on soil C emission in Dongting Lake wetland, China. One‐year emissions were measured in Carex meadow and mudflat using static chambers during 2013 to 2014, including nonflooded season ( NFs ) and flooded season ( Fs ). The results showed that soil C emission in the Carex meadow and mudflat was 307.8 and 264.3 g C·m −2 ·year −1 , respectively, and 50–66% of soil C were emitted during NFs. Compared with NFs, CO 2 emission was significantly decreased by 57% but CH 4 emission was significantly increased by 38 times during Fs in the Carex meadow. Stepwise regression combined with structural equation model analysis showed that CO 2 and CH 4 flux were mainly influenced by Ts during NFs, and they were controlled by water temperature ( Tw ) during Fs. During NFs, CO 2 flux increased with increasing Ts and SWC but decreased significantly when SWC was over 66% and 52% in the Carex meadow and mudflat, respectively. CH 4 flux showed an emission pulse at SWC and Ts of 65% and 17.2 °C, respectively. These results indicate that flooding significantly inhibited soil CO 2 emission but stimulated CH 4 emission. The continuous decrease of flooding days caused by anthropogenic disturbances may induce soil C loss in Dongting Lake wetlands. , Key Points Soil C emission in Dongting Lake floodplain was 264.3–307.8 g C.m ‐2 .year ‐1 Flooding significantly inhibited soil CO 2 emission but stimulated CH 4 emission The decline of flooding days in Dongting Lake wetlands can potentially increase soil C loss

Data supporting assessment for nitrous oxide emissions from soils under traditional cropland and apple orchard in the Loess Plateau of China - Pang, Junzhu; Wang, Xiaoke; Peng, Changhui; Mu, Yujing; Ouyang, Zhiyun; Lu, Fei; Zhang, Hongxing; Zhang, Shuoxin; Liu, Wenzhao (Data in Brief, 2018)

CH4 concentrations and fluxes in a subtropical metropolitan river network: Watershed urbanization impacts and environmental controls - Wang, Xiaofeng; He, Yixin; Chen, Huai; Yuan, Xingzhong; Peng, Changhui; Yue, Junsheng; Zhang, Qiaoyong; Zhou, Lilei (Science of The Total Environment, 2018)

A global strategy to mitigate the environmental impact of China’s ruminant consumption boom - Du, Yuanyuan; Ge, Ying; Ren, Yuan; Fan, Xing; Pan, Kaixuan; Lin, Linshan; Wu, Xu; Min, Yong; Meyerson, Laura A.; Heino, Mikko; Chang, Scott X.; Liu, Xiaozi; et al. (Nature Communications, 2018)
Abstract Rising demand for ruminant meat and dairy products in developing countries is expected to double anthropogenic greenhouse gas and ammonia emissions from livestock by 2050. Mitigation strategies are urgently needed to meet demand while minimizing environmental impacts. Here, we develop scenarios for mitigating emissions under local vs global supply policies using data from 308 livestock farms across mainland China, where emissions intensities are ~50% higher than those in developed nations. Intensification of domestic production and globalized expansion through increased trade result in reductions in global emissions by nearly 30% over a business-as-usual scenario, but at the expense of trading partners absorbing the associated negative externalities of environmental degradation. Only adoption of a mixed strategy combining global best-practice in sustainable intensification of domestic production, with increased green-source trading as a short-term coping strategy, can meet 2050 demand while minimizing the local and global environmental footprint of China’s ruminant consumption boom.

Contrasting Soil Bacterial Community, Diversity, and Function in Two Forests in China - Wei, Hua; Peng, Changhui; Yang, Bin; Song, Hanxiong; Li, Quan; Jiang, Lin; Wei, Gang; Wang, Kefeng; Wang, Hui; Liu, Shirong; Liu, Xiaojing; Chen, Dexiang; et al. (Frontiers in Microbiology, 2018)

Development of a New TRIPLEX-Insect Model for Simulating the Effect of Spruce Budworm on Forest Carbon Dynamics - Liu, Zelin; Peng, Changhui; De Grandpré, Louis; Candau, Jean-Noël; Zhou, Xiaolu; Kneeshaw, Daniel (Forests, 2018)
The spruce budworm (SBW) defoliates and kills conifer trees, consequently affecting carbon (C) exchanges between the land and atmosphere. Here, we developed a new TRIPLEX-Insect sub-model to quantify the impacts of insect outbreaks on forest C fluxes. We modeled annual defoliation (AD), cumulative defoliation (CD), and tree mortality. The model was validated against observed and published data at the stand level in the North Shore region of Québec and Cape Breton Island in Nova Scotia, Canada. The results suggest that TRIPLEX-Insect performs very well in capturing tree mortality following SBW outbreaks and slightly underestimates current annual volume increment (CAI). In both mature and immature forests, the simulation model suggests a larger reduction in gross primary productivity (GPP) than in autotrophic respiration (Ra) at the same defoliation level when tree mortality was low. After an SBW outbreak, the growth release of surviving trees contributes to the recovery of annual net ecosystem productivity (NEP) based on forest age if mortality is not excessive. Overall, the TRIPLEX-Insect model is capable of simulating C dynamics of balsam fir following SBW disturbances and can be used as an efficient tool in forest insect management.

Application of machine-learning methods in forest ecology: recent progress and future challenges - Liu, Zelin; Peng, Changhui; Work, Timothy; Candau, Jean-Noel; DesRochers, Annie; Kneeshaw, Daniel (Environmental Reviews, 2018)
Machine learning, an important branch of artificial intelligence, is increasingly being applied in sciences such as forest ecology. Here, we review and discuss three commonly used methods of machine learning (ML) including decision-tree learning, artificial neural network, and support vector machine and their applications in four different aspects of forest ecology over the last decade. These applications include: (i) species distribution models, (ii) carbon cycles, (iii) hazard assessment and prediction, and (iv) other applications in forest management. Although ML approaches are useful for classification, modeling, and prediction in forest ecology research, further expansion of ML technologies is limited by the lack of suitable data and the relatively “higher threshold” of applications. However, the combined use of multiple algorithms and improved communication and cooperation between ecological researchers and ML developers still present major challenges and tasks for the betterment of future ecological research. We suggest that future applications of ML in ecology will become an increasingly attractive tool for ecologists in the face of “big data” and that ecologists will gain access to more types of data such as sound and video in the near future, possibly opening new avenues of research in forest ecology.

Biochar amendment decreases soil microbial biomass and increases bacterial diversity in Moso bamboo ( Phyllostachys edulis ) plantations under simulated nitrogen deposition - Li, Quan; Lei, Zhaofeng; Song, Xinzhang; Zhang, Zhiting; Ying, Yeqing; Peng, Changhui (Environmental Research Letters, 2018)

The Global N2O Model Intercomparison Project - Tian, Hanqin; Yang, Jia; Lu, Chaoqun; Xu, Rongting; Canadell, Josep G.; Jackson, Robert B.; Arneth, Almut; Chang, Jinfeng; Chen, Guangsheng; Ciais, Philippe; Gerber, Stefan; Ito, Akihiko; et al. (Bulletin of the American Meteorological Society, 2018)
Abstract Nitrous oxide (N 2 O) is an important greenhouse gas and also an ozone-depleting substance that has both natural and anthropogenic sources. Large estimation uncertainty remains on the magnitude and spatiotemporal patterns of N 2 O fluxes and the key drivers of N 2 O production in the terrestrial biosphere. Some terrestrial biosphere models have been evolved to account for nitrogen processes and to show the capability to simulate N 2 O emissions from land ecosystems at the global scale, but large discrepancies exist among their estimates primarily because of inconsistent input datasets, simulation protocol, and model structure and parameterization schemes. Based on the consistent model input data and simulation protocol, the global N 2 O Model Intercomparison Project (NMIP) was initialized with 10 state-of-the-art terrestrial biosphere models that include nitrogen (N) cycling. Specific objectives of NMIP are to 1) unravel the major N cycling processes controlling N 2 O fluxes in each model and identify the uncertainty sources from model structure, input data, and parameters; 2) quantify the magnitude and spatial and temporal patterns of global and regional N 2 O fluxes from the preindustrial period (1860) to present and attribute the relative contributions of multiple environmental factors to N 2 O dynamics; and 3) provide a benchmarking estimate of N 2 O fluxes through synthesizing the multimodel simulation results and existing estimates from ground-based observations, inventories, and statistical and empirical extrapolations. This study provides detailed descriptions for the NMIP protocol, input data, model structure, and key parameters, along with preliminary simulation results. The global and regional N 2 O estimation derived from the NMIP is a key component of the global N 2 O budget synthesis activity jointly led by the Global Carbon Project and the International Nitrogen Initiative.

Controls of soil and aggregate‐associated organic carbon variations following natural vegetation restoration on the L oess P lateau in C hina - Deng, Lei; Kim, Dong‐Gill; Peng, Changhui; Shangguan, Zhouping (Land Degradation & Development, 2018)
Abstract Natural vegetation restoration can enhance soil organic carbon (SOC) sequestration, but the mechanisms and control factors underlying SOC sequestration are still unknown. The objectives of the study are to quantify the temporal variation of soil and aggregate‐associated organic carbon (OC) and identify factors controlling the variation following natural vegetation restoration after farmland abandonment. We collected soils from sites having 5, 30, 60, 100, and 160 years of a natural vegetation restoration chronosequence after farmland abandonment in the Loess Plateau, China. The results showed that natural vegetation restoration increased macroaggregates (0.25–2 mm; 46.6% to 73.9%), SOC (2.27 to 9.81 g kg −1 ), and aggregate OC (7.33 to 36.98 g kg −1 ) in the top 20‐cm soil compared with abandoned farmland, and the increases mainly occurred in the early stage (<60 years). The increase of SOC was contributed by OC accumulated in macroaggregates (0.25–2 mm) rather than microaggregates (≤0.25 mm). Moreover, SOC sequestration in the topsoil (0–10 cm) was mainly determined by fine root biomass (FR), labile organic carbon (LOC), and microbial biomass carbon (MBC). And in the subsoil (10–20 cm), SOC sequestration was mainly determined by the proportion of macroaggregates. The results suggest that natural vegetation restoration increased SOC and aggregate OC, and FR, MBC, LOC, and the physical protection of aggregates played important roles in regulating SOC and aggregate OC.

Asymmetric responses of primary productivity to altered precipitation simulated by ecosystem models across three long-term grassland sites - Wu, Donghai; Ciais, Philippe; Viovy, Nicolas; Knapp, Alan K.; Wilcox, Kevin; Bahn, Michael; Smith, Melinda D.; Vicca, Sara; Fatichi, Simone; Zscheischler, Jakob; He, Yue; Li, Xiangyi; et al. (Biogeosciences, 2018)
Abstract. Field measurements of aboveground net primary productivity (ANPP) in temperate grasslands suggest that both positive and negative asymmetric responses to changes in precipitation (P) may occur. Under normal range of precipitation variability, wet years typically result in ANPP gains being larger than ANPP declines in dry years (positive asymmetry), whereas increases in ANPP are lower in magnitude in extreme wet years compared to reductions during extreme drought (negative asymmetry). Whether the current generation of ecosystem models with a coupled carbon–water system in grasslands are capable of simulating these asymmetric ANPP responses is an unresolved question. In this study, we evaluated the simulated responses of temperate grassland primary productivity to scenarios of altered precipitation with 14 ecosystem models at three sites: Shortgrass steppe (SGS), Konza Prairie (KNZ) and Stubai Valley meadow (STU), spanning a rainfall gradient from dry to moist. We found that (1) the spatial slopes derived from modeled primary productivity and precipitation across sites were steeper than the temporal slopes obtained from inter-annual variations, which was consistent with empirical data; (2) the asymmetry of the responses of modeled primary productivity under normal inter-annual precipitation variability differed among models, and the mean of the model ensemble suggested a negative asymmetry across the three sites, which was contrary to empirical evidence based on filed observations; (3) the mean sensitivity of modeled productivity to rainfall suggested greater negative response with reduced precipitation than positive response to an increased precipitation under extreme conditions at the three sites; and (4) gross primary productivity (GPP), net primary productivity (NPP), aboveground NPP (ANPP) and belowground NPP (BNPP) all showed concave-down nonlinear responses to altered precipitation in all the models, but with different curvatures and mean values. Our results indicated that most models overestimate the negative drought effects and/or underestimate the positive effects of increased precipitation on primary productivity under normal climate conditions, highlighting the need for improving eco-hydrological processes in those models in the future.

Estimates and Predictions of Methane Emissions from Wastewater in China from 2000 to 2020 - Du, Mingxi; Zhu, Qiuan; Wang, Xiaoge; Li, Peng; Yang, Bin; Chen, Huai; Wang, Meng; Zhou, Xiaolu; Peng, Changhui (Earth's Future, 2018)
Methane accounts for 20% of the global warming caused by greenhouse gases, and wastewater is a major anthropogenic source of methane. Based on the Intergovernmental Panel on Climate Change greenhouse gas inventory guidelines and current research findings, we calculated the amount of methane emissions from 2000 to 2014 that originated from wastewater from different provinces in China. Methane emissions from wastewater increased from 1349.01 to 3430.03 Gg from 2000 to 2014, and the mean annual increase was 167.69 Gg. The methane emissions from industrial wastewater treated by wastewater treatment plants ( E It ) accounted for the highest proportion of emissions. We also estimated the future trend of industrial wastewater methane emissions using the artificial neural network model. A comparison of the emissions for the years 2020, 2010, and 2000 showed an increasing trend in methane emissions in China and a spatial transition of industrial wastewater emissions from eastern and southern regions to central and southwestern regions and from coastal regions to inland regions. These changes were caused by changes in economics, demographics, and relevant policies. , Key Points Methane emission from wastewater from 2000 to 2014 was calculated to increase from 1349.01 Gg to 3430.03 Gg. Methane emission from wastewater from 2015 to 2020 was estimated to increase from 3875.30 Gg to 5212.75 Gg. A spatial transition of methane emission from wastewater was found and discussed in the present study.

The response of the net primary production of Moso bamboo forest to the On and Off-year management: A case study in Anji County, Zhejiang, China - Chen, Shulin; Jiang, Hong; Cai, Zhijian; Zhou, Xiaolu; Peng, Changhui (Forest Ecology and Management, 2018)

Effect of Drought on Agronomic Traits of Rice and Wheat: A Meta-Analysis - Zhang, Jinmeng; Zhang, Shiqiao; Cheng, Min; Jiang, Hong; Zhang, Xiuying; Peng, Changhui; Lu, Xuehe; Zhang, Minxia; Jin, Jiaxin (International Journal of Environmental Research and Public Health, 2018)
Drought has been one of the most important limiting factors for crop production, which deleteriously affects food security worldwide. The main objective of the present study was to quantitatively assess the effect of drought on the agronomic traits (e.g., plant height, biomass, yield, and yield components) of rice and wheat in combination with several moderators (e.g., drought stress intensity, rooting environment, and growth stage) using a meta-analysis study. The database was created from 55 published studies on rice and 60 published studies on wheat. The results demonstrated that drought decreased the agronomic traits differently between rice and wheat among varying growth stages. Wheat and rice yields decreased by 27.5% and 25.4%, respectively. Wheat grown in pots showed greater decreases in agronomic traits than those grown in the field. Rice showed opposite growing patterns when compared to wheat in rooting environments. The effect of drought on rice increased with plant growth and drought had larger detrimental influences during the reproductive phase (e.g., blooming stage, filling stage, and maturity). However, an exception was found in wheat, which had similar decreased performance during the complete growth cycle. Based on these results, future droughts could produce lower yields of rice and wheat when compared to the current drought.

Large-scale detection of vegetation dynamics and their potential drivers using MODIS images and BFAST: A case study in Quebec, Canada - Fang, Xiuqin; Zhu, Qiuan; Ren, Liliang; Chen, Huai; Wang, Kai; Peng, Changhui (Remote Sensing of Environment, 2018)

Multi-scale temporal variation of methane flux and its controls in a subtropical tidal salt marsh in eastern China - Li, Hong; Dai, Shengqi; Ouyang, Zutao; Xie, Xiao; Guo, Haiqiang; Gu, Caihong; Xiao, Xiangming; Ge, Zhenming; Peng, Changhui; Zhao, Bin (Biogeochemistry, 2018)

The linkage between vegetation and soil nutrients and their variation under different grazing intensities in an alpine meadow on the eastern Qinghai-Tibetan Plateau - Yang, Zhenan; Zhu, Qiuan; Zhan, Wei; Xu, Yingyi; Zhu, Erxiong; Gao, Yongheng; Li, Shiqing; Zheng, Qunying; Zhu, Dan; He, Yixin; Peng, Changhui; Chen, Huai (Ecological Engineering, 2018)

Individual and combined effects of multiple global change drivers on terrestrial phosphorus pools: A meta-analysis - Yue, Kai; Yang, Wanqin; Peng, Yan; Peng, Changhui; Tan, Bo; Xu, Zhenfeng; Zhang, Li; Ni, Xiangyin; Zhou, Wei; Wu, Fuzhong (Science of The Total Environment, 2018)

A critical analysis of the carbon neutrality assumption in life cycle assessment of forest bioenergy systems - Liu, Weiguo; Yu, Zhen; Xie, Xinfeng; Von Gadow, Klaus; Peng, Changhui (Environmental Reviews, 2018)
This study presents a critical analysis regarding the assumption of carbon neutrality in life cycle assessment (LCA) models that assess climate change impacts of bioenergy usage. We identified a complex of problems in the carbon neutrality assumption, especially regarding bioenergy derived from forest residues. In this study, we summarized several issues related to carbon neutral assumptions, with particular emphasis on possible carbon accounting errors at the product level. We analyzed errors in estimating emissions in the supply chain, direct and indirect emissions due to forest residue extraction, biogenic CO 2 emission from biomass combustion for energy, and other effects related to forest residue extraction. Various modeling approaches are discussed in detail. We concluded that there is a need to correct accounting errors when estimating climate change impacts and proposed possible remedies. To accurately assess climate change impacts of bioenergy use, greater efforts are required to improve forest carbon cycle modeling, especially to identify and correct pitfalls associated with LCA accounting, forest residue extraction effects on forest fire risk and biodiversity. Uncertainties in accounting carbon emissions in LCA are also highlighted, and associated risks are discussed.

Interactive Effect of Radioactive and Heavy-MetalContamination on Soil Enzyme Activityin a Former Uranium Mine - Yang, Gang; Dong, Faqin; Liu, Mingxue; Nie, Xiaoqin; Zong, Meirong; Peng, Changhui; Chen, Huai; Wei, Hongfu; Wang, Pingping; Zhang, Wei (Polish Journal of Environmental Studies, 2018)

Variation in Soil Methane Fluxes and Comparison between Two Forests in China - Wei, Hua; Peng, Changhui; Liu, Shirong; Liu, Xiaojing; Li, Peng; Song, Hanxiong; Yuan, Minshu; Wang, Meng (Forests, 2018)
Methane (CH4) is a vital greenhouse gas with a 28-fold higher global warming potential than carbon dioxide when considering a molar basis for the time horizon of 100 years. Here, we investigated the variation of soil CH4 fluxes, soil physiochemical properties, and CH4-related bacteria community composition of two forests in China. We measured CH4 fluxes using static chambers and analyzed soil bacterial communities using next-generation high-throughput sequencing in a temperate broad-leaved deciduous forest at Baotianman Nature Reserve (TBDF-BTM) and a tropical rainforest at Jianfengling National Natural Reserve (TRF-JFL). Our results showed that the soils from both sites were CH4 sinks. Significant variation in soil CH4 fluxes was found at TBDF-BTM exclusively, while no seasonal variation in the CH4 uptake was observed at TRF-JFL. The CH4 fluxes at TBDF-BTM were substantially higher than those at TRF-JFL during all seasons. One genus of methanotrophs and three genera of methylotrophs were detected at both sites, though they had no direct relationship with soil CH4 fluxes. Water-filled pore space and soil total carbon content are the main factors controlling the soil CH4 fluxes at TBDF-BTM. At TRF-JFL, the soil CH4 fluxes showed no significant correlations with any of the soil properties. This study improves our understanding of soil CH4 fluxes and their influencing factors in forests in different climatic zones and provides a reference for future investigation of forest soil CH4 fluxes, the forest ecosystem carbon cycle, and the forest CH4 model.

Recoupling Industrial Dairy Feedlots and Industrial Farmlands Mitigates the Environmental Impacts of Milk Production in China - Fan, Xing; Chang, Jie; Ren, Yuan; Wu, Xu; Du, Yuanyuan; Xu, Ronghua; Liu, Dong; Chang, Scott X.; Meyerson, Laura A.; Peng, Changhui; Ge, Ying (Environmental Science & Technology, 2018)

Positive responses of belowground C dynamics to nitrogen enrichment in China - Deng, Lei; Peng, Changhui; Zhu, Guangyu; Chen, Lei; Liu, Yulin; Shangguan, Zhouping (Science of The Total Environment, 2018)

Stand carbon density drivers and changes under future climate scenarios across global forests - Guo, Yanrong; Peng, Changhui; Trancoso, Ralph; Zhu, Qiuan; Zhou, Xiaolu (Forest Ecology and Management, 2019)

Simulation of dissolved organic carbon concentrations and fluxes in Chinese monsoon forest ecosystems using a modified TRIPLEX-DOC model - Shi, Shengwei; Yang, Mingxia; Hou, Yue; Peng, Changhui; Wu, Haibin; Zhu, Qiuan; Liang, Qiong; Xie, Junfei; Wang, Meng (Science of The Total Environment, 2019)

Re-estimating the changes and ranges of forest biomass carbon in China during the past 40 years - Zhou, Xiaolu; Lei, Xiangdong; Liu, Caixia; Huang, Huabing; Zhou, Carl; Peng, Changhui (Forest Ecosystems, 2019)
Abstract Background In recent decades the future of global forests has been a matter of increasing concern, particularly in relation to the threat of forest ecosystem responses under potential climate change. To the future predictions of these responses, the current forest biomass carbon storage (FCS) should first be clarified as much as possible, especially at national scales. However, few studies have introduced how to verify an FCS estimate by delimiting the reasonable ranges. This paper addresses an estimation of national FCS and its verification using two-step process to narrow the uncertainty. Our study focuses on a methodology for reducing the uncertainty resulted by converting from growing stock volume to above- and below-ground biomass (AB biomass), so as to eliminate the significant bias in national scale estimations. Methods We recommend splitting the estimation into two parts, one part for stem and the other part for AB biomass to preclude possible significant bias. Our method estimates the stem biomass from volume and wood density (WD), and converts the AB biomass from stem biomass by using allometric relationships. Results Based on the presented two-step process, the estimation of China’s FCS is performed as an example to explicate how to infer the ranges of national FCS. The experimental results demonstrate a national FCS estimation within the reasonable ranges (relative errors: + 4.46% and − 4.44%), e.g., 5.6–6.1 PgC for China’s forest ecosystem at the beginning of the 2010s. These ranges are less than 0.52 PgC for confirming each FCS estimate of different periods during the last 40 years. In addition, our results suggest the upper-limits by specifying a highly impractical value of WD (0.7 t∙m − 3 ) on the national scale. As a control reference, this value decides what estimate is impossible to achieve for the FCS estimates. Conclusions Presented methodological analysis highlights the possibility to determine a range that the true value could be located in. The two-step process will help to verify national FCS and also to reduce uncertainty in related studies. While the true value of national FCS is immeasurable, our work should motivate future studies that explore new estimations to approach the true value by narrowing the uncertainty in FCS estimations on national and global scales.

Comparison of methane emissions among invasive and native mangrove species in Dongzhaigang, Hainan Island - He, Yixin; Guan, Wei; Xue, Dan; Liu, Liangfeng; Peng, Changhui; Liao, Baowen; Hu, Ji; Zhu, Qiu'an; Yang, Yanzhen; Wang, Xu; Zhou, Guanyi; Wu, Zhongming; et al. (Science of The Total Environment, 2019)

Exposures to temperature beyond threshold disproportionately reduce vegetation growth in the northern hemisphere - Wu, Xiuchen; Guo, Weichao; Liu, Hongyan; Li, Xiaoyan; Peng, Changhui; Allen, Craig D; Zhang, Cicheng; Wang, Pei; Pei, Tingting; Ma, Yujun; Tian, Yuhong; Song, Zhaoliang; et al. (National Science Review, 2019)
Abstract In recent decades, terrestrial vegetation in the northern hemisphere (NH) has been exposed to warming and more extremely high temperatures. However, the consequences of these changes for terrestrial vegetation growth remain poorly quantified and understood. By examining a satellite-based vegetation index, tree-ring measurements and land-surface model simulations, we discovered a consistent convex pattern in the responses of vegetation growth to temperature exposure (TE) for forest, shrub and grass in both the temperate (30°−50° N) and boreal (50°−70° N) NH during the period of 1982−2012. The response of vegetation growth to TE for the three vegetation types in both the temperate and boreal NH increased convergently with increasing temperature, until vegetation type-dependent temperature thresholds were reached. A TE beyond these temperature thresholds resulted in disproportionately weak positive or even strong negative responses. Vegetation growth in the boreal NH was more vulnerable to extremely high-temperature events than vegetation growth in the temporal NH. The non-linear responses discovered here provide new insights into the dynamics of northern terrestrial ecosystems in a warmer world.

Carbon and Water Use Efficiencies: A Comparative Analysis of Ten Terrestrial Ecosystem Models under Changing Climate - El Masri, Bassil; Schwalm, Christopher; Huntzinger, Deborah N.; Mao, Jiafu; Shi, Xiaoying; Peng, Changhui; Fisher, Joshua B.; Jain, Atul K.; Tian, Hanqin; Poulter, Benjamin; Michalak, Anna M. (Scientific Reports, 2019)
Abstract Terrestrial ecosystems carbon and water cycles are tightly coupled through photosynthesis and evapotranspiration processes. The ratios of carbon stored to carbon uptake and water loss to carbon gain are key ecophysiological indicators essential to assess the magnitude and response of the terrestrial plant to the changing climate. Here, we use estimates from 10 terrestrial ecosystem models to quantify the impacts of climate, atmospheric CO 2 concentration, and nitrogen (N) deposition on water use efficiency (WUE), and carbon use efficiency (CUE). We find that across models, WUE increases over the 20 th Century particularly due to CO 2 fertilization and N deposition and compares favorably to experimental studies. Also, the results show a decrease in WUE with climate for the last 3 decades, in contrasts with up-scaled flux observations that demonstrate a constant WUE. Modeled WUE responds minimally to climate with modeled CUE exhibiting no clear trend across space and time. The divergence between simulated and observationally-constrained WUE and CUE is driven by modeled NPP and autotrophic respiration, nitrogen cycle, carbon allocation, and soil moisture dynamics in current ecosystem models. We suggest that carbon-modeling community needs to reexamine stomatal conductance schemes and the soil-vegetation interactions for more robust modeling of carbon and water cycles.

Field-experiment constraints on the enhancement of the terrestrial carbon sink by CO2 fertilization - Liu, Yongwen; Piao, Shilong; Gasser, Thomas; Ciais, Philippe; Yang, Hui; Wang, Han; Keenan, Trevor F.; Huang, Mengtian; Wan, Shiqiang; Song, Jian; Wang, Kai; Janssens, Ivan A.; et al. (Nature Geoscience, 2019)

Pervasive decreases in living vegetation carbon turnover time across forest climate zones - Yu, Kailiang; Smith, William K.; Trugman, Anna T.; Condit, Richard; Hubbell, Stephen P.; Sardans, Jordi; Peng, Changhui; Zhu, Kai; Peñuelas, Josep; Cailleret, Maxime; Levanic, Tom; Gessler, Arthur; et al. (Proceedings of the National Academy of Sciences, 2019)
Forests play a major role in the global carbon cycle. Previous studies on the capacity of forests to sequester atmospheric CO 2 have mostly focused on carbon uptake, but the roles of carbon turnover time and its spatiotemporal changes remain poorly understood. Here, we used long-term inventory data (1955 to 2018) from 695 mature forest plots to quantify temporal trends in living vegetation carbon turnover time across tropical, temperate, and cold climate zones, and compared plot data to 8 Earth system models (ESMs). Long-term plots consistently showed decreases in living vegetation carbon turnover time, likely driven by increased tree mortality across all major climate zones. Changes in living vegetation carbon turnover time were negatively correlated with CO 2 enrichment in both forest plot data and ESM simulations. However, plot-based correlations between living vegetation carbon turnover time and climate drivers such as precipitation and temperature diverged from those of ESM simulations. Our analyses suggest that forest carbon sinks are likely to be constrained by a decrease in living vegetation carbon turnover time, and accurate projections of forest carbon sink dynamics will require an improved representation of tree mortality processes and their sensitivity to climate in ESMs.

Modelling the impacts of climate and land use changes on soil water erosion: Model applications, limitations and future challenges - Guo, Yanrong; Peng, Changhui; Zhu, Qiuan; Wang, Meng; Wang, Han; Peng, Shushi; He, Honglin (Journal of Environmental Management, 2019)

Modeling Global Riverine DOC Flux Dynamics From 1951 to 2015 - Li, Mingxu; Peng, Changhui; Zhou, Xiaolu; Yang, Yanzheng; Guo, Yanrong; Shi, Guohua; Zhu, Qiuan (Journal of Advances in Modeling Earth Systems, 2019)
Abstract Climate change has a profound impact on the global carbon cycle, including effects on riverine carbon pools, which connect terrestrial, oceanic, and atmospheric carbon pools. Until now, terrestrial ecosystem models have rarely incorporated riverine carbon components into global carbon budgets. Here we developed a new process‐based model, TRIPLEX‐HYDRA (TRIPLEX‐hydrological routing algorithm), that considers the production, consumption, and transport processes of nonanthropogenic dissolved organic carbon (DOC) from soil to river ecosystems. After the parameter calibration, model results explained more than 50% of temporal variations in all but three rivers. Validation results suggested that DOC yield simulated by TRIPLEX‐HYDRA has a good fit ( R 2 = 0.61, n = 71, p < 0.001) with global river observations. And then, we applied this model for global rivers. We found that mean DOC yield of global river approximately 1.08 g C/m 2 year, where most high DOC yield appeared in the rivers from high northern or tropic regions. Furthermore, our results suggested that global riverine DOC flux appeared a significant decrease trend (average rate: 0.38 Pg C/year) from 1951 to 2015, although the variation patterns of DOC fluxes in global rivers are diverse. A decreasing trend in riverine DOC flux appeared in the middle and high northern latitude regions (30–90°N), which could be attributable to an increased flow path and DOC degradation during the transport process. Furthermore, increasing trend of DOC fluxes is found in rivers from tropical regions (30°S–30°N), which might be related to an increase in terrestrial organic carbon input. Many other rivers (e.g., Mississippi, Yangtze, and Lena rivers) experienced no significant changes under a changing environment. , Key Points Terrestrial ecosystem models rarely incorporate riverine DOC components into the global carbon cycle The TRIPLEX‐HYDRA model simulates the spatiotemporal variation in the DOC fluxes in global rivers The global riverine DOC flux simulated by the TRIPLEX‐HYDRA model has significantly decreased from 1951 to 2015

Simulation and Analysis of the Effect of a Spruce Budworm Outbreak on Carbon Dynamics in Boreal Forests of Quebec - Liu, Zelin; Peng, Changhui; De Grandpré, Louis; Candau, Jean-Noël; Work, Timothy; Huang, Chunbo; Kneeshaw, Daniel (Ecosystems, 2019)

Responses of nitrogen concentrations and pools to multiple environmental change drivers: A meta‐analysis across terrestrial ecosystems - Yue, Kai; Peng, Yan; Fornara, Dario A.; Van Meerbeek, Koenraad; Vesterdal, Lars; Yang, Wanqin; Peng, Changhui; Tan, Bo; Zhou, Wei; Xu, Zhenfeng; Ni, Xiangyin; Zhang, Li; et al. (Global Ecology and Biogeography, 2019)
Abstract Aim We sought to understand how the individual and combined effects of multiple environmental change drivers differentially influence terrestrial nitrogen (N) concentrations and N pools and whether the interactive effects of these drivers are mainly antagonistic, synergistic or additive. Location Worldwide. Time period Contemporary. Major taxa studied Plants, soil, and soil microbes in terrestrial ecosystems. Methods We synthesized data from manipulative field studies from 758 published articles to estimate the individual, combined and interactive effects of key environmental change drivers (elevated CO 2 , warming, N addition, phosphorus addition, increased rainfall and drought) on plant, soil, and soil microbe N concentrations and pools using meta‐analyses. We assessed the influences of moderator variables on these effects through structural equation modelling. Results We found that (a) N concentrations and N pools were significantly affected by the individual and combined effects of multiple drivers, with N addition (either alone or in combination with another driver) showing the strongest positive effects; (b) the individual and combined effects of these drivers differed significantly between N concentrations and N pools in plants, but seldom in soils and microbes; (c) additive effects of driver pairs on N concentrations and pools were much more common than synergistic or antagonistic effects across plants, soils and microbes; and (d) environmental and experimental factors were important moderators of the individual, combined and interactive effects of these drivers on terrestrial N. Main conclusions Our results indicate that terrestrial N concentrations and N pools, especially those of plants, can be significantly affected by the individual and combined effects of environmental change drivers, with the interactive effects of these drivers being mostly additive. Our findings are important because they contribute to the development of models to better predict how altered N availability affects ecosystem carbon cycling under future environmental changes.

Structural and functional differentiation of the microbial community in the surface and subsurface peat of two minerotrophic fens in China - Wang, Meng; Tian, Jianqing; Bu, Zhaojun; Lamit, Louis J.; Chen, Huai; Zhu, Qiuan; Peng, Changhui (Plant and Soil, 2019)

Factors Affecting the Spatial and Temporal Variations in Soil Erodibility of China - Zhu, Guangyu; Tang, Zhuangsheng; Shangguan, Zhouping; Peng, Changhui; Deng, Lei (Journal of Geophysical Research: Earth Surface, 2019)
Abstract Soil erosion occurs extensively across China, leading to severe degradation of the land and ecosystem services. However, the spatial and temporal variations in soil erodibility ( k ) and the distribution of soil erosion across land use types and slopes remain unclear. We synthesized the results from 325 sites published in 152 literatures to analyze the factors affecting the k , such as land use type, climate, topography, soil, and vegetation restoration age. The results showed that areas with slopes >25° had a larger k factor ( k = 0.1047) than did those with slope <6° ( k = 0.0637) or 6–25° ( k = 0.0832). The k from 2006 to 2011 ( k = 0.0725) was higher than that from 1999 to 2005 ( k = 0.058) and that from 2012 to 2016 ( k = 0.0631). The k value initially increased with vegetation restoration age and then gradually decreased. Land use also had an impact on the k factor, with the k factor of cropland ( k = 0.0697) being higher than that of grassland ( k = 0.0663) but lower than that of forest ( k = 0.0967). Across China, North Shaanxi, Heilongjiang, and South Guizhou, which are located in the Loess Plateau in Northwest China, the Black Soil region of Northeast China, and the Karst areas in Southwest China, respectively, were the three most severely eroded regions due to hydraulic erosion, frost‐thaw erosion, and high‐intensity erosion, respectively. Overall, the most important factors affecting the k were soil characteristics, followed by topography and climate. Among them, soil nitrogen and precipitation were the two most critical factors influencing the k . , Key Points Grassland had lower soil erodibility than had cropland and forestland North Shaanxi, Heilongjiang, and South Guizhou were the three most severely eroded regions Precipitation and soil N play critical roles in controlling soil erosion

Assessment of frozen ground organic carbon pool on the Qinghai-Tibet Plateau - Jiang, Lin; Chen, Huai; Zhu, Qiuan; Yang, Yanzheng; Li, Mingxu; Peng, Changhui; Zhu, Dan; He, Yixin (Journal of Soils and Sediments, 2019)

Separating Regressions for Model Fitting to Reduce the Uncertainty in Forest Volume-Biomass Relationship - Liu, Caixia; Zhou, Xiaolu; Lei, Xiangdong; Huang, Huabing; Zhou, Carl; Peng, Changhui; Wang, Xiaoyi (Forests, 2019)
The method of forest biomass estimation based on a relationship between the volume and biomass has been applied conventionally for estimating stand above- and below-ground biomass (SABB, t ha−1) from mean growing stock volume (m3 ha−1). However, few studies have reported on the diagnosis of the volume-SABB equations fitted using field data. This paper addresses how to (i) check parameters of the volume-SABB equations, and (ii) reduce the bias while building these equations. In our analysis, all equations were applied based on the measurements of plots (biomass or volume per hectare) rather than individual trees. The volume-SABB equation is re-expressed by two Parametric Equations (PEs) for separating regressions. Stem biomass is an intermediate variable (parametric variable) in the PEs, of which one is established by regressing the relationship between stem biomass and volume, and the other is created by regressing the allometric relationship of stem biomass and SABB. A graphical analysis of the PEs proposes a concept of “restricted zone,” which helps to diagnose parameters of the volume-SABB equations in regression analyses of field data. The sampling simulations were performed using pseudo data (artificially generated in order to test a model) for the model test. Both analyses of the regression and simulation demonstrate that the wood density impacts the parameters more than the allometric relationship does. This paper presents an applicable method for testing the field data using reasonable wood densities, restricting the error in field data processing based on limited field plots, and achieving a better understanding of the uncertainty in building those equations.

Variation in the functional traits of fine roots is linked to phylogenetics in the common tree species of Chinese subtropical forests - Liu, Cong; Xiang, Wenhua; Zou, Limei; Lei, Pifeng; Zeng, Yelin; Ouyang, Shuai; Deng, Xiangwen; Fang, Xi; Liu, Zelin; Peng, Changhui (Plant and Soil, 2019)

Variations of Sediment Archaea Communitiesin Different Distribution Areasof Bruguiera gymnoihiza Mangrovein Dongzhaigang, China - Li, Wei; Guan, Wei; Chen, Huai; Liao, Baowen; Hu, Ji; Rui, Junpeng; Peng, Changhui; Zhu, Dan; He, Yixin; Tian, Jianqing (Polish Journal of Environmental Studies, 2019)

Linkage between tree species richness and soil microbial diversity improves phosphorus bioavailability - Wu, Huili; Xiang, Wenhua; Ouyang, Shuai; Forrester, David I.; Zhou, Bo; Chen, Lingxiu; Ge, Tida; Lei, Pifeng; Chen, Liang; Zeng, Yelin; Song, Xinzhang; Peñuelas, Josep; et al. (Functional Ecology, 2019)
Abstract Increased availability of soil phosphorus (P) has recently been recognised as an underlying driving factor for the positive relationship between plant diversity and ecosystem function. The effects of plant diversity on the bioavailable forms of P involved in biologically mediated rhizospheric processes and how the link between plant and soil microbial diversity facilitates soil P bioavailability, however, remain poorly understood. This study quantified four forms of bioavailable P (CaCl 2 ‐P, citric‐P, enzyme‐P and HCl‐P) in mature subtropical forests using a novel biologically based approach, which emulates how rhizospheric processes influence the release and supply of available P. Soil microbial diversity was measured by Illumina high‐throughput sequencing. Our results suggest that tree species richness significantly affects soil microbial diversity ( p < 0.05), increases litter decomposition, fine‐root biomass and length and soil organic carbon and thus increases the four forms of bioavailable P. A structural equation model that links plants, soil microbes and P forms indicated that soil bacterial and fungal diversity play dominant roles in mediating the effects of tree species richness on soil P bioavailability. An increase in the biodiversity of plants, soil bacteria and fungi could maintain soil P bioavailability and alleviate soil P limitations. Our results imply that biodiversity strengthens plant and soil feedback and increases P recycling. A plain language summary is available for this article.

Effects of stand age, richness and density on productivity in subtropical forests in China - Ouyang, Shuai; Xiang, Wenhua; Wang, Xiangping; Xiao, Wenfa; Chen, Liang; Li, Shenggong; Sun, Han; Deng, Xiangwen; Forrester, David I.; Zeng, Lixiong; Lei, Pifeng; Lei, Xiangdong; et al. (Journal of Ecology, 2019)
Abstract Forest productivity may be determined not only by biodiversity but also by environmental factors and stand structure attributes. However, the relative importance of these factors in determining productivity is still controversial for subtropical forests. Based on a large dataset from 600 permanent forest inventory plots across subtropical China, we examined the relationship between biodiversity and forest productivity and tested whether stand structural attributes (stand density in terms of trees per ha, age and tree size) and environmental factors (climate and site conditions) had larger effects on productivity. Furthermore, we quantified the relative importance of environmental factors, stand structure and diversity in determining forest productivity. Diversity, together with stand structure and site conditions, regulated the variability in forest productivity. The relationship between diversity and forest productivity did not vary along environmental gradients. Stand density and age were more important modulators of forest productivity than diversity. Synthesis . Diversity had significant and positive effects on productivity in species‐rich subtropical forests, but the effects of stand density and age were also important. Our work highlights that while biodiversity conservation is often important, the regulation of stand structure can be even more important to maintain high productivity in subtropical forests.

Trait-Based Climate Change Predictions of Vegetation Sensitivity and Distribution in China - Yang, Yanzheng; Zhao, Jun; Zhao, Pengxiang; Wang, Hui; Wang, Boheng; Su, Shaofeng; Li, Mingxu; Wang, Liming; Zhu, Qiuan; Pang, Zhiyong; Peng, Changhui (Frontiers in Plant Science, 2019)

The effects of persistent drought and waterlogging on the dynamics of nonstructural carbohydrates of Robinia pseudoacacia L. seedlings in Northwest China - Yang, Bin; Peng, Changhui; Zhu, Qiuan; Zhou, Xiaolu; Liu, Weiguo; Duan, Min; Wang, Hui; Liu, Zhihao; Guo, Xinyi; Wang, Meng (Forest Ecosystems, 2019)

Weakening of the ‘enzymatic latch’ mechanism following long-term fertilization in a minerotrophic peatland - Li, Tong; Bu, Zhaojun; Liu, Wenyan; Zhang, Mingying; Peng, Changhui; Zhu, Qiuan; Shi, Shengwei; Wang, Meng (Soil Biology and Biochemistry, 2019)

Changes in soil organic carbon and microbial carbon storage projected during the 21st century using TRIPLEX-MICROBE - Wang, Kefeng; Peng, Changhui; Zhu, Qiuan; Wang, Meng; Wang, Gangsheng; Zhou, Xiaolu; Yang, Yanzheng; Ding, Juhua; Wei, Hua (Ecological Indicators, 2019)

Vegetation restoration stimulates soil carbon sequestration and stabilization in a subtropical area of southern China - Gu, Xiang; Fang, Xi; Xiang, Wenhua; Zeng, Yelin; Zhang, Shiji; Lei, Pifeng; Peng, Changhui; Kuzyakov, Yakov (CATENA, 2019)

Global soil nitrous oxide emissions since the preindustrial era estimated by an ensemble of terrestrial biosphere models: Magnitude, attribution, and uncertainty - Tian, Hanqin; Yang, Jia; Xu, Rongting; Lu, Chaoqun; Canadell, Josep G.; Davidson, Eric A.; Jackson, Robert B.; Arneth, Almut; Chang, Jinfeng; Ciais, Philippe; Gerber, Stefan; Ito, Akihiko; et al. (Global Change Biology, 2019)
Abstract Our understanding and quantification of global soil nitrous oxide (N 2 O) emissions and the underlying processes remain largely uncertain. Here, we assessed the effects of multiple anthropogenic and natural factors, including nitrogen fertilizer (N) application, atmospheric N deposition, manure N application, land cover change, climate change, and rising atmospheric CO 2 concentration, on global soil N 2 O emissions for the period 1861–2016 using a standard simulation protocol with seven process‐based terrestrial biosphere models. Results suggest global soil N 2 O emissions have increased from 6.3 ± 1.1 Tg N 2 O‐N/year in the preindustrial period (the 1860s) to 10.0 ± 2.0 Tg N 2 O‐N/year in the recent decade (2007–2016). Cropland soil emissions increased from 0.3 Tg N 2 O‐N/year to 3.3 Tg N 2 O‐N/year over the same period, accounting for 82% of the total increase. Regionally, China, South Asia, and Southeast Asia underwent rapid increases in cropland N 2 O emissions since the 1970s. However, US cropland N 2 O emissions had been relatively flat in magnitude since the 1980s, and EU cropland N 2 O emissions appear to have decreased by 14%. Soil N 2 O emissions from predominantly natural ecosystems accounted for 67% of the global soil emissions in the recent decade but showed only a relatively small increase of 0.7 ± 0.5 Tg N 2 O‐N/year (11%) since the 1860s. In the recent decade, N fertilizer application, N deposition, manure N application, and climate change contributed 54%, 26%, 15%, and 24%, respectively, to the total increase. Rising atmospheric CO 2 concentration reduced soil N 2 O emissions by 10% through the enhanced plant N uptake, while land cover change played a minor role. Our estimation here does not account for indirect emissions from soils and the directed emissions from excreta of grazing livestock. To address uncertainties in estimating regional and global soil N 2 O emissions, this study recommends several critical strategies for improving the process‐based simulations.

Quantifying leaf‐trait covariation and its controls across climates and biomes - Yang, Yanzheng; Wang, Han; Harrison, Sandy P.; Prentice, I. Colin; Wright, Ian J.; Peng, Changhui; Lin, Guanghui (New Phytologist, 2019)
Summary Plant functional ecology requires the quantification of trait variation and its controls. Field measurements on 483 species at 48 sites across China were used to analyse variation in leaf traits, and assess their predictability. Principal components analysis ( PCA ) was used to characterize trait variation, redundancy analysis ( RDA ) to reveal climate effects, and RDA with variance partitioning to estimate separate and overlapping effects of site, climate, life‐form and family membership. Four orthogonal dimensions of total trait variation were identified: leaf area ( LA ), internal‐to‐ambient CO 2 ratio (χ), leaf economics spectrum traits (specific leaf area ( SLA ) versus leaf dry matter content ( LDMC ) and nitrogen per area ( N area )), and photosynthetic capacities ( V cmax , J max at 25°C). LA and χ covaried with moisture index. Site, climate, life form and family together explained 70% of trait variance. Families accounted for 17%, and climate and families together 29%. LDMC and SLA showed the largest family effects. Independent life‐form effects were small. Climate influences trait variation in part by selection for different life forms and families. Trait values derived from climate data via RDA showed substantial predictive power for trait values in the available global data sets. Systematic trait data collection across all climates and biomes is still necessary.

Spatial and temporal variations of N2O emissions from global forest and grassland ecosystems - Zhang, Kerou; Zhu, Qiuan; Liu, Jinxun; Wang, Meng; Zhou, Xiaolu; Li, Mingxu; Wang, Kefeng; Ding, Juhua; Peng, Changhui (Agricultural and Forest Meteorology, 2019)

Nitrous oxide emissions from soils under traditional cropland and apple orchard in the semi-arid Loess Plateau of China - Pang, Junzhu; Wang, Xiaoke; Peng, Changhui; Mu, Yujing; Ouyang, Zhiyun; Lu, Fei; Zhang, Hongxing; Zhang, Shuoxin; Liu, Wenzhao (Agriculture, Ecosystems & Environment, 2019)

Nitrogen depositions increase soil respiration and decrease temperature sensitivity in a Moso bamboo forest - Li, Quan; Song, Xinzhang; Chang, Scott X.; Peng, Changhui; Xiao, Wenfa; Zhang, Junbo; Xiang, Wenhua; Li, Yan; Wang, Weifeng (Agricultural and Forest Meteorology, 2019)

Land use/cover change in the Three Gorges Reservoir area, China: Reconciling the land use conflicts between development and protection - Huang, Chunbo; Huang, Xin; Peng, Changhui; Zhou, Zhixiang; Teng, Mingjun; Wang, Pengcheng (CATENA, 2019)

Differences of soil CO2 flux in two contrasting subalpine ecosystems on the eastern edge of the Qinghai-Tibetan Plateau: A four-year study - Duan, Min; Li, Andi; Wu, Yanhong; Zhao, Zuoping; Peng, Changhui; DeLuca, Thomas H.; Sun, Shouqin (Atmospheric Environment, 2019)

Comparative analyses of different biogenic CO2 emission accounting systems in life cycle assessment - Liu, Weiguo; Zhu, Qiuan; Zhou, Xiaolu; Peng, Changhui (Science of The Total Environment, 2019)

How is biodiversity changing in response to ecological restoration in terrestrial ecosystems? A meta-analysis in China - Huang, Chunbo; Zhou, Zhixiang; Peng, Changhui; Teng, Mingjun; Wang, Pengcheng (Science of The Total Environment, 2019)

Modeling and estimating aboveground biomass of Dacrydium pierrei in China using machine learning with climate change - Wu, Chunyan; Chen, Yongfu; Peng, Changhui; Li, Zhaochen; Hong, Xiaojiang (Journal of Environmental Management, 2019)

Vegetation Functional Properties Determine Uncertainty of Simulated Ecosystem Productivity: A Traceability Analysis in the East Asian Monsoon Region - Cui, Erqian; Huang, Kun; Arain, Muhammad Altaf; Fisher, Joshua B.; Huntzinger, Deborah N.; Ito, Akihiko; Luo, Yiqi; Jain, Atul K.; Mao, Jiafu; Michalak, Anna M.; Niu, Shuli; Parazoo, Nicholas C.; et al. (Global Biogeochemical Cycles, 2019)
Abstract Global and regional projections of climate change by Earth system models are limited by their uncertain estimates of terrestrial ecosystem productivity. At the middle to low latitudes, the East Asian monsoon region has higher productivity than forests in Europe‐Africa and North America, but its estimate by current generation of terrestrial biosphere models (TBMs) has seldom been systematically evaluated. Here, we developed a traceability framework to evaluate the simulated gross primary productivity (GPP) by 15 TBMs in the East Asian monsoon region. The framework links GPP to net primary productivity, biomass, leaf area and back to GPP via incorporating multiple vegetation functional properties of carbon‐use efficiency (CUE), vegetation C turnover time ( τ veg ), leaf C fraction (F leaf ), specific leaf area (SLA), and leaf area index (LAI)‐level photosynthesis (P LAI ), respectively. We then applied a relative importance algorithm to attribute intermodel variation at each node. The results showed that large intermodel variation in GPP over 1901–2010 were mainly propagated from their different representation of vegetation functional properties. For example, SLA explained 77% of the intermodel difference in leaf area, which contributed 90% to the simulated GPP differences. In addition, the models simulated higher CUE (18.1 ± 21.3%), τ veg (18.2 ± 26.9%), and SLA (27.4±36.5%) than observations, leading to the overestimation of simulated GPP across the East Asian monsoon region. These results suggest the large uncertainty of current TBMs in simulating GPP is largely propagated from their poor representation of the vegetation functional properties and call for a better understanding of the covariations between plant functional properties in terrestrial ecosystems. , Key Points A GPP‐traceability framework is established to diagnose the uncertainty sources of modeled GPP Large intermodel differences of modeled GPP result from their different representation of vegetation functional properties Positive bias in simulated GPP over the East Asian monsoon region could be attributed to the higher simulated CUE and SLA comparing with observations

Land-use changes driven by ‘Grain for Green’ program reduced carbon loss induced by soil erosion on the Loess Plateau of China - Deng, Lei; Kim, Dong-Gill; Li, Miaoyu; Huang, Chunbo; Liu, Qiuyu; Cheng, Min; Shangguan, Zhouping; Peng, Changhui (Global and Planetary Change, 2019)

Does direct-seeded rice decrease ecosystem-scale methane emissions?—A case study from a rice paddy in southeast China - Li, Hong; Guo, Hai-Qiang; Helbig, Manuel; Dai, Sheng-Qi; Zhang, Meng-Shan; Zhao, Min; Peng, Chang-Hui; Xiao, Xiang-Ming; Zhao, Bin (Agricultural and Forest Meteorology, 2019)

The impact of secondary forest restoration on multiple ecosystem services and their trade-offs - Zeng, Yelin; Gou, Mengmeng; Ouyang, Shuai; Chen, Liang; Fang, Xi; Zhao, Lijuan; Li, Jiaxiang; Peng, Changhui; Xiang, Wenhua (Ecological Indicators, 2019)

Drivers of soil microbial metabolic limitation changes along a vegetation restoration gradient on the Loess Plateau, China - Deng, Lei; Peng, Changhui; Huang, Chunbo; Wang, Kaibo; Liu, Qiuyu; Liu, Yulin; Hai, Xuying; Shangguan, Zhouping (Geoderma, 2019)

Immediate and carry-over effects of increased soil frost on soil respiration and microbial activity in a spruce forest - Yang, Kaijun; Peng, Changhui; Peñuelas, Josep; Kardol, Paul; Li, Zhijie; Zhang, Li; Ni, Xiangyin; Yue, Kai; Tan, Bo; Yin, Rui; Xu, Zhenfeng (Soil Biology and Biochemistry, 2019)

Distribution margins as natural laboratories to infer species’ flowering responses to climate warming and implications for frost risk - Guo, Liang; Wang, Jinghong; Li, Mingjun; Liu, Lu; Xu, Jianchu; Cheng, Jimin; Gang, Chengcheng; Yu, Qiang; Chen, Ji; Peng, Changhui; Luedeling, Eike (Agricultural and Forest Meteorology, 2019)

Peatland degradation reduces methanogens and methane emissions from surface to deep soils - Yang, Gang; Tian, Jianqing; Chen, Huai; Jiang, Lin; Zhan, Wei; Hu, Ji; Zhu, Erxiong; Peng, Changhui; Zhu, Qiuan; Zhu, Dan; He, Yixin; Li, Mingxu; et al. (Ecological Indicators, 2019)

Effects of Land Cover Changes on Net Primary Productivity in the Terrestrial Ecosystems of China from 2001 to 2012 - Li, Hanwei; Ding, Juhua; Zhang, Jiang; Yang, Zhenan; Yang, Bin; Zhu, Qiuan; Peng, Changhui (Land, 2020)
The 2001–2012 MODIS MCD12Q1 land cover data and MOD17A3 NPP data were used to calculate changes in land cover in China and annual changes in net primary productivity (NPP) during a 12-year period and to quantitatively analyze the effects of land cover change on the NPP of China’s terrestrial ecosystems. The results revealed that during the study period, no changes in land cover type occurred in 7447.31 thousand km2 of China, while the area of vegetation cover increased by 160.97 thousand km2 in the rest of the country. Forest cover increased to 20.91%, which was mainly due to the conversion of large areas of savanna (345.19 thousand km2) and cropland (178.96 thousand km2) to forest. During the 12-year study period, the annual mean NPP of China was 2.70 PgC and increased by 0.25 PgC, from 2.50 to 2.75 PgC. Of this change, 0.21 PgC occurred in areas where there was no land cover change, while 0.04 PgC occurred in areas where there was land cover change. The contributions of forest and cropland to NPP exhibited increasing trends, while the contributions of shrubland and grassland to NPP decreased. Among these land cover types, the contributions of forest and cropland to the national NPP were the greatest, accounting for 40.97% and 27.95%, respectively, of the annual total NPP. There was no significant correlation between changes in forest area and changes in total annual NPP (R2 < 0.1), while the correlation coefficient for changes in cropland area and total annual NPP was 0.48. Additionally, the area of cropland converted to other land cover types was negatively correlated with the changes in NPP, and the loss of cropland caused a reduction in the national NPP.

Quantifying the Effects of Vegetation Restorations on the Soil Erosion Export and Nutrient Loss on the Loess Plateau - Zhao, Jun; Feng, Xiaoming; Deng, Lei; Yang, Yanzheng; Zhao, Zhong; Zhao, Pengxiang; Peng, Changhui; Fu, Bojie (Frontiers in Plant Science, 2020)
The transport of eroded soil to rivers changes the nutrient cycles of river ecosystems and has significant impacts on the regional eco-environment and human health. The Loess Plateau, a leading vegetation restoration region in China and the world, has experienced severe soil erosion and nutrient loss, however, the extent to which vegetation restoration prevents soil erosion export (to rivers) and it caused nutrient loss is unknown. To evaluate the effects of the first stage of the Grain for Green Project (GFGP) on the Loess Plateau (started in 1999 and ended in 2013), we analyzed the vegetation change trends and quantified the effects of GFGP on soil erosion export (to rivers) and it caused nutrient loss by considering soil erosion processes. The results were as follows: (1) in the first half of study period (from 1982 to 1998), the vegetation cover changed little, but after the implementation of the first stage of the GFGP (from 1999 to 2013), the vegetation cover of 75.0% of the study area showed a significant increase; (2) The proportion of eroded areas decreased from 41.8 to 26.7% as a result of the GFGP, and the erosion intensity lessened in most regions; the implementation significantly reduce the soil nutrient loss; (3) at the county level, soil erosion export could be avoided significantly by the increasing of vegetation greenness in the study area ( R = −0.49). These results illustrate the relationships among changes in vegetation cover, soil erosion and nutrient export, which could provide a reference for local government for making ecology-relative policies.

Estimating soil organic carbon redistribution in three major river basins of China based on erosion processes - Yang, Yan; Zhu, Qiuan; Liu, Jinxun; Li, Mingxu; Yuan, Minshu; Chen, Huai; Peng, Changhui; Yang, Zhenan (Soil Research, 2020)
Soil erosion by water affects soil organic carbon (SOC) migration and distribution, which are important processes for defining ecosystem carbon sources and sinks. Little has been done to quantify soil carbon erosion in the three major basins in China, the Yangtze River, Yellow River and Pearl River Basins, which contain the most eroded areas. This research attempts to quantify the lateral movement of SOC based on spatial and temporal patterns of water erosion rates derived from an empirical Unit Stream Power Erosion Deposition Model (USPED) model. The water erosion rates simulated by the USPED model agreed reasonably with observations (R2 = 0.43, P < 0.01). We showed that regional water erosion ranged within 23.3–50 Mg ha–1 year–1 during 1992–2013, inducing the lateral redistribution of SOC caused by erosion in the range of 0.027–0.049 Mg C ha–1 year–1, and that caused by deposition of 0.0079–0.015 Mg C ha–1 year–1, in the three basins. The total eroded SOC was 0.006, 0.002 and 0.001 Pg year–1 in the Yangtze River, Yellow River and Pearl River Basins respectively. The net eroded SOC in the three basins was ~0.0075 Pg C year–1. Overall, the annual average redistributed SOC rate caused by erosion was greater than that caused by deposition, and the SOC loss in the Yangtze River Basin was greatest among the three basins. Our study suggests that considering both processes of erosion and deposition – as well as effects of topography, rainfall, land use types and their interactions – on these processes are important to understand SOC redistribution caused by water erosion.

A review of the mechanisms and controlling factors of methane dynamics in forest ecosystems - Feng, Huili; Guo, Jiahuan; Han, Menghua; Wang, Weifeng; Peng, Changhui; Jin, Jiaxin; Song, Xinzhang; Yu, Shuiqiang (Forest Ecology and Management, 2020)

The effects of the soil environment on soil organic carbon in tea plantations in Xishuangbanna, southwestern China - Di, Sun; Zong, Mingming; Li, Shiyu; Li, Haixia; Duan, Changqun; Peng, Changhui; Zhao, Yonggui; Bai, Jinyue; Lin, Chen; Feng, Yuan; Huang, Wuping; Wang, Di (Agriculture, Ecosystems & Environment, 2020)

Using machine learning to synthesize spatiotemporal data for modelling DBH-height and DBH-height-age relationships in boreal forests - Chen, Jiaxin; Yang, Hongqiang; Man, Rongzhou; Wang, Weifeng; Sharma, Mahadev; Peng, Changhui; Parton, John; Zhu, Huaiping; Deng, Ziwang (Forest Ecology and Management, 2020)

Warming‐induced global soil carbon loss attenuated by downward carbon movement - Luo, Zhongkui; Luo, Yiqi; Wang, Guocheng; Xia, Jianyang; Peng, Changhui (Global Change Biology, 2020)
Abstract The fate of soil organic carbon (SOC) under warming is poorly understood, particularly across large extents and in the whole‐soil profile. Using a data‐model integration approach applied across the globe, we find that downward movement of SOC along the soil profile reduces SOC loss under warming. We predict that global SOC stocks (down to 2 m) will decline by 4% (~80 Pg) on average when SOC reaches the steady state under 2°C warming, assuming no changes in net primary productivity (NPP). To compensate such decline (i.e. maintain current SOC stocks), a 3% increase of NPP is required. Without the downward SOC movement, global SOC declines by 15%, while a 20% increase in NPP is needed to compensate that loss. This vital role of downward SOC movement in controlling whole‐soil profile SOC dynamics in response to warming is due to the protection afforded to downward‐moving SOC by depth, indicated by much longer residence times of SOC in deeper layers. Additionally, we find that this protection could not be counteracted by promoted decomposition due to the priming of downward‐moving new SOC from upper layers on native old SOC in deeper layers. This study provides the first estimation of whole‐soil SOC changes under warming and additional NPP required to compensate such changes across the globe, and reveals the vital role of downward movement of SOC in reducing SOC loss under global warming.

The significant contribution of lake depth in regulating global lake diffusive methane emissions - Li, Mingxu; Peng, Changhui; Zhu, Qiuan; Zhou, Xiaolu; Yang, Gang; Song, Xinzhang; Zhang, Kerou (Water Research, 2020)

Effect of Urbanization on Ecosystem Service Values in the Beijing-Tianjin-Hebei Urban Agglomeration of China from 2000 to 2014 - Liu, Shan; Yang, Mingxia; Mou, Yuling; Meng, Yanrong; Zhou, Xiaolu; Peng, Changhui (Sustainability, 2020)
Rapid urbanization has led to the continuous deterioration of the surrounding natural ecosystem. It is important to identify the key urbanization factors that affect ecosystem services and analyze the potential effects of these factors on the ecosystem. We selected the Beijing, Tianjin, and Hebei (BTH) urban agglomeration to investigate these effects, and designed three indicators to map the urbanization level: Population density, gross domestic product (GDP) density, and the construction land proportion. Four indicators were chosen to quantify ecosystem services: Food production, carbon sequestration and oxygen production, water conservation, and soil conservation. To handle the nonlinear interactions, we used a random forest (RF) method to assess the effect of urbanization on ecosystem services in the BTH area from 2000 to 2014. Our study demonstrated that population density and economic growth were the internal driving forces affecting ecosystem services. We observed changing trends in the effect of urbanization: The effect of population density on ecosystem services increased, the effect of the proportion of construction land was consistent with population density, and the effect of GDP density on ecosystem services decreased. Our results suggest that controlling the population and GDP would significantly influence the sustainable development in large urban areas.

A new integrated framework to estimate the climate change impacts of biomass utilization for biofuel in life cycle assessment - Liu, Weiguo; Xu, Junming; Xie, Xinfeng; Yan, Yan; Zhou, Xiaolu; Peng, Changhui (Journal of Cleaner Production, 2020)

The Vertical Differences in the Change Rates and Controlling Factors of Soil Organic Carbon and Total Nitrogen along Vegetation Restoration in a Subtropical Area of China - Cao, Zhiwei; Fang, Xi; Xiang, Wenhua; Lei, Pifeng; Peng, Changhui (Sustainability, 2020)
The study was to investigate the change patterns of soil organic carbon (SOC), total nitrogen (TN), and soil C/N (C/N) in each soil sublayer along vegetation restoration in subtropical China. We collected soil samples in four typical plant communities along a restoration chronosequence. The soil physicochemical properties, fine root, and litter biomass were measured. Our results showed the proportion of SOC stocks (Cs) and TN stocks (Ns) in 20–30 and 30–40 cm soil layers increased, whereas that in 0–10 and 10–20 cm soil layers decreased. Different but well-constrained C/N was found among four restoration stages in each soil sublayer. The effect of soil factors was greater on the deep soil than the surface soil, while the effect of vegetation factors was just the opposite. Our study indicated that vegetation restoration promoted the uniform distribution of SOC and TN on the soil profile. The C/N was relatively stable along vegetation restoration in each soil layer. The accumulation of SOC and TN in the surface soil layer was controlled more by vegetation factors, while that in the lower layer was controlled by both vegetation factors and soil factors.

Global estimation of the climate change impact of logging residue utilization for biofuels - Liu, Weiguo; Hou, Yue; Liu, Wenyan; Yang, Mingxia; Yan, Yan; Peng, Changhui; Yu, Zhen (Forest Ecology and Management, 2020)

Effects of increasing aerosol optical depth on the gross primary productivity in China during 2000–2014 - Zhang, Jing; Ding, Juhua; Zhang, Jiang; Yuan, Minshu; Li, Peng; Xiao, Zhongyong; Peng, Changhui; Chen, Huai; Wang, Meng; Zhu, Qiuan (Ecological Indicators, 2020)

High uncertainties detected in the wetlands distribution of the Qinghai–Tibet Plateau based on multisource data - Wang, Jieyi; Zhu, Qiuan; Yang, Yan; Zhang, Xian; Zhang, Jiang; Yuan, Minshu; Chen, Huai; Peng, Changhui (Landscape and Ecological Engineering, 2020)

Assessment of biomass utilization potential of Caragana korshinskii and its effect on carbon sequestration on the Northern Shaanxi Loess Plateau, China - Liu, Weiguo; Yu, Zhen; Zhu, Qiuan; Zhou, Xiaolu; Peng, Changhui (Land Degradation & Development, 2020)
Abstract Biomass has been promoted as a promising energy resource to mitigate global climate change. To evaluate the contribution of biomass utilization to climate change mitigation under the “Grain for Green” program in Northern Shaanxi, China, a soil carbon dynamic model and a life cycle assessment model were integrated to examine the benefits of using Caragana korshinskii Kom. as an energy crop. We found that the annual dry biomass output is maintained at 0.7 Tg during the simulation period (2020–2097). Due to the compensatory effect of biomass regrowth, the global warming potential of biomass‐derived CO 2 emissions is approximately 0.045; therefore, the total annual biogenic CO 2 emission is 57,211 ± 6,168 Mg CO 2 eq. The total annual life cycle CO 2 emissions approach 867,072 Mg CO 2 eq yr −1 . Under the scenario of no biomass removal, final carbon storage ranges from 15.7 to 19.3 TgC, and the highest carbon sequestration rate is 0.47 TgC yr −1 . In comparison with the no biomass removal scenario, the carbon sequestration rate (close to 0 MgC yr −1 ) in the biomass utilization scenario indicates a carbon loss; however, a portion of the carbon loss (31.39–62.09%) can be offset by carbon emission reductions from the substitution of fossil fuels.

Dynamics of soil water extractable organic carbon and inorganic nitrogen and their environmental controls in mountain forest and meadow ecosystems in China - Zhang, Junjun; Peng, Changhui; Xue, Wei; Yang, Bin; Yang, Zhenan; Niu, Shuli; Zhu, Qiuan; Wang, Meng (CATENA, 2020)

Modeling the effects of precipitation and temperature patterns on agricultural drought in China from 1949 to 2015 - Yang, Mingxia; Mou, Yuling; Meng, Yanrong; Liu, Shan; Peng, Changhui; Zhou, Xiaolu (Science of The Total Environment, 2020)

Tree growth rate and soil nutrient status determine the shift in nutrient-use strategy of Chinese fir plantations along a chronosequence - Wu, Huili; Xiang, Wenhua; Ouyang, Shuai; Xiao, Wenfa; Li, Shenggong; Chen, Liang; Lei, Pifeng; Deng, Xiangwen; Zeng, Yelin; Zeng, Lixiong; Peng, Changhui (Forest Ecology and Management, 2020)

Aerial spraying of bacterial insecticides to control spruce budworm defoliation leads to reduced carbon losses - Liu, Zelin; Peng, Changhui; De Grandpré, Louis; Candau, Jean‐Noël; Work, Timothy; Zhou, Xiaolu; Kneeshaw, Daniel (Ecosphere, 2020)
Abstract Spruce budworm (SBW) outbreaks are a major natural disturbance in boreal forests of eastern North America. During large‐scale infestations, aerial spraying of bacterial insecticides is used to suppress local high‐density SBW populations. While the primary goal of spraying is the protection of wood volume for later harvest, it should also maintain carbon stored in trees. This study provides the first quantitative analysis of the efficacy of aerial spraying against SBW on carbon dynamics in balsam fir, spruce, and mixed fir–spruce forests. In this study, we used the TRIPLEX‐Insect model to simulate carbon dynamics with and without spray applications in 14 sites of the boreal forest located in various regions of Québec. We found that the efficacy of aerial spraying on reducing annual defoliation was greater in the early stage (<5 yr since the outbreak began) of the outbreak than in later (5–10 yr since the outbreak began) stage. Our results showed that more net ecosystem productivity is maintained in balsam fir (the most vulnerable species) than in either spruce or mixed fir–spruce forests following spraying. Also, average losses in aboveground biomass due to the SBW following spraying occurred more slowly than without spraying in balsam fir forests. Our findings suggest that aerial spraying could be used to maintain carbon in conifer forests during SBW disturbances, but that the efficacy of spray programs is affected by host species and stage of the SBW outbreak.

Soil GHG fluxes are altered by N deposition: New data indicate lower N stimulation of the N2 O flux and greater stimulation of the calculated C pools - Deng, Lei; Huang, Chunbo; Kim, Dong‐Gill; Shangguan, Zhouping; Wang, Kaibo; Song, Xinzhang; Peng, Changhui (Global Change Biology, 2020)
Abstract The effects of nitrogen (N) deposition on soil organic carbon (C) and greenhouse gas (GHG) emissions in terrestrial ecosystems are the main drivers affecting GHG budgets under global climate change. Although many studies have been conducted on this topic, we still have little understanding of how N deposition affects soil C pools and GHG budgets at the global scale. We synthesized a comprehensive dataset of 275 sites from multiple terrestrial ecosystems around the world and quantified the responses of the global soil C pool and GHG fluxes induced by N enrichment. The results showed that the soil organic C concentration and the soil CO 2 , CH 4 and N 2 O emissions increased by an average of 3.7%, 0.3%, 24.3% and 91.3% under N enrichment, respectively, and that the soil CH 4 uptake decreased by 6.0%. Furthermore, the percentage increase in N 2 O emissions (91.3%) was two times lower than that (215%) reported by Liu and Greaver ( Ecology Letters , 2009, 12:1103–1117). There was also greater stimulation of soil C pools (15.70 kg C ha −1 year −1 per kg N ha −1 year −1 ) than previously reported under N deposition globally. The global N deposition results showed that croplands were the largest GHG sources (calculated as CO 2 equivalents), followed by wetlands. However, forests and grasslands were two important GHG sinks. Globally, N deposition increased the terrestrial soil C sink by 6.34 Pg CO 2 /year. It also increased net soil GHG emissions by 10.20 Pg CO 2 ‐Geq (CO 2 equivalents)/year. Therefore, N deposition not only increased the size of the soil C pool but also increased global GHG emissions, as calculated by the global warming potential approach.

Extrapolation and Uncertainty Evaluation of Carbon Dioxide and Methane Emissions in the Qinghai-Tibetan Plateau Wetlands Since the 1960s - Zhang, Jiang; Zhu, Qiuan; Yuan, Minshu; Liu, Xinwei; Chen, Huai; Peng, Changhui; Wang, Meng; Yang, Zhenan; Jiang, Lin; Zhao, Pengxiang (Frontiers in Earth Science, 2020)
Wetlands are important modulators of atmospheric greenhouse gas (GHGs) concentrations. However, little is known about the magnitudes and spatiotemporal patterns of GHGs fluxes in wetlands on the Qinghai-Tibetan Plateau (QTP), the world’s largest and highest plateau. In this study, we measured soil temperature and the fluxes of carbon dioxide (CO 2 ) and methane (CH 4 ) in an alpine wetland on the QTP from April 2017 to April 2019 by the static chamber method, and from January 2017 to December 2017 by the eddy covariance (EC) method. The CO 2 and CH 4 emission measurements from both methods showed different relationships to soil temperature at different timescales (annual and seasonal). Based on such relationship patterns and soil temperature data (1960–2017), we extrapolated the CO 2 and CH 4 emissions of study site for the past 57 years: the mean CO 2 emission rate was 91.38 mg C m –2 h –1 on different measurement methods and timescales, with the range of the mean emission rate from 35.10 to 146.25 mg C m –2 h –1 , while the mean CH 4 emission rate was 2.75 mg C m –2 h –1 , with the ranges of the mean emission rate from 1.41 to 3.85 mg C m –2 h –1 . The estimated regional CO 2 and CH 4 emissions from permanent wetlands on the QTP were 94.29 and 2.37 Tg C year –1 , respectively. These results indicate that uncertainties caused by measuring method and timescale should be fully considered when extrapolating wetland GHGs fluxes from local sites to the regional level. Moreover, the results of global warming potential showed that CO 2 dominates the GHG balance of wetlands on the QTP.

Global vegetation biomass production efficiency constrained by models and observations - He, Yue; Peng, Shushi; Liu, Yongwen; Li, Xiangyi; Wang, Kai; Ciais, Philippe; Arain, M. Altaf; Fang, Yuanyuan; Fisher, Joshua B.; Goll, Daniel; Hayes, Daniel; Huntzinger, Deborah N.; et al. (Global Change Biology, 2020)
Abstract Plants use only a fraction of their photosynthetically derived carbon for biomass production (BP). The biomass production efficiency (BPE), defined as the ratio of BP to photosynthesis, and its variation across and within vegetation types is poorly understood, which hinders our capacity to accurately estimate carbon turnover times and carbon sinks. Here, we present a new global estimation of BPE obtained by combining field measurements from 113 sites with 14 carbon cycle models. Our best estimate of global BPE is 0.41 ± 0.05, excluding cropland. The largest BPE is found in boreal forests (0.48 ± 0.06) and the lowest in tropical forests (0.40 ± 0.04). Carbon cycle models overestimate BPE, although models with carbon–nitrogen interactions tend to be more realistic. Using observation‐based estimates of global photosynthesis, we quantify the global BP of non‐cropland ecosystems of 41 ± 6 Pg C/year. This flux is less than net primary production as it does not contain carbon allocated to symbionts, used for exudates or volatile carbon compound emissions to the atmosphere. Our study reveals a positive bias of 24 ± 11% in the model‐estimated BP (10 of 14 models). When correcting models for this bias while leaving modeled carbon turnover times unchanged, we found that the global ecosystem carbon storage change during the last century is decreased by 67% (or 58 Pg C).

Change in Autumn Vegetation Phenology and the Climate Controls From 1982 to 2012 on the Qinghai–Tibet Plateau - Li, Peng; Zhu, Qiuan; Peng, Changhui; Zhang, Jing; Wang, Meng; Zhang, Junjun; Ding, Juhua; Zhou, Xiaolu (Frontiers in Plant Science, 2020)

Nitrogen addition increased CO2 uptake more than non-CO2 greenhouse gases emissions in a Moso bamboo forest - Song, Xinzhang; Peng, Changhui; Ciais, Philippe; Li, Quan; Xiang, Wenhua; Xiao, Wenfa; Zhou, Guomo; Deng, Lei (Science Advances, 2020)
Moso bamboo forests have greater net carbon uptake benefits with increasing nitrogen deposition in the coming decades. , Atmospheric nitrogen (N) deposition affects the greenhouse gas (GHG) balance of ecosystems through the net atmospheric CO 2 exchange and the emission of non-CO 2 GHGs (CH 4 and N 2 O). We quantified the effects of N deposition on biomass increment, soil organic carbon (SOC), and N 2 O and CH 4 fluxes and, ultimately, the net GHG budget at ecosystem level of a Moso bamboo forest in China. Nitrogen addition significantly increased woody biomass increment and SOC decomposition, increased N 2 O emission, and reduced soil CH 4 uptake. Despite higher N 2 O and CH 4 fluxes, the ecosystem remained a net GHG sink of 26.8 to 29.4 megagrams of CO 2 equivalent hectare −1 year −1 after 4 years of N addition against 22.7 hectare −1 year −1 without N addition. The total net carbon benefits induced by atmospheric N deposition at current rates of 30 kilograms of N hectare −1 year −1 over Moso bamboo forests across China were estimated to be of 23.8 teragrams of CO 2 equivalent year −1 .

Evaluating soil nutrients of Dacrydium pectinatum in China using machine learning techniques - Wu, Chunyan; Chen, Yongfu; Hong, Xiaojiang; Liu, Zelin; Peng, Changhui (Forest Ecosystems, 2020)
Abstract Background The accurate estimation of soil nutrient content is particularly important in view of its impact on plant growth and forest regeneration. In order to investigate soil nutrient content and quality for the natural regeneration of Dacrydium pectinatum communities in China, designing advanced and accurate estimation methods is necessary. Methods This study uses machine learning techniques created a series of comprehensive and novel models from which to evaluate soil nutrient content. Soil nutrient evaluation methods were built by using six support vector machines and four artificial neural networks. Results The generalized regression neural network model was the best artificial neural network evaluation model with the smallest root mean square error (5.1), mean error (− 0.85), and mean square prediction error (29). The accuracy rate of the combined k -nearest neighbors ( k -NN) local support vector machines model (i.e. k -nearest neighbors -support vector machine (KNNSVM)) for soil nutrient evaluation was high, comparing to the other five partial support vector machines models investigated. The area under curve value of generalized regression neural network (0.6572) was the highest, and the cross-validation result showed that the generalized regression neural network reached 92.5%. Conclusions Both the KNNSVM and generalized regression neural network models can be effectively used to evaluate soil nutrient content and quality grades in conjunction with appropriate model variables. Developing a new feasible evaluation method to assess soil nutrient quality for Dacrydium pectinatum , results from this study can be used as a reference for the adaptive management of rare and endangered tree species. This study, however, found some uncertainties in data acquisition and model simulations, which will be investigated in upcoming studies.

Contrasting responses of soil exoenzymatic interactions and the dissociated carbon transformation to short- and long-term drainage in a minerotrophic peatland - Li, Tong; Ge, Leming; Huang, Jingjing; Yuan, Xin; Peng, Changhui; Wang, Shengzhong; Bu, Zhaojun; Zhu, Qiuan; Wang, Zucheng; Liu, Weiguo; Wang, Meng (Geoderma, 2020)

Interspecific difference in N:P stoichiometric homeostasis drives nutrient release and soil microbial community composition during decomposition - Song, Hanxiong; Huang, Jingjing; Ge, Leming; Peng, Changhui; Zhao, Pengxiang; Guo, Xinyi; Li, Tong; Shen, Xiaojuan; Zhu, Qiuan; Liu, Weiguo; Wei, Hua; Wang, Meng (Plant and Soil, 2020)

Rainfall manipulation experiments as simulated by terrestrial biosphere models: Where do we stand? - Paschalis, Athanasios; Fatichi, Simone; Zscheischler, Jakob; Ciais, Philippe; Bahn, Michael; Boysen, Lena; Chang, Jinfeng; De Kauwe, Martin; Estiarte, Marc; Goll, Daniel; Hanson, Paul J.; Harper, Anna B.; et al. (Global Change Biology, 2020)
Abstract Changes in rainfall amounts and patterns have been observed and are expected to continue in the near future with potentially significant ecological and societal consequences. Modelling vegetation responses to changes in rainfall is thus crucial to project water and carbon cycles in the future. In this study, we present the results of a new model‐data intercomparison project, where we tested the ability of 10 terrestrial biosphere models to reproduce the observed sensitivity of ecosystem productivity to rainfall changes at 10 sites across the globe, in nine of which, rainfall exclusion and/or irrigation experiments had been performed. The key results are as follows: (a) Inter‐model variation is generally large and model agreement varies with timescales. In severely water‐limited sites, models only agree on the interannual variability of evapotranspiration and to a smaller extent on gross primary productivity. In more mesic sites, model agreement for both water and carbon fluxes is typically higher on fine (daily–monthly) timescales and reduces on longer (seasonal–annual) scales. (b) Models on average overestimate the relationship between ecosystem productivity and mean rainfall amounts across sites (in space) and have a low capacity in reproducing the temporal (interannual) sensitivity of vegetation productivity to annual rainfall at a given site, even though observation uncertainty is comparable to inter‐model variability. (c) Most models reproduced the sign of the observed patterns in productivity changes in rainfall manipulation experiments but had a low capacity in reproducing the observed magnitude of productivity changes. Models better reproduced the observed productivity responses due to rainfall exclusion than addition. (d) All models attribute ecosystem productivity changes to the intensity of vegetation stress and peak leaf area, whereas the impact of the change in growing season length is negligible. The relative contribution of the peak leaf area and vegetation stress intensity was highly variable among models.

The impact of intensive management on net ecosystem productivity and net primary productivity of a Lei bamboo forest - Zhang, Minxia; Chen, Shulin; Jiang, Hong; Peng, Changhui; Zhang, Jinmeng; Zhou, Guomo (Ecological Modelling, 2020)

Long-term forest succession improves plant diversity and soil quality but not significantly increase soil microbial diversity: Evidence from the Loess Plateau - Liu, Yulin; Zhu, Guangyu; Hai, Xuying; Li, Jiwei; Shangguan, Zhouping; Peng, Changhui; Deng, Lei (Ecological Engineering, 2020)

No evidence for carryover effect in tree rings based on a pulse-labelling experiment on Juniperus communis in South Germany - He, Minhui; Bräuning, Achim; Rossi, Sergio; Gebrekirstos, Aster; Grießinger, Jussi; Mayr, Christoph; Peng, Changhui; Yang, Bao (Trees, 2021)

Effects of Nitrogen Additions on Soil Respiration in an Asian Tropical Montane Rainforest - Wu, Fangtao; Peng, Changhui; Liu, Weiguo; Liu, Zhihao; Wang, Hui; Chen, Dexiang; Li, Yide (Forests, 2021)
Understanding the impacts of nitrogen (N) addition on soil respiration (RS) and its temperature sensitivity (Q10) in tropical forests is very important for the global carbon cycle in a changing environment. Here, we investigated how RS respond to N addition in a tropical montane rainforest in Southern China. Four levels of N treatments (0, 25, 50, and 100 kg N ha−1 a−1 as control (CK), low N (N25), moderate N (N50), and high N (N100), respectively) were established in September 2010. Based on a static chamber-gas chromatography method, RS was measured from January 2015 to December 2018. RS exhibited significant seasonal variability, with low RS rates appeared in the dry season and high rates appeared in the wet season regardless of treatment. RS was significantly related to the measured soil temperature and moisture. Our results showed that soil RS increased after N additions, the mean annual RS was 7% higher in N25 plots, 8% higher in N50 plots, and 11% higher in N100 plots than that in the CK plots. However, the overall impacts of N additions on RS were statistically insignificant. For the entire study period, the CK, N25, N50, and N100 treatments yielded Q10 values of 2.27, 3.45, 4.11, and 2.94, respectively. N addition increased the temperature sensitivity (Q10) of RS. Our results suggest that increasing atmospheric N deposition may have a large impact on the stimulation of soil CO2 emissions from tropical rainforests in China.

Strong controls of daily minimum temperature on the autumn photosynthetic phenology of subtropical vegetation in China - Ren, Peixin; Liu, Zelin; Zhou, Xiaolu; Peng, Changhui; Xiao, Jingfeng; Wang, Songhan; Li, Xing; Li, Peng (Forest Ecosystems, 2021)
Abstract Background Vegetation phenology research has largely focused on temperate deciduous forests, thus limiting our understanding of the response of evergreen vegetation to climate change in tropical and subtropical regions. Results Using satellite solar-induced chlorophyll fluorescence (SIF) and MODIS enhanced vegetation index (EVI) data, we applied two methods to evaluate temporal and spatial patterns of the end of the growing season (EGS) in subtropical vegetation in China, and analyze the dependence of EGS on preseason maximum and minimum temperatures as well as cumulative precipitation. Our results indicated that the averaged EGS derived from the SIF and EVI based on the two methods (dynamic threshold method and derivative method) was later than that derived from gross primary productivity (GPP) based on the eddy covariance technique, and the time-lag for EGS sif and EGS evi was approximately 2 weeks and 4 weeks, respectively. We found that EGS was positively correlated with preseason minimum temperature and cumulative precipitation (accounting for more than 73% and 62% of the study areas, respectively), but negatively correlated with preseason maximum temperature (accounting for more than 59% of the study areas). In addition, EGS was more sensitive to the changes in the preseason minimum temperature than to other climatic factors, and an increase in the preseason minimum temperature significantly delayed the EGS in evergreen forests, shrub and grassland. Conclusions Our results indicated that the SIF outperformed traditional vegetation indices in capturing the autumn photosynthetic phenology of evergreen forest in the subtropical region of China. We found that minimum temperature plays a significant role in determining autumn photosynthetic phenology in the study region. These findings contribute to improving our understanding of the response of the EGS to climate change in subtropical vegetation of China, and provide a new perspective for accurately evaluating the role played by evergreen vegetation in the regional carbon budget.

Leaf Trait Covariation and Its Controls: A Quantitative Data Analysis Along a Subtropical Elevation Gradient - Yang, Yanzheng; Gou, Ruikun; Li, Wei; Kassout, Jalal; Wu, Jun; Wang, Liming; Peng, Changhui; Lin, Guanghui (Journal of Geophysical Research: Biogeosciences, 2021)
Abstract Elevation gradients are frequently treated as useful space‐for‐time substitutions for inferring trait variations in response to different environmental conditions. The independent variations in leaf traits in response to elevation are well understood, but far less is known about trait covariation and its controls. This limits our understanding of the principles and mechanisms of leaf trait covariation, especially along elevation gradients in subtropical forests. Here, we studied the covariation among seven functional traits, including leaf size (LS), leaf nitrogen per unit mass ( N mass ), leaf nitrogen per unit area ( N area ), leaf mass per area (LMA), leaf dry matter content (LDMC), leaf thickness (LT) and the leaf internal‐to‐ambient CO 2 ratio ( C i : C a , termed χ ). Sampling was conducted on 41 species in a subtropical forest on Mount Huangshan, China, and the data were analyzed using multivariate analysis and variance partitioning procedures. We found that (a) The first three principal components captured 79% of the total leaf trait covariation, which was caused mainly by within site differences; (b) N mass and LDMC were positively correlated with soil water content (SW) and negatively correlated with vapor pressure deficit (VPD), while χ showed negative relationships with elevation; and (c) 78% of the variation in the studied plant functional traits could be explained by climate, soil, and family controls in combination, while family distribution was the most important determining factor for trait covariation along the elevation gradient. Our findings provide relevant insights into plant adaptation to environmental gradients and present useful guidelines for ecosystem management and planning. , Plain Language Summary Changes of plant functional traits along elevation gradient are important indicators which reflect the behaviors and adaptations of plants. In this study we first analyzed the dominant signals of seven leaf functional traits and then we depicted the response of seven traits to changing elevation environments, and finally we quantified the contributions of climate, soil, and vegetation distribution. Our findings validate the hypothesis that trait covariation, and thus adaptation, occurs in response to the elevation gradients that most plant species experience. , Key Points The first three principal components captured 79% of the total leaf trait covariation Leaf nitrogen content ( N mass ) and leaf dry mass content (LDMC) were positively correlated with soil water content and negatively correlated with vapor pressure deficit Vegetation (family) distribution was the most important determining factor for trait covariation along the elevation gradient

A Process‐Based Model Integrating Remote Sensing Data for Evaluating Ecosystem Services - Niu, Zhongen; He, Honglin; Peng, Shushi; Ren, Xiaoli; Zhang, Li; Gu, Fengxue; Zhu, Gaofeng; Peng, Changhui; Li, Pan; Wang, Junbang; Ge, Rong; Zeng, Na; et al. (Journal of Advances in Modeling Earth Systems, 2021)
Abstract Terrestrial ecosystems provide multiple services interacting in complex ways. However, most ecosystem services (ESs) models (e.g., InVEST and ARIES) ignored the relationships among ESs. Process‐based models can overcome this limitation, and the integration of ecological models with remote sensing data could greatly facilitate the investigation of the complex ecological processes. Therefore, based on the Carbon and Exchange between Vegetation, Soil, and Atmosphere (CEVSA) models, we developed a process‐based ES model (CEVSA‐ES) integrating remotely sensed leaf area index to evaluate four important ESs (i.e., productivity provision, carbon sequestration, water retention, and soil retention) at annual timescale in China. Compared to the traditional terrestrial biosphere models, the main innovation of CEVSA‐ES model was the consideration of soil erosion processes and its impact on carbon cycling. The new version also improved the carbon‐water cycle algorithms. Then, the Sobol and DEMC methods that integrated the CEVSA‐ES model with nine flux sites comprising 39 site‐years were used to identify and optimize parameters. Finally, the model using the optimized parameters was validated at 26 field sites comprising 135 site‐years. Simulation results showed good fits with ecosystem processes, explaining 95%, 92%, 76%, and 65% interannual variabilities of gross primary productivity, ecosystem respiration, net ecosystem productivity, and evapotranspiration, respectively. The CEVSA‐ES model performed well for productivity provision and carbon sequestration, which explained 96% and 81% of the spatial‐temporal variations of the observed annual productivity provision and carbon sequestration, respectively. The model also captured the interannual trends of water retention and soil erosion for most sites or basins. , Plain Language Summary Terrestrial ecosystems simultaneously provide multiple ecosystem services (ESs). The common environmental drivers and internal mechanisms lead to nonlinear and dynamic relationships among ESs. Assessing the spatiotemporal changes of ESs have recently emerged as an element of ecosystem management and environmental policies. However, appropriate methods linking ESs to biogeochemical and biophysical processes are still lacking. In this study, we developed a process‐based model Carbon and Exchange between Vegetation, Soil, and Atmosphere (CEVSA‐ES) that integrates remote sensing data for evaluating ESs. We first described the model framework and detailed algorithms of the processes related to ESs. Then a model‐fusion method was applied to optimize parameters to which the model was sensitive and to improve model performance based on multi‐source observational data. The calibrated CEVSA‐ES model showed good performance for carbon and water fluxes (i.e., gross primary productivity, ecosystem respiration, net ecosystem productivity, and evapotranspiration). The CEVSA‐ES model performed well for productivity provision, and carbon sequestration. It also captured the interannual trends of water retention and soil erosion for most sites or basins in Chinese terrestrial ecosystems. The CEVSA‐ES model not only has the potential to improve the accuracy of simulated ESs, but also can capture the relationships among ESs, which could support the trade‐offs and synergies among ESs. , Key Points We developed an ecosystem service model Carbon and Exchange between Vegetation, Soil, and Atmosphere‐ecosystem services (CEVSA‐ES) that integrates ecosystem processes with satellite‐based data Accounting for soil retention/erosion and its impact on carbon cycling was the main difference from other process‐based models The CEVSA‐ES model with optimized parameters explained 47%–96% of the spatial and temporal variations of four ecosystem services in China

Vulnerability of maize, millet, and rice yields to growing season precipitation and socio-economic proxies in Cameroon - Epule, Terence Epule; Chehbouni, Abdelghani; Dhiba, Driss; Etongo, Daniel; Driouech, Fatima; Brouziyne, Youssef; Peng, Changhui (PLOS ONE, 2021)
In sub-Saharan Africa growing season precipitation is affected by climate change. Due to this, in Cameroon, it is uncertain how some crops are vulnerable to growing season precipitation. Here, an assessment of the vulnerability of maize, millet, and rice to growing season precipitation is carried out at a national scale and validated at four sub-national scales/sites. The data collected were historical yield, precipitation, and adaptive capacity data for the period 1961–2019 for the national scale analysis and 1991–2016 for the sub-national scale analysis. The crop yield data were collected for maize, millet, and rice from FAOSTAT and the global yield gap atlas to assess the sensitivity both nationally and sub-nationally. Historical data on mean crop growing season and mean annul precipitation were collected from a collaborative database of UNDP/Oxford University and the climate portal of the World Bank to assess the exposure both nationally and sub-nationally. To assess adaptive capacity, literacy, and poverty rate proxies for both the national and regional scales were collected from KNOEMA and the African Development Bank. These data were analyzed using a vulnerability index that is based on sensitivity, exposure, and adaptive capacity. The national scale results show that millet has the lowest vulnerability index while rice has the highest. An inverse relationship between vulnerability and adaptive capacity is observed. Rice has the lowest adaptive capacity and the highest vulnerability index. Sub-nationally, this work has shown that northern maize is the most vulnerable crop followed by western highland rice. This work underscores the fact that at different scales, crops are differentially vulnerable due to variations in precipitation, temperature, soils, access to farm inputs, exposure to crop pest and variations in literacy and poverty rates. Therefore, caution should be taken when transitioning from one scale to another to avoid generalization. Despite these differences, in the sub-national scale, western highland rice is observed as the second most vulnerable crop, an observation similar to the national scale observation.

The Characteristics and Seasonal Variation of Methane Fluxes From an Alpine Wetland in the Qinghai Lake watershed, China - Wu, Fangtao; Cao, Shengkui; Cao, Guangchao; Chen, Kelong; Peng, Changhui (Wetlands, 2021)

Effect of Grazing Intensities on Soil N2O Emissions from an Alpine Meadow of Zoige Plateau in China - Zhan, Wei; Yang, Zhenan; Liu, Jianliang; Chen, Huai; Yang, Gang; Zhu, Erxiong; Hu, Ji; Jiang, Lin; Liu, Liangfeng; Zhu, Dan; He, Yixin; Zhao, Chuan; et al. (Atmosphere, 2021)
The alpine meadow of Zoige Plateau plays a key role in local livestock production of cattle and sheep. However, it remains unclear how animal grazing or its intensity affect nitrous oxide (N2O) emissions, and the main driving factors. A grazing experiment including four grazing intensities (G0, G0.7, G1.2, G1.6 yak ha−1) was conducted between January 2013 and December 2014 to evaluate the soil nitrous oxide (N2O) fluxes under different grazing intensities in an alpine meadow on the eastern Qinghai–Tibet Plateau of China. The N2O fluxes were examined with gas collected by the static chamber method and by chromatographic concentration analysis. N2O emissions in the growing seasons (from May to September) were lower than that in non-growing seasons (from October to April) in 2013, 1.94 ± 0.30 to 3.37 ± 0.56 kg N2O ha−1 yr−1. Annual mean N2O emission rates were calculated as 1.17 ± 0.50 kg N2O ha−1 yr−1 in non-grazing land (G0) and 1.94 ± 0.23 kg N2O ha−1 yr−1 in the grazing land (G0.7, G1.2, and G1.6). The annual mean N2O flux showed no significant differences between grazing treatments in 2013. However, there were significantly greater fluxes from the G0.7 treatment than from the G1.6 treatment in 2014, especially in the growing season. Over the two years, the soil N2O emission rate was significantly negatively correlated with soil water-filled pore space (WFPS) and dissolved organic carbon (DOC) content as well as positively correlated with soil available phosphorus (P). No relationship was observed between soil N2O emission rate and temperature or rainfall. Our results showed that the meadow soils acted as a source of N2O for most periods and turned into a weak sink of N2O later during the sampling period. Our results highlight the importance of proper grazing intensity in reducing N2O emissions from alpine meadow. The interaction between grazing intensity and N2O emissions should be of more concern during future management of pastures in Zoige Plateau.

Identifying maize yield and precipitation gaps in Uganda - Epule, Terence Epule; Dhiba, Driss; Etongo, Daniel; Peng, Changhui; Lepage, Laurent (SN Applied Sciences, 2021)
Abstract In sub-Saharan Africa (SSA), precipitation is an important driver of agricultural production. In Uganda, maize production is essentially rain-fed. However, due to changes in climate, projected maize yield targets have not often been met as actual observed maize yields are often below simulated/projected yields. This outcome has often been attributed to parallel gaps in precipitation. This study aims at identifying maize yield and precipitation gaps in Uganda for the period 1998–2017. Time series historical actual observed maize yield data (hg/ha/year) for the period 1998–2017 were collected from FAOSTAT. Actual observed maize growing season precipitation data were also collected from the climate portal of World Bank Group for the period 1998–2017. The simulated or projected maize yield data and the simulated or projected growing season precipitation data were simulated using a simple linear regression approach. The actual maize yield and actual growing season precipitation data were now compared with the simulated maize yield data and simulated growing season precipitation to establish the yield gaps. The results show that three key periods of maize yield gaps were observed (period one: 1998, period two: 2004–2007 and period three: 2015–2017) with parallel precipitation gaps. However, in the entire series (1998–2017), the years 2008–2009 had no yield gaps yet, precipitation gaps were observed. This implies that precipitation is not the only driver of maize yields in Uganda. In fact, this is supported by a low correlation between precipitation gaps and maize yield gaps of about 6.3%. For a better understanding of cropping systems in SSA, other potential drivers of maize yield gaps in Uganda such as soils, farm inputs, crop pests and diseases, high yielding varieties, literacy, and poverty levels should be considered.

Decoupling the Complementarity Effect and the Selection Effect on the Overyielding of Fine Root Production Along a Tree Species Richness Gradient in Subtropical Forests - Liu, Cong; Xiang, Wenhua; Xie, Binggeng; Ouyang, Shuai; Zeng, Yelin; Lei, Pifeng; Peng, Changhui (Ecosystems, 2021)

Nitrogen addition mediates the response of foliar stoichiometry to phosphorus addition: a meta-analysis - You, Chengming; Peng, Changhui; Xu, Zhenfeng; Liu, Yang; Zhang, Li; Yin, Rui; Liu, Lin; Li, Han; Wang, Lixia; Liu, Sining; Tan, Bo; Kardol, Paul (Ecological Processes, 2021)
Abstract Background Changes in foliar nitrogen (N) and phosphorus (P) stoichiometry play important roles in predicting the effects of global change on ecosystem structure and function. However, there is substantial debate on the effects of P addition on foliar N and P stoichiometry, particularly under different levels of N addition. Thus, we conducted a global meta-analysis to investigate how N addition alters the effects of P addition on foliar N and P stoichiometry across different rates and durations of P addition and plant growth types based on more than 1150 observations. Results We found that P addition without N addition increased foliar N concentrations, whereas P addition with N addition had no effect. The positive effects of P addition on foliar P concentrations were greater without N addition than with N addition. Additionally, the effects of P addition on foliar N, P and N:P ratios varied with the rate and duration of P addition. In particular, short-term or low-dose P addition with and without N addition increased foliar N concentration, and the positive effects of short-term or low-dose P addition on foliar P concentrations were greater without N addition than with N addition. The responses of foliar N and P stoichiometry of evergreen plants to P addition were greater without N addition than with N addition. Moreover, regardless of N addition, soil P availability was more effective than P resorption efficiency in predicting the changes in foliar N and P stoichiometry in response to P addition. Conclusions Our results highlight that increasing N deposition might alter the response of foliar N and P stoichiometry to P addition and demonstrate the important effect of the experimental environment on the results. These results advance our understanding of the response of plant nutrient use efficiency to P addition with increasing N deposition.

Gross Ecosystem Productivity Dominates the Control of Ecosystem Methane Flux in Rice Paddies - Li, Hong; Zhao, Min; Peng, Changhui; Guo, Haiqiang; Wang, Qing; Zhao, Bin (Land, 2021)
Although rice paddy fields are one of the world’s largest anthropogenic sources of methane CH4, the budget of ecosystem CH4 and its’ controls in rice paddies remain unclear. Here, we analyze seasonal dynamics of direct ecosystem-scale measurements of CH4 flux in a rice-wheat rotation agroecosystem over 3 consecutive years. Results showed that the averaged CO2 uptakes and CH4 emissions in rice seasons were 2.2 and 20.9 folds of the wheat seasons, respectively. In sum, the wheat-rice rotation agroecosystem acted as a large net C sink (averaged 460.79 g C m−2) and a GHG (averaged 174.38 g CO2eq m−2) source except for a GHG sink in one year (2016) with a very high rice seeding density. While the linear correlation between daily CH4 fluxes and gross ecosystem productivity (GEP) was not significant for the whole rice season, daily CH4 fluxes were significantly correlated to daily GEP both before (R2: 0.52–0.83) and after the mid-season drainage (R2: 0.71–0.79). Furthermore, the F partial test showed that GEP was much greater than that of any other variable including soil temperature for the rice season in each year. Meanwhile, the parameters of the best-fit functions between daily CH4 fluxes and GEP shifted between rice growth stages. This study highlights that GEP is a good predictor of daily CH4 fluxes in rice paddies.

Combined control of multiple extreme climate stressors on autumn vegetation phenology on the Tibetan Plateau under past and future climate change - Li, Peng; Liu, Zelin; Zhou, Xiaolu; Xie, Binggeng; Li, Zhongwu; Luo, Yunpeng; Zhu, Qiuan; Peng, Changhui (Agricultural and Forest Meteorology, 2021)

Analysis and Prediction of Expansion of Central Cities Based on Nighttime Light Data in Hunan Province, China - Liu, Yuxin; He, Tian; Wang, Yi; Peng, Changhui; Du, Hui; Yuan, Shuai; Li, Peng (Sustainability, 2021)
Quantifying the characteristics of urban expansion as well as influencing factors is essential for the simulation and prediction of urban expansion. In this study, we extracted the built-up regions of 14 central cities in the Hunan province using the DMSP-OLS night light remote sensing datasets from 1992 to 2018, and evaluated the spatial and temporal characteristics of the built-up regions in terms of the area, expansion speed, and main expansion direction. The backpropagation (BP) neural network and autoregressive integrated moving average (ARIMA) model were used to predict the area of the built-up regions from 2019 to 2026. The model predictions were based on the GDP, ratio of the secondary industry output to the GDP, ratio of the tertiary industry output to the GDP, year-end urban population, and urban road area. The results demonstrated that the built-up area and expansion speed of the central cities in the eastern part of the Hunan province were significantly higher than those in the western part. The main expansion directions of the 14 central cities were east and south. The urban road area, year-end urban population, and GDP were the main driving factors of the expansion. The urban expansion model based on the BP neural network provided a high prediction accuracy (R = 0.966). It was estimated that the total area of urban built-up regions in the Hunan province will reach 2463.80 km2 by 2026. These findings provide a new perspective for predicting urban areas rapidly and simply, and it also provides a useful reference for studying the spatial expansion characteristics of central cities and formulating a sustainable urban development strategy during the 14th Five-Year Plan of China.

Quantifying Leaf Trait Covariations and Their Relationships with Plant Adaptation Strategies along an Aridity Gradient - Yang, Yanzheng; Kang, Le; Zhao, Jun; Qi, Ning; Li, Ruonan; Wen, Zhongming; Kassout, Jalal; Peng, Changhui; Lin, Guanghui; Zheng, Hua (Biology, 2021)
A trait-based approach is an effective way to quantify plant adaptation strategies in response to changing environments. Single trait variations have been well depicted before; however, multi-trait covariations and their roles in shaping plant adaptation strategies along aridity gradients remain unclear. The purpose of this study was to reveal multi-trait covariation characteristics, their controls and their relevance to plant adaptation strategies. Using eight relevant plant functional traits and multivariate statistical approaches, we found the following: (1) the eight studied traits show evident covariation characteristics and could be grouped into four functional dimensions linked to plant strategies, namely energy balance, resource acquisition, resource investment and water use efficiency; (2) leaf area (LA) together with traits related to the leaf economic spectrum, including leaf nitrogen content per area (Narea), leaf nitrogen per mass (Nmass) and leaf dry mass per area (LMA), covaried along the aridity gradient (represented by the moisture index, MI) and dominated the trait–environmental change axis; (3) together, climate, soil and family can explain 50.4% of trait covariations; thus, vegetation succession along the aridity gradient cannot be neglected in trait covariations. Our findings provide novel perspectives toward a better understanding of plant adaptations to arid conditions and serve as a reference for vegetation restoration and management programs in arid regions.

Observed Methane Uptake and Emissions at the Ecosystem Scale and Environmental Controls in a Subtropical Forest - Wang, Hui; Li, Hong; Liu, Zhihao; Lv, Jianhua; Song, Xinzhang; Li, Quan; Jiang, Hong; Peng, Changhui (Land, 2021)
Methane (CH4) is one of the three most important greenhouse gases. To date, observations of ecosystem-scale methane (CH4) fluxes in forests are currently lacking in the global CH4 budget. The environmental factors controlling CH4 flux dynamics remain poorly understood at the ecosystem scale. In this study, we used a state-of-the-art eddy covariance technique to continuously measure the CH4 flux from 2016 to 2018 in a subtropical forest of Zhejiang Province in China, quantify the annual CH4 budget and investigate its control factors. We found that the total annual CH4 budget was 1.15 ± 0.28~4.79 ± 0.49 g CH4 m−2 year−1 for 2017–2018. The daily CH4 flux reached an emission peak of 0.145 g m−2 d−1 during winter and an uptake peak of −0.142 g m−2 d−1 in summer. During the whole study period, the studied forest region acted as a CH4 source (78.65%) during winter and a sink (21.35%) in summer. Soil temperature had a negative relationship (p < 0.01; R2 = 0.344) with CH4 flux but had a positive relationship with soil moisture (p < 0.01; R2 = 0.348). Our results showed that soil temperature and moisture were the most important factors controlling the ecosystem-scale CH4 flux dynamics of subtropical forests in the Tianmu Mountain Nature Reserve in Zhejiang Province, China. Subtropical forest ecosystems in China acted as a net source of methane emissions from 2016 to 2018, providing positive feedback to global climate warming.

Response of Vegetation Photosynthetic Phenology to Urbanization in Dongting Lake Basin, China - Li, Peng; Sun, Mai; Liu, Yuxin; Ren, Peixin; Peng, Changhui; Zhou, Xiaolu; Tang, Jiayi (Remote Sensing, 2021)
Urbanization can induce environmental changes such as the urban heat island effect, which in turn influence the terrestrial ecosystem. However, the effect of urbanization on the phenology of subtropical vegetation remains relatively unexplored. This study analyzed the changing trend of vegetation photosynthetic phenology in Dongting Lake basin, China, and its response to urbanization using nighttime light and chlorophyll fluorescence datasets. Our results indicated the start of the growing season (SOS) of vegetation in the study area was significantly advanced by 0.70 days per year, whereas the end of the growing season (EOS) was delayed by 0.24 days per year during 2000–2017. We found that urbanization promoted the SOS advance and EOS delay. With increasing urbanization intensity, the sensitivity of SOS to urbanization firstly increased then decreased, while the sensitivity of EOS to urbanization decreased with urbanization intensity. The climate sensitivity of vegetation phenology varied with urbanization intensity; urbanization induced an earlier SOS by increasing preseason minimum temperatures and a later EOS by increasing preseason precipitation. These findings improve our understanding of the vegetation phenology response to urbanization in subtropical regions and highlight the need to integrate human activities into future vegetation phenology models.

Temperature and Moisture Modulate the Contribution of Soil Fauna to Litter Decomposition via Different Pathways - Tan, Bo; Yin, Rui; Zhang, Jian; Xu, Zhenfeng; Liu, Yang; He, Shuqin; Zhang, Li; Li, Han; Wang, Lixia; Liu, Sining; You, Chengming; Peng, Changhui (Ecosystems, 2021)

Modern cities modelled as “super‐cells” rather than multicellular organisms: Implications for industry, goods and services - Chang, Jie; Ge, Ying; Wu, Zhaoping; Du, Yuanyuan; Pan, Kaixuan; Yang, Guofu; Ren, Yuan; Heino, Mikko P.; Mao, Feng; Cheong, Kang Hao; Qu, Zelong; Fan, Xing; et al. (BioEssays, 2021)
Abstract The structure and “metabolism” (movement and conversion of goods and energy) of urban areas has caused cities to be identified as “super‐organisms”, placed between ecosystems and the biosphere, in the hierarchy of living systems. Yet most such analogies are weak, and render the super‐organism model ineffective for sustainable development of cities. Via a cluster analysis of 15 shared traits of the hierarchical living system, we found that industrialized cities are more similar to eukaryotic cells than to multicellular organisms; enclosed systems, such as factories and greenhouses, paralleling organelles in eukaryotic cells. We further developed a “super‐cell” industrialized city model: a “eukarcity” with citynucleus (urban area) as a regulating centre, and organaras (enclosed systems, which provide the majority of goods and services) as the functional components, and cityplasm (natural ecosystems and farmlands) as the matrix. This model may improve the vitality and sustainability of cities through planning and management.

Water table drawdown increases plant biodiversity and soil polyphenol in the Zoige Plateau - Zeng, Jia; Chen, Huai; Bai, Yinping; Dong, Faqin; Peng, Changhui; Yan, Fei; Cao, Qin; Yang, Zhenan; Yang, Suizhuang; Yang, Gang (Ecological Indicators, 2021)

African climate change policy performance index - Epule, Terence Epule; Chehbouni, Abdelghani; Dhiba, Driss; Moto, Mirielle Wase; Peng, Changhui (Environmental and Sustainability Indicators, 2021)

Woody plants reduce the sensitivity of soil extracellular enzyme activity to nutrient enrichment in wetlands: A meta-analysis - Li, Tong; Peng, Changhui; Bu, Zhaojun; Zhu, Qiuan; Song, Hanxiong; Guo, Xinyi; Wang, Meng (Soil Biology and Biochemistry, 2021)

Ecosystem service multifunctionality of Chinese fir plantations differing in stand age and implications for sustainable management - Zeng, Yelin; Wu, Huili; Ouyang, Shuai; Chen, Liang; Fang, Xi; Peng, Changhui; Liu, Shirong; Xiao, Wenfa; Xiang, Wenhua (Science of The Total Environment, 2021)

TRIPLEX-Mortality model for simulating drought-induced tree mortality in boreal forests: Model development and evaluation - Liu, Qiuyu; Peng, Changhui; Schneider, Robert; Cyr, Dominic; Liu, Zelin; Zhou, Xiaolu; Kneeshaw, Daniel (Ecological Modelling, 2021)

Evaluation of Future Impacts of Climate Change, CO2, and Land Use Cover Change on Global Net Primary Productivity Using a Processed Model - Hu, Xiao; He, Yujie; Kong, Ze; Zhang, Jiang; Yuan, Minshu; Yu, Le; Peng, Changhui; Zhu, Qiuan (Land, 2021)
Few studies have focused on the combined impact of climate change, CO2, and land-use cover change (LUCC), especially the evaluation of the impact of LUCC on net primary productivity (NPP) in the future. In this study, we simulated the overall NPP change trend from 2010 to 2100 and its response to climatic factors, CO2 concentration, and LUCC conditions under three typical emission scenarios (Representative Concentration Pathway RCP2.6, RCP4.5, and RCP8.5). (1) Under the predicted global pattern, NPP showed an increasing trend, with the most prominent variation at the end of the century. The increasing trend is mainly caused by the positive effect of CO2 on NPP. However, the increasing trend of LUCC has only a small positive effect. (2) Under the RCP 8.5 scenario, from 2090 to 2100, CO2 has the most significant positive impact on tropical areas, reaching 8.328 Pg C Yr−1. Under the same conditions, climate change has the greatest positive impact on the northern high latitudes (1.175 Pg C Yr−1), but it has the greatest negative impact on tropical areas, reaching −4.842 Pg C Yr−1. (3) The average contribution rate of LUCC to NPP was 6.14%. Under the RCP8.5 scenario, LUCC made the largest positive contribution on NPP (0.542 Pg C Yr−1) globally from 2010 to 2020.

Headwater stream ecosystem: an important source of greenhouse gases to the atmosphere - Li, Mingxu; Peng, Changhui; Zhang, Kerou; Xu, Li; Wang, Jianming; Yang, Yan; Li, Peng; Liu, Zelin; He, Nianpeng (Water Research, 2021)

Quantitative assessment of the importance of bio-physical drivers of land cover change based on a random forest method - Meng, Yanrong; Yang, Mingxia; Liu, Shan; Mou, Yuling; Peng, Changhui; Zhou, Xiaolu (Ecological Informatics, 2021)

Drought effects on soil carbon and nitrogen dynamics in global natural ecosystems - Deng, Lei; Peng, Changhui; Kim, Dong-Gill; Li, Jiwei; Liu, Yulin; Hai, Xuying; Liu, Qiuyu; Huang, Chunbo; Shangguan, Zhouping; Kuzyakov, Yakov (Earth-Science Reviews, 2021)

Global response of terrestrial gross primary productivity to climate extremes - Yuan, Minshu; Zhu, Qiuan; Zhang, Jiang; Liu, Jinxun; Chen, Huai; Peng, Changhui; Li, Peng; Li, Mingxu; Wang, Meng; Zhao, Pengxiang (Science of The Total Environment, 2021)

Nitrogen, water content, phosphorus and active iron jointly regulate soil organic carbon in tropical acid red soil forest - Bai, Jinyue; Zong, Mingming; Li, Shiyu; Li, Haixia; Duan, Changqun; Feng, Yuan; Peng, Changhui; Zhang, Xiaoling; Sun, Di; Lin, Chen; Shi, Yucheng; Zheng, Guangyu; et al. (European Journal of Soil Science, 2021)
Abstract Increasing forest soil organic carbon (SOC) storage is important for reducing carbon dioxide (CO 2 ) emissions from terrestrial ecosystems and mitigating global climate change. Although the effects of altitude, temperature and rainfall on organic carbon have been studied extensively, it is difficult to increase SOC storage by changing these factors in actual forest management. This study determined the SOC, soil physical and chemical properties, nutrient elements, heavy metal elements, soil minerals and microbial biomass in the 0–140‐cm soil layer of the monsoon broad‐leaved forest in the acid red soil region of southwestern China by stratification. We tried to identify the soil factors affecting the SOC storage of the forest in the acid red soil region and determine the weights of the factors affecting the SOC, with the aim of improving the SOC retention capacity in forest management by changing the main soil factors affecting SOC storage. The results showed that the soil factors affecting the forest SOC storage in this area are total nitrogen (N, 22.7%) > soil water content (19.9%) > active iron (including poorly crystalline iron, Fe o , 15.5%) > pH (9.5%) > phosphorus (P, 9.4%) > aluminium (Al, 8.9%) > silicon (Si, 7.1%) > sulphur (S, 6.8%). Of these factors, N, the water content, Fe o , and P are practical factors for forest management, whereas the pH, Al, Si and S are not. SOC was significantly positively correlated with the soil N concentration, water content, active iron content and P concentration ( p < .05). In acidic red soil areas, with active iron as the highlight, N, soil water content, phosphorus and active iron jointly regulate the forest SOC storage capacity. Consequently, in actual forest management, any measures to promote soil N and water content and to activate inactive iron can enhance the storage of SOC, as appropriate input of N and P fertiliser and irrigation in dry years and the dry season. Highlights The soil environmental factors affecting SOC storage in forest soil are quantified Activation of inactive iron helps SOC storage in forest soil Irrigation and N and P input are effective for helping SOC storage in forest soil N, WC, P and Fe o jointly regulate SOC in tropical acid red soil forest

Management scheme influence and nitrogen addition effects on soil CO2, CH4, and N2O fluxes in a Moso bamboo plantation - Zhang, Junbo; Li, Quan; Lv, Jianhua; Peng, Changhui; Gu, Zhikang; Qi, Lianghua; Song, Xuzhong; Song, Xinzhang (Forest Ecosystems, 2021)
Abstract Background It is still not clear whether the effects of N deposition on soil greenhouse gas (GHG) emissions are influenced by plantation management schemes. A field experiment was conducted to investigate the effects of conventional management (CM) versus intensive management (IM), in combination with simulated N deposition levels of control (ambient N deposition), 30 kg N·ha − 1 ·year − 1 (N30, ambient + 30 kg N·ha − 1 ·year − 1 ), 60 kg N·ha − 1 ·year − 1 (N60, ambient + 60 kg N·ha − 1 ·year − 1 ), or 90 kg N·ha − 1 ·year − 1 (N90, ambient + 90 kg N·ha − 1 ·year − 1 ) on soil CO 2 , CH 4 , and N 2 O fluxes. For this, 24 plots were set up in a Moso bamboo ( Phyllostachys edulis ) plantation from January 2013 to December 2015. Gas samples were collected monthly from January 2015 to December 2015. Results Compared with CM, IM significantly increased soil CO 2 emissions and their temperature sensitivity ( Q 10 ) but had no significant effects on soil CH 4 uptake or N 2 O emissions. In the CM plots, N30 and N60 significantly increased soil CO 2 emissions, while N60 and N90 significantly increased soil N 2 O emissions. In the IM plots, N30 and N60 significantly increased soil CO 2 and N 2 O emissions, while N60 and N90 significantly decreased soil CH 4 uptake. Overall, in both CM and IM plots, N30 and N60 significantly increased global warming potentials, whereas N90 did not significantly affect global warming potential. However, N addition significantly decreased the Q 10 value of soil CO 2 emissions under IM but not under CM. Soil microbial biomass carbon was significantly and positively correlated with soil CO 2 and N 2 O emissions but significantly and negatively correlated with soil CH 4 uptake. Conclusion Our results indicate that management scheme effects should be considered when assessing the effect of atmospheric N deposition on GHG emissions in bamboo plantations.

The Effects of Drought and Re-Watering on Non-Structural Carbohydrates of Pinus tabulaeformis Seedlings - Guo, Xinyi; Peng, Changhui; Li, Tong; Huang, Jingjing; Song, Hanxiong; Zhu, Qiuan; Wang, Meng (Biology, 2021)
Intense and frequent drought events strongly affect plant survival. Non-structural carbohydrates (NSCs) are important “buffers” to maintain plant functions under drought conditions. We conducted a drought manipulation experiment using three-year-old Pinus tabulaeformis Carr. seedlings. The seedlings were first treated under different drought intensities (i.e., no irrigation, severe, and moderate) for 50 days, and then they were re-watered for 25 days to explore the dynamics of NSCs in the leaves, twigs, stems, and roots. The results showed that the no irrigation and severe drought treatments significantly reduced photosynthetic rate by 93.9% and 32.6% for 30 days, respectively, leading to the depletion of the starch storage for hydraulic repair, osmotic adjustment, and plant metabolism. The seedlings under moderate drought condition also exhibited starch storage consumption in leaves and twigs. After re-watering, the reduced photosynthetic rate recovered to the control level within five days in the severe drought group but showed no sign of recovery in the no irrigation group. The seedlings under the severe and moderate drought conditions tended to invest newly fixed C to starch storage and hydraulic repair instead of growth due to the “drought legacy effect”. Our findings suggest the depletion and recovery of starch storage are important strategies for P. tabulaeformis seedlings, and they may play key roles in plant resistance and resilience under environmental stress.

Nitrogen addition decreases methane uptake caused by methanotroph and methanogen imbalances in a Moso bamboo forest - Li, Quan; Peng, Changhui; Zhang, Junbo; Li, Yongfu; Song, Xinzhang (Scientific Reports, 2021)
Abstract Forest soils play an important role in controlling global warming by reducing atmospheric methane (CH 4 ) concentrations. However, little attention has been paid to how nitrogen (N) deposition may alter microorganism communities that are related to the CH 4 cycle or CH 4 oxidation in subtropical forest soils. We investigated the effects of N addition (0, 30, 60, or 90 kg N ha −1 yr −1 ) on soil CH 4 flux and methanotroph and methanogen abundance, diversity, and community structure in a Moso bamboo ( Phyllostachys edulis ) forest in subtropical China. N addition significantly increased methanogen abundance but reduced both methanotroph and methanogen diversity. Methanotroph and methanogen community structures under the N deposition treatments were significantly different from those of the control. In N deposition treatments, the relative abundance of Methanoculleus was significantly lower than that in the control. Soil pH was the key factor regulating the changes in methanotroph and methanogen diversity and community structure. The CH 4 emission rate increased with N addition and was negatively correlated with both methanotroph and methanogen diversity but positively correlated with methanogen abundance. Overall, our results suggested that N deposition can suppress CH 4 uptake by altering methanotroph and methanogen abundance, diversity, and community structure in subtropical Moso bamboo forest soils.

Identifying the greenhouses by Google Earth Engine to promote the reuse of fragmented land in urban fringe - Yang, Guofu; Xu, Ronghua; Chen, Yi; Wu, Zhaoping; Du, Yuanyuan; Liu, Shun; Qu, Zelong; Guo, Kejian; Peng, Changhui; Chang, Jie; Ge, Ying (Sustainable Cities and Society, 2021)

Corrigendum: Extrapolation and Uncertainty Evaluation of Carbon Dioxide and Methane Emissions in the Qinghai-Tibetan Plateau Wetlands Since the 1960s - Zhang, Jiang; Zhu, Qiuan; Yuan, Minshu; Liu, Xinwei; Chen, Huai; Peng, Changhui; Wang, Meng; Yang, Zhenan; Jiang, Lin; Zhao, Pengxiang (Frontiers in Earth Science, 2021)

Tillage activates iron to prevent soil organic carbon loss following forest conversion to cornfields in tropical acidic red soils - Zong, Mingming; Lin, Chen; Li, Shiyu; Li, Haixia; Duan, Changqun; Peng, Changhui; Guo, Yongxing; An, Ruiqi (Science of The Total Environment, 2021)

The effects of elevated CO2, elevated O3, elevated temperature, and drought on plant leaf gas exchanges: a global meta-analysis of experimental studies - Zhang, Jinmeng; Deng, Lei; Jiang, Hong; Peng, Changhui; Huang, Chunbo; Zhang, Minxia; Zhang, Xiuying (Environmental Science and Pollution Research, 2021)

Nitrogen -addition accelerates phosphorus cycling and changes phosphorus use strategy in a subtropical Moso bamboo forest - Li, Quan; Lv, Jianhua; Peng, Changhui; Xiang, Wenhua; Xiao, Wenfa; Song, Xinzhang (Environmental Research Letters, 2021)
Abstract Ecosystem-level effects of increasing atmospheric nitrogen (N) deposition on the phosphorus (P) cycle and P use strategy are poorly understood. Here, we conducted a seven year N-addition experiment to comprehensively evaluate the effects of N deposition on P limitation, cycling, and use strategy in a subtropical Moso bamboo forest. N addition significantly increased foliar litterfall by 4.7%–21.7% and subsequent P return to the soil by 49.0%–70.1%. It also increased soil acidity, acid phosphatase activity, and soil microbial biomass P, which substantially contributed to a significantly increased soil P availability and largely alleviated the P limitation. This resulted in a significant decrease in the foliar P-resorption efficiency and the abundance and colonization of arbuscular mycorrhizal fungi. Our results indicate that N deposition can reduce plant internal cycling while enhancing ecosystem-scale cycling of P in Moso bamboo forests. This suggests a shift in P use from a ‘conservative consumption’ strategy to a ‘resource spending’ strategy. Our findings shed new light on N deposition effects on P cycle processes and P use strategy at the ecosystem scale under increasing atmospheric N deposition.

Effects of plant functional group removal on community structure, diversity and production in Alpine meadow - Jiang Lin, 姜林，胡骥，杨振安，詹伟，赵川，朱单，何奕忻，陈槐，彭长辉 (Acta Ecologica Sinica, 2021)

Stability in subtropical forests: The role of tree species diversity, stand structure, environmental and socio‐economic conditions - Ouyang, Shuai; Xiang, Wenhua; Gou, Mengmeng; Chen, Liang; Lei, Pifeng; Xiao, Wenfa; Deng, Xiangwen; Zeng, Lixiong; Li, Jiangrong; Zhang, Tao; Peng, Changhui; Forrester, David I. (Global Ecology and Biogeography, 2021)
Abstract Aim Tree species diversity can increase the stability of ecosystem productivity by increasing mean productivity and/or reducing the standard deviation in productivity. However, stand structure, environmental and socio‐economic conditions influence plant diversity and might strongly influence the relationships between diversity and stability in natural forest communities. The relative importance of these factors for community stability remains poorly understood in complex (species‐rich) subtropical forests. Location Subtropical area of southern China. Time period 1999–2014. Major taxa studied Forest trees. Methods We conducted bivariate analyses to examine the mechanisms (overyielding and species asynchrony) underlying the effects of diversity on stability. Multiple regression models were then used to determine the relative importance of tree species diversity, stand structure, socio‐economic factors and environmental conditions on stability. Structural equation modelling was used to disentangle how these variables directly and/or indirectly affect forest stability. Results Tree species richness exerted a positive effect on stability through overyielding and species asynchrony, and this effect was stronger in mountainous forests than in hilly forests. Species richness positively affected the mean productivity, whereas species asynchrony negatively affected the variability in productivity, hence increasing forest stability. Structural diversity also had a positive effect, whereas population density had a negative effect on stability. Precipitation variability and slope mainly had indirect influences on stability through their effects on tree species richness. Main conclusions Overall, tree species diversity governed stability; however, stand structure, socio‐economic conditions and environmental conditions also played an important role in shaping stability in these forests. Our work highlights the importance of regulating stand structure and socio‐economic factors in forest management and biodiversity conservation, to maintain and enhance their stability to provide ecosystem services in the face of unprecedented anthropogenic activities and global climate change.

Effects of vegetation restoration on soil nutrients, plant diversity, and its spatiotemporal heterogeneity in a desert–oasis ecotone - Wu, Chunyan; Deng, Lei; Huang, Chunbo; Chen, Yongfu; Peng, Changhui (Land Degradation & Development, 2021)
Abstract Vegetation restoration has been proposed as an effective measure for rehabilitating degraded land and slowing desertification in arid regions. However, the spatial variation in soil quality and plant diversity following vegetation restoration remains unclear. This study was designed to explore soil nutrient dynamics and how soil nutrients affect plant diversity and spatial heterogeneity after shrub restoration. We assessed the effect of Haloxylon ammodendron (C.A.Mey.) Bunge (which has been planted over 30 years) on the soil nutrients and plant diversity in a desert–oasis ecotone in Minqin County, Gansu, China, using geostatistics, beta diversity and rarefaction analyses, and Hill number extrapolation. Soil nutrients, including soil organic matter, total nitrogen, and alkali nitrogen, increased significantly after H. ammodendron planting. Species richness gradually increased from 1–5 years to 10–20 years after H. ammodendron was planted but then decreased at 20–30 years. The largest differences in plant composition were observed at 15 and 20 years. Plant diversity increased in the whole 30 years after shrub planting, increasing in the first 25 years and then decreasing at 26–30 year stage. The maximum coefficient of determination for the spatial heterogeneity model fit was 0.84 (25 years). The spatial heterogeneity in vegetation decreased with increasing soil available K content at 1–10 years. Our results suggest that planting shrubs can improve soil conditions and plant species diversity in desert–oasis ecotones and soil nutrients have a strong influence on plant diversity patterns and spatial heterogeneity following vegetation restoration.

Climate Change Will Reduce the Carbon Use Efficiency of Terrestrial Ecosystems on the Qinghai-Tibet Plateau: An Analysis Based on Multiple Models - Wang, Yue; Hu, Jinming; Yang, Yanzheng; Li, Ruonan; Peng, Changhui; Zheng, Hua (Forests, 2020)
The carbon use efficiency (CUE) of ecosystems, expressed as the ratio of net primary production (NPP) and gross primary production (GPP), is extremely sensitive to climate change and has a great effect on the carbon cycles of terrestrial ecosystems. Climate change leads to changes in vegetation, resulting in different CUE values, especially on the Qinghai-Tibet Plateau, one of the most climate-sensitive regions in the world. However, the change trend and the intrinsic mechanism of climate effects on CUE in the future climate change scenario are not clear in this region. Based on the scheme of the coupled model intercomparison project (CMIP6), we analyze the simulation results of the five models of the scenario model intercomparison project (ScenarioMIP) under three different typical future climate scenarios, including SSP1-2.6, SSP3-7.0 and SSP5-8.5, on the Qinghai-Tibet Plateau in 2015–2100 with methods of model-averaging to average the long-term forecast of the five several well-known forecast models for three alternative climate scenarios with three radiative forcing levels to discuss the CUE changes and a structural equations modeling (SEM) approach to examine how the trends in GPP, NPP, and CUE related to different climate factors. The results show that (1) GPP and NPP demonstrated an upward trend in a long time series of 86 years, and the upward trend became increasingly substantial with the increase in radiation forcing; (2) the ecosystem CUE of the Qinghai-Tibet Plateau will decrease in the long time series in the future, and it shows a substantial decreasing trend with the increase in radiation forcing; and (3) the dominant climate factor affecting CUE is temperature of the factors included in these models, which affects CUE mainly through GPP and NPP to produce indirect effects. Temperature has a higher comprehensive effect on CUE than precipitation and CO2, which are negative effects on CUE on an annual scale. Our finding that the CUE decreases in the future suggests that we must pay more attention to the vegetation and CUE changes, which will produce great effects on the regional carbon dynamics and balance.

Detecting and mapping tree crowns based on convolutional neural network and Google Earth images - Yang, Mingxia; Mou, Yuling; Liu, Shan; Meng, Yanrong; Liu, Zelin; Li, Peng; Xiang, Wenhua; Zhou, Xiaolu; Peng, Changhui (International Journal of Applied Earth Observation and Geoinformation, 2022)

Estimating natural nitrous oxide emissions from the Qinghai–Tibetan Plateau using a process-based model: Historical spatiotemporal patterns and future trends - Zhang, Kerou; Peng, Changhui; Zhu, Qiuan; Li, Mingxu; Yan, Zhongqing; Li, Meng; Yan, Liang; Zhang, Xiaodong; Wang, Jinzhi; Li, Yong; Kang, Enze; Song, Hanxiong; et al. (Ecological Modelling, 2022)

Evaluating and quantifying the effect of various spruce budworm intervention strategies on forest carbon dynamics in Atlantic Canada - Liu, Zelin; Peng, Changhui; MacLean, David A.; De Grandpré, Louis; Candau, Jean-Noël; Kneeshaw, Daniel (Forest Ecosystems, 2022)

Globally limited individual and combined effects of multiple global change factors on allometric biomass partitioning - Peng, Yan; Fornara, Dario A.; Yue, Kai; Peng, Xin; Peng, Changhui; Wu, Qiqian; Ni, Xiangyin; Liao, Shu; Yang, Yusheng; Wu, Fuzhong; Peñuelas, Josep (Global Ecology and Biogeography, 2022)
Abstract Aim Plant biomass allocation reflects the distribution of photosynthates among different organs in response to changing environmental conditions. Global change influences plant growth across terrestrial ecosystems, but impacts of individual and combined multiple global change factors (GCFs) on plant biomass allocation at the global scale are unclear. Location Global. Time period Contemporary. Major taxa studied Plants in terrestrial ecosystems. Methods We conducted a meta‐analysis of data comprising 4,180 pairwise observations to assess individual and combined effects of nitrogen addition (N), warming (W), elevated CO 2 (C), irrigation (I), and drought (D) on plant biomass allocation based on the ‘ratio‐based optimal partitioning’ and ‘isometric allocation’ hypotheses. Results We found that (a) ratio‐based plant biomass fractions of different organs were only minimally affected by individual and combined effects of the studied GCFs; (b) combined effects of two‐factor pairs of GCFs on plant biomass allocation were commonly additive, rather than synergistic or antagonistic; (c) moderator variables influenced, but seldom changed the direction of individual and combined effects of GCFs on plant biomass allocation; and (d) neither individual nor combined effects of the studied GCFs altered allometric relationships among different organs, indicating that patterns of plant biomass allocation under the environmental stress conditions exerted by the multiple GCFs were better explained by the isometric allocation rather than the ratio‐based optimal partitioning hypothesis. Main conclusions Our results show consistent patterns of allometric plant biomass partitioning under effects of multiple GCFs and provide evidence of an isometric plant biomass allocation trajectory in response to global change perturbations. These findings improve our understanding and prediction of terrestrial vegetation responses to future global change scenarios.

Global patterns of particulate organic carbon export from land to the ocean - Li, Mingxu; Peng, Changhui; He, Nianpeng (Ecohydrology, 2022)
Abstract Global rivers and streams are important carbon transport pathways from land to the ocean. However, few studies have quantified terrigenous carbon dynamics in river ecosystems and its variations due to climate change and anthropogenic perturbations. Therefore, our study analysed fluvial particulate organic carbon (POC) and developed a processed‐based model (TRIPLEX‐HYDRA) to simulate the production, transport and removal (i.e., deposition, degradation and dam retention) processes of fluvial POC along the land–ocean aquatic continuum (LOAC). Based on our results, approximately 0.29 Pg of POC is exported from land to the ocean through rivers each year. More specifically, we found that rivers at low latitudes (30°S–30°N, 0.18 Pg yr −1 ) and high northern latitudes (60°N–90°N, 0.05 Pg yr −1 ) had higher POC fluxes compared to rivers in other regions. This high POC flux is related to strong erosion rates and high soil organic carbon storage. Additionally, our model simulation revealed that total POC flux from global river has not significantly changed from 1983 to 2015 but displays markedly decreased or increased trend at regional scale. These regional variations in POC export are affected by climate warming and dam construction. Moreover, approximately 0.46 Pg of POC is deposited or trapped by dams along the LOAC system, which plays a vital role in the global river carbon budget. Although some limitations and uncertainties remain, this study establishes a theoretical and methodological basis for quantifying riverine POC dynamics in the LOAC system.

Quantification of Ecosystem-Scale Methane Sinks Observed in a Tropical Rainforest in Hainan, China - Liu, Zhihao; Li, Hong; Wu, Fangtao; Wang, Hui; Chen, Huai; Zhu, Qiuan; Yang, Gang; Liu, Weiguo; Chen, Dexiang; Li, Yide; Peng, Changhui (Land, 2022)
Tropical rainforest ecosystems are important when considering the global methane (CH4) budget and in climate change mitigation. However, there is a lack of direct and year-round observations of ecosystem-scale CH4 fluxes from tropical rainforest ecosystems. In this study, we examined the temporal variations in CH4 flux at the ecosystem scale and its annual budget and environmental controlling factors in a tropical rainforest of Hainan Island, China, using 3 years of continuous eddy covariance measurements from 2016 to 2018. Our results show that CH4 uptake generally occurred in this tropical rainforest, where strong CH4 uptake occurred in the daytime, and a weak CH4 uptake occurred at night with a mean daily CH4 flux of −4.5 nmol m−2 s−1. In this rainforest, the mean annual budget of CH4 for the 3 years was −1260 mg CH4 m−2 year−1. Furthermore, the daily averaged CH4 flux was not distinctly different between the dry season and wet season. Sixty-nine percent of the total variance in the daily CH4 flux could be explained by the artificial neural network (ANN) model, with a combination of air temperature (Tair), latent heat flux (LE), soil volumetric water content (VWC), atmospheric pressure (Pa), and soil temperature at −10 cm (Tsoil), although the linear correlation between the daily CH4 flux and any of these individual variables was relatively low. This indicates that CH4 uptake in tropical rainforests is controlled by multiple environmental factors and that their relationships are nonlinear. Our findings also suggest that tropical rainforests in China acted as a CH4 sink during 2016–2018, helping to counteract global warming.

Biochar amendments increase soil organic carbon storage and decrease global warming potentials of soil CH4 and N2O under N addition in a subtropical Moso bamboo plantation - Li, Quan; Cui, Kunkai; Lv, Jianhua; Zhang, Junbo; Peng, Changhui; Li, Yongfu; Gu, Zhikang; Song, Xinzhang (Forest Ecosystems, 2022)

Recent advances in carbon footprint studies of urban ecosystems: overview, application, and future challenges - Chen, Kexin; Yang, Mingxia; Zhou, Xiaolu; Liu, Zelin; Li, Peng; Tang, Jiayi; Peng, Changhui (Environmental Reviews, 2022)
Urban ecosystems are complex systems with anthropogenic features that generate considerable CO 2 emissions, which contributes to global climate change. Quantitative estimates of the carbon footprint of urban ecosystems are crucial for developing low-carbon development policies to mitigate climate change. Herein, we reviewed more than 195 urban carbon footprint and carbon footprint related studies, collated the recent progress in carbon footprint calculation methods and research applications of the urban ecosystem carbon footprint, analyzed the research applications of the carbon footprint of different cities, and focused on the need to study the urban ecosystem carbon footprint from a holistic perspective. Specifically, we aimed to: (i) compare the strengths and weaknesses of five existing carbon footprint calculation methods [life cycle assessment, input–output analysis, hybrid life cycle assessment, carbon footprint calculator, and Intergovernmental Panel on Climate Change (IPCC)]; (ii) analyze the status of current research on the carbon footprint of different urban subregions based on different features; and (iii) highlight new methods and areas of research on the carbon footprint of future urban ecosystems. Not all carbon footprint accounting methods are applicable to the carbon footprint determination of urban ecosystems; although the IPCC method is more widely used than the others, the hybrid life cycle assessment method is more accurate. With the emergence of new science and technology, quantitative methods to calculate the carbon footprint of urban ecosystems have evolved, becoming more accurate. Further development of new technologies, such as big data and artificial intelligence, to assess the carbon footprint of urban ecosystems is anticipated to help address the emerging challenges in urban ecosystem research effectively to achieve carbon neutrality and urban sustainability under global change.

Responses of soil CH4 fluxes to nitrogen addition in two tropical montane rainforests in southern China - Wu, Fangtao; Peng, Changhui; Wang, Chuanyao; Chen, Huai; Liu, Weiguo; Liu, Zhihao; Wang, Hui; Li, Hong; Chen, Dexiang; Li, Yide; Liu, Shirong (Forest Ecosystems, 2022)

Spatiotemporal patterns and drivers of stem methane flux from two poplar forests with different soil textures - Han, Menghua; Feng, Huili; Peng, Changhui; Lei, Xiangdong; Xue, Jianhui; Malghani, Saadatullah; Ma, Xuehong; Song, Xinzhang; Wang, Weifeng (Tree Physiology, 2022)
Abstract In forest ecosystems, the majority of methane (CH4) research focuses on soils, whereas tree stem CH4 flux and driving factors remain poorly understood. We measured the in situ stem CH4 flux using the static chamber–gas chromatography method at different heights in two poplar (Populus spp.) forests with separate soil textures. We evaluated the relationship between stem CH4 fluxes and environmental factors with linear mixed models and estimated the tree CH4 emission rate at the stand level. Our results showed that poplar stems were a net source of atmospheric CH4. The mean stem CH4 emission rates were 97.51 ± 6.21 μg·m−2·h−1 in Sihong and 67.04 ± 5.64 μg·m−2·h−1 in Dongtai. The stem CH4 emission rate in Sihong with clay loam soils was significantly higher (P < 0.001) than that in Dongtai with sandy loam soils. The stem CH4 emission rate also showed a seasonal variation, minimum in winter and maximum in summer. The stem CH4 emission rate generally decreased with increasing sampling height. Although the differences in CH4 emission rates between stem heights were significant in the annual averages, these differences were driven by differences observed in the summer. Stem CH4 emission rates were significantly and positively correlated with air temperature (P < 0.001), relative humidity (P < 0.001), soil water content (P < 0.001) and soil CH4 flux (P < 0.001). At these sites, the soil emitted CH4 to the atmosphere in summer (mainly from June to September) but absorbed CH4 from the atmosphere during the other season. At the stand level, tree CH4 emissions accounted for 2–35.4% of soil CH4 uptake. Overall, tree stem CH4 efflux could be an important component of the forest CH4 budget. Therefore, it is necessary to conduct more in situ monitoring of stem CH4 flux to accurately estimate the CH4 budget in the future.

A Review of General Methods for Quantifying and Estimating Urban Trees and Biomass - Yang, Mingxia; Zhou, Xiaolu; Liu, Zelin; Li, Peng; Tang, Jiayi; Xie, Binggeng; Peng, Changhui (Forests, 2022)
Understanding the biomass, characteristics, and carbon sequestration of urban forests is crucial for maintaining and improving the quality of life and ensuring sustainable urban planning. Approaches to urban forest management have been incorporated into interdisciplinary, multifunctional, and technical efforts. In this review, we evaluate recent developments in urban forest research methods, compare the accuracy and efficiency of different methods, and identify emerging themes in urban forest assessment. This review focuses on urban forest biomass estimation and individual tree feature detection, showing that the rapid development of remote sensing technology and applications in recent years has greatly benefited the study of forest dynamics. Included in the review are light detection and ranging-based techniques for estimating urban forest biomass, deep learning algorithms that can extract tree crowns and identify tree species, methods for measuring large canopies using unmanned aerial vehicles to estimate forest structure, and approaches for capturing street tree information using street view images. Conventional methods based on field measurements are highly beneficial for accurately recording species-specific characteristics. There is an urgent need to combine multi-scale and spatiotemporal methods to improve urban forest detection at different scales.

Nitrogen addition increases CO2, CH4, and N2O concentrations of topsoils and subsoils in a subtropical Moso bamboo forest - Lv, Jianhua; Li, Quan; Zhang, Junbo; Li, Yongfu; Peng, Changhui; Song, Xinzhang (CATENA, 2022)

Responses of autumn vegetation phenology to climate change and urbanization at northern middle and high latitudes - Du, Hui; Wang, Mei; Liu, Yuxin; Guo, Mengjiao; Peng, Changhui; Li, Peng (International Journal of Applied Earth Observation and Geoinformation, 2022)

Divergent responses of autumn vegetation phenology to climate extremes over northern middle and high latitudes - Wang, Mei; Li, Peng; Peng, Changhui; Xiao, Jingfeng; Zhou, Xiaolu; Luo, Yunpeng; Zhang, Cicheng (Global Ecology and Biogeography, 2022)
Abstract Aim Compared with gradual climate change, extreme climatic events have more direct and dramatic impacts on vegetation growth. However, the influence of climate extremes on important phenological periods, such as the end of the growing season (EOS), remains unclear. Here, we investigate the temporal trends of EOS across different biomes and quantify the response of EOS to multiple climate extreme indices (CEIs). Location Northern middle and high latitudes. Time period 2000–2020. Major taxa studied Plants. Methods Three phenology extraction methods were used to compute EOS from satellite, FLUXNET and Pan European Phenology Project PEP725 phenological datasets. Different stress states of cold, hot, dry and wet extremes were represented by 12 CEIs. Partial correlation and ridge regression analysis were used to quantify the response of EOS to climate extremes across latitudinal and biome scales. Results Our study showed a delayed EOS in boreal biomes, but a significantly advanced EOS in temperate biomes. The advanced EOS induced by cold stress was observed for c . 80% of the vegetated pixels. The warm‐related CEIs delayed the EOS in high latitudes, and the delayed effect weakened or even reversed with decreasing latitude. In contrast, EOS exhibited opposite response patterns to dry days and wet‐related CEIs. Overall, EOS exhibited higher sensitivity to extreme temperature in boreal biomes than in temperate biomes. Specifically, continuous drought and high heat stress induced an earlier EOS in some temperate forest biomes, whereas moderate heat stress delayed the EOS in most study biomes. In contrast, EOS was not sensitive to extreme drought in water‐restricted biomes. Main conclusions EOS exhibited divergent responses to various climate extremes with different intensities and frequencies. Moreover, the response of EOS to extreme climate stress was dependent on the biome and latitude. These findings emphasize the importance of incorporating the divergent extreme climate effects into vegetation phenological models and Earth system models.

Integrating major agricultural practices into the TRIPLEX-GHG model v2.0 for simulating global cropland nitrous oxide emissions: Development, sensitivity analysis and site evaluation - Song, Hanxiong; Peng, Changhui; Zhang, Kerou; Zhu, Qiuan (Science of The Total Environment, 2022)

Carbon and nitrogen cycling on the Qinghai–Tibetan Plateau - Chen, Huai; Ju, Peijun; Zhu, Qiuan; Xu, Xingliang; Wu, Ning; Gao, Yongheng; Feng, Xiaojuan; Tian, Jianqing; Niu, Shuli; Zhang, Yangjian; Peng, Changhui; Wang, Yanfen (Nature Reviews Earth & Environment, 2022)

Stand carbon storage and net primary production in China’s subtropical secondary forests are predicted to increase by 2060 - Jin, Jia; Xiang, Wenhua; Zeng, Yelin; Ouyang, Shuai; Zhou, Xiaolu; Hu, Yanting; Zhao, Zhonghui; Chen, Liang; Lei, Pifeng; Deng, Xiangwen; Wang, Hui; Liu, Shirong; et al. (Carbon Balance and Management, 2022)
Abstract Background Forest ecosystems play an important role in carbon sequestration, climate change mitigation, and achieving China's target to become carbon (C) neutral by 2060. However, changes in C storage and net primary production (NPP) in natural secondary forests stemming from tree growth and future climate change have not yet been investigated in subtropical areas in China. Here, we used data from 290 inventory plots in four secondary forests [evergreen broad-leaved forest (EBF), deciduous and evergreen broad-leaved mixed forest (DEF), deciduous broad-leaved forest (DBF), and coniferous and broad-leaved mixed forest (CDF)] at different restoration stages and run a hybrid model (TRIPLEX 1.6) to predict changes in stand carbon storage and NPP under two future climate change scenarios (RCP4.5 and RCP8.5). Results The runs of the hybrid model calibrated and validated by using the data from the inventory plots suggest significant increase in the carbon storage by 2060 under the current climate conditions, and even higher increase under the RCP4.5 and RCP8.5 climate change scenarios. In contrast to the carbon storage, the simulated EBF and DEF NPP declines slightly over the period from 2014 to 2060. Conclusions The obtained results lead to conclusion that proper management of China’s subtropical secondary forests could be considered as one of the steps towards achieving China’s target to become carbon neutral by 2060.

Photosynthetic and hydraulic traits influence forest resistance and resilience to drought stress across different biomes - Hu, Yanting; Xiang, Wenhua; Schäfer, Karina V.R.; Lei, Pifeng; Deng, Xiangwen; Forrester, David I.; Fang, Xi; Zeng, Yelin; Ouyang, Shuai; Chen, Liang; Peng, Changhui (Science of The Total Environment, 2022)

Stumps increased soil respiration in a subtropical Moso bamboo (Phyllostachys edulis) plantation under nitrogen addition - Li, Quan; Ma, Qiuhui; Gao, Jinpei; Zhang, Junbo; Li, Yongfu; Shi, Man; Peng, Changhui; Song, Xinzhang (Agricultural and Forest Meteorology, 2022)

Cold‐Season Methane Fluxes Simulated by GCP‐CH4 Models - Ito, A.; Li, T.; Qin, Z.; Melton, J. R.; Tian, H.; Kleinen, T.; Zhang, W.; Zhang, Z.; Joos, F.; Ciais, P.; Hopcroft, P. O.; Beerling, D. J.; et al. (Geophysical Research Letters, 2023)
Abstract Cold‐season methane (CH 4 ) emissions may be poorly constrained in wetland models. We examined cold‐season CH 4 emissions simulated by 16 models participating in the Global Carbon Project model intercomparison and analyzed temporal and spatial patterns in simulation results using prescribed inundation data for 2000–2020. Estimated annual CH 4 emissions from northern (>60°N) wetlands averaged 10.0 ± 5.5 Tg CH 4 yr −1 . While summer CH 4 emissions were well simulated compared to in‐situ flux measurement observations, the models underestimated CH 4 during September to May relative to annual total (27 ± 9%, compared to 45% in observations) and substantially in the months with subzero air temperatures (5 ± 5%, compared to 27% in observations). Because of winter warming, nevertheless, the contribution of cold‐season emissions was simulated to increase at 0.4 ± 0.8% decade −1 . Different parameterizations of processes, for example, freezing–thawing and snow insulation, caused conspicuous variability among models, implying the necessity of model refinement. , Plain Language Summary Wetlands in the northern high latitudes are a major source of methane (CH 4 ) to the atmosphere, mainly during the warm season. Previously, models have assumed that cold‐season CH 4 emissions are low, but recent observations suggest high‐latitude wetlands can be substantial sources even in winter. We compared CH 4 emissions simulated by 16 state‐of‐the‐art wetland models, participating in a model intercomparison project with a focus on the cold‐season in northern wetlands. The model simulations indicated that nearly one third of annual emissions were simulated to occur from September to May, and CH 4 emissions to the atmosphere were not negligible even under freezing air temperatures, although the results differed greatly among the models. However, field studies suggest cold‐season emissions account for an even larger fraction of annual emissions. These results highlight the contribution of cold‐season emissions to the annual CH 4 budget, which future climatic warming is expected to affect severely, and they also show that simulations of cold‐season CH 4 emissions from wetlands need to be improved. , Key Points Cold‐season methane (CH 4 ) emissions simulated by 16 Global Carbon Project‐CH 4 wetland models were analyzed Most models underestimate the cold‐season emissions in comparison with observational data Further model improvement by including cold‐season processes is required to reduce the model bias and uncertainty

An early warning signal for grassland degradation on the Qinghai-Tibetan Plateau - Zhu, Qiuan; Chen, Huai; Peng, Changhui; Liu, Jinxun; Piao, Shilong; He, Jin-Sheng; Wang, Shiping; Zhao, Xinquan; Zhang, Jiang; Fang, Xiuqin; Jin, Jiaxin; Yang, Qi-En; et al. (Nature Communications, 2023)
Abstract Intense grazing may lead to grassland degradation on the Qinghai-Tibetan Plateau, but it is difficult to predict where this will occur and to quantify it. Based on a process-based ecosystem model, we define a productivity-based stocking rate threshold that induces extreme grassland degradation to assess whether and where the current grazing activity in the region is sustainable. We find that the current stocking rate is below the threshold in ~80% of grassland areas, but in 55% of these grasslands the stocking rate exceeds half the threshold. According to our model projections, positive effects of climate change including elevated CO 2 can partly offset negative effects of grazing across nearly 70% of grasslands on the Plateau, but only in areas below the stocking rate threshold. Our analysis suggests that stocking rate that does not exceed 60% (within 50% to 70%) of the threshold may balance human demands with grassland protection in the face of climate change.

Developing allometric equations to estimate forest biomass for tree species categories based on phylogenetic relationships - Yang, Mingxia; Zhou, Xiaolu; Peng, Changhui; Li, Tong; Chen, Kexin; Liu, Zelin; Li, Peng; Zhang, Cicheng; Tang, Jiayi; Zou, Ziying (Forest Ecosystems, 2023)

Effects of daily variation of hydro-thermal factors on alpine grassland productivity on the Qinghai-Tibet Plateau - Ma Fulin, 马扶林，刘小伟，朵莹 (Acta Ecologica Sinica, 2023)

Plant functional trait diversity and structural diversity co-underpin ecosystem multifunctionality in subtropical forests - Ouyang, Shuai; Gou, Mengmeng; Lei, Pifeng; Liu, Yue; Chen, Liang; Deng, Xiangwen; Zhao, Zhonghui; Zeng, Yelin; Hu, Yanting; Peng, Changhui; Xiang, Wenhua (Forest Ecosystems, 2023)

Soil temperature, microbial biomass and enzyme activity are the critical factors affecting soil respiration in different soil layers in Ziwuling Mountains, China - Qu, Ruosong; Liu, Guanzhen; Yue, Ming; Wang, Gangsheng; Peng, Changhui; Wang, Kefeng; Gao, Xiaoping (Frontiers in Microbiology, 2023)
Soil microorganisms are critical biological indicators for evaluating soil health and play a vital role in carbon (C)-climate feedback. In recent years, the accuracy of models in terms of predicting soil C pools has been improved by considering the involvement of microbes in the decomposition process in ecosystem models, but the parameter values of these models have been assumed by researchers without combining observed data with the models and without calibrating the microbial decomposition models. Here, we conducted an observational experiment from April 2021 to July 2022 in the Ziwuling Mountains, Loess Plateau, China, to explore the main influencing factors of soil respiration (R S ) and determine which parameters can be incorporated into microbial decomposition models. The results showed that the R S rate is significantly correlated with soil temperature (T S ) and moisture (M S ), indicating that T S increases soil C loss. We attributed the non-significant correlation between R S and soil microbial biomass carbon (MBC) to variations in microbial use efficiency, which mitigated ecosystem C loss by reducing the ability of microorganisms to decompose organic resources at high temperatures. The structural equation modeling (SEM) results demonstrated that T S , microbial biomass, and enzyme activity are crucial factors affecting soil microbial activity. Our study revealed the relations between T S , microbial biomass, enzyme activity, and R S , which had important scientific implications for constructing microbial decomposition models that predict soil microbial activity under climate change in the future. To better understand the relationship between soil dynamics and C emissions, it will be necessary to incorporate climate data as well as R S and microbial parameters into microbial decomposition models, which will be important for soil conservation and reducing soil C loss in the Loess Plateau.

Satellite monitoring reveals short-term cumulative and time-lag effect of drought and heat on autumn photosynthetic phenology in subtropical vegetation - Ren, Peixin; Li, Peng; Tang, Jiayi; Li, Tong; Liu, Zelin; Zhou, Xiaolu; Peng, Changhui (Environmental Research, 2023)

Growing season temperature and precipitation affect nutrient resorption in herbaceous species through a foliar stoichiometric control strategy - Liu, Xiaowei; Wang, Youqi; Fu, Wenhui; Yuan, Zhiyou; Yu, Qiang; Peng, Changhui; Koerner, Sally E.; Guo, Liang (Plant and Soil, 2023)

Divergent response of leaf unfolding to climate warming in subtropical and temperate zones - Yu, Haiying; Yang, Lilin; Wang, Zuhua; Guo, Liang; Peng, Changhui; Yao, Qifu; Mo, Zhongmei; Tan, Tinghong (Agricultural and Forest Meteorology, 2023)

C:N:P stoichiometry of plants, soils, and microorganisms: Response to altered precipitation - Li, Jiwei; Deng, Lei; Peñuelas, Josep; Wu, Jianzhao; Shangguan, Zhouping; Sardans, Jordi; Peng, Changhui; Kuzyakov, Yakov (Global Change Biology, 2023)
Abstract Precipitation changes modify C, N, and P cycles, which regulate the functions and structure of terrestrial ecosystems. Although altered precipitation affects above‐ and belowground C:N:P stoichiometry, considerable uncertainties remain regarding plant–microbial nutrient allocation strategies under increased (IPPT) and decreased (DPPT) precipitation. We meta‐analyzed 827 observations from 235 field studies to investigate the effects of IPPT and DPPT on the C:N:P stoichiometry of plants, soils, and microorganisms. DPPT reduced leaf C:N ratio, but increased the leaf and root N:P ratios reflecting stronger decrease of P compared with N mobility in soil under drought. IPPT increased microbial biomass C (+13%), N (+15%), P (26%), and the C:N ratio, whereas DPPT decreased microbial biomass N (−12%) and the N:P ratio. The C:N and N:P ratios of plant leaves were more sensitive to medium DPPT than to IPPT because drought increased plant N content, particularly in humid areas. The responses of plant and soil C:N:P stoichiometry to altered precipitation did not fit the double asymmetry model with a positive asymmetry under IPPT and a negative asymmetry under extreme DPPT. Soil microorganisms were more sensitive to IPPT than to DPPT, but they were more sensitive to extreme DPPT than extreme IPPT, consistent with the double asymmetry model. Soil microorganisms maintained stoichiometric homeostasis, whereas N:P ratios of plants follow that of the soils under altered precipitation. In conclusion, specific N allocation strategies of plants and microbial communities as well as N and P availability in soil critically mediate C:N:P stoichiometry by altered precipitation that need to be considered by prediction of ecosystem functions and C cycling under future climate change scenarios.

Characterizing Performance of Freshwater Wetland Methane Models Across Time Scales at FLUXNET‐CH4 Sites Using Wavelet Analyses - Zhang, Zhen; Bansal, Sheel; Chang, Kuang‐Yu; Fluet‐Chouinard, Etienne; Delwiche, Kyle; Goeckede, Mathias; Gustafson, Adrian; Knox, Sara; Leppänen, Antti; Liu, Licheng; Liu, Jinxun; Malhotra, Avni; et al. (Journal of Geophysical Research: Biogeosciences, 2023)
Abstract Process‐based land surface models are important tools for estimating global wetland methane (CH 4 ) emissions and projecting their behavior across space and time. So far there are no performance assessments of model responses to drivers at multiple time scales. In this study, we apply wavelet analysis to identify the dominant time scales contributing to model uncertainty in the frequency domain. We evaluate seven wetland models at 23 eddy covariance tower sites. Our study first characterizes site‐level patterns of freshwater wetland CH 4 fluxes (FCH 4 ) at different time scales. A Monte Carlo approach was developed to incorporate flux observation error to avoid misidentification of the time scales that dominate model error. Our results suggest that (a) significant model‐observation disagreements are mainly at multi‐day time scales (<15 days); (b) most of the models can capture the CH 4 variability at monthly and seasonal time scales (>32 days) for the boreal and Arctic tundra wetland sites but have significant bias in variability at seasonal time scales for temperate and tropical/subtropical sites; (c) model errors exhibit increasing power spectrum as time scale increases, indicating that biases at time scales <5 days could contribute to persistent systematic biases on longer time scales; and (d) differences in error pattern are related to model structure (e.g., proxy of CH 4 production). Our evaluation suggests the need to accurately replicate FCH 4 variability, especially at short time scales, in future wetland CH 4 model developments. , Plain Language Summary Land surface models are useful tools to estimate and predict wetland methane (CH 4 ) flux but there is no evaluation of modeled CH 4 flux error at different time scales. Here we use a statistical approach and observations from eddy covariance sites to evaluate the performance of seven wetland models for different wetland types. The results suggest models have captured CH 4 flux variability at monthly or seasonal time scales for boreal and Arctic tundra wetlands but failed to capture the observed seasonal variability for temperate and tropical/subtropical wetlands. The analysis suggests that improving modeled flux at short time scale is important for future model development. , Key Points Significant model‐observation disagreements were found at multi‐day and weekly time scales (<15 days) Models captured variability at monthly and seasonal time (42–142 days) scales for boreal and Arctic tundra sites but not for temperate and tropical sites The model errors show that biases at multi‐day time scales may contribute to persistent systematic biases on longer time scales

Research progress, challenges, and prospects of PM2.5 concentration estimation using satellite data - Zhu, Shoutao; Tang, Jiayi; Zhou, Xiaolu; Li, Peng; Liu, Zelin; Zhang, Cicheng; Zou, Ziying; Li, Tong; Peng, Changhui (Environmental Reviews, 2023)
Satellite data are vital for understanding the large-scale spatial distribution of particulate matter (PM 2.5 ) due to their low cost, wide coverage, and all-weather capability. Estimation of PM 2.5 using satellite aerosol optical depth (AOD) products is a popular method. In this paper, we review the PM 2.5 estimation process based on satellite AOD data in terms of data sources (i.e., inversion algorithms, data sets, and interpolation methods), estimation models (i.e., statistical regression, chemical transport models, machine learning, and combinatorial analysis), and modeling validation (i.e., four types of cross-validation (CV) methods). We found that the accuracy of time-based CV is lower than others. We found significant differences in modeling accuracy between different seasons ( p < 0.01) and different spatial resolutions ( p < 0.01). We explain these phenomena in this article. Finally, we summarize the research process, present challenges, and future directions in this field. We opine that low-cost mobile devices combined with transfer learning or hybrid modeling offer research opportunities in areas with limited PM 2.5 monitoring stations and historical PM 2.5 estimation. These methods can be a good choice for air pollution estimation in developing countries. The purpose of this study is to provide a basic framework for future researchers to conduct relevant research, enabling them to understand current research progress and future research directions.

Can forest carbon sequestration offset industrial CO2 emissions? A case study of Hubei Province, China - Cheng, Jing; Huang, Chunbo; Gan, Xintao; Peng, Changhui; Deng, Lei (Journal of Cleaner Production, 2023)

Temporal and spatial variation of vegetation photosynthetic phenology in Dongting Lake basin and its response to climate change - Ren, Pei-Xin; Li, Peng; Peng, Chang-Hui; Zhou, Xiao-Lu; Yang, Ming-Xia; 1College of Geographic Sciences, Hunan Normal University, Changsha 410081, China; 2Department of Biology Sciences, Institute of Environment Sciences, University of Quebec at Montreal, Montreal H3C 3P8, Canada (Chinese Journal of Plant Ecology, 2023)

Divergent response of vegetation phenology to extreme temperatures and precipitation of different intensities on the Tibetan Plateau - Sun, Mai; Li, Peng; Ren, Peixin; Tang, Jiayi; Zhang, Cicheng; Zhou, Xiaolu; Peng, Changhui (Science China Earth Sciences, 2023)

Application of climate change scenarios in the simulation of forest ecosystems: an overview - Liu, Haoyun; Li, Peng; Peng, Changhui; Liu, Cong; Zhou, Xiaolu; Deng, Zhengmiao; Zhang, Cicheng; Liu, Zelin (Environmental Reviews, 2023)
Climate change scenarios established by the Intergovernmental Panel on Climate Change have developed a significant tool for analyzing, modeling, and predicting future climate change impacts in different research fields after more than 30 years of development and refinement. In the wake of future climate change, the changes in forest structure and functions have become a frontier and focal area of global change research. This study mainly reviews and synthesizes climate change scenarios and their applications in forest ecosystem research over the past decade. These applications include changes in (1) forest structure and spatial vegetation distribution, (2) ecosystem structure, (3) ecosystem services, and (4) ecosystem stability. Although climate change scenarios are useful for predicting future climate change impacts on forest ecosystems, the accuracy of model simulations needs to be further improved. Based on existing studies, climate change scenarios are used in future simulation applications to construct a biomonitoring network platform integrating observations and predictions for better conservation of species diversity.

Carbon fluxes and soil carbon dynamics along a gradient of biogeomorphic succession in alpine wetlands of Tibetan Plateau - Wang, Hao; Yu, Lingfei; Chen, Litong; Zhang, Zhenhua; Li, Xuefei; Liang, Naishen; Peng, Changhui; He, Jin-Sheng (Fundamental Research, 2023)

Soil-atmosphere exchange of carbon dioxide, methane and nitrous oxide in temperate forests along an elevation gradient in the Qinling Mountains, China - Pang, Junzhu; Peng, Changhui; Wang, Xiaoke; Zhang, Hongxing; Zhang, Shuoxin (Plant and Soil, 2023)

rTRIPLEXCWFlux: An R package for carbon–water coupling model to simulate net ecosystem productivity and evapotranspiration in forests - Sun, Shulan; Ouyang, Shuai; Hu, Yanting; Zhao, Zhonghui; Liu, Meixian; Chen, Liang; Zeng, Yelin; Peng, Changhui; Zhou, Xiaolu; Xiang, Wenhua (Environmental Modelling & Software, 2023)

Carbon in Chinese grasslands: meta-analysis and theory of grazing effects - Deng, Lei; Shangguan, Zhouping; Bell, Stephen Mackenzie; Soromotin, Andrey V.; Peng, Changhui; An, Shaoshan; Wu, Xing; Xu, Xingliang; Wang, Kaibo; Li, Jianping; Tang, Zhuangsheng; Yan, Weiming; et al. (Carbon Research, 2023)
Abstract Globally, livestock grazing is an important management factor influencing soil degradation, soil health and carbon (C) stocks of grassland ecosystems. However, the effects of grassland types, grazing intensity and grazing duration on C stocks are unclear across large geographic scales. To provide a more comprehensive assessment of how grazing drives ecosystem C stocks in grasslands, we compiled and analyzed data from 306 studies featuring four grassland types across China: desert steppes, typical steppes, meadow steppes and alpine steppes. Light grazing was the best management practice for desert steppes (< 2 sheep ha −1 ) and typical steppes (3 to 4 sheep ha −1 ), whereas medium grazing pressure was optimal for meadow steppes (5 to 6 sheep ha −1 ) and alpine steppes (7 to 8 sheep ha −1 ) leading to the highest ecosystem C stocks under grazing. Plant biomass (desert steppes) and soil C stocks (meadow steppes) increased under light or medium grazing, confirming the ‘ intermediate disturbance hypothesis ’. Heavy grazing decreased all C stocks regardless of grassland ecosystem types, approximately 1.4 Mg ha −1 per year for the whole ecosystem. The regrowth and regeneration of grasslands in response to grazing intensity (i.e., grazing optimization ) depended on grassland types and grazing duration. In conclusion, grassland grazing is a double-edged sword. On the one hand, proper management (light or medium grazing) can maintain and even increase C stocks above- and belowground, and increase the harvested livestock products from grasslands. On the other hand, human-induced overgrazing can lead to rapid degradation of vegetation and soils, resulting in significant carbon loss and requiring long-term recovery. Grazing regimes (i.e., intensity and duration applied) must consider specific grassland characteristics to ensure stable productivity rates and optimal impacts on ecosystem C stocks. Graphical Abstract

Global estimates of forest soil methane flux identify a temperate and tropical forest methane sink - Feng, Huili; Guo, Jiahuan; Peng, Changhui; Ma, Xuehong; Kneeshaw, Daniel; Chen, Huai; Liu, Qiuyu; Liu, Mengyao; Hu, Cheng; Wang, Weifeng (Geoderma, 2023)

Global Climate Change Increases Terrestrial Soil CH4 Emissions - Guo, Jiahuan; Feng, Huili; Peng, Changhui; Chen, Huai; Xu, Xuan; Ma, Xuehong; Li, Li; Kneeshaw, Daniel; Ruan, Honghua; Yang, Hongqiang; Wang, Weifeng (Global Biogeochemical Cycles, 2023)
Abstract Increased greenhouse gas emissions are causing unprecedented climate change, which is, in turn, altering emissions and removals (referring to the oxidation of atmospheric CH 4 by methanotrophs within the soil) of the atmospheric CH 4 in terrestrial ecosystems. In the global CH 4 budget, wetlands are the dominant natural source and upland soils are the primary biological sink. However, it is unclear whether and how the soil CH 4 exchanges across terrestrial ecosystems and the atmosphere will be affected by warming and changes in precipitation patterns. Here, we synthesize 762 observations of in situ soil CH 4 flux data based on the chamber method from the past three decades related to temperature and precipitation changes across major terrestrial ecosystems worldwide. Our meta‐analysis reveals that warming (average warming of +2°C) promotes upland soil CH 4 uptake and wetland soil CH 4 emission. Decreased precipitation (ranging from −100% to −7% of local mean annual precipitation) stimulates upland soil CH 4 uptake. Increased precipitation (ranging from +4% to +94% of local mean annual precipitation) accelerates the upland soil CH 4 emission. By 2100, under the shared socioeconomic pathway with a high radiative forcing level (SSP585), CH 4 emissions from global terrestrial ecosystems will increase by 22.8 ± 3.6 Tg CH 4 yr −1 as an additional CH 4 source, which may be mainly attributed to the increase in precipitation over 30°N latitudes. Our meta‐analysis strongly suggests that future climate change would weaken the natural buffering ability of terrestrial ecosystems on CH 4 fluxes and thus contributes to a positive feedback spiral. , Plain Language Summary This study is the first investigation to include scenarios of CH 4 sink–source transition due to climate change and provides the global estimate of soil CH 4 budgets in natural terrestrial ecosystems in the context of climate change. The enhanced effect of climate change on CH 4 emissions was mainly attributed to increased CH 4 emissions from natural upland ecosystems. Although an increased CH 4 uptake by forest and grassland soils caused by increased temperature and decreased precipitation can offset some part of additional CH 4 sources, the substantial increase of increased precipitation on CH 4 emissions makes these sinks insignificant. These findings highlight that future climate change would weaken the natural buffering ability of terrestrial ecosystems on CH 4 emissions and thus form a positive feedback spiral between methane emissions and climate change. , Key Points This study is the first CH 4 budget investigation to include CH 4 sink‐source transition due to climate change Climate change is estimated to add 22.8 ± 3.6 Tg CH 4 yr −1 emission by 2100 under the high socioeconomic pathway Climate change weakens the buffering capacity of upland soils to CH 4 emissions

Predicting potential climate change impacts of bioenergy from perennial grasses in 2050 - Liu, Weiguo; Wang, Kui; Hao, Hongke; Yan, Yan; Zhang, Han; Zhang, Huanling; Peng, Changhui (Resources, Conservation and Recycling, 2023)

Drought‐induced increase in tree mortality and corresponding decrease in the carbon sink capacity of Canada's boreal forests from 1970 to 2020 - Liu, Qiuyu; Peng, Changhui; Schneider, Robert; Cyr, Dominic; McDowell, Nate G.; Kneeshaw, Daniel (Global Change Biology, 2023)
Abstract Canada's boreal forests, which occupy approximately 30% of boreal forests worldwide, play an important role in the global carbon budget. However, there is little quantitative information available regarding the spatiotemporal changes in the drought‐induced tree mortality of Canada's boreal forests overall and their associated impacts on biomass carbon dynamics. Here, we develop spatiotemporally explicit estimates of drought‐induced tree mortality and corresponding biomass carbon sink capacity changes in Canada's boreal forests from 1970 to 2020. We show that the average annual tree mortality rate is approximately 2.7%. Approximately 43% of Canada's boreal forests have experienced significantly increasing tree mortality trends (71% of which are located in the western region of the country), and these trends have accelerated since 2002. This increase in tree mortality has resulted in significant biomass carbon losses at an approximate rate of 1.51 ± 0.29 MgC ha −1 year −1 (95% confidence interval) with an approximate total loss of 0.46 ± 0.09 PgC year −1 (95% confidence interval). Under the drought condition increases predicted for this century, the capacity of Canada's boreal forests to act as a carbon sink will be further reduced, potentially leading to a significant positive climate feedback effect.

Quantifying patterns, sources and uncertainty of nitrous oxide emissions from global grazing lands: Nitrogen forms are the determinant factors for estimation and mitigation - Song, Hanxiong; Peng, Changhui; Zhang, Kerou; Li, Tong; Yang, Mingxia; Liu, Qiuyu; Zhu, Qiuan (Global and Planetary Change, 2023)

Vegetation browning: global drivers, impacts, and feedbacks - Liu, Qiuyu; Peng, Changhui; Schneider, Robert; Cyr, Dominic; Liu, Zelin; Zhou, Xiaolu; Du, Mingxi; Li, Peng; Jiang, Zihan; McDowell, Nate G.; Kneeshaw, Daniel (Trends in Plant Science, 2023)

Nitrogen addition promotes terrestrial plants to allocate more biomass to aboveground organs: A global meta‐analysis - Feng, Huili; Guo, Jiahuan; Peng, Changhui; Kneeshaw, Daniel; Roberge, Gabrielle; Pan, Chang; Ma, Xuehong; Zhou, Dan; Wang, Weifeng (Global Change Biology, 2023)
Abstract A significant increase in reactive nitrogen (N) added to terrestrial ecosystems through agricultural fertilization or atmospheric deposition is considered to be one of the most widespread drivers of global change. Modifying biomass allocation is one primary strategy for maximizing plant growth rate, survival, and adaptability to various biotic and abiotic stresses. However, there is much uncertainty as to whether and how plant biomass allocation strategies change in response to increased N inputs in terrestrial ecosystems. Here, we synthesized 3516 paired observations of plant biomass and their components related to N additions across terrestrial ecosystems worldwide. Our meta‐analysis reveals that N addition (ranging from 1.08 to 113.81 g m −2 year −1 ) increased terrestrial plant biomass by 55.6% on average. N addition has increased plant stem mass fraction, shoot mass fraction, and leaf mass fraction by 13.8%, 12.9%, and 13.4%, respectively, but with an associated decrease in plant reproductive mass (including flower and fruit biomass) fraction by 3.4%. We further documented a reduction in plant root‐shoot ratio and root mass fraction by 27% (21.8%–32.1%) and 14.7% (11.6%–17.8%), respectively, in response to N addition. Meta‐regression results showed that N addition effects on plant biomass were positively correlated with mean annual temperature, soil available phosphorus, soil total potassium, specific leaf area, and leaf area per plant. Nevertheless, they were negatively correlated with soil total N, leaf carbon/N ratio, leaf carbon and N content per leaf area, as well as the amount and duration of N addition. In summary, our meta‐analysis suggests that N addition may alter terrestrial plant biomass allocation strategies, leading to more biomass being allocated to aboveground organs than belowground organs and growth versus reproductive trade‐offs. At the global scale, leaf functional traits may dictate how plant species change their biomass allocation pattern in response to N addition.

Integrating terrestrial and aquatic ecosystems to constrain estimates of land-atmosphere carbon exchange - Casas-Ruiz, Joan P.; Bodmer, Pascal; Bona, Kelly Ann; Butman, David; Couturier, Mathilde; Emilson, Erik J. S.; Finlay, Kerri; Genet, Hélène; Hayes, Daniel; Karlsson, Jan; Paré, David; Peng, Changhui; et al. (Nature Communications, 2023)
Abstract In this Perspective, we put forward an integrative framework to improve estimates of land-atmosphere carbon exchange based on the accumulation of carbon in the landscape as constrained by its lateral export through rivers. The framework uses the watershed as the fundamental spatial unit and integrates all terrestrial and aquatic ecosystems as well as their hydrologic carbon exchanges. Application of the framework should help bridge the existing gap between land and atmosphere-based approaches and offers a platform to increase communication and synergy among the terrestrial, aquatic, and atmospheric research communities that is paramount to advance landscape carbon budget assessments.

Time-lag effects of flood stimulation on methane emissions in the Dongting Lake floodplain, China - Wang, Tao; Deng, Zhengmiao; Xie, Yonghong; Wang, Buqing; Wu, Shaoan; Li, Feng; Wang, Wei; Zou, Yeai; Li, Xu; Hou, Zhiyong; Zeng, Jing; Wang, Mei; et al. (Agricultural and Forest Meteorology, 2023)

Eco-CCUS: A cost-effective pathway towards carbon neutrality in China - Li, Mingxu; He, Nianpeng; Xu, Li; Peng, Changhui; Chen, Huai; Yu, Guirui (Renewable and Sustainable Energy Reviews, 2023)

Climate change mitigation potential of kitchen waste utilization in China for combined heat and power production - Liu, Weiguo; Zhang, Dan; Tian, Jiajing; Yu, Feiyan; Xie, Yuanming; Cheng, Shengkui; Li, Qiang; Li, Weizhong; Peng, Changhui; Yan, Yan (Science of The Total Environment, 2023)

Climatic drivers and ecological implications of variation in the time interval between leaf-out and flowering - Guo, Liang; Liu, Xiaowei; Alatalo, Juha M.; Wang, Chuanyao; Xu, Jianchu; Yu, Haiying; Chen, Ji; Yu, Qiang; Peng, Changhui; Dai, Junhu; Luedeling, Eike (Current Biology, 2023)

Observational constraints reduce model spread but not uncertainty in global wetland methane emission estimates - Chang, Kuang‐Yu; Riley, William J.; Collier, Nathan; McNicol, Gavin; Fluet‐Chouinard, Etienne; Knox, Sara H.; Delwiche, Kyle B.; Jackson, Robert B.; Poulter, Benjamin; Saunois, Marielle; Chandra, Naveen; Gedney, Nicola; et al. (Global Change Biology, 2023)
Abstract The recent rise in atmospheric methane (CH 4 ) concentrations accelerates climate change and offsets mitigation efforts. Although wetlands are the largest natural CH 4 source, estimates of global wetland CH 4 emissions vary widely among approaches taken by bottom‐up (BU) process‐based biogeochemical models and top‐down (TD) atmospheric inversion methods. Here, we integrate in situ measurements, multi‐model ensembles, and a machine learning upscaling product into the International Land Model Benchmarking system to examine the relationship between wetland CH 4 emission estimates and model performance. We find that using better‐performing models identified by observational constraints reduces the spread of wetland CH 4 emission estimates by 62% and 39% for BU‐ and TD‐based approaches, respectively. However, global BU and TD CH 4 emission estimate discrepancies increased by about 15% (from 31 to 36 TgCH 4 year −1 ) when the top 20% models were used, although we consider this result moderately uncertain given the unevenly distributed global observations. Our analyses demonstrate that model performance ranking is subject to benchmark selection due to large inter‐site variability, highlighting the importance of expanding coverage of benchmark sites to diverse environmental conditions. We encourage future development of wetland CH 4 models to move beyond static benchmarking and focus on evaluating site‐specific and ecosystem‐specific variabilities inferred from observations.

Grazing alters vegetation phenology by regulating regional environmental factors on the Tibetan Plateau - Wang, Longjun; Li, Peng; Li, Tong; Zhou, Xiaolu; Liu, Zelin; Zou, Ziying; Zhu, Qiuan; Peng, Changhui (Agriculture, Ecosystems & Environment, 2023)

Stable oxic-anoxic transitional interface is beneficial to retard soil carbon loss in drained peatland - Liu, Liangfeng; Tian, Jianqing; Wang, Hongjun; Xue, Dan; Huang, Xinya; Wu, Ning; Wang, Meng; Xu, Xingliang; Peng, Changhui; Wang, Yanfen; Chen, Huai (Soil Biology and Biochemistry, 2023)

The microbial mechanisms by which long-term heavy metal contamination affects soil organic carbon levels - Xiao, Zhineng; Duan, Changqun; Li, Shiyu; Chen, Ji; Peng, Changhui; Che, Rongxiao; Liu, Chang'e; Huang, Yin; Mei, Runran; Xu, Liangliang; Luo, Pengfei; Yu, Yadong (Chemosphere, 2023)

Global net climate effects of anthropogenic reactive nitrogen - Gong, Cheng; Tian, Hanqin; Liao, Hong; Pan, Naiqing; Pan, Shufen; Ito, Akihiko; Jain, Atul K.; Kou-Giesbrecht, Sian; Joos, Fortunat; Sun, Qing; Shi, Hao; Vuichard, Nicolas; et al. (Nature, 2024)
Abstract Anthropogenic activities have substantially enhanced the loadings of reactive nitrogen (Nr) in the Earth system since pre-industrial times 1,2 , contributing to widespread eutrophication and air pollution 3–6 . Increased Nr can also influence global climate through a variety of effects on atmospheric and land processes but the cumulative net climate effect is yet to be unravelled. Here we show that anthropogenic Nr causes a net negative direct radiative forcing of −0.34 [−0.20, −0.50] W m −2 in the year 2019 relative to the year 1850. This net cooling effect is the result of increased aerosol loading, reduced methane lifetime and increased terrestrial carbon sequestration associated with increases in anthropogenic Nr, which are not offset by the warming effects of enhanced atmospheric nitrous oxide and ozone. Future predictions using three representative scenarios show that this cooling effect may be weakened primarily as a result of reduced aerosol loading and increased lifetime of methane, whereas in particular N 2 O-induced warming will probably continue to increase under all scenarios. Our results indicate that future reductions in anthropogenic Nr to achieve environmental protection goals need to be accompanied by enhanced efforts to reduce anthropogenic greenhouse gas emissions to achieve climate change mitigation in line with the Paris Agreement.

The effects of environmental factors and plant diversity on forest carbon sequestration vary between eastern and western regions of China - Chen, Kexin; Li, Tong; Yang, Mingxia; Zhou, Xiaolu; Peng, Changhui (Journal of Cleaner Production, 2024)

Fire effects on soil CH4 and N2O fluxes across terrestrial ecosystems - Guo, Jiahuan; Feng, Huili; Peng, Changhui; Du, Juan; Wang, Weifeng; Kneeshaw, Daniel; Pan, Chang; Roberge, Gabrielle; Feng, Lei; Chen, Anping (Science of The Total Environment, 2024)

Differential Responses of Soil Microbial and Carbon‐Nitrogen Processes to Future Environmental Changes Across Soil Depths and Environmental Factors - Wang, Kefeng; Wang, Gangsheng; Qu, Ruosong; Huang, Wenjuan; Zhou, Guoyi; Yue, Ming; Peng, Changhui (Earth's Future, 2024)
Abstract Accurately predicting carbon‐climate feedbacks relies on understanding the environmental factors regulating soil organic carbon (SOC) storage and dynamics. Here, we employed a microbial ecological model (MEND), driven by downscaled output data from six Earth system models under two Shared Socio‐economic Pathways (SSP1‐2.6 and SSP5‐8.5) scenarios, to simulate long‐term soil biogeochemical processes. We aim to analyze the responses of soil microbial and carbon‐nitrogen (C‐N) processes to changes in environmental factors, including litter input (L), soil moisture (W) and temperature (T), and soil pH, in a broadleaf forest (BF) and a pine forest (PF). For the entire soil layer in both forests, we found that, compared to the baseline period of 2009–2020, the mean SOC during 2081–2100 increased by 40.9%–90.6% under the L or T change scenarios, versus 5.2%–31.0% under the W change scenario. However, soil moisture emerged as a key regulator of SOC, MBC and inorganic N dynamics in the topsoil of BF and PF. For example, W change led to SOC gain of 5.5%–37.2%, compared to the SOC loss of 15.5%–18.0% under L or T scenario. Additionally, a further reduction in soil pH by 0.2 units in the BF, representing the acid rain effect, significantly resulted in an additional SOC gain by 14.2%–21.3%, compared to the LTW (simultaneous changes in the three factors) scenario. These results indicate that the results derived solely from topsoil may not be extrapolated to the entire soil profile. Overall, this study significantly advances our comprehension of how different environmental factors impact the dynamics of SOC and the implications they have for climate change. , Plain Language Summary Accurately predicting carbon‐climate feedbacks relies on understanding the environmental factors regulating soil organic carbon (SOC) storage and dynamics. We aim to analyze the responses of soil microbial and carbon‐nitrogen (C‐N) processes to changes in environmental factors, including litter input (L), soil moisture (W) and temperature (T), and soil pH, in a broadleaf forest (BF) and a pine forest (PF). We found that soil moisture change would be beneficial for SOC accumulation and serves as a key regulator of MBC and inorganic N in topsoil, whereas the change in litterfall or soil temperature are favorable for SOC accumulation in the entire soil profile. Additionally, a further reduction in soil pH by 0.2 units, representing the acid rain effect, significantly resulted in an additional SOC gain by 14.2%–21.3%, compared to the scenario with simultaneous changes in L, W, and T. These results indicate that findings solely from topsoil may not be extrapolated to the entire soil profile. Overall, this study significantly advances our comprehension of how different environmental factors impact the dynamics of SOC and the implications they have for climate change. , Key Points Soil C responses to climate change are depth dependent, therefore, results from just the topsoil may not apply to the entire soil profile Soil moisture change benefits topsoil SOC accumulation, whereas litterfall and soil temperature changes favor SOC accumulation in the entire soil profile We need to pay more attention to the effects of soil moisture and pH rather than temperature and litter‐input on soil biogeochemical processes

Impacts of landscape dynamics on terrestrial ecosystem health in the Three Gorges Reservoir Area, China - Huang, Chunbo; Cheng, Jing; Liu, Shuangshuang; Wan, Yunshan; Zhou, Jie; Liu, Zelin; Peng, Changhui (Journal of Cleaner Production, 2024)

Comparing standardised precipitation and barley yield across Quebec - Epule, Terence Epule; Poirier, Vincent; Lafontaine, Simon; Peng, Changhui (Environmental Science and Pollution Research, 2024)

Divergent contributions of spring and autumn photosynthetic phenology to seasonal carbon uptake of subtropical vegetation in China - Peng, Ying; Li, Peng; Zhou, Xiaolu; Luo, Yunpeng; Zhang, Cicheng; Wang, Longjun; Li, Tong; Peng, Changhui (Journal of Geographical Sciences, 2024)

Impacts of environmental and socioeconomic factors on gross ecosystem product of the Three Gorges reservoir area, China - Cheng, Jing; Liu, Shuangshuang; Huang, Chunbo; Wang, Lunche; Liu, Zelin; Peng, Changhui (Land Degradation & Development, 2024)
Abstract Environmental and socioeconomic drivers would alter landscapes, bringing various effects with different directions and magnitudes. Demonstrating these driving effects is key to relieving the conflicts between territorial vegetation restoration and regional economic growth. However, the relationship between ecological protection and economic development due to landscape dynamics has not been systematically demonstrated as environment is difficult to quantify by the monetary value. In this article, we explored the changes in gross ecosystem product (GEP) in the Three Gorges (TG) reservoir area and constructed a conceptual framework to explicate its driving mechanism. Our results suggested that topographic, soil, and climatic factors positively impact on GEP through their important effects on vegetation structure, distribution, and succession. Additionally, reforestation policies promote the conversion of farmland and grassland to forestland in the TG reservoir region, which was the main contributor to enhancing GEP. Conversely, socioeconomic factors negatively impact GEP, of which effects were mainly manifested by changes in the proportion of ecological land. Therefore, it is essential to maintain a suitable land use proportion in this region to optimize GEP, and we proposed a landscape restoration program to enhance four ecosystem productions. This article provides a reference for land resource allocation for environmental protection and sustainable development in ecologically fragile areas.

Phenolic compounds weaken the impact of drought on soil enzyme activity in global wetlands - Li, Tong; Ge, Leming; Zhao, Ruotong; Peng, Changhui; Zhou, Xiaolu; Li, Peng; Liu, Zelin; Song, Hanxiong; Tang, Jiayi; Zhang, Cicheng; Li, Quan; Wang, Meng; et al. (Frontiers in Microbiology, 2024)
Soil enzymes play a central role in carbon and nutrient cycling, and their activities can be affected by drought-induced oxygen exposure. However, a systematic global estimate of enzyme sensitivity to drought in wetlands is still lacking. Through a meta-analysis of 55 studies comprising 761 paired observations, this study found that phosphorus-related enzyme activity increased by 38% as result of drought in wetlands, while the majority of other soil enzyme activities remained stable. The expansion of vascular plants under long-term drought significantly promoted the accumulation of phenolic compounds. Using a 2-week incubation experiment with phenol supplementation, we found that phosphorus-related enzyme could tolerate higher biotoxicity of phenolic compounds than other enzymes. Moreover, a long-term (35 years) drainage experiment in a northern peatland in China confirmed that the increased phenolic concentration in surface layer resulting from a shift in vegetation composition inhibited the increase in enzyme activities caused by rising oxygen availability, except for phosphorus-related enzyme. Overall, these results demonstrate the complex and resilient nature of wetland ecosystems, with soil enzymes showing a high degree of adaptation to drought conditions. These new insights could help evaluate the impact of drought on future wetland ecosystem services and provide a theoretical foundation for the remediation of degraded wetlands.

Climate warming accelerates carbon release from foliar litter—A global synthesis - Chen, Zihao; Ni, Xiangyin; Patoine, Guillaume; Peng, Changhui; Yue, Kai; Yuan, Ji; Wu, Qiuxia; Eisenhauer, Nico; Guerra, Carlos A.; Bol, Roland; Wu, Fuzhong; Wang, G. Geoff (Global Change Biology, 2024)
Abstract With over one‐third of terrestrial net primary productivity transferring to the litter layer annually, the carbon release from litter serves as a crucial valve in atmospheric carbon dioxide concentrations. However, few quantitative global projections of litter carbon release rate in response to climate change exist. Here, we combined a global foliar litter carbon release dataset (8973 samples) to generate spatially explicitly estimates of the response of their residence time ( τ ) to climate change. Results show a global mean litter carbon release rate () of 0.69 year −1 (ranging from 0.09–5.6 year −1 ). Under future climate scenarios, global mean τ is projected to decrease by a mean of 2.7% (SSP 1–2.6) and 5.9% (SSP 5–8.5) during 2071–2100 period. Locally, the alleviation of temperature and moisture restrictions corresponded to obvious decreases in τ in cold and arid regions, respectively. In contract, τ in tropical humid broadleaf forests increased by 4.6% under SSP 5–8.5. Our findings highlight the vegetation type as a powerful proxy for explaining global patterns in foliar litter carbon release rates and the role of climate conditions in predicting responses of carbon release to climate change. Our observation‐based estimates could refine carbon cycle parameterization, improving projections of carbon cycle–climate feedbacks.

An optimized water table depth detected for mitigating global warming potential of greenhouse gas emissions in wetland of Qinghai-Tibetan Plateau - Zhang, Jiang; Chen, Huai; Wang, Meng; Liu, Xinwei; Peng, Changhui; Wang, Le; Yu, Dongxue; Zhu, Qiuan (iScience, 2024)

Responses of C:N:P stoichiometric correlations among plants, soils and microorganisms to warming: A meta-analysis - Yu, Zongkai; Zhang, Chao; Liu, Xiaowei; Lei, Jichu; Zhang, Qiang; Yuan, Zhiyou; Peng, Changhui; Koerner, Sally E.; Xu, Jianchu; Guo, Liang (Science of The Total Environment, 2024)

Potential future changes in soil carbon dynamics in the Ziwuling Forest, China under different climate change scenarios - Qu, Ruosong; Chen, Shiyi; Wang, Kefeng; Liu, Qiuyu; Yang, Bin; Yue, Ming; Peng, Changhui (Science of The Total Environment, 2024)

Effects of street plants on atmospheric particulate dispersion in urban streets: A review - Wang, Xiaoshuang; Zhou, Zhixiang; Xiang, Yang; Peng, Chucai; Peng, Changhui (Environmental Reviews, 2024)
Numerous empirical studies have demonstrated that street trees not only reduce dust pollution and absorb particulate matter (PM) but also improve microclimates, providing both ecological functions and aesthetic value. However, recent research has revealed that street tree canopy cover can impede the dispersion of atmospheric PM within street canyons, leading to the accumulation of street pollutants. Although many studies have investigated the impact of street trees on air pollutant dispersion within street canyons, the extent of their influence remains unclear and uncertain. Pollutant accumulation corresponds to the specific characteristics of individual street canyons, coupled with meteorological factors and pollution source strength. Notably, the characteristics of street tree canopy cover also exert a significant influence. There is still a quantitative research gap on street tree cover impacts with respect to pollution and dust reduction control measures within street spaces. To improve urban traffic environments, policymakers have mainly focused on scientifically based street vegetation deployment initiatives in building ecological garden cities and improving the living environment. To address uncertainties regarding the influence of street trees on the dispersion of atmospheric PM in urban streets, this study reviews dispersion mechanisms and key atmospheric PM factors in urban streets, summarizes the research approaches used to conceptualize atmospheric PM dispersion in urban street canyons, and examines urban plant efficiency in reducing atmospheric PM. Furthermore, we also address current challenges and future directions in this field to provide a more comprehensive understanding of atmospheric PM dispersion in urban streets and the role that street trees play in mitigating air pollution.

Global spectra of plant litter carbon, nitrogen and phosphorus concentrations and returning amounts - Yuan, Ji; Wu, Fuzhong; Peng, Changhui; Peñuelas, Josep; Vallicrosa, Helena; Sardans, Jordi; Peng, Yan; Wu, Qiqian; Li, Zimin; Heděnec, Petr; Li, Zhijie; Tan, Siyi; et al. (Journal of Ecology, 2024)
Abstract Litter decomposition is a key ecological process that determines carbon (C) and nutrient cycling in terrestrial ecosystems. The initial concentrations of C and nutrients in litter play a critical role in this process, yet the global patterns of litter initial concentrations of C, nitrogen (N) and phosphorus (P) are poorly understood. We employed machine learning with a global database to quantitatively assess the global patterns and drivers of leaf litter initial C, N and P concentrations, as well as their returning amounts (i.e. amounts returned to soils). The medians of litter C, N and P concentrations were 46.7, 1.1, and 0.1%, respectively, and the medians of litter C, N and P returning amounts were 1.436, 0.038 and 0.004 Mg ha −1 year −1 , respectively. Soil and climate emerged as the key predictors of leaf litter C, N and P concentrations. Predicted global maps showed that leaf litter N and P concentrations decreased with latitude, while C concentration exhibited an opposite pattern. Additionally, the returning amounts of leaf litter C, N and P all declined from the equator to the poles in both hemispheres. Synthesis : Our results provide a quantitative assessment of the global concentrations and returning amounts of leaf litter C, N and P, which showed new light on the role of leaf litter in global C and nutrients cycling.

Vegetation types and flood water level are dominant factors controlling the carbon sequestration potential in Dongting Lake floodplain, China - Wang, Tao; Deng, Zhengmiao; Zhang, Chengyi; Zou, Yeai; Xie, Yonghong; Li, Feng; Xiao, Fengjin; Peng, Changhui (Science of The Total Environment, 2024)

Dynamic carbon allocation trade‐off: A robust approach to model tree biomass allometry - Yang, Mingxia; Zhou, Xiaolu; Liu, Zelin; Li, Peng; Liu, Caixia; Huang, Huabing; Tang, Jiayi; Zhang, Cicheng; Zou, Ziying; Xie, Binggeng; Peng, Changhui (Methods in Ecology and Evolution, 2024)
Abstract Forest above‐ground biomass (AGB) is often estimated by converting the observed tree size using allometric scaling between the dry weight and size of an organism. However, the variations in biomass allocation and scaling between tree crowns and stems due to survival competition during a tree's lifecycle remain unclear. This knowledge gap can improve the understanding of modelling tree biomass allometry because traditional allometries ignore the dynamics of allocation. Herein, we characterised allometric scaling using the dynamic ratio ( r ) of the stem biomass (SB) to AGB and a dynamic exponent. The allometric models were biologically parameterised by the r values for initial, intermediate and final ages rather than only a regression result. The scaling was tested using field measurements of 421 species and 2213 different‐sized trees in pantropical regions worldwide. We found that the scaling fluctuated with tree size, and this fluctuation was driven by the trade‐off relationship of biomass allocation between the tree crown and stem depending on the dynamic crown trait. The allometric scaling between SB and AGB varied from 0.8 to 1.0 for a tree during its entire lifecycle. The fluctuations presented a general law for the allometric scaling of the pantropical tree biomass and size. Our model quantified the trade‐off and explained 94.1% of the allometric relationship between the SB and AGB (93.8% of which between D 2 H and AGB) for pantropical forests, which resulted in a better fit than that of the traditional model. Considering the effects of the trade‐off on modelling, the actual biomass of large trees could be substantially greater than conventional estimates. These results highlight the importance of coupling growth mechanisms in modelling allometry and provide a theoretical foundation for better describing and predicting forest carbon accumulation.

Quantification and uncertainty of global upland soil methane sinks: Processes, controls, model limitations, and improvements - Song, Hanxiong; Peng, Changhui; Zhu, Qiuan; Chen, Zhi; Blanchet, Jean-Pierre; Liu, Qiuyu; Li, Tong; Li, Peng; Liu, Zelin (Earth-Science Reviews, 2024)

Global responses of wetland methane emissions to extreme temperature and precipitation - Xu, Min; Zhang, Jiang; Zhang, Zhen; Wang, Meng; Chen, Huai; Peng, Changhui; Yu, Dongxue; Zhan, Hao; Zhu, Qiuan (Environmental Research, 2024)

Soil methane emissions from plain poplar (Populus spp.) plantations with contrasting soil textures - Ma, Xuehong; Feng, Huili; Guo, Jiahuan; Peng, Changhui; Kneeshaw, Daniel; Wang, Weifeng (Scientific Reports, 2024)
Abstract The forest soil methane (CH 4 ) flux exhibits high spatiotemporal variability. Understanding these variations and their driving factors is crucial for accurately assessing the forest CH 4 budget. In this study, we monitored the diurnal and seasonal variations in soil CH 4 fluxes in two poplar ( Populus spp.) plantations (Sihong and Dongtai) with different soil textures using the static chamber-based method. The results showed that the annual average soil CH 4 flux in the Sihong and Dongtai poplar plantations was 4.27 ± 1.37 kg CH 4 -C ha –1 yr –1 and 1.92 ± 1.07 kg CH 4 -C ha –1 yr –1 , respectively. Both plantations exhibited net CH 4 emissions during the growing season, with only weak CH 4 absorption (–0.01 to –0.007 mg m –2 h –1 ) during the non-growing season. Notably, there was a significant difference in soil CH 4 flux between the clay loam of the Sihong poplar plantation and the sandy loam of the Dongtai poplar plantation. From August to December 2019 and from July to August and November 2020, the soil CH 4 flux in the Sihong poplar plantation was significantly higher than in the Dongtai poplar plantation. Moreover, the soil CH 4 flux significantly increased with rising soil temperature and soil water content. Diurnally, the soil CH 4 flux followed a unimodal variation pattern at different growing stages of poplars, with peaks occurring at noon and in the afternoon. However, the soil CH 4 flux did not exhibit a consistent seasonal pattern across different years, likely due to substantial variations in precipitation and soil water content. Overall, our study emphasizes the need for a comprehensive understanding of the spatiotemporal variations in forest soil CH 4 flux with different soil textures. This understanding is vital for developing reasonable forest management strategies and reducing uncertainties in the global CH 4 budget.

Chapter Eighteen Uncertainty and Sensitivity Issues in Process-based Models of Carbon and Nitrogen Cycles in Terrestrial Ecosystems - Larocque, G.R.; Bhatti, J.S.; Gordon, A.M.; Luckai, N.; Wattenbach, M.; Liu, J.; Peng, C.; Arp, P.A.; Liu, S.; Zhang, C.-F.; Komarov, A.; Grabarnik, P.; et al. (Developments in Integrated Environmental Assessment, 2008)

Methane Emissions from Unique Wetlands in China: Case Studies, Meta Analyses and Modelling - Chen, Huai; Wu, Ning; Peng, Changhui; Wang, Yanfen (DE GRUYTER, 2015)

Climate changes in the Holocene: impact, adaptation, and resilience - Chiotis, Eustathios (CRC Press, 2019)
Climate change in the current geological era, from approximately 11,000 years ago to the present

Variability of Arctic sea-ice cover at decadal to millennial scales: the proxy records - De Vernal, Anne (Past Global Changes Magazine, 2017)

Svalbard ice-sheet decay after the Last Glacial Maximum: New insights from micropalaeontological and organic biomarker paleoceanographical reconstructions - Rigual-Hernández, A.S.; Colmenero-Hidalgo, E.; Martrat, B.; Bárcena, M.A.; De Vernal, A.; Sierro, F.J.; Flores, J.A.; Grimalt, J.O.; Henry, M.; Lucchi, R.G. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)

A New Chronology of Late Quaternary Sequences From the Central Arctic Ocean Based on “Extinction Ages” of Their Excesses in231 Pa and230 Th - Hillaire‐Marcel, C.; Ghaleb, B.; De Vernal, A.; Maccali, J.; Cuny, K.; Jacobel, A.; Le Duc, C.; McManus, J. (Geochemistry, Geophysics, Geosystems, 2017)
Abstract Merging the late Quaternary Arctic paleoceanography into the Earth's global climate history remains challenging due to the lack of robust marine chronostratigraphies. Over ridges notably, low and variable sedimentation rates, scarce biogenic remains ensuing from low productivity and/or poor preservation, and oxygen isotope and paleomagnetic records differing from global stacks represent major impediments. However, as illustrate here based on consistent records from Mendeleev‐Alpha and Lomonosov Ridges, disequilibria between U‐series isotopes can provide benchmark ages. In such settings, fluxes of the particle‐reactive U‐daughter isotopes 230 Th and 231 Pa from the water column, are not unequivocally linked to sedimentation rates, but rather to sea‐ice rafting and brine production histories, thus to the development of sea‐ice factories over shelves during intervals of high relative sea level. The excesses in 230 Th and 231 Pa over fractions supported by their parent U‐isotopes, collapse down sedimentary sequences, due to radioactive decay, and provide radiometric benchmark ages of approximately 300 and 140 ka, respectively. These “extinction ages” point to mean sedimentation rates of ∼4.3 and ∼1.7 mm/ka, respectively, over the Lomonosov and Mendeleev Ridges, which are significantly lower than assumed in most recent studies, thus highlighting the need for revisiting current interpretations of Arctic lithostratigraphies in relation to the global‐scale late Quaternary climatostratigraphy. , Plain Language Summary The Arctic Ocean represents a major component of the Earth climate system notably with regard to the Arctic amplification and freshwater fluxes toward the global ocean. Understanding its role versus the global climate history of the recent glacial/interglacial cycles remains challenging due to the lack of robust chronology of marine sedimentary archives. In the present study, we demonstrate that the decay of Uranium series isotopes in sediments from major Arctic ridges provide benchmark ages for the last ∼300,000 years and support the concept of a “sediment‐starved” environment in the central Arctic Ocean. , Key Points New chronology of late Quaternary marine sequences from the central Arctic Mean sedimentation rates of the order of millimeters per thousand years over ridges Highly discontinuous ice‐rafted sedimentation over ridges with gaps

Holocene paleoceanography of the Bay of Biscay: Evidence for west-east linkages in the North Atlantic based on dinocyst data - Zumaque, Jena; Eynaud, Frédérique; De Vernal, Anne (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)

New data on the Holocene evolution of the Dvina Bay (White Sea) - Novichkova, Ye. A.; Reikhard, L. Ye.; Lisitzin, A. P.; Rybalko, A. Ye.; De Vernal, A. (Doklady Earth Sciences, 2017)

Comparison of qualitative and quantitative dinoflagellate cyst approaches in reconstructing glacial-interglacial climate variability at West Iberian Margin IODP ‘Shackleton’ Site U1385 - Datema, Mariska; Sangiorgi, Francesca; De Vernal, Anne; Reichart, Gert-Jan; Lourens, Lucas J.; Sluijs, Appy (Marine Micropaleontology, 2017)

Quaternary dinoflagellate cysts in the Arctic Ocean: Potential and limitations for stratigraphy and paleoenvironmental reconstructions - Matthiessen, Jens; Schreck, Michael; De Schepper, Stijn; Zorzi, Coralie; De Vernal, Anne (Quaternary Science Reviews, 2018)

Identification key for Pliocene and Quaternary Spiniferites taxa bearing intergonal processes based on observations from estuarine and coastal environments - Limoges, Audrey; Londeix, Laurent; Mertens, Kenneth Neil; Rochon, André; Pospelova, Vera; Cuéllar, Tomasa; De Vernal, Anne (Palynology, 2018)

Environmental forcing on the flux of organic-walled dinoflagellate cysts in recent sediments from a subtropical lagoon in the Gulf of California - Cuellar-Martinez, Tomasa; Alonso-Rodríguez, Rosalba; Ruiz-Fernández, Ana Carolina; De Vernal, Anne; Morquecho, Lourdes; Limoges, Audrey; Henry, Maryse; Sanchez-Cabeza, Joan-Albert (Science of The Total Environment, 2018)

Paleoceanography of northeastern Fram Strait since the last glacial maximum: Palynological evidence of large amplitude changes - Falardeau, Jade; De Vernal, Anne; Spielhagen, Robert F. (Quaternary Science Reviews, 2018)

Climate variability in subarctic area for the last two millennia - Nicolle, Marie; Debret, Maxime; Massei, Nicolas; Colin, Christophe; deVernal, Anne; Divine, Dmitry; Werner, Johannes P.; Hormes, Anne; Korhola, Atte; Linderholm, Hans W. (Feedback and Forcing/Ice Cores/Holocene, 2017)
Abstract. To put in perspective the recent climate change, it is necessary to extend the instrumental climate records with proxy data from palaeoclimate archives. Arctic climate variability for the last two millennia has been investigated using statistical and signal analyses from three regionally averaged records from the North Atlantic, Siberia and Alaska based on many sort of proxy data archived in the Arctic 2k database. In the North Atlantic and Alaska areas, the major climatic trend is characterized by long-term cooling interrupted by the recent warming that started at the beginning of the 19th century. This cooling trend is not clearly visible in the Siberian region. The Little Ice Age (LIA) was identified from the individual series and is characterized by an important spatial and temporal expression of climate variability. It started at the earliest by around 1200 AD and ended at the latest in the middle of the 20th century. The large spread temporal coverage of LIA did not show regional consistency or particular spatial distribution and did not show relationship with archive/proxy type either. A focus on the last two centuries shows a recent warming characterized by a well-marked warming trend paralleling with increasing greenhouse gas emissions. It also shows a multi-decadal variability likely due to natural processes acting on the internal climate system variability at regional scale. A 16–30 years cycle is found in Alaska and seems to be linked to the Pacific Decadal Oscillation (PDO) whereas ~ 20–30 and ~ 50–90 years periodicities characterize the North Atlantic climate regime, likely in relation with the Atlantic Multidecadal Oscillation (AMO). These regional features are apparently linked to the sea-ice cover fluctuations through ice-temperature positive feedback.

Arctic environmental change beyond instrumental records: introduction and overview - Ó Cofaigh, Colm; Kirchner, Nina; Fedorov, Grigory; Noormets, Riko; De Vernal, Anne (arktos, 2018)

Late Holocene Sea Surface Instabilities in the Disko Bugt Area, West Greenland, in Phase With δ18 O Oscillations at Camp Century - Allan, Estelle; De Vernal, Anne; Knudsen, Mads Faurschou; Hillaire‐Marcel, Claude; Moros, Matthias; Ribeiro, Sofia; Ouellet‐Bernier, Marie‐Michèle; Seidenkrantz, Marit‐Solveig (Paleoceanography and Paleoclimatology, 2018)
Abstract Palynological analyses of sediment core MSM343310 from Disko Bugt (68°38′861°N, 53°49′493°W) document decadal‐ to centennial‐scale variability of sea surface conditions during the last ~ 3,600 years. Dinocyst fluxes (>10 4 cysts/cm 2 yr −1 ) indicate a very high productivity. Dinocyst assemblages dominated by Islandinium minutum , Brigantedinium spp., Islandinium ? cezare , and the cyst of Pentapharsodinium dalei suggest low surface salinity and marked shifts in summer sea surface temperature. The application of the modern analog technique to dinocyst assemblages, using an updated reference data set with new sites from the West Greenland margin, led to reconstruct decadal‐centennial‐scale variations in sea surface salinity and temperature, in phase with the δ 18 O variations in the Camp Century ice core. At ~ 1.5 ka BP, the seasonal sea ice cover records an important regime change, from winter‐only sea ice to more unstable conditions marked by successive cooling pulses with sea ice cover of up to 8 months/yr. The data suggest a close relationship between hydrographic conditions and regional climate over Greenland. Our record shows variations with a mean 200 years periodicity until ~2 ka BP, which supports the hypothesis of climate variations driven by solar variability. After 1.5 ka BP, our data show a variability characterized by a 60–70 year periodicity, which suggests linkages with the Atlantic Multidecadal Oscillation and southwestward migration of the atmospheric polar front. The most recent part of the record, from ~1900 CE to 2007 CE, is characterized by assemblages reflecting warmer surface conditions and reduced sea ice cover. , Key Points Sea surface salinity changes are used as indicators of fresh‐meltwater events and sea ice cover as a diagnostic feature of regional climate Changing sea surface conditions from Disko Bugt are closely related with regional climate over Greenland A marked change in surface waters at about 1.5 ka BP corresponds to enhanced sea ice cover and the onset of unstable conditions

The dinoflagellate cyst genera Achomosphaera Evitt 1963 and Spiniferites Mantell 1850 in Pliocene to modern sediments: a summary of round table discussions - Mertens, Kenneth Neil; Van Nieuwenhove, Nicolas; Gurdebeke, Pieter R.; Aydin, Hilal; Bogus, Kara; Bringué, Manuel; Dale, Barrie; De Schepper, Stijn; De Vernal, Anne; Ellegaard, Marianne; Grothe, Arjen; Gu, Haifeng; et al. (Palynology, 2018)

Distribution and (palaeo)ecological affinities of the main Spiniferites taxa in the mid-high latitudes of the Northern Hemisphere - De Vernal, Anne; Eynaud, Frédérique; Henry, Maryse; Limoges, Audrey; Londeix, Laurent; Matthiessen, Jens; Marret, Fabienne; Pospelova, Vera; Radi, Taoufik; Rochon, André; Van Nieuwenhove, Nicolas; Zaragosi, Sébastien (Palynology, 2018)

Palaeoclimate constraints on the impact of 2 °C anthropogenic warming and beyond - Fischer, Hubertus; Meissner, Katrin J.; Mix, Alan C.; Abram, Nerilie J.; Austermann, Jacqueline; Brovkin, Victor; Capron, Emilie; Colombaroli, Daniele; Daniau, Anne-Laure; Dyez, Kelsey A.; Felis, Thomas; Finkelstein, Sarah A.; et al. (Nature Geoscience, 2018)

Postglacial paleoceanography and paleoenvironments in the northwestern Barents Sea - Ivanova, Elena; Murdmaa, Ivar; De Vernal, Anne; Risebrobakken, Bjørg; Peyve, Alexander; Brice, Camille; Seitkalieva, Elvira; Pisarev, Sergey (Quaternary Research, 2019)
Abstract The Barents Sea offers a suitable location for documenting advection of warm and saline Atlantic Water (AW) into the Arctic and its impact on deglaciation and postglacial conditions. We investigate the timing, succession, and mechanisms of the transition from proximal glaciomarine to marine environment in the northwestern Barents Sea. Two studied sediment cores demonstrate diachronous retreat of the grounded ice sheet from the Kvitøya Trough (core S2528) to Erik Eriksen Trough (core S2519). Oxygen isotope records from core S2528 depict a two-step pattern, with lower δ 18 O values prior to the Younger Dryas (YD), and higher values afterward because of advection of the more saline, 18 O-enriched AW. At this location, subsurface AW penetration increased during the Allerød and YD/Preboreal transition. In the study area, foraminiferal and dinocyst data from the YD interval suggest cold conditions, extensive sea-ice cover, and brine formation, along with the flow of chilled AW at subsurface and the development of a high-productivity polynya in the Erik Eriksen Trough. Dense winter sea-ice cover with seasonal productivity persisted in the Kvitøya Trough area during the early Holocene, whereas surface warming seems to have occurred during the middle Holocene interval.

Millennial‐Scale Climate Variability and Dinoflagellate‐Cyst‐Based Seasonality Changes Over the Last ~150 kyrs at “Shackleton Site” U1385 - Datema, Mariska; Sangiorgi, Francesca; De Vernal, Anne; Reichart, Gert‐Jan; Lourens, Lucas J.; Sluijs, Appy (Paleoceanography and Paleoclimatology, 2019)
Abstract During the last glacial period, climate conditions in the North Atlantic region were determined by the alternation of relatively warm interstadials and relatively cool stadials, with superimposed rapid warming (Dansgaard‐Oeschger) and cooling (Heinrich) events. So far little is known about the impact of these rapid climate shifts on the seasonal variations in sea surface temperature (SST) within the North Atlantic region. Here, we present a high‐resolution seasonal SST record for the past 152 kyrs derived from Integrated Ocean Drilling Program “Shackleton” Site U1385, offshore Portugal. Assemblage counts of dinoflagellates cysts (dinocysts) in combination with a modern analog technique (MAT), and regression analyses were used for the reconstructions. We compare our records with previously published SST records from the same location obtained from the application of MAT on planktonic foraminifera. Our dinocyst‐based reconstructions confirm the impression of the Greenland stadials and interstadials offshore the Portuguese margin and indicate increased seasonal contrast of temperature during the cold periods of the glacial cycle (average 9.0 °C, maximum 12.2 °C) with respect to present day (5.1 °C), due to strong winter cooling by up to 8.3 °C. Our seasonal temperature reconstructions are in line with previously published data, which showed increased seasonality due to strong winter cooling during the Younger Dryas and the Last Glacial Maximum over the European continent and North Atlantic region. In addition, we show that over longer time scales, increased seasonal contrasts of temperature remained characteristic of the colder phases of the glacial cycle. , Key Points New high‐resolution dinocyst‐based summer and winter SST record from IODP “Shackleton” Site U1385 for the last 150 kyrs is presented Dinocyst‐based SST confirms the D‐O cycles and HEs at Site U1385 Increased seasonal contrast of SST (up to 12 degree C) during cold periods of the glacial cycle related to strong winter cooling is shown

Challenges and research priorities to understand interactions between climate, ice sheets and global mean sea level during past interglacials - Capron, Emilie; Rovere, Alessio; Austermann, Jacqueline; Axford, Yarrow; Barlow, Natasha L.M.; Carlson, Anders E.; De Vernal, Anne; Dutton, Andrea; Kopp, Robert E.; McManus, Jerry F.; Menviel, Laurie; Otto-Bliesner, Bette L.; et al. (Quaternary Science Reviews, 2019)

Impagidinium detroitense and I.? diaphanum: Two new dinoflagellate cyst species from the Pliocene of the North Pacific Ocean, and their biostratigraphic significance - Zorzi, Coralie; Head, Martin J.; Matthiessen, Jens; De Vernal, Anne (Review of Palaeobotany and Palynology, 2019)

Natural variability of the Arctic Ocean sea ice during the present interglacial - De Vernal, Anne; Hillaire-Marcel, Claude; Le Duc, Cynthia; Roberge, Philippe; Brice, Camille; Matthiessen, Jens; Spielhagen, Robert F.; Stein, Ruediger (Proceedings of the National Academy of Sciences, 2020)
Significance Arctic sea ice is an important component of the Earth’s climate system, but prior to its recent reduction, its long-term natural instabilities need to be better documented. In this study, information on past sea-ice conditions across the Arctic Ocean demonstrates that whereas its western and central parts remained occupied by perennial sea ice throughout the present interglacial, its southeastern sector close to the Russian margin experienced, at least, sporadic seasonal sea-ice-free conditions during the warmer part of the present interglacial until ∼4,000 y ago. Sea-ice-free conditions during summer in the southeastern Arctic Ocean seem, therefore, to be a recurrent feature linked to its natural variability during warm episodes of the past. , The impact of the ongoing anthropogenic warming on the Arctic Ocean sea ice is ascertained and closely monitored. However, its long-term fate remains an open question as its natural variability on centennial to millennial timescales is not well documented. Here, we use marine sedimentary records to reconstruct Arctic sea-ice fluctuations. Cores collected along the Lomonosov Ridge that extends across the Arctic Ocean from northern Greenland to the Laptev Sea were radiocarbon dated and analyzed for their micropaleontological and palynological contents, both bearing information on the past sea-ice cover. Results demonstrate that multiyear pack ice remained a robust feature of the western and central Lomonosov Ridge and that perennial sea ice remained present throughout the present interglacial, even during the climate optimum of the middle Holocene that globally peaked ∼6,500 y ago. In contradistinction, the southeastern Lomonosov Ridge area experienced seasonally sea-ice-free conditions, at least, sporadically, until about 4,000 y ago. They were marked by relatively high phytoplanktonic productivity and organic carbon fluxes at the seafloor resulting in low biogenic carbonate preservation. These results point to contrasted west–east surface ocean conditions in the Arctic Ocean, not unlike those of the Arctic dipole linked to the recent loss of Arctic sea ice. Hence, our data suggest that seasonally ice-free conditions in the southeastern Arctic Ocean with a dominant Arctic dipolar pattern, may be a recurrent feature under “warm world” climate.

Palynology, biostratigraphy, and paleoceanography of the Plio-Pleistocene at Ocean Drilling Program Site 887, Gulf of Alaska - Zorzi, Coralie; Matthiessen, Jens; De Vernal, Anne (Palaeogeography, Palaeoclimatology, Palaeoecology, 2020)

From bi-polar to regional distribution of modern dinoflagellate cysts, an overview of their biogeography - Marret, Fabienne; Bradley, Lee; De Vernal, Anne; Hardy, William; Kim, So-Young; Mudie, Peta; Penaud, Aurélie; Pospelova, Vera; Price, Andrea M.; Radi, Taoufik; Rochon, André (Marine Micropaleontology, 2020)

Dinocyst and acritarch biostratigraphy of the Late Pliocene to Early Pleistocene at Integrated Ocean Drilling Program Site U1307 in the Labrador Sea - Aubry, Aurélie Marcelle Renée; De Schepper, Stijn; De Vernal, Anne (Journal of Micropalaeontology, 2020)
Abstract. We have analyzed marine palynomorphs (mainly dinocysts and acritarchs) from the Integrated Ocean Drilling Program Site U1307 in the Labrador Sea in order to establish a detailed biostratigraphy for the Late Pliocene to Early Pleistocene. We have defined three magnetostratigraphically calibrated dinocyst and acritarch biozones in the Late Pliocene to Early Pleistocene. Zone LS1 is defined based on the highest occurrence of Barssidinium graminosum and covers the later Pliocene from 3.21 to 2.75 Ma. Zone LS2 is marked by the acme of Pyxidinopsis braboi which occurs between 2.75 and 2.57 Ma, thus encompassing the Plio–Pleistocene transition. Finally, zone LS3 extends from 2.57 to 2.23 Ma in the Early Pleistocene. The palynostratigraphic record of IODP Site U1307 is difficult to correlate to other North Atlantic and Nordic Seas sites mainly because of a different temporal resolution and a lack of well-defined biostratigraphic marker species at the basin scale. The low abundance, discontinuous occurrence and asynchronous events of warm-water Pliocene taxa such as Invertocysta lacrymosa, Impagidinium solidum, Ataxiodinium confusum, Melitasphaeridium choanophorum and Operculodinium? eirikianum suggest cooler conditions in the Labrador Sea than elsewhere in the North Atlantic, reflecting a strong regionalism. Nevertheless, as recorded at other locations in the North Atlantic, the disappearance of many dinocyst and acritarch taxa around 2.75 Ma at Site U1307 reflects a strong ecological response accompanying the intensification of the Northern Hemisphere glaciation.

Biomarker Distributions in (Sub)‐Arctic Surface Sediments and Their Potential for Sea Ice Reconstructions - Kolling, Henriette M.; Stein, Ruediger; Fahl, Kirsten; Sadatzki, Henrik; De Vernal, Anne; Xiao, Xiaotong (Geochemistry, Geophysics, Geosystems, 2020)
Abstract To evaluate the present sea ice changes in a longer‐term perspective, the knowledge of sea ice variability on preindustrial and geological time scales is essential. For the interpretation of proxy reconstructions it is necessary to understand the recent signals of different sea ice proxies from various regions. We present 260 new sediment surface samples collected in the (sub‐)Arctic Oceans that were analyzed for specific sea ice (IP 25 ) and open‐water phytoplankton biomarkers (brassicasterol, dinosterol, and highly branched isoprenoid [HBI] III). This new biomarker data set was combined with 615 previously published biomarker surface samples into a pan‐Arctic database. The resulting pan‐Arctic biomarker and sea ice index (PIP 25 ) database shows a spatial distribution correlating well with the diverse modern sea ice concentrations. We find correlations of P B IP 25 , P D IP 25 , and P III IP 25 with spring and autumn sea ice concentrations. Similar correlations with modern sea ice concentrations are observed in Baffin Bay. However, the correlations of the PIP 25 indices with modern sea ice concentrations differ in Fram Strait from those of the (sub‐)Arctic data set, which is likely caused by region‐specific differences in sea ice variability, nutrient availability, and other environmental conditions. The extended (sea ice) biomarker database strengthens the validity of biomarker sea ice reconstructions in different Arctic regions and shows how different sea ice proxies combined may resolve specific seasonal sea ice conditions. , Key Points IP 25 provides information about modern sea ice cover on a (sub‐)Arctic‐wide scale All PIP 25 indices correlate well with spring and autumn sea ice concentrations on a (sub‐)Arctic‐wide scale The combination of biomarker data and dinoflagellate cysts may yield an approach to reconstruct sea ice conditions during different seasons

A global database of Holocene paleotemperature records - Kaufman, Darrell; McKay, Nicholas; Routson, Cody; Erb, Michael; Davis, Basil; Heiri, Oliver; Jaccard, Samuel; Tierney, Jessica; Dätwyler, Christoph; Axford, Yarrow; Brussel, Thomas; Cartapanis, Olivier; et al. (Scientific Data, 2020)
Abstract A comprehensive database of paleoclimate records is needed to place recent warming into the longer-term context of natural climate variability. We present a global compilation of quality-controlled, published, temperature-sensitive proxy records extending back 12,000 years through the Holocene. Data were compiled from 679 sites where time series cover at least 4000 years, are resolved at sub-millennial scale (median spacing of 400 years or finer) and have at least one age control point every 3000 years, with cut-off values slackened in data-sparse regions. The data derive from lake sediment (51%), marine sediment (31%), peat (11%), glacier ice (3%), and other natural archives. The database contains 1319 records, including 157 from the Southern Hemisphere. The multi-proxy database comprises paleotemperature time series based on ecological assemblages, as well as biophysical and geochemical indicators that reflect mean annual or seasonal temperatures, as encoded in the database. This database can be used to reconstruct the spatiotemporal evolution of Holocene temperature at global to regional scales, and is publicly available in Linked Paleo Data (LiPD) format.

Distribution of dinocyst assemblages in surface sediment samples from the West Greenland margin - Allan, Estelle; De Vernal, Anne; Krawczyk, Diana; Moros, Matthias; Radi, Taoufik; Rochon, André; Seidenkrantz, Marit-Solveig; Zaragosi, Sébastien (Marine Micropaleontology, 2020)

Pollen-based climate reconstruction techniques for late Quaternary studies - Chevalier, Manuel; Davis, Basil A.S.; Heiri, Oliver; Seppä, Heikki; Chase, Brian M.; Gajewski, Konrad; Lacourse, Terri; Telford, Richard J.; Finsinger, Walter; Guiot, Joël; Kühl, Norbert; Maezumi, S. Yoshi; et al. (Earth-Science Reviews, 2020)

A database of Holocene temperature records for north‐eastern North America and the north‐western Atlantic - Van Bellen, Simon; De Vernal, Anne; To, Anna; Ouellet‐Bernier, Marie‐Michèle; Roy, Natasha; ClimHuNor Members (Geoscience Data Journal, 2020)
Abstract Centennial‐to‐millennial temperature records of the past provide a context for the interpretation of current and future changes in climate. Quaternary climates have been relatively well studied in north‐east North America and the adjacent Atlantic Ocean over the last decades, and new research methods have been developed to improve reconstructions. We present newly inferred reconstructions of sea surface temperature for the north‐western Atlantic region, together with a compilation of published temperature records. The database thus comprises a total of 86 records from both marine and terrestrial sites, including lakes, peatlands, ice and tree rings, each covering at least part of the Holocene. For each record, we present details on seasons covered, chronologies and information on radiocarbon dates and analytical time steps. The 86 records contain a total of 154 reconstructions of temperature and temperature‐related variables. Main proxies include pollen and dinocysts, while summer was the season for which the highest number of reconstructions were available. Many records covered most of the Holocene, but many dinocyst records did not extend to the surface, due to sediment mixing, and dendroclimate records were limited to the last millennium. The database allows for the exploration of linkages between sea ice and climate and may be used in conjunction with other palaeoclimate and palaeoenvironmental records, such as wildfire records and peatland dynamics. This inventory may also aid the identification of gaps in the geographic distribution of past temperature records thus guiding future research efforts.

An overview and brief description of common marine organic-walled dinoflagellate cyst taxa occurring in surface sediments of the Northern Hemisphere - Van Nieuwenhove, Nicolas; Head, Martin J.; Limoges, Audrey; Pospelova, Vera; Mertens, Kenneth N.; Matthiessen, Jens; De Schepper, Stijn; De Vernal, Anne; Eynaud, Frédérique; Londeix, Laurent; Marret, Fabienne; Penaud, Aurélie; et al. (Marine Micropaleontology, 2020)

Historical Perspectives on Exceptional Climatic Years at the Labrador/Nunatsiavut Coast 1780 to 1950 - Ouellet-Bernier, Marie-Michèle; De Vernal, Anne; Chartier, Daniel; Boucher, Étienne (Quaternary Research, 2021)
Abstract This interdisciplinary study presents a human perspective on climatic variations by combining documentary, discursive, instrumental, and proxy data. Historical sources were used to characterize climate variations along the coast of Labrador/Nunatsiavut during the 19 th century and the first half of the 20 th century. Written and early instrumental archives provided original information on the state and perception of climate before the establishment of meteorological stations, which permitted an intra-annual perspective on climatic variations. Written sources depicted the sensitivity of humans to climatic variations. Exceptional seasonal climatic events were extracted from documentary and discursive sources, which were complemented by tree-ring and early instrumental data. From 1780 to 1900, data indicated a succession of relatively warm and cold episodes. Most warm periods were described as stormy and variable. The final part of the studied records showed cold conditions from 1900 to 1925 and warm conditions from 1925 to 1950. Historical sources helped to discriminate a seasonal signal. Mild autumn-winter conditions were recorded since 1910 in relation with positive anomalies of the North Atlantic Oscillation in winter. Relatively warm spring-summer conditions were recorded after 1920, which corresponds to a phase of positive anomaly of the Atlantic Multidecadal Oscillation.

Holocene variability in sea ice and primary productivity in the northeastern Baffin Bay - Saini, Jeetendra; Stein, Ruediger; Fahl, Kirsten; Weiser, Jens; Hebbeln, Dierk; Hillaire-Marcel, Claude; De Vernal, Anne (arktos, 2020)
Abstract Arctic sea ice is a critical component of the climate system, known to influence ocean circulation, earth’s albedo, and ocean–atmosphere heat and gas exchange. Current developments in the use of IP 25 (a sea ice proxy with 25 carbon atoms only synthesized by Arctic sea ice diatoms) have proven it to be a suitable proxy for paleo-sea ice reconstructions over hundreds of thousands to even millions of years. In the NE Baffin Bay, off NW Greenland, Melville Bugt is a climate-sensitive region characterized by strong seasonal sea ice variability and strong melt-water discharge from the Greenland Ice Sheet (GIS). Here, we present a centennial-scale resolution Holocene sea ice record, based on IP 25 and open-water phytoplankton biomarkers (brassicasterol, dinosterol and HBI III) using core GeoB19927-3 (73° 35.26′ N, 58° 05.66′ W). Seasonal to ice-edge conditions near the core site are documented for most of the Holocene period with some significant variability. In the lower-most part, a cold interval characterized by extensive sea ice cover and very low local productivity is succeeded by an interval (~ 9.4–8.5 ka BP) with reduced sea ice cover, enhanced GIS spring melting, and strong influence of the West Greenland Current (WGC). From ~ 8.5 until ~ 7.8 ka BP, a cooling event is recorded by ice algae and phytoplankton biomarkers. They indicate an extended sea ice cover, possibly related to the opening of Nares Strait, which may have led to an increased influx of Polar Water into NE-Baffin Bay. The interval between ~ 7.8 and ~ 3.0 ka BP is characterized by generally reduced sea ice cover with millennial-scale variability of the (late winter/early spring) ice-edge limit, increased open-water conditions (polynya type), and a dominant WGC carrying warm waters at least as far as the Melville Bugt area. During the last ~ 3.0 ka BP, our biomarker records do not reflect the late Holocene ‘Neoglacial cooling’ observed elsewhere in the Northern Hemisphere, possibly due to the persistent influence of the WGC and interactions with the adjacent fjords. Peaks in HBI III at about ~ 2.1 and ~ 1.3 ka BP, interpreted as persistent ice-edge situations, might correlate with the Roman Warm Period (RWP) and Medieval Climate Anomaly (MCA), respectively, in-phase with the North Atlantic Oscillation (NAO) mode. When integrated with marine and terrestrial records from other circum-Baffin Bay areas (Disko Bay, the Canadian Arctic, the Labrador Sea), the Melville Bugt biomarker records point to close ties with high Arctic and Northern Hemispheric climate conditions, driven by solar and oceanic circulation forcings.

Winter freeze-up and summer break-up in Nunatsiavut, Canada, from 1770 to 1910 (Past Global Changes Magazine, 2020)

Distribution of common modern dinoflagellate cyst taxa in surface sediments of the Northern Hemisphere in relation to environmental parameters: The new n=1968 database - De Vernal, Anne; Radi, Taoufik; Zaragosi, Sebastien; Van Nieuwenhove, Nicolas; Rochon, André; Allan, Estelle; De Schepper, Stijn; Eynaud, Frédérique; Head, Martin J.; Limoges, Audrey; Londeix, Laurent; Marret, Fabienne; et al. (Marine Micropaleontology, 2020)

Identifying the signature of sea-surface properties in dinocyst assemblages: Implications for quantitative palaeoceanographical reconstructions by transfer functions and analogue techniques - Hohmann, Sabrina; Kucera, Michal; De Vernal, Anne (Marine Micropaleontology, 2020)

Greenland Ice Sheet mass loss rate will exceed Holocene values this century - Briner, J. P.; Cuzzone, J. K.; Badgeley, J.; Allan, E.; Bennike, O.; Cluett, A.; Csatho, B. M.; de Vernal, A.; Downs, J.; Hakim, G. J.; Johnson, J. V.; Larour, E. Y.; et al. (2019)
The Greenland Ice Sheet (GrIS) is a major contributor to sea level rise and may already be in irreversible decline. Observations spanning recent decades show the GrIS losing mass at an increasing rate; however, projecting this trend into the future is complicated by year-to-year variability and requires looking at longer timescales. Historical data suggest the GrIS was nearly in balance in the 1800s (-900 Gt/century), but had negative balance in the 1900s (-4000 to -8000 Gt/century). Projecting observations made thus far from the 2000s, mass-loss rate could average anywhere from ca. -40,000 to -100,000 Gt/century. Our goal is to evaluate these historic and contemporary rates of GrIS mass loss within the framework of the current Holocene interglacial spanning the last 12,000 years. To do so we combine the first highly resolved paleo-GrIS simulations using NASA's Ice Sheet System Model with novel climate forcing based on a data assimilation approach using multiple paleoclimate records. Our new simulations take place across a glaciologically simple domain in SW Greenland (encompassing ca. 30% of the ice sheet), where they are validated with our detailed glacial chronology of Holocene ice margin change. During the Holocene thermal maximum, a period between ca. 10,000 and 8000 years ago, the GrIS experienced elevated mass loss rates, with maximum values on the order of -5000 to -10,000 Gt/century for our model domain. When these values are scaled to the entire GrIS (using the proportion of SW mass loss vs. total GrIS mass loss from contemporary studies), they equate to maximum mass loss rates of ca. -20,000 to -40,000 Gt/century. From this we conclude that the rate of GrIS mass loss will exceed Holocene values this century.
Keywords: 0726 Ice sheets; 1616 Climate variability; 1621 Cryospheric change; 1641 Sea level change; CRYOSPHERE; GLOBAL CHANGE

Large-scale features of Last Interglacial climate: results from evaluating the lig127k simulations for the Coupled Model Intercomparison Project (CMIP6)–Paleoclimate Modeling Intercomparison Project (PMIP4) - Otto-Bliesner, Bette L.; Brady, Esther C.; Zhao, Anni; Brierley, Chris M.; Axford, Yarrow; Capron, Emilie; Govin, Aline; Hoffman, Jeremy S.; Isaacs, Elizabeth; Kageyama, Masa; Scussolini, Paolo; Tzedakis, Polychronis C.; et al. (Climate of the Past, 2021)
Abstract. The modeling of paleoclimate, using physically based tools, is increasingly seen as a strong out-of-sample test of the models that are used for the projection of future climate changes. New to the Coupled Model Intercomparison Project (CMIP6) is the Tier 1 Last Interglacial experiment for 127 000 years ago (lig127k), designed to address the climate responses to stronger orbital forcing than the midHolocene experiment, using the same state-of-the-art models as for the future and following a common experimental protocol. Here we present a first analysis of a multi-model ensemble of 17 climate models, all of which have completed the CMIP6 DECK (Diagnostic, Evaluation and Characterization of Klima) experiments. The equilibrium climate sensitivity (ECS) of these models varies from 1.8 to 5.6 ∘C. The seasonal character of the insolation anomalies results in strong summer warming over the Northern Hemisphere continents in the lig127k ensemble as compared to the CMIP6 piControl and much-reduced minimum sea ice in the Arctic. The multi-model results indicate enhanced summer monsoonal precipitation in the Northern Hemisphere and reductions in the Southern Hemisphere. These responses are greater in the lig127k than the CMIP6 midHolocene simulations as expected from the larger insolation anomalies at 127 than 6 ka. New synthesis for surface temperature and precipitation, targeted for 127 ka, have been developed for comparison to the multi-model ensemble. The lig127k model ensemble and data reconstructions are in good agreement for summer temperature anomalies over Canada, Scandinavia, and the North Atlantic and for precipitation over the Northern Hemisphere continents. The model–data comparisons and mismatches point to further study of the sensitivity of the simulations to uncertainties in the boundary conditions and of the uncertainties and sparse coverage in current proxy reconstructions. The CMIP6–Paleoclimate Modeling Intercomparison Project (PMIP4) lig127k simulations, in combination with the proxy record, improve our confidence in future projections of monsoons, surface temperature, and Arctic sea ice, thus providing a key target for model evaluation and optimization.

Baffin Bay late Neogene palynostratigraphy at Ocean Drilling Program Site 645 - Aubry, Aurélie M.R.; De Vernal, Anne; Knutz, Paul C. (Canadian Journal of Earth Sciences, 2021)
Analyses of marine and terrestrial palynomorphs of Ocean Drilling Program (ODP) Site 645 in Baffin Bay led us to define a new biostratigraphical scheme covering the late Miocene to Pleistocene based on dinocyst and acritarch assemblages. Four biozones were defined. The first one, from 438.6 m below sea floor (mbsf) to 388 mbsf, can be assigned a late Miocene to early Pliocene age (>4.5 Ma), based on the common occurrence of Cristadinium diminutivum and Selenopemphix brevispinosa. Biozone 2, spanning from an erosional unconformity to a recovery hiatus, is marked by the highest occurrences (HOs) of Veriplicidium franklinii and Cristadinium diminutivum, which suggest an early Pliocene age >3.6 Ma (∼4.5 to ∼3.6 Ma). Biozone 3, above the recovery hiatus and up to 220.94 mbsf, corresponds to a late Pliocene or early Pleistocene age based on occurrences of Bitectatodinium readwaldii, Cymatiosphaera? icenorum, and Lavradosphaera canalis. Finally, between 266.4 and 120.56 mbsf, Biozone 4, marked by the HO of Filisphaera filifera, Filisphaera microornata, and Habibacysta tectata, has an early Pleistocene age (>1.4 Ma). Our biostratigraphy implies that horizon b1 of the Baffin Bay seismic stratigraphy corresponds to the recovery hiatus at ODP Site 645, which suggests a very thick Pliocene sequence along the Baffin Island slope. Dinocyst assemblages and terrestrial palynomorphs in our records indicate that the late Miocene and (or) early Pliocene were characterized by relatively warm coastal surface waters and boreal forest or forested tundra vegetation over adjacent lands. In contrast, the early Pleistocene dinocyst assemblages above the recovery hiatus indicate cold surface waters, while pollen data suggest reduced vegetation cover on adjacent lands.

The role of Arctic gateways on sea ice and circulation in the Arctic and North Atlantic Oceans: a sensitivity study with an ocean-sea-ice model - Karami, Mehdi Pasha; Myers, Paul G.; De Vernal, Anne; Tremblay, L. Bruno; Hu, Xianmin (Climate Dynamics, 2021)

Past abrupt changes, tipping points and cascading impacts in the Earth system - Brovkin, Victor; Brook, Edward; Williams, John W.; Bathiany, Sebastian; Lenton, Timothy M.; Barton, Michael; DeConto, Robert M.; Donges, Jonathan F.; Ganopolski, Andrey; McManus, Jerry; Praetorius, Summer; De Vernal, Anne; et al. (Nature Geoscience, 2021)

A multi-model CMIP6-PMIP4 study of Arctic sea ice at 127 ka: sea ice data compilation and model differences - Kageyama, Masa; Sime, Louise C.; Sicard, Marie; Guarino, Maria-Vittoria; De Vernal, Anne; Stein, Ruediger; Schroeder, David; Malmierca-Vallet, Irene; Abe-Ouchi, Ayako; Bitz, Cecilia; Braconnot, Pascale; Brady, Esther C.; et al. (Climate of the Past, 2021)
Abstract. The Last Interglacial period (LIG) is a period with increased summer insolation at high northern latitudes, which results in strong changes in the terrestrial and marine cryosphere. Understanding the mechanisms for this response via climate modelling and comparing the models' representation of climate reconstructions is one of the objectives set up by the Paleoclimate Modelling Intercomparison Project for its contribution to the sixth phase of the Coupled Model Intercomparison Project. Here we analyse the results from 16 climate models in terms of Arctic sea ice. The multi-model mean reduction in minimum sea ice area from the pre industrial period (PI) to the LIG reaches 50 % (multi-model mean LIG area is 3.20×106 km2, compared to 6.46×106 km2 for the PI). On the other hand, there is little change for the maximum sea ice area (which is 15–16×106 km2 for both the PI and the LIG. To evaluate the model results we synthesise LIG sea ice data from marine cores collected in the Arctic Ocean, Nordic Seas and northern North Atlantic. The reconstructions for the northern North Atlantic show year-round ice-free conditions, and most models yield results in agreement with these reconstructions. Model–data disagreement appear for the sites in the Nordic Seas close to Greenland and at the edge of the Arctic Ocean. The northernmost site with good chronology, for which a sea ice concentration larger than 75 % is reconstructed even in summer, discriminates those models which simulate too little sea ice. However, the remaining models appear to simulate too much sea ice over the two sites south of the northernmost one, for which the reconstructed sea ice cover is seasonal. Hence models either underestimate or overestimate sea ice cover for the LIG, and their bias does not appear to be related to their bias for the pre-industrial period. Drivers for the inter-model differences are different phasing of the up and down short-wave anomalies over the Arctic Ocean, which are associated with differences in model albedo; possible cloud property differences, in terms of optical depth; and LIG ocean circulation changes which occur for some, but not all, LIG simulations. Finally, we note that inter-comparisons between the LIG simulations and simulations for future climate with moderate (1 % yr−1) CO2 increase show a relationship between LIG sea ice and sea ice simulated under CO2 increase around the years of doubling CO2. The LIG may therefore yield insight into likely 21st century Arctic sea ice changes using these LIG simulations.

Biogenic carbonate fluxes and preservation in the northwestern Labrador Sea since the Last Glacial Maximum - Marshall, Nicole R.; De Vernal, Anne; Mucci, Alfonso; Filippova, Alexandra; Kienast, Markus; Gibb, Olivia; Hillaire-Marcel, Claude (Palaeogeography, Palaeoclimatology, Palaeoecology, 2021)

Insolation vs. meltwater control of productivity and sea surface conditions off SW Greenland during the Holocene - Allan, Estelle; De Vernal, Anne; Seidenkrantz, Marit‐Solveig; Briner, Jason P.; Hillaire‐Marcel, Claude; Pearce, Christof; Meire, Lorenz; Røy, Hans; Mathiasen, Anders Møller; Nielsen, Mikkel Thy; Plesner, Jane Lund; Perner, Kerstin (Boreas, 2021)
We address here the specific timing and amplitude of sea‐surface conditions and productivity changes off SW Greenland, northern Labrador Sea, in response to the high deglacial meltwater rates, the Early Holocene maximum insolation and Neoglacial cooling. Dinocyst assemblages from sediment cores collected off Nuuk were used to set up quantitative records of sea ice cover, seasonal sea‐surface temperature (SST), salinity (SSS), and primary productivity, with a centennial to millennial scale resolution. Until ~10 ka BP, ice‐proximal conditions are suggested by the quasi‐exclusive dominance of heterotrophic taxa and low dinocyst concentrations. At about 10 ka BP, an increase in species diversity and abundance of phototrophic taxa marks the onset of interglacial conditions at a regional scale, with summer SST reaching up to 10 °C between 8 and 5 ka BP, thus in phase with the Holocene Thermal Maximum as recorded in the southern Greenlandic areas/northern Labrador Sea. During this interval, low SSS but high productivity prevailed in response to high meltwater discharge and nutrient inputs from the Greenland Ice Sheet. After ~5 ka BP, a decrease in phototrophic taxa marks a two‐step cooling of surface waters. The first started at ~5 ka BP, and the second at ~3 ka BP, with a shift toward colder conditions and higher SSS suggesting reduced meltwater discharge during the Neoglacial. This second step coincides with the disappearance of the Saqqaq culture. The gap in human occupation in west Greenland, between the Dorset and the Norse settlements from 2000 to 1000 years BP, might be linked to high amplitude and high frequency variability of ocean and climate conditions.

Past Warmth and Its Impacts During the Holocene Thermal Maximum in Greenland - Axford, Yarrow; De Vernal, Anne; Osterberg, Erich C. (Annual Review of Earth and Planetary Sciences, 2021)
Higher boreal summer insolation in the early to middle Holocene drove thousands of years of summer warming across the Arctic. Modern-day warming has distinctly different causes, but geologic data from this past warm period hold lessons for the future. We compile Holocene temperature reconstructions from ice, lake, and marine cores around Greenland, where summer temperatures are globally important due to their influence on ice sheet mass balance, ocean circulation, and sea ice. Highlighting and accounting for some key issues with proxy interpretation, we find that much of Greenland experienced summers 3 to 5°C warmer than the mid-twentieth century in the early Holocene—earlier and stronger warming than often presumed. Warmth had dramatic consequences: Many glaciers disappeared, perennial sea ice retreated, plants and animals migrated northward, the Greenland Ice Sheet shrank rapidly, and increased meltwater discharge led to strong marine water stratification and enhanced winter sea ice in some areas. ▪  Summer air temperatures and open ocean temperatures around much of Greenland peaked in the early Holocene in response to elevated summer insolation. ▪  Peak summer air temperatures ranged from 3 to 5°C warmer than the mid-twentieth century in northwest and central Greenland to perhaps 1 to 2°C warmer in south Greenland. ▪  Many differences between records can be explained by proxy seasonality, ice sheet elevation changes, vegetation analogs and lags, and the nearshore effects of ice sheet meltwater. ▪  Early Holocene warmth dramatically affected glaciers and the Greenland Ice Sheet; meltwater discharge, nearshore ocean salinity, and sea ice; and diverse flora and fauna.

Challenging the hypothesis of an Arctic Ocean lake during recent glacial episodes - Hillaire‐Marcel, Claude; Myers, Paul G.; Marshall, Shawn; Tarasov, Lev; Purcell, Karl; Not, Christelle; De Vernal, Anne (Journal of Quaternary Science, 2022)
ABSTRACT The Arctic Ocean is one of the last frontiers on Earth with many unknowns about its geological and climate history and considerable speculation on its role in the Earth's climate and ocean system. It has been proposed recently that it was occupied by a freshwater body of more than 9.5 × 10 6 km 3 underneath a thick ice mass during part of glacial isotopic stages 6 and 4. We argue that such a dramatic scenario, implying replacement of marine waters by freshwater throughout the entire Arctic Ocean and Nordic Seas, is physically implausible. The very low 230 Th excesses ( 230 Th xs ) observed in sediments from these intervals were used as evidence for the presence of a U‐depleted overlying freshwater column. We show here that they may simply result from short, sporadic sedimentary pulses, below multiyear sea ice or ice shelves, linked to deglacial ice streaming and surging events interrupting long‐duration sedimentary gaps. Due to this sporadic sedimentation regime, interpolating time from 230 Th xs data or between benchmark ages in sedimentary sequences would simply be erroneous.

Complex spatio-temporal structure of the Holocene Thermal Maximum - Cartapanis, Olivier; Jonkers, Lukas; Moffa-Sanchez, Paola; Jaccard, Samuel L.; De Vernal, Anne (Nature Communications, 2022)
Abstract Inconsistencies between Holocene climate reconstructions and numerical model simulations question the robustness of climate models and proxy temperature records. Climate reconstructions suggest an early-middle Holocene Thermal Maximum (HTM) followed by gradual cooling, whereas climate models indicate continuous warming. This discrepancy either implies seasonal biases in proxy-based climate reconstructions, or that the climate model sensitivity to forcings and feedbacks needs to be reevaluated. Here, we analyze a global database of Holocene paleotemperature records to investigate the spatiotemporal structure of the HTM. Continental proxy records at mid and high latitudes of the Northern Hemisphere portray a “classic” HTM (8–4 ka). In contrast, marine proxy records from the same latitudes reveal an earlier HTM (11–7ka), while a clear temperature anomaly is missing in the tropics. The results indicate a heterogeneous response to climate forcing and highlight the lack of globally synchronous HTM.

Quaternary Arctic sea-ice cover: Mostly perennial with seasonal openings during interglacials (Past Global Changes Magazine, 2022)

A reassessment of Nd-isotopes and clay minerals as tracers of the Holocene Pacific water flux through Bering Strait - Song, Tengfei; Hillaire-Marcel, Claude; De Vernal, Anne; Liu, Yanguang; Wang, Weiguo; Huang, Yuanhui (Marine Geology, 2022)

Potential and limitation of 230Th-excess as a chronostratigraphic tool for late Quaternary Arctic Ocean sediment studies: An example from the Southern Lomonosov Ridge - Purcell, Karl; Hillaire-Marcel, Claude; De Vernal, Anne; Ghaleb, Bassam; Stein, Ruediger (Marine Geology, 2022)

Challenging Radiocarbon Chronostratigraphies in Central Arctic Ocean Sediment - Hillaire‐Marcel, C.; De Vernal, A.; Rong, Y.; Roberge, P.; Song, T. (Geophysical Research Letters, 2022)
Abstract Based on the analysis of fish otolith assemblages from surface sediments of the Lomonosov Ridge (Arctic Ocean), we demonstrate that the very low Holocene sedimentation rates and winnowing of fine sediments result in the mixing of the whole Holocene populations at the sediment surface. Specimens from the Marine Isotope Stage (MIS) 3 or older could even be recovered in the surface due to a sedimentary hiatus at some locations in the central Arctic during the last glacial maximum. Two examples illustrate that 14 C‐stratigraphies from planktic foraminifers in underlying cored sediments reflect the mixing between Holocene and MIS 3 or older populations, thus invalidating continuous age‐depth inferences based on 14 C ages. Hence, much caution is required when attempting to set paleoceanographic reconstructions based on 14 C chronologies in a low sediment accumulation rate environment such as the central Arctic Ocean. Already published paleoceanographic reconstructions from this area might thus require some revisions. , Plain Language Summary Radiocarbon ages of microfossils (fish otoliths) collected at the surface sediments of the Lomonosov Ridge, in the central Arctic Ocean, indicate that all populations that developed during the present interglacial are mixed within the approximately 1 cm‐thick surface layer. Fossil assemblages occasionally include specimens from older warm intervals. The stacking of fossil spanning thousands of years is due to the very low sediment accumulation rate of the area, the post‐depositional winnowing of fine sediments and mixing by benthic organisms. These process result in the impossibility to document the faunal evolution in the central Arctic Ocean during the last few tens of thousands of years using such fossils. , Key Points Fish otolith radiocarbon age distributions in surface sediments illustrate the mixing of Holocene and pre‐Last Glacial Maximum populations Low sedimentation rates, particle winnowing and sedimentary gaps may impact microfossil mixing and 14 C chronologies Published paleoclimate/paleoceanographic records from similar sites might thus require some reinterpretation

A comment about "A sedimentary record from the Makarov Basin, Arctic Ocean, reveals changing middle to Late Pleistocene glaciation patterns" (Quat. Sci. Rev., 270 (2021), p. 107176) from W. Xiao, L. Polyak, R. Wang, C. Not, L. Dong, Y. Liu, T. Ma, T. Zhang - Hillaire-Marcel, Claude; De Vernal, Anne (Quaternary Science Reviews, 2022)

Millennial‐scale oscillations and an environmental regime shift around the Middle to Late Holocene transition in the North Atlantic region based on a multiproxy record from Isfjorden, West Spitsbergen - Brice, Camille; De Vernal, Anne; Francus, Pierre; Forwick, Matthias; Nam, Seung‐Il (Boreas, 2023)
Palynological and sedimentological analyses were performed on the sediment core HH16‐1205‐GC retrieved from the central Isfjorden, West Spitsbergen. The sequence, which spans the last 7000 years, revealed an overall cooling trend with an important climate shift between 4.4 and 3.8 cal. ka BP, in addition to millennial‐scale oscillations. Sea‐surface reconstruction from dinocyst assemblages indicates a decrease in summer sea‐surface temperature, from 2.5 to 1.5 °C, and primary productivity, from 750 to 650 gC m −2 a −1 over the last 7000 years. From around 6.8 to 5.8 cal. ka BP, the sedimentological and palynological data suggest a predominant sediment supply from the inner part of the fjord, ice rafting, dense sea ice cover, strongly stratified water masses and high primary productivity. The interval from 4.4 to 3.8 cal. ka BP is marked by a layer of coarser material and a significant decrease in the grain‐size mode. Our geochemical data show large‐amplitude fluctuations after 2.0 cal. ka BP, while an increase in the dinocysts Impagidinium pallidum and Spiniferites elongatus from 2.0 to 1.2 cal. ka BP suggests enhanced Atlantic Water inflow. The dinocyst‐based reconstructions also reveal large‐amplitude millennial fluctuations in sea ice cover, summer sea‐surface temperature and salinity. Wavelet analysis and cross‐wavelet analysis on K/Ti ratio coupled with sea‐ice estimates confirm a strong signal with a periodicity of 1200–1500 years.

Distribution of modern dinocysts and pollen in the western Mediterranean Sea (Algerian margin and Gulf of Lion) - Coussin, V.; Penaud, A.; Combourieu-Nebout, N.; Peyron, O.; Schmidt, S.; Zaragosi, S.; De Vernal, A.; Babonneau, N. (Marine Micropaleontology, 2022)

Benthic Foraminiferal Assemblages from the Laurentian Channel in the Lower Estuary and Gulf of ST. Lawrence, Eastern Canada: Tracers of Bottom-Water Hypoxia - Audet, Tiffany; De Vernal, Anne; Mucci, Alfonso; Seidenkrantz, Marit-Solveig; Hillaire-Marcel, Claude; Carnero-Bravo, Vladislav; Gélinas, Yves (Journal of Foraminiferal Research, 2023)
ABSTRACT Over the past century, an increase in temperatures and a decrease in dissolved oxygen concentrations have been observed in the bottom waters of the Laurentian Channel (LC), throughout the Lower St. Lawrence Estuary (LSLE) and the Gulf of St. Lawrence (GSL), eastern Canada. To document the impact of these changes, we analyzed the benthic foraminiferal assemblages and geochemical signatures of four sediment cores taken in the LC. Radiometric measurements (210Pb, 226Ra, 137Cs) indicate that the studied cores encompass the last 50 years of sedimentation in the LSLE and the last ∼160 years in the GSL. The sedimentary record shows a 60 to 65% decrease in benthic foraminiferal taxonomic diversity in the LC since the 1960s. An accelerated change in the foraminiferal assemblages is observed at approximately the same time at all studied sites, around the late 1990s and the early 2000s, towards populations dominated by the hypoxia-tolerant indicator taxa Brizalina subaenariensis, Eubuliminella exilis, and Globobulimina auriculata. This evolution of assemblages reflects incursions of the hypoxic zone into the western GSL over the last decades. The results of our multivariate analyses highlight the potential of benthic foraminiferal assemblages as a proxy of bottom-water hypoxia.

Holocene Paleoenvironmental Implications of Diatom, Non-Pollen Palynomorph, and Organic Carbon Records from the Kandalaksha Bay of the White Sea (European Arctic) - Polyakova, Yelena; Agafonova, Elizaveta; Novichkova, Ekaterina; De Vernal, Anne (Geosciences, 2023)
Variations in sea surface conditions and sea level through the Holocene in the Kandalaksha Bay, the White Sea, were reconstructed based on the study of core sediments from the outer Kandalaksha Bay, using the modern analog technique applied to dinocysts in addition to diatoms, TOC, δ13Corg, CaCO3, and grain size data. The chronostratigraphy of the core sediments was defined from accelerator mass spectrometry 14C dates on mollusk shells. The results indicated an increase in water depth in the outer Kandalaksha Bay and in the central Dvina Bay until the late Holocene. From about 9.5 to 7.5 cal kyr BP, the data suggested a general trend of increasing sea surface temperatures (up to 14 °C), at least in areas with inflow of Atlantic waters. The last 2.5 kyr were characterized by increased freshwater runoff to the White Sea.

Microfaunal Recording of Recent Environmental Changes in the Herschel Basin, Western Arctic Ocean - Falardeau, Jade; De Vernal, Anne; Seidenkrantz, Marit-Solveig; Cronin, Thomas M.; Gemery, Laura; Chassiot, Léo; Fritz, Michael; Carnero-Bravo, Vladislav; Hillaire-Marcel, Claude; Archambault, Philippe (Journal of Foraminiferal Research, 2023)
ABSTRACT Microfaunal assemblages of benthic foraminifera, ostracods, and tintinnids from two marine sediment cores retrieved from the Herschel Basin of the Canadian Beaufort Sea shelf document relationships with environmental parameters such as salinity, sea-ice cover, and turbulence. Cores YC18-HB-GC01 and PG2303-1 were collected at 18 and 32 m water depth, respectively. At these sites, sediment accumulation rates range between 0.6 and 1.7 cm yr–1 allowing a near-annual temporal resolution over the last 50 years. Multivariate analyses indicate that benthic foraminiferal assemblages respond primarily to food supply. Dissimilarities between the microfaunal assemblages of the two cores are mainly the result of bottom water salinity levels linked to water depth. High abundance of the benthic foraminiferal species Elphidium clavatum and occurrences of Elphidium bartletti point to varying, but relatively low, salinities at the shallow core site YC18-HB-GC01, which may be affected by variations in the summer halocline depth. Higher species diversity and more abundant Cassidulina reniforme and Stainforthia feylingi characterize the deeper core PG2303-1, which might reflect more stable conditions and higher bottom-water salinities throughout the studied time interval. The most important microfaunal shift of the last 50 years, observed in the shallower longer core YC18-HB-GC01, occurred at the turn of the 21st century. Prior to ∼2000 CE, the presence of Islandiella norcrossi indicates more stable and saline conditions. Since ∼2000 CE, increased abundances of Haynesina nivea and of the ciliate Tintinnopsis fimbriata suggest decreased salinity and increased turbidity. An increased abundance of Eoeponidella pulchella after ∼2000 CE suggests a concurrent increase in productivity in the last two decades. This shift is nearly synchronous with a decrease in mean summer sea-ice concentration, which can play an important role in bottom water stability on the shelf. Easterly winds can induce a reduction in the sea-ice cover, but also foster a westward spreading of the Mackenzie River plume and the upwelling of nutrient-rich Pacific waters onto the shelf. Both factors would explain the increased freshening and productivity of the Herschel Basin. The last two decades were also marked by a decrease in ostracod abundance that may relate to higher water turbidity. This study shows that combining information from benthic foraminifera, ostracods, and tintinnids provides a comprehensive insight into recent hydrographic/climatic changes in nearshore Arctic habitats, where productivity is critical for the food security of local communities.

Southern westerly winds and paleoceanography of the San Jorge Gulf (SW-Atlantic ocean, Argentina) during the last 14,000 years - Faye, Simon; Rochon, André; St-Onge, Guillaume; Vilanova, Isabel; De Vernal, Anne; Desiage, Pierre-Arnaud (Quaternary Science Reviews, 2023)

Changes in atmospheric variability in a glacial climate and the impacts on proxy data: a model intercomparison - Pausata, F. S. R.; Li, C.; Wettstein, J. J.; Nisancioglu, K. H.; Battisti, D. S. (Climate of the Past, 2009)
Abstract. Using four different climate models, we investigate sea level pressure variability in the extratropical North Atlantic in the preindustrial climate (1750 AD) and at the Last Glacial Maximum (LGM, 21 kyrs before present) in order to understand how changes in atmospheric circulation can affect signals recorded in climate proxies. In general, the models exhibit a significant reduction in interannual variance of sea level pressure at the LGM compared to pre-industrial simulations and this reduction is concentrated in winter. For the preindustrial climate, all models feature a similar leading mode of sea level pressure variability that resembles the leading mode of variability in the instrumental record: the North Atlantic Oscillation (NAO). In contrast, the leading mode of sea level pressure variability at the LGM is model dependent, but in each model different from that in the preindustrial climate. In each model, the leading (NAO-like) mode of variability explains a smaller fraction of the variance and also less absolute variance at the LGM than in the preindustrial climate. The models show that the relationship between atmospheric variability and surface climate (temperature and precipitation) variability change in different climates. Results are model-specific, but indicate that proxy signals at the LGM may be misinterpreted if changes in the spatial pattern and seasonality of surface climate variability are not taken into account.

Holocene trends in the foraminifer record from the Norwegian Sea and the North Atlantic Ocean - Andersson, C.; Pausata, F. S. R.; Jansen, E.; Risebrobakken, B.; Telford, R. J. (Climate of the Past, 2010)
Abstract. The early to mid-Holocene thermal optimum is a well-known feature in a wide variety of paleoclimate archives from the Northern Hemisphere. Reconstructed summer temperature anomalies from across northern Europe show a clear maximum around 6000 years before present (6 ka). For the marine realm, Holocene trends in sea-surface temperature reconstructions for the North Atlantic and Norwegian Sea do not exhibit a consistent pattern of early to mid-Holocene warmth. Sea-surface temperature records based on alkenones and diatoms generally show the existence of a warm early to mid-Holocene optimum. In contrast, several foraminifer and radiolarian based temperature records from the North Atlantic and Norwegian Sea show a cool mid-Holocene anomaly and a trend towards warmer temperatures in the late Holocene. In this paper, we revisit the foraminifer record from the Vøring Plateau in the Norwegian Sea. We also compare this record with published foraminifer based temperature reconstructions from the North Atlantic and with modelled (CCSM3) upper ocean temperatures. Model results indicate that while the seasonal summer warming of the sea-surface was stronger during the mid-Holocene, sub-surface depths experienced a cooling. This hydrographic setting can explain the discrepancies between the Holocene trends exhibited by phytoplankton and zooplankton based temperature proxy records.

Catastrophic Drought in the Afro-Asian Monsoon Region During Heinrich Event 1 - Stager, J. Curt; Ryves, David B.; Chase, Brian M.; Pausata, Francesco S. R. (Science, 2011)
An extreme megadrought occurred in the Afro-Asian monsoon region during an iceberg melting episode 50,000 years ago. , Between 15,000 and 18,000 years ago, large amounts of ice and meltwater entered the North Atlantic during Heinrich stadial 1. This caused substantial regional cooling, but major climatic impacts also occurred in the tropics. Here, we demonstrate that the height of this stadial, about 16,000 to 17,000 years ago (Heinrich event 1), coincided with one of the most extreme and widespread megadroughts of the past 50,000 years or more in the Afro-Asian monsoon region, with potentially serious consequences for Paleolithic cultures. Late Quaternary tropical drying commonly is attributed to southward drift of the intertropical convergence zone, but the broad geographic range of the Heinrich event 1 megadrought suggests that severe, systemic weakening of Afro-Asian rainfall systems also occurred, probably in response to sea surface cooling.

Chinese stalagmite δ18O controlled by changes in the Indian monsoon during a simulated Heinrich event - Pausata, Francesco S. R.; Battisti, David S.; Nisancioglu, Kerim H.; Bitz, Cecilia M. (Nature Geoscience, 2011)

The key role of topography in altering North Atlantic atmospheric circulation during the last glacial period - Pausata, F. S. R.; Li, C.; Wettstein, J. J.; Kageyama, M.; Nisancioglu, K. H. (Climate of the Past, 2011)
Abstract. The Last Glacial Maximum (LGM; 21 000 yr before present) was a period of low atmospheric greenhouse gas concentrations, when vast ice sheets covered large parts of North America and Europe. Paleoclimate reconstructions and modeling studies suggest that the atmospheric circulation was substantially altered compared to today, both in terms of its mean state and its variability. Here we present a suite of coupled model simulations designed to investigate both the separate and combined influences of the main LGM boundary condition changes (greenhouse gases, ice sheet topography and ice sheet albedo) on the mean state and variability of the atmospheric circulation as represented by sea level pressure (SLP) and 200-hPa zonal wind in the North Atlantic sector. We find that ice sheet topography accounts for most of the simulated changes during the LGM. Greenhouse gases and ice sheet albedo affect the SLP gradient in the North Atlantic, but the overall placement of high and low pressure centers is controlled by topography. Additional analysis shows that North Atlantic sea surface temperatures and sea ice edge position do not substantially influence the pattern of the climatological-mean SLP field, SLP variability or the position of the North Atlantic jet in the LGM.

An Abrupt Shift in the Indian Monsoon 4000 Years Ago - Berkelhammer, M.; Sinha, A.; Stott, L.; Cheng, H.; Pausata, F.S.R.; Yoshimura, K. (Geophysical Monograph Series, 2013)

North Atlantic Oscillation and tropospheric ozone variability in Europe: model analysis and measurements intercomparison - Pausata, F. S. R.; Pozzoli, L.; Vignati, E.; Dentener, F. J. (Atmospheric Chemistry and Physics, 2012)
Abstract. Ozone pollution represents a serious health and environmental problem. While ozone pollution is mostly produced by photochemistry in summer, elevated ozone concentrations can also be influenced by long range transport driven by the atmospheric circulation and stratospheric ozone intrusions. We analyze the role of large scale atmospheric circulation variability in the North Atlantic basin in determining surface ozone concentrations over Europe. Here, we show, using ground station measurements and a coupled atmosphere-chemistry model simulation for the period 1980–2005, that the North Atlantic Oscillation (NAO) does affect surface ozone concentrations – on a monthly timescale, over 10 ppbv in southwestern, central and northern Europe – during all seasons except fall. The commonly used NAO index is able to capture the link existing between atmospheric dynamics and surface ozone concentrations in winter and spring but it fails in summer. We find that the first Principal Component, computed from the time variation of the sea level pressure (SLP) field, detects the atmosphere circulation/ozone relationship not only in winter and spring but also during summer, when the atmospheric circulation weakens and regional photochemical processes peak. Given the NAO forecasting skill at intraseasonal time scale, the first Principal Component of the SLP field could be used as an indicator to identify areas more exposed to forthcoming ozone pollution events. Finally, our results suggest that the increasing baseline ozone in western and northern Europe during the 1990s could be related to the prevailing positive phase of the NAO in that period.

Impacts of changes in North Atlantic atmospheric circulation on particulate matter and human health in Europe - R. Pausata, Francesco S.; Pozzoli, Luca; Dingenen, Rita Van; Vignati, Elisabetta; Cavalli, Fabrizia; Dentener, Frank J. (Geophysical Research Letters, 2013)
In this study we use a global climate model to assess particulate matter (PM) variability induced by the North Atlantic Oscillation (NAO) in Europe during winter and the potential impact on human health of a future shift in the NAO mean state. Our study shows that extreme NAO phases in the 1990s modulated most of the interannual variability of winter PM concentrations in several European countries. Increased PM concentrations as a result of a positive shift in the mean winter NAO of one standard deviation would lead to about 5500 additional premature deaths in Mediterranean countries, compared to the simulated average PM health impact for the year 2000. In central‐northern Europe, instead, higher wind speed and increased PM removal by precipitation lead to negative PM concentration anomalies with associated health benefits. We suggest that the NAO index is a useful indicator for the role of interannual atmospheric variability on large‐scale pollution‐health impacts. , Key Points NAO impacts on PM concentrations Potential impacts of NAO shifts on human health Large‐scale atmospheric indicators as proxy for risk estimates of PM episodes

The role of aerosol in altering North Atlantic atmospheric circulation in winter and its impact on air quality - Pausata, F. S. R.; Gaetani, M.; Messori, G.; Kloster, S.; Dentener, F. J. (Atmospheric Chemistry and Physics, 2015)
Abstract. Numerical model scenarios of future climate depict a global increase in temperatures and changing precipitation patterns, primarily driven by increasing greenhouse gas (GHG) concentrations. Aerosol particles also play an important role by altering the Earth's radiation budget and consequently surface temperature. Here, we use the general circulation aerosol model ECHAM5-HAM, coupled to a mixed layer ocean model, to investigate the impacts of future air pollution mitigation strategies in Europe on winter atmospheric circulation over the North Atlantic. We analyse the extreme case of a maximum feasible end-of-pipe reduction of aerosols in the near future (2030), in combination with increasing GHG concentrations. Our results show a more positive North Atlantic Oscillation (NAO) mean state by 2030, together with a significant eastward shift of the southern centre of action of sea-level pressure (SLP). Moreover, we show a significantly increased blocking frequency over the western Mediterranean. By separating the impacts of aerosols and GHGs, our study suggests that future aerosol abatement may be the primary driver of both the eastward shift in the southern SLP centre of action and the increased blocking frequency over the western Mediterranean. These concomitant modifications of the atmospheric circulation over the Euro-Atlantic sector lead to more stagnant weather conditions that favour air pollutant accumulation, especially in the western Mediterranean sector. Changes in atmospheric circulation should therefore be included in future air pollution mitigation assessments. The indicator-based evaluation of atmospheric circulation changes presented in this work will allow an objective first-order assessment of the role of changes in wintertime circulation on future air quality in other climate model simulations.

How Do High-Latitude Volcanic Eruptions Affect Climate? - Pausata, Francesco S. R. (Eos, 2015)
High-Latitude Volcanic Eruption Impacts on Climate: Filling the Gaps; Stockholm, Sweden, 5–7 November 2014

High-latitude volcanic eruptions in the Norwegian Earth System Model: the effect of different initial conditions and of the ensemble size - Pausata, Francesco S. R.; Grini, Alf; Caballero, Rodrigo; Hannachi, Abdel; Seland, Øyvind (Tellus B: Chemical and Physical Meteorology, 2015)

Late-glacial to late-Holocene shifts in global precipitation δ18O - Jasechko, S.; Lechler, A.; Pausata, F. S. R.; Fawcett, P. J.; Gleeson, T.; Cendón, D. I.; Galewsky, J.; LeGrande, A. N.; Risi, C.; Sharp, Z. D.; Welker, J. M.; Werner, M.; et al. (Climate of the Past, 2015)
Abstract. Reconstructions of Quaternary climate are often based on the isotopic content of paleo-precipitation preserved in proxy records. While many paleo-precipitation isotope records are available, few studies have synthesized these dispersed records to explore spatial patterns of late-glacial precipitation δ18O. Here we present a synthesis of 86 globally distributed groundwater (n = 59), cave calcite (n = 15) and ice core (n = 12) isotope records spanning the late-glacial (defined as ~ 50 000 to ~ 20 000 years ago) to the late-Holocene (within the past ~ 5000 years). We show that precipitation δ18O changes from the late-glacial to the late-Holocene range from −7.1 ‰ (δ18Olate-Holocene > δ18Olate-glacial) to +1.7 ‰ (δ18Olate-glacial > δ18Olate-Holocene), with the majority (77 %) of records having lower late-glacial δ18O than late-Holocene δ18O values. High-magnitude, negative precipitation δ18O shifts are common at high latitudes, high altitudes and continental interiors (δ18Olate-Holocene > δ18Olate-glacial by more than 3 ‰). Conversely, low-magnitude, positive precipitation δ18O shifts are concentrated along tropical and subtropical coasts (δ18Olate-glacial > δ18Olate-Holocene by less than 2 ‰). Broad, global patterns of late-glacial to late-Holocene precipitation δ18O shifts suggest that stronger-than-modern isotopic distillation of air masses prevailed during the late-glacial, likely impacted by larger global temperature differences between the tropics and the poles. Further, to test how well general circulation models reproduce global precipitation δ18O shifts, we compiled simulated precipitation δ18O shifts from five isotope-enabled general circulation models simulated under recent and last glacial maximum climate states. Climate simulations generally show better inter-model and model-measurement agreement in temperate regions than in the tropics, highlighting a need for further research to better understand how inter-model spread in convective rainout, seawater δ18O and glacial topography parameterizations impact simulated precipitation δ18O. Future research on paleo-precipitation δ18O records can use the global maps of measured and simulated late-glacial precipitation isotope compositions to target and prioritize field sites.

Impacts of high-latitude volcanic eruptions on ENSO and AMOC - Pausata, Francesco S. R.; Chafik, Leon; Caballero, Rodrigo; Battisti, David S. (Proceedings of the National Academy of Sciences, 2015)
Significance In the model simulations analyzed here, large high-latitude volcanic eruptions have global and long-lasting effects on climate, altering the spatiotemporal characteristic of the El Niño–Southern Oscillation (ENSO) on both short (<1 y) and long timescales and affecting the strength of the Atlantic Meridional Overturning Circulation (AMOC). In the first 8–9 mo following the start of the eruption, El Niño-like anomalies develop over the equatorial Pacific. The large high-latitude eruptions also trigger a strengthening of the AMOC in the first 25 y after the eruption, which is associated with an increase in ENSO variability. This is then followed by a weakening of the AMOC lasting another 30–35 y, associated with decreased ENSO variability. , Large volcanic eruptions can have major impacts on global climate, affecting both atmospheric and ocean circulation through changes in atmospheric chemical composition and optical properties. The residence time of volcanic aerosol from strong eruptions is roughly 2–3 y. Attention has consequently focused on their short-term impacts, whereas the long-term, ocean-mediated response has not been well studied. Most studies have focused on tropical eruptions; high-latitude eruptions have drawn less attention because their impacts are thought to be merely hemispheric rather than global. No study to date has investigated the long-term effects of high-latitude eruptions. Here, we use a climate model to show that large summer high-latitude eruptions in the Northern Hemisphere cause strong hemispheric cooling, which could induce an El Niño-like anomaly, in the equatorial Pacific during the first 8–9 mo after the start of the eruption. The hemispherically asymmetric cooling shifts the Intertropical Convergence Zone southward, triggering a weakening of the trade winds over the western and central equatorial Pacific that favors the development of an El Niño-like anomaly. In the model used here, the specified high-latitude eruption also leads to a strengthening of the Atlantic Meridional Overturning Circulation (AMOC) in the first 25 y after the eruption, followed by a weakening lasting at least 35 y. The long-lived changes in the AMOC strength also alter the variability of the El Niño–Southern Oscillation (ENSO).

Fennoscandian freshwater control on Greenland hydroclimate shifts at the onset of the Younger Dryas - Muschitiello, Francesco; Pausata, Francesco S. R.; Watson, Jenny E.; Smittenberg, Rienk H.; Salih, Abubakr A. M.; Brooks, Stephen J.; Whitehouse, Nicola J.; Karlatou-Charalampopoulou, Artemis; Wohlfarth, Barbara (Nature Communications, 2015)
Abstract Sources and timing of freshwater forcing relative to hydroclimate shifts recorded in Greenland ice cores at the onset of Younger Dryas, ∼12,800 years ago, remain speculative. Here we show that progressive Fennoscandian Ice Sheet (FIS) melting 13,100–12,880 years ago generates a hydroclimate dipole with drier–colder conditions in Northern Europe and wetter–warmer conditions in Greenland. FIS melting culminates 12,880 years ago synchronously with the start of Greenland Stadial 1 and a large-scale hydroclimate transition lasting ∼180 years. Transient climate model simulations forced with FIS freshwater reproduce the initial hydroclimate dipole through sea-ice feedbacks in the Nordic Seas. The transition is attributed to the export of excess sea ice to the subpolar North Atlantic and a subsequent southward shift of the westerly winds. We suggest that North Atlantic hydroclimate sensitivity to FIS freshwater can explain the pace and sign of shifts recorded in Greenland at the climate transition into the Younger Dryas.

On the enigmatic similarity in Greenland δ18 O between the Oldest and Younger Dryas - Pausata, Francesco S. R.; Löfverström, Marcus (Geophysical Research Letters, 2015)
Abstract The last deglaciation (20.0–10.0 kyr B.P.) was punctuated by two major cooling events affecting the Northern Hemisphere: the Oldest Dryas (OD; 18.0–14.7 kyr B.P.) and the Younger Dryas (YD; 12.8–11.5 kyr B.P.). Greenland ice core δ 18 O temperature reconstructions suggest that the YD was as cold as the OD, despite a 50 ppmv increase in atmospheric CO 2 , while modeling studies suggest that the YD was approximately 4–5°C warmer than the OD. This discrepancy has been surmised to result from changes in the origin of the water vapor delivered to Greenland; however, this hypothesis has not been hitherto tested. Here we use an atmospheric circulation model with an embedded moisture‐tracing module to investigate atmospheric processes that may have been responsible for the similar δ 18 O values during the OD and YD. Our results show that the summer‐to‐winter precipitation ratio over central Greenland in the OD is twice as high as in the YD experiment, which shifts the δ 18 O signal toward warmer (summer) temperatures (enriched δ 18 O values and it accounts for ~45% of the expected YD‐OD δ 18 O difference). A change in the inversion (cloud) temperature relationship between the two climate states further contributes (~20%) to altering the δ 18 O‐temperature‐relation model. Our experiments also show a 7% decrease of δ 18 O‐depleted precipitation from distant regions (e.g., the Pacific Ocean) in the OD, hence further contributing (15–20%) in masking the actual temperature difference. All together, these changes provide a physical explanation for the ostensible similarity in the ice core δ 18 O temperature reconstructions in Greenland during OD and YD. , Key Points Precipitation seasonality and inversion temperature changes behind YD‐OD δ 18 O enigma Local processes changes accounting up to 65% of the expected YD‐OD δ 18 O difference Moisture transport changes from the Pacific accounting only up to 20% of the expected YD‐OD δ 18 O difference

Deglacial Indian monsoon failure and North Atlantic stadials linked by Indian Ocean surface cooling - Tierney, Jessica E.; Pausata, Francesco S. R.; deMenocal, Peter (Nature Geoscience, 2016)

Impacts of dust reduction on the northward expansion of the African monsoon during the Green Sahara period - Pausata, Francesco S.R.; Messori, Gabriele; Zhang, Qiong (Earth and Planetary Science Letters, 2016)

How Will Sea Ice Loss Affect the Greenland Ice Sheet? - Pausata, Francesco S. R.; LeGrande, Allegra; Roberts, William (Eos, 2016)
On the Puzzling Features of Greenland Ice-Core Isotopic Composition; Copenhagen, Denmark, 26–28 October 2015

Sources of Sahelian‐Sudan moisture: Insights from a moisture‐tracing atmospheric model - Salih, Abubakr A. M.; Zhang, Qiong; Pausata, Francesco S. R.; Tjernström, Michael (Journal of Geophysical Research: Atmospheres, 2016)
Abstract The summer rainfall across Sahelian‐Sudan is one of the main sources of water for agriculture, human, and animal needs. However, the rainfall is characterized by large interannual variability, which has attracted extensive scientific efforts to understand it. This study attempts to identify the source regions that contribute to the Sahelian‐Sudan moisture budget during July through September. We have used an atmospheric general circulation model with an embedded moisture‐tracing module (Community Atmosphere Model version 3), forced by observed (1979–2013) sea‐surface temperatures. The result suggests that about 40% of the moisture comes with the moisture flow associated with the seasonal migration of the Intertropical Convergence Zone (ITCZ) and originates from Guinea Coast, central Africa, and the Western Sahel. The Mediterranean Sea, Arabian Peninsula, and South Indian Ocean regions account for 10.2%, 8.1%, and 6.4%, respectively. Local evaporation and the rest of the globe supply the region with 20.3% and 13.2%, respectively. We also compared the result from this study to a previous analysis that used the Lagrangian model FLEXPART forced by ERA‐Interim. The two approaches differ when comparing individual regions, but are in better agreement when neighboring regions of similar atmospheric flow features are grouped together. Interannual variability with the rainfall over the region is highly correlated with contributions from regions that are associated with the ITCZ movement, which is in turn linked to the Atlantic Multidecadal Oscillation. Our result is expected to provide insights for the effort on seasonal forecasting of the rainy season over Sahelian Sudan. , Key Points The moisture associated with ITCZ flow accounts for about 40%‐50% of the precipitated water The local evaporation provides about 20% of the precipitated water The multiyear variability in the rainfall seems to be linked to the AMO

ENSO response to high‐latitude volcanic eruptions in the Northern Hemisphere: The role of the initial conditions - Pausata, Francesco S. R.; Karamperidou, Christina; Caballero, Rodrigo; Battisti, David S. (Geophysical Research Letters, 2016)
Abstract A large ensemble of Earth System Model simulations is analyzed to show that high‐latitude Northern Hemisphere eruptions give rise to El Niño‐like anomalies in the winter following the eruption, the amplitude of which depends on the state of the tropical Pacific at the time of the eruption. The El Niño‐like anomalies are almost three times larger when the eruption occurs during an incipient La Niña or during a neutral state compared to an incipient El Niño. The differential response results from stronger atmosphere‐ocean coupling and extra‐tropical feedbacks during an incipient La Niña compared to El Niño. Differences in the response continue through the second and third years following the eruption. When the eruption happens in a year of an incipient El Niño, a large cold (La Niña‐like) anomaly develops in year 2; if the eruption occurs in a year of an incipient La Niña, no anomalies are simulated in year 2 and a La Niña‐like response appears in year 3. After the El Niño‐like anomaly in the first winter, the overall tendency of ENSO in the following 2 years is toward a La Niña state. Our results highlight the high sensitivity of tropical Pacific dynamics under volcanic forcing to the ENSO initial state and lay the groundwork for improved predictions of the global climatic response to high‐latitude volcanic eruptions. , Key Points HL eruptions alter the mean state of ENSO, and detectable anomalies are seen up to 3 years after the eruption Stronger El Niño‐like anomalies on year 1 when eruptions occurs under developing La Niñas La Niña‐like anomalies on year 2 and year 3 when eruptions occurs under developing El Niños and La Niñas, respectively

The Model Intercomparison Project on the climatic response toVolcanic forcing (VolMIP): experimental design and forcing input data for CMIP6 - Zanchettin, Davide; Khodri, Myriam; Timmreck, Claudia; Toohey, Matthew; Schmidt, Anja; Gerber, Edwin P.; Hegerl, Gabriele; Robock, Alan; Pausata, Francesco S. R.; Ball, William T.; Bauer, Susanne E.; Bekki, Slimane; et al. (Geoscientific Model Development, 2016)
Abstract. The enhancement of the stratospheric aerosol layer by volcanic eruptions induces a complex set of responses causing global and regional climate effects on a broad range of timescales. Uncertainties exist regarding the climatic response to strong volcanic forcing identified in coupled climate simulations that contributed to the fifth phase of the Coupled Model Intercomparison Project (CMIP5). In order to better understand the sources of these model diversities, the Model Intercomparison Project on the climatic response to Volcanic forcing (VolMIP) has defined a coordinated set of idealized volcanic perturbation experiments to be carried out in alignment with the CMIP6 protocol. VolMIP provides a common stratospheric aerosol data set for each experiment to minimize differences in the applied volcanic forcing. It defines a set of initial conditions to assess how internal climate variability contributes to determining the response. VolMIP will assess to what extent volcanically forced responses of the coupled ocean–atmosphere system are robustly simulated by state-of-the-art coupled climate models and identify the causes that limit robust simulated behavior, especially differences in the treatment of physical processes. This paper illustrates the design of the idealized volcanic perturbation experiments in the VolMIP protocol and describes the common aerosol forcing input data sets to be used.

Climate effects of a hypothetical regional nuclear war: Sensitivity to emission duration and particle composition - Pausata, Francesco S. R.; Lindvall, Jenny; Ekman, Annica M. L.; Svensson, Gunilla (Earth's Future, 2016)
Abstract Here, we use a coupled atmospheric‐ocean‐aerosol model to investigate the plume development and climate effects of the smoke generated by fires following a regional nuclear war between emerging third‐world nuclear powers. We simulate a standard scenario where 5 Tg of black carbon ( BC ) is emitted over 1 day in the upper troposphere–lower stratosphere. However, it is likely that the emissions from the fires ignited by bomb detonations include a substantial amount of particulate organic matter ( POM ) and that they last more than 1 day. We therefore test the sensitivity of the aerosol plume and climate system to the BC / POM ratio (1:3, 1:9) and to the emission length (1 day, 1 week, 1 month). We find that in general, an emission length of 1 month substantially reduces the cooling compared to the 1‐day case, whereas taking into account POM emissions notably increases the cooling and the reduction of precipitation associated with the nuclear war during the first year following the detonation. Accounting for POM emissions increases the particle size in the short‐emission‐length scenarios (1 day/1 week), reducing the residence time of the injected particle. While the initial cooling is more intense when including POM emission, the long‐lasting effects, while still large, may be less extreme compared to the BC ‐only case. Our study highlights that the emission altitude reached by the plume is sensitive to both the particle type emitted by the fires and the emission duration. Consequently, the climate effects of a nuclear war are strongly dependent on these parameters. , Key Points Importance of including OC when simulating nuclear wars Importance of the fire emission length when simulating nuclear wars

Rainfall regimes of the Green Sahara - Tierney, Jessica E.; Pausata, Francesco S. R.; deMenocal, Peter B. (Science Advances, 2017)
We estimate rainfall during the “Green Sahara” period. , During the “Green Sahara” period (11,000 to 5000 years before the present), the Sahara desert received high amounts of rainfall, supporting diverse vegetation, permanent lakes, and human populations. Our knowledge of rainfall rates and the spatiotemporal extent of wet conditions has suffered from a lack of continuous sedimentary records. We present a quantitative reconstruction of western Saharan precipitation derived from leaf wax isotopes in marine sediments. Our data indicate that the Green Sahara extended to 31°N and likely ended abruptly. We find evidence for a prolonged “pause” in Green Sahara conditions 8000 years ago, coincident with a temporary abandonment of occupational sites by Neolithic humans. The rainfall rates inferred from our data are best explained by strong vegetation and dust feedbacks; without these mechanisms, climate models systematically fail to reproduce the Green Sahara. This study suggests that accurate simulations of future climate change in the Sahara and Sahel will require improvements in our ability to simulate vegetation and dust feedbacks.

On the links between meteorological variables, aerosols, and tropical cyclone frequency in individual ocean basins - Chiacchio, Marc; Pausata, Francesco S. R.; Messori, Gabriele; Hannachi, Abdel; Chin, Mian; Önskog, Thomas; Ekman, Annica M. L.; Barrie, Leonard (Journal of Geophysical Research: Atmospheres, 2017)
Abstract A generalized linear model based on Poisson regression has been used to assess the impact of environmental variables modulating tropical cyclone frequency in six main cyclone development areas: the East Pacific, West Pacific, North Atlantic, North Indian, South Indian, and South Pacific. The analysis covers the period 1980–2009 and focuses on widely used meteorological parameters including wind shear, sea surface temperature, and relative humidity from different reanalyses as well as aerosol optical depth for different compounds simulated by the Goddard Chemistry Aerosol Radiation and Transport model. Circulation indices are also included. Cyclone frequency is obtained from the International Best Track Archive for Climate Stewardship. A strong link is found between cyclone frequency and the relative sea surface temperature, Atlantic Meridional Mode, and wind shear with significant explained log likelihoods in the North Atlantic of 37%, 27%, and 28%, respectively. A significant impact of black carbon and organic aerosols on cyclone frequency is found over the North Indian Ocean, with explained log likelihoods of 27%. A weaker but still significant impact is found for observed dust aerosols in the North Atlantic with an explained log likelihood of 11%. Changes in lower stratospheric temperatures explain 28% of the log likelihood in the North Atlantic. Lower stratospheric temperatures from a subset of Coupled Model Intercomparison Project Phase 5 models properly simulate the warming and subsequent cooling of the lower stratosphere that follows a volcanic eruption but underestimates the cooling by about 0.5°C. , Key Points Significant impact of black carbon and organic aerosols Significant impact of observed dust aerosols in the North Atlantic Lower stratospheric temperatures explain 28% of the log likelihood

Future Response of Temperature and Precipitation to Reduced Aerosol Emissions as Compared with Increased Greenhouse Gas Concentrations - Acosta Navarro, Juan C.; Ekman, Annica M. L.; Pausata, Francesco S. R.; Lewinschal, Anna; Varma, Vidya; Seland, Øyvind; Gauss, Michael; Iversen, Trond; Kirkevåg, Alf; Riipinen, Ilona; Hansson, Hans Christen (Journal of Climate, 2017)
Abstract Experiments with a climate model (NorESM1) were performed to isolate the effects of aerosol particles and greenhouse gases on surface temperature and precipitation in simulations of future climate. The simulations show that by 2025–49 a reduction of aerosol emissions from fossil fuels following a maximum technically feasible reduction (MFR) scenario could lead to a global and Arctic warming of 0.26 and 0.84 K, respectively, as compared with a simulation with fixed aerosol emissions at the level of 2005. If fossil fuel emissions of aerosols follow a current legislation emissions (CLE) scenario, the NorESM1 model simulations yield a nonsignificant change in global and Arctic average surface temperature as compared with aerosol emissions fixed at year 2005. The corresponding greenhouse gas effect following the representative concentration pathway 4.5 (RCP4.5) emission scenario leads to a global and Arctic warming of 0.35 and 0.94 K, respectively. The model yields a marked annual average northward shift in the intertropical convergence zone with decreasing aerosol emissions and subsequent warming of the Northern Hemisphere. The shift is most pronounced in the MFR scenario but also visible in the CLE scenario. The modeled temperature response to a change in greenhouse gas concentrations is relatively symmetric between the hemispheres, and there is no marked shift in the annual average position of the intertropical convergence zone. The strong reduction in aerosol emissions in the MFR scenario also leads to a net southward cross-hemispheric energy transport anomaly both in the atmosphere and ocean, and enhanced monsoon circulation in Southeast Asia and East Asia causing an increase in precipitation over a large part of this region.

Tropical cyclone activity enhanced by Sahara greening and reduced dust emissions during the African Humid Period - Pausata, Francesco S. R.; Emanuel, Kerry A.; Chiacchio, Marc; Diro, Gulilat T.; Zhang, Qiong; Sushama, Laxmi; Stager, J. Curt; Donnelly, Jeffrey P. (Proceedings of the National Academy of Sciences, 2017)
Significance Our modeling study shows the crucial role of vegetation cover over the Sahara and reduced dust emission in altering tropical cyclone activity during the mid-Holocene (6,000 yBP). Our results also demonstrate how these regional changes in land cover and dust emission are able to affect areas far afield through changes of large-scale atmospheric circulation. Our study strongly suggests that an appropriate representation of land cover and dust emission is of paramount importance to be able to capture past—and potentially future—climate changes. , Tropical cyclones (TCs) can have devastating socioeconomic impacts. Understanding the nature and causes of their variability is of paramount importance for society. However, historical records of TCs are too short to fully characterize such changes and paleo-sediment archives of Holocene TC activity are temporally and geographically sparse. Thus, it is of interest to apply physical modeling to understanding TC variability under different climate conditions. Here we investigate global TC activity during a warm climate state (mid-Holocene, 6,000 yBP) characterized by increased boreal summer insolation, a vegetated Sahara, and reduced dust emissions. We analyze a set of sensitivity experiments in which not only solar insolation changes are varied but also vegetation and dust concentrations. Our results show that the greening of the Sahara and reduced dust loadings lead to more favorable conditions for tropical cyclone development compared with the orbital forcing alone. In particular, the strengthening of the West African Monsoon induced by the Sahara greening triggers a change in atmospheric circulation that affects the entire tropics. Furthermore, whereas previous studies suggest lower TC activity despite stronger summer insolation and warmer sea surface temperature in the Northern Hemisphere, accounting for the Sahara greening and reduced dust concentrations leads instead to an increase of TC activity in both hemispheres, particularly over the Caribbean basin and East Coast of North America. Our study highlights the importance of regional changes in land cover and dust concentrations in affecting the potential intensity and genesis of past TCs and suggests that both factors may have appreciable influence on TC activity in a future warmer climate.

The role of the meridional sea surface temperature gradient in controlling the Caribbean low‐level jet - Maldonado, Tito; Rutgersson, Anna; Caballero, Rodrigo; Pausata, Francesco S. R.; Alfaro, Eric; Amador, Jorge (Journal of Geophysical Research: Atmospheres, 2017)
Abstract The Caribbean low‐level jet (CLLJ) is an important modulator of regional climate, especially precipitation, in the Caribbean and Central America. Previous work has inferred, due to their semiannual cycle, an association between CLLJ strength and meridional sea surface temperature (SST) gradients in the Caribbean Sea, suggesting that the SST gradients may control the intensity and vertical shear of the CLLJ. In addition, both the horizontal and vertical structure of the jet have been related to topographic effects via interaction with the mountains in Northern South America (NSA), including funneling effects and changes in the meridional geopotential gradient. Here we test these hypotheses, using an atmospheric general circulation model to perform a set of sensitivity experiments to examine the impact of both SST gradients and topography on the CLLJ. In one sensitivity experiment, we remove the meridional SST gradient over the Caribbean Sea and in the other, we flatten the mountains over NSA. Our results show that the SST gradient and topography have little or no impact on the jet intensity, vertical, and horizontal wind shears, contrary to previous works. However, our findings do not discount a possible one‐way coupling between the SST and the wind over the Caribbean Sea through friction force. We also examined an alternative approach based on barotropic instability to understand the CLLJ intensity, vertical, and horizontal wind shears. Our results show that the current hypothesis about the CLLJ must be reviewed in order to fully understand the atmospheric dynamics governing the Caribbean region. , Key Points Atmospheric dynamics in the Caribbean SST over the Caribbean Sea is examined as kinetic energy source for the CLLJ Impact of meridional SST gradient on the vertical structure of CLLJ

Understanding the Mechanisms behind the Northward Extension of the West African Monsoon during the Mid-Holocene - Gaetani, Marco; Messori, Gabriele; Zhang, Qiong; Flamant, Cyrille; Pausata, Francesco S. R. (Journal of Climate, 2017)
Abstract Understanding the West African monsoon (WAM) dynamics in the mid-Holocene (MH) is a crucial issue in climate modeling, because numerical models typically fail to reproduce the extensive precipitation suggested by proxy evidence. This discrepancy may be largely due to the assumption of both unrealistic land surface cover and atmospheric aerosol concentration. In this study, the MH environment is simulated in numerical experiments by imposing extensive vegetation over the Sahara and the consequent reduction in airborne dust concentration. A dramatic increase in precipitation is simulated across the whole of West Africa, up to the Mediterranean coast. This precipitation response is in better agreement with proxy data, in comparison with the case in which only changes in orbital forcing are considered. Results show a substantial modification of the monsoonal circulation, characterized by an intensification of large-scale deep convection through the entire Sahara, and a weakening and northward shift (~6.5°) of the African easterly jet. The greening of the Sahara also leads to a substantial reduction in the African easterly wave activity and associated precipitation. The reorganization of the regional atmospheric circulation is driven by the vegetation effect on radiative forcing and associated heat fluxes, with the reduction in dust concentration to enhance this response. The results for the WAM in the MH present important implications for understanding future climate scenarios in the region and in teleconnected areas, in the context of projected wetter conditions in West Africa.

Toward predicting volcanically-forced decadal climate variability - Zanchettin, Davide; Pausata, Francesco Sr; Khodri, Myriam; Timmreck, Claudia; Graf, Hans; Jungclaus, Johann H; Robock, Alan; Rubino, Angelo; Thompson, Vikki (Past Global Changes Magazine, 2017)

Greening of the Sahara suppressed ENSO activity during the mid-Holocene - Pausata, Francesco S. R.; Zhang, Qiong; Muschitiello, Francesco; Lu, Zhengyao; Chafik, Léon; Niedermeyer, Eva M.; Stager, J. Curt; Cobb, Kim M.; Liu, Zhengyu (Nature Communications, 2017)
Abstract The evolution of the El Niño-Southern Oscillation (ENSO) during the Holocene remains uncertain. In particular, a host of new paleoclimate records suggest that ENSO internal variability or other external forcings may have dwarfed the fairly modest ENSO response to precessional insolation changes simulated in climate models. Here, using fully coupled ocean-atmosphere model simulations, we show that accounting for a vegetated and less dusty Sahara during the mid-Holocene relative to preindustrial climate can reduce ENSO variability by 25%, more than twice the decrease obtained using orbital forcing alone. We identify changes in tropical Atlantic mean state and variability caused by the momentous strengthening of the West Africa Monsoon (WAM) as critical factors in amplifying ENSO’s response to insolation forcing through changes in the Walker circulation. Our results thus suggest that potential changes in the WAM due to anthropogenic warming may influence ENSO variability in the future as well.

The PMIP4 contribution to CMIP6 – Part 2: Two interglacials, scientific objective and experimental design for Holocene and Last Interglacial simulations - Otto-Bliesner, Bette L.; Braconnot, Pascale; Harrison, Sandy P.; Lunt, Daniel J.; Abe-Ouchi, Ayako; Albani, Samuel; Bartlein, Patrick J.; Capron, Emilie; Carlson, Anders E.; Dutton, Andrea; Fischer, Hubertus; Goelzer, Heiko; et al. (Geoscientific Model Development, 2017)
Abstract. Two interglacial epochs are included in the suite of Paleoclimate Modeling Intercomparison Project (PMIP4) simulations in the Coupled Model Intercomparison Project (CMIP6). The experimental protocols for simulations of the mid-Holocene (midHolocene, 6000 years before present) and the Last Interglacial (lig127k, 127 000 years before present) are described here. These equilibrium simulations are designed to examine the impact of changes in orbital forcing at times when atmospheric greenhouse gas levels were similar to those of the preindustrial period and the continental configurations were almost identical to modern ones. These simulations test our understanding of the interplay between radiative forcing and atmospheric circulation, and the connections among large-scale and regional climate changes giving rise to phenomena such as land–sea contrast and high-latitude amplification in temperature changes, and responses of the monsoons, as compared to today. They also provide an opportunity, through carefully designed additional sensitivity experiments, to quantify the strength of atmosphere, ocean, cryosphere, and land-surface feedbacks. Sensitivity experiments are proposed to investigate the role of freshwater forcing in triggering abrupt climate changes within interglacial epochs. These feedback experiments naturally lead to a focus on climate evolution during interglacial periods, which will be examined through transient experiments. Analyses of the sensitivity simulations will also focus on interactions between extratropical and tropical circulation, and the relationship between changes in mean climate state and climate variability on annual to multi-decadal timescales. The comparative abundance of paleoenvironmental data and of quantitative climate reconstructions for the Holocene and Last Interglacial make these two epochs ideal candidates for systematic evaluation of model performance, and such comparisons will shed new light on the importance of external feedbacks (e.g., vegetation, dust) and the ability of state-of-the-art models to simulate climate changes realistically.

Enhanced ice sheet melting driven by volcanic eruptions during the last deglaciation - Muschitiello, Francesco; Pausata, Francesco S. R.; Lea, James M.; Mair, Douglas W. F.; Wohlfarth, Barbara (Nature Communications, 2017)
Abstract Volcanic eruptions can impact the mass balance of ice sheets through changes in climate and the radiative properties of the ice. Yet, empirical evidence highlighting the sensitivity of ancient ice sheets to volcanism is scarce. Here we present an exceptionally well-dated annual glacial varve chronology recording the melting history of the Fennoscandian Ice Sheet at the end of the last deglaciation (∼13,200–12,000 years ago). Our data indicate that abrupt ice melting events coincide with volcanogenic aerosol emissions recorded in Greenland ice cores. We suggest that enhanced ice sheet runoff is primarily associated with albedo effects due to deposition of ash sourced from high-latitude volcanic eruptions. Climate and snowpack mass-balance simulations show evidence for enhanced ice sheet runoff under volcanically forced conditions despite atmospheric cooling. The sensitivity of past ice sheets to volcanic ashfall highlights the need for an accurate coupling between atmosphere and ice sheet components in climate models.

The impact of future atmospheric circulation changes over the Euro-Atlantic sector on urban PM2.5 concentrations - Messori, Gabriele; Van Wees, Dave; Pausata, Francesco S.R.; Navarro, Juan C. Acosta; Hannachi, Abdel; Dentener, Frank J. (Tellus B: Chemical and Physical Meteorology, 2018)

On the low-frequency variability of wintertime Euro-Atlantic planetary wave-breaking - Messori, Gabriele; Davini, Paolo; Alvarez-Castro, M. Carmen; Pausata, Francesco S. R.; Yiou, Pascal; Caballero, Rodrigo (Climate Dynamics, 2019)

The water cycle of the mid‐Holocene West African monsoon: The role of vegetation and dust emission changes - Messori, Gabriele; Gaetani, Marco; Zhang, Qiang; Zhang, Qiong; Pausata, Francesco S. R. (International Journal of Climatology, 2019)
During the mid‐Holocene (6 kyr BP), West Africa experienced a much stronger and geographically extensive monsoon than in the present day. Changes in orbital forcing, vegetation and dust emissions from the Sahara have been identified as key factors driving this intensification. Here, we analyse how the timing, origin and convergence of moisture fluxes contributing to the monsoonal precipitation change under a range of scenarios: orbital forcing only; orbital and vegetation forcings (Green Sahara); orbital, vegetation and dust forcings (Green Sahara‐reduced dust). We further compare our results to a range of reconstructions of mid‐Holocene precipitation from palaeoclimate archives. In our simulations, the greening of the Sahara leads to a cyclonic water vapour flux anomaly over North Africa with an anomalous westerly flow bringing large amounts of moisture into the Sahel from the Atlantic Ocean. Changes in atmospheric dust under a vegetated Sahara shift the anomalous moisture advection pattern northwards, increasing both moisture convergence and precipitation recycling over the northern Sahel and Sahara and the associated precipitation during the boreal summer. During this season, under both the Green Sahara and Green Sahara‐reduced dust scenarios, local recycling in the Saharan domain exceeds that of the Sahel. This points to local recycling as an important factor modulating vegetation‐precipitation feedbacks and the impact of Saharan dust emissions. Our results also show that temperature and evapotranspiration over the Sahara in the mid‐Holocene are close to Sahelian pre‐industrial values. This suggests that pollen‐based paleoclimate reconstructions of precipitation during the Green Sahara period are likely not biased by possible large evapotranspiration changes in the region.

Tropical cyclone activity affected by volcanically induced ITCZ shifts - Pausata, Francesco S. R.; Camargo, Suzana J. (Proceedings of the National Academy of Sciences, 2019)
Significance Volcanic eruptions can inject a large amount of aerosol particles, which interact with solar radiation and consequently can affect the climate worldwide, hence the intensity and frequency of extreme events for a few years following the eruption. However, only a handful of studies have investigated the impacts of volcanic eruptions on tropical cyclone activity. Through a set of sensitivity modeling experiments, our study demonstrates that volcanic eruptions by shifting the Intertropical convergence zone can impact tropical cyclone activity up to 4 years following the eruption. These results will prove valuable to society, allowing us to better prepare for the consequences of changes in tropical cyclone activity following large volcanic eruptions. , Volcanic eruptions can affect global climate through changes in atmospheric and ocean circulation, and therefore could impact tropical cyclone (TC) activity. Here, we use ensemble simulations performed with an Earth System Model to investigate the impact of strong volcanic eruptions occurring in the tropical Northern (NH) and Southern (SH) Hemisphere on the large-scale environmental factors that affect TCs. Such eruptions cause a strong asymmetrical hemispheric cooling, either in the NH or SH, which shifts the Intertropical Convergence Zone (ITCZ) southward or northward, respectively. The ITCZ shift and the associated surface temperature anomalies then cause changes to the genesis potential indices and TC potential intensity. The effect of the volcanic eruptions on the ITCZ and hence on TC activity lasts for at least 4 years. Finally, our analysis suggests that volcanic eruptions do not lead to an overall global reduction in TC activity but rather a redistribution following the ITCZ movement. On the other hand, the volcanically induced changes in El Niño-Southern Oscillation (ENSO) or sea-surface temperature do not seem to have a significant impact on TC activity as previously suggested.

Enhanced Himalayan Glacial Melting During YD and H1 Recorded in the Northern Bay of Bengal - Weldeab, Syee; Rühlemann, Carsten; Bookhagen, Bodo; Pausata, Francesco S. R.; Perez‐Lua, Fabiola M. (Geochemistry, Geophysics, Geosystems, 2019)
Abstract Ocean‐land thermal feedback mechanisms in the Indian Summer Monsoon (ISM) domain are an important but not well understood component of regional climate dynamics. Here we present a δ 18 O record analyzed in the mixed‐layer dwelling planktonic foraminifer Globigerinoides ruber ( sensu stricto ) from the northernmost Bay of Bengal (BoB). The δ 18 O time series provides a spatially integrated measure of monsoonal precipitation and Himalayan meltwater runoff into the northern BoB and reveals two brief episodes of anomalously low δ 18 O values between 16.3±0.4 and 16±0.5 and 12.6±0.4 and 12.3±0.4 thousand years before present. The timing of these events is centered at Heinrich event 1 and the Younger Dryas, well‐known phases of weak northern hemisphere monsoon systems. Numerical climate model experiments, simulating Heinrich event‐like conditions, suggest a surface warming over the monsoon‐dominated Himalaya and foreland in response to ISM weakening. Corroborating the simulation results, our analysis of published moraine exposure ages in the monsoon‐dominated Himalaya indicates enhanced glacier retreats that, considering age model uncertainties, coincide and overlap with the episodes of anomalously low δ 18 O values in the northernmost BoB. Our climate proxy and simulation results provide insights into past regional climate dynamics, suggesting reduced cloud cover, increased solar radiation, and air warming of the Himalaya and foreland areas and, as a result, glacier mass losses in response to weakened ISM. , Plain Language Summary Indian Summer Monsoon rainfall and Himalayan glacier/snow melts constitute the main water source for the densely populated Indian subcontinent. Better understanding of how future climate changes will affect the monsoon rainfall and Himalayan glaciers requires a long climate record. In this study, we create a 13,000‐year‐long climate record that allows us to better understand the response of Indian Summer Monsoon rainfall and Himalayan glaciers to past climate changes. The focus of our study is the time window between 9,000 and 22,000 years ago, an episode where the global climate experienced large and rapid changes. Our sediment record from the northern Bay of Bengal and climate change simulation indicate that during episodes of weak monsoon, the melting of the Himalayan glaciers increases substantially significantly. This is because the weakening of the monsoon results in less cloud cover and, as a result, the surface receives more sunlight and causes glacier melting. , Key Points Core sediments from the northern Bay of Bengal are a viable archive to reconstruct past changes in monsoonal and Himalayan meltwater runoff Weak monsoon reduces cloud cover and leads to increased radiative flux over the Himalaya and foreland areas and causes glacier mass loss A spatially integrated record of monsoon and Himalayan climate provides insights into regional climate dynamics

Northern Hemisphere Land Monsoon Precipitation Increased by the Green Sahara During Middle Holocene - Sun, Weiyi; Wang, Bin; Zhang, Qiong; Pausata, Francesco S. R.; Chen, Deliang; Lu, Guonian; Yan, Mi; Ning, Liang; Liu, Jian (Geophysical Research Letters, 2019)
Abstract Changes in land cover and dust emission may significantly influence the Northern Hemisphere land monsoon precipitation (NHLMP), but observations are too short to fully evaluate their impacts. The “Green Sahara” during the mid‐Holocene (6,000 years BP) provides an opportunity to unravel these mechanisms. Here we show that during the mid‐Holocene, most of the NHLMP changes revealed by proxy data are reproduced by the Earth System model results when the Saharan vegetation cover and dust reduction are taken into consideration. The simulated NHLMP significantly increases by 33.10% under the effect of the Green Sahara. The North African monsoon precipitation increases most significantly. Additionally, the Saharan vegetation (dust reduction under vegetated Sahara) alone remotely intensifies the Asian (North American) monsoon precipitation through large‐scale atmospheric circulation changes. These findings imply that future variations in land cover and dust emissions may appreciably influence the NHLMP. , Plain Language Summary Northern Hemisphere land monsoon precipitation (NHLMP) provides water resources for about two thirds of the world's population, which is vital for infrastructure planning, disaster mitigation, food security, and economic development. Changes in land cover and dust emissions may significantly influence the NHLMP, but observations are too short to understand the mechanisms. The Sahara Desert was once covered by vegetation and dust emission was substantially reduced during the mid‐Holocene (6,000 years BP), which provides an opportunity to test the models' capability and unravel these mechanisms. Here we use an Earth System model and find that when the Saharan vegetation and dust reduction are taken into consideration, the simulated annual mean precipitation over most of the NHLM regions shows a closer agreement with proxy records. The sensitivity experiments show that the North African monsoon precipitation increases most significantly under the regional effects of “Green Sahara.” The Saharan vegetation (dust reduction under vegetated Sahara) alone also remotely increases the Asian (North American) monsoon precipitation through large‐scale atmospheric circulation changes. The knowledge gained from this study is critical for improved understanding of the potential impacts of the land cover and dust changes on the projected future monsoon change. , Key Points The first study of the impact of Saharan vegetation and dust reduction on the NHLMP Comparison with proxy records shows the effect of the Green Sahara improves the simulated NHLMP The Saharan vegetation and dust reduction significantly increase the NHLMP by 33.10%

Northward extension of the East Asian summer monsoon during the mid-Holocene - Piao, Jinling; Chen, Wen; Wang, Lin; Pausata, Francesco S.R.; Zhang, Qiong (Global and Planetary Change, 2020)

Hydroclimate in the Pamirs Was Driven by Changes in Precipitation‐Evaporation Seasonality Since the Last Glacial Period - Aichner, Bernhard; Makhmudov, Zafar; Rajabov, Ilhomjon; Zhang, Qiong; Pausata, Francesco S. R.; Werner, Martin; Heinecke, Liv; Kuessner, Marie L.; Feakins, Sarah J.; Sachse, Dirk; Mischke, Steffen (Geophysical Research Letters, 2019)
Abstract The Central Asian Pamir Mountains (Pamirs) are a high‐altitude region sensitive to climatic change, with only few paleoclimatic records available. To examine the glacial‐interglacial hydrological changes in the region, we analyzed the geochemical parameters of a 31‐kyr record from Lake Karakul and performed a set of experiments with climate models to interpret the results. δD values of terrestrial biomarkers showed insolation‐driven trends reflecting major shifts of water vapor sources. For aquatic biomarkers, positive δD shifts driven by changes in precipitation seasonality were observed at ca. 31–30, 28–26, and 17–14 kyr BP. Multiproxy paleoecological data and modelling results suggest that increased water availability, induced by decreased summer evaporation, triggered higher lake levels during those episodes, possibly synchronous to northern hemispheric rapid climate events. We conclude that seasonal changes in precipitation‐evaporation balance significantly influenced the hydrological state of a large waterbody such as Lake Karakul, while annual precipitation amount and inflows remained fairly constant. , Plain Language Summary Lakes in arid Central Asia are particularly susceptible to the rise and fall of lake levels as a consequence of climatic changes. To evaluate drivers behind this phenomenon, we developed a record of humidity and lake levels throughout the last 31,000 years from a high‐altitude lake in the Pamir Mountains. Herefore, we combined hydrological and ecological reconstructions with climate model experiments. Results show that neither the enhanced inflow by melting glaciers nor the significantly increased precipitation amount was responsible for higher lake levels during the studied interval. Instead, reduced summer evaporation during cold episodes was the major trigger for lake transgressions. These fluctuations were driven by changes in radiative forcing (i.e., insolation and hence temperature change) as a consequence of changes in the Earth's orbit around the Sun. As such, our results suggest that a significant impact on lake levels in arid regions is also to be expected by the current anthropogenically driven global warming. , Key Points Proxies for hydroclimate and catchment ecology show insolation‐driven trends, with higher δD values during the LGM similar to outputs from climate models Reduced summer evaporation during cold episodes increased water availability Increased summer moisture caused higher lake levels at 31–30, 28–26, and 17–14 kyr BP coinciding with northern hemispheric rapid climate events

Development and testing scenarios for implementing land use and land cover changes during the Holocene in Earth system model experiments - Harrison, Sandy P.; Gaillard, Marie-José; Stocker, Benjamin D.; Vander Linden, Marc; Klein Goldewijk, Kees; Boles, Oliver; Braconnot, Pascale; Dawson, Andria; Fluet-Chouinard, Etienne; Kaplan, Jed O.; Kastner, Thomas; Pausata, Francesco S. R.; et al. (Geoscientific Model Development, 2020)
Abstract. Anthropogenic changes in land use and land cover (LULC) during the pre-industrial Holocene could have affected regional and global climate. Existing scenarios of LULC changes during the Holocene are based on relatively simple assumptions and highly uncertain estimates of population changes through time. Archaeological and palaeoenvironmental reconstructions have the potential to refine these assumptions and estimates. The Past Global Changes (PAGES) LandCover6k initiative is working towards improved reconstructions of LULC globally. In this paper, we document the types of archaeological data that are being collated and how they will be used to improve LULC reconstructions. Given the large methodological uncertainties involved, both in reconstructing LULC from the archaeological data and in implementing these reconstructions into global scenarios of LULC, we propose a protocol to evaluate the revised scenarios using independent pollen-based reconstructions of land cover and climate. Further evaluation of the revised scenarios involves carbon cycle model simulations to determine whether the LULC reconstructions are consistent with constraints provided by ice core records of CO2 evolution and modern-day LULC. Finally, the protocol outlines how the improved LULC reconstructions will be used in palaeoclimate simulations in the Palaeoclimate Modelling Intercomparison Project to quantify the magnitude of anthropogenic impacts on climate through time and ultimately to improve the realism of Holocene climate simulations.

Initiation of a stable convective hydroclimatic regime in Central America circa 9000 years BP - Winter, Amos; Zanchettin, Davide; Lachniet, Matthew; Vieten, Rolf; Pausata, Francesco S. R.; Ljungqvist, Fredrik Charpentier; Cheng, Hai; Edwards, R. Lawrence; Miller, Thomas; Rubinetti, Sara; Rubino, Angelo; Taricco, Carla (Nature Communications, 2020)
Abstract Many Holocene hydroclimate records show rainfall changes that vary with local orbital insolation. However, some tropical regions display rainfall evolution that differs from gradual precessional pacing, suggesting that direct rainfall forcing effects were predominantly driven by sea-surface temperature thresholds or inter-ocean temperature gradients. Here we present a 12,000 yr continuous U/Th-dated precipitation record from a Guatemalan speleothem showing that Central American rainfall increased within a 2000 yr period from a persistently dry state to an active convective regime at 9000 yr BP and has remained strong thereafter. Our data suggest that the Holocene evolution of Central American rainfall was driven by exceeding a temperature threshold in the nearby tropical oceans. The sensitivity of this region to slow changes in radiative forcing is thus strongly mediated by internal dynamics acting on much faster time scales.

The Greening of the Sahara: Past Changes and Future Implications - Pausata, Francesco S.R.; Gaetani, Marco; Messori, Gabriele; Berg, Alexis; Maia De Souza, Danielle; Sage, Rowan F.; deMenocal, Peter B. (One Earth, 2020)

The Effect of Strong Volcanic Eruptions on ENSO - McGregor, Shayne; Khodri, Myriam; Maher, Nicola; Ohba, Masamichi; Pausata, Francesco S. R.; Stevenson, Samantha (Geophysical Monograph Series, 2020)

ITCZ shift and extratropical teleconnections drive ENSO response to volcanic eruptions - Pausata, Francesco S. R.; Zanchettin, Davide; Karamperidou, Christina; Caballero, Rodrigo; Battisti, David S. (Science Advances, 2020)
Volcanic eruptions trigger ENSO response through shifts in the ITCZ and extratropical-to-tropical teleconnections. , The mechanisms through which volcanic eruptions affect the El Niño–Southern Oscillation (ENSO) state are still controversial. Previous studies have invoked direct radiative forcing, an ocean dynamical thermostat (ODT) mechanism, and shifts of the Intertropical Convergence Zone (ITCZ), among others, to explain the ENSO response to tropical eruptions. Here, these mechanisms are tested using ensemble simulations with an Earth system model in which volcanic aerosols from a Tambora-like eruption are confined either in the Northern or the Southern Hemisphere. We show that the primary drivers of the ENSO response are the shifts of the ITCZ together with extratropical circulation changes, which affect the tropics; the ODT mechanism does not operate in our simulations. Our study highlights the importance of initial conditions in the ENSO response to tropical volcanic eruptions and provides explanations for the predominance of posteruption El Niño events and for the occasional posteruption La Niña in observations and reconstructions.

End of Green Sahara amplified mid- to late Holocene megadroughts in mainland Southeast Asia - Griffiths, Michael L.; Johnson, Kathleen R.; Pausata, Francesco S. R.; White, Joyce C.; Henderson, Gideon M.; Wood, Christopher T.; Yang, Hongying; Ersek, Vasile; Conrad, Cyler; Sekhon, Natasha (Nature Communications, 2020)
Abstract Between 5 and 4 thousand years ago, crippling megadroughts led to the disruption of ancient civilizations across parts of Africa and Asia, yet the extent of these climate extremes in mainland Southeast Asia (MSEA) has never been defined. This is despite archeological evidence showing a shift in human settlement patterns across the region during this period. We report evidence from stalagmite climate records indicating a major decrease of monsoon rainfall in MSEA during the mid- to late Holocene, coincident with African monsoon failure during the end of the Green Sahara. Through a set of modeling experiments, we show that reduced vegetation and increased dust loads during the Green Sahara termination shifted the Walker circulation eastward and cooled the Indian Ocean, causing a reduction in monsoon rainfall in MSEA. Our results indicate that vegetation-dust climate feedbacks from Sahara drying may have been the catalyst for societal shifts in MSEA via ocean-atmospheric teleconnections.

Robust Longitudinally Variable Responses of the ITCZ to a Myriad of Climate Forcings - Atwood, Alyssa R.; Donohoe, Aaron; Battisti, David S.; Liu, Xiaojuan; Pausata, Francesco S. R. (Geophysical Research Letters, 2020)
Abstract We evaluate the longitudinal variation in meridional shifts of the tropical rainbelt in response to natural and anthropogenic forcings using a large suite of coupled climate model simulations. We find that the energetic framework of the zonal mean Hadley cell is generally not useful for characterizing shifts of the rainbelt at regional scales, regardless of the characteristics of the forcing. Forcings with large hemispheric asymmetry such as extratropical volcanic forcing, meltwater forcing, and the Last Glacial Maximum give rise to robust zonal mean shifts of the rainbelt; however, the direction and magnitude of the shift vary strongly as a function of longitude. Even the Pacific rainband does not shift uniformly under any forcing considered. Forcings with weak hemispheric asymmetry such as CO 2 and mid‐Holocene forcing give rise to zonal mean shifts that are small or absent, but the rainbelt does shift regionally in coherent ways across models that may have important dynamical consequences. , Plain Language Summary A band of heavy precipitation spanning the deep tropics is an essential feature of the climate system that diverse ecosystems and billions of people depend on. It is well known that this rainbelt, when averaged across all longitudes, shifts north and south in response to heating or cooling the atmosphere in one hemisphere more than the other; this framework has been widely applied to study past tropical rainfall changes under differing climate states. However, we show using many different climate model experiments that this framework does not apply to regional shifts in the rainbelt. Changes in the rainbelt vary from place to place, and thus, data documenting north or south shifts in one location cannot be used to infer similar shifts at other longitudes. , Key Points The zonal mean ITCZ framework is generally not useful for characterizing regional shifts of the tropical rainbelt, regardless of the forcing Meridional shifts of the tropical rainbelt vary strongly with longitude under all forcings considered All forcings produce robust regional shifts in the rainbelt that are larger than (and sometime oppose the direction of) the zonal mean shift

Impacts of the North Atlantic Oscillation on Winter Precipitations and Storm Track Variability in Southeast Canada and Northeast US - Chartrand, Julien; Pausata, Francesco Salvatore Rocco (Atmospheric teleconnections incl. stratosphere–troposphere coupling, 2020)
Abstract. The North Atlantic Oscillation (NAO) affects atmospheric variability from eastern North America to Europe. Although the link between the NAO and winter precipitations in the eastern North America have been the focus of previous work, only few studies have hitherto provided clear physical explanations on these relationships. In this study we revisit and extend the analysis of the effect of the NAO on winter precipitations over a large domain covering southeast Canada and the northeastern United States. Furthermore, here we use the recent ERA5 reanalysis dataset (1979–2018), which currently has the highest available horizontal resolution for a global reanalysis (0.25°), to track extratropical cyclones to delve into the physical processes behind the relationship between NAO and precipitation, snowfall, snowfall-to-precipitation ratio (S/P), and snow cover depth anomalies in the region. In particular, our results show that positive NAO phases are associated with less snowfall over a wide region covering Nova Scotia, New England and the Mid-Atlantic of the United States relative to negative NAO phases. Henceforth, a significant negative correlation is also seen between S/P and the NAO over this region. This is due to a decrease (increase) in cyclogenesis of coastal storms near the United States east coast during positive (negative) NAO phases, as well as a northward (southward) displacement of the mean storm track over North America.

Atlantic hurricane response to Saharan greening and reduced dust emissions during the mid-Holocene - Dandoy, Samuel; Pausata, Francesco S. R.; Camargo, Suzana J.; Laprise, René; Winger, Katja; Emanuel, Kerry (Climate of the Past, 2021)
Abstract. We use a high-resolution regional climate model to investigate the changes in Atlantic tropical cyclone (TC) activity during the period of the mid-Holocene (MH: 6000 years BP) with a larger amplitude of the seasonal cycle relative to today. This period was characterized by increased boreal summer insolation over the Northern Hemisphere, a vegetated Sahara and reduced airborne dust concentrations. A set of sensitivity experiments was conducted in which solar insolation, vegetation and dust concentrations were changed in turn to disentangle their impacts on TC activity in the Atlantic Ocean. Results show that the greening of the Sahara and reduced dust loadings (MHGS+RD) lead to a larger increase in the number of Atlantic TCs (27 %) relative to the pre-industrial (PI) climate than the orbital forcing alone (MHPMIP; 9 %). The TC seasonality is also highly modified in the MH climate, showing a decrease in TC activity during the beginning of the hurricane season (June to August), with a shift of its maximum towards October and November in the MHGS+RD experiment relative to PI. MH experiments simulate stronger hurricanes compared to PI, similar to future projections. Moreover, they suggest longer-lasting cyclones relative to PI. Our results also show that changes in the African easterly waves are not relevant in altering the frequency and intensity of TCs, but they may shift the location of their genesis. This work highlights the importance of considering vegetation and dust changes over the Sahara region when investigating TC activity under a different climate state.

The remote response of the South Asian Monsoon to reduced dust emissions and Sahara greening during the middle Holocene - Pausata, Francesco S. R.; Messori, Gabriele; Yun, Jayoung; Jalihal, Chetankumar A.; Bollasina, Massimo A.; Marchitto, Thomas M. (Climate of the Past, 2021)
Abstract. Previous studies based on multiple paleoclimate archives suggested a prominent intensification of the South Asian Monsoon (SAM) during the mid-Holocene (MH, ∼6000 years before present). The main forcing that contributed to this intensification is related to changes in the Earth's orbital parameters. Nonetheless, other key factors likely played important roles, including remote changes in vegetation cover and airborne dust emission. In particular, northern Africa also experienced much wetter conditions and a more mesic landscape than today during the MH (the so-called African Humid Period), leading to a large decrease in airborne dust globally. However, most modeling studies investigating the SAM changes during the Holocene overlooked the potential impacts of the vegetation and dust emission changes that took place over northern Africa. Here, we use a set of simulations for the MH climate, in which vegetation over the Sahara and reduced dust concentrations are considered. Our results show that SAM rainfall is strongly affected by Saharan vegetation and dust concentrations, with a large increase in particular over northwestern India and a lengthening of the monsoon season. We propose that this remote influence is mediated by anomalies in Indian Ocean sea surface temperatures and may have shaped the evolution of the SAM during the termination of the African Humid Period.

The archaeology of climate change: The case for cultural diversity - Burke, Ariane; Peros, Matthew C.; Wren, Colin D.; Pausata, Francesco S. R.; Riel-Salvatore, Julien; Moine, Olivier; De Vernal, Anne; Kageyama, Masa; Boisard, Solène (Proceedings of the National Academy of Sciences, 2021)
Anthropogenic climate change is currently driving environmental transformation on a scale and at a pace that exceeds historical records. This represents an undeniably serious challenge to existing social, political, and economic systems. Humans have successfully faced similar challenges in the past, however. The archaeological record and Earth archives offer rare opportunities to observe the complex interaction between environmental and human systems under different climate regimes and at different spatial and temporal scales. The archaeology of climate change offers opportunities to identify the factors that promoted human resilience in the past and apply the knowledge gained to the present, contributing a much-needed, long-term perspective to climate research. One of the strengths of the archaeological record is the cultural diversity it encompasses, which offers alternatives to the solutions proposed from within the Western agro-industrial complex, which might not be viable cross-culturally. While contemporary climate discourse focuses on the importance of biodiversity, we highlight the importance of cultural diversity as a source of resilience.

The sensitivity of the El Niño–Southern Oscillation to volcanic aerosol spatial distribution in the MPI Grand Ensemble - Ward, Benjamin; Pausata, Francesco S. R.; Maher, Nicola (Earth System Dynamics, 2021)
Abstract. Using the Max Planck Institute Grand Ensemble (MPI-GE) with 200 members for the historical simulation (1850–2005), we investigate the impact of the spatial distribution of volcanic aerosols on the El Niño–Southern Oscillation (ENSO) response. In particular, we select three eruptions (El Chichón, Agung and Pinatubo) in which the aerosol is respectively confined to the Northern Hemisphere, the Southern Hemisphere or equally distributed across the Equator. Our results show that relative ENSO anomalies start at the end of the year of the eruption and peak in the following one. We especially found that when the aerosol is located in the Northern Hemisphere or is symmetrically distributed, relative El Niño-like anomalies develop, while aerosol distribution confined to the Southern Hemisphere leads to a relative La Niña-like anomaly. Our results point to the volcanically induced displacement of the Intertropical Convergence Zone (ITCZ) as a key mechanism that drives the ENSO response, while suggesting that the other mechanisms (the ocean dynamical thermostat and the cooling of tropical northern Africa or the Maritime Continent) commonly invoked to explain the post-eruption ENSO response may be less important in our model.

Holocene forcing of East Asian hydroclimate recorded in a subtropical peatland from southeastern China - Huang, Xianyu; Zhang, Hongbin; Griffiths, Michael L.; Zhao, Bingyan; Pausata, Francesco S. R.; Tabor, Clay; Shu, Junwu; Xie, Shucheng (Climate Dynamics, 2023)

A fully calibrated and updated mid-Holocene climate reconstruction for Eastern South America - Gorenstein, Iuri; Prado, Luciana F.; Bianchini, Paula R.; Wainer, Ilana; Griffiths, Michael L.; Pausata, Francesco S.R.; Yokoyama, Elder (Quaternary Science Reviews, 2022)

Constraining Clouds and Convective Parameterizations in a Climate Model Using Paleoclimate Data - Ramos, R. D.; LeGrande, A. N.; Griffiths, M. L.; Elsaesser, G. S.; Litchmore, D. T.; Tierney, J. E.; Pausata, F. S. R.; Nusbaumer, J. (Journal of Advances in Modeling Earth Systems, 2022)
Abstract Cloud and convective parameterizations strongly influence uncertainties in equilibrium climate sensitivity. We provide a proof‐of‐concept study to constrain these parameterizations in a perturbed parameter ensemble of the atmosphere‐only version of the Goddard Institute for Space Studies Model E2.1 simulations by evaluating model biases in the present‐day runs using multiple satellite climatologies and by comparing simulated δ 18 O of precipitation (δ 18 O p ), known to be sensitive to parameterization schemes, with a global database of speleothem δ 18 O records covering the Last Glacial Maximum (LGM), mid‐Holocene (MH) and pre‐industrial (PI) periods. Relative to modern interannual variability, paleoclimate simulations show greater sensitivity to parameter changes, allowing for an evaluation of model uncertainties over a broader range of climate forcing and the identification of parts of the world that are parameter sensitive. Certain simulations reproduced absolute δ 18 O p values across all time periods, along with LGM and MH δ 18 O p anomalies relative to the PI, better than the default parameterization. No single set of parameterizations worked well in all climate states, likely due to the non‐stationarity of cloud feedbacks under varying boundary conditions. Future work that involves varying multiple parameter sets simultaneously with coupled ocean feedbacks will likely provide improved constraints on cloud and convective parameterizations. , Plain Language Summary Equilibrium climate sensitivity (ECS) is a key climate metric that quantifies the rise in global mean surface temperature in response to doubling of atmospheric CO 2 . Changes in hydroclimate, temperature extremes, and other aspects of future climate projections are closely tied to a model's ECS. For decades, ECS range has remained wide despite improvements from using multiple lines of evidence. One persistent source of this spread is related to cloud and convective processes, which occur at scales too small to be explicitly resolved, and thus require parameterizations to be represented in climate models. These parameterizations directly influence water isotopes by modulating simulated clouds and atmospheric circulation, and thus can be used to constrain model processes and identify model biases. In this work, we demonstrated that paleoclimate simulations are more parameter sensitive than the modern, highlighting the potential of past climates in discriminating cloud and convective parameterizations. Using satellite‐ and proxy‐model comparisons, we identified the top performing parameterizations which differ for each time period likely due to varying cloud feedbacks under diverse climatic forcing. Overall, our results provide a framework for fine‐tuning model representations using combined paleoclimate and satellite data, offering a unique opportunity to assess model uncertainties over a broader range of climate variability. , Key Points Paleoclimate relative to modern are more parameter sensitive, allowing for an assessment of uncertainties over a variety of climate forcing Certain simulations reproduced the δ 18 O of precipitation from paleoclimate proxies better than the default parameterization No single set of parameters works well in all climate states likely due to varying boundary conditions influencing cloud feedbacks

Unravelling the roles of orbital forcing and oceanic conditions on the mid-Holocene boreal summer monsoons - Mudra, Lekshmi; Sabin, T. P.; Krishnan, R.; Pausata, Francesco S. R.; Marti, Olivier; Braconnot, Pascale (Climate Dynamics, 2023)

Sensitivity of northwest Australian tropical cyclone activity to ITCZ migration since 500 CE - Denniston, Rhawn F.; Ummenhofer, Caroline C.; Emanuel, Kerry; Ingrosso, Roberto; Pausata, Francesco S. R.; Wanamaker, Alan D.; Lachniet, Matthew S.; Carr, Kenneth T.; Asmerom, Yemane; Polyak, Victor J.; Nott, Jonathan; Zhang, Wei; et al. (Science Advances, 2023)
Tropical cyclones (TCs) regularly form in association with the intertropical convergence zone (ITCZ), and thus, its positioning has implications for global TC activity. While the poleward extent of the ITCZ has varied markedly over past centuries, the sensitivity with which TCs responded remains poorly understood from the proxy record, particularly in the Southern Hemisphere. Here, we present a high-resolution, composite stalagmite record of ITCZ migrations over tropical Australia for the past 1500 years. When integrated with a TC reconstruction from the Australian subtropics, this time series, along with downscaled climate model simulations, provides an unprecedented examination of the dependence of subtropical TC activity on meridional shifts in the ITCZ. TCs tracked the ITCZ at multidecadal to centennial scales, with a more southward position enhancing TC-derived rainfall in the subtropics. TCs may play an increasingly important role in Western Australia’s moisture budgets as subtropical aridity increases due to anthropogenic warming. , Stalagmites and climate models reveal ITCZ shifts drove concurrent changes in Australian tropical cyclone and monsoon rainfall.

Revisiting the Mechanisms of ENSO Response to Tropical Volcanic Eruptions - Pausata, Francesco S. R.; Zhao, Yang; Zanchettin, Davide; Caballero, Rodrigo; Battisti, David S. (Geophysical Research Letters, 2023)
Abstract Stratospheric volcanic aerosol can have major impacts on global climate. Despite a consensus among studies on an El Niño‐like response in the first or second post‐eruption year, the mechanisms that trigger a change in the state of El Niño‐Southern Oscillation (ENSO) following volcanic eruptions are still debated. Here, we shed light on the processes that govern the ENSO response to tropical volcanic eruptions through a series of sensitivity experiments with an Earth System Model where a uniform stratospheric volcanic aerosol loading is imposed over different parts of the tropics. Three tropical mechanisms are tested: the “ocean dynamical thermostat” (ODT); the cooling of the Maritime Continent; and the cooling of tropical northern Africa (NAFR). We find that the NAFR mechanism plays the largest role, while the ODT mechanism is absent in our simulations as La Niña‐like rather than El‐Niño‐like conditions develop following a uniform radiative forcing over the equatorial Pacific. , Plain Language Summary Volcanic eruptions emit large quantity of sulfate aerosol up to the stratosphere. Such aerosol can alter global climate by interacting with solar radiation and in turn modifying atmospheric and ocean circulation. In particular, volcanic aerosol can alter the state of the El Niño‐Southern Oscillation (ENSO), the major mode of tropical climate variability. However, the mechanisms that trigger a change in the ENSO state following volcanic eruptions are still debated. In this study, we use an Earth System Model to revisit the main mechanisms that have been proposed to alter ENSO, causing positive temperature anomalies over the equatorial Pacific (EqPAC) Ocean. We tested three mechanisms: the “ocean dynamical thermostat” (ODT); the cooling of the Maritime Continent; and the cooling of tropical northern Africa (NAFR). Our experiments show that the NAFR mechanism plays the largest role, while the ODT mechanism is absent in our simulations as cold rather than warm develop over the EqPAC Ocean following the applied volcanic forcing. , Key Points Radiative cooling by volcanic aerosol over the tropical northern Africa triggers El Niño‐like conditions via atmospheric circulation changes The “ocean thermostat mechanism” is absent in our simulations when a uniform aerosol forcing is applied over the equatorial Pacific (EqPAC) The Maritime Continent cooling mechanism is not at play when the aerosol forcing extends over the entire EqPAC

Elevation-dependent intensification of fire danger in the western United States - Alizadeh, Mohammad Reza; Abatzoglou, John T.; Adamowski, Jan; Modaresi Rad, Arash; AghaKouchak, Amir; Pausata, Francesco S. R.; Sadegh, Mojtaba (Nature Communications, 2023)
Abstract Studies have identified elevation-dependent warming trends, but investigations of such trends in fire danger are absent in the literature. Here, we demonstrate that while there have been widespread increases in fire danger across the mountainous western US from 1979 to 2020, trends were most acute at high-elevation regions above 3000 m. The greatest increase in the number of days conducive to large fires occurred at 2500–3000 m, adding 63 critical fire danger days between 1979 and 2020. This includes 22 critical fire danger days occurring outside the warm season (May–September). Furthermore, our findings indicate increased elevational synchronization of fire danger in western US mountains, which can facilitate increased geographic opportunities for ignitions and fire spread that further complicate fire management operations. We hypothesize that several physical mechanisms underpinned the observed trends, including elevationally disparate impacts of earlier snowmelt, intensified land-atmosphere feedbacks, irrigation, and aerosols, in addition to widespread warming/drying.

On the Remote Impacts of Mid‐Holocene Saharan Vegetation on South American Hydroclimate: A Modeling Intercomparison - Tiwari, S.; Ramos, R. D.; Pausata, F. S. R.; LeGrande, A. N.; Griffiths, M. L.; Beltrami, H.; Wainer, I.; De Vernal, A.; Litchmore, D. T.; Chandan, D.; Peltier, W. R.; Tabor, C. R. (Geophysical Research Letters, 2023)
Abstract Proxy reconstructions from the mid‐Holocene (MH: 6,000 years ago) indicate an intensification of the West African Monsoon and a weakening of the South American Monsoon, primarily resulting from orbitally‐driven insolation changes. However, model studies that account for MH orbital configurations and greenhouse gas concentrations can only partially reproduce these changes. Most model studies do not account for the remarkable vegetation changes that occurred during the MH, in particular over the Sahara, precluding realistic simulations of the period. Here, we study precipitation changes over northern Africa and South America using four fully coupled global climate models by accounting for the Saharan greening. Incorporating the Green Sahara amplifies orbitally‐driven changes over both regions, and leads to an improvement in proxy‐model agreement. Our work highlights the local and remote impacts of vegetation and the importance of considering vegetation changes in the Sahara when studying and modeling global climate. , Plain Language Summary Paleoclimate modeling offers a way to test the ability of climate models to detect climate change outside the envelope of historical climatic variability. The mid‐Holocene (MH: 6,000 years ago) is a key interval for paleoclimate studies, as the Northern Hemisphere received greater summer‐time insolation and experienced stronger monsoons than today. Due to a stronger MH West African Monsoon, the Saharan region received enough rainfall to be able to host vegetation. The vegetation changes in the Sahara affected not only the local climate but also far‐afield locations through teleconnections in the global climate system. In this study, we simulate the MH climate using four climate models, each with two types of simulations—with and without the Green Sahara. We show that simulations with the Green Sahara capture greater drying over the South American continent than the simulations which only account for changes in orbital forcing and greenhouse gas concentrations. The simulations with the Green Sahara are more in line with proxy reconstructions, lending further support to incorporating vegetation changes as a necessary boundary condition to simulate the MH climate realistically. , Key Points We simulate the mid‐Holocene with and without the Green Sahara using four fully coupled global climate models The mid‐Holocene simulation with the Green Sahara shows intensification of orbitally‐driven changes in precipitation over northern Africa and South America Incorporation of the Green Sahara leads to greater proxy‐model agreement over both northern Africa and South America

Effect of urban heat island mitigation strategies on precipitation and temperature in Montreal, Canada: Case studies - Lauer, Audrey; Pausata, Francesco S. R.; Leroyer, Sylvie; Argueso, Daniel (PLOS Climate, 2023)
High-resolution numerical weather prediction experiments using the Global Environmental Multiscale (GEM) model at a 250-m horizontal resolution are used to investigate the effect of the urban land-use on 2-m surface air temperature, thermal comfort, and rainfall over the Montreal (Canada) area. We focus on two different events of high temperatures lasting 2–3 days followed by intense rainfall: one is a large-scale synoptic system that crosses Montreal at night and the other is an afternoon squall line. Our model shows an overall good performance in adequately capturing the surface air temperature, dew-point temperature and rainfall during the events, although the precipitation pattern seems to be slightly blocked upwind of the city. Sensitivity experiments with different land use scenarios were conducted. Replacing all urban surfaces by low vegetation showed an increase of human comfort, lowering the heat index during the night between 2° and 6°C. Increasing the albedo of urban surfaces led to an improvement of comfort of up to 1°C during daytime, whereas adding street-level low vegetation had an improvement of comfort throughout the day of up to 0.5°C in the downtown area. With respect to precipitation, significant differences are only seen for the squall line event, for which removing the city modifies the precipitation pattern. For the large-scale synoptic system, the presence of the city does not seem to impact precipitation. These findings offer insight on the effects of urban morphology on the near-surface atmospheric conditions.

Deciphering local and regional hydroclimate resolves contradicting evidence on the Asian monsoon evolution - Wolf, Annabel; Ersek, Vasile; Braun, Tobias; French, Amanda D.; McGee, David; Bernasconi, Stefano M.; Skiba, Vanessa; Griffiths, Michael L.; Johnson, Kathleen R.; Fohlmeister, Jens; Breitenbach, Sebastian F. M.; Pausata, Francesco S. R.; et al. (Nature Communications, 2023)
Abstract The winter and summer monsoons in Southeast Asia are important but highly variable sources of rainfall. Current understanding of the winter monsoon is limited by conflicting proxy observations, resulting from the decoupling of regional atmospheric circulation patterns and local rainfall dynamics. These signals are difficult to decipher in paleoclimate reconstructions. Here, we present a winter monsoon speleothem record from Southeast Asia covering the Holocene and find that winter and summer rainfall changed synchronously, forced by changes in the Pacific and Indian Oceans. In contrast, regional atmospheric circulation shows an inverse relation between winter and summer controlled by seasonal insolation over the Northern Hemisphere. We show that disentangling the local and regional signal in paleoclimate reconstructions is crucial in understanding and projecting winter and summer monsoon variability in Southeast Asia.

Changes in climate extremes in Zambia during green and dry Sahara periods and their potential impacts on hominid dispersal - Pausata, Francesco S.R.; Alain, Dominic; Ingrosso, Roberto; Winger, Katja; Drapeau, Michelle S.M.; Burke, Ariane (Quaternary Science Reviews, 2023)

A 50-year cycle of sea surface temperature regulates decadal precipitation in the tropical and South Atlantic region - Gorenstein, Iuri; Wainer, Ilana; Pausata, Francesco S. R.; Prado, Luciana F.; Khodri, Myriam; Dias, Pedro L. Silva (Communications Earth & Environment, 2023)
Abstract Northeast Brazil and Western Africa are two regions geographically separated by the Atlantic Ocean, both home to vulnerable populations living in semi-arid areas. Atlantic Ocean modes of variability and their interactions with the atmosphere are the main drivers of decadal precipitation in these Atlantic Ocean coastal areas. How these low-frequency modes of variability evolve and interact with each other is key to understanding and predicting decadal precipitation. Here we use the Self-Organizing Maps neural network with different variables to unravel causality between the Atlantic modes of variability and their interactions with the atmosphere. Our study finds an 82% (p<0.05) anti-correlation between decadal rainfall in Northeast Brazil and Western Africa from 1979 to 2005. We also find three multi-decadal cycles: 1870-1920, 1920-1970, and 1970-2019 (satellite era), pointing to a 50-year periodicity governing the sea surface temperature anomalies of Tropical and South Atlantic. Our results demonstrate how Northeast Brazil and Western Africa rainfall anti-correlation was formed in the satellite era and how it might be part of a 50-year cycle from the Tropical and South Atlantic decadal variability.

Tipping points in ocean and atmosphere circulations - Loriani, Sina; Aksenov, Yevgeny; Armstrong McKay, David; Bala, Govindasamy; Born, Andreas; Chiessi, Cristiano M.; Dijkstra, Henk; Donges, Jonathan F.; Drijfhout, Sybren; England, Matthew H.; Fedorov, Alexey V.; Jackson, Laura; et al. (Climate change/Human/Earth system interactions/Earth system and climate modeling, 2023)
Abstract. In this review, we assess scientific evidence for tipping points in ocean and atmosphere circulations. The warming of oceans, modified wind patterns and increasing freshwater influx from melting ice hold the potential to disrupt established circulation patterns. The literature provides evidence for oceanic tipping points in the Atlantic Meridional Overturning Circulation (AMOC), the North Atlantic Subpolar Gyre (SPG), and the Antarctic Overturning Circulation, which may collapse under warmer and ‘fresher’ (i.e. less salty) conditions. A slowdown or collapse of these oceanic circulations would have far-reaching consequences for the rest of the climate system and could lead to strong impacts on human societies and the biosphere. Among the atmospheric circulation systems considered, we classify the West African monsoon as a tipping system. Its abrupt changes in the past have led to vastly different vegetation states of the Sahara (e.g. “green Sahara” states). Evidence about tipping of the monsoon systems over South America and Asia is limited however, there are multiple potential sources of destabilisation, including large-scale deforestation, air pollution, and shifts in other circulation patterns (in particular the AMOC). Although theoretically possible, there is currently little indication for tipping points in tropical clouds or mid-latitude atmospheric circulations. Similarly, tipping towards a more extreme or persistent state of the El Niño-Southern Oscillation (ENSO) is currently not fully supported by models and observations. While the tipping thresholds for many of these systems are uncertain, tipping could have severe socio-environmental consequences. Stabilising Earth’s climate (along with minimising other environmental pressures, like aerosol pollution and ecosystem degradation) is critical for reducing the likelihood of reaching tipping points in the ocean-atmosphere system.

Contrasting consequences of the Great Green Wall: Easing aridity while increasing heat extremes - Ingrosso, Roberto; Pausata, Francesco S.R. (One Earth, 2024)

On the length and intensity of the West African summer monsoon during the last interglacial African humid period - Shi, Xiaoxu; Werner, Martin; Pausata, Francesco S.R.; Yang, Hu; Liu, Jiping; D'Agostino, Roberta; Ingrosso, Roberto; Yang, Chaoyuan; Gao, Qinggang; Lohmann, Gerrit (Quaternary Science Reviews, 2024)

Evaluating the role of city representation in modelling the urban precipitation effect of Kuala Lumpur - Ghielmini, Chiara; Pausata, Francesco S.R.; Argüeso, Daniel; Demuzere, Matthias; Vhuiyan, Razib (Urban Climate, 2024)

Causes of Past African Temperature Change in PMIP Simulations of the Mid‐Holocene - Marshall, Charlie; Morrill, Carrie; Dee, Sylvia; Pausata, Francesco S. R.; Russell, James (Paleoceanography and Paleoclimatology, 2024)
Abstract Current‐generation climate models project that Africa will warm by up to 5°C in the coming century, severely stressing African populations. Past and ongoing work indicates, however, that the models used to create these projections do not match proxy records of past temperature in Africa during the mid‐Holocene (MH), raising concerns that their future projections may house large uncertainties. Rather than reproducing proxy‐based reconstructions of MH warming relative to the Pre‐Industrial (PI), models instead simulate MH temperatures very similar to or slightly colder than the PI. This data‐model mismatch could be due to a variety of factors, including biases in model surface energy budgets or inaccurate representation of the feedbacks between temperature and hydrologic change during the “Green Sahara.” We focus on the differences among model simulations in the Paleoclimate Modeling Intercomparison Project Phases 3 and 4 (PMIP3 and PMIP4), examining surface temperature and energy budgets to investigate controls on temperature and the potential model sources of this paleoclimate data‐model mismatch. Our results suggest that colder conditions simulated by PMIP3 and PMIP4 models during the MH are in large part due to the joint impacts of feedback uncertainties in response to increased precipitation, a strengthened West African Monsoon (WAM) in the Sahel, and the Green Sahara. We extend these insights into suggestions for model physics and boundary condition changes, and discuss implications for the accuracy of future climate model projections over Africa. , Key Points We evaluate the simulation of African air temperatures in Paleoclimate Modeling Intercomparison Project Phases 3 and 4 simulations of the mid‐Holocene Energy balance decomposition analyses indicate the hydrologic cycle plays a key role in causing mid‐Holocene cooling in model simulations “Green Sahara” experiments show that dust and vegetation affect simulated temperatures, revealing pathways for refining model simulations

An assessment of climate change impacts on oases in northern Africa - Leal Filho, Walter; Stojanov, Robert; Matsoukas, Christos; Ingrosso, Roberto; Franke, James A.; Pausata, Francesco S.R.; Grassi, Tommaso; Landa, Jaromír; Harrouni, Cherif (Ecological Indicators, 2024)

Mid-Holocene climate at mid-latitudes: assessing the impact of Saharan greening - Gaetani, Marco; Messori, Gabriele; Pausata, Francesco S. R.; Tiwari, Shivangi; Alvarez Castro, M. Carmen; Zhang, Qiong (Climate of the Past, 2024)
Abstract. During the first half of the Holocene (11 000 to 5000 years ago), the Northern Hemisphere experienced a strengthening of the monsoonal regime, with climate reconstructions robustly suggesting a greening of the Sahara region. Palaeoclimate archives also show that this so-called African humid period (AHP) was accompanied by changes in climate conditions at middle to high latitudes. However, inconsistencies still exist in reconstructions of the mid-Holocene (MH) climate at mid-latitudes, and model simulations provide limited support in reducing these discrepancies. In this paper, a set of simulations performed using a climate model are used to investigate the hitherto unexplored impact of Saharan greening on mid-latitude atmospheric circulation during the MH. Numerical simulations show Saharan greening has a year-round impact on the main circulation features in the Northern Hemisphere, especially during boreal summer (when the African monsoon develops). Key findings include a westward shift in the global Walker Circulation, leading to modifications in the North Atlantic jet stream in summer and the North Pacific jet stream in winter. Furthermore, Saharan greening modifies atmospheric synoptic circulation over the North Atlantic, enhancing the effect of orbital forcing on the transition of the North Atlantic Oscillation phase from predominantly positive to negative in winter and summer. Although the prescription of vegetation in the Sahara does not improve the proxy–model agreement, this study provides the first constraint on the influence of Saharan greening on northern mid-latitudes, opening new opportunities for understanding MH climate anomalies in regions such as North America and Eurasia.

Meteorological observations and measurements collected during the Storms and Precipitation Across the continental Divide Experiment (SPADE), April – June 2019 - Thériault, Julie M.; Déry, Stephen J.; Pomeroy, John; Stewart, Ronald E.; Smith, Hilary; Thompson, Hadleigh; Bertoncini, André; Desroches-Lapointe, Aurélie; Hébert-Pinard, Charlie; Mitchell, Selina; Morris, Jeremy; Almonte, Juris; et al. (Federated Research Data Repository / dépôt fédéré de données de recherche, 2020)
Global Water Future’s Storms and Precipitation Across the continental Divide Experiment (SPADE) was initiated to enhance our knowledge of the contribution of different moisture flows on precipitation across the Canadian Rockies. SPADE installed instrumentation on both sides of the continental divide to gather automated and manual observations during an intensive field campaign from 24 April to 26 June 2019. Various meteorological instruments were deployed including a two Doppler LiDARs, three vertically pointing micro rain radars and three optical disdrometers, alongside human observers during precipitation events. Detailed meteorological data such as air temperature, relative humidity, 3D wind fields, vertical profiles of radar reflectivity and Doppler velocity, precipitation and its type, and snow microphotography images were collected. This dataset will serve as a baseline for future work on atmospheric conditions over major orographic features by comparing the varying conditions on either side of a large topographic feature.
Keywords: Canadian Rockies; Hydrometeorology; Meteorology and weather; Météorologie et temps; atmospheric sciences; continental divide; meteorology; precipitation

Annual frequencies of freezing rain diagnosed from the fifth-generation Canadian Regional Climate Model (CRCM5) for the past and future climates - McCray, Christopher D.; Paquin, Dominique; Thériault, Julie M.; Bresson, Émilie (Federated Research Data Repository / dépôt fédéré de données de recherche, 2022)
This dataset contains output of yearly frequencies (hours) of freezing rain identified using four precipitation-type algorithms applied to output of the fifth-generation Canadian Regional Climate Model (CRCM5) run at Ouranos. Algorithms are applied to three-hourly output of eight simulations of four dynamically-downscaled global climate models (GCMs) on a 0.22° horizontal grid over the North American domain. Simulations for 1980-2005 are forced with observed greenhouse gas concentrations, with data for 2006-2099 using the RCP 8.5 greenhouse gas concentration trajectory. Each occurrence of freezing rain identified in the model output is multiplied by 3 for comparison with hourly observations. These data are associated with the article "A multi-algorithm analysis of projected changes to freezing rain over North America in an ensemble of regional climate model simulations" by McCray et al., submitted in 2022 to the Journal of Geophysical Research: Atmospheres.
Keywords: CRCM5; Climate change; Climate model; Climate modelling; Dynamical Downscaling; Freezing rain; Ice storms; Modélisation climatique; Precipitation type

WINTRE-MIX Field Collected Sounding Data. Version 4.0 - Winters, A.; Minder, J. R.; Han, B.; Thériault, J.; Lachapelle, M.; Gyakum, J.; Wray, J.; Baiman, R. (UCAR/NCAR - Earth Observing Laboratory, 2022)
Sounding data collected during the WINTRE-MIX project field phase are included in this dataset. This dataset has soundings from the University of Colorado (CU) DOWs, McGill University at Gault, St Jean sur Richelieu, University at Albany (UA) DOWs, Université du Québec à Montréal (UQAM), and UA Essex sites. data file names are of the form "upperair.sounding.YYYYMMDDHHMM.siteName.[txt or csv]" where the YYYMMDDHHMM indicates the date and time of the sounding and the siteName indicates the site source and location. See the documentation for more information on this dataset.

WINTRE-MIX: CFI Climate Sentinels Pyranometer and Radiation Data. Version 1.0 - Low, Y.; Lachapelle, M.; Gyakum, J.; Bigras, È.; Meunier, V.; Thériault, J.; Thompson, H.; Girouard, M.; Fraser, D.; Wray, J. (UCAR/NCAR - Earth Observing Laboratory, 2022)
The Sentinel Radiation MetData provided in situ measurements of radiation fluxes for the Winter Precip Type Research Multi-scale Experiment (WINTRE-MIX) are included in this dataset. Pyranometer and radiation data are provided in netCDF format. Data were collected from the following 4 sites: Gault, Arboretum, UQAM-PK and Trois-Rivières.

WINTRE-MIX: CFI Climate Sentinels Pressure, Wind, Temperature, Relative Humidity, and Precipitation Data. Version 1.0 - Low, Y.; Lachapelle, M.; Kinnard, C.; Gyakum, J.; Bigras, È.; Meunier, V.; Thériault, J.; Thompson, H.; Girouard, M.; Fraser, D.; Wray, J. (UCAR/NCAR - Earth Observing Laboratory, 2022)
The Sentinel Non-Radiation MetData provided in situ measurements of meteorological variables (such as 2-meter temperature, relative humidity, wind speed and direction, and precipitation) collected for the the Winter Precip Type Research Multi-scale Experiment (WINTRE-MIX) are included in this dataset. Data are provided in netCDF format. Data were collected from the following 4 sites: Gault, Arboretum, UQAM-PK and Trois-Rivières.

WINTRE-MIX: CFI Climate Sentinels Hotplate Precipitation Gauge data. Version 1.0 - Girouard, M.; Lachapelle, M.; Thériault, J.; Gyakum, J.; Bigras, È.; Meunier, V.; Thompson, H.; Fraser, D.; Wray, J.; Low, Y. (UCAR/NCAR - Earth Observing Laboratory, 2022)
This dataset includes hotplate precipitation gauge data from 4 different sites sitting in the St. Lawrence River Valley. The hotplate data were obtained by the K63 Hotplate Total Precipitation Gauge. The instruments belonged to Université du Québec à Montréal (UQAM) and McGill University. UQAM has one hotplate permanently installed on the rooftop of the President-Kennedy building, in downtown Montreal. Another hotplate was temporarily deployed by the UQAM team in the instrument yard of UQTR as part of the WINTRE-MIX field campaign. McGill’s instruments are permanently installed in the instrument yards of Gault and Arboretum.

WINTRE-MIX: CFI Climate Sentinels Snow Depth Data. Version 1.0 - Girouard, M.; Lachapelle, M.; Thompson, H.; Bigras, È.; Meunier, V.; Fraser, D.; Low, Y.; Wray, J.; Thériault, J.; Gyakum, J. (UCAR/NCAR - Earth Observing Laboratory, 2022)
This dataset includes snow depth and snow water equivalent data from 4 sites in the St. Lawrence River Valley collected for the WINTRE-MIX field project. The snow depth data were obtained by the SDMS40: Multipoint Scanning Snowfall Sensor and the SR50A Snow-Depth Sensor. The CS725 Snow-Water Equivalent Sensor measured the snow water equivalent data. This dataset includes measurements done at 4 different sites: UQAM-PK (UQAM), Trois-Rivières, Gault and Arboretum.

WINTRE-MIX: CFI Climate Sentinels Icing Detector Data. Version 1.0 - Fraser, D.; Bigras, È.; Gyakum, J.; Lachapelle, M.; Meunier, V.; Thériault, J.; Thompson, H.; Girouard, M.; Low, Y.; Wray, J. (UCAR/NCAR - Earth Observing Laboratory, 2022)
This dataset contains ice thickness data collected by ice detectors installed at various climate sentinels within the Saint Lawrence River Valley for the WINTRE-MIX field project. The names of four stations for which ice accretion data are available in ‘CFI_Climate_Sentinels_Icing_Detector_Data.nc’ are given in Table 1 of the readme documentation, along with their corresponding four-letter identifiers.

WINTRE-MIX: CFI Climate Sentinels Gault Parsivel Disdrometer Data. Version 1.0 - Fraser, D.; Bigras, È.; Gyakum, J.; Lachapelle, M.; Meunier, V.; Thériault, J.; Thompson, H.; Girouard, M.; Low, Y.; Wray, J. (UCAR/NCAR - Earth Observing Laboratory, 2022)
This dataset contains raw data collected from an OTT Parsivel laser disdrometer installed at a climate sentinel (Gault) in the Saint Lawrence River Valley The data is available from 1 Nov 2021 to 31 March 2022 (inclusive) to support the Winter Precipitation Type Research Multi-Scale Experiment (WINTRE-MIX). The instrument provides histograms of hydrometeor size and fallspeed. The Gault site is located behind Mont-Saint-Hilaire, about an hour’s drive east of Montreal. Other sites also collected Parsivel data during WINTRE-MIX.

WINTRE-MIX: CFI Climate Sentinels Arboretum Parsivel Disdrometer Data. Version 1.0 - Fraser, D.; Bigras, È.; Gyakum, J.; Lachapelle, M.; Meunier, V.; Thériault, J.; Thompson, H.; Girouard, M.; Low, Y.; Wray, J. (UCAR/NCAR - Earth Observing Laboratory, 2022)
This dataset contains raw data collected from an OTT Parsivel laser disdrometer installed at a climate sentinel (Arboretum) in the Saint Lawrence River Valley. The data is available from 1 Nov 2021 to 31 March 2022 (inclusive) to support the Winter Precipitation Type Research Multi-Scale Experiment (WINTRE-MIX). The instrument provides histograms of hydrometeor size and fallspeed. The Arboretum site is located on the southwestern tip of Montreal Island near the confluence of the Ottawa River and the St. Lawrence River. Several other sites also collected Parsivel data during WINTRE-MIX.

WINTRE-MIX: CFI Climate Sentinels Trois-Rivières MRR-Pro data. Version 1.0 - Lachapelle, M.; Girouard, M.; Thompson, H.; Thériault, J. (UCAR/NCAR - Earth Observing Laboratory, 2022)
This dataset contains data from a METEK vertically profiling K-band Micro Rain Radar Pro (MRR-Pro) that was temporarily installed at the Université du Québec à Trois-Rivières (UQTR) campus during February and March 2022 to support the Winter Precipitation Type Research Multi-Scale Experiment (WINTRE-MIX). The instrument provides vertical profiles of reflectivity, Doppler velocity, and spectrum width. The site sits in the St. Lawrence River Valley. Several other sites also collected MRR data during WINTRE-MIX.

WINTRE-MIX: CFI Climate Sentinels UQAM-PK MRR-2 Processed Data. Version 1.0 - Lachapelle, M.; Girouard, M.; Thompson, H.; Thériault, J. (UCAR/NCAR - Earth Observing Laboratory, 2022)
This dataset contains processed data from a METEK vertically profiling K-band Micro Rain Radar (MRR-2) permanently installed on the rooftop of UQAM President-Kennedy building in Montréal downtown, Québec. The instrument provides vertical profiles of reflectivity, Doppler velocity, and spectrum width. The site sits in the St. Lawrence River Valley. Several other sites also collected MRR data during WINTRE-MIX.

WINTRE-MIX: CFI Climate Sentinels UQAM-PK MRR-2 Raw Data. Version 1.0 - Lachapelle, M.; Girouard, M.; Thompson, H.; Thériault, J. (UCAR/NCAR - Earth Observing Laboratory, 2022)
This dataset contains raw data from a METEK vertically profiling K-band Micro Rain Radar (MRR-2) permanently installed on the rooftop of UQAM President-Kennedy building in Montréal downtown, Québec. The instrument provides vertical profiles of reflectivity, Doppler velocity, and spectrum width. The site sits in the St. Lawrence River Valley. Several other sites also collected MRR data during WINTRE-MIX.

WINTRE-MIX: CFI Climate Sentinels UQAM-PK Parsivel Disdrometer Data. Version 1.0 - Lachapelle, M.; Girouard, M.; Thompson, H.; Thériault, J. (UCAR/NCAR - Earth Observing Laboratory, 2022)
This dataset contains raw data from an OTT Parsivel laser disdrometer permanently installed on the rooftop of UQAM President-Kennedy building in Montréal downtown, Québec. The instrument provides histograms of hydrometeor size and fallspeed. The site sits in the St. Lawrence River Valley. Several other sites also collected Parsivel data during WINTRE-MIX 2022.

WINTRE-MIX: Trois-Rivieres Parsivel Disdrometer Data. Version 1.0 - Lachapelle, M.; Girouard, M.; Thompson, H.; Thériault, J. (UCAR/NCAR - Earth Observing Laboratory, 2022)
This dataset contains raw data from an OTT Parsivel laser disdrometer that was temporarily installed at the Université du Québec à Trois-Rivières (UQTR) campus from December 2021 to April 2022 to support the Winter Precipitation Type Research Multi-Scale Experiment (WINTRE-MIX). The instrument provides histograms of hydrometeor size and fallspeed. The site sits in the St. Lawrence River Valley. Several other sites also collected Parsivel data during WINTRE-MIX.

WINTRE-MIX: CFI Climate Sentinels Gault MRR-2 Raw Data. Version 1.0 - Lachapelle, M.; Fraser, D.; Bigras, È.; Gyakum, J.; Meunier, V.; Thériault, J.; Thompson, H.; Girouard, M.; Low, Y.; Wray, J. (UCAR/NCAR - Earth Observing Laboratory, 2022)
This dataset contains raw data from a METEK vertically profiling K-band Micro Rain Radar (MRR-2) installed at the climate sentinel in the Gault Nature Reserve (GAUL), about 30 km east of Montréal, Québec.The data were collected as part of the Winter Precipitation Type Research Multi-scale Experiment (WINTRE-MIX) field project held in February and March of 2022. The instrument provides vertical profiles of reflectivity, Doppler velocity, and spectrum width. The site is located at the southern flank of Mont-Saint-Hilaire, a mountain with an elevation of about 400 m (above mean sea-level). Several other sites also collected MRR data during WINTRE-MIX.

WINTRE-MIX: CFI Climate Sentinels Gault MRR-2 Processed Data. Version 1.0 - Lachapelle, M.; Fraser, D.; Bigras, È.; Gyakum, J.; Meunier, V.; Thériault, J.; Thompson, H.; Girouard, M.; Low, Y.; Wray, J. (UCAR/NCAR - Earth Observing Laboratory, 2022)
This dataset contains post-processed data from a METEK vertically profiling K-band Micro Rain Radar (MRR-2) installed at the climate sentinel in the Gault Nature Reserve (GAUL), about 30 km east of Montréal, Québec. The data were collected as part of the Winter Precipitation Type Research Multi-scale Experiment (WINTRE-MIX) field project held in February and March of 2022. The instrument provides vertical profiles of reflectivity, Doppler velocity, and spectrum width. The site is located at the southern flank of Mont-Saint-Hilaire, a mountain with an elevation of about 400 m (above mean sea-level). Several other sites also collected MRR data during WINTRE-MIX.

WINTRE-MIX: CFI Climate Sentinels Arboretum MRR-2 raw data. Version 1.0 - Lachapelle, M.; Fraser, D.; Bigras, È.; Gyakum, J.; Meunier, V.; Thériault, J.; Thompson, H.; Girouard, M.; Low, Y.; Wray, J. (UCAR/NCAR - Earth Observing Laboratory, 2022)
This dataset contains raw data from a METEK vertically profiling K-band Micro Rain Radar (MRR-2) installed at the climate sentinel in the Arboretum forest reserve (ARBO), about 30 km west of Montréal downtown, Québec, Canada. The data were collected as part of the Winter Precipitation Type Research Multi-scale Experiment (WINTRE-MIX) field project held in February and March of 2022. The instrument used to collect the data in this dataset provides vertical profiles of reflectivity, Doppler velocity, and spectrum width. The site is located near the confluence of the Ottawa River and the St. Lawrence River. Several other sites also collected MRR data during WINTRE-MIX.

WINTRE-MIX: Manual Hydrometeor Photographs Dataset. Version 1.0 - Lachapelle, M.; Han, B.; Minder, J. R.; Winters, A.; Baiman, R.; Thériault, J.; Gyakum, J.; Wray, J. (UCAR/NCAR - Earth Observing Laboratory, 2022)
Manual hydrometeor macro photographs were collected during the Winter Precipitation Type Research Multi-Scale Experiment (WINTRE-MIX) between 01 Feb – 15 March 2022. The macro photographs were collected by manual ground observation teams from the University at Albany (UAlbany), University of Colorado Boulder (CU), Université du Québec à Montréal (UQAM), and McGill University (McGill). Sections in the readme provide information on the camera setup, protocol, and dataset file formats, as well as limitations associated with the data.

Atmospheric and surface observation data collected during the Saint John River Experiment on Cold Season Storms - Thompson, Hadleigh D; Thériault, Julie M; Rickard, Lisa; Déry, Stephen J; Leroux, Nicolas R; Stewart, Ronald E; Vionnet, Vincent; Colli, Matteo; Boisvert, Dominique (Federated Research Data Repository / dépôt fédéré de données de recherche, 2023)
Meteorological data, manual observations, and photographic images of hydrometeors recorded during the Saint John River Experiment on Cold Season Storms. The dataset covers the period December 2020 to April 2021, with an intensive observation period from March 2021 to April 2021.
Keywords: Cold season; Disdrometre; Edmundston; Flux; Hydrology; Hydrometeorology; Meteorology; Meteorology and weather; Micro Rain Radar; Météorologie et temps; New Brunswick; Spring; Winter

Observation data for four ice pellet events - Lachapelle, Mathieu; Thériault, Julie M.; Thompson, Hadleigh D. (Borealis, 2023)
This dataset contains the observation data used to prepare the thesis of Mathieu Lachapelle. It contains radar data, laser-optical disdrometer data, standard meteorological data, manual observations, and macrophotography recorded during four ice pellet events that occurred in 2019 and 2020. The ice pellet episodes occurred in the Montreal region and most observational data were collected at UQAM-PK weather station, on the rooftop of President Kennedy building, in Downtown Montreal. More documentation is available in the READMEs provided with the dataset. Cette base de données contient les données d'observation utilisées pour rédiger la thèse de Mathieu Lachapelle. Elle inclut des données radar, des données d'un disdromètre optique, des mesures météorologiques de base, des observations manuelles et des macro photographies collectées pendant quatre épisodes de grésil qui se sont produit en 2019 et en 2020. Les épisodes de grésil ont eu lieu dans la région de Montréal et la plupart des données d'observation ont été collectées à la station météo UQAM-PK, installée sur le toit du bâtiment Président-Kennedy au centre-ville de Montréal. Davantage de documentation est accessible via les fichiers READMEs inclus dans la base de données.

Mountain Weather Research and Forecasting: Recent Progress and Current Challenges - Chow, Fotini K.; De Wekker, Stephan F.J.; Snyder, Bradley J. (Springer Atmospheric Sciences, 2013)

On the simulation of winter precipitation types - Thériault, J. M.; Stewart, R. E.; Milbrandt, J. A; Yau, M. K. (Journal of Geophysical Research: Atmospheres, 2006)
Winter storms produce major problems for society, and the key responsible factor is often the varying types of precipitation. The objective of this study is to better understand the formation of different types of winter precipitation (freezing rain, ice pellets, snow, slush, wet snow and refrozen wet snow) within the varying and interacting environmental conditions in many winter storms. To address this issue, a one‐dimensional cloud model utilizing a double‐moment bulk microphysics scheme has been developed. Temperature and moisture profiles favorable for the formation of different winter precipitation types were varied in a systematic manner in an environment where snow is falling continuously through a temperature inversion. The ensuing precipitation evolved as a result of the variations in atmospheric temperature and moisture arising from phase changes such as melting and freezing. This study underlines the often complex manner through which different precipitation types form. It also demonstrates that the formation of semimelted particles can have a profound effect on the evolution of precipitation types aloft and at the surface. Furthermore, some types of precipitation only form within a narrow range of environmental conditions.

On the effects of vertical air velocity on winter precipitation types - Thériault, J. M.; Stewart, R. E. (Natural Hazards and Earth System Sciences, 2007)
Abstract. The various precipitation types formed within winter storms (such as snow, wet snow and freezing rain) often lead to very hazardous weather conditions. These types of precipitation often occur during the passage of a warm front as a warm air mass ascends over a cold air mass. To address this issue further, we used a one-dimensional kinematic cloud model to simulate this gentle ascent (≤10 cm/s) of warm air. The initial temperature profile has an above 0°C inversion, a lower subfreezing layer, and precipitation falls from above the temperature inversion. The cloud model is coupled to a double-moment microphysics scheme that simulates the production of various types of winter precipitation. The results are compared with those from a previous study carried out in still air. Based on the temporal evolution of surface precipitation, snow reaches the surface significantly faster than in still air whereas other precipitation types including freezing rain and ice pellets have a shorter duration. Overall, even weak background vertical ascent has an important impact on the precipitation reaching the surface, the time of the elimination of the melting layer, and also the evolution of the lower subfreezing layer.

On the Dependence of Winter Precipitation Types on Temperature, Precipitation Rate, and Associated Features - Thériault, Julie M.; Stewart, Ronald E.; Henson, William (Journal of Applied Meteorology and Climatology, 2010)
Abstract The phase of precipitation formed within the atmosphere is highly dependent on the vertical temperature profile through which it falls. In particular, several precipitation types can form in an environment with a melting layer aloft and a refreezing layer below. These precipitation types include freezing rain, ice pellets, wet snow, and slush. To examine the formation of such precipitation, a bulk microphysics scheme was used to compare the characteristics of the hydrometeors produced by the model and observed by a research aircraft flight during the 1998 ice storm near Montreal, Canada. The model reproduced several of the observed key precipitation characteristics. Sensitivity tests on the precipitation types formed during the ice storm were also performed. These tests utilized temperature profiles produced by the North American Regional Reanalysis. The results show that small variations (±0.5°C) in the temperature profiles as well as in the precipitation rate can have major impacts on the types of precipitation formed at the surface. These results impose strong requirements on the accuracy needed by prediction models.

A Parameterization of the Microphysical Processes Forming Many Types of Winter Precipitation - Thériault, Julie M.; Stewart, Ronald E. (Journal of the Atmospheric Sciences, 2010)
Abstract Several types of precipitation, such as freezing rain, ice pellets, and wet snow, are commonly observed during winter storms. The objective of this study is to better understand the formation of these winter precipitation types. To address this issue, detailed melting and refreezing of precipitation was added onto an existing bulk microphysics scheme. These modifications allow the formation of mixed-phase particles and these particles in turn lead to, or affect, the formation of many of the other types of precipitation. The precipitation type characteristics, such as the mass content, liquid fraction, and threshold diameters formed during a storm over St John’s, Newfoundland, Canada, are studied and compared with observations. Many of these features were reproduced by the model. Sensitivity experiments with the model were carried out to examine the dependence of precipitation characteristics in this event on thresholds of particle evolution in the new parameterization.

The 1998 Ice Storm: Local flow fields and linkages to precipitation - Henson, William; Stewart, Ronald; Kochtubajda, Bohdan; Thériault, Julie (Atmospheric Research, 2011)

Environmental conditions favoring ice pellet aggregation - Carmichael, H.E.; Stewart, R.E.; Henson, W.; Thériault, J.M. (Atmospheric Research, 2011)

Impacts of terminal velocity on the trajectory of winter precipitation types - Thériault, Julie M.; Stewart, Ronald E.; Henson, William (Atmospheric Research, 2012)

How Well Are We Measuring Snow: The NOAA/FAA/NCAR Winter Precipitation Test Bed - Rasmussen, Roy; Baker, Bruce; Kochendorfer, John; Meyers, Tilden; Landolt, Scott; Fischer, Alexandre P.; Black, Jenny; Thériault, Julie M.; Kucera, Paul; Gochis, David; Smith, Craig; Nitu, Rodica; et al. (Bulletin of the American Meteorological Society, 2012)

Dependence of Snow Gauge Collection Efficiency on Snowflake Characteristics - Thériault, Julie M.; Rasmussen, Roy; Ikeda, Kyoko; Landolt, Scott (Journal of Applied Meteorology and Climatology, 2012)
Abstract Accurate snowfall measurements are critical for a wide variety of research fields, including snowpack monitoring, climate variability, and hydrological applications. It has been recognized that systematic errors in snowfall measurements are often observed as a result of the gauge geometry and the weather conditions. The goal of this study is to understand better the scatter in the snowfall precipitation rate measured by a gauge. To address this issue, field observations and numerical simulations were carried out. First, a theoretical study using finite-element modeling was used to simulate the flow around the gauge. The snowflake trajectories were investigated using a Lagrangian model, and the derived flow field was used to compute a theoretical collection efficiency for different types of snowflakes. Second, field observations were undertaken to determine how different types, shapes, and sizes of snowflakes are collected inside a Geonor, Inc., precipitation gauge. The results show that the collection efficiency is influenced by the type of snowflakes as well as by their size distribution. Different types of snowflakes, which fall at different terminal velocities, interact differently with the airflow around the gauge. Fast-falling snowflakes are more efficiently collected by the gauge than slow-falling ones. The correction factor used to correct the data for the wind speed is improved by adding a parameter for each type of snowflake. The results show that accurate measure of snow depends on the wind speed as well as the type of snowflake observed during a snowstorm.

A Case Study of Processes Impacting Precipitation Phase and Intensity during the Vancouver 2010 Winter Olympics - Thériault, Julie M.; Rasmussen, Roy; Smith, Trevor; Mo, Ruping; Milbrandt, Jason A.; Brugman, Melinda M.; Joe, Paul; Isaac, George A.; Mailhot, Jocelyn; Denis, Bertrand (Weather and Forecasting, 2012)
Abstract Accurate forecasting of precipitation phase and intensity was critical information for many of the Olympic venue managers during the Vancouver 2010 Olympic and Paralympic Winter Games. Precipitation forecasting was complicated because of the complex terrain and warm coastal weather conditions in the Whistler area of British Columbia, Canada. The goal of this study is to analyze the processes impacting precipitation phase and intensity during a winter weather storm associated with rain and snow over complex terrain. The storm occurred during the second day of the Olympics when the downhill ski event was scheduled. At 0000 UTC 14 February, 2 h after the onset of precipitation, a rapid cooling was observed at the surface instrumentation sites. Precipitation was reported for 8 h, which coincided with the creation of a nearly 0°C isothermal layer, as well as a shift of the valley flow from up valley to down valley. Widespread snow was reported on Whistler Mountain with periods of rain at the mountain base despite the expectation derived from synoptic-scale models (15-km grid spacing) that the strong warm advection would maintain temperatures above freezing. Various model predictions are compared with observations, and the processes influencing the temperature, wind, and precipitation types are discussed. Overall, this case study provided a well-observed scenario of winter storms associated with rain and snow over complex terrain.

Reexamination of the State of the Art of Cloud Modeling Shows Real Improvements - Muhlbauer, Andreas; Grabowski, Wojciech W.; Malinowski, Szymon P.; Ackerman, Thomas P.; Bryan, George H.; Lebo, Zachary J.; Milbrandt, Jason A.; Morrison, Hugh; Ovchinnikov, Mikhail; Tessendorf, Sarah; Thériault, Julie M.; Thompson, Greg (Bulletin of the American Meteorological Society, 2013)

Weather observations on Whistler Mountain during five storms - Thériault, Julie M.; Rasmussen, Kristen L.; Fisico, Teresa; Stewart, Ronald E.; Joe, Paul; Gultepe, Ismail; Clément, Marilys; Isaac, George A. (Pure and Applied Geophysics, 2014)

The Monitoring Network of the Vancouver 2010 Olympics - Joe, Paul; Scott, Bill; Doyle, Chris; Isaac, George; Gultepe, Ismail; Forsyth, Douglas; Cober, Stewart; Campos, Edwin; Heckman, Ivan; Donaldson, Norman; Hudak, David; Rasmussen, Roy; et al. (Pure and Applied Geophysics, 2014)

Roundhouse (RND) Mountain Top Research Site: Measurements and Uncertainties for Winter Alpine Weather Conditions - Gultepe, I.; Isaac, G. A.; Joe, P.; Kucera, P. A.; Theriault, J. M.; Fisico, T. (Pure and Applied Geophysics, 2014)

Modeling the Phase Transition Associated with Melting Snow in a 1D Kinematic Framework: Sensitivity to the Microphysics - Milbrandt, J. A.; Thériault, J.; Mo, R. (Pure and Applied Geophysics, 2014)

Perspectives for Very High-Resolution Climate Simulations with Nested Models: Illustration of Potential in Simulating St. Lawrence River Valley Channelling Winds with the Fifth-Generation Canadian Regional Climate Model - Cholette, Mélissa; Laprise, René; Thériault, Julie (Climate, 2015)
With the refinement of grid meshes in regional climate models permitted by the increase in computing power, the grid telescoping or cascade method, already used in numerical weather prediction, can be applied to achieve very high-resolution climate simulations. The purpose of this study is two-fold: (1) to illustrate the perspectives offered by climate simulations on kilometer-scale grid meshes using the wind characteristics in the St. Lawrence River Valley (SLRV) as the test-bench; and (2) to establish some constraints to be satisfied for the physical realism and the computational affordability of these simulations. The cascade method is illustrated using a suite of five one-way nested, time-slice simulations carried out with the fifth-generation Canadian Regional Climate Model, with grid meshes varying from roughly 81 km, successively to 27, 9, 3 and finally 1 km, over domains centered on the SLRV. The results show the added value afforded by very high-resolution meshes for a realistic simulation of the SLRV winds. Kinetic energy spectra are used to document the spin-up time and the effective resolution of the simulations as a function of their grid meshes. A pragmatic consideration is developed arguing that kilometer-scale simulations could be achieved at a reasonable computational cost with time-slice simulations of high impact climate events. This study lends confidence to the idea that climate simulations and projections at kilometer-scale could soon become operationally feasible, thus offering interesting perspectives for resolving features that are currently out of reach with coarser-mesh models.

On the Characteristics of and Processes Producing Winter Precipitation Types near 0°C - Stewart, Ronald E.; Thériault, Julie M.; Henson, William (Bulletin of the American Meteorological Society, 2015)
Abstract This article examines the types of winter precipitation that occur near 0°C, specifically rain, freezing rain, freezing drizzle, ice pellets, snow pellets, and wet snow. It follows from a call by M. Ralph et al. for more attention to be paid to this precipitation since it represents one of the most serious wintertime quantitative precipitation forecasting (QPF) issues. The formation of the many precipitation types involves ice-phase and/or liquid-phase processes, and thresholds in the degree of melting and/or freezing often dictate the types occurring at the surface. Some types can occur simultaneously so that, for example, ensuing collisions between supercooled raindrops and ice pellets that form ice pellet aggregates can lead to substantial reductions in the occurrence of freezing rain at the surface, and ice crystal multiplication processes can lead to locally produced ice crystals in the subfreezing layer below inversions. Highly variable fall velocities within the background temperature and wind fields of precipitation-type transition regions lead to varying particle trajectories and significant alterations in the distribution of precipitation amount and type at the surface. Physically based predictions that account for at least some of the phase changes and particle interactions are now in operation. Outstanding issues to be addressed include the impacts of accretion on precipitation-type formation, quantification of melting and freezing rates of the highly variable precipitation, the consequences of collisions between the various types, and the onset of ice nucleation and its effects. The precipitation physics perspective of this article furthermore needs to be integrated into a comprehensive understanding involving the surrounding and interacting environment.

Impact of Wind Direction, Wind Speed, and Particle Characteristics on the Collection Efficiency of the Double Fence Intercomparison Reference - Thériault, Julie M.; Rasmussen, Roy; Petro, Eddy; Trépanier, Jean-Yves; Colli, Matteo; Lanza, Luca G. (Journal of Applied Meteorology and Climatology, 2015)
Abstract The accurate measurement of snowfall is important in various fields of study such as climate variability, transportation, and water resources. A major concern is that snowfall measurements are difficult and can result in significant errors. For example, collection efficiency of most gauge–shield configurations generally decreases with increasing wind speed. In addition, much scatter is observed for a given wind speed, which is thought to be caused by the type of snowflake. Furthermore, the collection efficiency depends strongly on the reference used to correct the data, which is often the Double Fence Intercomparison Reference (DFIR) recommended by the World Meteorological Organization. The goal of this study is to assess the impact of weather conditions on the collection efficiency of the DFIR. Note that the DFIR is defined as a manual gauge placed in a double fence. In this study, however, only the double fence is being investigated while still being called DFIR. To address this issue, a detailed analysis of the flow field in the vicinity of the DFIR is conducted using computational fluid dynamics. Particle trajectories are obtained to compute the collection efficiency associated with different precipitation types for varying wind speed. The results show that the precipitation reaching the center of the DFIR can exceed 100% of the actual precipitation, and it depends on the snowflake type, wind speed, and direction. Overall, this study contributes to a better understanding of the sources of uncertainty associated with the use of the DFIR as a reference gauge to measure snowfall.

Impact of melting snow on the valley flow field and precipitation phase transition - Thériault, Julie M.; Milbrandt, Jason A.; Doyle, Jonathan; Minder, Justin R.; Thompson, Gregory; Sarkadi, Noemi; Geresdi, Istvan (Atmospheric Research, 2015)

Clarification of the Water Saturation Represented on Ice Crystal Growth Diagrams - St-Pierre, Médéric; Thériault, Julie M. (Journal of the Atmospheric Sciences, 2015)
It has been known for a long time that the shape of ice crystals depends on both the air temperature and the relative humidity of the environment. The relationships among these factors have been summarized in classification diagrams and are intensively referred to in the cloud physics literature. To put in perspective the atmospheric conditions in which the different ice crystal habits grow with respect to the level of saturation in the atmosphere, the vapor density excess and supersaturation with respect to ice at liquid water saturation have been included on those diagrams as a function of air temperature. Over the years, the definition of the water saturation included in those types of diagrams has been misdefined. The goal of this study is to show that an error has been introduced in the definition of the excess of water vapor with respect to ice.

An Improved Trajectory Model to Evaluate the Collection Performance of Snow Gauges - Colli, Matteo; Rasmussen, Roy; Thériault, Julie M.; Lanza, Luca G.; Baker, C. Bruce; Kochendorfer, John (Journal of Applied Meteorology and Climatology, 2015)
Abstract Recent studies have used numerical models to estimate the collection efficiency of solid precipitation gauges when exposed to the wind in both shielded and unshielded configurations. The models used computational fluid dynamics (CFD) simulations of the airflow pattern generated by the aerodynamic response to the gauge–shield geometry. These are used as initial conditions to perform Lagrangian tracking of solid precipitation particles. Validation of the results against field observations yielded similarities in the overall behavior, but the model output only approximately reproduced the dependence of the experimental collection efficiency on wind speed. This paper presents an improved snowflake trajectory modeling scheme due to the inclusion of a dynamically determined drag coefficient. The drag coefficient was estimated using the local Reynolds number as derived from CFD simulations within a time-independent Reynolds-averaged Navier–Stokes approach. The proposed dynamic model greatly improves the consistency of results with the field observations recently obtained at the Marshall Field winter precipitation test bed in Boulder, Colorado.

The June 2013 Alberta catastrophic flooding event – part 2: fine‐scale precipitation and associated features - Kochtubajda, B.; Stewart, R. E.; Boodoo, S.; Thériault, J. M.; Li, Y.; Liu, A.; Mooney, C.; Goodson, R.; Szeto, K. (Hydrological Processes, 2016)
Abstract Data obtained from a variety of sources including the Canadian Lightning Detection Network, weather radars, weather stations and operational numerical weather model analyses were used to address the evolution of precipitation during the June 2013 southern Alberta flood. The event was linked to a mid‐level closed low pressure system to the west of the region and a surface low pressure region initially to its south. This configuration brought warm, moist unstable air into the region that led to dramatic, organized convection with an abundance of lightning and some hail. Such conditions occurred in the southern parts of the region whereas the northern parts were devoid of lightning. Initially, precipitation rates were high (extreme 15‐min rainfall rates up to 102 mm h −1 were measured) but decreased to lower values as the precipitation shifted to long‐lived stratiform conditions. Both the convective and stratiform precipitation components were affected by the topography. Similar flooding events, such as June 2002, have occurred over this region although the 2002 event was colder and precipitation was not associated with substantial convection over southwest Alberta. Copyright © 2016 Her Majesty the Queen in Right of Canada. Hydrological Processes. © John Wiley & Sons, Ltd.

The June 2013 Alberta Catastrophic Flooding Event: Part 1—Climatological aspects and hydrometeorological features - Liu, A. Q.; Mooney, C.; Szeto, K.; Thériault, J. M.; Kochtubajda, B.; Stewart, R. E.; Boodoo, S.; Goodson, R.; Li, Y.; Pomeroy, J. (Hydrological Processes, 2016)
Abstract In June 2013, excessive rainfall associated with an intense weather system triggered severe flooding in southern Alberta, which became the costliest natural disaster in Canadian history. This article provides an overview of the climatological aspects and large‐scale hydrometeorological features associated with the flooding event based upon information from a variety of sources, including satellite data, upper air soundings, surface observations and operational model analyses. The results show that multiple factors combined to create this unusually severe event. The event was characterized by a slow‐moving upper level low pressure system west of Alberta, blocked by an upper level ridge, while an associated well‐organized surface low pressure system kept southern Alberta, especially the eastern slopes of the Rocky Mountains, in continuous precipitation for up to two days. Results from air parcel trajectory analysis show that a significant amount of the moisture originated from the central Great Plains, transported into Alberta by a southeasterly low level jet. The event was first dominated by significant thunderstorm activity, and then evolved into continuous precipitation supported by the synoptic‐scale low pressure system. Both the thunderstorm activity and upslope winds associated with the low pressure system produced large rainfall amounts. A comparison with previous similar events occurring in the same region suggests that the synoptic‐scale features associated with the 2013 rainfall event were not particularly intense; however, its storm environment was the most convectively unstable. The system also exhibited a relatively high freezing level, which resulted in rain, rather than snow, mainly falling over the still snow‐covered mountainous areas. Melting associated with this rain‐on‐snow scenario likely contributed to downstream flooding. Furthermore, above‐normal snowfall in the preceding spring helped to maintain snow in the high‐elevation areas, which facilitated the rain‐on‐snow event. Copyright © 2016 John Wiley & Sons, Ltd.

The Collection Efficiency of Shielded and Unshielded Precipitation Gauges. Part II: Modeling Particle Trajectories - Colli, Matteo; Lanza, Luca G.; Rasmussen, Roy; Thériault, Julie M. (Journal of Hydrometeorology, 2016)
Abstract The use of windshields to reduce the impact of wind on snow measurements is common. This paper investigates the catching performance of shielded and unshielded gauges using numerical simulations. In Part II, the role of the windshield and gauge aerodynamics, as well as the varying flow field due to the turbulence generated by the shield–gauge configuration, in reducing the catch efficiency is investigated. This builds on the computational fluid dynamics results obtained in Part I, where the airflow patterns in the proximity of an unshielded and single Alter shielded Geonor T-200B gauge are obtained using both time-independent [Reynolds-averaged Navier–Stokes (RANS)] and time-dependent [large-eddy simulation (LES)] approaches. A Lagrangian trajectory model is used to track different types of snowflakes (wet and dry snow) and to assess the variation of the resulting gauge catching performance with the wind speed. The collection efficiency obtained with the LES approach is generally lower than the one obtained with the RANS approach. This is because of the impact of the LES-resolved turbulence above the gauge orifice rim. The comparison between the collection efficiency values obtained in case of shielded and unshielded gauge validates the choice of installing a single Alter shield in a windy environment. However, time-dependent simulations show that the propagating turbulent structures produced by the aerodynamic response of the upwind single Alter blades have an impact on the collection efficiency. Comparison with field observations provides the validation background for the model results.

The Collection Efficiency of Shielded and Unshielded Precipitation Gauges. Part I: CFD Airflow Modeling - Colli, Matteo; Lanza, Luca G.; Rasmussen, Roy; Thériault, Julie M. (Journal of Hydrometeorology, 2016)
Abstract The aerodynamic response of snow gauges when exposed to the wind is responsible for a significant reduction of their collection performance. The modifications induced by the gauge and the windshield onto the space–time patterns of the undisturbed airflow deviate the snowflake trajectories. In Part I, the disturbed air velocity field in the vicinity of shielded and unshielded gauge configurations is investigated. In Part II, the airflow is the basis for a particle tracking model of snowflake trajectories to estimate the collection efficiency. A Geonor T-200B gauge inside a single Alter shield is simulated for wind speeds varying from 1 to 8 m s−1. Both time-averaged and time-dependent computational fluid dynamics simulations are performed, based on Reynolds-averaged Navier–Stokes (RANS) and large-eddy simulation (LES) models, respectively. A shear stress tensor k–Ω model (where k is the turbulent kinetic energy and Ω is the turbulent specific dissipation rate) is used for the RANS formulation and solved within a finite-volume method. The LES is implemented with a Smagorinsky subgrid-scale method that models the subgrid stresses as a gradient-diffusion process. The RANS simulations confirm the attenuation of the airflow velocity above the gauge when using a single Alter shield, but the generated turbulence above the orifice rim is underestimated. The intensity and spatial extension of the LES-resolved turbulent region show a dependency on the wind speed that was not detected by the RANS. The time-dependent analysis showed the propagation of turbulent structures and the impact on the turbulent kinetic energy above the gauge collecting section.

Spatial spin-up of fine scales in a regional climate model simulation driven by low-resolution boundary conditions - Matte, Dominic; Laprise, René; Thériault, Julie M.; Lucas-Picher, Philippe (Climate Dynamics, 2017)

On the relationship between the snowflake type aloft and the surface precipitation types at temperatures near 0 °C - Sankaré, Housseyni; Thériault, Julie M. (Atmospheric Research, 2016)

Comparison between high-resolution climate simulations using single- and double-nesting approaches within the Big-Brother experimental protocol - Matte, Dominic; Laprise, René; Thériault, Julie Mireille (Climate Dynamics, 2016)

Evaluating the Ability of CRCM5 to Simulate Mixed Precipitation - Bresson, É.; Laprise, R.; Paquin, D.; Thériault, J.M.; De Elía, R. (Atmosphere-Ocean, 2017)

A Numerical Study of the June 2013 Flood-Producing Extreme Rainstorm over Southern Alberta - Li, Yanping; Szeto, Kit; Stewart, Ronald E.; Thériault, Julie M.; Chen, Liang; Kochtubajda, Bohdan; Liu, Anthony; Boodoo, Sudesh; Goodson, Ron; Mooney, Curtis; Kurkute, Sopan (Journal of Hydrometeorology, 2017)
Abstract A devastating, flood-producing rainstorm occurred over southern Alberta, Canada, from 19 to 22 June 2013. The long-lived, heavy rainfall event was a result of complex interplays between topographic, synoptic, and convective processes that rendered an accurate simulation of this event a challenging task. In this study, the Weather Research and Forecasting (WRF) Model was used to simulate this event and was validated against several observation datasets. Both the timing and location of the model precipitation agree closely with the observations, indicating that the WRF Model is capable of reproducing this type of severe event. Sensitivity tests with different microphysics schemes were conducted and evaluated using equitable threat and bias frequency scores. The WRF double-moment 6-class microphysics scheme (WDM6) generally performed better when compared with other schemes. The application of a conventional convective/stratiform separation algorithm shows that convective activity was dominant during the early stages, then evolved into predominantly stratiform precipitation later in the event. The HYSPLIT back-trajectory analysis and regional water budget assessments using WRF simulation output suggest that the moisture for the precipitation was mainly from recycling antecedent soil moisture through evaporation and evapotranspiration over the Canadian Prairies and the U.S. Great Plains. This analysis also shows that a small fraction of the moisture can be traced back to the northeastern Pacific, and direct uptake from the Gulf of Mexico was not a significant source in this event.

Improving the Explicit Prediction of Freezing Rain in a Kilometer-Scale Numerical Weather Prediction Model - Barszcz, Agnieszka; Milbrandt, Jason A.; Thériault, Julie M. (Weather and Forecasting, 2018)
Abstract A freezing rain event, in which the Meteorological Centre of Canada’s 2.5-km numerical weather prediction system significantly underpredicted the quantity of freezing rain, is examined. The prediction system models precipitation types explicitly, directly from the Milbrandt–Yau microphysics scheme. It was determined that the freezing rain underprediction for this case was due primarily to excessive refreezing of rain, originating from melting snow and graupel, in and under the temperature inversion of the advancing warm front ultimately depleting the supply of rain reaching the surface. The refreezing was caused from excessive collisional freezing between rain and graupel. Sensitivity experiments were conducted to examine the effects of a temperature threshold for collisional freezing and on varying the values of the collection efficiencies between rain and ice-phase hydrometeors. It was shown that by reducing the rain–graupel collection efficiency and by imposing a temperature threshold of −5°C, above which collisional freezing is not permitted, excessive rain–graupel collection and graupel formation can be controlled in the microphysics scheme, leading to an improved simulation of freezing rain at the surface.

Mixed precipitation occurrences over southern Québec, Canada, under warmer climate conditions using a regional climate model - Matte, Dominic; Thériault, Julie M.; Laprise, René (Climate Dynamics, 2019)

Precipitation characteristics and associated weather conditions on the eastern slopes of the Canadian Rockies during March–April 2015 - Thériault, Julie M.; Hung, Ida; Vaquer, Paul; Stewart, Ronald E.; Pomeroy, John W. (Hydrology and Earth System Sciences, 2018)
Abstract. Precipitation events that bring rain and snow to the Banff–Calgary area of Alberta are a critical aspect of the region's water cycle and can lead to major flooding events such as the June 2013 event that was the second most costly natural disaster in Canadian history. Because no special atmospheric-oriented observations of these events have been made, a field experiment was conducted in March and April 2015 in Kananaskis, Alberta, to begin to fill this gap. The goal was to characterize and better understand the formation of the precipitation at the surface during spring 2015 at a specific location in the Kananaskis Valley. Within the experiment, detailed measurements of precipitation and weather conditions were obtained, a vertically pointing Doppler radar was deployed and weather balloons were released. Although 17 precipitation events occurred, this period was associated with much less precipitation than normal (−35 %) and above-normal temperatures (2.5 ∘C). Of the 133 h of observed precipitation, solid precipitation occurred 71 % of the time, mixed precipitation occurred 9 % and rain occurred 20 %. An analysis of 17 504 precipitation particles from 1181 images showed that a wide variety of crystals and aggregates occurred and approximately 63 % showed signs of riming. This was largely independent of whether flows aloft were upslope (easterly) or downslope (westerly). In the often sub-saturated surface conditions, hydrometeors containing ice occurred at temperatures as high as 9 ∘C. Radar structures aloft were highly variable with reflectivity sometimes >30 dBZe and Doppler velocity up to −1 m s−1, which indicates upward motion of particles within ascending air masses. Precipitation was formed in this region within cloud fields sometimes having variable structures and within which supercooled water at least sometimes existed to produce accreted particles massive enough to reach the surface through the relatively dry sub-cloud region.

Parameterization of the Bulk Liquid Fraction on Mixed-Phase Particles in the Predicted Particle Properties (P3) Scheme: Description and Idealized Simulations - Cholette, Mélissa; Morrison, Hugh; Milbrandt, Jason A.; Thériault, Julie M. (Journal of the Atmospheric Sciences, 2019)
Abstract Bulk microphysics parameterizations that are used to represent clouds and precipitation usually allow only solid and liquid hydrometeors. Predicting the bulk liquid fraction on ice allows an explicit representation of mixed-phase particles and various precipitation types, such as wet snow and ice pellets. In this paper, an approach for the representation of the bulk liquid fraction into the predicted particle properties (P3) microphysics scheme is proposed and described. Solid-phase microphysical processes, such as melting and sublimation, have been modified to account for the liquid component. New processes, such as refreezing and condensation of the liquid portion of mixed-phase particles, have been added to the parameterization. Idealized simulations using a one-dimensional framework illustrate the overall behavior of the modified scheme. The proposed approach compares well to a Lagrangian benchmark model. Temperatures required for populations of ice crystals to melt completely also agree well with previous studies. The new processes of refreezing and condensation impact both the surface precipitation type and feedback between the temperature and the phase changes. Overall, prediction of the bulk liquid fraction allows an explicit description of new precipitation types, such as wet snow and ice pellets, and improves the representation of hydrometeor properties when the temperature is near 0°C.

Influence of the Model Horizontal Resolution on Atmospheric Conditions Leading to Freezing Rain in Regional Climate Simulations - St-Pierre, Médéric; Thériault, Julie M.; Paquin, Dominique (Atmosphere-Ocean, 2019)

A Review and Synthesis of Future Earth System Change in theInterior of Western Canada: Part I – Climate and Meteorology - Stewart, Ronald E.; Szeto, Kit K.; Bonsal, Barrie R.; Hanesiak, John M.; Kochtubajda, Bohdan; Li, Yanping; Thériault, Julie M.; DeBeer, Chris M.; Tam, Benita Y.; Li, Zhenhua; Liu, Zhuo; Bruneau, Jennifer A.; et al. (Hydrometeorology/Modelling approaches, 2019)
Abstract. The Interior of Western Canada, up to and including the Arctic, has experienced rapid change in its climate, hydrology, cryosphere and ecosystems and this is expected to continue. Although there is general consensus that warming will occur in the future, many critical issues remain. In this first of two articles, attention is placed on atmospheric-related issues that range from large scales down to individual precipitation events. Each of these is considered in terms of expected change organized by season and utilizing climate scenario information as well as thermodynamically-driven future climatic forcing simulations. Large scale atmospheric circulations affecting this region are generally projected to become stronger in each season and, coupled with warming temperatures, lead to enhancements of numerous water-related and temperature-related extremes. These include winter snowstorms, freezing rain, drought as well as atmospheric forcing of spring floods although not necessarily summer convection. Collective insights of these atmospheric findings are summarized in a consistent, connected physical framework.

Role of sublimation and riming in the precipitation distribution in the Kananaskis Valley, Alberta, Canada - Poirier, Émilie; Thériault, Julie M.; Leriche, Maud (Hydrology and Earth System Sciences, 2019)
Abstract. The phase of precipitation and its distribution at the surface can affect water resources and the regional water cycle of a region. A field project was held in March–April 2015 on the eastern slope of the Canadian Rockies to document precipitation characteristics and associated atmospheric conditions. During the project, 60 % of the particles documented were rimed in relatively warm and dry conditions. Rain–snow transitions also occurred aloft and at the surface in sub-saturated conditions. Ice-phase precipitation falling through a saturated atmospheric layer with temperatures > 0 ∘C will start melting. In contrast, if the melting layer is sub-saturated, the ice-phase precipitation undergoes sublimation, which increases the depth of the rain–snow transition. In this context, this study investigates the role of sublimation and riming in precipitation intensity and type reaching the surface in the Kananaskis Valley, Alberta, during March–April 2015. To address this, a set of numerical simulations of an event of mixed precipitation observed at the surface was conducted. This event on 31 March 2015 was documented with a set of devices at the main observation site (Kananaskis Emergency Services, KES), including a precipitation gauge, disdrometer, and micro rain radar. Sensitivity experiments were performed to assess the impacts of temperature changes from sublimation and the role of the production of graupel (riming) aloft in the surface precipitation evolution. A warmer environment associated with no temperature changes from sublimation leads to a peak in the intensity of graupel at the surface. When the formation of graupel is not considered, the maximum snowfall rate occurred at later times. Results suggest that unrimed snow reaching the surface is formed on the western flank and is advected eastward. In contrast, graupel would form aloft in the Kananaskis Valley. The cooling from sublimation and melting by rimed particles increases the vertical shear near KES. Overall, this study illustrated that the presence of graupel influenced the surface evolution of precipitation type in the valley due to the horizontal transport of precipitation particles.

Near-0 °C surface temperature and precipitation type patterns across Canada - Mekis, Eva; Stewart, Ronald E.; Theriault, Julie M.; Kochtubajda, Bohdan; Bonsal, Barrie R.; Liu, Zhuo (Hydrology and Earth System Sciences, 2020)
Abstract. The 0 ∘C temperature threshold is critical for many meteorological and hydrological processes driven by melting and freezing in the atmosphere, surface, and sub-surface and by the associated precipitation varying between rain, freezing rain, wet snow, and snow. This threshold is especially important in cold regions such as Canada, because it is linked with freeze–thaw, snowmelt, and permafrost. This study develops a Canada-wide perspective on near-0 ∘C conditions using hourly surface temperature and precipitation type observations from 92 climate stations for the period from 1981 to 2011. In addition, nine stations from various climatic regions are selected for further analysis. Near-0 ∘C conditions are defined as periods when the surface temperature is between −2 and 2 ∘C. Near-0 ∘C conditions occur often across all regions of the country, although the annual number of days and hours and the duration of these events varies dramatically. Various types of precipitation (e.g., rain, freezing rain, wet snow, and ice pellets) sometimes occur with these temperatures. Near-0 ∘C conditions and the reported precipitation type occurrences tend to be higher in Atlantic Canada, although high values also occur in other regions. Trends of most temperature-based and precipitation-based indicators show little or no change despite a systematic warming in annual surface temperatures over Canada. Over the annual cycle, near-0 ∘C temperatures and precipitation often exhibit a pattern: short durations occur around summer, driven by the diurnal cycle, and a tendency toward longer durations around winter, associated with storms. There is also a tendency for near-0 ∘C surface temperatures to occur more often than expected relative to other temperature windows at some stations due, at least in part, to diabatic cooling and heating that take place with melting and freezing, respectively, in the atmosphere and at the surface.

Adjustments for Wind-Induced Undercatch in Snowfall Measurements Based on Precipitation Intensity - Colli, Matteo; Stagnaro, Mattia; Lanza, Luca G.; Rasmussen, Roy; Thériault, Julie M. (Journal of Hydrometeorology, 2020)
Abstract Adjustments for the wind-induced undercatch of snowfall measurements use transfer functions to account for the expected reduction of the collection efficiency with increasing the wind speed for a particular catching-type gauge. Based on field experiments or numerical simulation, collection efficiency curves as a function of wind speed also involve further explanatory variables such as surface air temperature and/or precipitation type. However, while the wind speed or wind speed and temperature approach is generally effective at reducing the measurement bias, it does not significantly reduce the root-mean-square error (RMSE) of the residuals, implying that part of the variance is still unexplained. In this study, we show that using precipitation intensity as the explanatory variable significantly reduces the scatter of the residuals. This is achieved by optimized curve fitting of field measurements from the Marshall Field Site (Colorado, United States), using a nongradient optimization algorithm to ensure optimal binning of experimental data. The analysis of a recent quality-controlled dataset from the Solid Precipitation Intercomparison Experiment (SPICE) campaign of the World Meteorological Organization confirms the scatter reduction, showing that this approach is suitable to a variety of locations and catching-type gauges. Using computational fluid dynamics simulations, we demonstrate that the physical basis of the reduction in RMSE is the correlation of precipitation intensity with the particle size distribution. Overall, these findings could be relevant in operational conditions since the proposed adjustment of precipitation measurements only requires wind sensor and precipitation gauge data.

Impacts of Predicting the Liquid Fraction of Mixed-Phase Particles on the Simulation of an Extreme Freezing Rain Event: The 1998 North American Ice Storm - Cholette, Mélissa; Thériault, Julie M.; Milbrandt, Jason A.; Morrison, Hugh (Monthly Weather Review, 2020)
Abstract A prognostic equation for the liquid fraction of mixed-phase particles has been recently added to the Predicted Particle Properties (P3) bulk microphysics scheme. Mixed-phase particles are necessary to simulate key microphysical processes leading to various winter precipitation types, such as ice pellets and freezing rain. To illustrate the impacts of predicting the bulk liquid fraction, the 1998 North American Ice Storm is simulated using the Weather Research and Forecasting (WRF) Model with the modified P3 scheme. It is found that simulating partial melting by predicting the bulk liquid fraction produces higher mass and number mixing ratios of rain. This leads to smaller rain sizes reaching the refreezing layer as well as a decrease in the freezing rain accumulation at the surface by up to 30% in some locations compared to when no liquid fraction is predicted. The increase in fall speed and density and decrease of particle diameter during partial melting combined with an improved representation of the refreezing process in the modified P3 leads to generally higher total solid surface precipitation rates than using the original P3 scheme. There is also an increase of solid precipitation in regions of ice pellet accumulation. Overall, the simulation of mixed-phase particles notably impacts the vertical and spatial distributions of precipitation properties.

Summary and synthesis of Changing Cold Regions Network (CCRN) research in the interior of western Canada – Part 2: Future change in cryosphere, vegetation, and hydrology - DeBeer, Chris M.; Wheater, Howard S.; Pomeroy, John W.; Barr, Alan G.; Baltzer, Jennifer L.; Johnstone, Jill F.; Turetsky, Merritt R.; Stewart, Ronald E.; Hayashi, Masaki; Van Der Kamp, Garth; Marshall, Shawn; Campbell, Elizabeth; et al. (Hydrology and Earth System Sciences, 2021)
Abstract. The interior of western Canada, like many similar cold mid- to high-latitude regions worldwide, is undergoing extensive and rapid climate and environmental change, which may accelerate in the coming decades. Understanding and predicting changes in coupled climate–land–hydrological systems are crucial to society yet limited by lack of understanding of changes in cold-region process responses and interactions, along with their representation in most current-generation land-surface and hydrological models. It is essential to consider the underlying processes and base predictive models on the proper physics, especially under conditions of non-stationarity where the past is no longer a reliable guide to the future and system trajectories can be unexpected. These challenges were forefront in the recently completed Changing Cold Regions Network (CCRN), which assembled and focused a wide range of multi-disciplinary expertise to improve the understanding, diagnosis, and prediction of change over the cold interior of western Canada. CCRN advanced knowledge of fundamental cold-region ecological and hydrological processes through observation and experimentation across a network of highly instrumented research basins and other sites. Significant efforts were made to improve the functionality and process representation, based on this improved understanding, within the fine-scale Cold Regions Hydrological Modelling (CRHM) platform and the large-scale Modélisation Environmentale Communautaire (MEC) – Surface and Hydrology (MESH) model. These models were, and continue to be, applied under past and projected future climates and under current and expected future land and vegetation cover configurations to diagnose historical change and predict possible future hydrological responses. This second of two articles synthesizes the nature and understanding of cold-region processes and Earth system responses to future climate, as advanced by CCRN. These include changing precipitation and moisture feedbacks to the atmosphere; altered snow regimes, changing balance of snowfall and rainfall, and glacier loss; vegetation responses to climate and the loss of ecosystem resilience to wildfire and disturbance; thawing permafrost and its influence on landscapes and hydrology; groundwater storage and cycling and its connections to surface water; and stream and river discharge as influenced by the various drivers of hydrological change. Collective insights, expert elicitation, and model application are used to provide a synthesis of this change over the CCRN region for the late 21st century.

Precipitation Type Distribution and Microphysical Processes During the 1998 Ice Storm Simulated Under Pseudo‐Warmer Conditions - Cholette, Mélissa; Thériault, Julie Mireille (Journal of Geophysical Research: Atmospheres, 2021)
Abstract In the future, the intensity, phases, and frequency of precipitation are expected to change due to global warming, in particular during colder seasons when temperatures are near 0°C. To investigate the impacts of warmer atmospheric conditions on the microphysical processes that lead to several precipitation types, the extreme 1998 Ice Storm was simulated using the Weather Research and Forecasting (WRF) model, with and without a pseudo‐global warming. The pseudo‐global warming approach simulates similar large‐scale conditions but in warmer conditions, which allows for the assessment of thermodynamic feedback from cloud and precipitation microphysics. For both simulations, WRF was coupled with the Predicted Particle Properties (P3) bulk microphysics scheme that predicts the liquid fraction of mixed‐phase particles. Results of the pseudo‐global warming simulation show an increase of ∼828 m in the upper 0°C level and a northeastward migration (∼60 km) of the rain‐snow transition region. The results also show a 20% decrease in domain‐averaged freezing rain amounts, but with an increased maximum amount of 50%. The horizontal distance associated with a melting aloft and a refreezing layer near the surface is 105 km longer in southern Quebec due to the combined effects of the pseudo‐warming and the presence of the Appalachian Mountains. The microphysical processes that lead to precipitation are impacted as well; the increased ice mass and riming conditions aloft in warmer temperatures result in higher liquid precipitation rates. This study contributes to our understanding of the changes in the fine‐scale processes of an extreme storm, simulated with pseudo‐global warming conditions. , Key Points The major 1998 Ice Storm was simulated with the Weather Research and Forecasting model, with and without a pseudo‐global warming A higher melting layer in warmer conditions led to more riming aloft, larger drops, and higher maximum amounts of rain and freezing rain The precipitation type transition region is wider in the warmer conditions over the geographical areas of both southern Quebec and Maine

Meteorological observations collected during the Storms and Precipitation Across the continental Divide Experiment (SPADE), April–June 2019 - Thériault, Julie M.; Déry, Stephen J.; Pomeroy, John W.; Smith, Hilary M.; Almonte, Juris; Bertoncini, André; Crawford, Robert W.; Desroches-Lapointe, Aurélie; Lachapelle, Mathieu; Mariani, Zen; Mitchell, Selina; Morris, Jeremy E.; et al. (Earth System Science Data, 2021)
Abstract. The continental divide along the spine of the Canadian Rockies in southwestern Canada is a critical headwater region for hydrological drainages to the Pacific, Arctic, and Atlantic oceans. Major flooding events are typically attributed to heavy precipitation on its eastern side due to upslope (easterly) flows. Precipitation can also occur on the western side of the divide when moisture originating from the Pacific Ocean encounters the west-facing slopes of the Canadian Rockies. Often, storms propagating across the divide result in significant precipitation on both sides. Meteorological data over this critical region are sparse, with few stations located at high elevations. Given the importance of all these types of events, the Storms and Precipitation Across the continental Divide Experiment (SPADE) was initiated to enhance our knowledge of the atmospheric processes leading to storms and precipitation on either side of the continental divide. This was accomplished by installing specialized meteorological instrumentation on both sides of the continental divide and carrying out manual observations during an intensive field campaign from 24 April–26 June 2019. On the eastern side, there were two field sites: (i) at Fortress Mountain Powerline (2076 m a.s.l.) and (ii) at Fortress Junction Service, located in a high-elevation valley (1580 m a.s.l.). On the western side, Nipika Mountain Resort, also located in a valley (1087 m a.s.l.), was chosen as a field site. Various meteorological instruments were deployed including two Doppler light detection and ranging instruments (lidars), three vertically pointing micro rain radars, and three optical disdrometers. The three main sites were nearly identically instrumented, and observers were on site at Fortress Mountain Powerline and Nipika Mountain Resort during precipitation events to take manual observations of precipitation type and microphotographs of solid particles. The objective of the field campaign was to gather high-temporal-frequency meteorological data and to compare the different conditions on either side of the divide to study the precipitation processes that can lead to catastrophic flooding in the region. Details on field sites, instrumentation used, and collection methods are discussed. Data from the study are publicly accessible from the Federated Research Data Repository at https://doi.org/10.20383/101.0221 (Thériault et al., 2020). This dataset will be used to study atmospheric conditions associated with precipitation events documented simultaneously on either side of a continental divide. This paper also provides a sample of the data gathered during a precipitation event.

Improvement of Solid Precipitation Measurements Using a Hotplate Precipitation Gauge - Thériault, Julie M.; Leroux, Nicolas R.; Rasmussen, Roy M. (Journal of Hydrometeorology, 2021)
Abstract Accurate snowfall measurement is challenging because it depends on the precipitation gauge used, meteorological conditions, and the precipitation microphysics. Upstream of weighing gauges, the flow field is disturbed by the gauge and any shielding used usually creates an updraft, which deflects solid precipitation from falling in the gauge, resulting in significant undercatch. Wind shields are often used with weighing gauges to reduce this updraft, and transfer functions are required to adjust the snowfall measurements to consider gauge undercatch. Using these functions reduces the bias in precipitation measurement but not the root-mean-square error (RMSE). In this study, the accuracy of the Hotplate precipitation gauge was compared to standard unshielded and shielded weighing gauges collected during the WMO Solid Precipitation Intercomparison Experiment program. The analysis performed in this study shows that the Hotplate precipitation gauge bias after wind correction is near zero and similar to wind corrected weighing gauges. The RMSE of the Hotplate precipitation gauge measurements is lower than weighing gauges (with or without an Alter shield) for wind speeds up to 5 m s −1 , the wind speed limit at which sufficient data were available. This study shows that the Hotplate precipitation gauge measurement has a low bias and RMSE due to its aerodynamic shape, making its performance mostly independent of the type of solid precipitation.

Improvement of Snow Gauge Collection Efficiency through a Knowledge of Solid Precipitation Fall Speed - Leroux, Nicolas R.; Thériault, Julie M.; Rasmussen, Roy (Journal of Hydrometeorology, 2021)
Abstract The collection efficiency of a typical precipitation gauge-shield configuration decreases with increasing wind speed, with a high scatter for a given wind speed. The high scatter in the collection efficiency for a given wind speed arises in part from the variability in the characteristics of falling snow and atmospheric turbulence. This study uses weighing gauge data collected at the Marshall Field Site near Boulder, Colorado, during the WMO Solid Precipitation Intercomparison Experiment (SPICE). Particle diameter and fall speed data from a laser disdrometer were used to show that the scatter in the collection efficiency can be reduced by considering the fall speed of solid precipitation particles. The collection efficiency was divided into two classes depending on the measured mean-event particle fall speed during precipitation events. Slower-falling particles were associated with a lower collection efficiency. A new transfer function (i.e., the relationship between collection efficiency and other meteorological variables, such as wind speed or air temperature) that includes the fall speed of the hydrometeors was developed. The root-mean-square error of the adjusted precipitation with the new transfer function with respect to a weighing gauge placed in a double fence intercomparison reference was lower than using previously developed transfer functions that only consider wind speed and air temperature. This shows that the measured fall speed of solid precipitation with a laser disdrometer accounts for a large amount of the observed scatter in weighing gauge collection efficiency.

How Well Are We Measuring Snow Post-SPICE? - Kochendorfer, John; Earle, Michael; Rasmussen, Roy; Smith, Craig; Yang, Daqing; Morin, Samuel; Mekis, Eva; Buisan, Samuel; Roulet, Yves-Alain; Landolt, Scott; Wolff, Mareile; Hoover, Jeffery; et al. (Bulletin of the American Meteorological Society, 2022)
Abstract Accurate snowfall measurements are necessary for meteorology, hydrology, and climate research. Typical uses include creating and calibrating gridded precipitation products, the verification of model simulations, driving hydrologic models, input into aircraft deicing processes, and estimating streamflow runoff in the spring. These applications are significantly impacted by errors in solid precipitation measurements. The recent WMO Solid Precipitation Intercomparison Experiment (SPICE) attempted to characterize and reduce some of the measurement uncertainties through an international effort involving 15 countries utilizing over 20 types and models of precipitation gauges from various manufacturers. Key results from WMO-SPICE are presented herein. Recent work and future research opportunities that build on the results of WMO-SPICE are also highlighted.

Meteorological Factors Responsible for Major Power Outages during a Severe Freezing Rain Storm over Eastern Canada - Thériault, Julie M.; McFadden, Vanessa; Thompson, Hadleigh D.; Cholette, Mélissa (Journal of Applied Meteorology and Climatology, 2022)
Abstract Winter precipitation is the source of many inconveniences in many regions of North America, for both infrastructure and the economy. The ice storm that hit the Canadian Maritime Provinces on 24–26 January 2017 remains one of the most expensive in history for the province of New Brunswick. Up to 50 mm of freezing rain caused power outages across the province, depriving up to one-third of New Brunswick residences of electricity, with some outages lasting 2 weeks. This study aims to use high-resolution atmospheric modeling to investigate the meteorological conditions during this severe storm and their contribution to major power outages. The persistence of a deep warm layer aloft, coupled with the slow movement of the associated low pressure system, contributed to widespread ice accumulation. When combined with the strong winds observed, extensive damage to electricity networks was inevitable. A 2-m temperature cold bias was identified between the simulation and the observations, in particular during periods of freezing rain. In the northern part of New Brunswick, cold-air advection helped keep temperatures below 0°C, while in southern regions, the 2-m temperature increased rapidly to slightly above 0°C because of radiational heating. The knowledge gained in this study on the processes associated with either maintaining or stopping freezing rain will enhance the ability to forecast and, in turn, to mitigate the hazards associated with those extreme events. Significance Statement A slow-moving low pressure system produced up to 50 mm of freezing rain for 31 h along the east coast of New Brunswick, Canada, on 24–26 January 2017, causing unprecedented power outages. Warm-air advection aloft, along with a combination of higher wind speeds and large amounts of ice accumulation, created ideal conditions for severe freezing rain. The storm began with freezing rain along the entire north–south cross section of eastern New Brunswick and changed to rain only in the south, when local temperatures increased to >0°C. Near-surface cold-air advection kept temperatures below 0°C in the north. Warming from the latent heat produced by freezing contributed to persistent near-0°C conditions during freezing rain.

Freezing Rain Events that Impacted the Province of New Brunswick, Canada, and Their Evolution in a Warmer Climate - Chartrand, Julien; Thériault, Julie M.; Marinier, Sébastien (Atmosphere-Ocean, 2023)

Characteristics of Precipitation Particles and Microphysical Processes during the 11–12 January 2020 Ice Pellet Storm in the Montréal Area, Québec, Canada - Lachapelle, Mathieu; Thériault, Julie M. (Monthly Weather Review, 2022)
Abstract Freezing rain and ice pellets are particularly difficult to forecast when solid precipitation is completely melted aloft. This study addresses this issue by investigating the processes that led to a long-duration ice pellet event in Montreal, Québec, Canada, on 11–12 January 2020. To do so, a benchmark model initialized with ERA5 data is used to show that solid precipitation was completely melted below the melting layer, which discards partial melting from the possible ice pellet formation processes. Macro photography of precipitation reveals that small columnar crystals (∼200 μ m) and ice pellets occurred simultaneously for more than 10 h. The estimation of ice crystal number concentration using macro photographs and laser-optical disdrometer data suggests that all supercooled drops could have refrozen by contact freezing with ice crystals. Rimed ice pellets also indicate ice supersaturation in the subfreezing layer. Given these observations, the formation of ice pellets and ice crystals was probably promoted by secondary ice production and the horizontal advection of ice crystals below the melting layer, as we illustrate using a conceptual model. Overall, these findings demonstrate how ice nucleation processes at temperatures near 0°C can drastically change the precipitation phase and the impact of a storm. Significance Statement Ice pellets are generally formed when snow particles partially melt while falling through a warm layer aloft before completely refreezing in a cold layer closer to the surface. Ice pellets can also be formed when snow particles completely melt aloft, but freezing rain is often produced in such conditions. On 11–12 January 2020, ice pellets were produced during more than 10 h in Montreal, Quebec, Canada. Macro photographs of the precipitation particles show that ice pellets occurred simultaneously with small ice crystals. Most of the ice pellets were produced while snow particles were completely melted aloft. The supercooled drops probably refroze due to collisions with the ice crystals that could have been advected by the northeasterly winds near the surface.

Quantifying the Impact of Precipitation-Type Algorithm Selection on the Representation of Freezing Rain in an Ensemble of Regional Climate Model Simulations - McCray, Christopher D.; Thériault, Julie M.; Paquin, Dominique; Bresson, Émilie (Journal of Applied Meteorology and Climatology, 2022)
Abstract Given their potentially severe impacts, understanding how freezing rain events may change as the climate changes is of great importance to stakeholders including electrical utility companies and local governments. Identification of freezing rain in climate models requires the use of precipitation-type algorithms, and differences between algorithms may lead to differences in the types of precipitation identified for a given thermodynamic profile. We explore the uncertainty associated with algorithm selection by applying four algorithms (Cantin and Bachand, Baldwin, Ramer, and Bourgouin) offline to an ensemble of simulations of the fifth-generation Canadian Regional Climate Model (CRCM5) at 0.22° grid spacing. First, we examine results for the CRCM5 driven by ERA-Interim reanalysis to analyze how well the algorithms reproduce the recent climatology of freezing rain and how results vary depending on algorithm parameters and the characteristics of available model output. We find that while the Ramer and Baldwin algorithms tend to be better correlated with observations than Cantin and Bachand or Bourgouin, their results are highly sensitive to algorithm parameters and to the number of pressure levels used. We also apply the algorithms to four CRCM5 simulations driven by different global climate models (GCMs) and find that the uncertainty associated with algorithm selection is generally similar to or greater than that associated with choice of driving GCM for the recent past climate. Our results provide guidance for future studies on freezing rain in climate simulations and demonstrate the importance of accounting for uncertainty between algorithms when identifying precipitation type from climate model output. Significance Statement Freezing rain events and ice storms can have major consequences, including power outages and dangerous road conditions. It is therefore important to understand how climate change might affect the frequency and severity of these events. One source of uncertainty in climate studies of these events is related to the choice of algorithm used to detect freezing rain in model output. We compare the frequency of freezing rain identified using four different algorithms and find sometimes large differences depending on the algorithm chosen over some regions. Our findings highlight the importance of taking this source of uncertainty into account and will provide researchers with guidance as to which algorithms are best suited for climate studies of freezing rain.

A Multi‐Algorithm Analysis of Projected Changes to Freezing Rain Over North America in an Ensemble of Regional Climate Model Simulations - McCray, Christopher D.; Paquin, Dominique; Thériault, Julie M.; Bresson, Émilie (Journal of Geophysical Research: Atmospheres, 2022)
Abstract Freezing rain events have caused severe socioeconomic and ecosystem impacts. An understanding of how these events may evolve as the Earth warms is necessary to adequately adapt infrastructure to these changes. We present an analysis of projected changes to freezing rain events over North America relative to the 1980–2009 recent past climate for the periods during which +2, +3, and +4°C of global warming is attained. We diagnose freezing rain using four precipitation‐type algorithms (Cantin and Bachand, Bourgouin, Ramer, and Baldwin) applied to four simulations of the fifth‐generation Canadian Regional Climate Model (CRCM5) driven by four global climate models (GCMs). We find that the choice of driving GCM strongly influences the spatial pattern of projected change. The choice of algorithm has a comparatively smaller impact, and primarily affects the magnitude but not the sign of projected change. We identify several regions where all simulations and algorithms agree on the sign of change, with increases projected over portions of western Canada and decreases over the central, eastern, and southern United States. However, we also find large regions of disagreement on the sign of change depending on driving GCM and even ensemble member of the same GCM, highlighting the importance of examining freezing rain events in a multi‐member ensemble of simulations driven by multiple GCMs to sufficiently account for uncertainty in projections of these hazardous events. , Plain Language Summary Freezing rain events, or ice storms, can have major impacts on electrical infrastructure, agriculture, and road and air travel. Despite these impacts, relatively little research has been done on how these events may change as the Earth warms. We therefore examine several climate model simulations to determine how the frequency of freezing rain may change at different levels of future global warming. We focus in particular on how sensitive the projected changes are to the method used to identify freezing rain in the model output, as well as to the choice of climate model used to produce the projections. We find strong agreement among methods and models on a decrease in freezing rain frequency over much of the United States (from Texas northeastward to Maine) and an increase in freezing rain frequency over portions of western Canada (Alberta, Saskatchewan, Manitoba). In many other areas, however, the different methods and simulations disagree on the direction of projected change. Our findings highlight the importance of using many different climate models, rather than single simulations, to paint a clearer picture of the level of certainty in projections of freezing rain in the context of global warming. , Key Points Freezing rain is projected to increase in frequency over portions of western and central Canada and decrease over most of the United States The sign of projected changes is not highly sensitive to the precipitation‐type algorithm used to diagnose freezing rain The choice of driving global climate model is a key source of uncertainty in both the sign and magnitude of projected changes

Snow Level From Post‐Processing of Atmospheric Model Improves Snowfall Estimate and Snowpack Prediction in Mountains - Vionnet, V.; Verville, M.; Fortin, V.; Brugman, M.; Abrahamowicz, M.; Lemay, F.; Thériault, J. M.; Lafaysse, M.; Milbrandt, J. A. (Water Resources Research, 2022)
Abstract In mountains, the precipitation phase greatly varies in space and time and affects the evolution of the snow cover. Snowpack models usually rely on precipitation‐phase partitioning methods (PPMs) that use near‐surface variables. These PPMs ignore conditions above the surface thus limiting their ability to predict the precipitation phase at the surface. In this study, the impact on snowpack simulations of atmospheric‐based PPMs, incorporating upper atmospheric information, is tested using the snowpack scheme Crocus. Crocus is run at 2.5‐km grid spacing over the mountains of southwestern Canada and northwestern United States and is driven by meteorological fields from an atmospheric model at the same resolution. Two atmospheric‐based PPMs were considered from the atmospheric model: the output from a detailed microphysics scheme and a post‐processing algorithm determining the snow level and the associated precipitation phase. Two ground‐based PPMs were also included as lower and upper benchmarks: a single air temperature threshold at 0°C and a PPM using wet‐bulb temperature. Compared to the upper benchmark, the snow‐level based PPM improved the estimation of snowfall occurrence by 5% and the simulation of snow water equivalent (SWE) by 9% during the snow melting season. In contrast, due to missing processes, the microphysics scheme decreased performances in phase estimate and SWE simulations compared to the upper benchmark. These results highlight the need for detailed evaluation of the precipitation phase from atmospheric models and the benefit for mountain snow hydrology of the post‐processed snow level. The limitations to drive snowpack models at slope scale are also discussed. , Plain Language Summary The partitioning of precipitation between rainfall and snowfall is a crucial component of the evolution of the snowpack in mountains. Most snowpack models use the air temperature and humidity near the surface to derive the precipitation phase. However, the phase at the surface is strongly influenced by processes such as melting and refreezing of falling hydrometeors that occur above the surface. Atmospheric models simulate these processes and the corresponding phase at the surface. However, snowpack models rarely use this information. In this study, we considered two estimates of precipitation phase from an atmospheric model and tested them with a physically‐based snow model over the mountains of southwestern Canada and northwestern United States. The results were compared with traditional approaches using the air temperature and humidity near the surface to derive the precipitation phase. Our results showed that the precipitation phase associated with the snow level obtained from the atmospheric model improved snowfall estimate and snowpack prediction compared to the traditional approaches. In contrast, the cloud/precipitation scheme of the atmospheric model decreased performance in phase estimate and snow simulations due to missing physical processes. Our study highlights that snowpack predictions in the mountains can be improved if valuable information is obtained from atmospheric models. , Key Points Estimates of precipitation phase from an atmospheric model were used to drive snow simulations with a detailed snowpack model Snowfall prediction and snowpack modeling are improved by using the snow level from post‐processing of the atmospheric model Direct precipitation phase from the microphysics scheme does not improve snow simulations compared to simpler rain‐snow partitioning schemes

Storms and Precipitation Across the continental Divide Experiment (SPADE) - Thériault, Julie M.; Leroux, Nicolas R.; Stewart, Ronald E.; Bertoncini, André; Déry, Stephen J.; Pomeroy, John W.; Thompson, Hadleigh D.; Smith, Hilary; Mariani, Zen; Desroches-Lapointe, Aurélie; Mitchell, Selina; Almonte, Juris (Bulletin of the American Meteorological Society, 2022)
Abstract The Canadian Rockies are a triple-continental divide, whose high mountains are drained by major snow-fed and rain-fed rivers flowing to the Pacific, Atlantic, and Arctic Oceans. The objective of the April–June 2019 Storms and Precipitation Across the continental Divide Experiment (SPADE) was to determine the atmospheric processes producing precipitation on the eastern and western sides of the Canadian Rockies during springtime, a period when upslope events of variable phase dominate precipitation on the eastern slopes. To do so, three observing sites across the divide were instrumented with advanced meteorological sensors. During the 13 observed events, the western side recorded only 25% of the eastern side’s precipitation accumulation, rainfall occurred rather than snowfall, and skies were mainly clear. Moisture sources and amounts varied markedly between events. An atmospheric river landfall in California led to moisture flowing persistently northward and producing the longest duration of precipitation on both sides of the divide. Moisture from the continental interior always produced precipitation on the eastern side but only in specific conditions on the western side. Mainly slow-falling ice crystals, sometimes rimed, formed at higher elevations on the eastern side (>3 km MSL), were lifted, and subsequently drifted westward over the divide during nonconvective storms to produce rain at the surface on the western side. Overall, precipitation generally crossed the divide in the Canadian Rockies during specific spring-storm atmospheric conditions although amounts at the surface varied with elevation, condensate type, and local and large-scale flow fields.

Changes in freezing rain occurrence over eastern Canada using convection-permitting climate simulations - Marinier, Sébastien; Thériault, Julie M.; Ikeda, Kyoko (Climate Dynamics, 2023)
Abstract Freezing precipitation has major consequences for ground and air transportation, the health of citizens, and power networks. Previous studies using coarse resolution climate models have shown a northward migration of freezing rain in the future. Increased model resolution can better define local topography leading to improved representation of conditions that are favorable for freezing rain. The goal of this study is to examine the climatology and characteristics of future freezing rain events using very-high resolution climate simulations. Historical and pseudo-global warming simulations with a 4-km horizontal grid length were used and compared with available observations. Simulations revealed a northerly shift of freezing rain occurrence, and an increase in the winter. Freezing rain was still shown to occur in the Saint-Lawrence River Valley in a warmer climate, primarily due to stronger wind channeling. Up to 50% of the future freezing rain events also occurred in present day climate within 12 h of each other. In northern Maine, they are typically shorter than 6 h in current climate and longer than 6 h in warmer conditions due to the onset of precipitation during low-pressure systems occurrences. The occurrence of freezing rain also locally increases slightly north of Québec City in a warmer climate because of freezing rain that is produced by warm rain processes. Overall, the study shows that high-resolution regional climate simulations are needed to study freezing rain events in warmer climate conditions, because high horizontal resolutions better define small-scale topographic features and local physical mechanisms that have an influence on these events.

The Occurrence of Near‐0°C Surface Air Temperatures in the Current and Pseudo‐Global Warming Future Over Southern Canada - Stewart, R. E.; Liu, Z.; Thériault, J. M.; Ruman, C. J. (Journal of Geophysical Research: Atmospheres, 2023)
Abstract Temperatures near 0°C represent a critical threshold for many environmental processes and socio‐economic activities. This study examines surface air temperatures ( T ) near 0°C (−2°C ≤ T ≤ 2°C) across much of southern Canada over a 13 year period (October 2000–September 2013). It utilized hourly data from 39 weather stations and from 4‐km resolution Weather Research and Forecasting model simulations that were both a retrospective simulation as well as a pseudo‐global warming simulation applicable near the end of the 21st century. Average annual occurrences of near‐0°C conditions increase by a relatively small amount of 5.1% from 985 hr in the current climate to 1,035 hr within the future one. Near‐0°C occurrences with precipitation vary from <5% to approximately 50% of these values. Near‐0°C occurrences are sometimes higher than values of neighboring temperatures. These near‐0°C peaks in temperature distributions can occur in both the current and future climate, in only one, or in neither. Only 4.3% of southern Canada is not associated with a near‐0°C peak and 65.8% is associated with a near‐0°C peak in both climates. It is inferred that latent heat exchanges from the melting and freezing of, for example, precipitation and the snowpack contribute significantly to some of these findings. , Plain Language Summary Our changing climate is spurring the development of huge efforts to improve resiliency. For many regions of the world, these efforts must account for potential changes in near‐0°C conditions within which both melting and freezing can occur and the accompanying latent heat exchanges can push air temperature toward 0°C. This article focuses on the occurrence of near‐0°C surface temperatures across southern Canada through an examination of observational and model information including projections in a future warmer (average 6.1°C increase) climate near the end of the 21st century. Average annual occurrences of near‐0°C conditions increase by a relatively small amount of 5.1% in the future climate and highest values continue to be along the Pacific coast or within the Western Cordillera and lowest values continue to be within central and northern areas. Near‐0°C occurrences are often higher than those of neighboring temperatures in the present climate and some of these elevated occurrences persist into the future one despite dramatic warming. It is inferred that latent heat exchanges from the melting and freezing of precipitation and snowcover contribute to these findings. , Key Points Near‐0°C surface air temperatures were examined over southern Canada using retrospective and pseudo‐global warming simulations Overall average occurrences increase slightly and their spatial patterns are largely maintained in the warmer climate Near‐0°C occurrences sometimes exceed those of neighboring temperatures and this feature often persists despite dramatic warming

Adhering Solid Precipitation in the Current and Pseudo-Global Warming Future Climate over the Canadian Provinces of Manitoba and Saskatchewan - Stewart, Ronald; Liu, Zhuo; Painchaud-Niemi, Dylan; Hanesiak, John; Thériault, Julie M. (Atmosphere, 2023)
Solid precipitation falling near 0 °C, mainly snow, can adhere to surface features and produce major impacts. This study is concerned with characterizing this precipitation over the Canadian Prairie provinces of Manitoba and Saskatchewan in the current (2000–2013) and pseudo-global warming future climate, with an average 5.9 °C temperature increase, through the use of high resolution (4 km) model simulations. On average, simulations in the current climate suggest that this precipitation occurs within 11 events per year, lasting 33.6 h in total and producing 27.5 mm melted equivalent, but there are wide spatial variations that are partly due to enhancements arising from its relatively low terrain. Within the warmer climate, average values generally increase, and spatial patterns shift somewhat. This precipitation consists of four categories covering its occurrence just below and just above a wet-bulb temperature of 0 °C, and with or without liquid precipitation. It generally peaks in March or April, as well as in October, and these peaks move towards mid-winter by approximately one month within the warmer climate. Storms producing this precipitation generally produce winds with a northerly component during or shortly after the precipitation; these winds contribute to further damage. Overall, this study has determined the features of and expected changes to adhering precipitation across this region.

Atmospheric and surface observations during the Saint John River Experiment on Cold Season Storms (SAJESS) - Thompson, Hadleigh D.; Thériault, Julie M.; Déry, Stephen J.; Stewart, Ronald E.; Boisvert, Dominique; Rickard, Lisa; Leroux, Nicolas R.; Colli, Matteo; Vionnet, Vincent (Earth System Science Data, 2023)
Abstract. The amount and the phase of cold-season precipitation accumulating in the upper Saint John River (SJR) basin are critical factors in determining spring runoff, ice jams, and flooding. To study the impact of winter and spring storms on the snowpack in the upper SJR basin, the Saint John River Experiment on Cold Season Storms (SAJESS) was conducted during winter–spring 2020–2021. Here, we provide an overview of the SAJESS study area, field campaign, and data collected. The upper SJR basin represents 41 % of the entire SJR watershed and encompasses parts of the US state of Maine and the Canadian provinces of Quebec and New Brunswick. In early December 2020, meteorological instruments were co-located with an Environment and Climate Change Canada station near Edmundston, New Brunswick. This included a separate weather station for measuring standard meteorological variables, an optical disdrometer, and a micro rain radar. This instrumentation was augmented during an intensive observation period that also included upper-air soundings, surface weather observations, a multi-angle snowflake camera, and macrophotography of solid hydrometeors throughout March and April 2021. During the study, the region experienced a lower-than-average snowpack that peaked at ∼ 65 cm, with a total of 287 mm of precipitation (liquid-equivalent) falling between December 2020 and April 2021, a 21 % lower amount of precipitation than the climatological normal. Observers were present for 13 storms during which they conducted 183 h of precipitation observations and took more than 4000 images of hydrometeors. The inclusion of local volunteers and schools provided an additional 1700 measurements of precipitation amounts across the area. The resulting datasets are publicly available from the Federated Research Data Repository at https://doi.org/10.20383/103.0591 (Thompson et al., 2023). We also include a synopsis of the data management plan and a brief assessment of the rewards and challenges of conducting the field campaign and utilizing community volunteers for citizen science.

P-Type Processes and Predictability: The Winter Precipitation Type Research Multiscale Experiment (WINTRE-MIX) - Minder, Justin R.; Bassill, Nick; Fabry, Frédéric; French, Jeffrey R.; Friedrich, Katja; Gultepe, Ismail; Gyakum, John; Kingsmill, David E.; Kosiba, Karen; Lachapelle, Mathieu; Michelson, Daniel; Nichman, Leonid; et al. (Bulletin of the American Meteorological Society, 2023)
Abstract During near-0°C surface conditions, diverse precipitation types (p-types) are possible, including rain, drizzle, freezing rain, freezing drizzle, ice pellets, wet snow, snow, and snow pellets. Near-0°C precipitation affects wide swaths of the United States and Canada, impacting aviation, road transportation, power generation and distribution, winter recreation, ecology, and hydrology. Fundamental challenges remain in observing, diagnosing, simulating, and forecasting near-0°C p-types, particularly during transitions and within complex terrain. Motivated by these challenges, the field phase of the Winter Precipitation Type Research Multiscale Experiment (WINTRE-MIX) was conducted from 1 February to 15 March 2022 to better understand how multiscale processes influence the variability and predictability of p-type and amount under near-0°C surface conditions. WINTRE-MIX took place near the U.S.–Canadian border, in northern New York and southern Quebec, a region with plentiful near-0°C precipitation influenced by terrain. During WINTRE-MIX, existing advanced mesonets in New York and Quebec were complemented by deployment of 1) surface instruments, 2) the National Research Council Convair-580 research aircraft with W- and X-band Doppler radars and in situ cloud and aerosol instrumentation, 3) two X-band dual-polarization Doppler radars and a C-band dual-polarization Doppler radar from the University of Illinois, and 4) teams collecting manual hydrometeor observations and radiosonde measurements. Eleven intensive observing periods (IOPs) were coordinated. Analysis of these WINTRE-MIX IOPs is illuminating how synoptic dynamics, mesoscale dynamics, and microscale processes combine to determine p-type and its predictability under near-0°C conditions. WINTRE-MIX research will contribute to improving nowcasts and forecasts of near-0°C precipitation through evaluation and refinement of observational diagnostics and numerical forecast models.

Characteristics of Rain-Snow Transitions Over the Canadian Rockies and their Changes in Warmer Climate Conditions - Thériault, Julie M.; Leroux, Nicolas R.; Tchuem Tchuente, Obert; Stewart, Ronald E. (Atmosphere-Ocean, 2023)

Impact of Adjusted and Nonadjusted Surface Observations on the Cold Season Performance of the Canadian Precipitation Analysis (CaPA) System - Feng, Pei-Ning; Bélair, Stéphane; Khedhaouiria, Dikraa; Lespinas, Franck; Mekis, Eva; Thériault, Julie M. (Journal of Hydrometeorology, 2024)
Abstract The Canadian Precipitation Analysis System (CaPA) is an operational system that uses a combination of weather gauge and ground-based radar measurements together with short-term forecasts from a numerical weather model to provide near-real-time estimates of 6- and 24-h precipitation amounts. During the winter season, many gauge measurements are rejected by the CaPA quality control process because of the wind-induced undercatch for solid precipitation. The goal of this study is to improve the precipitation estimates over central Canada during the winter seasons from 2019 to 2022. Two approaches were tested. First, the quality control procedure in CaPA has been relaxed to increase the number of surface observations assimilated. Second, the automatic solid precipitation measurements were adjusted using a universal transfer function to compensate for the undercatch problem. Although increasing the wind speed threshold resulted in lower amounts and worse biases in frequency, the overall precipitation estimates are improved as the equitable threat score is improved because of a substantial decrease in the false alarm ratio, which compensates the degradation of the probability of detection. The increase of solid precipitation amounts using a transfer function improves the biases in both frequency and amounts and the probability of detection for all precipitation thresholds. However, the false alarm ratio deteriorates for large thresholds. The statistics vary from year to year, but an overall improvement is demonstrated by increasing the number of stations and adjusting the solid precipitation amounts for wind speed undercatch.

Climatology of and Factors Contributing to Occurrences of Near-0°C Temperatures and Associated Precipitation At and Near Terrace, British Columbia, Canada - Cardinal, Émile; Thériault, Julie M.; Stewart, Ronald E.; Thompson, Hadleigh D.; Déry, Stephen J. (Atmosphere-Ocean, 2024)

Performance of precipitation phase partitioning methods and their impact on snowpack evolution in a humid continental climate - Leroux, Nicolas R.; Vionnet, Vincent; Thériault, Julie M. (Hydrological Processes, 2023)
Abstract Accurate estimations of the precipitation phase at the surface are critical for hydrological and snowpack modelling in cold regions. Precipitation phase partitioning methods (PPMs) vary in their ability to estimate the precipitation phase at around 0°C and can significantly impact simulations of snowpack accumulation and melt. The goal of this study is to evaluate PPMs of varying complexity using high‐quality observations of precipitation phase and to assess the impact on snowpack simulations. We used meteorological data collected in Edmundston, New Brunswick, Canada, during the 2021 Saint John River Experiment on Cold Season Storms (SAJESS). These data were combined with manual observations of snow depth. Five PPMs commonly used in hydrological models were tested against observations from a laser‐optical disdrometer and a Micro Rain Radar. Most PPMs produced similar accuracy in estimating only rainfall and snowfall. Mixed precipitation was the most difficult phase to predict. The multi‐physics model Crocus was then used to simulate snowpack evolution and to diagnose model sensitivity to snowpack accumulation processes (PPM, snowfall density, and snowpack compaction). Sixteen snowpack accumulation periods, including nine warm accumulation events (average temperatures above −2°C) were observed during the study period. When considering all accumulation events, simulated changes in snow water equivalent ( SWE ) were more sensitive to the type of PPM used, whereas simulated changes in snow depth were more sensitive to uncertainties in snowfall density. Choice of PPM was the main source of model sensitivity for changes in SWE and snow depth when only considering warm events. Overall, this study highlights the impact of precipitation phase estimations on snowpack accumulation at the surface during near‐0°C conditions.

Measuring Ice Pellets and Refrozen Wet Snow Using a Laser-Optical Disdrometer - Lachapelle, Mathieu; Thompson, Hadleigh D.; Leroux, Nicolas R.; Thériault, Julie M. (Journal of Applied Meteorology and Climatology, 2024)
Abstract This study aims to characterize the shapes and fall speeds of ice pellets formed in various atmospheric conditions and to investigate the possibility to use a laser-optical disdrometer to distinguish between ice pellets and other types of precipitation. To do so, four ice pellet events were documented using manual observations, macrophotography, and laser-optical disdrometer data. First, various ice pellet fall speeds and shapes, including spherical, bulged, fractured, and irregular particles, were associated with distinct atmospheric conditions. A higher fraction of bulged and fractured ice pellets was observed when solid precipitation was completely melted aloft while more irregular particles were observed during partial melting. These characteristics affected the diameter–fall speed relations measured. Second, the measurements of particles’ fall speed and diameter show that ice pellets could be differentiated from rain or freezing rain. Ice pellets larger than 1.5 mm tend to fall > 0.5 m s −1 slower than raindrops of the same size. In addition, the fall speed of a small fraction of ice pellets was < 2 m s −1 regardless of their size, as compared with a fall speed > 3 m s −1 for ice pellets with diameter > 1.5 mm. Video analysis suggests that these slower particles could be ice pellets passing through the laser-optical disdrometer after colliding with the head of the instrument. Overall, these findings contribute to a better understanding of the microphysics of ice pellets and their measurement using a laser-optical disdrometer. Significance Statement Ice pellets are challenging to forecast and to detect automatically. In this study, we documented the fall speed and physical characteristics of ice pellets during various atmospheric conditions using a combination of a laser-optical disdrometer, manual observations, and macrophotography images. Relationships were found between the shape and fall speed of ice pellets. These findings could be used to refine the parameterization of ice pellets in atmospheric models and, consequently, improve the forecast of impactful winter precipitation types such as freezing rain. Furthermore, they will also help to physically interpret laser-optical disdrometer data during ice pellets and freezing rain.

Effect of Secondary Ice Production Processes on the Simulation of ice pellets using the Predicted Particle Properties microphysics scheme - Lachapelle, Mathieu; Cholette, Mélissa; Thériault, Julie M. (Clouds and Precipitation/Atmospheric Modelling and Data Analysis/Troposphere/Physics (physical properties and processes), 2024)
Abstract. Ice pellets can form when supercooled raindrops collide with small ice particles that can be generated through secondary ice production processes. The use of atmospheric models that neglect these collisions can lead to an overestimation of freezing rain. The objective of this study is therefore to understand the impacts of collisional freezing and secondary ice production on simulations of ice pellets and freezing rain. We studied the properties of precipitation simulated with the microphysical scheme Predicted Particle Properties (P3) for two distinct secondary ice production processes. Possible improvements to the representation of ice pellets and ice crystals in P3 were analyzed by simulating an ice pellet storm that occurred over eastern Canada in January 2020. Those simulations showed that adding secondary ice production processes increased the accumulation of ice pellets but led to unrealistic size distributions of precipitation particles. Realistic size distributions of ice pellets were obtained by modifying the collection of rain by small ice particles and the merging criteria of ice categories in P3.

Leveraging a Disdrometer Network to Develop a Probabilistic Precipitation Phase Model in Eastern Canada - Bédard-Therrien, Alexis; Anctil, François; Thériault, Julie M.; Chalifour, Olivier; Payette, Fanny; Vidal, Alexandre; Nadeau, Daniel F. (Hydrometeorology/Modelling approaches, 2024)
Abstract. This study presents a probabilistic model that partitions the precipitation phase based on hourly measurements from a network of radar-based disdrometers in eastern Canada. The network consists of 27 meteorological stations located in a boreal climate for the years 2020–2023. Precipitation phase observations showed a 2-m air temperature interval between 0–4 °C where probabilities of occurrence of solid, liquid, or mixed precipitation significantly overlapped. Single-phase precipitation was also found to occur more frequently than mixed-phase precipitation. Probabilistic phase-guided partitioning (PGP) models of increasing complexity using random forest algorithms were developed. The PGP models classified the precipitation phase and partitioned the precipitation accordingly into solid and liquid amounts. PGP_basic is based on 2-m air temperature and site elevation, while PGP_hydromet integrates relative humidity. PGP_full includes all the above data plus atmospheric reanalysis data. The PGP models were compared to benchmark precipitation phase partitioning methods. These included a single temperature threshold model set at 1.5 °C, a linear transition model with dual temperature thresholds of –0.38 and 5 °C, and a psychrometric balance model. Among the benchmark models, the single temperature threshold had the best classification performance (F1 score of 0.74) due to a low count of mixed-phase events. The other benchmark models tended to over-predict mixed-phase precipitation in order to decrease partitioning error. All PGP models showed significant phase classification improvement by reproducing the observed overlapping precipitation phases based on 2-m air temperature. PGP_hydromet and PGP_full displayed the best classification performance (F1 score of 0.84). In terms of partitioning error, PGP_full had the lowest RMSE (0.27 mm) and the least variability in performance. The RMSE of the single temperature threshold model was the highest (0.40 mm) and showed the greatest performance variability. An input variable importance analysis revealed that the additional data used in the more complex PGP models mainly improved mixed-phase precipitation prediction. The improvement of mixed-phase prediction remains a challenge. Relative humidity was deemed the least important input variable used, due to consistent near water vapor saturation conditions. Additionally, the reanalysis atmospheric data proved to be an important factor to increase the robustness of the partitioning process. This study establishes a basis for integrating automated phase observations into a hydrometeorological observation network and developing probabilistic precipitation phase models.

A New GPM-DPR Algorithm to Estimate Snowfall in Mountain Regions - Bertoncini, André; Pomeroy, John W; Thériault, Julie M. (Preprints, 2024)
Reliable precipitation forcing is essential for calculating the water balance, seasonal snowpack, glacier mass balance, streamflow, and other hydrological variables. However, satellite precipitation is often the only forcing available to run hydrological models in data-scarce regions, compromising hydrological calculations when unreliable. The IMERG product estimates precipitation quasi-globally from a combination of passive microwave and infrared satellites, which are intercalibrated based on GPM’s DPR and GMI instruments. Current GPM-DPR radar algorithms have satisfactorily estimated rainfall, but a limited consideration of PSD, attenuation correction, and ground clutter have degraded snowfall estimation, especially in mountain regions. This study aims to improve satellite radar snowfall estimates for this situation. Nearly two years (between 2019 and 2022) of aloft precipitation concentration, surface hydrometeor size, number and fall velocity, and surface precipitation rate from a high elevation site in the Canadian Rockies and collocated GPM-DPR reflectivities were used to develop a new snowfall estimation algorithm. Snowfall estimates using the new algorithm and measured GPM-DPR reflectivities were compared to other GPM-DPR-based products, including CORRA, which is employed to intercalibrate IMERG. Snowfall rates estimated with measured Ka reflectivities, and from CORRA were compared to MRR-2 observations, and had correlation, bias, and RMSE of 0.58 and 0.07, 0.43 and -0.38 mm h-1, and 0.83 and 0.85 mm h-1, respectively. Predictions using measured Ka reflectivity suggest that enhanced satellite radar snowfall estimates can be achieved using a simple measured reflectivity algorithm. These improved snowfall estimates can be adopted to intercalibrate IMERG in cold mountain regions, thereby improving regional precipitation estimates.

Impact of Assimilating Radar Solid Precipitation Data in the Canadian Precipitation Analysis System - Beaudry, Florence L.; Bélair, Stéphane; Thériault, Julie M.; Khedhaouiria, Dikra; Lespinas, Franck; Michelson, Daniel; Feng, Pei-Ning; Aubry, Catherine (Journal of Hydrometeorology, 2024)
Abstract The Canadian Precipitation Analysis (CaPA) system provides near-real-time precipitation analyses over Canada by combining observations with short-term numerical weather prediction forecasts. CaPA’s snowfall estimates suffer from the lack of accurate solid precipitation measurements to correct the first-guess estimate. Weather radars have the potential to add precipitation measurements to CaPA in all seasons but are not assimilated in winter due to radar snowfall estimate imprecision and lack of precipitation gauges for calibration. The main objective of this study is to assess the impact of assimilating Canadian dual-polarized radar-based snowfall data in CaPA to improve precipitation estimates. Two sets of experiments were conducted to evaluate the impact of including radar snowfall retrievals, one set using the high-resolution CaPA (HRDPA) with the currently operational quality control configuration and another increasing the number of assimilated surface observations by relaxing quality control. Experiments spanned two winter seasons (2021 and 2022) in central Canada, covering part of the entire CaPA domain. The results showed that the assimilation of radar-based snowfall data improved CaPA’s precipitation estimates 81.75% of the time for 0.5-mm precipitation thresholds. An increase in the probability of detection together with a decrease in the false alarm ratio suggested an improvement of the precipitation spatial distribution and estimation accuracy. Additionally, the results showed improvements for both precipitation mass and frequency biases for low precipitation amounts. For larger thresholds, the frequency bias was degraded. The results also indicated that the assimilation of dual-polarization radar data is beneficial for the two CaPA configurations tested in this study.

Climatological context of the mid-November 2021 floods in the province of British Columbia, Canada - Richards-Thomas, Tamar S.; Déry, Stephen J.; Stewart, Ronald E.; Thériault, Julie M. (Weather and Climate Extremes, 2024)

IMERG in the Canadian Precipitation Analysis (CaPA) System for Winter Applications - Bélair, Stéphane; Feng, Pei-Ning; Lespinas, Franck; Khedhaouiria, Dikra; Hudak, David; Michelson, Daniel; Aubry, Catherine; Beaudry, Florence; Carrera, Marco L.; Thériault, Julie M. (Atmosphere, 2024)
Several configurations of the Canadian Precipitation Analysis system (CaPA) currently produce precipitation analyses at Environment and Climate Change Canada (ECCC). To improve CaPA’s performance during the winter season, the impact of assimilating the IMERG V06 product (IMERG: Integrated Multi-satellitE Retrievals for GPM—Global Precipitation Measurement mission) into CaPA is examined in this study. Tests are conducted with CaPA’s 10 km deterministic version, evaluated over Canada and the northern part of the United States (USA). Maps from a case study show that IMERG plays a contradictory role in the production of CaPA’s precipitation analyses for a synoptic-scale winter storm over North America’s eastern coast. While its contribution appears to be physically correct over southern portions of the meteorological system, and early in its intensification phase, IMERG displays unrealistic spatial structures over land later in the system’s life cycle when it is located over northern (colder) areas. Objective evaluation of CaPA’s analyses when IMERG is assimilated without any restrictions shows an overall decrease in precipitation, which has a mixed effect (positive and negative) on the bias indicators. But IMERG’s influence on the Equitable Threat Score (ETS), a measure of CaPA’s analyses accuracy, is clearly negative. Using IMERG’s quality index (QI) to filter out areas where it is less accurate improves CaPA’s objective evaluation, leading to better ETS versus the control experiment in which no IMERG data are assimilated. Several diagnostics provide insight into the nature of IMERG’s contribution to CaPA. For the most successful configuration, with a QI threshold of 0.3, IMERG’s impact is mostly found in the warmer parts of the domain, i.e., in northern US states and in British Columbia. Spatial means of the temporal sums of absolute differences between CaPA’s analyses with and without IMERG indicate that this product also contributes meaningfully over land areas covered by snow, and areas where air temperature is below −2 °C (where precipitation is assumed to be in solid phase).

Dynamical downscaling with the fifth-generation Canadian regional climate model (CRCM5) over the CORDEX Arctic domain: effect of large-scale spectral nudging and of empirical correction of sea-surface temperature - Takhsha, Maryam; Nikiéma, Oumarou; Lucas-Picher, Philippe; Laprise, René; Hernández-Díaz, Leticia; Winger, Katja (Climate Dynamics, 2018)

A metrics‐based analysis of seasonal daily precipitation and near‐surface temperature within seven Coordinated Regional Climate Downscaling Experiment domains - Glisan, Justin M.; Jones, Richard; Lennard, Chris; Castillo Pérez, Nadia I.; Lucas‐Picher, Philippe; Rinke, Annette; Solman, Silvina; Gutowski, William J. (Atmospheric Science Letters, 2019)
We compare ensemble mean daily precipitation and near‐surface temperatures from regional climate model simulations over seven Coordinated Regional Climate Downscaling Experiment domains for the winter and summer seasons. We use Taylor diagrams to show the domain‐wide pattern similarity between the model ensemble and the observational data sets. We use the Climatic Research Unit (CRU) and the University of Delaware gridded observations and ERA‐Interim reanalysis data as an additional observationally based estimate of historical climatology. Taylor diagrams determine the relative skill of the seven sets of simulations and quantify these results in terms of center pattern root‐mean square error and correlation coefficient. Results suggest that there is good agreement between the models and the CRU, in terms of their respective seasonal cycles, as shown in Taylor diagrams and bias plots. There is also good agreement between both gridded observation sets. In addition, downscaled ERA‐Interim precipitation is closer to observations than raw ERA‐Interim precipitation. Domains located in the low latitudes and those having high topography appear to have larger biases, especially precipitation.

Application of a High‐Resolution Distributed Hydrological Model on a U.S.‐Canada Transboundary Basin: Simulation of the Multiyear Mean AnnualHydrograph and 2011 Flood of theRichelieu River Basin - Lucas‐Picher, Philippe; Arsenault, Richard; Poulin, Annie; Ricard, Simon; Lachance‐Cloutier, Simon; Turcotte, Richard (Journal of Advances in Modeling Earth Systems, 2020)
Abstract During spring 2011, an extreme flood occurred along the Richelieu River located in southern Quebec, Canada. The Richelieu River is the last section of the complex Richelieu basin, which is composed of the large Lake Champlain located in a valley between two large mountains. Previous attempts in reproducing the Richelieu River flow relied on the use of simplified lumped models and showed mixed results. In order to prepare a tool to assess accurately the change of flood recurrences in the future, a state‐of‐the‐art distributed hydrological model was applied over the Richelieu basin. The model setup comprises several novel methods and data sets such as a very high resolution river network, a modern calibration technique considering the net basin supply of Lake Champlain, a new optimization algorithm, and the use of an up‐to‐date meteorological data set to force the model. The results show that the hydrological model is able to satisfactorily reproduce the multiyear mean annual hydrograph and the 2011 flow time series when compared with the observed river flow and an estimation of the Lake Champlain net basin supply. Many factors, such as the quality of the meteorological forcing data, that are affected by the low density of the station network, the steep terrain, and the lake storage effect challenged the simulation of the river flow. Overall, the satisfactory validation of the hydrological model allows to move to the next step, which consists in assessing the impacts of climate change on the recurrence of Richelieu River floods. , Plain Language Summary In order to study the 2011 Richelieu flood and prepare a tool capable of estimating the effects of climate change on the recurrence of floods, a hydrological model is applied over the Richelieu basin. The application of a distributed hydrological model is useful to simulate the flow of all the tributaries of the Richelieu basin. This new model setup stands out from past models due to its distribution in several hydrological units, its high‐resolution river network, the calibration technique, and the high‐resolution weather forcing data set used to drive the model. The model successfully reproduced the 2011 Richelieu River flood and the annual hydrograph. The simulation of the Richelieu flow was challenging due to the contrasted elevation of the Richelieu basin and the presence of the large Lake Champlain that acts as a reservoir and attenuates short‐term fluctuations. Overall, the application was deemed satisfactory, and the tool is ready to assess the impacts of climate change on the recurrence of Richelieu River floods. , Key Points An advanced high‐resolution distributed hydrological model is applied over a U.S.‐Canada transboundary basin The simulated net basin supply of Lake Champlain and the Richelieu River discharge are in good agreement with observations of the 2011 flood The flow simulation is challenging due to the topographic and meteorological complexities of the basin and uncertainties in the observations

Climate Change and Rainfall Intensity–Duration–Frequency Curves: Overview of Science and Guidelines for Adaptation - Martel, Jean-Luc; Brissette, François P.; Lucas-Picher, Philippe; Troin, Magali; Arsenault, Richard (Journal of Hydrologic Engineering, 2021)

Will Evolving Climate Conditions Increase the Risk of Floods of the Large U.S.‐Canada Transboundary Richelieu River Basin? - Lucas‐Picher, Philippe; Lachance‐Cloutier, Simon; Arsenault, Richard; Poulin, Annie; Ricard, Simon; Turcotte, Richard; Brissette, François (JAWRA Journal of the American Water Resources Association, 2021)
Abstract In spring 2011, an unprecedented flood hit the complex eastern United States (U.S.)–Canada transboundary Lake Champlain–Richelieu River (LCRR) Basin, destructing properties and inducing negative impacts on agriculture and fish habitats. The damages, covered by the Governments of Canada and the U.S., were estimated to C$90M. This natural disaster motivated the study of mitigation measures to prevent such disasters from reoccurring. When evaluating flood risks, long‐term evolving climate change should be taken into account to adopt mitigation measures that will remain relevant in the future. To assess the impacts of climate change on flood risks of the LCRR basin, three bias‐corrected multi‐resolution ensembles of climate projections for two greenhouse gas concentration scenarios were used to force a state‐of‐the‐art, high‐resolution, distributed hydrological model. The analysis of the hydrological simulations indicates that the 20‐year return period flood (corresponding to a medium flood) should decrease between 8% and 35% for the end of the 21st Century (2070–2099) time horizon and for the high‐emission scenario representative concentration pathway (RCP) 8.5. The reduction in flood risks is explained by a decrease in snow accumulation and an increase in evapotranspiration expected with the future warming of the region. Nevertheless, due to the large climate inter‐annual variability, short‐term flood probabilities should remain similar to those experienced in the recent past.

Impacts du changement climatique sur les pluies intenses et les crues en Méditerranée - Tramblay, Yves; Ribes, Aurélien; Somot, Samuel; Neppel, Luc; Lucas-Picher, Philippe; Vinet, Freddy; Sauquet, Eric (LHB, 2021)

Use of expert elicitation to assign weights to climate and hydrological models in climate impact studies - Sebok, Eva; Henriksen, Hans Jørgen; Pastén-Zapata, Ernesto; Berg, Peter; Thirel, Guillaume; Lemoine, Anthony; Lira-Loarca, Andrea; Photiadou, Christiana; Pimentel, Rafael; Royer-Gaspard, Paul; Kjellström, Erik; Christensen, Jens Hesselbjerg; et al. (Hydrology and Earth System Sciences, 2022)
Abstract. Various methods are available for assessing uncertainties in climate impact studies. Among such methods, model weighting by expert elicitation is a practical way to provide a weighted ensemble of models for specific real-world impacts. The aim is to decrease the influence of improbable models in the results and easing the decision-making process. In this study both climate and hydrological models are analysed, and the result of a research experiment is presented using model weighting with the participation of six climate model experts and six hydrological model experts. For the experiment, seven climate models are a priori selected from a larger EURO-CORDEX (Coordinated Regional Downscaling Experiment – European Domain) ensemble of climate models, and three different hydrological models are chosen for each of the three European river basins. The model weighting is based on qualitative evaluation by the experts for each of the selected models based on a training material that describes the overall model structure and literature about climate models and the performance of hydrological models for the present period. The expert elicitation process follows a three-stage approach, with two individual rounds of elicitation of probabilities and a final group consensus, where the experts are separated into two different community groups: a climate and a hydrological modeller group. The dialogue reveals that under the conditions of the study, most climate modellers prefer the equal weighting of ensemble members, whereas hydrological-impact modellers in general are more open for assigning weights to different models in a multi-model ensemble, based on model performance and model structure. Climate experts are more open to exclude models, if obviously flawed, than to put weights on selected models in a relatively small ensemble. The study shows that expert elicitation can be an efficient way to assign weights to different hydrological models and thereby reduce the uncertainty in climate impact. However, for the climate model ensemble, comprising seven models, the elicitation in the format of this study could only re-establish a uniform weight between climate models.

CMIP5 and CMIP6 Model Projection Comparison for Hydrological Impacts Over North America - Martel, J.‐L.; Brissette, F.; Troin, M.; Arsenault, R.; Chen, J.; Su, T.; Lucas‐Picher, P. (Geophysical Research Letters, 2022)
Abstract A warmer climate impacts streamflows and these changes need to be quantified to assess future risk, vulnerability, and to implement efficient adaptation measures. The climate simulations from the fifth phase of the Coupled Model Intercomparison Project (CMIP5), which have been the basis of most such assessments over the past decade, are being gradually superseded by the more recent Coupled Model Intercomparison Project Phase 6 (CMIP6). Our study portrays the added value of the CMIP6 ensemble over CMIP5 in a first North America wide comparison using 3,107 catchments. Results show a reduced spread of the CMIP6 ensemble compared to the CMIP5 ensemble for temperature and precipitation projections. In terms of flow indicators, the CMIP6 driven hydrological projections result in a smaller spread of future mean and high flow values, except for mountainous areas. Overall, we assess that the CMIP6 ensemble provides a narrower band of uncertainty of future climate projections, bringing more confidence for hydrological impact studies. , Plain Language Summary Greenhouse gas emissions are causing the climate to warm significantly, which in turn impacts flows in rivers worldwide. To adapt to these changes, it is essential to quantify them and assess future risk and vulnerability. Climate models are the primary tools used to achieve this. The main data set that provides scientists with state‐of‐the‐art climate model simulations is known as the Coupled Model Intercomparison Project (CMIP). The fifth phase of that project (CMIP5) has been used over the past decade in multiple hydrological studies to assess the impacts of climate change on streamflow. The more recent sixth phase (CMIP6) has started to generate projections, which brings the following question: is it necessary to update the hydrological impact studies performed using CMIP5 with the new CMIP6 models? To answer this question, a comparison between CMIP5 and CMIP6 using 3,107 catchments over North America was conducted. Results show that there is less spread in temperature and precipitation projections for CMIP6. This translates into a smaller spread of future mean, high and low flow values, except for mountainous areas. Overall, we assess that using the CMIP6 data set would provide a more concerted range of future climate projections, leading to more confident hydrological impact studies. , Key Points A comparison of hydrological impacts using Coupled Model Intercomparison Project version 5 (CMIP5) and Coupled Model Intercomparison Project Phase 6 (CMIP6) ensembles is performed over 3,107 catchments in North America The CMIP6 ensembles provide a narrower band of uncertainty for hydrological indicators in the future It is recommended to update hydrological impact studies performed using CMIP5 with the CMIP6 ensemble

Evaluation of the convection-permitting regional climate model CNRM-AROME41t1 over Northwestern Europe - Lucas-Picher, Philippe; Brisson, E.; Caillaud, C.; Alias, A.; Nabat, P.; Lemonsu, A.; Poncet, N.; Cortés Hernandez, V. E.; Michau, Y.; Doury, A.; Monteiro, D.; Somot, S. (Climate Dynamics, 2024)
Abstract Since a decade, convection-permitting regional climate models (CPRCM) have emerged showing promising results, especially in improving the simulation of precipitation extremes. In this article, the CPRCM CNRM-AROME developed at the Centre National de Recherches Météorologiques (CNRM) since a few years is described and evaluated using a 2.5-km 19-year long hindcast simulation over a large northwestern European domain using different observations through an added-value analysis in which a comparison with its driving 12-km RCM CNRM-ALADIN is performed. The evaluation is challenging due to the lack of high-quality observations at both high temporal and spatial resolutions. Thus, a high spatio-temporal observed gridded precipitation dataset was built from the collection of seven national datasets that helped the identification of added value in CNRM-AROME. The evaluation is based on a series of standard climatic features that include long-term means and mean annual cycles of precipitation and near-surface temperature where CNRM-AROME shows little improvements compared to CNRM-ALADIN. Additional indicators such as the summer diurnal cycle and indices of extreme precipitation show, on the contrary, a more realistic behaviour of the CNRM-AROME model. Moreover, the analysis of snow cover shows a clear added-value in the CNRM-AROME simulation, principally due to the improved description of the orography with the CPRCM high resolution. Additional analyses include the evaluation of incoming shortwave radiation, and cloud cover using satellite estimates. Overall, despite some systematic biases, the evaluation indicates that CNRM-AROME is a suitable CPRCM that is superior in many aspects to the RCM CNRM-ALADIN.

Evaluation of the Urban Heat Island of 12 cities of France in a high-resolution regional climate model simulation - Michau, Y.; Lemonsu, A.; Lucas-Picher, P.; Caillaud, C. (Urban Climate, 2023)

What added value of CNRM-AROME convection-permitting regional climate model compared to CNRM-ALADIN regional climate model for urban climate studies ? Evaluation over Paris area (France) - Lemonsu, A.; Caillaud, C.; Alias, A.; Riette, S.; Seity, Y.; Le Roy, B.; Michau, Y.; Lucas-Picher, P. (Climate Dynamics, 2023)

Producing reliable hydrologic scenarios from raw climate model outputs without resorting to meteorological observations - Ricard, Simon; Lucas-Picher, Philippe; Thiboult, Antoine; Anctil, François (Hydrology and Earth System Sciences, 2023)
Abstract. A simplified hydroclimatic modelling workflow is proposed to quantify the impact of climate change on water discharge without resorting to meteorological observations. This alternative approach is designed by combining asynchronous hydroclimatic modelling and quantile perturbation applied to streamflow observations. Calibration is run by forcing hydrologic models with raw climate model outputs using an objective function that excludes the day-to-day temporal correlation between simulated and observed hydrographs. The resulting hydrologic scenarios provide useful and reliable information considering that they (1) preserve trends and physical consistency between simulated climate variables, (2) are implemented from a modelling cascade despite observation scarcity, and (3) support the participation of end-users in producing and interpreting climate change impacts on water resources. The proposed modelling workflow is implemented over four sub-catchments of the Chaudière River, Canada, using nine North American Coordinated Regional Climate Downscaling Experiment (NA-CORDEX) simulations and a pool of lumped conceptual hydrologic models. Results confirm that the proposed workflow produces equivalent projections of the seasonal mean flows in comparison to a conventional hydroclimatic modelling approach. They also highlight the sensibility of the proposed workflow to strong biases affecting raw climate model outputs, frequently causing outlying projections of the hydrologic regime. Inappropriate forcing climate simulations were however successfully identified (and excluded) using the performance of the simulated hydrologic response as a ranking criterion. Results finally suggest that further works should be conducted to confirm the reliability of the proposed workflow to assess the impact of climate change on high- and low-flow events.

On the future evolution of heatwaves in French cities and associated rural areas: Insights from a convection-permitting model - Michau, Y.; Lemonsu, A.; Lucas-Picher, P.; Schneider, M.; Caillaud, C. (Urban Climate, 2024)

Does a convection-permitting regional climate model bring new perspectives on the projection of Mediterranean floods? - Poncet, Nils; Lucas-Picher, Philippe; Tramblay, Yves; Thirel, Guillaume; Vergara, Humberto; Gourley, Jonathan; Alias, Antoinette (Natural Hazards and Earth System Sciences, 2024)
Abstract. Floods are the primary natural hazard in the French Mediterranean area, causing damages and fatalities every year. These floods are triggered by heavy precipitation events (HPEs) characterized by limited temporal and spatial extents. A new generation of regional climate models at the kilometer scale have been developed, allowing an explicit representation of deep convection and improved simulations of local-scale phenomena such as HPEs. Convection-permitting regional climate models (CPMs) have been scarcely used in hydrological impact studies, and future projections of Mediterranean floods remain uncertain with regional climate models (RCMs). In this paper, we use the CNRM-AROME CPM (2.5 km) and its driving CNRM-ALADIN RCM (12 km) at the hourly timescale to simulate floods over the Gardon d'Anduze catchment located in the French Mediterranean region. Climate simulations are bias-corrected with the CDF-t method. Two hydrological models, a lumped and conceptual model (GR5H) and a process-based distributed model (CREST), forced with historical and future climate simulations from the CPM and from the RCM, have been used. The CPM model confirms its ability to better reproduce extreme hourly rainfall compared to the RCM. This added value is propagated on flood simulation with a better reproduction of flood peaks. Future projections are consistent between the hydrological models but differ between the two climate models. Using the CNRM-ALADIN RCM, the magnitude of all floods is projected to increase. With the CNRM-AROME CPM, a threshold effect is found: the magnitude of the largest floods is expected to intensify, while the magnitude of the less severe floods is expected to decrease. In addition, different flood event characteristics indicate that floods are expected to become flashier in a warmer climate, with shorter lag time between rainfall and runoff peak and a smaller contribution of base flow, regardless of the model. This study is a first step for impact studies driven by CPMs over the Mediterranean.

Evaluation of the convection permitting regional climate model CNRM-AROME on the orographically complex island of Corsica - Cortés-Hernández, Virginia Edith; Caillaud, Cécile; Bellon, Gilles; Brisson, Erwan; Alias, Antoinette; Lucas-Picher, Philippe (Climate Dynamics, 2024)
Abstract Meteorological processes over islands with complex orography could be better simulated by Convection Permitting Regional Climate Models (CP-RCMs) thanks to an improved representation of the orography, land–sea contrasts, the combination of coastal and orographic effects, and explicit deep convection. This paper evaluates the ability of the CP-RCM CNRM-AROME (2.5-km horizontal resolution) to simulate relevant meteorological characteristics of the Mediterranean island of Corsica for the 2000–2018 period. These hindcast simulations are compared to their driving Regional Climate Model (RCM) CNRM-ALADIN (12.5-km horizontal resolution and parameterised convection), weather stations for precipitation and wind and gridded precipitation datasets. The main benefits are found in the representation of (i) precipitation extremes resulting mainly from mesoscale convective systems affected by steep mountains during autumn and (ii) the formation of convection through thermally induced diurnal circulations and their interaction with the orography during summer. Simulations of hourly precipitation extremes, the diurnal cycle of precipitation, the distribution of precipitation intensities, the duration of precipitation events, and sea breezes are all improved in the 2.5-km simulations with respect to the RCM, confirming an added value. However, existing differences between model simulations and observations are difficult to explain as the main biases are related to the availability and quality of observations, particularly at high elevations. Overall, better results from the 2.5-km resolution, increase our confidence in CP-RCMs to investigate future climate projections for Corsica and islands with complex terrain.

Quintessentially flat scalar potentials - Burgess, C P; Grenier, P; Hoover, D (Journal of Cosmology and Astroparticle Physics, 2004)

A Decade of Climate Scenarios: The Ouranos Consortium Modus Operandi - Huard, David; Chaumont, Diane; Logan, Travis; Sottile, Marie-France; Brown, Ross D.; St-Denis, Blaise Gauvin; Grenier, Patrick; Braun, Marco (Bulletin of the American Meteorological Society, 2014)

Quantifying Vulnerability to Extreme Heat in Time Series Analyses: A Novel Approach Applied to Neighborhood Social Disparities under Climate Change - Benmarhnia, Tarik; Grenier, Patrick; Brand, Allan; Fournier, Michel; Deguen, Séverine; Smargiassi, Audrey (International Journal of Environmental Research and Public Health, 2015)
Objectives: We propose a novel approach to examine vulnerability in the relationship between heat and years of life lost and apply to neighborhood social disparities in Montreal and Paris. Methods: We used historical data from the summers of 1990 through 2007 for Montreal and from 2004 through 2009 for Paris to estimate daily years of life lost social disparities (DYLLD), summarizing social inequalities across groups. We used Generalized Linear Models to separately estimate relative risks (RR) for DYLLD in association with daily mean temperatures in both cities. We used 30 climate scenarios of daily mean temperature to estimate future temperature distributions (2021–2050). We performed random effect meta-analyses to assess the impact of climate change by climate scenario for each city and compared the impact of climate change for the two cities using a meta-regression analysis. Results: We show that an increase in ambient temperature leads to an increase in social disparities in daily years of life lost. The impact of climate change on DYLLD attributable to temperature was of 2.06 (95% CI: 1.90, 2.25) in Montreal and 1.77 (95% CI: 1.61, 1.94) in Paris. The city explained a difference of 0.31 (95% CI: 0.14, 0.49) on the impact of climate change. Conclusion: We propose a new analytical approach for estimating vulnerability in the relationship between heat and health. Our results suggest that in Paris and Montreal, health disparities related to heat impacts exist today and will increase in the future.

Toward daily climate scenarios for Canadian Arctic coastal zones with more realistic temperature‐precipitation interdependence - Gennaretti, Fabio; Sangelantoni, Lorenzo; Grenier, Patrick (Journal of Geophysical Research: Atmospheres, 2015)
Abstract The interdependence between climatic variables should be taken into account when developing climate scenarios. For example, temperature‐precipitation interdependence in the Arctic is strong and impacts on other physical characteristics, such as the extent and duration of snow cover. However, this interdependence is often misrepresented in climate simulations. Here we use two two‐dimensional (2‐D) methods for statistically adjusting climate model simulations to develop plausible local daily temperature ( T mean ) and precipitation ( Pr ) scenarios. The first 2‐D method is based on empirical quantile mapping (2Dqm) and the second on parametric copula models (2Dcopula). Both methods are improved here by forcing the preservation of the modeled long‐term warming trend and by using moving windows to obtain an adjustment specific to each day of the year. These methods were applied to a representative ensemble of 13 global climate model simulations at 26 Canadian Arctic coastal sites and tested using an innovative cross‐validation approach. Intervariable dependence was evaluated using correlation coefficients and empirical copula density plots. Results show that these 2‐D methods, especially 2Dqm, adjust individual distributions of climatic time series as adequately as one common one‐dimensional method (1Dqm) does. Furthermore, although 2Dqm outperforms the other methods in reproducing the observed temperature‐precipitation interdependence over the calibration period, both 2Dqm and 2Dcopula perform similarly over the validation periods. For cases where temperature‐precipitation interdependence is important (e.g., characterizing extreme events and the extent and duration of snow cover), both 2‐D methods are good options for producing plausible local climate scenarios in Canadian Arctic coastal zones. , Key Points We improved two methods for adjusting T mean , Pr , and their dependence in scenarios Methods are tested at Arctic coastal sites where T mean ‐ Pr dependence is crucial Both methods improve the plausibility of the local climate scenarios

Partitioning prediction uncertainty in climate-dependent population models - Gauthier, Gilles; Péron, Guillaume; Lebreton, Jean-Dominique; Grenier, Patrick; Van Oudenhove, Louise (Proceedings of the Royal Society B: Biological Sciences, 2016)
The science of complex systems is increasingly asked to forecast the consequences of climate change. As a result, scientists are now engaged in making predictions about an uncertain future, which entails the efficient communication of this uncertainty. Here we show the benefits of hierarchically decomposing the uncertainty in predicted changes in animal population size into its components due to structural uncertainty in climate scenarios (greenhouse gas emissions and global circulation models), structural uncertainty in the demographic model, climatic stochasticity, environmental stochasticity unexplained by climate–demographic trait relationships, and sampling variance in demographic parameter estimates. We quantify components of uncertainty surrounding the future abundance of a migratory bird, the greater snow goose ( Chen caeruslescens atlantica ), using a process-based demographic model covering their full annual cycle. Our model predicts a slow population increase but with a large prediction uncertainty. As expected from theoretical variance decomposition rules, the contribution of sampling variance to prediction uncertainty rapidly overcomes that of process variance and dominates. Among the sources of process variance, uncertainty in the climate scenarios contributed less than 3% of the total prediction variance over a 40-year period, much less than environmental stochasticity. Our study exemplifies opportunities to improve the forecasting of complex systems using long-term studies and the challenges inherent to predicting the future of stochastic systems.

Probabilistic climate change scenarios for viticultural potential in Québec - Roy, Philippe; Grenier, Patrick; Barriault, Evelyne; Logan, Travis; Blondlot, Anne; Bourgeois, Gaétan; Chaumont, Diane (Climatic Change, 2017)

Impact of climate change on Ostrinia nubilalis (Lepidoptera: Crambidae) phenology and its implications on pest management - Gagnon, Annie‐Ève; Bourgeois, Gaétan; Bourdages, Line; Grenier, Patrick; Blondlot, Anne (Agricultural and Forest Entomology, 2019)
Abstract Climate change can cause negative impacts to the agricultural sector by increasing pest damage to crops. The European corn borer (ECB) is a major insect pest of corn in North America. Its speed of development could potentially accelerate under a warmer climate, leading to an earlier development of the first generation and an increase in the number of generations per year. The main objective of this study was to assess the potential impacts of climate change on ECB management for the future period 2041–2070 in Quebec, Canada, using bioclimatic modelling and climate analogues. First flight of ECB moths could occur about 15 days earlier in the season in 2041–2070 compared to the reference period 1970–1999. The window for insecticide interventions may be reduced under climate change by 15.6% to 27.8% for univoltine ECB and by 13.8% to 52.7% for bivoltine ECB. Climate change could promote the development of an additional generation in the southern region for both races, considering temperature increases and factors inducing the overwintering diapause. ECB management could become more costly both economically and environmentally under the future climate, and it should be revised according to the results of this study.

Characterizing and avoiding physical inconsistency generated by the application of univariate quantile mapping on daily minimum and maximum temperatures over Hudson Bay - Agbazo, Médard Noukpo; Grenier, Patrick (International Journal of Climatology, 2020)
Abstract Quantile mapping (QM) is a technique often used for statistical post‐processing (SPP) of climate model simulations, in order to adjust their biases relative to a selected reference product and/or to downscale their resolution. However, when QM is applied in univariate mode, there is a risk of generating other problems, like intervariable physical inconsistency (PI). Here, such a risk is investigated with daily temperature minimum ( T min ) and maximum ( T max ), for which the relationship T min > T max would be inconsistent with the definition of the variables. QM is applied to an ensemble of 78 daily CMIP5 simulations over Hudson Bay for the application period 1979–2100, with Climate Forecast System Reanalysis (CFSR) selected as the reference product during the calibration period 1979–2010. This study's specific objectives are as follows: to investigate the conditions under which PI situations are generated; to test whether PI may be prevented simply by tuning some of the QM technique's numerical choices; and to compare the suitability of alternative approaches that hinder PI by design. Primary results suggest that PI situations appear preferentially for small values of the initial (simulated) diurnal temperature range (DTR), but the differential between the respective biases of T min and T max also plays an important role; one cannot completely prevent the generation of PI simply by adjusting QM parameters and options, but forcing preservation of the simulated long‐term trends generates fewer PI situations; for avoiding PI between T min and T max , the present study supports a previous recommendation to directly post‐process T max and DTR before deducing T min .

Projected economic losses from milk performance detriments under heat stress in Quebec dairy herds - Ouellet, V.; Grenier, P.; Santschi, D.E.; Cabrera, V.E.; Fadul-Pacheco, L.; Charbonneau, É. (Canadian Journal of Animal Science, 2021)
The objective of this study was to estimate economic losses associated with milk performance detriments under different climate scenarios. A dataset containing milk records of Holstein and daily temperature–humidity indexes compiled over 6 yr in two contrasting climatic dairy regions of Quebec [eastern (EQ) and southwestern Quebec (SWQ)] was used to develop equations for modeling milk performance. Milk performance, including milk, fat, protein, and lactose yields of dairy herds (kg·d −1 ), were then projected considering six plausible climate scenarios during a climatic reference period (REF: 1971–2000) and two future periods (FUT1: 2020–2049; FUT2: 2050–2079). Economic losses were assessed by comparing future to reference milk prices based on components. Results indicated that fat and protein yields could decline in the future, thus resulting in economic losses ranging from $5.34 to $7.07 CAD·hL −1 in EQ and from $5.03 to $6.99 CAD·hL −1 in SWQ, depending on the amplitude of future temperature and humidity changes and on whether it is milk quota or cow number which is adjusted to avoid under-quota production. The projected increase in occurrence and duration of heat stress episodes under climate change could result in substantial financial harm for producers, thereby reinforcing the necessity of implementing heat-abatement strategies on dairy farms.

Modeled performance of forage mixtures and annual crops grown in eastern Canada under climate change - Payant, Camille; Jégo, Guillaume; Ouellet, Véronique; Grenier, Patrick; Tremblay, Gaëtan F.; Bélanger, Gilles; Charbonneau, Édith (Agronomy Journal, 2021)
Abstract Timothy ( Phleum pratense L.) is expected to be more affected by climate change than other forage grasses. Therefore, alternatives to timothy, such as tall fescue [ Schedonorus arundinaceus (Shreb.) Dumort.], meadow fescue [ S. pratensis (Huds.) P. Beauv.], or meadow bromegrass ( Bromus biebersteinii Roem. & Schult.) should be explored. Our objective was to simulate and compare the yield and nutritive value of four alfalfa ( Medicago sativa L.)–grass mixtures and annual crops grown on two virtual dairy farms representative of eastern Canada under future climate conditions. The Integrated Farm System Model (IFSM) was used for these projections under the reference (1971–2000), near future (2020–2049), and distant future (2050–2079) climates for two climatically contrasting agricultural areas in eastern Canada (eastern Quebec; southwestern Quebec). In both future periods, annual forage dry matter (DM) yields of the four alfalfa–grass mixtures are projected to increase because of additional harvests, with greater DM yield increases projected in the colder area than in the warmer area. In both areas, the highest yield increase is projected for alfalfa–tall fescue mixture and the lowest for alfalfa–timothy mixture. The nutritive value of all mixtures should increase due to a greater proportion of alfalfa. In both areas, yields of silage and grain corn ( Zea mays L.), and soybean [ Glycine max (L.) Merr.] are projected to increase, but not those of wheat ( Triticum aestivum L.) and barley ( Hordeum vulgare L.). Tall fescue, meadow bromegrass, and meadow fescue are adequate alternatives to timothy grown in association with alfalfa under future climate conditions. , Core Ideas Forage yields of alfalfa–grass mixtures are projected to increase due to additional harvests. Mixture with tall fescue is projected to increase the most and timothy the least. Tall fescue, meadow fescue, and meadow bromegrass are valuable alternatives to timothy. Nutritive value is projected to increase due to more alfalfa in the mixture. Corn and soybean grain yields are projected to increase but not those of wheat and barley.

The distinct problems of physical inconsistency and of multivariate bias involved in the statistical adjustment of climate simulations - Alavoine, Mégane; Grenier, Patrick (International Journal of Climatology, 2023)
Abstract Bias adjustment of numerical climate model simulations involves several arguments wherein the notion of physical inconsistency is referred to, either for rejecting the legitimacy of bias adjustment in general or for justifying the necessity of sophisticated multivariate techniques. However, this notion is often mishandled, in part because the literature generally proceeds without defining it. In this context, the central objective of this study is to clarify and illustrate the distinction between physical inconsistency and multivariate bias, by investigating the effect of bias adjustment on two different kinds of intervariable relationships, namely a physical constraint expected to hold at every step of a time series and statistical properties that emerge with potential bias over a climatic timescale. To this end, 18 alternative bias adjustment techniques are applied on 10 climate simulations at 12 sites over North America. Adjusted variables are temperature, pressure, relative humidity and specific humidity, linked by a thermodynamic constraint. The analysis suggests on the one hand that a clear instance of potential physical inconsistency can be avoided with either a univariate or a multivariate technique, if and only if the bias adjustment strategy explicitly considers the physical constraint to be preserved. On the other hand, it also suggests that sophisticated multivariate techniques alone are not complete adjustment strategies in presence of a physical constraint, as they cannot replace its explicit consideration. By involving common bias adjustment procedures with likely effects on diverse basic statistical properties, this study may also help guide climate information users in the determination of adequate bias adjustment strategies for their research purposes.

An Assessment of Six Dissimilarity Metrics for Climate Analogs - Grenier, Patrick; Parent, Annie-Claude; Huard, David; Anctil, François; Chaumont, Diane (Journal of Applied Meteorology and Climatology, 2013)
Abstract Spatial analog techniques consist in identifying locations whose historical climate is similar to the anticipated future climate at a reference location. In the process of identifying analogs, one key step is the quantification of the dissimilarity between two climates separated in time and space, which involves the choice of a metric. In this study, six a priori suitable metrics are described (the standardized Euclidean distance, the Kolmogorov–Smirnov statistic, the nearest-neighbor distance, the Zech–Aslan energy statistic, the Friedman–Rafsky runs statistic, and the Kullback–Leibler divergence) and criteria are proposed and investigated in an attempt to identify the best metric for selecting spatial analogs. The case study involves the use of numerical simulations performed with the Canadian Regional Climate Model (CRCM, version 4.2.3), from which three annual indicators (total precipitation, heating degree-days, and cooling degree-days) are calculated over 30-yr periods (1971–2000 and 2041–70). It is found that the six metrics identify comparable analog regions at a relatively large scale but that best analogs may differ substantially. For best analogs, it is shown that the uncertainty stemming from the metric choice does not generally exceed that stemming from the simulation or model choice. On the basis of the set of criteria considered in this study, the Zech–Aslan energy statistic stands out as the most recommended metric for analog studies, whereas the Friedman–Rafsky runs statistic is the least recommended.

Chances of Short-Term Cooling Estimated from a Selection of CMIP5-Based Climate Scenarios during 2006–35 over Canada - Grenier, Patrick; De Elía, Ramón; Chaumont, Diane (Journal of Climate, 2015)
Abstract The path toward a warmer global climate is not smooth, but, rather, is made up of a succession of positive and negative temperature trends, with cooling having more chance to occur the shorter the time scale considered. In this paper, estimates of the probabilities of short-term cooling ( P cool ) during the period 2006–35 are performed for 5146 locations across Canada. Probabilities of cooling over durations from 5 to 25 yr come from an ensemble of 60 climate scenarios, based on three different methods using a gridded observational product and CMIP5 climate simulations. These methods treat interannual variability differently, and an analysis in hindcast mode suggests they are relatively reliable. Unsurprisingly, longer durations imply smaller P cool values; in the case of annual temperatures, the interdecile range of P cool values across Canada is, for example, ~2%–18% for 25 yr and ~40%–46% for 5 yr. Results vary slightly with the scenario design method, with similar geographical patterns emerging. With regards to seasonal influence, spring and winter are generally associated with higher P cool values. Geographical P cool patterns and their seasonality are explained in terms of the interannual variability over background trend ratio. This study emphasizes the importance of natural variability superimposed on anthropogenically forced long-term trends and the fact that regional and local short-term cooling trends are to be expected with nonnegligible probabilities.

Two Types of Physical Inconsistency to Avoid with Univariate Quantile Mapping: A Case Study over North America Concerning Relative Humidity and Its Parent Variables - Grenier, Patrick (Journal of Applied Meteorology and Climatology, 2018)
Abstract Univariate quantile mapping (QM), a technique often used to statistically postprocess climate simulations, may generate physical inconsistency. This issue is investigated here by classifying physical inconsistency into two types. Type I refers to the attribution of an impossible value to a single variable, and type II refers to the breaking of a fixed intervariable relationship. Here QM is applied to relative humidity (RH) and its parent variables, namely, temperature, pressure, and specific humidity. Twelve sites representing various climate types across North America are investigated. Time series from an ensemble of ten 3-hourly simulations are postprocessed, with the CFSR reanalysis used as the reference product. For type I, results indicate that direct postprocessing of RH generates supersaturation values (>100%) at relatively small frequencies of occurrence. Generated supersaturation amplitudes exceed observed values in fog and clouds. Supersaturation values are generally more frequent and higher when RH is deduced from postprocessed parent variables. For type II, results show that univariate QM practically always breaks the intervariable thermodynamic relationship. Heuristic proxies are designed for comparing the initial bias with physical inconsistency of type II, and results suggest that QM generates a problem that is arguably lesser than the one it is intended to solve. When physical inconsistency is avoided by capping one humidity variable at its saturation level and deducing the other, statistical equivalence with the reference product remains much improved relative to the initial situation. A recommendation for climate services is to postprocess RH and deduce specific humidity rather than the opposite.

The issue of properly ordering climate indices calculation and bias correction before identifying spatial analogs for agricultural applications - Grenier, Patrick; Firlej, Annabelle; Blondlot, Anne; Logan, Travis; Ricard, Marie-Pier (Climate Services, 2019)

Investigating added value of regional climate modeling in North American winter storm track simulations - Poan, E. D.; Gachon, P.; Laprise, R.; Aider, R.; Dueymes, G. (Climate Dynamics, 2018)

Predicted Northward Expansion of the Geographic Range of the Tick Vector Amblyomma americanum in North America under Future Climate Conditions - Sagurova, Irina; Ludwig, Antoinette; Ogden, Nicholas H.; Pelcat, Yann; Dueymes, Guillaume; Gachon, Philippe (Environmental Health Perspectives, 2019)

Climate change and infectious diseases: What can we expect? - Ogden, Nh; Gachon, P (Canada Communicable Disease Report, 2019)

Risk assessment strategies for early detection and prediction of infectious disease outbreaks associated with climate change - Rees, Ee; Ng, V; Gachon, P; Mawudeku, A; McKenney, D; Pedlar, J; Yemshanov, D; Parmely, J; Knox, J (Canada Communicable Disease Report, 2019)

Current and Projected Distributions of Aedes aegypti and Ae. albopictus in Canada and the U.S. - Khan, Salah Uddin; Ogden, Nicholas H.; Fazil, Aamir A.; Gachon, Philippe H.; Dueymes, Guillaume U.; Greer, Amy L.; Ng, Victoria (Environmental Health Perspectives, 2020)

Psychological impacts of the 2019 Quebec floods: findings from a large population-based study - Genereux, M; Maltais, D; Lansard, A L; Gachon, P (European Journal of Public Health, 2020)
Abstract Background During Spring 2019, many regions in Quebec (Canada) experienced severe floods. As much as 5,245 households were flooded and 7,452 persons were evacuated, causing extensive material and human damages. A large population-based study was therefore conducted to examine medium-term effects of this natural disaster on health and well-being. Methods Six to eight months post-floods, households located in the flooded zones (in one of the 6 Quebec regions the most severely affected) were randomly invited to participate to a telephone or a web-based survey (response rate=15.3%). Several psychological health outcomes were examined, including psychological distress (based on the 6-item Kessler Scale, score 0-24) and post-traumatic stress (based on the 15-item Impact of Event Scale, score 0-75). These outcomes were compared among 3 levels of exposure using Chi-square test: flooded (floodwater in ≥ 1 liveable room), disrupted (floodwater in non-liveable areas, loss of utilities, loss of access to services, or evacuation), and unaffected. Results Of the 3,437 participating households, 349 (10.2%) were flooded and 1230 (35.8%) were disrupted (but not flooded) during the 2019 floods. A steep gradient was observed for moderate/severe symptoms of post-traumatic stress (score ≥ 26) according to the level of exposure to flooding (unaffected: 3.0%; disrupted: 14.6%; flooded: 44.1%; p < 0.0005). For psychological distress (score ≥ 7), the baseline level (i.e. unaffected group) was 7.3% while it reached 15.0% and 38.4% in the disrupted and the flooded groups, respectively (p < 0.0005). Conclusions This study is among the largest to examine the psychological impacts of flooding. The magnitude of effects observed in flooded households is consistent with the literature and calls for stronger social and economic measures to support flood victims. Such support should help coping with initial stress, but also alleviating secondary stressors classically observed in post-flood settings. Key messages Psychological impacts of floods may persist for several months and may be observed in both flooded and disrupted people. Stronger social and economic measures are needed to better support flood victims, not only in the short but also in the longer term.

Evaluating the Dependence between Temperature and Precipitation to Better Estimate the Risks of Concurrent Extreme Weather Events - Wazneh, Hussein; Arain, M. Altaf; Coulibaly, Paulin; Gachon, Philippe (Advances in Meteorology, 2020)
Precipitation and temperature are among major climatic variables that are used to characterize extreme weather events, which can have profound impacts on ecosystems and society. Accurate simulation of these variables at the local scale is essential to adapt urban systems and policies to future climatic changes. However, accurate simulation of these climatic variables is difficult due to possible interdependence and feedbacks among them. In this paper, the concept of copulas was used to model seasonal interdependence between precipitation and temperature. Five copula functions were fitted to grid (approximately 10 km × 10 km) climate data from 1960 to 2013 in southern Ontario, Canada. Theoretical and empirical copulas were then compared with each other to select the most appropriate copula family for this region. Results showed that, of the tested copulas, none of them consistently performed the best over the entire region during all seasons. However, Gumbel copula was the best performer during the winter season, and Clayton performed best in the summer. More variability in terms of best copula was found in spring and fall seasons. By examining the likelihoods of concurrent extreme temperature and precipitation periods including wet/cool in the winter and dry/hot in the summer, we found that ignoring the joint distribution and confounding impacts of precipitation and temperature lead to the underestimation of occurrence of probabilities for these two concurrent extreme modes. This underestimation can also lead to incorrect conclusions and flawed decisions in terms of the severity of these extreme events.

Projected Wind Impact on Abies balsamea (Balsam fir)-Dominated Stands in New Brunswick (Canada) Based on Remote Sensing and Regional Modelling of Climate and Tree Species Distribution - Bourque, Charles P.-A.; Gachon, Philippe; MacLellan, Benjamin R.; MacLellan, James I. (Remote Sensing, 2020)
The paper describes the development of predictive equations of windthrow for five tree species based on remote sensing of wind-affected stands in southwestern New Brunswick (NB). The data characterises forest conditions before, during and after the passing of extratropical cyclone Arthur, July 4–5, 2014. The five-variable logistic function developed for balsam fir (bF) was validated against remote-sensing-acquired windthrow data for bF-stands affected by the Christmas Mountains windthrow event of November 7, 1994. In general, the prediction of windthrow in the area agreed fairly well with the windthrow sites identified by photogrammetry. The occurrence of windthrow in the Christmas Mountains was prominent in areas with shallow soils and prone to localised accelerations in mean and turbulent airflow. The windthrow function for bF was subsequently used to examine the future impact of windthrow under two climate scenarios (RCP’s 4.5 and 8.5) and species response to local changes anticipated with global climate change, particularly with respect to growing degree-days and soil moisture. Under climate change, future windthrow in bF stands (2006–2100) is projected to be modified as the species withdraws from the high-elevation areas and NB as a whole, as the climate progressively warms and precipitation increases, causing the growing environment of bF to deteriorate.

Atmospheric blocking events in the North Atlantic: trends and links to climate anomalies and teleconnections - Wazneh, Hussein; Gachon, Philippe; Laprise, René; De Vernal, Anne; Tremblay, Bruno (Climate Dynamics, 2021)
Abstract Atmospheric blockings are generally associated with large-scale high-pressure systems that interrupt west-to-east atmospheric flow in mid and high latitudes. Blockings cause several days of quasi-stationary weather conditions, and therefore can result in monthly or seasonal climate anomalies and extreme weather events on the affected regions. In this paper, the long-term coupled CERA-20C reanalysis data from 1901 to 2010 are used to evaluate the links between blocking events over the North Atlantic north of 35° N, and atmospheric and oceanic modes of climate variability on decadal time scales. This study indicates more frequent and longer lasting blocking events than previous studies using other reanalyses products. A strong relationship was found between North Atlantic blocking events and North Atlantic Oscillation (NAO), Atlantic Multidecadal Oscillation (AMO) and Baffin Island–West Atlantic (BWA) indices, in fall, winter and spring. More blocking events occur during the negative phases of the NAO index and positive phases of the BWA mode. In some situations, the BWA patterns provide clearer links with the North Atlantic blocking occurrence than with the NAO alone. The correlation between the synchronous occurrences of AMO and blocking is generally weak, although it does increase for a lag of about 6–10 years. Convergent cross mapping (CCM) furthermore demonstrates a significant two-way causal effect between blocking occurrences and the NAO and BWA indices. Finally, while we find no significant trends in blocking frequencies over the last 110 years in the Northern Hemisphere, these events become longer lasting in summer and fall, and more intense in spring in the North Atlantic.

Recent advances in polar low research: current knowledge, challenges and future perspectives - Moreno-Ibáñez, Marta; Laprise, René; Gachon, Philippe (Tellus A: Dynamic Meteorology and Oceanography, 2021)

Yellow fever virus outbreak in Brazil under current and future climate - Sadeghieh, Tara; Sargeant, Jan M.; Greer, Amy L.; Berke, Olaf; Dueymes, Guillaume; Gachon, Philippe; Ogden, Nicholas H.; Ng, Victoria (Infectious Disease Modelling, 2021)

Zika virus outbreak in Brazil under current and future climate - Sadeghieh, Tara; Sargeant, Jan M.; Greer, Amy L.; Berke, Olaf; Dueymes, Guillaume; Gachon, Philippe; Ogden, Nicholas H.; Ng, Victoria (Epidemics, 2021)

Respiratory and Otolaryngology Symptoms Following the 2019 Spring Floods in Quebec - Landaverde, Elsa; Généreux, Mélissa; Maltais, Danielle; Gachon, Philippe (International Journal of Environmental Research and Public Health, 2022)
Background: Although floods may have important respiratory health impacts, few studies have examined this issue. This study aims to document the long-term impacts of the spring floods of 2019 in Quebec by (1) describing the population affected by the floods; (2) assessing the impacts on the respiratory system according to levels of exposure; and (3) determining the association between stressors and respiratory health. Methods: A population health survey was carried out across the six most affected regions 8–10 months post-floods. Data were collected on self-reported otolaryngology (ENT) and respiratory symptoms, along with primary and secondary stressors. Three levels of exposure were examined: flooded, disrupted and unaffected. Results: One in ten respondents declared being flooded and 31.4% being disrupted by the floods. Flooded and disrupted participants reported significantly more ENT symptoms (adjusted odds ratio (aOR): 3.18; 95% CI: 2.45–4.14; aOR: 1.76; 95% CI: 1.45–2.14) and respiratory symptoms (aOR: 3.41; 95% CI: 2.45–4.75; aOR: 1.45; 95% CI: 1.10–1.91) than the unaffected participants. All primary stressors and certain secondary stressors assessed were significantly associated with both ENT and respiratory symptoms, but no “dose–response” gradient could be observed. Conclusion: This study highlights the long-term adverse effects of flood exposure on respiratory health.

The influence of the environment and indoor residual spraying on malaria risk in a cohort of children in Uganda - Sadoine, Margaux L.; Smargiassi, Audrey; Liu, Ying; Gachon, Philippe; Dueymes, Guillaume; Dorsey, Grant; Fournier, Michel; Nankabirwa, Joaniter I.; Rek, John; Zinszer, Kate (Scientific Reports, 2022)
Abstract Studies have estimated the impact of the environment on malaria incidence although few have explored the differential impact due to malaria control interventions. Therefore, the objective of the study was to evaluate the effect of indoor residual spraying (IRS) on the relationship between malaria and environment (i.e. rainfall, temperatures, humidity, and vegetation) using data from a dynamic cohort of children from three sub-counties in Uganda. Environmental variables were extracted from remote sensing sources and averaged over different time periods. General linear mixed models were constructed for each sub-counties based on a log-binomial distribution. The influence of IRS was analysed by comparing marginal effects of environment in models adjusted and unadjusted for IRS. Great regional variability in the shape (linear and non-linear), direction, and magnitude of environmental associations with malaria risk were observed between sub-counties. IRS was significantly associated with malaria risk reduction (risk ratios vary from RR = 0.03, CI 95% [0.03–0.08] to RR = 0.35, CI95% [0.28–0.42]). Model adjustment for this intervention changed the magnitude and/or direction of environment-malaria associations, suggesting an interaction effect. This study evaluated the potential influence of IRS in the malaria-environment association and highlighted the necessity to control for interventions when they are performed to properly estimate the environmental influence on malaria. Local models are more informative to guide intervention program compared to national models.

Climate change alone cannot explain boreal caribou range recession in Quebec since 1850 - Morineau, Chloé; Boulanger, Yan; Gachon, Philippe; Plante, Sabrina; St‐Laurent, Martin‐Hugues (Global Change Biology, 2023)
Abstract The contraction of species range is one of the most significant symptoms of biodiversity loss worldwide. While anthropogenic activities and habitat alteration are major threats for several species, climate change should also be considered. For species at risk, differentiating the effects of human disturbances and climate change on past and current range transformations is an important step towards improved conservation strategies. We paired historical range maps with global atmospheric reanalyses from different sources to assess the potential effects of recent climate change on the observed northward contraction of the range of boreal populations of woodland caribou ( Rangifer tarandus caribou ) in Quebec (Canada) since 1850. We quantified these effects by highlighting the discrepancies between different southern limits of the caribou's range (used as references) observed in the past and reconstitutions obtained through the hindcasting of the climate conditions within which caribou are currently found. Hindcasted southern limits moved ~105 km north over time under all reanalysis datasets, a trend drastically different from the ~620 km reported for observed southern limits since 1850. The differences in latitudinal shift through time between the observed and hindcasted southern limits of distribution suggest that caribou range recession should have been only 17% of what has been observed since 1850 if recent climate change had been the only disturbance driver. This relatively limited impact of climate reinforces the scientific consensus stating that caribou range recession in Quebec is mainly caused by anthropogenic drivers (i.e. logging, development of the road network, agriculture, urbanization) that have modified the structure and composition of the forest over the past 160 years, paving the way for habitat‐mediated apparent competition and overharvesting. Our results also call for a reconsideration of past ranges in models aiming at projecting future distributions, especially for endangered species.

Analysis of the Development Mechanisms of a Polar Low over the Norwegian Sea Simulated with the Canadian Regional Climate Model - Moreno-Ibáñez, Marta; Laprise, René; Gachon, Philippe (Atmosphere, 2023)
Polar lows (PLs) are maritime mesoscale cyclones associated with severe weather. They develop during marine cold air outbreaks near coastlines and the sea ice edge. Unfortunately, our knowledge about the mechanisms leading to PL development is still incomplete. This study aims to provide a detailed analysis of the development mechanisms of a PL that formed over the Norwegian Sea on 25 March 2019 using the output of a simulation with the sixth version of the Canadian Regional Climate Model (CRCM6/GEM4), a convection-permitting model. First, the life cycle of the PL is described and the vertical wind shear environment is analysed. Then, the horizontal wind divergence and the baroclinic conversion term are computed, and a surface pressure tendency equation is developed. In addition, the roles of atmospheric static stability, latent heat release, and surface heat and moisture fluxes are explored. The results show that the PL developed in a forward-shear environment and that moist baroclinic instability played a major role in its genesis and intensification. Baroclinic instability was initially only present at low levels of the atmosphere, but later extended upward until it reached the mid-troposphere. Whereas the latent heat of condensation and the surface heat fluxes also contributed to the development of the PL, convective available potential energy and barotropic conversion do not seem to have played a major role in its intensification. In conclusion, this study shows that a convection-permitting model simulation is a powerful tool to study the details of the structure of PLs, as well as their development mechanisms.

Precipitation Extremes and Their Links with Regional and Local Temperatures: A Case Study over the Ottawa River Basin, Canada - Llerena, Ana; Gachon, Philippe; Laprise, René (Atmosphere, 2023)
In the context of global warming, the Clausius–Clapeyron (CC) relationship has been widely used as an indicator of the evolution of the precipitation regime, including daily and sub-daily extremes. This study aims to verify the existence of links between precipitation extremes and 2 m air temperature for the Ottawa River Basin (ORB, Canada) over the period 1981–2010, applying an exponential relationship between the 99th percentile of precipitation and temperature characteristics. Three simulations of the Canadian Regional Climate Model version 5 (CRCM5), at three different resolutions (0.44°, 0.22°, and 0.11°), one simulation using the recent CRCM version 6 (CRCM6) at “convection-permitting” resolution (2.5 km), and two reanalysis products (ERA5 and ERA5-Land) were used to investigate the CC scaling hypothesis that precipitation increases at the same rate as the atmospheric moisture-holding capacity (i.e., 6.8%/°C). In general, daily precipitation follows a lower rate of change than the CC scaling with median values between 2 and 4%/°C for the ORB and with a level of statistical significance of 5%, while hourly precipitation increases faster with temperature, between 4 and 7%/°C. In the latter case, rates of change greater than the CC scaling were even up to 10.2%/°C for the simulation at 0.11°. A hook shape is observed in summer for CRCM5 simulations, near the 20–25 °C temperature threshold, where the 99th percentile of precipitation decreases with temperature, especially at higher resolution with the CRCM6 data. Beyond the threshold of 20 °C, it appears that the atmospheric moisture-holding capacity is not the only determining factor for generating precipitation extremes. Other factors need to be considered, such as the moisture availability at the time of the precipitation event, and the presence of dynamical mechanisms that increase, for example, upward vertical motion. As mentioned in previous studies, the applicability of the CC scaling should not be generalised in the study of precipitation extremes. The time and spatial scales and season are also dependent factors that must be taken into account. In fact, the evolution of precipitation extremes and temperature relationships should be identified and evaluated with very high spatial resolution simulations, knowing that local temperature and regional physiographic features play a major role in the occurrence and intensity of precipitation extremes. As precipitation extremes have important effects on the occurrence of floods with potential deleterious damages, further research needs to explore the sensitivity of projections to resolution with various air temperature and humidity thresholds, especially at the sub-daily scale, as these precipitation types seem to increase faster with temperature than with daily-scale values. This will help to develop decision-making and adaptation strategies based on improved physical knowledge or approaches and not on a single assumption based on CC scaling.

Mixture Probability Models with Covariates: Applications in Estimating Risk of Hydroclimatic Extremes - Yousfi, Nawres; El Adlouni, Salaheddine; Papalexiou, Simon Michael; Gachon, Philippe (Journal of Hydrologic Engineering, 2023)

Climate change more than doubled the likelihood of extreme fire weather conditions in Eastern Canada - Barnes, C; Boulanger, Y; Keeping, T; Gachon, P; Gillett, N; Haas, O; Wang, X; Roberge, F; Kew, S; Heinrich, D; Singh, R; Vahlberg, M; et al. (Imperial College London, 2023)

Differential Influence of Environmental Factors on Malaria Due to Vector Control Interventions in Uganda - Sadoine, Margaux L.; Smargiassi, Audrey; Liu, Ying; Gachon, Philippe; Fournier, Michel; Dueymes, Guillaume; Namuganga, Jane Frances; Dorsey, Grant; Nasri, Bouchra; Zinszer, Kate (International Journal of Environmental Research and Public Health, 2023)
Background: Few studies have explored how vector control interventions may modify associations between environmental factors and malaria. Methods: We used weekly malaria cases reported from six public health facilities in Uganda. Environmental variables (temperature, rainfall, humidity, and vegetation) were extracted from remote sensing sources. The non-linearity of environmental variables was investigated, and negative binomial regression models were used to explore the influence of indoor residual spraying (IRS) and long-lasting insecticidal nets (LLINs) on associations between environmental factors and malaria incident cases for each site as well as pooled across the facilities, with or without considering the interaction between environmental variables and vector control interventions. Results: An average of 73.3 weekly malaria cases per site (range: 0–597) occurred between 2010 and 2018. From the pooled model, malaria risk related to environmental variables was reduced by about 35% with LLINs and 63% with IRS. Significant interactions were observed between some environmental variables and vector control interventions. There was site-specific variability in the shape of the environment–malaria risk relationship and in the influence of interventions (6 to 72% reduction in cases with LLINs and 43 to 74% with IRS). Conclusion: The influence of vector control interventions on the malaria–environment relationship need to be considered at a local scale in order to efficiently guide control programs.

Intersectoral approaches: the key to mitigating psychosocial and health consequences of disasters and systemic risks - Gousse-Lessard, Anne-Sophie; Gachon, Philippe; Lessard, Lily; Vermeulen, Valérie; Boivin, Maxime; Maltais, Danielle; Landaverde, Elsa; Généreux, Mélissa; Motulsky, Bernard; Le Beller, Julien (Disaster Prevention and Management: An International Journal, 2023)
Purpose The current pandemic and ongoing climate risks highlight the limited capacity of various systems, including health and social ones, to respond to population-scale and long-term threats. Practices to reduce the impacts on the health and well-being of populations must evolve from a reactive mode to preventive, proactive and concerted actions beginning at individual and community levels. Experiences and lessons learned from the pandemic will help to better prevent and reduce the psychosocial impacts of floods, or other hydroclimatic risks, in a climate change context. Design/methodology/approach The present paper first describes the complexity and the challenges associated with climate change and systemic risks. It also presents some systemic frameworks of mental health determinants, and provides an overview of the different types of psychosocial impacts of disasters. Through various Quebec case studies and using lessons learned from past and recent flood-related events, recommendations are made on how to better integrate individual and community factors in disaster response. Findings Results highlight the fact that people who have been affected by the events are significantly more likely to have mental health problems than those not exposed to flooding. They further demonstrate the adverse and long-term effects of floods on psychological health, notably stemming from indirect stressors at the community and institutional levels. Different strategies are proposed from individual-centered to systemic approaches, in putting forward the advantages from intersectoral and multirisk researches and interventions. Originality/value The establishment of an intersectoral flood network, namely the InterSectoral Flood Network of Québec (RIISQ), is presented as an interesting avenue to foster interdisciplinary collaboration and a systemic view of flood risks. Intersectoral work is proving to be a major issue in the management of systemic risks, and should concern communities, health and mental health professionals, and the various levels of governance. As climate change is called upon to lead to more and more systemic risks, close collaboration between all the areas concerned with the management of the factors of vulnerability and exposure of populations will be necessary to respond effectively to damages and impacts (direct and indirect) linked to new meteorological and compound hazards. This means as well to better integrate the communication managers into the risk management team.

Assessment of simulations of a polar low with the Canadian Regional Climate Model - Moreno-Ibáñez, Marta; Laprise, René; Gachon, Philippe (PLOS ONE, 2023)
Polar lows (PLs), which are intense maritime polar mesoscale cyclones, are associated with severe weather conditions. Due to their small size and rapid development, PL forecasting remains a challenge. Convection-permitting models are adequate to forecast PLs since, compared to coarser models, they provide a better representation of convection as well as surface and near-surface processes. A PL that formed over the Norwegian Sea on 25 March 2019 was simulated using the convection-permitting Canadian Regional Climate Model version 6 (CRCM6/GEM4, using a grid mesh of 2.5 km) driven by the reanalysis ERA5. The objectives of this study were to quantify the impact of the initial conditions on the simulation of the PL, and to assess the skill of the CRCM6/GEM4 at reproducing the PL. The results show that the skill of the CRCM6/GEM4 at reproducing the PL strongly depends on the initial conditions. Although in all simulations the synoptic environment is favourable for PL development, with a strong low-level temperature gradient and an upper-level through, only the low-level atmospheric fields of three of the simulations lead to PL development through baroclinic instability. The two simulations that best captured the PL represent a PL deeper than the observed one, and they show higher temperature mean bias compared to the other simulations, indicating that the ocean surface fluxes may be too strong. In general, ERA5 has more skill than the simulations at reproducing the observed PL, but the CRCM6/GEM4 simulation with initialisation time closer to the genesis time of the PL reproduces quite well small scale features as low-level baroclinic instability during the PL development phase.

Estimating the Incidence and Economic Cost of Lyme Disease Cases in Canada in the 21st Century with Projected Climate Change - Ogden, Nicholas H.; Dumas, Ariane; Gachon, Philippe; Rafferty, Ellen (Environmental Health Perspectives, 2024)

The 2023 wildfire season in Québec: an overview of extreme conditions, impacts, lessons learned and considerations for the future - Boulanger, Yan; Arseneault, Dominique; Bélisle, Annie Claude; Bergeron, Yves; Boucher, Jonathan; Boucher, Yan; Danneyrolles, Victor; Erni, Sandy; Gachon, Philippe; Girardin, Martin P.; Grant, Eliane; Grondin, Pierre; et al. (Canadian Journal of Forest Research, 2024)
The 2023 wildfire season in Québec set records due to extreme warm and dry conditions, burning 4.5 million hectares and indicating persistent and escalating impacts associated with climate change. This study reviews the unusual weather conditions that led to the fires, discussing their extensive impacts on the forest sector, fire management, boreal caribou habitats, and particularly the profound effects on First Nation communities. The wildfires led to significant declines in forest productivity and timber supply, overwhelming fire management resources, and necessitating widespread evacuations. First Nation territories were dramatically altered, facing severe air quality issues and disruptions. While caribou impacts were modest across the province, the broader ecological, economical, and social repercussions were considerable. To mitigate future extreme wildfire seasons, the study suggests changes in forest management practices to increase forest resilience and resistance, adapting industrial structures to changes in wood type harvested, and enhancing fire suppression and risk management strategies. It calls for a comprehensive, unified approach to risk management that incorporates the lessons learned from the 2023 fire season and accounts for ongoing climate change. The studyunderscores the urgent need for detailed planning and proactive measures to reduce the growing risks and impacts of wildfires in a changing climate.

Predicting malaria risk considering vector control interventions under climate change scenarios - Sadoine, Margaux L.; Zinszer, Kate; Liu, Ying; Gachon, Philippe; Fournier, Michel; Dueymes, Guillaume; Dorsey, Grant; Llerena, Ana; Namuganga, Jane Frances; Nasri, Bouchra; Smargiassi, Audrey (Scientific Reports, 2024)
Abstract Many studies have projected malaria risks with climate change scenarios by modelling one or two environmental variables and without the consideration of malaria control interventions. We aimed to predict the risk of malaria with climate change considering the influence of rainfall, humidity, temperatures, vegetation, and vector control interventions (indoor residual spraying (IRS) and long-lasting insecticidal nets (LLIN)). We used negative binomial models based on weekly malaria data from six facility-based surveillance sites in Uganda from 2010–2018, to estimate associations between malaria, environmental variables and interventions, accounting for the non-linearity of environmental variables. Associations were applied to future climate scenarios to predict malaria distribution using an ensemble of Regional Climate Models under two Representative Concentration Pathways (RCP4.5 and RCP8.5). Predictions including interaction effects between environmental variables and interventions were also explored. The results showed upward trends in the annual malaria cases by 25% to 30% by 2050s in the absence of intervention but there was great variability in the predictions (historical vs RCP 4.5 medians [Min–Max]: 16,785 [9,902–74,382] vs 21,289 [11,796–70,606]). The combination of IRS and LLIN, IRS alone, and LLIN alone would contribute to reducing the malaria burden by 76%, 63% and 35% respectively. Similar conclusions were drawn from the predictions of the models with and without interactions between environmental factors and interventions, suggesting that the interactions have no added value for the predictions. The results highlight the need for maintaining vector control interventions for malaria prevention and control in the context of climate change given the potential public health and economic implications of increasing malaria in Uganda.

High-Resolution Modelling of Extreme Storms over the East Coast of Australia v1.0 - Di Luca, Alejandro (NCI Australia, 2021)

North America Extratropical Cyclone (NAEC) Catalogue - Chen, Ting-Chen; Di Luca, Alejandro; Winger, Katja (Borealis, 2022)
The NAEC catalogue comprises information on extratropical cyclone (ETC) tracks in North America (20–80 N and 180-0W) from January 1979 to December 2020. The source data used to produce this dataset is obtained from the ECMWF ERA5 reanalysis at 1-hour spatial resolution and 0.25x0.25 degree spatial resolution. In addition to the location, time, and intensity, this dataset also includes ETC-associated impact variables such as the near-surface wind speed, wind gust, and precipitation, averaged using different radii around the ETC center. Both absolute and relative (to the local climatology) measures are provided. This catalogue provides useful information for the assessment of ETC-induced impacts over North America.

North America ISD to ERA5 (NA-ISD2ERA) Catalogue - Collet, François; Di Luca, Alejandro; Chen, Ting-Chen (Borealis, 2022)
The NA-ISD2ERA is a station-based gridded dataset of hourly 10-m wind speed, surface total precipitation, sea-level pressure, and 2-m air and dew point temperature observations interpolated on the regular 0.25° latitude-longitude ERA5 grid over North America for the 1990-2021 period. Station observations are from the Integrated Surface Database (ISD) developed by the National Centers for Environmental Information (NCEI) of the National Oceanic and Atmospheric Administration (NOAA) (Smith et al. 2011). It includes over 35,000 weather stations around the world of hourly to sub-hourly in situ observations for numerous variables such as wind speed, precipitation, sea-level pressure, air and dew point temperature. The NCEI ISD dataset is available at https://www.ncei.noaa.gov. ERA5 is the fifth generation of the European Centre for Medium-Range Weather Forecasts (ECMWF) reanalysis (Hersbach et al., 2020). Quality checks implemented in ISD are used to select reliable observations. For each ERA5 grid cell and at each hour, the data are interpolated by taking the nearest available ISD observation to the grid cell center that is located within the targeted grid cell.

Spatial Spin-Up Distance Simulations Catalogue (SSUDC), V1 - Roberge, François; Di Luca, Alejandro (Borealis, 2023)
This catalogue includes seasonal mean precipitation fields from simulations and reanalysis used for the calculation of the Spatial Spin-Up Distance (SSUD). A total of seven simulation were conducted using the convection-permitting configuration (2.5-km grid spacing) of version 6 of the Canadian Regional Climate Model (CRCM6/GEM5; hereafter denoted as GEM2.5 for simplicity). The CRCM6/GEM5 version used here is based on version 5.0.2 of the Global Environmental Multiscale model (GEM5). GEM2.5 simulations were driven directly by the ERA5 reanalysis or by 12-km (GEM12) simulations also performed using the CRCM6/GEM5 model (which was in turn driven by the ERA5 reanalysis). The catalogue comprises seasonal mean precipitation fields from all seven GEM2.5 simulations, from the ERA5 reanalysis and from two GEM12 intermediate simulations (GEM12_SUN and GEM12_P3). Seasonal means were calculated using the common convention: December, January and February (DJF) for winter; March, April and May (MAM) for spring; June, July and August (JJA) for summer; and September, October and November (SON) for fall. Precipitations fields are given in mm/h.

UQAM-Heatwave ERA5 Archive and Temperatures (U-HEAT) Catalog - Comeau, Elise; Di Luca, Alejandro; Roberge, François (Borealis, 2023)
The UQAM Heatwave ERA5 Archive and Temperatures (U-HEAT) catalog is a global dataset of temperature and heatwave data spanning 1940 to 2022. The temperature data features the maximum daily 2-m temperature, the 90th percentile of the maximum daily 2-m temperature, and an indication as to whether a given location (grid point) is experiencing a heatwave or not on a given day. The heatwave data includes metrics such as the duration, the cumulated intensity and the maximum intensity of heatwaves occuring in the study period as well as their location (grid point) and start date. Both the temperature and the heatwave metrics data were calculated from the ERA5 data produced by the European Centre for Medium-Range Weather Forecasts (ECMWF). More information on the catalog can be found in the documentation and the README files. Le catalogue UQAM Heatwave ERA5 Archive and Temperatures (U-HEAT) est un jeu de données global de température et de vague de chaleur pour la période entre 1940 et 2022. Les données de température comprennent le maximum quotidien de la température à 2m, le 90e percentile du maximum quotidien de la température à 2m et une indication permettant de savoir si un lieu donné (point de grille) subit ou non une vague de chaleur pour un jour donné. Les données de vague de chaleur incluent des métriques comme la durée, l'intensité cumulée et l'intensité maximale de vagues de chaleur qui se sont produites durant la période d'étude en plus de leur emplacement (point de grille) et leur date de début. Les données de température et de vague de chaleur ont été calculées à partir du jeu de données ERA5 produit par le European Centre for Medium-Range Weather Forecasts (ECMWF). Le fichier de documentation et le fichier README peuvent être consultés pour obtenir plus d'information à propos du catalogue.

Considerations of Domain Size and Large-Scale Driving for Nested Regional Climate Models: Impact on Internal Variability and Ability at Developing Small-Scale Details - Laprise, René; Kornic, Dragana; Rapaić, Maja; Šeparović, Leo; Leduc, Martin; Nikiema, Oumarou; Di Luca, Alejandro; Diaconescu, Emilia; Alexandru, Adelina; Lucas-Picher, Philippe; De Elía, Ramón; Caya, Daniel; et al. (Climate Change, 2012)

Climate Change 2021 – The Physical Science Basis: Working Group I Contribution to the Sixth Assessment Report of the Intergovernmental Panel on Climate Change - Intergovernmental Panel On Climate Change (Ipcc) (Cambridge University Press, 2023)
The Working Group I contribution to the Sixth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC) provides a comprehensive assessment of the physical science basis of climate change. It considers in situ and remote observations; paleoclimate information; understanding of climate drivers and physical, chemical, and biological processes and feedbacks; global and regional climate modelling; advances in methods of analyses; and insights from climate services. It assesses the current state of the climate; human influence on climate in all regions; future climate change including sea level rise; global warming effects including extremes; climate information for risk assessment and regional adaptation; limiting climate change by reaching net zero carbon dioxide emissions and reducing other greenhouse gas emissions; and benefits for air quality. The report serves policymakers, decision makers, stakeholders, and all interested parties with the latest policy-relevant information on climate change. Available as Open Access on Cambridge Core.

Storms as Forming and Threatening Factors for Coasts - Von Storch, Hans; Feser, Frauke; Blender, Richard; Camargo, Suzana J.; Cavicchia, Leone; Di Luca, Alejandro; Fu, Gang; Gozzo, Luiz Felippe; Koks, Elco; Messmer, Martina; Mori, Nobuhito; Priestley, Matthew D.K.; et al. (Oxford Research Encyclopedia of Climate Science, 2024)
Storms are the most significant meteorological phenomena that affect the formation of coasts and human livelihood along them. Thus, risks related to coastal storms, such as flooding, loss of land, shipping, and other offshore activity, have had a significant influence on coastal societies and their economies. In the early 21st century, anthropogenic climate change will affect the locations and intensities of coastal storminess, impacting society. Storms are studied not only by natural scientists but also by social scientists. The former deal with the climatologies, dynamics, and mechanisms of storms but also with the identification of different types of storms, such as extratropical baroclinic storms, explosive cyclones, tropical storms, polar lows, medicanes, Vb-cyclones, and Australian east coast storms. Their significance is often through their physical impacts, in particular ocean waves and storm surges, which were and are associated with massive losses of lives, sometimes up to several hundred thousand people, and wealth. The perceptions of what storms constitute were different in different cultural contexts and times. In earlier days, higher forces were responsible for such storms, which they used to transfer messages to humans, physically based ideas have been forming since the 16th century. Another significant historical development was societies preparing to reduce their vulnerability to storms and to implement practices of insurance and risk management.

Potential for added value in precipitation simulated by high-resolution nested Regional Climate Models and observations - Di Luca, Alejandro; De Elía, Ramón; Laprise, René (Climate Dynamics, 2012)

Potential for small scale added value of RCM’s downscaled climate change signal - Di Luca, Alejandro; De Elía, Ramón; Laprise, René (Climate Dynamics, 2013)

The atmospheric component of the Mediterranean Sea water budget in a WRF multi-physics ensemble and observations - Di Luca, Alejandro; Flaounas, Emmanouil; Drobinski, Philippe; Brossier, Cindy Lebeaupin (Climate Dynamics, 2014)

Resolution Sensitivity of Cyclone Climatology over Eastern Australia Using Six Reanalysis Products* - Di Luca, Alejandro; Evans, Jason P.; Pepler, Acacia; Alexander, Lisa; Argüeso, Daniel (Journal of Climate, 2015)
Abstract The climate of the eastern seaboard of Australia is strongly influenced by the passage of low pressure systems over the adjacent Tasman Sea due to their associated precipitation and their potential to develop into extreme weather events. The aim of this study is to quantify differences in the climatology of east coast lows derived from the use of six global reanalyses. The methodology is explicitly designed to identify differences between reanalyses arising from differences in their horizontal resolution and their structure (type of forecast model, assimilation scheme, and the kind and number of observations assimilated). As a basis for comparison, reanalysis climatologies are compared with an observation-based climatology. Results show that reanalyses, specially high-resolution products, lead to very similar climatologies of the frequency, intensity, duration, and size of east coast lows when using spatially smoothed (about 300-km horizontal grid meshes) mean sea level pressure fields as input data. Moreover, at these coarse horizontal scales, monthly, interannual, and spatial variabilities appear to be very similar across the various reanalyses with a generally stronger agreement between winter events compared with summer ones. Results also show that, when looking at cyclones using reanalysis data at their native resolution (approaching 50-km grid spacing for the most recent products), uncertainties related to the frequency, intensity, and size of lows are very large and it is not clear which reanalysis, if any, gives a better description of cyclones. Further work is needed in order to evaluate the usefulness of the finescale information in modern reanalyses and to better understand the sources of their differences.

Using large-scale diagnostic quantities to investigate change in East Coast Lows - Ji, Fei; Evans, Jason P.; Argueso, Daniel; Fita, Lluis; Di Luca, Alejandro (Climate Dynamics, 2015)

Impact of Identification Method on the Inferred Characteristics and Variability of Australian East Coast Lows - Pepler, Acacia S.; Di Luca, Alejandro; Ji, Fei; Alexander, Lisa V.; Evans, Jason P.; Sherwood, Steven C. (Monthly Weather Review, 2015)
Abstract The Australian east coast low (ECL) is both a major cause of damaging severe weather and an important contributor to rainfall and dam inflow along the east coast, and is of interest to a wide range of groups including catchment managers and emergency services. For this reason, several studies in recent years have developed and interrogated databases of east coast lows using a variety of automated cyclone detection methods and identification criteria. This paper retunes each method so that all yield a similar event frequency within the ECL region, to enable a detailed intercomparison of the similarities, differences, and relative advantages of each method. All methods are shown to have substantial skill at identifying ECL events leading to major impacts or explosive development, but the choice of method significantly affects both the seasonal and interannual variation of detected ECL numbers. This must be taken into consideration in studies on trends or variability in ECLs, with a subcategorization of ECL events by synoptic situation of key importance.

Challenges in the Quest for Added Value of Regional Climate Dynamical Downscaling - Di Luca, Alejandro; De Elía, Ramón; Laprise, René (Current Climate Change Reports, 2015)

Effects of City Expansion on Heat Stress under Climate Change Conditions - Argüeso, Daniel; Evans, Jason P.; Pitman, Andrew J.; Di Luca, Alejandro (PLOS ONE, 2015)

Evaluating the representation of Australian East Coast Lows in a regional climate model ensemble - Di Luca, Alejandro; Evans, Jason; Pepler, Acacia; Alexander, Lisa; Argüeso, Daniel (Journal of Southern Hemisphere Earth System Science, 2016)

Quantifying the overall added value of dynamical downscaling and the contribution from different spatial scales - Di Luca, Alejandro; Argüeso, Daniel; Evans, Jason P.; De Elía, Ramón; Laprise, René (Journal of Geophysical Research: Atmospheres, 2016)
Abstract This study evaluates the added value in the representation of surface climate variables from an ensemble of regional climate model (RCM) simulations by comparing the relative skill of the RCM simulations and their driving data over a wide range of RCM experimental setups and climate statistics. The methodology is specifically designed to compare results across different variables and metrics, and it incorporates a rigorous approach to separate the added value occurring at different spatial scales. Results show that the RCMs' added value strongly depends on the type of driving data, the climate variable, and the region of interest but depends rather weakly on the choice of the statistical measure, the season, and the RCM physical configuration. Decomposing climate statistics according to different spatial scales shows that improvements are coming from the small scales when considering the representation of spatial patterns, but from the large‐scale contribution in the case of absolute values. Our results also show that a large part of the added value can be attained using some simple postprocessing methods. , Key Points A rigorous methodology that allows evaluating the overall benefits of high‐resolution simulations The most reliable source of added value is the better representation of the spatial variability Substantial added value can also be attained using simple postprocessing methods

Evaluation of long-term precipitation and temperature Weather Research and Forecasting simulations for southeast Australia - Ji, F; Evans, Jp; Teng, J; Scorgie, Y; Argüeso, D; Di Luca, A (Climate Research, 2016)

The NARCliM project: model agreement and significance of climate projections - Olson, R; Evans, Jp; Di Luca, A; Argüeso, D (Climate Research, 2016)

Projected changes in east Australian midlatitude cyclones during the 21st century - Pepler, Acacia S.; Di Luca, Alejandro; Ji, Fei; Alexander, Lisa V.; Evans, Jason P.; Sherwood, Steven C. (Geophysical Research Letters, 2016)
Abstract The east coast of Australia is regularly influenced by midlatitude cyclones known as East Coast Lows. These form in a range of synoptic situations and are both a cause of severe weather and an important contributor to water security. This paper presents the first projections of future cyclone activity in this region using a regional climate model ensemble, with the use of a range of cyclone identification methods increasing the robustness of results. While there is considerable uncertainty in projections of cyclone frequency during the warm months, there is a robust agreement on a decreased frequency of cyclones during the winter months, when they are most common in the current climate. However, there is a potential increase in the frequency of cyclones with heavy rainfall and those closest to the coast and accordingly those with potential for severe flooding. , Key Points Winter cyclones are projected to decrease on the Australian east coast Cyclones associated with heavy rainfall may increase in frequency Projections of warm season cyclones remain uncertain

Cyclone contribution to the Mediterranean Sea water budget - Flaounas, E.; Di Luca, A.; Drobinski, P.; Mailler, S.; Arsouze, T.; Bastin, S.; Beranger, K.; Lebeaupin Brossier, C. (Climate Dynamics, 2016)

Precipitation over urban areas in the western Maritime Continent using a convection-permitting model - Argüeso, Daniel; Di Luca, Alejandro; Evans, Jason P. (Climate Dynamics, 2016)

Seasonal mean temperature changes control future heat waves - Argüeso, Daniel; Di Luca, Alejandro; Perkins‐Kirkpatrick, Sarah E.; Evans, Jason P. (Geophysical Research Letters, 2016)
Abstract Increased temperature will result in longer, more frequent, and more intense heat waves. Changes in temperature variability have been deemed necessary to account for future heat wave characteristics. However, this has been quantified only in Europe and North America, while the rest of the globe remains unexplored. Using late century global climate projections, we show that annual mean temperature increases is the key factor defining heat wave changes in most regions. We find that commonly studied areas are an exception rather than the standard and the mean climate change signal generally outweighs any influence from variability changes. More importantly, differences in warming across seasons are responsible for most of the heat wave changes and their consideration relegates the contribution of variability to a marginal role. This reveals that accurately capturing mean seasonal changes is crucial to estimate future heat waves and reframes our interpretation of future temperature extremes. , Key Points The influence of projected temperature variability changes on future heat waves varies across the globe Future heat waves are primarily controlled by annual mean changes, except in Europe and North America Mean seasonal warming is responsible for over 95% of projected heat wave changes in most region

Bias-corrected regional climate projections of extreme rainfall in south-east Australia - Evans, Jason P.; Argueso, D.; Olson, R.; Di Luca, A. (Theoretical and Applied Climatology, 2017)

Trends and low frequency variability of East Coast Lows in the twentieth century - Ji, Fei; Pepler, Acacia; Browning, Stuart; Evans, Jasona; Di Luca, Alejandro (Journal of Southern Hemisphere Earth System Science, 2018)

Australian snowpack in the NARCliM ensemble: evaluation, bias correction and future projections - Luca, Alejandro Di; Evans, Jason P.; Ji, Fei (Climate Dynamics, 2018)

Independently assessing the representation of midlatitude cyclones in high‐resolution reanalyses using satellite observed winds - Pepler, Acacia S.; Di Luca, Alejandro; Evans, Jason P. (International Journal of Climatology, 2018)
ABSTRACT High‐resolution reanalyses offer the potential to improve our understanding of midlatitude cyclones, particularly smaller‐scale systems and those with complex structures. However, previous studies have demonstrated large variations in the frequency and characteristics of Australian midlatitude cyclones between reanalyses when using their native resolution. In this paper we use satellite observations of winds and rainfall in order to evaluate the ability of the ERA‐Interim, JRA55, MERRA and CFSR reanalyses to reproduce Australian east coast cyclones. The MERRA reanalysis produces a large number of erroneous small‐scale lows without cyclonic wind patterns using a simple pressure‐difference‐based cyclone identification and tracking method. Consequently, we recommend the ERA‐Interim reanalysis when using such methods, or applying more complex tracking methods that are able to compensate for these issues.

Projected change in characteristics of near surface temperature inversions for southeast Australia - Ji, Fei; Evans, Jason Peter; Di Luca, Alejandro; Jiang, Ningbo; Olson, Roman; Fita, Lluis; Argüeso, Daniel; Chang, Lisa T.-C.; Scorgie, Yvonne; Riley, Matt (Climate Dynamics, 2019)

Evaluating reanalysis-driven CORDEX regional climate models over Australia: model performance and errors - Di Virgilio, Giovanni; Evans, Jason P.; Di Luca, Alejandro; Olson, Roman; Argüeso, Daniel; Kala, Jatin; Andrys, Julia; Hoffmann, Peter; Katzfey, Jack J.; Rockel, Burkhardt (Climate Dynamics, 2019)

Review of Australian east coast low pressure systems and associated extremes - Dowdy, Andrew J.; Pepler, Acacia; Di Luca, Alejandro; Cavicchia, Leone; Mills, Graham; Evans, Jason P.; Louis, Simon; McInnes, Kathleen L.; Walsh, Kevin (Climate Dynamics, 2019)

Projected changes in vertical temperature profiles for Australasia - Ji, Fei; Evans, Jason P.; Di Virgilio, Giovanni; Nishant, Nidhi; Di Luca, Alejandro; Herold, Nicholas; Downes, Stephanie M.; Tam, Eugene; Beyer, Kathleen (Climate Dynamics, 2020)

Regional Versus Remote Atmosphere‐Ocean Drivers of the Rapid Projected Intensification of the East Australian Current - Bull, Christopher Y. S.; Kiss, Andrew E.; Gupta, Alex Sen; Jourdain, Nicolas C.; Argüeso, Daniel; Di Luca, Alejandro; Sérazin, Guillaume (Journal of Geophysical Research: Oceans, 2020)
Abstract Like many western boundary currents, the East Australian Current (EAC) extension is projected to get stronger and warmer in the future. The CMIP5 multimodel mean (MMM) projection suggests up to 5°C of warming under an RCP85 scenario by 2100. Previous studies employed Sverdrup balance to associate a trend in basin wide zonally integrated wind stress curl (resulting from the multidecadal poleward intensification in the westerly winds over the Southern Ocean) with enhanced transport in the EAC extension. Possible regional drivers are yet to be considered. Here we introduce the NEMO‐OASIS‐WRF coupled regional climate model as a framework to improve our understanding of CMIP5 projections. We analyze a hierarchy of simulations in which the regional atmosphere and ocean circulations are allowed to freely evolve subject to boundary conditions that represent present‐day and CMIP5 RCP8.5 climate change anomalies. Evaluation of the historical simulation shows an EAC extension that is stronger than similar ocean‐only models and observations. This bias is not explained by a linear response to differences in wind stress. The climate change simulations show that regional atmospheric CMIP5 MMM anomalies drive 73% of the projected 12 Sv increase in EAC extension transport whereas the remote ocean boundary conditions and regional radiative forcing (greenhouse gases within the domain) play a smaller role. The importance of regional changes in wind stress curl in driving the enhanced EAC extension is consistent with linear theory where the NEMO‐OASIS‐WRF response is closer to linear transport estimates compared to the CMIP5 MMM. , Plain Language Summary In recent decades, enhanced warming, severe marine heatwaves, and increased transport by the East Australian Current have led to the invasion of nonnative species and the destruction of kelp forests east of Tasmania. The East Australian Current extension is projected to get stronger and warmer in the future. We seek to better understand coupled climate model projections for the Tasman Sea. This is difficult because there is large model diversity and considerable uncertainty as to how and where future changes will occur. In addition, little is known about the possible importance of regional versus large‐scale changes in surface time‐mean winds in driving future circulation changes. Here we use a single limited‐domain ocean‐atmosphere coupled model that takes the average model projections as its inputs and finds that changes in the regional wind stress are most important for the enhanced projected East Australian Current extension. We also find that these projected changes are consistent with simple linear theory and the simulated regional changes in wind stress. , Key Points NEMO‐OASIS‐WRF coupled regional climate model is evaluated and introduced as a new tool for analyzing Tasman Sea climate projections NEMO‐OASIS‐WRF projections suggest that local atmospheric changes drive 73% of the projected 12 Sv increase in EAC extension transport The importance of regional changes in wind stress curl driving the enhanced EAC extension is consistent with linear theory

Realised added value in dynamical downscaling of Australian climate change - Di Virgilio, Giovanni; Evans, Jason P.; Di Luca, Alejandro; Grose, Michael R.; Round, Vanessa; Thatcher, Marcus (Climate Dynamics, 2020)

Future Changes in the Occurrence of Hybrid Cyclones: The Added Value of Cyclone Classification for the East Australian Low‐Pressure Systems - Cavicchia, L.; Pepler, A.; Dowdy, A.; Evans, J.; Di Luca, A.; Walsh, K. (Geophysical Research Letters, 2020)
Abstract Several regions of the world, including the east coast of Australia, are characterized by the occurrence of low‐pressure systems with a range of different dynamical structures, including tropical, extratropical, and hybrid cyclones. Future changes in the occurrence of cyclones are better understood if storms are classified according to their dynamical structure. Therefore, we apply a classification of cyclones according to their cold‐core or warm‐core structure to an ensemble of regional climate model simulations. First, we show that historical simulations reproduce well the reanalysis results in terms of cyclone classification. We then show that once cyclone classification is applied, projections of future cyclone activity become more robust, including a decrease in the occurrence of both cold‐core and warm‐core cyclones. Finally, we show that in a warmer climate warm‐core hybrid cyclone activity could increase close to the coast, while the associated rainfall and wind are projected to increase. , Plain Language Summary Cyclones in the tropics derive their energy from the temperature difference between warm ocean waters and the atmosphere and their interior is warmer than the environment (warm core), while cyclones in the midlatitudes derive their energy from differences in the atmospheric temperature and density at different locations and their interior is colder than the environment (cold core). In subtropical regions both types of cyclone can form. Also in those regions cyclones known as hybrid cyclones form, with mixed tropical‐extratropical features, such as a partial lower tropospheric warm core and a partial upper tropospheric cold core. This study is focused on cyclones along the eastern coast of Australia. Here we show that dividing cyclones in different classes according to their thermal structure provides a better framework to interpret changes in cyclone activity at subtropical latitudes. This study has two main results. First, classifying cyclones adds value to climate projection robustness. A large number of models agree on the decrease in the occurrence of both cold‐core and warm‐core cyclones. The study also indicates increased occurrence of hybrid cyclones close to the Australian coast. Second, the study shows evidence of future changes in cyclone‐related impacts, such as an increase in the associated rainfall. , Key Points A physically based classification of hybrid cyclones is applied to an ensemble of regional climate model simulations The cyclone classification method adds value to the projections of future cyclone activity, making them more robust Results indicate future changes (2060–2079) toward more intense impacts associated with hybrid cyclones

An update of IPCC climate reference regions for subcontinental analysis of climate model data: definition and aggregated datasets - Iturbide, Maialen; Gutiérrez, José M.; Alves, Lincoln M.; Bedia, Joaquín; Cerezo-Mota, Ruth; Cimadevilla, Ezequiel; Cofiño, Antonio S.; Di Luca, Alejandro; Faria, Sergio Henrique; Gorodetskaya, Irina V.; Hauser, Mathias; Herrera, Sixto; et al. (Earth System Science Data, 2020)
Abstract. Several sets of reference regions have been used in the literature for the regional synthesis of observed and modelled climate and climate change information. A popular example is the series of reference regions used in the Intergovernmental Panel on Climate Change (IPCC) Special Report on Managing the Risks of Extreme Events and Disasters to Advance Climate Adaptation (SREX). The SREX regions were slightly modified for the Fifth Assessment Report of the IPCC and used for reporting subcontinental observed and projected changes over a reduced number (33) of climatologically consistent regions encompassing a representative number of grid boxes. These regions are intended to allow analysis of atmospheric data over broad land or ocean regions and have been used as the basis for several popular spatially aggregated datasets, such as the Seasonal Mean Temperature and Precipitation in IPCC Regions for CMIP5 dataset. We present an updated version of the reference regions for the analysis of new observed and simulated datasets (including CMIP6) which offer an opportunity for refinement due to the higher atmospheric model resolution. As a result, the number of land and ocean regions is increased to 46 and 15, respectively, better representing consistent regional climate features. The paper describes the rationale for the definition of the new regions and analyses their homogeneity. The regions are defined as polygons and are provided as coordinates and a shapefile together with companion R and Python notebooks to illustrate their use in practical problems (e.g. calculating regional averages). We also describe the generation of a new dataset with monthly temperature and precipitation, spatially aggregated in the new regions, currently for CMIP5 and CMIP6, to be extended to other datasets in the future (including observations). The use of these reference regions, dataset and code is illustrated through a worked example using scatter plots to offer guidance on the likely range of future climate change at the scale of the reference regions. The regions, datasets and code (R and Python notebooks) are freely available at the ATLAS GitHub repository: https://github.com/SantanderMetGroup/ATLAS (last access: 24 August 2020), https://doi.org/10.5281/zenodo.3998463 (Iturbide et al., 2020).

Assessing the role of the ocean–atmosphere coupling frequency in the western Maritime Continent rainfall - Li, Yue; Gupta, Alex Sen; Taschetto, Andréa S.; Jourdain, Nicolas C.; Di Luca, Alejandro; Done, James M.; Luo, Jing-Jia (Climate Dynamics, 2020)

Global hotspots for the occurrence of compound events - Ridder, Nina N.; Pitman, Andy J.; Westra, Seth; Ukkola, Anna; Do, Hong X.; Bador, Margot; Hirsch, Annette L.; Evans, Jason P.; Di Luca, Alejandro; Zscheischler, Jakob (Nature Communications, 2020)
Abstract Compound events (CEs) are weather and climate events that result from multiple hazards or drivers with the potential to cause severe socio-economic impacts. Compared with isolated hazards, the multiple hazards/drivers associated with CEs can lead to higher economic losses and death tolls. Here, we provide the first analysis of multiple multivariate CEs potentially causing high-impact floods, droughts, and fires. Using observations and reanalysis data during 1980–2014, we analyse 27 hazard pairs and provide the first spatial estimates of their occurrences on the global scale. We identify hotspots of multivariate CEs including many socio-economically important regions such as North America, Russia and western Europe. We analyse the relative importance of different multivariate CEs in six continental regions to highlight CEs posing the highest risk. Our results provide initial guidance to assess the regional risk of CE events and an observationally-based dataset to aid evaluation of climate models for simulating multivariate CEs.

Decomposing Temperature Extremes Errors in CMIP5 and CMIP6 Models - Di Luca, Alejandro; Pitman, Andrew J.; de Elía, Ramón (Geophysical Research Letters, 2020)
Abstract We quantify the skill of Coupled Model Intercomparison Project Phase 5 (CMIP5) and CMIP6 models to represent daily temperature extremes. We find CMIP models systematically exaggerate the magnitude of daily temperature anomalies for both cold and hot extremes. We assess the contribution to a daily temperature extreme from four terms: the long‐term mean annual cycle, the diurnal cycle, synoptic variability, and seasonal variability for both cold and hot extremes. These four terms are combined, and the overall performance of individual climate models assessed. This identifies those models that can simulate temperature extremes well and simulate them well for the right reasons. The new error metric shows that increases in horizontal resolution usually lead to a better performance particularly for the coarser resolution models. The CMIP6 improvements relative to CMIP5 are systematic across most land regions and are only partially explained by the increase in horizontal resolution, and other differences must therefore help explain the higher CMIP6 skill. , Key Points CMIP5 and CMIP6 models exaggerate the magnitude of daily temperature anomalies for hot days and cold nights extremes Higher‐resolution models improve the simulation of temperature extremes largely due to better simulation of synoptic scales CMIP6 outperforms the simulation of temperature extremes compared to CMIP5 beyond the benefits given by the higher resolution

Contribution of mean climate to hot temperature extremes for present and future climates - Di Luca, Alejandro; De Elía, Ramón; Bador, Margot; Argüeso, Daniel (Weather and Climate Extremes, 2020)

East Australian Cyclones and Air‐Sea Feedbacks - Sérazin, G.; Di Luca, A.; Sen Gupta, A.; Rogé, M.; Jourdain, N. C.; Argüeso, D.; Bull, C. Y. S. (Journal of Geophysical Research: Atmospheres, 2021)
Abstract The importance of resolving mesoscale air‐sea interactions to represent cyclones impacting the East Coast of Australia, the so‐called East Coast Lows (ECLs), is investigated using the Australian Regional Coupled Model based on NEMO‐OASIS‐WRF (NOW) at resolution. The fully coupled model is shown to be capable of reproducing correctly relevant features such as the seasonality, spatial distribution and intensity of ECLs while it partially resolves mesoscale processes, such as air‐sea feedbacks over ocean eddies and fronts. The mesoscale thermal feedback (TFB) and the current feedback (CFB) are shown to influence the intensity of northern ECLs (north of ), with the TFB modulating the pre‐storm sea surface temperature (SST) by shifting ECL locations eastwards and the CFB modulating the wind stress. By fully uncoupling the atmospheric model of NOW, the intensity of northern ECLs is increased due to the absence of the cold wake that provides a negative feedback to the cyclone. The number of ECLs might also be affected by the air‐sea feedbacks but large interannual variability hampers significant results with short‐term simulations. The TFB and CFB modify the climatology of SST (mean and variability) but no direct link is found between these changes and those noticed in ECL properties. These results show that the representation of ECLs, mainly north of , depend on how air‐sea feedbacks are simulated. This is particularly important for atmospheric downscaling of climate projections as small‐scale SST interactions and the effects of ocean currents are not accounted for. , Plain Language Summary Air‐sea interactions occur at a variety of spatial scales, including those of the size of ocean eddies. Such interactions are partially resolved in the Australian Regional Coupled Model used to simulate the cyclones impacting the East Coast of Australia, the so‐called East Coast Lows (ECLs). The effect of different feedbacks between the ocean and the atmosphere, including those due to mechanical and thermal exchanges over ocean eddies, are tested on the properties of ECLs. Significant effects are found on the intensity of ECLs north of , with also potential effects on the number of ECLs. The air‐sea feedbacks modify the climatology of sea surface temperature, with no direct link to ECL changes. Such experiments eventually demonstrate that small‐scale air‐sea feedbacks may matter for representing current Australian climate and its change in the future. , Key Points High‐resolution regional coupled modeling can simulate key features of East Australian cyclones Cyclone intensity is sensitive to mechanical and thermal air‐sea feedbacks at mesoscales Coupled and atmosphere‐only models mainly differ in simulating cyclone properties north of

Evaluating Precipitation Errors Using the Environmentally Conditioned Intensity‐Frequency Decomposition Method - Di Luca, A.; Argüeso, D.; Sherwood, S.; Evans, J. P. (Journal of Advances in Modeling Earth Systems, 2021)
Abstract A fundamental issue when evaluating the simulation of precipitation is the difficulty of quantifying specific sources of errors and recognizing compensation of errors. We assess how well a large ensemble of high‐resolution simulations represents the precipitation associated with strong cyclones. We propose a framework to breakdown precipitation errors according to different dynamical (vertical velocity) and thermodynamical (vertically integrated water vapor) regimes and the frequency and intensity of precipitation. This approach approximates the error in the total precipitation of each regime as the sum of three terms describing errors in the large‐scale environmental conditions, the frequency of precipitation and its intensity. We show that simulations produce precipitation too often, that its intensity is too weak, that errors are larger for weak than for strong dynamical forcing and that biases in the vertically integrated water vapor can be large. Using the error breakdown presented above, we define four new error metrics differing on the degree to which they include the compensation of errors. We show that convection‐permitting simulations consistently improve the simulation of precipitation compared to coarser‐resolution simulations using parameterized convection, and that these improvements are revealed by our new approach but not by traditional metrics which can be affected by compensating errors. These results suggest that convection‐permitting models are more likely to produce better results for the right reasons. We conclude that the novel decomposition and error metrics presented in this study give a useful framework that provides physical insights about the sources of errors and a reliable quantification of errors. , Plain Language Summary The simulations of complex physical processes always entail various sources of errors. These errors can be of different sign and can consequently cancel each other out when using traditional performance metrics such as the bias error metric. We present a formal framework that allows us to approximate precipitation according to three terms that describe different aspects of the rainfall field including large‐scale environmental conditions and the frequency and intensity of rainfall. We apply the methodology to a large ensemble of high‐resolution simulations representing the precipitation associated with strong cyclones in eastern Australia. We show that simulations produce precipitation too often, with an intensity that is too weak leading to strong compensation. We further define new error metrics that explicitly quantify the degree of error compensation when simulating precipitation. We show that convection‐permitting simulations consistently improve the performance compared to coarser resolution simulations using parameterized convection and that these improvements are only revealed when using the new error metrics but are not apparent in traditional metrics (e.g., bias). , Key Points Multiple high‐resolution simulations produce precipitation too often with underestimated intensity leading to strong error compensation Errors in precipitation are quantified using novel metrics that prevent error compensation showing value compared with traditional metrics Convection permitting simulations outperform the representation of precipitation compared to simulations using parameterized convection

Mechanisms for Extreme Precipitation Changes in a Tropical Archipelago - Argüeso, Daniel; Luca, A. Di; Jourdain, N. C.; Romero, R.; Homar, V. (Journal of Climate, 2022)
Abstract The Maritime Continent is one of the most challenging regions for atmospheric models. Processes that modulate deep convection are poorly represented in models, which affects their ability to simulate precipitation features accurately. Thus, future projections of precipitation over the region are prone to large uncertainties. One of the key players in modeling tropical precipitation is the convective representation, and hence convection-permitting experiments have contributed to improve aspects of precipitation in models. This improvement creates opportunities to explore the physical processes that govern rainfall in the Maritime Continent, as well as their role in a warming climate. Here, we examine the response to climate change of models with explicit and parameterized convection and how that reflects in precipitation changes. We focus on the intensification of spatial contrasts as precursors of changes in mean and extreme precipitation in the tropical archipelago. Our results show that the broad picture is similar in both model setups, where islands will undergo an increase in mean and extreme precipitation in a warmer climate and the ocean will see less rain. However, the magnitude and spatial structure of such changes, as well as the projection of rainfall percentiles, are different across model experiments. We suggest that while the primary effect of climate change is thermodynamical and it is similarly reproduced by both model configurations, dynamical effects are represented quite differently in explicit and parameterized convection experiments. In this study, we link such differences to horizontal and vertical spatial contrasts and how convective representations translate them into precipitation changes.

Seasonality of Continental Extratropical‐Cyclone Wind Speeds Over Northeastern North America - Chen, Ting‐Chen; Di Luca, Alejandro; Winger, Katja; Laprise, René; Thériault, Julie M. (Geophysical Research Letters, 2022)
Abstract This study investigates the seasonality of near‐surface wind speeds associated with extratropical cyclones (ETCs) over northeastern North America using a global reanalysis data set during 1979–2020. As opposed to most studies that emphasize winter storms, ETCs during the fall exhibit significantly stronger 10‐m winds over this region due to the slightly stronger continental cyclones and significantly weaker low‐level stability during that time of the year. Also, ETCs favor inland lakes and Hudson Bay during the low‐ice‐content fall season, leading to lower surface roughness. Combining these results, we derive simple linear regressions to predict the 10‐m wind speed given three variables: 850‐hPa wind speed, low‐level Richardson number, and surface roughness length. This formula captures the observed seasonality and serves as a valuable tool for cyclone near‐surface wind risk assessment. , Plain Language Summary Extratropical cyclones can bring powerful winds that can cause severe damage to infrastructure. We find that cyclones with severe winds are the most frequent in the fall season over continental northeastern North America. Three reasons are found responsible: stronger continental cyclones, weaker low‐level atmospheric stability, and the lower surface roughness over lakes and Hudson Bay, where cyclones frequently occur in fall. A simple formula that can effectively assess the near‐surface wind speeds associated with cyclones is derived based on these results. , Key Points Extratropical‐cyclone‐associated 10‐m wind speeds are the strongest in the fall season over northeastern North America Besides stronger continental cyclones and 850‐hPa winds, weaker low‐level stability in fall favors stronger 10‐m wind speeds in this region Linear regression using 850‐hPa wind, Richardson number, and surface roughness well predicts cyclones' 10‐m wind speeds and seasonality

On the Intercontinental Transferability of Regional Climate Model Response to Severe Forestation - Asselin, Olivier; Leduc, Martin; Paquin, Dominique; Di Luca, Alejandro; Winger, Katja; Bukovsky, Melissa; Music, Biljana; Giguère, Michel (Climate, 2022)
The biogeophysical effects of severe forestation are quantified using a new ensemble of regional climate simulations over North America and Europe. Following the protocol outlined for the Land-Use and Climate Across Scales (LUCAS) intercomparison project, two sets of simulations are compared, FOREST and GRASS, which respectively represent worlds where all vegetation is replaced by trees and grasses. Three regional climate models were run over North America. One of them, the Canadian Regional Climate Model (CRCM5), was also run over Europe in an attempt to bridge results with the original LUCAS ensemble, which was confined to Europe. Overall, the CRCM5 response to forestation reveals strong inter-continental similarities, including a pronounced wintertime and springtime warming concentrated over snow-masking evergreen forests. Crucially, these northern evergreen needleleaf forests populate lower, hence sunnier, latitudes in North America than in Europe. Snow masking reduces albedo similarly over both continents, but stronger insolation amplifies the net shortwave radiation and hence warming simulated over North America. In the summertime, CRCM5 produces a mixed response to forestation, with warming over northern needleleaf forests and cooling over southern broadleaf forests. The partitioning of the turbulent heat fluxes plays a major role in determining this response, but it is not robust across models over North America. Implications for the inter-continental transferability of the original LUCAS results are discussed.

Rapid Warming in the Australian Alps from Observation and NARCliM Simulations - Ji, Fei; Nishant, Nidhi; Evans, Jason P.; Di Luca, Alejandro; Di Virgilio, Giovanni; Cheung, Kevin K. W.; Tam, Eugene; Beyer, Kathleen; Riley, Matthew L. (Atmosphere, 2022)
The Australian Alps are the highest mountain range in Australia, which are important for biodiversity, energy generation and winter tourism. Significant increases in temperature in the past decades has had a huge impact on biodiversity and ecosystem in this region. In this study, observed temperature is used to assess how temperature changed over the Australian Alps and surrounding areas. We also use outputs from two generations of NARCliM (NSW and Australian Regional Climate Modelling) to investigate spatial and temporal variation of future changes in temperature and its extremes. The results show temperature increases faster for the Australian Alps than the surrounding areas, with clear spatial and temporal variation. The changes in temperature and its extremes are found to be strongly correlated with changes in albedo, which suggests faster warming in cool season might be dominated by decrease in albedo resulting from future changes in natural snowfall and snowpack. The warming induced reduction in future snow cover in the Australian Alps will have a significant impact on this region.

Evaluation of ERA5 precipitation and 10‐m wind speed associated with extratropical cyclones using station data over North America - Chen, Ting‐Chen; Collet, François; Di Luca, Alejandro (International Journal of Climatology, 2024)
Abstract While the ERA5 reanalysis is commonly utilized in climate studies on extratropical cyclones (ETCs), only a few studies have quantified its ability in the representation of ETCs over land. To address this gap, this study evaluates ERA5's skill in representing the ETC‐associated 10‐m wind speed and the precipitation in central and eastern North America during 2005–2019. Hourly data collected from ~3000 stations, amounting to around 420 million reports stored in the Integrated Surface Database, is used as reference. For the spatial‐averaged ETC properties, ERA5 shows a good skill for wind speed with normalized mean bias (NMB) of −0.7% and normalized root‐mean‐square error (NRMSE) of 14.3%, despite a tendency to overestimate low winds and underestimate high winds. The ERA5 skill is worse for precipitation than for wind speed with NMB of −10.4% and NRMSE of 56.5% and a strong tendency to underestimate high values. For both variables, the best and worst performance is found in DJF and JJA, respectively. Negative biases are often identified over regions with stronger precipitation/wind speeds, and a systematic underestimation of wind speed is found over the Rockies with complex topography. Compared to the averaged ETCs, ERA5's performance deteriorates for the top 5% extreme ETCs with a stronger tendency to underestimate both wind speed and precipitation (NMB of −10.2% and −22.6%, respectively). Furthermore, ERA5's skill is worse for local extreme values within ETCs than for spatial averages. Our results highlight some important limitations of the ERA5 reanalysis products for studies looking at the possible impacts of ETCs.

Uncertainty and outliers in high‐resolution gridded precipitation products over eastern North America - Picart, Tangui; Di Luca, Alejandro; Laprise, René (International Journal of Climatology, 2024)
Abstract Several observational precipitation products that provide high temporal (≤3 h) and spatial (≤0.25°) resolution gridded estimates are available, although no single product can be assumed worldwide to be closest to the (unknown) “reality.” Here, we propose and apply a methodology to quantify the uncertainty of a set of precipitation products and to identify, at individual grid points, the products that are likely wrong (i.e., outliers). The methodology is applied over eastern North America for the 2015–2019 period for eight high‐resolution gridded precipitation products: CMORPH, ERA5, GSMaP, IMERG, MSWEP, PERSIANN, STAGE IV and TMPA. Four difference metrics are used to quantify discrepancies in different aspects of the precipitation time series, such as the total accumulation, two characteristics of the intensity‐frequency distribution, and the timing of precipitating events. Large regional and seasonal variations in the observational uncertainty are found across the ensemble. The observational uncertainty is higher in Canada than in the United States, reflecting large differences in the density of precipitation gauge measurements. In northern midlatitudes, the uncertainty is highest in winter, demonstrating the difficulties of satellite retrieval algorithms in identifying precipitation in snow‐covered areas. In southern midlatitudes, the uncertainty is highest in summer, probably due to the more discontinuous nature of precipitation. While the best product cannot be identified due to the lack of an absolute reference, our study is able to identify products that are likely wrong and that should be excluded depending on the specific application.

Spatial spin-up of precipitation in limited-area convection-permitting simulations over North America using the CRCM6/GEM5.0 model - Roberge, François; Di Luca, Alejandro; Laprise, René; Lucas-Picher, Philippe; Thériault, Julie (Geoscientific Model Development, 2024)
Abstract. A fundamental issue associated with the dynamical downscaling technique using limited-area models is related to the presence of a “spatial spin-up” belt close to the lateral boundaries where small-scale features are only partially developed. Here, we introduce a method to identify the distance from the border that is affected by the spatial spin-up (i.e., the spatial spin-up distance) of the precipitation field in convection-permitting model (CPM) simulations. Using a domain over eastern North America, this new method is applied to several simulations that differ on the nesting approach (single or double nesting) and the 3-D variables used to drive the CPM simulation. Our findings highlight three key points. Firstly, when using a single nesting approach, the spin-up distance from lateral boundaries can extend up to 300 km (around 120 CPM grid points), varying across seasons, boundaries and driving variables. Secondly, the greatest spin-up distances occur in winter at the western and southern boundaries, likely due to strong atmospheric inflow during these seasons. Thirdly, employing a double nesting approach with a comprehensive set of microphysical variables to drive CPM simulations offers clear advantages. The computational gains from reducing spatial spin-up outweigh the costs associated with the more demanding intermediate simulation of the double nesting. These results have practical implications for optimizing CPM simulation configurations, encompassing domain selection and driving strategies.

Extratropical storms induce carbon outgassing over the Southern Ocean - Carranza, Magdalena M.; Long, Matthew. C.; Di Luca, Alejandro; Fassbender, Andrea J.; Johnson, Kenneth S.; Takeshita, Yui; Mongwe, Precious; Turner, Katherine E. (npj Climate and Atmospheric Science, 2024)
Abstract The strength and variability of the Southern Ocean carbon sink is a significant source of uncertainty in the global carbon budget. One barrier to reconciling observations and models is understanding how synoptic weather patterns modulate air-sea carbon exchange. Here, we identify and track storms using atmospheric sea level pressure fields from reanalysis data to assess the role that storms play in driving air-sea CO 2 exchange. We examine the main drivers of CO 2 fluxes under storm forcing and quantify their contribution to Southern Ocean annual air-sea CO 2 fluxes. Our analysis relies on a forced ocean-ice simulation from the Community Earth System Model, as well as CO 2 fluxes estimated from Biogeochemical Argo floats. We find that extratropical storms in the Southern Hemisphere induce CO 2 outgassing, driven by CO 2 disequilibrium. However, this effect is an order of magnitude larger in observations compared to the model and caused by different reasons. Despite large uncertainties in CO 2 fluxes and storm statistics, observations suggest a pivotal role of storms in driving Southern Ocean air-sea CO 2 outgassing that remains to be well represented in climate models, and needs to be further investigated in observations.

How Can Municipalities in British Columbia and Quebec Contribute to Flood Risk Reduction? - Deschamps, Bernard; Bourdeau-Brien, Michael; Boudreault, Mathieu (Institute on Municipal Finance and Governance, 2023)
Flood-related losses are on the rise in Canada and private insurance remains costly or unavailable in high-risk areas. Despite the introduction of overland flood insurance in 2015, following the federal government’s invitation to the insurance industry to participate in flood risk-sharing, federal and provincial disaster financial assistance programs still cover a large portion of these costs. As the risks increase, governments are questioning the sustainability of using taxpayers’ money to finance such losses, leaving municipalities with significant residual risk. The growing number of people and assets occupying flood-prone areas, including public infrastructure, has contributed to the sharp increase in flood damage costs. Based on a literature review and discussions with experts, this paper describes the municipal role in flood-risk management, and shows how provincial and federal financial assistance to municipalities for flood damage in British Columbia and Québec may be counterproductive in fostering flood-risk management at the municipal level. We conclude that municipalities can play a more proactive role in incorporating risk reduction as the key objective of disaster financial assistance and propose three specific policy instruments to help reduce the growing number of people living in flood zones: flood mapping, land-use planning, and the relocation of high-risk properties.

On a risk model with dependence between interclaim arrivals and claim sizes - Boudreault, Mathieu; Cossette, Hélène; Landriault, David; Marceau, Etienne (Scandinavian Actuarial Journal, 2006)

Multivariate Models of Equity Returns for Investment Guarantees Valuation - Boudreault, Mathieu; Panneton, Christian-Marc (North American Actuarial Journal, 2009)

An Out-of-Sample Analysis of Investment Guarantees for Equity-Linked Products: Lessons from the Financial Crisis of the Late 2000s - Augustyniak, Maciej; Boudreault, Mathieu (North American Actuarial Journal, 2012)

Recovery rate risk and credit spreads in a hybrid credit risk model - Boudreault, Mathieu; Gauthier, Geneviève; Thomassin, Tommy (The Journal of Credit Risk, 2013)

Contagion effect on bond portfolio risk measures in a hybrid credit risk model - Boudreault, Mathieu; Gauthier, Geneviève; Thomassin, Tommy (Finance Research Letters, 2014)

Risk models with dependence between claim occurrences and severities for Atlantic hurricanes - Boudreault, Mathieu; Cossette, Hélène; Marceau, Étienne (Insurance: Mathematics and Economics, 2014)

Changes in large-scale controls of Atlantic tropical cyclone activity with the phases of the Atlantic multidecadal oscillation - Caron, Louis-Philippe; Boudreault, Mathieu; Bruyère, Cindy L. (Climate Dynamics, 2015)

On the Variability and Predictability of Eastern Pacific Tropical Cyclone Activity* - Caron, Louis-Philippe; Boudreault, Mathieu; Camargo, Suzana J. (Journal of Climate, 2015)
Abstract Variability in tropical cyclone activity in the eastern Pacific basin has been linked to a wide range of climate factors, yet the dominant factors driving this variability have yet to be identified. Using Poisson regressions and a track clustering method, the authors analyze and compare the climate influence on cyclone activity in this region. The authors show that local sea surface temperature and upper-ocean heat content as well as large-scale conditions in the northern Atlantic are the dominant influence in modulating eastern North Pacific tropical cyclone activity. The results also support previous findings suggesting that the influence of the Atlantic Ocean occurs through changes in dynamical conditions over the eastern Pacific. Using model selection algorithms, the authors then proceed to construct a statistical model of eastern Pacific tropical cyclone activity. The various model selection techniques used agree in selecting one predictor from the Atlantic (northern North Atlantic sea surface temperature) and one predictor from the Pacific (relative sea surface temperature) to represent the best possible model. Finally, we show that this simple model could have predicted the anomalously high level of activity observed in 2014.

Estimation of correlations in portfolio credit risk models based on noisy security prices - Boudreault, Mathieu; Gauthier, Geneviève; Thomassin, Tommy (Journal of Economic Dynamics and Control, 2015)

Mitigating Interest Rate Risk in Variable Annuities: An Analysis of Hedging Effectiveness under Model Risk - Augustyniak, Maciej; Boudreault, Mathieu (North American Actuarial Journal, 2017)

Reanalysis of climate influences on Atlantic tropical cyclone activity using cluster analysis - Boudreault, Mathieu; Caron, Louis‐Philippe; Camargo, Suzana J. (Journal of Geophysical Research: Atmospheres, 2017)
Abstract We analyze, using Poisson regressions, the main climate influences on North Atlantic tropical cyclone activity. The analysis is performed using not only various time series of basin‐wide storm counts but also various series of regional clusters, taking into account shortcomings of the hurricane database through estimates of missing storms. The analysis confirms that tropical cyclones forming in different regions of the Atlantic are susceptible to different climate influences. We also investigate the presence of trends in these various time series, both at the basin‐wide and cluster levels, and show that, even after accounting for possible missing storms, there remains an upward trend in the eastern part of the basin and a downward trend in the western part. Using model selection algorithms, we show that the best model of Atlantic tropical cyclone activity for the recent past is constructed using Atlantic sea surface temperature and upper tropospheric temperature, while for the 1878–2015 period, the chosen covariates are Atlantic sea surface temperature and El Niño–Southern Oscillation. We also note that the presence of these artificial trends can impact the selection of the best covariates. If the underlying series shows an upward trend, then the mean Atlantic sea surface temperature captures both interannual variability and the upward trend, artificial or not. The relative sea surface temperature is chosen instead for stationary counts. Finally, we show that the predictive capability of the statistical models investigated is low for U.S. landfalling hurricanes but can be considerably improved when forecasting combinations of clusters whose hurricanes are most likely to make landfall. , Key Points Estimates of missing storms are not sufficient to account for the increase in hurricane activity in the eastern tropical Atlantic Recent upward trends, artificial or not, affect the selection of key determinants of tropical cyclone activity, especially the SST variable Despite previous results to that effect, the May–June NAO does not provide predictive skill for Atlantic landfalling hurricanes

Firm-specific credit risk estimation in the presence of regimes and noisy prices - Bégin, Jean-François; Boudreault, Mathieu; Gauthier, Geneviève (Finance Research Letters, 2017)

Maximum Likelihood Estimation of the Markov-Switching GARCH Model Based on a General Collapsing Procedure - Augustyniak, Maciej; Boudreault, Mathieu; Morales, Manuel (Methodology and Computing in Applied Probability, 2018)

Impact of reanalysis boundary conditions on downscaled Atlantic hurricane activity - Baudouin, Jean-Philippe; Caron, Louis-Philippe; Boudreault, Mathieu (Climate Dynamics, 2019)

Maximum likelihood estimation of first-passage structural credit risk models correcting for the survivorship bias - Amaya, Diego; Boudreault, Mathieu; McLeish, Don L. (Journal of Economic Dynamics and Control, 2019)

Credit and Systemic Risks in the Financial Services Sector: Evidence From the 2008 Global Crisis - Bégin, Jean‐François; Boudreault, Mathieu; Doljanu, Delia Alexandra; Gauthier, Geneviève (Journal of Risk and Insurance, 2019)
Abstract We develop a portfolio credit risk model that includes firm‐specific Markov‐switching regimes as well as individual stochastic and endogenous recovery rates. Using weekly credit default swap premiums for 35 financial firms, we analyze the credit risk of each of these companies and their statistical linkages, putting emphasis on the 2005–2012 period. Moreover, we study the systemic risk affecting both the banking and insurance subsectors.

Pricing Flood Insurance with a Hierarchical Physics-Based Model - Boudreault, Mathieu; Grenier, Patrick; Pigeon, Mathieu; Potvin, Jean-Mathieu; Turcotte, Richard (North American Actuarial Journal, 2020)

Limite à vie sur les inondations successives : vers un nouveau pacte social ? - Boudreault, Mathieu; Bourdeau-Brien, Michaël (Assurances et gestion des risques, 2020)
Après les nombreuses crues printanières qui ont affecté le sud du Québec depuis 2011, le gouvernement du Québec a annoncé en avril 2019 une refonte importante de son programme d’aide financière aux sinistrés. Le programme introduit désormais une couverture limitée à vie de 100 000 $ pour les inondations successives, une mesure unique au Canada. L’objectif de cet article est d’analyser le coût des inondations successives et les impacts financiers de cette limite de couverture pour les ménages.

Likelihood Evaluation of Jump-Diffusion Models Using Deterministic Nonlinear Filters - Bégin, Jean-François; Boudreault, Mathieu (Journal of Computational and Graphical Statistics, 2021)

A Global Flood Risk Modeling Framework Built With Climate Models and Machine Learning - Carozza, David A.; Boudreault, Mathieu (Journal of Advances in Modeling Earth Systems, 2021)
Abstract Large scale flood risk analyses are fundamental to many applications requiring national or international overviews of flood risk. While large‐scale climate patterns such as teleconnections and climate change become important at this scale, it remains a challenge to represent the local hydrological cycle over various watersheds in a manner that is physically consistent with climate. As a result, global models tend to suffer from a lack of available scenarios and flexibility that are key for planners, relief organizations, regulators, and the financial services industry to analyze the socioeconomic, demographic, and climatic factors affecting exposure. Here we introduce a data‐driven, global, fast, flexible, and climate‐consistent flood risk modeling framework for applications that do not necessarily require high‐resolution flood mapping. We use statistical and machine learning methods to examine the relationship between historical flood occurrence and impact from the Dartmouth Flood Observatory (1985–2017), and climatic, watershed, and socioeconomic factors for 4,734 HydroSHEDS watersheds globally. Using bias‐corrected output from the NCAR CESM Large Ensemble (1980–2020), and the fitted statistical relationships, we simulate 1 million years of events worldwide along with the population displaced in each event. We discuss potential applications of the model and present global flood hazard and risk maps. The main value of this global flood model lies in its ability to quickly simulate realistic flood events at a resolution that is useful for large‐scale socioeconomic and financial planning, yet we expect it to be useful to climate and natural hazard scientists who are interested in socioeconomic impacts of climate. , Plain Language Summary Flood is among the deadliest and most damaging natural disasters. To protect against large scale flood risk, stakeholders need to understand how floods can occur and their potential impacts. Stakeholders rely on global flood models to provide them with plausible flood scenarios around the world. For a flood model to operate at the global scale, climate effects must be represented in addition to hydrological ones to demonstrate how rivers can overflow throughout the world each year. Global flood models often lack the flexibility and variety of scenarios required by many stakeholders because they are computationally demanding. Designed for applications where detailed local flood impacts are not required, we introduce a rapid and flexible global flood model that can generate hundreds of thousands of scenarios everywhere in the world in a matter of minutes. The model is based on a historical flood database from 1985 to 2017 that is represented using an algorithm that learns from the data. With this model, the output from a global climate model is used to simulate a large sample of floods for risk analyses that are coherent with global climate. Maps of the annual average number of floods and number of displaced people illustrate the models results. , Key Points We present a global flood model built using machine learning methods fitted with historical flood occurrences and impacts Forced with a climate model, the global flood model is fast, flexible and consistent with global climate We provide global flood hazard (occurrence) and risk (population displaced) maps over 4,734 watersheds

Gridded flood depth estimates from satellite-derived inundations - Bryant, Seth; McGrath, Heather; Boudreault, Mathieu (Natural Hazards and Earth System Sciences, 2022)
Abstract. Canada's RADARSAT missions improve the potential to study past flood events; however, existing tools to derive flood depths from this remote-sensing data do not correct for errors, leading to poor estimates. To provide more accurate gridded depth estimates of historical flooding, a new tool is proposed that integrates Height Above Nearest Drainage and Cost Allocation algorithms. This tool is tested against two trusted, hydraulically derived, gridded depths of recent floods in Canada. This validation shows the proposed tool outperforms existing tools and can provide more accurate estimates from minimal data without the need for complex physics-based models or expert judgement. With improvements in remote-sensing data, the tool proposed here can provide flood researchers and emergency managers accurate depths in near-real time.

Ratemaking territories and adverse selection for flood insurance - Boudreault, Mathieu; Ojeda, Angelica (Insurance: Mathematics and Economics, 2022)

On the Measurement of Hedging Effectiveness for Long-Term Investment Guarantees - Augustyniak, Maciej; Badescu, Alexandru; Boudreault, Mathieu (Journal of Risk and Financial Management, 2023)
Although the finance literature has devoted a lot of research into the development of advanced models for improving the pricing and hedging performance, there has been much less emphasis on approaches to measure dynamic hedging effectiveness. This article discusses a statistical framework based on regression analysis to measure the effectiveness of dynamic hedges for long-term investment guarantees. The importance of taking model risk into account is emphasized. The difficulties in reducing hedging risk to an appropriately low level lead us to propose a new perspective on hedging, and recognize it as a tool to modify the risk–reward relationship of the unhedged position.

Global Asymmetries in the Influence of ENSO on Flood Risk Based on 1,600 Years of Hybrid Simulations - Del Rio Amador, L.; Boudreault, M.; Carozza, D. A. (Geophysical Research Letters, 2023)
Abstract El Niño‐Southern Oscillation (ENSO) is often considered as a source of long‐term predictability for extreme events via its teleconnection patterns. However, given that its characteristic cycle varies from two to 7 years, it is difficult to obtain statistically significant conclusions based on observational periods spanning only a few decades. To overcome this, we apply the global flood risk modeling framework developed by Carozza and Boudreault to an equivalent of 1,600 years of bias‐corrected General Circulation Model outputs. The results show substantial anomalies in flood occurrences and impacts for El Niño and La Niña when compared to the all‐year baseline. We were able to obtain a larger global coverage of statistically significant results than previous studies limited to observational data. Asymmetries in anomalies for both ENSO phases show a larger global influence of El Niño than La Niña on flood hazard and risk. , Plain Language Summary El Niño‐Southern Oscillation (ENSO) is one of the most important global climate phenomena. It is well‐known to affect precipitation and temperature in many areas of the world. It is therefore very important for researchers (environmental and climate sciences, economics, etc.), risk managers, decision‐ and policy‐makers to understand the influence of ENSO on flooding. Previous studies analyzed the link between ENSO and flooding but because they were based upon 40 years of data, a lot of uncertainties remained as to how ENSO has any significance on flooding. In this study, we use outputs from a climate model large ensemble that provides 1,600 years of simulated data to determine the impacts of ENSO on flooding. But because it is very difficult to run traditional flood models on 1,600 years of data, we rather leverage a machine learning approach to accelerate computations in a context where the focus is on socioeconomic impacts. We find that ENSO is a significant driver of flooding in more regions than what was previously found. Finally, there appears to be a greater global influence of El Niño than La Niña on flooding. , Key Points We simulated an equivalent of 1,600 years of realistic flood events globally using a statistical model forced with climate model outputs We found a statistically significant ( α = 0.05) influence of El Niño‐Southern Oscillation (ENSO) over 55% of land area for flood occurrence and over 69% for flood impact Asymmetries in anomalies for both ENSO phases show a larger global influence of El Niño than La Niña on flood hazard and risk

Comparison of three flood-related relocation programs with probabilistic cost-benefit analyses - Boudreault, Mathieu; Bourdeau-Brien, Michael; Milot, Nicolas (International Journal of Disaster Risk Reduction, 2023)

Leveraging prices from credit and equity option markets for portfolio risk management - Bégin, Jean‐François; Boudreault, Mathieu; Thériault, Mathieu (Journal of Futures Markets, 2024)
Abstract This study presents a firm‐specific methodology for extracting implied default intensities and recovery rates jointly from unit recovery claim prices—backed by out‐of‐the‐money put options—and credit default swap premiums, therefore providing time‐varying and market‐consistent views of credit risk at the individual level. We apply the procedure to about 400 firms spanning different sectors of the US economy between 2003 and 2019. The main determinants of default intensities and recovery rates are analyzed with statistical and machine learning methods linking default risk and credit losses to market, sector, and individual variables. Consistent with the literature, we find that individual volatility, leverage, and corporate bond market determinants are key factors explaining the implied default intensities and recovery rates. Then, we apply the framework in the context of credit risk management in applications, like, market‐consistent credit value‐at‐risk calculation and stress testing.

UQAM‐TCW: A Global Hybrid Tropical Cyclone Wind Model Based Upon Statistical and Coupled Climate Models - Carozza, David A.; Boudreault, Mathieu; Grenier, Manuel; Caron, Louis‐Philippe (Journal of Advances in Modeling Earth Systems, 2024)
Abstract Tropical cyclones (TCs) are among the most destructive natural hazards and yet, quantifying their financial impacts remains a significant methodological challenge. It is therefore of high societal value to synthetically simulate TC tracks and winds to assess potential impacts along with their probability distributions for example, land use planning and financial risk management. A common approach to generate TC tracks is to apply storm detection methodologies to climate model output, but such an approach is sensitive to the method and parameterization used and tends to underestimate intense TCs. We present a global TC model (the UQAM‐TCW model thereafter) that melds statistical modeling, to capture historical risk features, with a climate model large ensemble, to generate large samples of physically coherent TC seasons. Integrating statistical and physical methods, the model is probabilistic and consistent with the physics of how TCs develop. The model includes frequency and location of cyclogenesis, full trajectories with maximum sustained winds and the entire wind structure along each track for the six typical cyclogenesis basins from IBTrACS. Being an important driver of TCs globally, we also integrate ENSO effects in key components of the model. The global TC model thus belongs to a recent strand of literature that combines probabilistic and physical approaches to TC track generation. As an application of the model, we show global hazard maps for direct and indirect hits expressed in terms of return periods. The global TC model can be of interest to climate and environmental scientists, economists and financial risk managers. , Plain Language Summary Tropical cyclones (TCs) are among the most destructive natural hazards and yet, quantifying their financial impacts remains a difficult task. Being able to randomly simulate TCs and their features (such as wind speed) with mathematical models is therefore critical to build scenarios (and their corresponding probability) for land use planning and financial risk management. A common approach is to simulate TCs by tracking them directly in climate model outputs but this often underestimates the frequency of intense TCs while being computationally costly overall to generate a large number of events. For these reasons, many authors have looked into alternative approaches that replicate key physical features of TCs but rather using statistical models that are much less computationally demanding. This paper therefore presents a global TC model that leverages the strengths of both statistical and climate models to simulate a large number of TCs whose features are consistent with the physics and observations. As an important global phenomenon that affects TCs globally, we also integrate in our model the effects of El Niño. The paper focuses on the methodology and validation of each model component and concludes with global hazard maps for direct and indirect hits. , Key Points We present a global tropical cyclone (TC) wind model built upon a climate model large ensemble that can be used for risk analysis We integrate ENSO into our model since it is a strong driver of storm annual frequency, cyclogenesis, trajectories, and intensity We present global hazard maps consistent with statistical features of TC components and coherent with a global climate model

A Simulation and Empirical Study of the Maximum Likelihood Estimator for Stochastic Volatility Jump-Diffusion Models - Bégin, Jean-François; Boudreault, Mathieu (Studies in Nonlinear Dynamics & Econometrics, 2024)
Abstract We investigate the behaviour of the maximum likelihood estimator (MLE) for stochastic volatility jump-diffusion models commonly used in financial risk management. A simulation study shows the practical conditions under which the MLE behaves according to theory. In an extensive empirical study based on nine indices and more than 6000 individual stocks, we nonetheless find that the MLE is unable to replicate key higher moments. We then introduce a moment-targeted MLE – robust to model misspecification – and revisit both simulation and empirical studies. We find it performs better than the MLE, improving the management of financial risk.

Projected seasonal flooding in Canada under climate change with statistical and machine learning - Grenier, Manuel; Boudreault, Jérémie; Raymond, Sébastien; Boudreault, Mathieu (Journal of Hydrology: Regional Studies, 2024)

A data science approach to climate change risk assessment applied to pluvial flood occurrences for the United States and Canada - Bourget, Mathilde; Boudreault, Mathieu; Carozza, David A.; Boudreault, Jérémie; Raymond, Sébastien (ASTIN Bulletin, 2024)
Abstract There is mounting pressure on (re)insurers to quantify the impacts of climate change, notably on the frequency and severity of claims due to weather events such as flooding. This is however a very challenging task for (re)insurers as it requires modeling at the scale of a portfolio and at a high enough spatial resolution to incorporate local climate change effects. In this paper, we introduce a data science approach to climate change risk assessment of pluvial flooding for insurance portfolios over Canada and the United States (US). The underlying flood occurrence model quantifies the financial impacts of short-term (12–48 h) precipitation dynamics over the present (2010–2030) and future climate (2040–2060) by leveraging statistical/machine learning and regional climate models. The flood occurrence model is designed for applications that do not require street-level precision as is often the case for scenario and trend analyses. It is applied at the full scale of Canada and the US over 10–25 km grids. Our analyses show that climate change and urbanization will typically increase losses over Canada and the US, while impacts are strongly heterogeneous from one state or province to another, or even within a territory. Portfolio applications highlight the importance for a (re)insurer to differentiate between future changes in hazard and exposure, as the latter may magnify or attenuate the impacts of climate change on losses.

Flood occurrence and impact models for socioeconomic applications over Canada and the United States - Grenier, Manuel; Boudreault, Mathieu; Carozza, David A.; Boudreault, Jérémie; Raymond, Sébastien (Natural Hazards and Earth System Sciences, 2024)
Abstract. Large-scale socioeconomic studies of the impacts of floods are difficult and costly for countries such as Canada and the United States due to the large number of rivers and size of watersheds. Such studies are however very important for analyzing spatial patterns and temporal trends to inform large-scale flood risk management decisions and policies. In this paper, we present different flood occurrence and impact models based upon statistical and machine learning methods of over 31 000 watersheds spread across Canada and the US. The models can be quickly calibrated and thereby easily run predictions over thousands of scenarios in a matter of minutes. As applications of the models, we present the geographical distribution of the modelled average annual number of people displaced due to flooding in Canada and the US, as well as various scenario analyses. We find for example that an increase of 10 % in average precipitation yields an increase in the displaced population of 18 % in Canada and 14 % in the US. The model can therefore be used by a broad range of end users ranging from climate scientists to economists who seek to translate climate and socioeconomic scenarios into flood probabilities and impacts measured in terms of the displaced population.

A Global Multi-Source Tropical Cyclone Precipitation (MSTCP) Dataset - Morin, Gabriel; Boudreault, Mathieu; García-Franco, Jorge L. (Scientific Data, 2024)
Abstract A global tropical cyclone precipitation dataset covering the period from January 1979 to February 2023 is presented. Global precipitation estimates were taken from the newly developed high-resolution Multi-Source Weighted-Ensemble Precipitation, version 2 (MSWEP V2) and TC tracks were obtained from the International Best Track Archive for Climate Stewardship (IBTrACS) dataset. This Global Multi-Source Tropical Cyclone Precipitation (MSTCP) dataset is comprised of two main products and files in the format of tables: the main and profile datasets. The main file provides various TCP statistics per TC track, including mean and maximum precipitation rates over a fixed and symmetrical radius of 500 km. The profile dataset comprises the azimuthally averaged precipitation every 10-km away from the center of each storm (until 500 km). The case study of Hurricane Harvey is used to show that MSWEP estimates agree well with another commonly used satellite product. The main statistics of the dataset are analyzed as well, including the differences in the dataset metrics for each of the six TC basins and for each Saffir-Simpson category for storm intensity.

Contributing Factors to Residential Flood Damage in Canada - Deschamps, Bernard; Boudreault, Mathieu; Gachon, Philippe (2023)

Retrieving cloud optical depth and ice particle size using thermal and Far infrered radiometry in an Arctic environment - Blanchard, Yann; Royer, Alain; O'neill, Norman T.; Blanchet, Jean-Pierre (2009 IEEE International Geoscience and Remote Sensing Symposium, 2009)

Study of polar thin ice clouds and aerosols seen by CloudSat and CALIPSO during midwinter 2007 - Grenier, Patrick; Blanchet, Jean‐Pierre; Muñoz‐Alpizar, Rodrigo (Journal of Geophysical Research: Atmospheres, 2009)
Data sets from CloudSat radar reflectivity and CALIPSO lidar backscattering measurements provide a new regard on Arctic and Antarctic winter cloud systems, as well as on the way aerosols determine their formation and evolution. Especially, links between the cloud ice crystal size and the surrounding aerosol field may be further investigated. In this study, the satellite observations are used to heuristically separate polar thin ice clouds into two crystal size categories, and an aerosol index based on the attenuated backscattering and color ratio of the sampled volumes is used for identifying haze in cloud‐free regions. Statistics from 386 Arctic satellite overpasses during January 2007 and from 379 overpasses over Antarctica during July 2007 reveal that sectors with the highest proportion of thin ice clouds having large ice crystals at their top are those for which the aerosol index is highest. Moreover, a weak but significant correlation between the cloud top ice effective radius and the above‐cloud aerosol index suggests that more polluted clouds tend to have higher ice effective radius, in 10 of the 11 sectors investigated. These results are interpreted in terms of a sulphate‐induced freezing inhibition effect.

Investigation of the sulphate‐induced freezing inhibition effect from CloudSat and CALIPSO measurements - Grenier, Patrick; Blanchet, Jean‐Pierre (Journal of Geophysical Research: Atmospheres, 2010)
The hypothesis according to which higher sulphate concentrations favor ice clouds made of larger ice crystals is tested using data sets from the CloudSat and Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) satellites. This is a potential consequence of the sulphate‐induced freezing inhibition (SIFI) effect, namely, the hypothesis that sulphates contribute to inhibit the onset of ice crystal formation by deactivating ice‐forming nuclei during Arctic winter. A simple index based on the backscattering at 532 nm and the color ratio from the CALIPSO lidar measurements is compared against in situ sulphate concentration time series and used as a proxy for this variable. An algorithm using the lidar data and the CloudSat radar microphysical retrievals is also developed for identifying cloud types, focusing on those supposedly favored by the SIFI effect. The analysis includes the effect of the lidar off‐nadir angle on the sulphate index and the cloud classification, the validation of the index, as well as the production of circum‐Arctic maps of the sulphate index and of the SIFI‐favored clouds fraction. The increase of the lidar off‐nadir angle is shown to cause an increase in the measured depolarization ratio and hence in the ability to detect ice crystals. The index correlates positively with both sulphates and sea salt concentrations, with a Pearson correlation coefficient ( ) varying from 0.10 to 0.42 for the different comparisons performed. Ultimate findings are the results of two correlation tests of the SIFI effect, which allow for a new outlook on its possible role in the Arctic troposphere during winter.

On the relationship between Arctic ice clouds and polluted air masses over the North Slope of Alaska in April 2008 - Jouan, C.; Pelon, J.; Girard, E.; Ancellet, G.; Blanchet, J. P.; Delanoë, J. (Atmospheric Chemistry and Physics, 2014)
Abstract. Recently, two types of ice clouds (TICs) properties have been characterized using the Indirect and Semi-Direct Aerosol Campaign (ISDAC) airborne measurements (Alaska, April 2008). TIC-2B were characterized by fewer (< 10 L−1) and larger (> 110 μm) ice crystals, and a larger ice supersaturation (> 15%) compared to TIC-1/2A. It has been hypothesized that emissions of SO2 may reduce the ice nucleating properties of ice nuclei (IN) through acidification, resulting in a smaller concentration of larger ice crystals and leading to precipitation (e.g., cloud regime TIC-2B). Here, the origin of air masses forming the ISDAC TIC-1/2A (1 April 2008) and TIC-2B (15 April 2008) is investigated using trajectory tools and satellite data. Results show that the synoptic conditions favor air masses transport from three potential SO2 emission sources into Alaska: eastern China and Siberia where anthropogenic and biomass burning emissions, respectively, are produced, and the volcanic region of the Kamchatka/Aleutians. Weather conditions allow the accumulation of pollutants from eastern China and Siberia over Alaska, most probably with the contribution of acidic volcanic aerosol during the TIC-2B period. Observation Monitoring Instrument (OMI) satellite observations reveal that SO2 concentrations in air masses forming the TIC-2B were larger than in air masses forming the TIC-1/2A. Airborne measurements show high acidity near the TIC-2B flight where humidity was low. These results support the hypothesis that acidic coating on IN could be at the origin of the formation of TIC-2B.

Challenges in operating an Arctic telescope - Ivanescu, Liviu; Baibakov, Konstantin; O'Neill, Norman T.; Blanchet, Jean-Pierre; Blanchard, Yann; Saha, Auromeet; Rietze, Martin; Schulz, Karl-Heinz (SPIE Astronomical Telescopes + Instrumentation, 2014)

Spatio-temporal models to estimate daily concentrations of fine particulate matter in Montreal: Kriging with external drift and inverse distance-weighted approaches - Ramos, Yuddy; St-Onge, Benoît; Blanchet, Jean-Pierre; Smargiassi, Audrey (Journal of Exposure Science & Environmental Epidemiology, 2016)

Towards the Thin Ice Clouds in the Far-InfraRed Experiment (TICFIRE) - Libois, Quentin; Blanchet, Jean-Pierre; Proulx, Christian; Ivanescu, Liviu; Pelletier, Ludovick S. (Hyperspectral Imaging and Sounding of the Environment, 2016)

Spatial modeling of daily concentrations of ground-level ozone in Montreal, Canada: A comparison of geostatistical approaches - Ramos, Yuddy; Requia, Weeberb J.; St-Onge, Benoît; Blanchet, Jean-Pierre; Kestens, Yan; Smargiassi, Audrey (Environmental Research, 2018)

Overview paper: New insights into aerosol and climate in the Arctic - Abbatt, Jonathan P. D.; Leaitch, W. Richard; Aliabadi, Amir A.; Bertram, Allan K.; Blanchet, Jean-Pierre; Boivin-Rioux, Aude; Bozem, Heiko; Burkart, Julia; Chang, Rachel Y. W.; Charette, Joannie; Chaubey, Jai P.; Christensen, Robert J.; et al. (Atmospheric Chemistry and Physics, 2019)
Abstract. Motivated by the need to predict how the Arctic atmosphere will change in a warming world, this article summarizes recent advances made by the research consortium NETCARE (Network on Climate and Aerosols: Addressing Key Uncertainties in Remote Canadian Environments) that contribute to our fundamental understanding of Arctic aerosol particles as they relate to climate forcing. The overall goal of NETCARE research has been to use an interdisciplinary approach encompassing extensive field observations and a range of chemical transport, earth system, and biogeochemical models. Several major findings and advances have emerged from NETCARE since its formation in 2013. (1) Unexpectedly high summertime dimethyl sulfide (DMS) levels were identified in ocean water (up to 75 nM) and the overlying atmosphere (up to 1 ppbv) in the Canadian Arctic Archipelago (CAA). Furthermore, melt ponds, which are widely prevalent, were identified as an important DMS source (with DMS concentrations of up to 6 nM and a potential contribution to atmospheric DMS of 20 % in the study area). (2) Evidence of widespread particle nucleation and growth in the marine boundary layer was found in the CAA in the summertime, with these events observed on 41 % of days in a 2016 cruise. As well, at Alert, Nunavut, particles that are newly formed and grown under conditions of minimal anthropogenic influence during the months of July and August are estimated to contribute 20 % to 80 % of the 30–50 nm particle number density. DMS-oxidation-driven nucleation is facilitated by the presence of atmospheric ammonia arising from seabird-colony emissions, and potentially also from coastal regions, tundra, and biomass burning. Via accumulation of secondary organic aerosol (SOA), a significant fraction of the new particles grow to sizes that are active in cloud droplet formation. Although the gaseous precursors to Arctic marine SOA remain poorly defined, the measured levels of common continental SOA precursors (isoprene and monoterpenes) were low, whereas elevated mixing ratios of oxygenated volatile organic compounds (OVOCs) were inferred to arise via processes involving the sea surface microlayer. (3) The variability in the vertical distribution of black carbon (BC) under both springtime Arctic haze and more pristine summertime aerosol conditions was observed. Measured particle size distributions and mixing states were used to constrain, for the first time, calculations of aerosol–climate interactions under Arctic conditions. Aircraft- and ground-based measurements were used to better establish the BC source regions that supply the Arctic via long-range transport mechanisms, with evidence for a dominant springtime contribution from eastern and southern Asia to the middle troposphere, and a major contribution from northern Asia to the surface. (4) Measurements of ice nucleating particles (INPs) in the Arctic indicate that a major source of these particles is mineral dust, likely derived from local sources in the summer and long-range transport in the spring. In addition, INPs are abundant in the sea surface microlayer in the Arctic, and possibly play a role in ice nucleation in the atmosphere when mineral dust concentrations are low. (5) Amongst multiple aerosol components, BC was observed to have the smallest effective deposition velocities to high Arctic snow (0.03 cm s−1).

A new parameterization of ice heterogeneous nucleation coupled to aerosol chemistry in WRF-Chem model version 3.5.1: evaluation through ISDAC measurements - Keita, Setigui Aboubacar; Girard, Eric; Raut, Jean-Christophe; Leriche, Maud; Blanchet, Jean-Pierre; Pelon, Jacques; Onishi, Tatsuo; Cirisan, Ana (Geoscientific Model Development, 2020)
Abstract. In the Arctic, during polar night and early spring, ice clouds are separated into two leading types of ice clouds (TICs): (1) TIC1 clouds characterized by a large concentration of very small crystals and TIC2 clouds characterized by a low concentration of large ice crystals. Using a suitable parameterization of heterogeneous ice nucleation is essential for properly representing ice clouds in meteorological and climate models and subsequently understanding their interactions with aerosols and radiation. Here, we describe a new parameterization for ice crystal formation by heterogeneous nucleation in water-subsaturated conditions coupled to aerosol chemistry in the Weather Research and Forecasting model coupled with chemistry (WRF-Chem). The parameterization is implemented in the Milbrandt and Yau (2005a, b) two-moment cloud microphysics scheme, and we assess how the WRF-Chem model responds to the run-time interaction between chemistry and the new parameterization. Well-documented reference cases provided us with in situ data from the spring 2008 Indirect and Semi-Direct Aerosol Campaign (ISDAC) over Alaska. Our analysis reveals that the new parameterization clearly improves the representation of the ice water content (IWC) in polluted or unpolluted air masses and shows the poor performance of the reference parameterization in representing ice clouds with low IWC. The new parameterization is able to represent TIC1 and TIC2 microphysical characteristics at the top of the clouds, where heterogenous ice nucleation is most likely occurring, even with the known bias of simulated aerosols by WRF-Chem over the Arctic.

Accuracy in starphotometry - Ivănescu, Liviu; Baibakov, Konstantin; O'Neill, Norman T.; Blanchet, Jean-Pierre; Schulz, Karl-Heinz (Atmospheric Measurement Techniques, 2021)
Abstract. Starphotometry, the night-time counterpart of sunphotometry, has not yet achieved the commonly sought observational error level of 1 %: a spectral optical depth (OD) error level of 0.01. In order to address this issue, we investigate a large variety of systematic (absolute) uncertainty sources. The bright-star catalogue of extraterrestrial references is noted as a major source of errors with an attendant recommendation that its accuracy, particularly its spectral photometric variability, be significantly improved. The small field of view (FOV) employed in starphotometry ensures that it, unlike sun- or moonphotometry, is only weakly dependent on the intrinsic and artificial OD reduction induced by scattering into the FOV by optically thin clouds. A FOV of 45 arcsec (arcseconds) was found to be the best trade-off for minimizing such forward-scattering errors concurrently with flux loss through vignetting. The importance of monitoring the sky background and using interpolation techniques to avoid spikes and to compensate for measurement delay was underscored. A set of 20 channels was identified to mitigate contamination errors associated with stellar and terrestrial atmospheric gas absorptions, as well as aurora and airglow emissions. We also note that observations made with starphotometers similar to our High Arctic instrument should be made at high angular elevations (i.e. at air masses less than 5). We noted the significant effects of snow crystal deposition on the starphotometer optics, how pseudo OD increases associated with this type of contamination could be detected, and how proactive techniques could be employed to avoid their occurrence in the first place. If all of these recommendations are followed, one may aspire to achieve component errors that are well below 0.01: in the process, one may attain a total 0.01 OD target error.

Central Role of Nitrogen Fertilizer Relative to Water Management in Determining Direct Nitrous Oxide Emissions From Global Rice‐Based Ecosystems - Song, Hanxiong; Zhu, Qiuan; Blanchet, Jean‐Pierre; Chen, Zhi; Zhang, Kerou; Li, Tong; Zhou, Feng; Peng, Changhui (Global Biogeochemical Cycles, 2023)
Abstract The increasing atmospheric nitrous oxide (N 2 O) concentration stems from the development of agriculture. However, N 2 O emissions from global rice‐based ecosystems have not been explicitly and systematically quantified. Therefore, this study aims to estimate the spatiotemporal magnitudes of the N 2 O emissions from global rice‐based ecosystems and determine different contribution factors by improving a process‐based biogeochemical model, TRIPLEX‐GHG v2.0. Model validation suggested that the modeled N 2 O agreed well with field observations under varying management practices at daily, seasonal, and annual steps. Simulated N 2 O emissions from global rice‐based ecosystems exhibited significant increasing trends from 0.026 ± 0.0013 to 0.18 ± 0.003 TgN yr −1 from 1910 to 2020, with ∼69.5% emissions attributed to the rice‐growing seasons. Irrigated rice ecosystems accounted for a majority of global rice N 2 O emissions (∼76.9%) because of their higher N 2 O emission rates than rainfed systems. Regarding spatial analysis, Southern China, Northeast India, and Southeast Asia are hotspots for rice‐based N 2 O emissions. Experimental scenarios revealed that N fertilizer is the largest global rice‐N 2 O source, especially since the 1960s (0.047 ± 0.010 TgN yr −1 , 35.24%), while the impact of expanded irrigation plays a minor role. Overall, this study provides a better understanding of the rice‐based ecosystem in the global agricultural N 2 O budget; further, it quantitively demonstrated the central role of N fertilizer in rice‐based N 2 O emissions by including rice crop calendars, covering non‐rice growing seasons, and differentiating the effects of various water regimes and input N forms. Our findings emphasize the significance of co‐management of N fertilizer and water regimes in reducing the net climate impact of global rice cultivation. , Plain Language Summary Nitrous oxide (N 2 O) is a greenhouse gas with ∼300 times greater effect on climate warming than carbon dioxide. Global croplands represent the largest source of anthropogenic N 2 O emissions. However, the contribution of global rice‐based cropping ecosystems to the N 2 O budget remains largely uncertain because of inconsistent observed results. Inspired by the increasing availability of reliable global data sets, we improved and applied a process‐based biogeochemical model by describing the dynamics of various microbial activities to simulate N 2 O emissions from rice‐based ecosystems on a global scale. Model simulations showed that 0.18 million tons of N 2 O‐N were emitted from global rice‐based N 2 O emissions in the 2010s, which was five times larger than that in the 1910s. In the context of regional contribution, southern China, northern India, and Southeast Asia are responsible for more than 80% of the total emissions during 1910–2020. Results suggest that N fertilizer is the most important rice‐N 2 O source quantitively and that increasing irrigation exerts a buffering effect. This study confirmed the potential mitigating effect of co‐managing N fertilizer and irrigation on mitigating rice‐based N 2 O emissions globally. , Key Points N 2 O emissions from global rice‐based ecosystem increased from 0.026 to 0.18 TgN yr −1 between 1910 and 2020 Irrigated rice‐based ecosystems showed larger N 2 O fluxes than rainfed rice globally due to higher N fertilizer use and frequent aerations N fertilizer represents the largest N 2 O source, and co‐management of N fertilizer and flooding regimes is important for mitigation

Contribution of the Order Ericales to Improving Paleoclimate Reconstructions - Wei, Gang; Peng, Changhui; Zhu, Qiuan; Zhou, Xiaolu; Liu, Weiguo (Sustainability, 2022)
Paleobotanists have long built leaf climate models based on site mean of leaf physiognomic characteristics of woody dicotyledons species (WDS) for estimating past climate. To explore the potential of the order Ericales in estimating paleoclimate, we developed two linear models for each climatic factor. One is based on WDS, and the other is based on both WDS and leaf physiognomic characters of the order Ericales (WDS-E). We found that, compared with WDS models, WDS-E models improved greatly in mean annual precipitation (MAP), growing season precipitation (GSP) and mean annual range in temperature (MART). When the minimum species number of the order Ericales is three per site, the WDS-E models improved the r2 from 0.64 to 0.78 for MART, from 0.23 to 0.61 for ln(MAP), and from 0.37 to 0.64 for ln(GSP) compared with the WDS models. For mean annual temperature (MAT), the WDS-E model (r2 = 0.86) also exhibited a moderate improvement in precision over the WDS model (r2 = 0.82). This study demonstrates that other patterns, such as those of the order Ericales, can contribute additional information towards building more precise paleoclimate models.

Contribution of Incorporating the Phosphorus Cycle into TRIPLEX-CNP to Improve the Quantification of Land Carbon Cycle - Ding, Juhua; Zhu, Qiuan; Li, Hanwei; Zhou, Xiaolu; Liu, Weiguo; Peng, Changhui (Land, 2022)
Phosphorus (P) is a key and a limiting nutrient in ecosystems and plays an important role in many physiological and biochemical processes, affecting both terrestrial ecosystem productivity and soil carbon storage. However, only a few global land surface models have incorporated P cycle and used to investigate the interactions of C-N-P and its limitation on terrestrial ecosystems. The overall objective of this study was to integrate the P cycle and its interaction with carbon (C) and nitrogen (N) into new processes model of TRIPLEX-CNP. In this study, key processes of the P cycle, including P pool sizes and fluxes in plant, litter, and soil were integrated into a new model framework, TRIPLEX-CNP. We also added dynamic P:C ratios for different ecosystems. Based on sensitivity analysis results, we identified the phosphorus resorption coefficient of leaf (rpleaf) as the most influential parameter to gross primary productivity (GPP) and biomass, and determined optimal coefficients for different plant functional types (PFTs). TRIPLEX-CNP was calibrated with 49 sites and validated against 116 sites across eight biomes globally. The results suggested that TRIPLEX-CNP performed well on simulating the global GPP and soil organic carbon (SOC) with respective R2 values of 0.85 and 0.78 (both p < 0.01) between simulated and observed values. The R2 of simulation and observation of total biomass are 0.67 (p < 0.01) by TRIPLEX-CNP. The overall model performance had been improved in global GPP, total biomass and SOC after adding the P cycle comparing with the earlier version. Our work represents the promising step toward new coupled ecosystem process models for improving the quantifications of land carbon cycle and reducing uncertainty.

Improving a Process-Based Model to Simulate Forest Carbon Allocation under Varied Stand Density - Jiao, Wenxing; Wang, Weifeng; Peng, Changhui; Lei, Xiangdong; Ruan, Honghua; Li, Haikui; Yang, Yanrong; Grabarnik, Pavel; Shanin, Vladimir (Forests, 2022)
Carbon allocation is an important mechanism through which plants respond to environmental changes. To enhance our understanding of maximizing carbon uptake by controlling planting densities, the carbon allocation module of a process-based model, TRIPLEX-Management, was modified and improved by introducing light, soil water, and soil nitrogen availability factors to quantify the allocation coefficients for different plant organs. The modified TRIPLEX-Management model simulation results were verified against observations from northern Jiangsu Province, China, and then the model was used to simulate dynamic changes in forest carbon under six density scenarios (200, 400, 600, 800, 1000, and 1200 stems ha−1). The mean absolute errors between the predicted and observed variables of the mean diameter at breast height, mean height, and estimated aboveground biomass ranged from 15.0% to 26.6%, and were lower compared with the original model simulated results, which ranged from 24.4% to 60.5%. The normalized root mean square errors ranged from 0.2 to 0.3, and were lower compared with the original model simulated results, which ranged from 0.3 to 0.6. The Willmott index between the predicted and observed variables also varied from 0.5 to 0.8, indicating that the modified TRIPLEX-Management model could accurately simulate the dynamic changes in poplar (Populus spp.) plantations with different densities in northern Jiangsu Province. The density scenario results showed that the leaf and fine root allocation coefficients decreased with the increase in stand density, while the stem allocation increased. Overall, our study showed that the optimum stand density (approximately 400 stems ha−1) could reach the highest aboveground biomass for poplar stands and soil organic carbon storage, leading to higher ecological functions related to carbon sequestration without sacrificing wood production in an economical way in northern Jiangsu Province. Therefore, reasonable density control with different soil and climate conditions should be recommended to maximize carbon sequestration.

The Importance of Energy Theory in Shaping Elevational Species Richness Patterns in Plants - Jiang, Zihan; Liu, Qiuyu; Xu, Wei; Peng, Changhui (Biology, 2022)
Many hypotheses have been proposed to explain elevational species richness patterns; however, evaluating their importance remains a challenge, as mountains that are nested within different biogeographic regions have different environmental attributes. Here, we conducted a comparative study for trees, shrubs, herbs, and ferns along the same elevational gradient for 22 mountains worldwide, examining the performance of hypotheses of energy, tolerance, climatic variability, and spatial area to explain the elevational species richness patterns for each plant group. Results show that for trees and shrubs, energy-related factors exhibit greater explanatory power than other factors, whereas the factors that are associated with climatic variability performed better in explaining the elevational species richness patterns of herbs and ferns. For colder mountains, energy-related factors emerged as the main drivers of woody species diversity, whereas in hotter and wetter ecosystems, temperature and precipitation were the most important predictors of species richness along elevational gradients. For herbs and ferns, the variation in species richness was less than that of woody species. These findings provide important evidence concerning the generality of the energy theory for explaining the elevational species richness pattern of plants, highlighting that the underlying mechanisms may change among different growth form groups and regions within which mountains are nested.

Temporal and Spatial Variation of Wetland CH4 Emissions from the Qinghai–Tibet Plateau under Future Climate Change Scenarios - Zhang, Xian; Wang, Jieyi; Zhang, Jiang; Chen, Huai; Peng, Changhui; Zhu, Qiuan (Atmosphere, 2022)
Wetlands are an important natural source of methane (CH4), so it is important to quantify how their emissions may vary under future climate change conditions. The Qinghai–Tibet Plateau contains more than a third of China’s wetlands. Here, we simulated temporal and spatial variation in CH4 emissions from natural wetlands on the Qinghai–Tibet Plateau from 2008 to 2100 under Representative Concentration Pathways (RCP) 2.6, 4.5, and 8.5. Based on the simulation results of the TRIPLEX-GHG model forced with data from 24 CMIP5 models of global climate, we predict that, assuming no change in wetland distribution on the Plateau, CH4 emissions from natural wetlands will increase by 35%, 98% and 267%, respectively, under RCP 2.6, 4.5 and 8.5. The predicted increase in atmospheric CO2 concentration will contribute 10–28% to the increased CH4 emissions from wetlands on the Plateau by 2100. Emissions are predicted to be majorly in the range of 0 to 30.5 g C m−2·a−1 across the Plateau and higher from wetlands in the southern region of the Plateau than from wetlands in central or northern regions. Under RCP8.5, the methane emissions of natural wetlands on the Qinghai–Tibet Plateau increased much more significantly than that under RCP2.6 and RCP4.5.

Weak impact of nutrient enrichment on peat: Evidence from physicochemical properties - Li, Tong; Yuan, Xin; Ge, Leming; Cao, Chenhao; Suo, Yuchen; Bu, Zhao-Jun; Peng, Changhui; Song, Hanxiong; Liu, Ziping; Liu, Shasha; Wang, Meng (Frontiers in Ecology and Evolution, 2022)
Atmospheric deposition of nitrogen (N) and phosphorus (P) far exceeding the pre-industrial levels have the potential to change carbon (C) dynamics in northern peatlands. However, the responses of soil C concentration and organo-chemical composition to different rates and durations of nutrient enrichment are still unclear. Here, we compared the short- (3 years) and long-term (10 years) effects of N and P fertilizations on the physicochemical properties of peat and porewater in a bog-fen complex in northern China. Our results showed that the short-term fertilization increased Sphagnum moss cover, while the expansion of vascular plants was observed owing to the long-term fertilization. The preserved soil C did not vary considerably after the short- and long-term fertilizations. The harsh soil conditions may impede the decomposition of organic matters by soil microorganisms during the short-term fertilization. For the long-term fertilization, the input of high-phenolic litters owing to vascular plant expansion likely exerted an important control on soil C dynamics. These processes constrained the variation in soil C concentrations when the addition rate and cumulative amount of external N and P increased, which will advance our understanding and prediction of the resilience of soil C storage to imbalanced nutrient enrichment of N and P in northern peatlands.

The Severe Multi-Day October 2019 Snow Storm Over Southern Manitoba, Canada - Hanesiak, John; Stewart, Ronald; Painchaud-Niemi, Dylan; Milrad, Shawn; Liu, George; Vieira, Michael; Theriault, Julie; Cholette, Melissa; Ziolkowski, Kyle (Atmosphere-Ocean, 2022)

Boundary Layer and Shallow Cumulus Clouds in a Medium-Range Forecast of a Large-Scale Weather System - Bélair, Stéphane; Mailhot, Jocelyn; Girard, Claude; Vaillancourt, Paul (Monthly Weather Review, 2005)
Abstract The role and impact that boundary layer and shallow cumulus clouds have on the medium-range forecast of a large-scale weather system is discussed in this study. A mesoscale version of the Global Environmental Multiscale (GEM) atmospheric model is used to produce a 5-day numerical forecast of a midlatitude large-scale weather system that occurred over the Pacific Ocean during February 2003. In this version of GEM, four different schemes are used to represent (i) boundary layer clouds (including stratus, stratocumulus, and small cumulus clouds), (ii) shallow cumulus clouds (overshooting cumulus), (iii) deep convection, and (iv) nonconvective clouds. Two of these schemes, that is, the so-called MoisTKE and Kuo Transient schemes for boundary layer and overshooting cumulus clouds, respectively, have been recently introduced in GEM and are described in more detail. The results show that GEM, with this new cloud package, is able to represent the wide variety of clouds observed in association with the large-scale weather system. In particular, it is found that the Kuo Transient scheme is mostly responsible for the shallow/intermediate cumulus clouds in the rear portion of the large-scale system, whereas MoisTKE produces the low-level stratocumulus clouds ahead of the system. Several diagnostics for the rear portion of the system reveal that the role of MoisTKE is mainly to increase the vertical transport (diffusion) associated with the boundary layer clouds, while Kuo Transient is acting in a manner more consistent with convective stabilization. As a consequence, MoisTKE is not able to remove the low-level shallow cloud layer that is incorrectly produced by the GEM nonconvective condensation scheme. Kuo Transient, in contrast, led to a significant reduction of these nonconvective clouds, in better agreement with satellite observations. This improved representation of stratocumulus and cumulus clouds does not have a large impact on the overall sea level pressure patterns of the large-scale weather system. Precipitation in the rear portion of the system, however, is found to be smoother when MoisTKE is used, and significantly less when the Kuo Transient scheme is switched on.

Ocean Productivity in the Gulf of Cadiz Over the Last 50 kyr - Penaud, A.; Eynaud, F.; Etourneau, J.; Bonnin, J.; De Vernal, A.; Zaragosi, S.; Kim, J.‐H.; Kang, S.; Gal, J.‐K.; Oliveira, D.; Waelbroeck, C. (Paleoceanography and Paleoclimatology, 2022)
Abstract Reconstructions of ocean primary productivity (PP) help to explain past and present biogeochemical cycles and climate changes in the oceans. We document PP variations over the last 50 kyr in a currently oligotrophic subtropical region, the Gulf of Cadiz. Data combine refined results from previous investigations on dinocyst assemblages, alkenones, and stable isotopes ( 18 O, 13 C) in planktonic ( Globigerina bulloides ) and endobenthic ( Uvigerina mediterranea ) foraminifera from cores MD04‐2805 CQ and MD99‐2339, with new isotopic measurements on epibenthic ( Cibicides pachyderma ‐ Cibicidoides wuellerstorfi ) foraminifera and dinocyst‐based estimates of PP using the new n = 1,968 modern database. We constrain PP variations and export production by integrating qualitative information from bioindicators with dinocyst‐based quantitative reconstructions such as PP and seasonal sea surface temperature and information about remineralization from the benthic Δδ 13 C (difference between epibenthic and endobenthic foraminiferal δ 13 C signatures). This study also includes new information on alkenone‐based SST and total organic carbon which provides insights into the relationship between past regional hydrological activity and PP regime change. We show that PP, carbon export, and remineralization were generally high in the NE subtropical Atlantic Ocean during the last glacial period and that the Last Glacial Maximum (LGM) had lower Δδ 13 C than the Heinrich Stadials with sustained high PP, likely allowing enhanced carbon sequestration. We link these PP periods to the dynamics of upwelling, active almost year‐round during sadials, but restricted to spring‐summer during interstadials and LGM, like today. During interstadials, nutrient advection through freshwater inputs during autumn‐winter needs also to be considered to fully understand PP regimes. , Key Points Productivity (PP) in the Gulf of Cadiz is dependent on the seasonality control for both upwelling and nutrient‐enriched freshwater inputs We show generally high PP, carbon export, and remineralization during the last glacial period at the study site The Last Glacial Maximum had lower Δδ 13 C than the Heinrich Stadials with sustained high PP likely allowing enhanced carbon sequestration

Carbon emission limits required to satisfy future representative concentration pathways of greenhouse gases: ALLOWABLE FUTURE CARBON EMISSIONS - Arora, V. K.; Scinocca, J. F.; Boer, G. J.; Christian, J. R.; Denman, K. L.; Flato, G. M.; Kharin, V. V.; Lee, W. G.; Merryfield, W. J. (Geophysical Research Letters, 2011)

The signal of climate changes over the last two millennia in the Gulf of St. Lawrence, eastern Canada - Wu, Xiner; De Vernal, Anne; Fréchette, Bianca; Moros, Matthias; Perner, Kerstin (Quaternary Research, 2022)
Abstract Climate changes over the past two millennia in the central part of the Gulf of St. Lawrence are documented in this paper with the aim of determining and understanding the natural climate variability and the impact of anthropogenic forcing at a regional scale. The palynological content (dinocysts, pollen, and spores) of the composite marine sediment core MSM46-03 collected in the Laurentian Channel was used to reconstruct oceanographic and climatic changes with a multidecadal temporal resolution. Sea-surface conditions, including summer salinity and temperature, sea-ice cover, and primary productivity, were reconstructed from dinocyst assemblages. Results revealed a remarkable cooling trend of about 4°C after 1230 cal yr BP (720 CE) and a culmination with a cold pulse dated to 170–40 cal yr BP (1780–1910 CE), which likely corresponds to the regional signal of the Little Ice Age. This cold interval was followed by a rapid warming of about 3°C. In the pollen assemblages, the decrease of Pinus abundance over the past 1700 yr suggests changes in wind regimes, likely resulting from increased southerly incursions of cold and dry Arctic air masses into southeastern Canada.

Pacific walrus diet across 4000 years of changing sea ice conditions - Clark, Casey T.; Horstmann, Lara; De Vernal, Anne; Jensen, Anne M.; Misarti, Nicole (Quaternary Research, 2022)
Abstract Declining sea ice is expected to change the Arctic's physical and biological systems in ways that are difficult to predict. This study used stable isotope compositions (δ 13 C and δ 15 N) of archaeological, historic, and modern Pacific walrus ( Odobenus rosmarus divergens ) bone collagen to investigate the impacts of changing sea ice conditions on walrus diet during the last ~4000 yr. An index of past sea ice conditions was generated using dinocyst-based reconstructions from three locations in the northeastern Chukchi Sea. Archaeological walrus samples were assigned to intervals of high and low sea ice, and δ 13 C and δ 15 N were compared across ice states. Mean δ 13 C and δ 15 N values were similar for archaeological walruses from intervals of high and low sea ice; however, variability among walruses was greater during low-ice intervals, possibly indicating decreased availability of preferred prey. Overall, sea ice conditions were not a primary driver of changes in walrus diet. The diet of modern walruses was not consistent with archaeological low sea ice intervals. Rather, the low average trophic position of modern walruses (primarily driven by males), with little variability among individuals, suggests that trophic changes to this Arctic ecosystem are still underway or are unprecedented in the last ~4000 yr.

Relationship between environmental pollution and economic development in late-developing regions shows an inverted V - Yu, Yadong; Duan, Changqun; Li, Shiyu; Peng, Changhui; Yang, Jian; Yan, Kun; Bi, Xiaoyi; Zou, Ping (Science of The Total Environment, 2022)

Effects of diversity, climate and litter on soil organic carbon storage in subtropical forests - Li, Yin; Liu, Xiaojuan; Xu, Wubing; Bongers, Franca J.; Bao, Weikai; Chen, Bin; Chen, Guoke; Guo, Ke; Lai, Jiangshan; Lin, Dunmei; Mi, Xiangcheng; Tian, Xingjun; et al. (Forest Ecology and Management, 2020)

Objective Calibration of Regional Climate Models: Application over Europe and North America - Bellprat, Omar; Kotlarski, Sven; Lüthi, Daniel; De Elía, Ramón; Frigon, Anne; Laprise, René; Schär, Christoph (Journal of Climate, 2016)
Abstract An important source of model uncertainty in climate models arises from unconfined model parameters in physical parameterizations. These parameters are commonly estimated on the basis of manual adjustments (expert tuning), which carries the risk of overtuning the parameters for a specific climate region or time period. This issue is particularly germane in the case of regional climate models (RCMs), which are often developed and used in one or a few geographical regions only. This study addresses the role of objective parameter calibration in this context. Using a previously developed objective calibration methodology, an RCM is calibrated over two regions (Europe and North America) and is used to investigate the transferability of the results. A total of eight different model parameters are calibrated, using a metamodel to account for parameter interactions. The study demonstrates that the calibration is effective in reducing model biases in both domains. For Europe, this concerns in particular a pronounced reduction of the summer warm bias and the associated overestimation of interannual temperature variability that have persisted through previous expert tuning efforts and are common in many global and regional climate models. The key process responsible for this improvement is an increased hydraulic conductivity. Higher hydraulic conductivity increases the water availability at the land surface and leads to increased evaporative cooling, stronger low cloud formation, and associated reduced incoming shortwave radiation. The calibrated parameter values are found to be almost identical for both domains; that is, the parameter calibration is transferable between the two regions. This is a promising result and indicates that models may be more universal than previously considered.

Palynological evidence of sea-surface conditions in the Barents Sea off northeast Svalbard during the postglacial period - Brice, Camille; De Vernal, Anne; Ivanova, Elena; Van Bellen, Simon; Van Nieuwenhove, Nicolas (Quaternary Research, 2022)
Abstract Postglacial changes in sea-surface conditions, including sea-ice cover, summer temperature, salinity, and productivity were reconstructed from the analyses of dinocyst assemblages in core S2528 collected in the northwestern Barents Sea. The results show glaciomarine-type conditions until about 11,300 ± 300 cal yr BP and limited influence of Atlantic water at the surface into the Barents Sea possibly due to the proximity of the Svalbard-Barents Sea ice sheet. This was followed by a transitional period generally characterized by cold conditions with dense sea-ice cover and low-salinity pulses likely related to episodic freshwater or meltwater discharge, which lasted until 8700 ± 700 cal yr BP. The onset of “interglacial” conditions in surface waters was marked by a major change in dinocyst assemblages, from dominant heterotrophic to dominant phototrophic taxa. Until 4100 ± 150 cal yr BP, however, sea-surface conditions remained cold, while sea-surface salinity and sea-ice cover recorded large amplitude variations. By ~4000 cal yr BP optimum sea-surface temperature of up to 4°C in summer and maximum salinity of ~34 psu suggest enhanced influence of Atlantic water, and productivity reached up to 150 gC/m 2 /yr. After 2200 ± 1300 cal yr BP, a distinct cooling trend accompanied by sea-ice spreading characterized surface waters. Hence, during the Holocene, with exception of an interval spanning about 4000 to 2000 cal yr BP, the northern Barents Sea experienced harsh environments, relatively low productivity, and unstable conditions probably unsuitable for human settlements.

Dynamics of SARS-CoV-2 spreading under the influence of environmental factors and strategies to tackle the pandemic: A systematic review - Asif, Zunaira; Chen, Zhi; Stranges, Saverio; Zhao, Xin; Sadiq, Rehan; Olea-Popelka, Francisco; Peng, Changhui; Haghighat, Fariborz; Yu, Tong (Sustainable Cities and Society, 2022)

Do Jumps Matter in the Long Term? A Tale of Two Horizons - Bégin, Jean-François; Boudreault, Mathieu (North American Actuarial Journal, 2022)

Application of machine learning methods for paleoclimatic reconstructions from leaf traits - Wei, Gang; Peng, Changhui; Zhu, Qiuan; Zhou, Xiaolu; Yang, Bin (International Journal of Climatology, 2021)
Abstract Digital leaf physiognomy (DLP) is considered as one of the most promising methods for estimating past climate. However, current models built using the DLP data set still lack precision, especially for mean annual precipitation (MAP). To improve predictive power, we developed five machine learning (ML) models for mean annual temperature (MAT) and MAP respectively, and then tested the precision of these models and some of their averaging compared with that obtained from other models. The precision of all models was assessed using a repeated stratified 10‐fold cross‐validation. For MAT, three combinations of models ( R 2 = .77) presented moderate improvements in precision over the multiple linear regression (MLR) model ( R 2 = .68). For log e (MAP), the averaging of the support vector machine (SVM) and boosting models improved the R 2 from .19 to .63 compared with that of the MLR model. For MAP, the R 2 of this model combination was 0.49, which was much better than that of the artificial neural network (ANN) model ( R 2 = .21). Even the bagging model, which had the lowest R 2 (.37) for log e (MAP), demonstrated better precision ( R 2 = .27) for MAP. Our palaeoclimate estimates for nine fossil floras were also more accurate, because they were in better agreement with independent paleoclimate evidence. Our study confirms that our ML models and their averaging can improve paleoclimatic reconstructions, providing a better understanding of the relationship between climate and leaf physiognomy.

Natural hazards in Australia: storms, wind and hail - Walsh, Kevin; White, Christopher J.; McInnes, Kathleen; Holmes, John; Schuster, Sandra; Richter, Harald; Evans, Jason P.; Di Luca, Alejandro; Warren, Robert A. (Climatic Change, 2016)

Correcting the overestimate of forest biomass carbon on the national scale - Zhou, Xiaolu; Lei, Xiangdong; Peng, Changhui; Wang, Weifeng; Zhou, Carl; Liu, Caixia; Liu, Zhenggang (Methods in Ecology and Evolution, 2016)
Summary For decades, researchers have thought it was difficult to remove the uncertainty from the estimates of forest carbon storage and its changes on national sales. This is not only because of stochasticity in the data but also the bias to overcome in the computations. Most studies of the estimation, however, ignore quantitative analyses for the latter uncertainty. This bias primarily results from the widely used volume‐biomass method via scaling up forest biomass from limited sample plots to large areas. This paper addresses (i) the mechanism of scaling‐up error occurrence, and (ii) the quantitative effects of the statistical factors on the error. The error compensators were derived, and expressed by ternary functions with three variables: expectation, variance and the power in the volume‐biomass equation. This is based on analysing the effect of power‐law function convexity on scaling‐up error by solving the difference of both sides of the weighted Jensen inequality. The simulated data and the national forest inventory of China were used for algorithm testing and application, respectively. Scaling‐up error occurrence stems primarily from an effect of the distribution heterogeneity of volume density on the total biomass amount, and secondarily from the extent of function nonlinearities. In our experiments, on average 94·2% of scaling‐up error can be reduced for the statistical populations of forest stands in a region. China's forest biomass carbon was estimated as approximately 6·0 PgC or less at the beginning of the 2010s after on average 1·1% error compensation. The results of both the simulated data experiment and national‐scale estimation suggest that the biomass is overestimated for young forests more than others. It implies a necessity to compensate scaling‐up error, especially for the areas going through extensive afforestation and reforestation in past decades. This study highlights the importance of understanding how both the function nonlinearity and the statistics of the variables quantitatively affect the scaling‐up error. Generally, the presented methods will help to translate fine‐scale ecological relationships to estimate coarser scale ecosystem properties by correcting aggregation errors.

2009 IEEE International Geoscience and Remote Sensing Symposium: IGARSS 2009 ; Cape Town, South Africa, 12 - 17 July 2009 - Institute of Electrical and Electronics Engineers; IEEE Geoscience and Remote Sensing Society (IEEE, 2009)
Keywords: Radiométrie

A microbolometer-based far infrared radiometer to study thin ice clouds in the Arctic - Libois, Quentin; Proulx, Christian; Ivanescu, Liviu; Coursol, Laurence; Pelletier, Ludovick S.; Bouzid, Yacine; Barbero, Francesco; Girard, Éric; Blanchet, Jean-Pierre (Atmospheric Measurement Techniques, 2016)
Abstract. A far infrared radiometer (FIRR) dedicated to measuring radiation emitted by clear and cloudy atmospheres was developed in the framework of the Thin Ice Clouds in Far InfraRed Experiment (TICFIRE) technology demonstration satellite project. The FIRR detector is an array of 80 × 60 uncooled microbolometers coated with gold black to enhance the absorptivity and responsivity. A filter wheel is used to select atmospheric radiation in nine spectral bands ranging from 8 to 50 µm. Calibrated radiances are obtained using two well-calibrated blackbodies. Images are acquired at a frame rate of 120 Hz, and temporally averaged to reduce electronic noise. A complete measurement sequence takes about 120 s. With a field of view of 6°, the FIRR is not intended to be an imager. Hence spatial average is computed over 193 illuminated pixels to increase the signal-to-noise ratio and consequently the detector resolution. This results in an improvement by a factor of 5 compared to individual pixel measurements. Another threefold increase in resolution is obtained using 193 non-illuminated pixels to remove correlated electronic noise, leading an overall resolution of approximately 0.015 W m−2 sr−1. Laboratory measurements performed on well-known targets suggest an absolute accuracy close to 0.02 W m−2 sr−1, which ensures atmospheric radiance is retrieved with an accuracy better than 1 %. Preliminary in situ experiments performed from the ground in winter and in summer on clear and cloudy atmospheres are compared to radiative transfer simulations. They point out the FIRR ability to detect clouds and changes in relative humidity of a few percent in various atmospheric conditions, paving the way for the development of new algorithms dedicated to ice cloud characterization and water vapor retrieval.
Keywords: Arctique; Atmosphère; Radiométrie

Airborne observations of far-infrared upwelling radiance in the Arctic - Libois, Quentin; Ivanescu, Liviu; Blanchet, Jean-Pierre; Schulz, Hannes; Bozem, Heiko; Leaitch, W. Richard; Burkart, Julia; Abbatt, Jonathan P. D.; Herber, Andreas B.; Aliabadi, Amir A.; Girard, Éric (Atmospheric Chemistry and Physics, 2016)
Abstract. The first airborne measurements of the Far-InfraRed Radiometer (FIRR) were performed in April 2015 during the panarctic NETCARE campaign. Vertical profiles of spectral upwelling radiance in the range 8–50 µm were measured in clear and cloudy conditions from the surface up to 6 km. The clear sky profiles highlight the strong dependence of radiative fluxes to the temperature inversion typical of the Arctic. Measurements acquired for total column water vapour from 1.5 to 10.5 mm also underline the sensitivity of the far-infrared greenhouse effect to specific humidity. The cloudy cases show that optically thin ice clouds increase the cooling rate of the atmosphere, making them important pieces of the Arctic energy balance. One such cloud exhibited a very complex spatial structure, characterized by large horizontal heterogeneities at the kilometre scale. This emphasizes the difficulty of obtaining representative cloud observations with airborne measurements but also points out how challenging it is to model polar clouds radiative effects. These radiance measurements were successfully compared to simulations, suggesting that state-of-the-art radiative transfer models are suited to study the cold and dry Arctic atmosphere. Although FIRR in situ performances compare well to its laboratory performances, complementary simulations show that upgrading the FIRR radiometric resolution would greatly increase its sensitivity to atmospheric and cloud properties. Improved instrument temperature stability in flight and expected technological progress should help meet this objective. The campaign overall highlights the potential for airborne far-infrared radiometry and constitutes a relevant reference for future similar studies dedicated to the Arctic and for the development of spaceborne instruments.
Keywords: Arctique; Radiométrie

Added value of far‐infrared radiometry for remote sensing of ice clouds - Libois, Quentin; Blanchet, Jean‐Pierre (Journal of Geophysical Research: Atmospheres, 2017)
Abstract Several cloud retrieval algorithms based on satellite observations in the infrared have been developed in the last decades. However, these observations only cover the midinfrared (MIR, λ < 15 μm) part of the spectrum, and none are available in the far‐infrared (FIR, λ ≥ 15 μm). Using the optimal estimation method, we show that adding a few FIR channels to existing spaceborne radiometers would significantly improve their ability to retrieve ice cloud radiative properties. For clouds encountered in the polar regions and the upper troposphere, where the atmosphere is sufficiently transparent in the FIR, using FIR channels would reduce by more than 50% the uncertainties on retrieved values of optical thickness, effective particle diameter, and cloud top altitude. Notably, this would extend the range of applicability of current retrieval methods to the polar regions and to clouds with large optical thickness, where MIR algorithms perform poorly. The high performance of solar reflection‐based algorithms would thus be reached in nighttime conditions. Since the sensitivity of ice cloud thermal emission to effective particle diameter is approximately 5 times larger in the FIR than in the MIR, using FIR observations is a promising venue for studying ice cloud microphysics and precipitation processes. This is highly relevant for cirrus clouds and convective towers. This is also essential to study precipitation in the driest regions of the atmosphere, where strong feedbacks are at play between clouds and water vapor. The deployment in the near future of a FIR spaceborne radiometer is technologically feasible and should be strongly supported. , Plain Language Summary The size of ice cloud particles can be estimated from space by measuring the infrared emission of ice clouds. However, this method no longer works when clouds are too thick or when particles are too large, although such clouds are encountered in many regions of the Earth and are critical for the Earth's climate. Using new sensors that measure cloud emission at longer wavelengths, in the so‐called far‐infrared region, would extend the potential of satellite observations to thick clouds, to clouds made of larger particles, and to clouds found in the polar regions which are very poorly known. These new sensors have become available in the last years, but none is deployed in space so far. We show that a satellite equipped with a few channels in the far‐infrared would greatly increase our capacity to observe ice clouds. This is promising for our understanding of cloud microphysics and precipitation in general, and for studying the water cycle in the polar regions in particular. For these reasons, it is highly recommended to deploy a far‐infrared radiometer in space. , Key Points Ice cloud remote sensing would be greatly improved by adding far‐infrared channels to existing midinfrared spaceborne radiometers Far‐infrared radiometry is well suited to study ice clouds in the polar regions and upper troposphere Using far‐infrared radiometry extends current infrared capabilities to large optical thickness and large cloud particles
Keywords: Atmosphère; Radiométrie

Urban surface effects on current and future climate - Garuma, Gemechu Fanta; Blanchet, Jean-Pierre; Girard, Éric; Leduc, Martin (Urban Climate, 2018)

Simulating Arctic Ice Clouds during Spring Using an Advanced Ice Cloud Microphysics in the WRF Model - Keita, Setigui; Girard, Eric; Raut, Jean-Christophe; Pelon, Jacques; Blanchet, Jean-Pierre; Lemoine, Olivier; Onishi, Tatsuo (Atmosphere, 2019)
Two Types of Ice Clouds (TICs) have been characterized in the Arctic during the polar night and early spring. TIC-1 are composed by non-precipitating small ice crystals of less than 30 µm in diameter. The second type, TIC-2, are characterized by a low concentration of large precipitating ice crystals (>30 µm). Here, we evaluate the Weather Research and Forecasting (WRF) model performance both in space and time after implementing a parameterization based on a stochastic approach dedicated to the simulation of ice clouds in the Arctic. Well documented reference cases provided us in situ data from the spring of 2008 Indirect and Semi-Direct Aerosol Campaign (ISDAC) campaign over Alaska. Simulations of the microphysical properties of the TIC-2 clouds on 15 and 25 April 2008 (polluted or acidic cases) and TIC-1 clouds on non-polluted cases are compared to DARDAR (raDAR/liDAR) satellite products. Our results show that the stochastic approach based on the classical nucleation theory, with the appropriate contact angle, is better than the original scheme in WRF model to represent TIC-1 and TIC-2 properties (ice crystal concentration and size) in response to the IN acidification.
Keywords: Arctique; Atmosphère

Optimal Configuration of a Far‐Infrared Radiometer to Study the Arctic Winter Atmosphere - Coursol, Laurence; Libois, Quentin; Gauthier, Pierre; Blanchet, Jean‐Pierre (Journal of Geophysical Research: Atmospheres, 2020)
Abstract Several far‐infrared (FIR) satellite missions are planned for the next decade, with a special interest for the Arctic region. A theoretical study is performed to help with the design of an FIR radiometer, whose configuration in terms of channels number and frequencies is optimized based on information content analysis. The problem is cast in a context of vertical column experiments (1D) to determine the optimal configuration of a FIR radiometer to study the Arctic polar night. If only observations of the FIR radiometer were assimilated, the results show that for humidity, 90% of the total information content is obtained with four bands, whereas for temperature, 10 bands are needed. When the FIR measurements are assimilated on top of those from the advanced infrared sounder (AIRS), the former bring in additional information between the surface and 850 hPa and from 550 to 250 hPa for humidity. Moreover, between 400 and 200 hPa, the FIR radiometer is better than AIRS at reducing the analysis error variance for humidity. This indicates the potential of FIR observations for improving water vapor analysis in the Arctic. , Key Points FIR channels add information for UTLS water vapor compared to standard MIR channels IC is used to optimize the channels frequencies and widths of a FIR radiometer A high DFS is reached with only a few channels of an optimized FIR radiometer
Keywords: Arctique; Atmosphère; Radiométrie

Enhanced automated meteorological observations at the Canadian Arctic Weather Science (CAWS) supersites - Mariani, Zen; Huang, Laura; Crawford, Robert; Blanchet, Jean-Pierre; Hicks-Jalali, Shannon; Mekis, Eva; Pelletier, Ludovick; Rodriguez, Peter; Strawbridge, Kevin (Earth System Science Data, 2022)
Abstract. The changing Arctic climate is creating increased economic, transportation, and recreational activities requiring reliable and relevant weather information. However, the Canadian Arctic is sparsely observed, and processes governing weather systems in the Arctic are not well understood. There is a recognized lack of meteorological data to characterize the Arctic atmosphere for operational forecasting and to support process studies, satellite calibration/validation, search and rescue operations (which are increasing in the region), high-impact weather (HIW) detection and prediction, and numerical weather prediction (NWP) model verification and evaluation. To address this need, Environment and Climate Change Canada commissioned two supersites, one in Iqaluit (63.74∘ N, 68.51∘ W) in September 2015 and the other in Whitehorse (60.71∘ N, 135.07∘ W) in November 2017 as part of the Canadian Arctic Weather Science (CAWS) project. The primary goals of CAWS are to provide enhanced meteorological observations in the Canadian Arctic for HIW nowcasting (short-range forecast) and NWP model verification, evaluation, and process studies and to provide recommendations on the optimal cost-effective observing system for the Canadian Arctic. Both sites are in provincial/territorial capitals and are economic hubs for the region; they also act as transportation gateways to the north and are in the path of several common Arctic storm tracks. The supersites are located at or next to major airports and existing Meteorological Service of Canada ground-based weather stations that provide standard meteorological surface observations and upper-air radiosonde observations; they are also uniquely situated in close proximity to frequent overpasses by polar-orbiting satellites. The suite of in situ and remote sensing instruments at each site is completely automated (no on-site operator) and operates continuously in all weather conditions, providing near-real-time data to operational weather forecasters, the public, and researchers via obrs.ca. The two sites have similar instruments, including mobile Doppler weather radars, multiple vertically profiling and/or scanning lidars (Doppler, ceilometer, water vapour), optical disdrometers, precipitation gauges in different shielded configurations, present weather sensors, fog monitoring devices, radiation flux sensors, and other meteorological instruments. Details on the two supersites, the suites of instruments deployed, the data collection methods, and example case studies of HIW events are discussed. CAWS data are publicly accessible via the Canadian Government Open Data Portal (https://doi.org/10.18164/ff771396-b22c-4bc3-844d-38fc697049e9, Mariani et al., 2022a, and https://doi.org/10.18164/d92ed3cf-4ba0-4473-beec-357ec45b0e78, Mariani et al., 2022b); this dataset is being used to improve our understanding of synoptic and fine-scale meteorological processes in the Arctic and sub-Arctic, including HIW detection and prediction and NWP verification, assimilation, and processes.
Keywords: Arctique

Simulation of Arctic Thin Ice Clouds with Canadian Regional Climate Model Version 6: Verification against CloudSat-CALIPSO - Sankaré, Housseyni; Blanchet, Jean-Pierre; Laprise, René; O’Neill, Norman T. (Atmosphere, 2022)
Polar clouds are, as a consequence of the paucity of in situ observations, poorly understood compared to their lower latitude analogs, yet highly climate-sensitive through thermal radiation emission. The prevalence of Thin Ice Clouds (TIC) dominates in cold Polar Regions and the Upper Troposphere Lower Stratosphere (UTLS) altitudes. They can be grouped into 2 broad categories. The first thin ice cloud type (TIC1) is made up of high concentrations of small, non-precipitating ice crystals. The second type (TIC2) is composed of relatively small concentrations of larger, precipitating ice crystals. In this study, we investigate the ability of a developmental version of the Canadian Regional Climate Model (CRCM6) in simulating cold polar-night clouds over the Arctic Ocean, a remote region that is critical to atmospheric circulation reaching out to the mid-latitudes. The results show that, relative to CloudSat-CALIPSO vertical profile products, CRCM6 simulates high-latitude and low spatial frequency variations of Ice Water Content (IWC), effective radius (re) and cooling rates reasonably well with only small to moderate wet and dry biases. The model can also simulate cloud type, location, and temporal occurrence effectively. As well, it successfully simulated higher altitude TIC1 clouds whose small size evaded CloudSat detection while being visible to CALIPSO.
Keywords: Arctique; Atmosphère

CNT Parameterization Based on the Observed INP Concentration during Arctic Summer Campaigns in a Marine Environment - Cirisan, Ana; Girard, Eric; Blanchet, Jean-Pierre; Keita, Setigui Aboubacar; Gong, Wanmin; Irish, Vickie; Bertram, Allan K. (Atmosphere, 2020)
Aerosol–cloud interactions present a large source of uncertainties in atmospheric and climate models. One of the main challenges to simulate ice clouds is to reproduce the right ice nucleating particle concentration. In this study, we derive a parameterization for immersion freezing according to the classical nucleation theory. Our objective was to constrain this parameterization with observations taken over the Canadian Arctic during the Amundsen summer 2014 and 2016 campaigns. We found a linear dependence of contact angle and temperature. Using this approach, we were able to reproduce the scatter in ice nucleated particle concentrations within a factor 5 of observed values with a small negative bias. This parameterization would be easy to implement in climate and atmospheric models, but its representativeness has to first be validated against other datasets.
Keywords: Arctique